2q36.3 is associated with prognosis for oestrogen receptor-negative breast cancer patients treated with chemotherapy - Li, Jingmei; Lindstroem, Linda S.; Foo, Jia N.; Rafiq, Sajjad; Schmidt, Marjanka K.; Pharoah, Paul D. P.; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Van'T Veer, Laura J.; Cornelissen, Sten; et al. (Nature Communications, 2014)
Large population-based registry studies have shown that breast cancer prognosis is inherited. Here we analyse single-nucleotide polymorphisms (SNPs) of genes implicated in human immunology and inflammation as candidates for prognostic markers of breast cancer survival involving 1,804 oestrogen receptor (ER)-negative patients treated with chemotherapy (279 events) from 14 European studies in a prior large-scale genotyping experiment, which is part of the Collaborative Oncological Gene-environment Study (COGS) initiative. We carry out replication using Asian COGS samples (n=522, 53 events) and the Prospective Study of Outcomes in Sporadic versus Hereditary breast cancer (POSH) study (n=315, 108 events). Rs4458204_A near CCL20 (2q36.3) is found to be associated with breast cancer-specific death at a genome-wide significant level (n=2,641, 440 events, combined allelic hazard ratio (HR)=1.81 (1.49-2.19); P for trend=1.90 × 10(-9)). Such survival-associated variants can represent ideal targets for tailored therapeutics, and may also enhance our current prognostic prediction capabilities.
EVALuna2:9232

7q31.2q31.31 deletion downstream of FOXP2 segregating in a family with speech and language disorder - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Chromosomal 7q31 deletions have been described in individuals with variable neurodevelopmental phenotypes including speech and language impairment. These copy number variants usually encompass FOXP2, haploinsufficiency of which represents a widely acknowledged cause for specific speech and language disorders. By chromosomal microarray analysis we identified a 4.7 Mb microdeletion at 7q31.2q31.31 downstream of FOXP2 in three family members presenting with variable speech, language and neurodevelopmental phenotypes. The index individual showed delayed speech development with impaired speech production, reduced language comprehension, and additionally learning difficulties, microcephaly, and attention deficit. His younger sister had delayed speech development with impaired speech production and partially reduced language comprehension. Their mother had attended a school for children with speech and language deficiencies and presented with impaired articulation. The deletion had occurred de novo in the mother, includes 15 protein-coding genes and is located in close proximity to the 3′ end of FOXP2. Though a novel locus at 7q31.2q31.31 associated with mild neurodevelopmental and more prominent speech and language impairment is possible, the close phenotypic overlap with FOXP2-associated speech and language disorder rather suggests a positional effect on FOXP2 expression and function.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7q; deletion; FOXP2; language; speech

ABCA transporter gene expression and poor outcome in epithelial ovarian cancer - Hedditch, Ellen L.; Gao, Bo; Russell, Amanda J.; Lu, Yi; Emmanuel, Catherine; Beesley, Jonathan; Johnatty, Sharon E.; Chen, Xiaoqing; Harnett, Paul; George, Joshy; Williams, Rebekka T.; Flemming, Claudia; et al. (Journal of the National Cancer Institute, 2014)
ATP-binding cassette (ABC) transporters play various roles in cancer biology and drug resistance, but their association with outcomes in serous epithelial ovarian cancer (EOC) is unknown.The relationship between clinical outcomes and ABC transporter gene expression in two independent cohorts of high-grade serous EOC tumors was assessed with real-time quantitative polymerase chain reaction, analysis of expression microarray data, and immunohistochemistry. Associations between clinical outcomes and ABCA transporter gene single nucleotide polymorphisms were tested in a genome-wide association study. Impact of short interfering RNA-mediated gene suppression was determined by colony forming and migration assays. Association with survival was assessed with Kaplan-Meier analysis and log-rank tests. All statistical tests were two-sided.Associations with outcome were observed with ABC transporters of the "A" subfamily, but not with multidrug transporters. High-level expression of ABCA1, ABCA6, ABCA8, and ABCA9 in primary tumors was statistically significantly associated with reduced survival in serous ovarian cancer patients. Low levels of ABCA5 and the C-allele of rs536009 were associated with shorter overall survival (hazard ratio for death = 1.50; 95% confidence interval [CI] =1.26 to 1.79; P = 6.5e-6). The combined expression pattern of ABCA1, ABCA5, and either ABCA8 or ABCA9 was associated with particularly poor outcome (mean overall survival in group with adverse ABCA1, ABCA5 and ABCA9 gene expression = 33.2 months, 95% CI = 26.4 to 40.1; vs 55.3 months in the group with favorable ABCA gene expression, 95% CI = 49.8 to 60.8; P = .001), independently of tumor stage or surgical debulking status. Suppression of cholesterol transporter ABCA1 inhibited ovarian cancer cell growth and migration in vitro, and statin treatment reduced ovarian cancer cell migration.Expression of ABCA transporters was associated with poor outcome in serous ovarian cancer, implicating lipid trafficking as a potentially important process in EOC.
EVALuna2:9230

Aberrant NOVA1 function disrupts alternative splicing in early stages of amyotrophic lateral sclerosis - Krach, Florian; Wheeler, Emily C.; Regensburger, Martin; Börstler, Tom; Wend, Holger; Vu, Anthony Q.; Wang, Ruth; Reischl, Stephanie; Boldt, Karsten; Batra, Ranjan; Aigner, Stefan; Ravits, John; et al. (Acta Neuropathologica, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal disease characterized by aberrant alternative splicing (AS). Nuclear loss and cytoplasmic accumulation of the splicing factor TDP-43 in motor neurons (MN) are hallmarks of ALS at late stages of the disease. However, it is unknown if altered AS is present before TDP-43 pathology occurs. Here, we investigate altered AS and its origins in early stages of ALS using human induced pluripotent stem cell-derived motor neurons (MNs) from sporadic and familial ALS patients. We find high levels of the RNA-binding proteins NOVA1, NOVA2, and RBFOX2 in the insoluble protein fractions and observe that AS events in ALS-associated MNs are enriched for binding sites of these proteins. Our study points to an early disrupted function of NOVA1 that drives AS changes in a complex fashion, including events caused by a consistent loss of NOVA1 function. NOVA1 exhibits increased cytoplasmic protein levels in early stage MNs without TDP-43 pathology in ALS postmortem tissue. As nuclear TDP-43 protein level depletes, NOVA1 is reduced. Potential indications for a reduction of NOVA1 also came from mice over-expressing TDP-43 lacking its nuclear localization signal and iPSC-MN stressed with puromycin. This study highlights that additional RBP-RNA perturbations in ALS occur in parallel to TDP-43.
CRIS-Team WoS Importer:2022-07-08

Aberrant phase separation and nucleolar dysfunction in rare genetic diseases - Mensah, Martin A.; Niskanen, Henri; Magalhaes, Alexandre P.; Basu, Shaon; Kircher, Martin; Sczakiel, Henrike L.; Reiter, Alisa M.V.; Elsner, Jonas; Meinecke, Peter; Biskup, Saskia; Chung, Brian H.Y.; Dombrowsky, Gregor; et al. (Nature, 2023)
Thousands of genetic variants in protein-coding genes have been linked to disease. However, the functional impact of most variants is unknown as they occur within intrinsically disordered protein regions that have poorly defined functions1–3. Intrinsically disordered regions can mediate phase separation and the formation of biomolecular condensates, such as the nucleolus4,5. This suggests that mutations in disordered proteins may alter condensate properties and function6–8. Here we show that a subset of disease-associated variants in disordered regions alter phase separation, cause mispartitioning into the nucleolus and disrupt nucleolar function. We discover de novo frameshift variants in HMGB1 that cause brachyphalangy, polydactyly and tibial aplasia syndrome, a rare complex malformation syndrome. The frameshifts replace the intrinsically disordered acidic tail of HMGB1 with an arginine-rich basic tail. The mutant tail alters HMGB1 phase separation, enhances its partitioning into the nucleolus and causes nucleolar dysfunction. We built a catalogue of more than 200,000 variants in disordered carboxy-terminal tails and identified more than 600 frameshifts that create arginine-rich basic tails in transcription factors and other proteins. For 12 out of the 13 disease-associated variants tested, the mutation enhanced partitioning into the nucleolus, and several variants altered rRNA biogenesis. These data identify the cause of a rare complex syndrome and suggest that a large number of genetic variants may dysregulate nucleoli and other biomolecular condensates in humans.
CRIS-Team Scopus Importer:2023-02-17

A biallelic truncating AEBP1 variant causes connective tissue disorder in two siblings - Hebebrand, Moritz; Vasileiou, Georgia; Krumbiegel, Mandy; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Thiel, Christian; Reis, André; Popp, Bernt (American Journal of Medical Genetics Part A, 2018)
Biallelic variants in the AEBP1 gene cause a novel autosomal-recessive connective tissue disorder (CTD) reminiscent of Ehlers-Danlos Syndrome (EDS). The four previously reported individuals show considerable clinical variability. Unbiased high-throughput sequencing enables the rapid identification of additional cases for such rare entities. We identified the homozygous nonsense variant c.917dup, p.Tyr306* in AEBP1 using clinical exome sequencing in a female individual with previously unsolved CTD. Segregation testing confirmed homozygosity in the clinically affected brother and heterozygous carrier status in the healthy mother. Chromosomal microarray showed that the variant lies in a run of homozygosity, suggesting a common origin of this genomic segment. RT-PCR analysis in the mother revealed a monoallelic expression of the normal transcript supporting a nonsense-mediated mRNA decay and functional nullizygosity as disease mechanism. We describe two individuals from a fourth family with AEBP1-associated CTD. Our results further verify that autosomal-recessive inherited LOF variants in the AEBP1 gene cause clinical features of different EDS subtypes, but also of the marfanoid spectrum. As identification of further individuals is necessary to inform the clinical characterization, we stress the added value of exome sequencing for such rare diseases.
EVALuna2:35120

A case of autosomal recessive spinocerebellar ataxia type 18 with a novel mutation in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, C.; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

A case of severe autosomal recessive spinocerebellar ataxia type 18 with a novel nonsense variant in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Trollmann, Regina; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2020)
Autosomal-recessive spinocerebellar ataxia type 18 (SCAR18) is a rare neurologic disorder. It is caused by bi-allelic aberrations in the GRID2 gene, encoding an ionotropic glutamate receptor. In total, 20 affected individuals with mainly homozygous/compound heterozygous intragenic deletions/duplications, two different missense variants and one nonsense variant in GRID2 have been reported, so far. SCAR18 is characterized by delayed psychomotor development, intellectual disability, severely impaired gait due to cerebellar ataxia, ocular movement abnormalities, and cerebellar atrophy in brain imaging. By trio exome sequencing, we now identified a novel homozygous nonsense variant (c.568C > T; p.Gln190*) in GRID2 in a four year old female from a consanguineous family who presented with a particularly severe manifestation of SCAR18. The girl was born after an uneventful pregnancy and showed early-onset, profoundly delayed psychomotor development with no achieved psychomotor milestones at age 4 years. Additionally, she presented with severe muscular hypotonia, progressive truncal and appendicular ataxia, binocular vertical nystagmus, central hearing loss and incomplete loss of sight. She was dystrophic, interacted only very little and had behavioral anomalies such as eating hair and bruxism. Brain imaging showed cerebellar hypoplasia, extended cerebrospinal fluid spaces and beginning reduction of cerebral volume. Our findings further delineate the mutational and clinical spectrum of GRID2-associated spinocerebellar ataxia type 18 and indicate that homozygous nonsense variants are possibly associated with the severe end of the SCAR18 phenotypic spectrum.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Ataxia; Autosomal-recessive; Cerebellar hypoplasia; GRID2; Psychomotor development; SCAR18

Accumulation of oligomer-prone ?-synuclein exacerbates synaptic and neuronal degeneration in vivo - Rockenstein, Edward; Nuber, Silke; Overk, Cassia R.; Ubhi, Kiren; Mante, Michael; Patrick, Christina; Adame, Anthony; Trejo-Morales, Margarita; Gerez, Juan; Picotti, Paola; Jensen, Poul H.; Campioni, Silvia; et al. (Brain, 2014)
In Parkinson's disease and dementia with Lewy bodies, ?-synuclein aggregates to form oligomers and fibrils; however, the precise nature of the toxic ?-synuclein species remains unclear. A number of synthetic ?-synuclein mutations were recently created (E57K and E35K) that produce species of ?-synuclein that preferentially form oligomers and increase ?-synuclein-mediated toxicity. We have shown that acute lentiviral expression of ?-synuclein E57K leads to the degeneration of dopaminergic neurons; however, the effects of chronic expression of oligomer-prone ?-synuclein in synapses throughout the brain have not been investigated. Such a study could provide insight into the possible mechanism(s) through which accumulation of ?-synuclein oligomers in the synapse leads to neurodegeneration. For this purpose, we compared the patterns of neurodegeneration and synaptic damage between a newly generated mThy-1 ?-synuclein E57K transgenic mouse model that is prone to forming oligomers and the mThy-1 ?-synuclein wild-type mouse model (Line 61), which accumulates various forms of ?-synuclein. Three lines of ?-synuclein E57K (Lines 9, 16 and 54) were generated and compared with the wild-type. The ?-synuclein E57K Lines 9 and 16 were higher expressings of ?-synuclein, similar to ?-synuclein wild-type Line 61, and Line 54 was a low expressing of ?-synuclein compared to Line 61. By immunoblot analysis, the higher-expressing ?-synuclein E57K transgenic mice showed abundant oligomeric, but not fibrillar, ?-synuclein whereas lower-expressing mice accumulated monomeric ?-synuclein. Monomers, oligomers, and fibrils were present in ?-synuclein wild-type Line 61. Immunohistochemical and ultrastructural analyses demonstrated that ?-synuclein accumulated in the synapses but not in the neuronal cells bodies, which was different from the ?-synuclein wild-type Line 61, which accumulates ?-synuclein in the soma. Compared to non-transgenic and lower-expressing mice, the higher-expressing ?-synuclein E57K mice displayed synaptic and dendritic loss, reduced levels of synapsin 1 and synaptic vesicles, and behavioural deficits. Similar alterations, but to a lesser extent, were seen in the ?-synuclein wild-type mice. Moreover, although the oligomer-prone ?-synuclein mice displayed neurodegeneration in the frontal cortex and hippocampus, the ?-synuclein wild-type only displayed neuronal loss in the hippocampus. These results support the hypothesis that accumulating oligomeric ?-synuclein may mediate early synaptic pathology in Parkinson's disease and dementia with Lewy bodies by disrupting synaptic vesicles. This oligomer-prone model might be useful for evaluating therapies directed at oligomer reduction.
EVALuna2:25331

A common variant mapping to CACNA1A is associated with susceptibility to exfoliation syndrome - Aung, Tin; Ozaki, Mineo; Mizoguchi, Takanori; Allingham, R. Rand; Li, Zheng; Haripriya, Aravind; Nakano, Satoko; Uebe, Steffen; Harder, Jeffrey M.; Chan, Anita S. Y.; Lee, Mei Chin; Burdon, Kathryn P.; et al. (Nature Genetics, 2015)
Exfoliation syndrome (XFS) is the most common recognizable cause of open-angle glaucoma worldwide. To better understand the etiology of XFS, we conducted a genome-wide association study (GWAS) of 1,484 cases and 1,188 controls from Japan and followed up the most significant findings in a further 6,901 cases and 20,727 controls from 17 countries across 6 continents. We discovered a genome-wide significant association between a new locus (CACNA1A rs4926244) and increased susceptibility to XFS (odds ratio (OR) = 1.16, P = 3.36 × 10(-11)). Although we also confirmed overwhelming association at the LOXL1 locus, the key SNP marker (LOXL1 rs4886776) demonstrated allelic reversal depending on the ancestry group (Japanese: OR(A allele) = 9.87, P = 2.13 × 10(-217); non-Japanese: OR(A allele) = 0.49, P = 2.35 × 10(-31)). Our findings represent the first genetic locus outside of LOXL1 surpassing genome-wide significance for XFS and provide insight into the biology and pathogenesis of the disease.
EVALuna2:9286

A comparative observational study on intrasphincteric injections with Botulinum toxin vs. enteral neuromodulation in chronic refractory constipation - Walther, Mona; Müller, Hanna; Weiß, Christel; Carbon, Roman; Diez, Sonja; Besendörfer, Manuel (BMC Pediatrics, 2023)
Purpose: Botulinum toxin injections in the anal sphincter apparatus (Botox) and enteral neuromodulation (ENM) are options for treatment of refractory chronic constipation. We present a retrospective comparative observational study. Patients and methods: From 2014 to 2022, pediatric patients with chronic constipation were either treated with Botox or ENM with continuation of conservative treatment. Comparison was conducted regarding the primary outcome variables defecation frequency, stool consistency, and abdominal pain. Secondary outcomes were fecal incontinence, enuresis, change of medication and safety of treatment. Results: 19 Botox patients (10 boys, 9 girls, 12 patients with Hirschsprung disease (HD), 7 patients with functional constipation (FC)) were compared to 24 ENM patients (18 boys, 6 girls, 12 HD patients, 7 FC patients). Groups differed significantly in age (5.0 years (Botulinum toxin) and 6.5 years (ENM), mean values, p-value 0.008). Improvement of constipation was seen in 68% (n = 13/19) of Botox and 88% (n = 21/24) of ENM patients (p = 0.153). Influence of etiology on therapeutic effects was not observed. Complications were minor. Conclusions: Botox and ENM can be considered as valuable and effective treatment options in refractory chronic constipation. Prospective, large-population studies should be designed to enable improved evidence.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Botulinum toxin; Chronic refractory constipation; Enteral neuromodulation; Fecal incontinence; Hirschsprung disease

A complex microcephaly syndrome in a Pakistani family associated with a novel missense mutation in RBBP8 and a heterozygous deletion in NRXN1 - Agha, Zehra; Iqbal, Zafar; Azam, Maleeha; Siddique, Maimoona; Willemsen, Marjolein H.; Kleefstra, Tjitske; Zweier, Christiane; De Leeuw, Nicole; Qamar, Raheel; Van Bokhoven, Hans (Gene, 2014)
We report on a consanguineous Pakistani family with a severe congenital microcephaly syndrome resembling the Seckel syndrome and Jawad syndrome. The affected individuals in this family were born to consanguineous parents of whom the mother presented with mild intellectual disability (ID), epilepsy and diabetes mellitus. The two living affected brothers presented with microcephaly, white matter disease of the brain, hyponychia, dysmorphic facial features with synophrys, epilepsy, diabetes mellitus and ID. Genotyping with a 250K SNP array in both affected brothers revealed an 18 MB homozygous region on chromosome 18 p11.21-q12.1 encompassing the SCKL2 locus of the Seckel and Jawad syndromes. Sequencing of the RBBP8 gene, underlying the Seckel and Jawad syndromes, identified the novel mutation c.919A>G, p.Arg307Gly, segregating in a recessive manner in the family. In addition, in the two affected brothers and their mother we have also found a heterozygous 607kb deletion, encompassing exons 13-19 of NRXN1. Bidirectional sequencing of the coding exons of NRXN1 did not reveal any other mutation on the other allele. It thus appears that the phenotype of the mildly affected mother can be explained by the NRXN1 deletion, whereas the more severe and complex microcephalic phenotype of the two affected brothers is due to the simultaneous deletion in NRXN1 and the homozygous missense mutation affecting RBBP8.
EVALuna2:9226

A comprehensive evaluation of interaction between genetic variants and use of menopausal hormone therapy on mammographic density - Rudolph, Anja; Fasching, Peter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Thompson, Deborah; Czene, Kamila; Brand, Judith S.; Li, Jingmei; Scott, Christopher; Pankratz, V. Shane; et al. (Breast Cancer Research, 2015)
Mammographic density is an established breast cancer risk factor with a strong genetic component and can be increased in women using menopausal hormone therapy (MHT). Here, we aimed to identify genetic variants that may modify the association between MHT use and mammographic density.The study comprised 6,298 postmenopausal women from the Mayo Mammography Health Study and nine studies included in the Breast Cancer Association Consortium. We selected for evaluation 1327 single nucleotide polymorphisms (SNPs) showing the lowest P-values for interaction (P int) in a meta-analysis of genome-wide gene-environment interaction studies with MHT use on risk of breast cancer, 2541 SNPs in candidate genes (AKR1C4, CYP1A1-CYP1A2, CYP1B1, ESR2, PPARG, PRL, SULT1A1-SULT1A2 and TNF) and ten SNPs (AREG-rs10034692, PRDM6-rs186749, ESR1-rs12665607, ZNF365-rs10995190, 8p11.23-rs7816345, LSP1-rs3817198, IGF1-rs703556, 12q24-rs1265507, TMEM184B-rs7289126, and SGSM3-rs17001868) associated with mammographic density in genome-wide studies. We used multiple linear regression models adjusted for potential confounders to evaluate interactions between SNPs and current use of MHT on mammographic density.No significant interactions were identified after adjustment for multiple testing. The strongest SNP-MHT interaction (unadjusted P int <0.0004) was observed with rs9358531 6.5kb 5' of PRL. Furthermore, three SNPs in PLCG2 that had previously been shown to modify the association of MHT use with breast cancer risk were found to modify also the association of MHT use with mammographic density (unadjusted P int <0.002), but solely among cases (unadjusted P int SNP×MHT×case-status <0.02).The study identified potential interactions on mammographic density between current use of MHT and SNPs near PRL and in PLCG2, which require confirmation. Given the moderate size of the interactions observed, larger studies are needed to identify genetic modifiers of the association of MHT use with mammographic density.
EVALuna2:9284

A Costa Rican family affected with Charcot-Marie-Tooth disease due to the myelin protein zero (MPZ) p.Thr124Met mutation shares the Belgian haplotype - Leal, Alejandro; Berghoff, Corinna; Berghoff, Martin; Rojas-Araya, Melissa; Ortiz, Carolina; Heuss, Dieter; Del Valle, Gerardo; Rautenstrauß, Bernd (Revista De Biologia Tropical, 2014)
The p.Thr124Met mutation in the myelin protein zero (MPZ) causes the Charcot-Marie-Tooth disease type 2J, a peripheral neuropathy with additional symptoms as pupillary alterations and deafness. It was observed in several families around the world originating e. g. from Germany, Belgium, Japan, Italy and North America. Here we report Central American patients originating from a family in Costa Rica carrying this mutation. Clinical, electrophysiological and molecular analysis of patients and controls were performed, including gene and linked markers' sequencing. Carriers share almost the entire haplotype with two non related Belgian CMT patients. As a result of the haplotype analysis, based on ten markers (seven SNPs, two microsatellites and an intronic polyA stretch), the founder effect hypothesis for this allele migration is suggestive.
EVALuna2:22390

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease. - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea T.; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon ?2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing.Colitis was induced in C57BL/6JCrl mice (controls), mice with IEC-specific disruption of Stat1 (Stat1IEC-KO), mice with disruption of the interferon ? receptor 1 gene (Il28ra(-/-)), and mice with disruption of the interferon regulatory factor 3 gene (Irf3(-/-)), with or without disruption of Irf7 (Irf7(-/-)). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging.Lamina propria cells in colon tissues of patients with IBD, and mice with colitis, had increased expression of IL28 compared with controls; levels of IL28R were increased in the colonic epithelium of patients with IBD and mice with colitis. Administration of IL28 induced phosphorylation of STAT1 in primary human and mouse IECs, increasing with dose. Il28ra(-/-), Irf3(-/-), Irf3(-/-)Irf7(-/-), as well as Stat1IEC-KO mice, developed more severe colitis after administration of dextran sulfate sodium than control mice, with reduced epithelial restitution. Il28ra(-/-) and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing.IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD.
EVALuna2:9356

Acute care and secondary prevention of stroke with newly detected versus known atrial fibrillation - Wang, Ruihao; Macha, Kosmas; Haupenthal, David; Gaßmann, Luise; Siedler, Gabriela; Stoll, Svenja; Fröhlich, Kilian; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd (European Journal of Neurology, 2022)
Background and purpose: Atrial fibrillation (AF) in stroke patients can be classified as either “known AF” (KAF), defined as AF confirmed before stroke onset, or “AF detected after stroke” (AFDAS), defined as AF diagnosed after stroke onset. While KAF is considered primarily cardiogenic, AFDAS includes patients with stroke-triggered neurogenic arrhythmias. This study aimed to investigate the clinical course of stroke, functional outcomes and the value of oral anticoagulation (OAC) for secondary prevention according to AF subtype. Methods: Acute ischemic stroke patients were consecutively enrolled and AF was classified as AFDAS or KAF. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and 3-month functional outcomes were measured on the modified Rankin scale. Inverse probability weighting was applied to adjust for baseline confounders in patients with AFDAS and KAF. Multivariate logistic regression models were calculated to investigate the value of OAC for secondary prevention. Results: A total of 822 stroke patients with AF were included, of whom 234 patients (28.5%) had AFDAS. AFDAS patients had a lower prevalence of coronary artery disease, heart failure, and sustained AF, but higher rates of large vessel occlusion compared to KAF patients. NIHSS scores were lower in patients on pre-stroke anticoagulation. OAC for secondary prevention was associated with favorable 3-month functional outcome (odds ratio 7.60, 95% confidence interval 3.42–16.88) independently of AF subtype. The rate of stroke recurrence did not differ significantly. Conclusions: Clinical characteristics suggest that AFDAS might comprise a distinct pathophysiological and clinical entity among stroke patients with AF. The benefit of anticoagulation for secondary prevention was not affected by AF subtype.
CRIS-Team Scopus Importer:2022-04-22
Keywords: acute ischemic stroke; atrial fibrillation detected after stroke; known atrial fibrillation; modified Rankin scale; oral anticoagulation; stroke recurrence

Adaptor protein complex 4 deficiency: a paradigm of childhood-onset hereditary spastic paraplegia caused by defective protein trafficking - Behne, Robert; Teinert, Julian; Wimmer, Miriam; D'Amore, Angelica; Davies, Alexandra K.; Scarrott, Joseph M.; Eberhardt, Kathrin; Brechmann, Barbara; Chen, Ivy Pin Fang; Buttermore, Elizabeth D.; Barrett, Lee; Dwyer, Sean; et al. (Human Molecular Genetics, 2020)
Deficiency of the adaptor protein complex 4 (AP-4) leads to childhood-onset hereditary spastic paraplegia (AP-4-HSP): SPG47 (AP4B1), SPG50 (AP4M1), SPG51 (AP4E1) and SPG52 (AP4S1). This study aims to evaluate the impact of loss-of-function variants in AP-4 subunits on intracellular protein trafficking using patient-derived cells. We investigated 15 patient-derived fibroblast lines and generated six lines of induced pluripotent stem cell (iPSC)-derived neurons covering a wide range of AP-4 variants. All patient-derived fibroblasts showed reduced levels of the AP4E1 subunit, a surrogate for levels of the AP-4 complex. The autophagy protein ATG9A accumulated in the trans-Golgi network and was depleted from peripheral compartments. Western blot analysis demonstrated a 3-5-fold increase in ATG9A expression in patient lines. ATG9A was redistributed upon re-expression of AP4B1 arguing that mistrafficking of ATG9A is AP-4-dependent. Examining the downstream effects of ATG9A mislocalization, we found that autophagic flux was intact in patient-derived fibroblasts both under nutrient-rich conditions and when autophagy is stimulated. Mitochondrial metabolism and intracellular iron content remained unchanged. In iPSC-derived cortical neurons from patients with AP4B1-associated SPG47, AP-4 subunit levels were reduced while ATG9A accumulated in the trans-Golgi network. Levels of the autophagy marker LC3-II were reduced, suggesting a neuron-specific alteration in autophagosome turnover. Neurite outgrowth and branching were reduced in AP-4-HSP neurons pointing to a role of AP-4-mediated protein trafficking in neuronal development. Collectively, our results establish ATG9A mislocalization as a key marker of AP-4 deficiency in patient-derived cells, including the first human neuron model of AP-4-HSP, which will aid diagnostic and therapeutic studies.
CRIS-Team Scopus Importer:2020-02-14

Addition of triple negativity of breast cancer as an indicator for germline mutations in predisposing genes increases sensitivity of clinical selection criteria - Hoyer, Juliane; Vasileiou, Georgia; Uebe, Steffen; Wunderle, Marius; Kraus, Cornelia; Fasching, Peter; Thiel, Christian; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; Reis, André (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common cancer in women. 12-15% of all tumors are triple-negative breast cancers (TNBC). So far, TNBC has been mainly associated with mutations in BRCA1. The presence of other predisposing genes seems likely since DNA damage repair is a complex process that involves several genes. Therefore we investigated if mutations in other genes are involved in cancer development and whether TNBC is an additional indicator of mutational status besides family history and age of onset. METHODS: We performed a germline panel-based screening of 10 high and low-moderate penetrance breast cancer susceptibility genes (BRCA1, BRCA2, ATM, CDH1, CHEK2, NBN, PALB2, RAD51C, RAD51D and TP53) in 229 consecutive individuals affected with TNBC unselected for age, family history or bilateral disease. Within this cohort we compared the number of mutation carriers fulfilling clinical selection criteria with the total number of carriers identified. RESULTS: Age at diagnosis ranged from 23 to 80 years with an average age of 50.2 years. In 57 women (24.9%) we detected a pathogenic mutation, with a higher frequency (29.7%) in the group manifesting cancer before 60 years. Deleterious BRCA1 mutations occurred in 14.8% of TNBC patients. These were predominantly recurrent frameshift mutations (24/34, 70.6%). Deleterious BRCA2 mutations occurred in 5.7% of patients, all but one (c.1813dupA) being unique. While no mutations were found in CDH1 and TP53, 10 mutations were detected in one of the six other predisposition genes. Remarkably, neither of the ATM, RAD51D, CHEK2 and PALB2 mutation carriers had a family history. Furthermore, patients with non-BRCA1/2 mutations were not significantly younger than mutation negative women (p = 0.3341). Most importantly, among the 57 mutation carriers, ten (17.5%) would be missed using current clinical testing criteria including five (8%) with BRCA1/2 mutations. CONCLUSIONS: In summary, our data confirm and expand previous studies of a high frequency of germline mutations in genes associated with ineffective repair of DNA damage in women with TNBCs. Neither age of onset, contralateral disease nor family history were able to discern all mutation positive individuals. Therefore, TNBC should be considered as an additional criterion for panel based genetic testing.
EVALuna2:34811

A distinct CD38+CD45RA+ population of CD4+, CD8+, and double-negative T cells is controlled by FAS - Maccari, Maria Elena; Fuchs, Sebastian; Kury, Patrick; Andrieux, Geoffroy; Bengsch, Bertram; Lorenz, Myriam Ricarda; Heeg, Maximilian; Rohr, Jan; Jägle, Sabine; Castro, Carla N.; Groß, Miriam; Warthorst, Ursula; et al. (Journal of Experimental Medicine, 2021)
The identification and characterization of rare immune cell populations in humans can be facilitated by their growth advantage in the context of specific genetic diseases. Here, we use autoimmune lymphoproliferative syndrome to identify a population of FAS-controlled TCRαβ+ T cells. They include CD4+, CD8+, and double-negative T cells and can be defined by a CD38+CD45RA+T-BET- expression pattern. These unconventional T cells are present in healthy individuals, are generated before birth, are enriched in lymphoid tissue, and do not expand during acute viral infection. They are characterized by a unique molecular signature that is unambiguously different from other known T cell differentiation subsets and independent of CD4 or CD8 expression. Functionally, FAS-controlled T cells represent highly proliferative, noncytotoxic T cells with an IL-10 cytokine bias. Mechanistically, regulation of this physiological population is mediated by FAS and CTLA4 signaling, and its survival is enhanced by mTOR and STAT3 signals. Genetic alterations in these pathways result in expansion of FAS-controlled T cells, which can cause significant lymphoproliferative disease.
CRIS-Team Scopus Importer:2020-12-18

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

Adult hippocampal neurogenesis in Parkinson's disease: impact on neuronal survival and plasticity - Regensburger, Martin; Prots, Iryna; Winner, Beate (Neural Plasticity, 2014)
In Parkinson's disease (PD) and other synucleinopathies, chronic neurodegeneration occurs within different areas of the central nervous system leading to progressive motor and nonmotor symptoms. The symptomatic treatment options that are currently available do not slow or halt disease progression. This highlights the need of a better understanding of disease mechanisms and disease models. The generation of newborn neurons in the adult hippocampus and in the subventricular zone/olfactory bulb system is affected by many different regulators and possibly involved in memory processing, depression, and olfaction, symptoms which commonly occur in PD. The pathology of the adult neurogenic niches in human PD patients is still mostly elusive, but different preclinical models have shown profound alterations of adult neurogenesis. Alterations in stem cell proliferation, differentiation, and survival as well as neurite outgrowth and spine formation have been related to different aspects in PD pathogenesis. Therefore, neurogenesis in the adult brain provides an ideal model to study disease mechanisms and compounds. In addition, adult newborn neurons have been proposed as a source of endogenous repair. Herein, we review current knowledge about the adult neurogenic niches in PD and highlight areas of future research.
EVALuna2:26222

Adult neurogenesis and neurite outgrowth are impaired in LRRK2 G2019S mice - Winner, Beate; Gage, Fred H.; Winkler, Jürgen; et al. (Neurobiology of Disease, 2011)
The generation and maturation of adult neural stem/progenitor cells are impaired in many neurodegenerative diseases, among them is Parkinson's disease (PD). In mammals, including humans, adult neurogenesis is a lifelong feature of cellular brain plasticity in the hippocampal dentate gyrus (DG) and in the subventricular zone (SVZ)/olfactory bulb system. Hyposmia, depression, and anxiety are early non-motor symptoms in PD. There are parallels between brain regions associated with non-motor symptoms in PD and neurogenic regions. In autosomal dominant PD, mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are frequent LRRK2 homologs in non-vertebrate systems play an important role in chemotaxis, cell polarity, and neurite arborization. We investigated adult neurogenesis and the neurite development of new neurons in the DG and SVZ/olfactory bulb system in bacterial artificial chromosome (BAC) human Lrrk2 G2019S transgenic mice. We report that mutant human Lrrk2 is highly expressed in the hippocampus in the DG and the SVZ of adult Lrrk2 G2019S mice. Proliferation of newly generated cells is significantly decreased and survival of newly generated neurons in the DG and olfactory bulb is also severely impaired. In addition, after stereotactic injection of a GFP retrovirus, newly generated neurons in the DG of Lrrk2 G2019S mice exhibited reduced dendritic arborization and fewer spines. This loss in mature, developed spines might point towards a decrease in synaptic connectivity. Interestingly, physical activity partially reverses the decrease in neuroblasts observed in Lrrk2 G2010S mice. These data further support a role for Lrrk2 in neuronal morphogenesis and provide new insights into the role of Lrrk2 in adult neurogenesis. Published by Elsevier Inc.
Keywords: Neural progenitor cells; Neurogenesis; Parkinson's disease; Dendrites; Spines; LRRK2

Adult neurogenesis in neurodegenerative diseases - Winner, Beate; Winkler, Jürgen (Cold Spring Harbor Perspectives in Biology, 2015)
Adult neurogenesis is limited to specific brain regions in the mammalian brain, such as the hippocampal dentate gyrus and the subventricular zone/olfactory bulb system. Alterations in adult neurogenesis appear to be a common hallmark in different neurodegenerative diseases including Parkinson's disease (PD), Alzheimer's disease (AD), and Huntington's disease (HD). This is remarkable, because the distinct pathological proteins responsible for the different diseases induce the loss of different neural populations. Impaired adult neurogenesis was shown in numerous animal models of neurodegenerative diseases; however, only few postmortem studies have been performed. We will review concepts related to the interplay between cellular plasticity in regions of adult neurogenesis with a specific focus on cell-autonomous and non-cell-autonomous factors. Furthermore, various strategies aimed to stimulate neuronal plasticity will be discussed within the context of a potential translation into therapeutic approaches for neuropsychiatric symptoms associated with PD, HD, and AD.
EVALuna2:25348

Aggregation tests identify new gene associations with breast cancer in populations with diverse ancestry - Mueller, Stefanie H.; Lai, Alvina G.; Valkovskaya, Maria; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Lush, Michael; Abu-Ful, Zomoruda; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; et al. (Genome Medicine, 2023)
Background: Low-frequency variants play an important role in breast cancer (BC) susceptibility. Gene-based methods can increase power by combining multiple variants in the same gene and help identify target genes. Methods: We evaluated the potential of gene-based aggregation in the Breast Cancer Association Consortium cohorts including 83,471 cases and 59,199 controls. Low-frequency variants were aggregated for individual genes’ coding and regulatory regions. Association results in European ancestry samples were compared to single-marker association results in the same cohort. Gene-based associations were also combined in meta-analysis across individuals with European, Asian, African, and Latin American and Hispanic ancestry. Results: In European ancestry samples, 14 genes were significantly associated (q < 0.05) with BC. Of those, two genes, FMNL3 (P = 6.11 × 10−6) and AC058822.1 (P = 1.47 × 10−4), represent new associations. High FMNL3 expression has previously been linked to poor prognosis in several other cancers. Meta-analysis of samples with diverse ancestry discovered further associations including established candidate genes ESR1 and CBLB. Furthermore, literature review and database query found further support for a biologically plausible link with cancer for genes CBLB, FMNL3, FGFR2, LSP1, MAP3K1, and SRGAP2C. Conclusions: Using extended gene-based aggregation tests including coding and regulatory variation, we report identification of plausible target genes for previously identified single-marker associations with BC as well as the discovery of novel genes implicated in BC development. Including multi ancestral cohorts in this study enabled the identification of otherwise missed disease associations as ESR1 (P = 1.31 × 10−5), demonstrating the importance of diversifying study cohorts.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Breast cancer susceptibility; Diverse ancestry; Gene regulation; Genome-wide association study; Rare variants

A Homozygous Mutation in GPT2 Associated with Nonsyndromic Intellectual Disability in a Consanguineous Family from Costa Rica - Lobo-Prada, Tanya; Sticht, Heinrich; Bogantes-Ledezma, Sixto; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Leal, Alejandro (JIMD reports, 2017)
Intellectual disability is a highly heterogeneous disease that affects the central nervous system and impairs patients' ability to function independently. Despite multiples genes involved in the etiology of disease, most of the genetic background is yet to be discovered. We used runs of homozygosity and exome sequencing to study a large Costa Rican family with four individuals affected with severe intellectual disability and found a novel homozygous missense mutation, p. 96G>R, c. 286G>A, in all affected individuals. This gene encodes for a pyridoxal enzyme involved in the production of the neurotransmitter glutamate and is highly expressed in the white matter of brain and cerebellum. Protein modeling of GPT2 predicted that the mutation is located in a loop where the substrate binds to the active site of the enzyme, therefore, suggesting that the catalytic activity is impaired. With our report of a second mutation we fortify the importance of GPT2 as a novel cause of autosomal recessive nonsyndromic intellectual disability and support the premise that GPT2 is highly important for the neurodevelopment of the central nervous system.The mutation p. 96G>R c. 286G>A in GPT2, located in a loop where the substrate binds to the active site of the enzyme, fortifies the importance of GPT2 in the pathogenesis of nonsyndromic intellectual disability.
EVALuna2:9390

A large-scale assessment of two-way SNP interactions in breast cancer susceptibility using 46 450 cases and 42 461 controls from the breast cancer association consortium - Milne, Roger L.; Herranz, Jesus; Michailidou, Kyriaki; Dennis, Joe; Tyrer, Jonathan P.; Zamora, M. Pilar; Arias-Perez, Jose Ignacio; Gonzalez-Neira, Anna; Pita, Guillermo; Alonso, M. Rosario; Wang, Qin; Bolla, Manjeet K.; et al. (Human Molecular Genetics, 2014)
Part of the substantial unexplained familial aggregation of breast cancer may be due to interactions between common variants, but few studies have had adequate statistical power to detect interactions of realistic magnitude. We aimed to assess all two-way interactions in breast cancer susceptibility between 70 917 single nucleotide polymorphisms (SNPs) selected primarily based on prior evidence of a marginal effect. Thirty-eight international studies contributed data for 46 450 breast cancer cases and 42 461 controls of European origin as part of a multi-consortium project (COGS). First, SNPs were preselected based on evidence (P < 0.01) of a per-allele main effect, and all two-way combinations of those were evaluated by a per-allele (1 d.f.) test for interaction using logistic regression. Second, all 2.5 billion possible two-SNP combinations were evaluated using Boolean operation-based screening and testing, and SNP pairs with the strongest evidence of interaction (P < 10(-4)) were selected for more careful assessment by logistic regression. Under the first approach, 3277 SNPs were preselected, but an evaluation of all possible two-SNP combinations (1 d.f.) identified no interactions at P < 10(-8). Results from the second analytic approach were consistent with those from the first (P > 10(-10)). In summary, we observed little evidence of two-way SNP interactions in breast cancer susceptibility, despite the large number of SNPs with potential marginal effects considered and the very large sample size. This finding may have important implications for risk prediction, simplifying the modelling required. Further comprehensive, large-scale genome-wide interaction studies may identify novel interacting loci if the inherent logistic and computational challenges can be overcome.
EVALuna2:9207

Alpha-synuclein fine-tunes neuronal response to pro-inflammatory cytokines - Sigutova, Veronika; Xiang, Wei; Regensburger, Martin; Winner, Beate; Prots, Iryna (Brain Behavior and Immunity, 2024)
Pro-inflammatory cytokines are emerging as neuroinflammatory mediators in Parkinson's disease (PD) due to their ability to act through neuronal cytokine receptors. Critical questions persist regarding the role of cytokines in neuronal dysfunction and their contribution to PD pathology. Specifically, the potential synergy of the hallmark PD protein alpha-synuclein (α-syn) with cytokines is of interest. We therefore investigated the direct impact of pro-inflammatory cytokines on neurons and hypothesized that α-syn pathology exacerbates cytokine-induced neuronal deficits in PD. iPSC-derived cortical neurons (CNs) from healthy controls and patients with α-syn gene locus duplication (SNCA dupl) were stimulated with IL-17A, TNF-α, IFN-γ, or a combination thereof. For rescue experiments, CNs were pre-treated with α-syn anti-oligomerisation compound NPT100-18A prior to IL-17A stimulation. Cytokine receptor expression, microtubule cytoskeleton, axonal transport and neuronal activity were assessed. SNCA dupl CNs displayed an increased IL-17A receptor expression and impaired IL-17A-mediated cytokine receptor regulation. Cytokines exacerbated the altered distribution of tubulin post-translational modifications in SNCA dupl neurites, with SNCA dupl-specific IL-17A effects. Tau pathology in SNCA dupl CNs was also aggravated by IL-17A and cytokine mix. Cytokines slowed down mitochondrial axonal transport, with IL-17A-mediated retrograde slowing in SNCA dupl only. The pre-treatment of SNCA dupl CNs with NPT100-18A prevented the IL-17A-induced functional impairments in axonal transport and neural activity. Our work elucidates the detrimental effects of pro-inflammatory cytokines, particularly IL-17A, on human neuronal structure and function in the context of α-syn pathology, suggesting that cytokine-mediated inflammation represents a second hit to neurons in PD which is amenable to disease modifying therapies that are currently in clinical trials.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Alpha-synuclein; Cytokines; Neuroinflammation; Parkinson's disease

Alpha-synuclein prevents the formation of spherical mitochondria and apoptosis under oxidative stress - Winner, Beate; Menges, Stefanie; Minakaki, Georgia; Schaefer, Patrick; Meixner, Holger; Prots, Iryna; Schlötzer-Schrehardt, Ursula; Friedland, Kristina; Outeiro, Tiago F.; Winklhofer, Konstanze F.; Von Arnim, Christine A. F.; Xiang, Wei; et al. (Scientific Reports, 2017)
Oxidative stress (OS), mitochondrial dysfunction, and dysregulation of alpha-synuclein (aSyn) homeostasis are key pathogenic factors in Parkinson's disease. Nevertheless, the role of aSyn in mitochondrial physiology remains elusive. Thus, we addressed the impact of aSyn specifically on mitochondrial response to OS in neural cells. We characterize a distinct type of mitochondrial fragmentation, following H2O2 or 6-OHDA-induced OS, defined by spherically-shaped and hyperpolarized mitochondria, termed "mitospheres". Mitosphere formation mechanistically depended on the fission factor Drp1, and was paralleled by reduced mitochondrial fusion. Furthermore, mitospheres were linked to a decrease in mitochondrial activity, and preceded Caspase3 activation. Even though fragmentation of dysfunctional mitochondria is considered to be a prerequisite for mitochondrial degradation, mitospheres were not degraded via Parkin-mediated mitophagy. Importantly, we provide compelling evidence that aSyn prevents mitosphere formation and reduces apoptosis under OS. In contrast, aSyn did not protect against Rotenone, which led to a different, previously described donut-shaped mitochondrial morphology. Our findings reveal a dichotomic role of aSyn in mitochondrial biology, which is linked to distinct types of stress-induced mitochondrial fragmentation. Specifically, aSyn may be part of a cellular defense mechanism preserving neural mitochondrial homeostasis in the presence of increased OS levels, while not protecting against stressors directly affecting mitochondrial function.

Alport syndrome and autosomal dominant tubulointerstitial kidney disease frequently underlie end-stage renal disease of unknown origin-a single-center analysis - Leenen, Esther; Erger, Florian; Altmuller, Janine; Wenzel, Andrea; Thiele, Holger; Harth, Ana; Tschernoster, Nikolai; Lokhande, Shanti; Joerres, Achim; Becker, Jan-Ulrich; Ekici, Arif Bülent; Huettel, Bruno; et al. (Nephrology Dialysis Transplantation, 2022)
Background The prevalence of end-stage renal disease of unknown etiology in adult patients is globally high and accounts for almost 20% of all dialysis patients. Recent studies have suggested that the percentage of adult patients with a causal genetic variant has been underestimated so far. Despite severe prognostic and therapeutic implications, awareness about prevalence and manifestations of genetic kidney diseases in adult renal patients is still limited. Methods We recruited 58 individuals from 39 families at our transplantation center, fulfilling at least one of the following criteria: (i) unclear etiology of kidney disease, (ii) clinically suspected genetic kidney disease and (iii) positive family history for nephropathies. The cohort consisted of patients waitlisted for kidney transplantation and patients in the follow-up after transplantation. Detailed documentation of family history and phenotype was obtained before initiating gene panel sequencing of 479 nephropathy-associated genes. Results With this study design, a molecular genetic diagnosis was established in one-third of all patients. Mutations in the collagen COL4A genes, and mutations in MUC1 and UMOD were the most frequent among all detected causal variants. Overall, rare genetic variants were detected in more than half of all cases. Conclusion The combination of detailed phenotyping prior to next-generation sequencing diagnostics was highly efficient. Elucidating the underlying genetic causes in a cohort of adult renal patients has considerable clinical impact on medical management.
CRIS-Team WoS Importer:2022-08-12

ALS-associated VRK1 R321C mutation causes proteostatic imbalance and mitochondrial defects in iPSC-derived motor neurons - Oliveira, D.; Assoni, A. F.; Alves, L. M.; Sakugawa, A.; Melo, U. S.; Teles e Silva, A. L.; Sertie, A. L.; Caires, L. C.; Goulart, E.; Ghirotto, Bruno; Carvalho, V. M.; Ferrari, M. R.; et al. (Neurobiology of Disease, 2024)
Vaccinia-related kinase 1 (VRK1) is a gene which has been implicated in the pathological process of a broad range of neurodevelopmental disorders as well as neuropathies, such as Amyotrophic Lateral Sclerosis (ALS). Here we report a family presenting ALS in an autosomal recessive mode of inheritance, segregating with a homozygous missense mutation located in VRK1 gene (p.R321C; Arg321Cys). Proteomic analyses from iPSC-derived motor neurons identified 720 proteins eligible for subsequent investigation, and our exploration of protein profiles revealed significant enrichments in pathways such as mTOR signaling, E2F, MYC targets, DNA repair response, cell proliferation and energetic metabolism. Functional studies further validated such alterations, showing that affected motor neurons presented decreased levels of global protein output, ER stress and downregulation of mTOR signaling. Mitochondrial alterations also pointed to decreased reserve capacity and increased non-mitochondrial oxygen consumption. Taken together, our results present the main pathological alterations associated with VRK1 mutation in ALS.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Amyotrophic lateral sclerosis; Autosomal recessive inheritance; Neurogenetics; VRK1

ALS is imprinted in the chromatin accessibility of blood cells - Kühlwein, Julia K.; Ruf, Wolfgang P.; Kandler, Katharina; Witzel, Simon; Lang, Christina; Mulaw, Medhanie A.; Ekici, Arif Bülent; Weishaupt, Jochen H.; Ludolph, Albert C.; Grozdanov, Veselin; Danzer, Karin M. (Cellular and Molecular Life Sciences, 2023)
Amyotrophic Lateral Sclerosis (ALS) is a complex and incurable neurodegenerative disorder in which genetic and epigenetic factors contribute to the pathogenesis of all forms of ALS. The interplay of genetic predisposition and environmental footprints generates epigenetic signatures in the cells of affected tissues, which then alter transcriptional programs. Epigenetic modifications that arise from genetic predisposition and systemic environmental footprints should in theory be detectable not only in affected CNS tissue but also in the periphery. Here, we identify an ALS-associated epigenetic signature (‘epiChromALS’) by chromatin accessibility analysis of blood cells of ALS patients. In contrast to the blood transcriptome signature, epiChromALS includes also genes that are not expressed in blood cells; it is enriched in CNS neuronal pathways and it is present in the ALS motor cortex. By combining simultaneous ATAC-seq and RNA-seq with single-cell sequencing in PBMCs and motor cortex from ALS patients, we demonstrate that epigenetic changes associated with the neurodegenerative disease can be found in the periphery, thus strongly suggesting a mechanistic link between the epigenetic regulation and disease pathogenesis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Chromatin remodeling; Epigenome; Integrated analysis; Motor neuron disease; Regulatory elements; Single-nuclei sequencing

Altered GPM6A/M6 Dosage Impairs Cognition and Causes Phenotypes Responsive to Cholesterol in Human and Drosophila - Gregor, Anne; Kramer, Jamie M.; Van Der Voet, Monique; Schanze, Ina; Uebe, Steffen; Donders, Rogier; Reis, André; Schenck, Annette; Zweier, Christiane (Human Mutation, 2014)
Glycoprotein M6A (GPM6A) is a neuronal transmembrane protein of the PLP/DM20 (proteolipid protein) family that associates with cholesterol-rich lipid rafts and promotes filopodia formation. We identified a de novo duplication of the GPM6A gene in a patient with learning disability and behavioral anomalies. Expression analysis in blood lymphocytes showed increased GPM6A levels. An increase of patient-derived lymphoblastoid cells carrying membrane protrusions supports a functional effect of this duplication. To study the consequences of GPM6A dosage alterations in an intact nervous system, we employed Drosophila melanogaster as a model organism. We found that knockdown of Drosophila M6, the sole member of the PLP family in flies, in the wing, and whole organism causes malformation and lethality, respectively. These phenotypes as well as the protrusions of patient-derived lymphoblastoid cells with increased GPM6A levels can be alleviated by cholesterol supplementation. Notably, overexpression as well as loss of M6 in neurons specifically compromises long-term memory in the courtship conditioning paradigm. Our findings thus indicate a critical role of correct GPM6A/M6 levels for cognitive function and support a role of the GPM6A duplication for the patient's phenotype. Together with other recent findings, this study highlights compromised cholesterol homeostasis as a recurrent feature in cognitive phenotypes.
EVALuna2:9228

Alternative splicing and nonsense-mediated mRNA decay contribute to regulation of LOXL1 expression in response to cellular stress in pseudoexfoliation - Berner, Daniel; Zenkel, Matthias; Pasutto, Francesca; Schödel, Johannes; Reis, André; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (2017)
EVALuna2:34538

A monocyte gene expression signature in the early clinical course of Parkinson's disease - Schlachetzki, Johannes; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Winner, Beate; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2018)
Microglia are the main immune cells of the brain and express a large genetic pattern of genes linked to Parkinson's disease risk alleles. Monocytes like microglia are myeloid-lineage cells, raising the questions of the extent to which they share gene expression with microglia and whether they are already altered early in the clinical course of the disease. To decipher a monocytic gene expression signature in Parkinson's disease, we performed RNA-seq and applied the two-sample Kolmogorov-Smirnov test to identify differentially expressed genes between controls and patients with Parkinson's disease and changes in gene expression variability and dysregulation. The gene expression profiles of normal human monocytes and microglia showed a plethora of differentially expressed genes. Additionally, we identified a distinct gene expression pattern of monocytes isolated from Parkinson's disease patients at an early disease stage compared to controls using the Kolmogorov-Smirnov test. Differentially expressed genes included genes involved in immune activation such as HLA-DQB1, MYD88, REL, and TNF-alpha. Our data suggest that future studies of distinct leukocyte subsets are warranted to identify possible surrogate biomarkers and may lead to the identification of novel interventions early in the disease course.
EVALuna2:35780

A monocyte gene expression signature in the early clinical course of Parkinson's disease (vol 8, 10757, 2018) - Winner, Beate; Schlachetzki, Johannes C.M.; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2020)

AMPA-receptor specific biogenesis complexes control synaptic transmission and intellectual ability - Brechet, Aline; Buchert, Rebecca; Schwenk, Jochen; Boudkkazi, Sami; Zolles, Gerd; Siquier-Pernet, Karine; Schaber, Irene; Bildl, Wolfgang; Saadi, Abdelkrim; Bole-Feysot, Christine; Nitschke, Patrick; Reis, André; et al. (Nature Communications, 2017)
AMPA-type glutamate receptors (AMPARs), key elements in excitatory neurotransmission in the brain, are macromolecular complexes whose properties and cellular functions are determined by the co-assembled constituents of their proteome. Here we identify AMPAR complexes that transiently form in the endoplasmic reticulum (ER) and lack the core-subunits typical for AMPARs in the plasma membrane. Central components of these ER AMPARs are the proteome constituents FRRS1l (C9orf4) and CPT1c that specifically and cooperatively bind to the pore-forming GluA1-4 proteins of AMPARs. Bi-allelic mutations in the human FRRS1L gene are shown to cause severe intellectual disability with cognitive impairment, speech delay and epileptic activity. Virus-directed deletion or overexpression of FRRS1l strongly impact synaptic transmission in adult rat brain by decreasing or increasing the number of AMPARs in synapses and extra-synaptic sites. Our results provide insight into the early biogenesis of AMPARs and demonstrate its pronounced impact on synaptic transmission and brain function.
EVALuna2:9374

An alternative splicing modulator decreases mutant HTT and improves the molecular fingerprint in Huntington’s disease patient neurons - Krach, Florian; Stemick, Judith; Börstler, Tom; Weiss, Alexander; Lingos, Ioannis; Reischl, Stephanie; Meixner, Holger; Ploetz, Sonja; Farrell, Michaela; Hehr, Ute; Kohl, Zacharias; Winner, Beate; et al. (Nature Communications, 2022)
Huntington’s disease (HD) is a neurodegenerative disorder caused by poly-Q expansion in the Huntingtin (HTT) protein. Here, we delineate elevated mutant HTT (mHTT) levels in patient-derived cells including fibroblasts and iPSC derived cortical neurons using mesoscale discovery (MSD) HTT assays. HD patients’ fibroblasts and cortical neurons recapitulate aberrant alternative splicing as a molecular fingerprint of HD. Branaplam is a splicing modulator currently tested in a phase II study in HD (NCT05111249). The drug lowers total HTT (tHTT) and mHTT levels in fibroblasts, iPSC, cortical progenitors, and neurons in a dose dependent manner at an IC50 consistently below 10 nM without inducing cellular toxicity. Branaplam promotes inclusion of non-annotated novel exons. Among these Branaplam-induced exons, there is a 115 bp frameshift-inducing exon in the HTT transcript. This exon is observed upon Branaplam treatment in Ctrl and HD patients leading to a profound reduction of HTT RNA and protein levels. Importantly, Branaplam ameliorates aberrant alternative splicing in HD patients’ fibroblasts and cortical neurons. These findings highlight the applicability of splicing modulators in the treatment of CAG repeat disorders and decipher their molecular effects associated with the pharmacokinetic and -dynamic properties in patient-derived cellular models.
CRIS-Team Scopus Importer:2022-11-25

Analyses of association of psoriatic arthritis and psoriasis vulgaris with functional NCF1 variants - Löhr, Sabine; Ekici, Arif Bülent; Uebe, Steffen; Büttner, Christian; Köhm, Michaela; Behrens, Frank; Böhm, Beate; Sticherling, Michael; Schett, Georg; Simon, David; Mössner, Rotraut; Nimeh, Ali; et al. (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-07-02

Analysis of genetically determined gene expression suggest role of inflammatory processes in etiology of exfoliation syndrome - Hirbo, Jibril; Pasutto, Francesca; Sealock, Julia; Evans, Patrick; Pawar, Priyanka; Tao, Ran; Straub, Peter; Breyer, Max; Berner, Daniel; Reis, André; Schlötzer-Schrehardt, Ursula; Khor, C. C.; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-10-16

Analysis of genetically determined gene expression suggests role of inflammatory processes in exfoliation syndrome - Hirbo, Jibril B.; Pasutto, Francesca; Gamazon, Eric R.; Evans, Patrick; Pawar, Priyanka; Berner, Daniel; Sealock, Julia; Tao, Ran; Straub, Peter S.; Konkashbaev, Anuar I.; Breyer, Max A.; Schlötzer-Schrehardt, Ursula; et al. (BMC Genomics, 2023)
Background: Exfoliation syndrome (XFS) is an age-related systemic disorder characterized by excessive production and progressive accumulation of abnormal extracellular material, with pathognomonic ocular manifestations. It is the most common cause of secondary glaucoma, resulting in widespread global blindness. The largest global meta-analysis of XFS in 123,457 multi-ethnic individuals from 24 countries identified seven loci with the strongest association signal in chr15q22–25 region near LOXL1. Expression analysis have so far correlated coding and a few non-coding variants in the region with LOXL1 expression levels, but functional effects of these variants is unclear. We hypothesize that analysis of the contribution of the genetically determined component of gene expression to XFS risk can provide a powerful method to elucidate potential roles of additional genes and clarify biology that underlie XFS. Results: Transcriptomic Wide Association Studies (TWAS) using PrediXcan models trained in 48 GTEx tissues leveraging on results from the multi-ethnic and European ancestry GWAS were performed. To eliminate the possibility of false-positive results due to Linkage Disequilibrium (LD) contamination, we i) performed PrediXcan analysis in reduced models removing variants in LD with LOXL1 missense variants associated with XFS, and variants in LOXL1 models in both multiethnic and European ancestry individuals, ii) conducted conditional analysis of the significant signals in European ancestry individuals, and iii) filtered signals based on correlated gene expression, LD and shared eQTLs, iv) conducted expression validation analysis in human iris tissues. We observed twenty-eight genes in chr15q22–25 region that showed statistically significant associations, which were whittled down to ten genes after statistical validations. In experimental analysis, mRNA transcript levels for ARID3B, CD276, LOXL1, NEO1, SCAMP2, and UBL7 were significantly decreased in iris tissues from XFS patients compared to control samples. TWAS genes for XFS were significantly enriched for genes associated with inflammatory conditions. We also observed a higher incidence of XFS comorbidity with inflammatory and connective tissue diseases. Conclusion: Our results implicate a role for connective tissues and inflammation pathways in the etiology of XFS. Targeting the inflammatory pathway may be a potential therapeutic option to reduce progression in XFS.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Exfoliation syndrome; GTEx; GWAS; predicted expressions; transcriptomics; TWAS

Analysis of the expression pattern of the schizophrenia-risk and intellectual disability gene TCF4 in the developing and adult brain suggests a role in development and plasticity of cortical and hippocampal neurons - Jung, Matthias; Häberle, Benjamin; Tschaikowsky, Tristan; Wittmann, Marie-Theres; Balta, Elli-Anna; Stadler, Vivien-Charlott; Zweier, Christiane; Dörfler, Arnd; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Molecular Autism, 2018)
Background: Haploinsufficiency of the class I bHLH transcription factor TCF4 causes Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder, while common variants in the TCF4 gene have been identified as susceptibility factors for schizophrenia. It remains largely unknown, which brain regions are dependent on TCF4 for their development and function. Methods: We systematically analyzed the expression pattern of TCF4 in the developing and adult mouse brain. We used immunofluorescent staining to identify candidate regions whose development and function depend on TCF4. In addition, we determined TCF4 expression in the developing rhesus monkey brain and in the developing and adult human brain through analysis of transcriptomic datasets and compared the expression pattern between species. Finally, we morphometrically and histologically analyzed selected brain structures in Tcf4-haploinsufficient mice and compared our morphometric findings to neuroanatomical findings in PTHS patients. Results: TCF4 is broadly expressed in cortical and subcortical structures in the developing and adult mouse brain. The TCF4 expression pattern was highly similar between humans, rhesus monkeys, and mice. Moreover, Tcf4 haploinsufficiency in mice replicated structural brain anomalies observed in PTHS patients. Conclusion: Our data suggests that TCF4 is involved in the development and function of multiple brain regions and indicates that its regulation is evolutionary conserved. Moreover, our data validate Tcf4-haploinsufficient mice as a model to study the neurodevelopmental basis of PTHS.
EVALuna:34022

An assessment of guca1c variants in primary congenital glaucoma - Souzeau, Emmanuelle; Weisschuh, Nicole; Craig, Jamie E.; Pasutto, Francesca; Koch, Karl Wilhelm (Genes, 2021)
CRIS-Team Scopus Importer:2021-04-02
Keywords: GCAP3; GUCA1C; Primary congenital glaucoma

A nation-wide, multi-center study on the quality of life of ALS patients in Germany - Peseschkian, Tara; Cordts, Isabell; Günther, René; Stolte, Benjamin; Zeller, Daniel; Schröter, Carsten; Weyen, Ute; Regensburger, Martin; Wolf, Joachim; Schneider, Ilka; Hermann, Andreas; Metelmann, Moritz; et al. (Brain Sciences, 2021)
Improving quality of life (QoL) is central to amyotrophic lateral sclerosis (ALS) treatment. This Germany-wide, multicenter cross-sectional study analyses the impact of different symptom-specific treatments and ALS variants on QoL. Health-related QoL (HRQoL) in 325 ALS patients was assessed using the Amyotrophic Lateral Sclerosis Assessment Questionnaire 5 (ALSAQ-5) and Eu-roQol Five Dimension Five Level Scale (EQ-5D-5L), together with disease severity (captured by the revised ALS Functional Rating Scale (ALSFRS-R)) and the current care and therapies used by our cohort. At inclusion, the mean ALSAQ-5 total score was 56.93 (max. 100, best = 0) with a better QoL associated with a less severe disease status (β = −1.96 per increase of one point in the ALSFRS-R score, p < 0.001). “Limb onset” ALS (lALS) was associated with a better QoL than “bulbar onset” ALS (bALS) (mean ALSAQ-5 total score 55.46 versus 60.99, p = 0.040). Moreover, with the ALSFRS-R as a covariate, using a mobility aid (β = −7.60, p = 0.001), being tracheostomized (β = −14.80, p = 0.004) and using non-invasive ventilation (β = –5.71, p = 0.030) were associated with an improved QoL, compared to those at the same disease stage who did not use these aids. In contrast, antide-pressant intake (β = 5.95, p = 0.007), and increasing age (β = 0.18, p = 0.023) were predictors of worse QoL. Our results showed that the ALSAQ-5 was better-suited for ALS patients than the EQ-5D-5L. Further, the early and symptom-specific clinical management and supply of assistive devices can significantly improve the individual HRQoL of ALS patients. Appropriate QoL questionnaires are needed to monitor the impact of treatment to provide the best possible and individualized care.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ALS treatment; Amyotrophic lateral sclerosis (ALS); Amyotrophic Lateral Sclerosis Assessment Questionnaire 5 (ALSAQ-5); Assistive devices; EuroQol Five Dimension Five Level Scale (EQ-5D-5L); Health-related quality of life (HRQoL); Quality of life (QoL); Symptom-specific treatment; “Bulbar onset” ALS (bALS); “Limb onset” ALS (lALS)

A NEW DIAGNOSTIC APPROACH TO HLA TESTING IN KIDNEY TRANSPLANT RECIPIENTS USING CULTURED URINE DERIVED TUBULAR CELLS - Spriewald, Bernd; Herrmann, Markus; Bach, Christian; Knaup, Karl; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Schiffer, Mario; Wiesener, Michael (Joint 34th European Immunogenetics and Histocompatibility and 31st British Society for Histocompatibility and Immunogenetics Conference, 2020)
CRIS-Team WoS Importer:2020-03-24

A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines - Nolte, Elke; Wach, Sven; Silva, Izabella Thais; Lukat, Sabine; Ekici, Arif Bülent; Munkert, Jennifer; Müller-Uri, Frieder; Kreis, Wolfgang; Simões, Cláudia M. O.; Vera González, Julio; Wullich, Bernd; Taubert, Helge; et al. (Oncotarget, 2017)
EVALuna2:9377
Keywords: Cardiac glycoside analog; Cell cycle; 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin; Human renal cell carcinoma cells; MiRNA

Angiopoietin-1 is required for Schlemm's canal development in mice and humans - Thomson, Benjamin R.; Souma, Tomokazu; Tompson, Stuart W.; Onay, Tuncer; Kizhatil, Krishnakumar; Siggs, Owen M.; Feng, Liang; Whisenhunt, Kristina N.; Yanovitch, Tammy L.; Kalaydjieva, Luba; Azmanov, Dimitar N.; Finzi, Simone; et al. (Journal of Clinical Investigation, 2017)
Primary congenital glaucoma (PCG) is a leading cause of blindness in children worldwide and is caused by developmental defects in 2 aqueous humor outflow structures, Schlemm's canal (SC) and the trabecular meshwork. We previously identified loss-of-function mutations in the angiopoietin (ANGPT) receptor TEK in families with PCG and showed that ANGPT/TEK signaling is essential for SC development. Here, we describe roles for the major ANGPT ligands in the development of the aqueous outflow pathway. We determined that ANGPT1 is essential for SC development, and that Angpt1-knockout mice form a severely hypomorphic canal with elevated intraocular pressure. By contrast, ANGPT2 was dispensable, although mice deficient in both Angpt1 and Angpt2 completely lacked SC, indicating that ANGPT2 compensates for the loss of ANGPT1. In addition, we identified 3 human subjects with rare ANGPT1 variants within an international cohort of 284 PCG patients. Loss of function in 2 of the 3 patient alleles was observed by functional analysis of ANGPT1 variants in a combined in silico, in vitro, and in vivo approach, supporting a causative role for ANGPT1 in disease. By linking ANGPT1 with PCG, these results highlight the importance of ANGPT/TEK signaling in glaucoma pathogenesis and identify a candidate target for therapeutic development.
EVALuna2:9397

Angiopoietin receptor TEK mutations underlie primary congenital glaucoma with variable expressivity - Souma, Tomokazu; Tompson, Stuart W.; Thomson, Benjamin R.; Siggs, Owen M.; Kizhatil, Krishnakumar; Yamaguchi, Shinji; Feng, Liang; Limviphuvadh, Vachiranee; Whisenhunt, Kristina N.; Maurer-Stroh, Sebastian; Yanovitch, Tammy L.; Kalaydjieva, Luba; et al. (Journal of Clinical Investigation, 2016)
Primary congenital glaucoma (PCG) is a devastating eye disease and an important cause of childhood blindness worldwide. In PCG, defects in the anterior chamber aqueous humor outflow structures of the eye result in elevated intraocular pressure (IOP); however, the genes and molecular mechanisms involved in the etiology of these defects have not been fully characterized. Previously, we observed PCG-like phenotypes in transgenic mice that lack functional angiopoietin-TEK signaling. Herein, we identified rare TEK variants in 10 of 189 unrelated PCG families and demonstrated that each mutation results in haploinsufficiency due to protein loss of function. Multiple cellular mechanisms were responsible for the loss of protein function resulting from individual TEK variants, including an absence of normal protein production, protein aggregate formation, enhanced proteasomal degradation, altered subcellular localization, and reduced responsiveness to ligand stimulation. Further, in mice, hemizygosity for Tek led to the formation of severely hypomorphic Schlemm's canal and trabecular meshwork, as well as elevated IOP, demonstrating that anterior chamber vascular development is sensitive to Tek gene dosage and the resulting decrease in angiopoietin-TEK signaling. Collectively, these results identify TEK mutations in patients with PCG that likely underlie disease and are transmitted in an autosomal dominant pattern with variable expressivity.
EVALuna2:9325

A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection

A novel human stem cell model for Coffin-Siris syndrome-like syndrome reveals the importance of SOX11 dosage for neuronal differentiation and survival - Turan, Sören; Börstler, Tom; Kavyanifar, Atria; Loskarn, Sandra; Reis, André; Winner, Beate; Lie, Dieter Chichung (Human Molecular Genetics, 2019)
The SOXC transcription factors Sox4, Sox11 and Sox12, are critical neurodevelopmental regulators that are thought to function in a highly redundant fashion. Surprisingly, heterozygous missense mutations or deletions of SOX11 were recently detected in patients with Coffin-Siris syndrome-like syndrome (CSSLS), a neurodevelopmental disorder associated with intellectual disability, demonstrating that in humans SOX11 haploinsufficiency cannot be compensated and raising the question of the function of SOX11 in human neurodevelopment. Here, we describe the generation of SOX11(+/-) heterozygous human embryonic stem cell (hESC) lines by CRISPR/Cas9 genome engineering. SOX11 haploinsufficiency impaired the generation of neurons and resulted in a proliferation/differentiation imbalance of neural precursor cells and enhanced neuronal cell death. Using the SOX11(+/-) hESC model we provide for the first time experimental evidence that SOX11 haploinsufficiency is sufficient to impair key processes of human neurodevelopment, giving a first insight into the pathophysiology of CSSLS and SOX11 function in human neurodevelopment.
CRIS-Team WoS Importer:2019-11-12

A novel splice variant expands the LAMC3-associated cortical phenotype to frontal only polymicrogyria and adult-onset epilepsy - Kasper, Burkhard; Kraus, Cornelia; Schwarz, Michael; Rösch, Julie; Thiel, Christian; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Bi-allelic loss-of-function variants in LAMC3, encoding extracellular matrix protein laminin gamma 3, represent a rare cause of occipital polymicrogyria with epilepsy, developmental delay and cognitive impairment. So far, only five families have been reported. We now identified a novel, homozygous splice variant in LAMC3 in an individual with an unusual manifestation of cortical malformation. She presented with polymicrogyria in the frontal but not the occipital lobes, with adult-onset seizures and normal psychomotor development and cognition. Additionally, ictal asystole, requiring implantation of a pacemaker, and nonepileptic seizures occurred. This case expands the spectrum of LAMC3-associated cortical malformation phenotypes to frontal only polymicrogyria and adult-onset of epilepsy.
CRIS-Team Scopus Importer:2020-09-18
Keywords: cortical malformation; epilepsy; LAMC3; polymicrogyria; seizures

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A.; Szymanska, Katarzyna; Nguyen, Thanh-Minh T.; Racher, Hilary; Phelps, Ian G.; Toedts, Grischa; Kennedy, Julie; Wunderlich, Kirsten A.; Sorusch, Nasrin; Abdelhamed, Zakia A.; et al. (Nature Cell Biology, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
EVALuna2:9277

Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

A Peroxisomal Disorder of Severe Intellectual Disability, Epilepsy, and Cataracts Due to Fatty Acyl-CoA Reductase 1 Deficiency - Buchert, Rebecca; Tawamie, Hasan; Smith, Christopher; Uebe, Steffen; Innes, A. Micheil; Al Hallak, Bassam; Ekici, Arif Bülent; Sticht, Heinrich; Schwarze, Bernd; Lamont, Ryan E.; Parboosingh, Jillian S.; Bernier, Francois P.; et al. (American Journal of Human Genetics, 2014)
Rhizomelic chondrodysplasia punctata (RCDP) is a group of disorders with overlapping clinical features including rhizomelia, chondrodysplasia punctata, coronal clefts, cervical dysplasia, congenital cataracts, profound postnatal growth retardation, severe intellectual disability, and seizures. Mutations in PEX7, GNPAT, and AGPS, all involved in the plasmalogen-biosynthesis pathway, have been described in individuals with RCDP. Here, we report the identification of mutations in another gene in plasmalogen biosynthesis, fatty acyl-CoA reductase 1 (FAR1), in two families affected by severe intellectual disability, early-onset epilepsy, microcephaly, congenital cataracts, growth retardation, and spasticity. Exome analyses revealed a homozygous in-frame indel mutation (c.495_507delinsT [p.Glu165_Pro169delinsAsp]) in two siblings from a consanguineous family and compound-heterozygous mutations (c.[787C>T];[1094A>G], p.[Arg263(*)];[Asp365Gly]) in a third unrelated individual. FAR1 reduces fatty acids to their respective fatty alcohols for the plasmalogen-biosynthesis pathway. To assess the pathogenicity of the identified mutations, we transfected human embryonic kidney 293 cells with plasmids encoding FAR1 with either wild-type or mutated constructs and extracted the lipids from the cells. We screened the lipids with gas chromatography and mass spectrometry and found that all three mutations abolished the reductase activity of FAR1, given that no fatty alcohols could be detected. We also observed reduced plasmalogens in red blood cells in one individual to a range similar to that seen in individuals with RCDP, further supporting abolished FAR1 activity. We thus expand the spectrum of clinical features associated with defects in plasmalogen biosynthesis to include FAR1 deficiency as a cause of syndromic severe intellectual disability with cataracts, epilepsy, and growth retardation but without rhizomelia.
EVALuna2:9238

A potential role for impaired retinoic acid signaling in the pathophysiology of pseudoexfoliation syndrome/glaucoma - Zenkel, Matthias; Berner, Daniel; Hoja, Ursula; Pasutto, Francesca; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

A recessive form of extreme macrocephaly and mild intellectual disability complements the spectrum of PTEN hamartoma tumour syndrome - Schwerd, Tobias; Khaled, Andrea V.; Schürmann, Manfred; Chen, Hannah; Händel, Norman; Reis, André; Gillessen-Kaesbach, Gabriele; Uhlig, Holm H.; Abou Jamra, Rami (European journal of human genetics, 2015)
PTEN hamartoma tumour syndrome (PHTS) is caused by heterozygous variants in PTEN and is characterised by tumour predisposition, macrocephaly, and cognition impairment. Bi-allelic loss of PTEN activity has not been reported so far and animal models suggest that bi-allelic loss of PTEN activity is embryonically lethal. Here, we report the identification of a novel homozygous variant in PTEN, NM_000314.4; c.545T>C; p.Leu182Ser, in two adolescent siblings with severe macrocephaly and mild intellectual disability. The variant is predicted to be damaging and is associated with significantly increased phospho-S6 downstream of PTEN. The absence of tumours in the two homozygous siblings as well as lack of symptoms of PHTS in the heterozygous carriers of the family suggest that this particular variant is functionally hypomorphic rather than deleterious.European Journal of Human Genetics advance online publication, 7 October 2015; doi:10.1038/ejhg.2015.209.
EVALuna2:9252

A reversible state of hypometabolism in a human cellular model of sporadic Parkinson’s disease - Schmidt, Sebastian; Stautner, Constantin; Vu, Duc Tung; Heinz, Alexander; Regensburger, Martin; Karayel, Ozge; Trümbach, Dietrich; Artati, Anna; Kaltenhäuser, Sabine; Nassef, Mohamed Zakaria; Hembach, Sina; Steinert, Letyfee; et al. (Nature Communications, 2023)
Sporadic Parkinson’s Disease (sPD) is a progressive neurodegenerative disorder caused by multiple genetic and environmental factors. Mitochondrial dysfunction is one contributing factor, but its role at different stages of disease progression is not fully understood. Here, we showed that neural precursor cells and dopaminergic neurons derived from induced pluripotent stem cells (hiPSCs) from sPD patients exhibited a hypometabolism. Further analysis based on transcriptomics, proteomics, and metabolomics identified the citric acid cycle, specifically the α-ketoglutarate dehydrogenase complex (OGDHC), as bottleneck in sPD metabolism. A follow-up study of the patients approximately 10 years after initial biopsy demonstrated a correlation between OGDHC activity in our cellular model and the disease progression. In addition, the alterations in cellular metabolism observed in our cellular model were restored by interfering with the enhanced SHH signal transduction in sPD. Thus, inhibiting overactive SHH signaling may have potential as neuroprotective therapy during early stages of sPD.
CRIS-Team Scopus Importer:2023-12-08

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

ARHGEF9 disease: Phenotype clarification and genotype-phenotype correlation - Alber, Michael; Kalscheuer, Vera M.; Marco, Elysa; Sherr, Elliott; Lesca, Gaetan; Till, Marianne; Gradek, Gyri; Wiesener, Antje; Korenke, Christoph; Mercier, Sandra; Becker, Felicitas; Yamamoto, Toshiyuki; et al. (Neurology Genetics, 2017)
OBJECTIVE: We aimed to generate a review and description of the phenotypic and genotypic spectra of ARHGEF9 mutations. METHODS: Patients with mutations or chromosomal disruptions affecting ARHGEF9 were identified through our clinics and review of the literature. Detailed medical history and examination findings were obtained via a standardized questionnaire, or if this was not possible by reviewing the published phenotypic features. RESULTS: A total of 18 patients (including 5 females) were identified. Six had de novo, 5 had maternally inherited mutations, and 7 had chromosomal disruptions. All females had strongly skewed X-inactivation in favor of the abnormal X-chromosome. Symptoms presented in early childhood with delayed motor development alone or in combination with seizures. Intellectual disability was severe in most and moderate in patients with milder mutations. Males with severe intellectual disability had severe, often intractable, epilepsy and exhibited a particular facial dysmorphism. Patients with mutations in exon 9 affecting the protein's PH domain did not develop epilepsy. CONCLUSIONS: ARHGEF9 encodes a crucial neuronal synaptic protein; loss of function of which results in severe intellectual disability, epilepsy, and a particular facial dysmorphism. Loss of only the protein's PH domain function is associated with the absence of epilepsy.
EVALuna2:33864

ARID1B-related disorder in 87 adults: Natural history and self-sustainability - van der Sluijs, P. J.; Gösgens, M.; Dingemans, A. J.M.; Striano, P.; Riva, A.; Mignot, C.; Faudet, A.; Vasileiou, Georgia; Walther, Mona; Schrier Vergano, S. A.; Alders, M.; Alkuraya, F. S.; et al. (Genetics in Medicine Open, 2024)
Purpose: ARID1B is one of the most frequently mutated genes in intellectual disability cohorts. Thus, far few adult-aged patients with ARID1B-related disorder have been described, which limits our understanding of the disease's natural history and our ability to counsel patients and their families. Methods: Data on patients aged 18+ years with ARID1B-related disorder were collected through an online questionnaire completed by clinicians and parents. Results: Eighty-seven adult patients with ARID1B were included. Cognitive functioning ranged from borderline to severe intellectual disability. Patients identified through the genetic workup of their child were either mosaic or had a variant in exon 1. New clinical features identified in this population are loss of skill (16/64, 25%) and recurrent patella luxation (12/45, 32%). Self-sustainability data showed that 88% (45/51) could eat independently, and 16% (7/45) could travel alone by public transport. Facial photo analysis showed that patients’ photographs taken at different ages clustered consistently, separate from matched controls. Conclusion: The ARID1B spectrum is broad, and as patients age, there is a significant shift in the medical aspects requiring attention. To address the changing medical needs with increasing age, we have formulated recommendations to promote timely intervention in an attempt to mitigate disease progression.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Adult; ARID1B; Coffin–Siris syndrome; Developmental delay; Intellectual disability

Artificial light at night affects brain plasticity and melatonin in birds - Moaraf, Stan; Vistoropsky, Yulia; Pozner, Tatyana; Heiblum, Rachel; Okuliarová, Monika; Zeman, Michal; Barnea, Anat (Neuroscience Letters, 2019)
Artificial light at night (ALAN), which disrupts the daily cycle of light, has vast biological impacts on all organisms, and is also associated with several health problems. The few existing studies on neuronal plasticity and cognitive functions in mammals indicate that a disruption of the circadian cycle impairs learning and memory and suppresses neurogenesis. However, nothing is known about the effect of ALAN on neuronal plasticity in birds. To this end, zebra finches (Taeniopygia guttata) were exposed to ecologically relevant ALAN intensities (0.5, 1.5 and 5 lx), treated with BrdU to quantify cell proliferation in their ventricular zone (VZ), and compared to controls that were kept under dark nights. We found, in our diurnal birds, that ALAN significantly increased cell proliferation in the VZ. However, neuronal densities in two brain regions decreased under ALAN, suggesting neuronal death. In addition, ALAN suppressed nocturnal melatonin production in a dose-dependent manner, and might also increase body mass. Taken together, our findings add to the notion of the deleterious effect of ALAN.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Artificial light at night (ALAN); Cell proliferation; Circadian cycle; Melatonin; Neuronal densities; Zebra finches (Taeniopygia guttata)

A saturated map of common genetic variants associated with human height - Yengo, Loic; Vedantam, Sailaja; Marouli, Eirini; Sidorenko, Julia; Bartell, Eric; Sakaue, Saori; Graff, Marielisa; Eliasen, Anders U.; Jiang, Yunxuan; Raghavan, Sridharan; Miao, Jenkai; Arias, Joshua D.; et al. (Nature, 2022)
Common single-nucleotide polymorphisms (SNPs) are predicted to collectively explain 40–50% of phenotypic variation in human height, but identifying the specific variants and associated regions requires huge sample sizes1. Here, using data from a genome-wide association study of 5.4 million individuals of diverse ancestries, we show that 12,111 independent SNPs that are significantly associated with height account for nearly all of the common SNP-based heritability. These SNPs are clustered within 7,209 non-overlapping genomic segments with a mean size of around 90 kb, covering about 21% of the genome. The density of independent associations varies across the genome and the regions of increased density are enriched for biologically relevant genes. In out-of-sample estimation and prediction, the 12,111 SNPs (or all SNPs in the HapMap 3 panel2) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10–20% (14–24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.
CRIS-Team Scopus Importer:2022-10-28

A spinal epidural abscess due to Streptobacillus moniliformis infection following a rat bite: case report - Hammer, Alexander; Wolff, Dorit; Geißdörfer, Walter; Schrey, Michael; Ziegler, Renate; Steiner, Hans-Herbert; Bogdan, Christian (Journal of Neurosurgery-Spine, 2017)
The authors describe the case of a 40-year-old man suffering from an epidural abscess in the thoracic spine due to a rarely isolated pathogen, Streptobacillus moniliformis, the causative agent of rat bite fever. Besides diffuse abdominal pain, ataxia, paresthesia, hypesthesia, and enhanced reflexes of the lower extremities, the patient suffered from a decreased sensation of bladder filling. His history was also positive for a rat bite 6 weeks earlier. Magnetic resonance imaging showed an epidural, space-occupying lesion compressing the spinal cord at the vertebral levels of T6-8. Neurosurgery revealed an epidural abscess, which was drained via laminectomy (T-7) and excision of the ligamentum flavum (T6-8). The etiological agent S. moniliformis was identified by 16S rRNA-based polymerase chain reaction and sequencing as well as by culture and mass spectrometry. Treatment with penicillin G led to complete resolution of the abscess and clinical recovery of the patient, who regained his bladder-filling sensation and free walking ability. This case demonstrates that careful attention to the patient's history is essential in suspecting unusual bacterial pathogens as the cause of an epidural abscess and initiating the optimal diagnostic procedure and antimicrobial therapy.
EVALuna2:7753

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with prognosis of estrogen receptor-negative breast cancer after chemotherapy - Lei, Jieping; Rudolph, Anja; Moysich, Kirsten B.; Rafiq, Sajjad; Behrens, Sabine; Goode, Ellen L.; Pharoah, Paul Pd; Seibold, Petra; Fasching, Peter; Andrulis, Irene L.; Kristensen, Vessela N.; Couch, Fergus J.; et al. (Breast Cancer Research, 2015)
Tumor lymphocyte infiltration is associated with clinical response to chemotherapy in estrogen receptor (ER) negative breast cancer. To identify variants in immunosuppressive pathway genes associated with prognosis after adjuvant chemotherapy for ER-negative patients, we studied stage I-III invasive breast cancer patients of European ancestry, including 9,334 ER-positive (3,151 treated with chemotherapy) and 2,334 ER-negative patients (1,499 treated with chemotherapy).We pooled data from sixteen studies from the Breast Cancer Association Consortium (BCAC), and employed two independent studies for replications. Overall 3,610 single nucleotide polymorphisms (SNPs) in 133 genes were genotyped as part of the Collaborative Oncological Gene-environment Study, in which phenotype and clinical data were collected and harmonized. Multivariable Cox proportional hazard regression was used to assess genetic associations with overall survival (OS) and breast cancer-specific survival (BCSS). Heterogeneity according to chemotherapy or ER status was evaluated with the log-likelihood ratio test.Three independent SNPs in TGFBR2 and IL12B were associated with OS (P <10?³) solely in ER-negative patients after chemotherapy (267 events). Poorer OS associated with TGFBR2 rs1367610 (G > C) (per allele hazard ratio (HR) 1.54 (95% confidence interval (CI) 1.22 to 1.95), P = 3.08 × 10??) was not found in ER-negative patients without chemotherapy or ER-positive patients with chemotherapy (P for interaction <10-3). Two SNPs in IL12B (r² = 0.20) showed different associations with ER-negative disease after chemotherapy: rs2546892 (G > A) with poorer OS (HR 1.50 (95% CI 1.21 to 1.86), P = 1.81 × 10??), and rs2853694 (A > C) with improved OS (HR 0.73 (95% CI 0.61 to 0.87), P = 3.67 × 10??). Similar associations were observed with BCSS. Association with TGFBR2 rs1367610 but not IL12B variants replicated using BCAC Asian samples and the independent Prospective Study of Outcomes in Sporadic versus Hereditary Breast Cancer Study and yielded a combined HR of 1.57 ((95% CI 1.28 to 1.94), P = 2.05 × 10??) without study heterogeneity.TGFBR2 variants may have prognostic and predictive value in ER-negative breast cancer patients treated with adjuvant chemotherapy. Our findings provide further insights into the development of immunotherapeutic targets for ER-negative breast cancer.
EVALuna2:9270

Assessment of variation in immunosuppressive pathway genes reveals TGFBR2 to be associated with risk of clear cell ovarian cancer - Hampras, Shalaka S.; Sucheston-Campbell, Lara E.; Cannioto, Rikki; Chang-Claude, Jenny; Modugno, Francesmary; Doerk, Thilo; Hillemanns, Peter; Preus, Leah; Knutson, Keith L.; Wallace, Paul K.; Hong, Chi-Chen; Friel, Grace; et al. (Oncotarget, 2016)
Regulatory T (Treg) cells, a subset of CD4+ T lymphocytes, are mediators of immunosuppression in cancer, and, thus, variants in genes encoding Treg cell immune molecules could be associated with ovarian cancer.In a population of 15,596 epithelial ovarian cancer (EOC) cases and 23,236 controls, we measured genetic associations of 1,351 SNPs in Treg cell pathway genes with odds of ovarian cancer and tested pathway and gene-level associations, overall and by histotype, for the 25 genes, using the admixture likelihood (AML) method. The most significant single SNP associations were tested for correlation with expression levels in 44 ovarian cancer patients.The most significant global associations for all genes in the pathway were seen in endometrioid (p = 0.082) and clear cell (p = 0.083), with the most significant gene level association seen with TGFBR2 (p = 0.001) and clear cell EOC. Gene associations with histotypes at p < 0.05 included: IL12 (p = 0.005 and p = 0.008, serous and high-grade serous, respectively), IL8RA (p = 0.035, endometrioid and mucinous), LGALS1 (p = 0.03, mucinous), STAT5B (p = 0.022, clear cell), TGFBR1 (p = 0.021 endometrioid) and TGFBR2 (p = 0.017 and p = 0.025, endometrioid and mucinous, respectively).Common inherited gene variation in Treg cell pathways shows some evidence of germline genetic contribution to odds of EOC that varies by histologic subtype and may be associated with mRNA expression of immune-complex receptor in EOC patients.
EVALuna2:9345

Association analyses of functional NCF1 variants in psoriatic arthritis and psoriasis vulgaris - Hüffmeier, Ulrike; Löhr, Sabine; Ekici, Arif Bülent; Uebe, S.; Koehm, M.; Behrens, F.; Boehm, B.; Sticherling, Michael; Schett, Georg; Moessner, R.; Nimeh, A.; Assmann, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Association analysis identifies 65 new breast cancer risk loci - Michailidou, Kyriaki; Lindstrom, Sara; Dennis, Joe; Beesley, Jonathan; Hui, Shirley; Kar, Siddhartha; Lemacon, Audrey; Soucy, Penny; Glubb, Dylan; Rostamianfar, Asha; Bolla, Manjeet K.; Wang, Qin; et al. (Nature, 2017)
Breast cancer risk is influenced by rare coding variants in susceptibility genes, such as BRCA1, and many common, mostly non-coding variants. However, much of the genetic contribution to breast cancer risk remains unknown. Here we report the results of a genome-wide association study of breast cancer in 122,977 cases and 105,974 controls of European ancestry and 14,068 cases and 13,104 controls of East Asian ancestry. We identified 65 new loci that are associated with overall breast cancer risk at P < 5 × 10-8. The majority of credible risk single-nucleotide polymorphisms in these loci fall in distal regulatory elements, and by integrating in silico data to predict target genes in breast cells at each locus, we demonstrate a strong overlap between candidate target genes and somatic driver genes in breast tumours. We also find that heritability of breast cancer due to all single-nucleotide polymorphisms in regulatory features was 2-5-fold enriched relative to the genome-wide average, with strong enrichment for particular transcription factor binding sites. These results provide further insight into genetic susceptibility to breast cancer and will improve the use of genetic risk scores for individualized screening and prevention.
EVALuna2:9385

Association analysis of psoriasis vulgaris and psoriatic arthritis with loss-of-function mutations in IL36RN in German patients - Loehr, S.; Uebe, Steffen; Behrens, F.; Boehm, B.; Koehm, M.; Traupe, H.; Oji, Vinzenz; Burkhardt, H.; Reis, André; Hüffmeier, Ulrike (British Journal of Dermatology, 2016)
EVALuna2:9335

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study - Haycock, Philip C.; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N.; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J.; Evans, David M.; Willeit, Peter; Aviv, Abraham; Gaunt, Tomr.; et al. (JAMA Oncology, 2017)
The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation.To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases.Genomewide association studies (GWAS) published up to January 15, 2015.GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available.Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population.Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation.Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]).It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
EVALuna2:9371

Association of genetic and psychological factors with persistent pain after cosmetic thoracic surgery - Dimova, Violeta; Loetsch, Joern; Hühne, Kathrin; Winterpacht, Andreas; Heesen, Michael; Parthum, Andreas; Weber, Peter G.; Carbon, Roman; Grießinger, Norbert; Sittl, Reinhard; Lautenbacher, Stefan (Journal of Pain Research, 2015)
The genetic control of pain has been repeatedly demonstrated in human association studies. In the present study, we assessed the relative contribution of 16 single nucleotide polymorphisms in pain-related genes, such as cathechol-O-methyl transferase gene (COMT), fatty acid amino hydrolase gene (FAAH), transient receptor potential cation channel, subfamily V, member 1 gene (TRPV1), and ?-opioid receptor gene (OPRD1), for postsurgical pain chronification. Ninety preoperatively pain-free male patients were assigned to good or poor outcome groups according to their intensity or disability score assessed at 1 week, 3 months, 6 months, and 1 year after funnel chest correction. The genetic effects were compared with those of two psychological predictors, the attentional bias toward positive words (dot-probe task) and the self-reported pain vigilance (Pain Vigilance and Awareness Questionnaire [PVAQ]), which were already shown to be the best predictors for pain intensity and disability at 6 months after surgery in the same sample, respectively. Cox regression analyses revealed no significant effects of any of the genetic predictors up to the end point of survival time at 1 year after surgery. Adding the genetics to the prediction by the attentional bias to positive words for pain intensity and the PVAQ for pain disability, again no significant additional explanation could be gained by the genetic predictors. In contrast, the preoperative PVAQ score was also, in the present enlarged sample, a meaningful predictor for lasting pain disability after surgery. Effect size measures suggested some genetic variables, for example, the polymorphism rs1800587G>A in the interleukin 1 alpha gene (IL1A) and the COMT haplotype rs4646312T>C/rs165722T>C/rs6269A>G/rs4633T>C/rs4818C>G/rs4680A>G, as possible relevant modulators of long-term postsurgical pain outcome. A comparison between pathophysiologically different predictor groups appears to be helpful in identifying clinically relevant predictors of chronic pain.
EVALuna2:9288

Association of genomic variants at the human leukocyte antigen locus with cervical cancer risk,HPVstatus and gene expression levels - Ramachandran, Dhanya; Schuermann, Peter; Mao, Qianqian; Wang, Yingying; Bretschneider, Lisa-Marie; Speith, Lisa-Marie; Huelse, Fabienne; Enssen, Julia; Bousset, Kristine; Jentschke, Matthias; Boehmer, Gerd; Strauss, Hans-Georg; et al. (International Journal of Cancer, 2020)
The human leukocyte antigen (HLA) locus on chromosome 6 has been reported to be associated with cervical cancer. We investigated two independent single-nucleotide polymorphisms in a large case-control series of cervical dysplasia and carcinoma that has been newly established by the German Cervigen Consortium, comprising a total of 2481 cases and 1556 healthy females. We find significant associations for both variants, rs9272117 atHLA-DQA1and rs2844511 atMICAandHCP5, with cervical disease. Both variants showed evidence of association with invasive cervical cancer (rs9272117: OR 0.89, 95% CI 0.79-0.99,P= .036; rs2844511: OR 1.17, 95% CI 1.04-1.31,P= .008) and with high-grade dysplasia (rs9272117: OR 0.78, 95% CI 0.70-0.87,P= 7.1 x 10(-6); rs2844511: OR 1.13, 95% CI 1.01-1.26,P= .035), as well as in a combined analysis of both groups (rs9272117: OR 0.83, 95% CI 0.75-0.91,P= 6.9 x 10(-5); rs2844511: OR 1.14, 95% CI 1.04-1.26,P= .005). Variant rs2844511, but not rs9272117, also showed modest evidence of association with low-grade dysplasia (OR 1.26, 95% CI 1.04-1.54,P= .019). In case-only analyses, rs2844511 tended to predict HPV status (P= .044) and rs9272117 tended to associate with HPV16 (P= .022). RNA studies in cervical samples showed a significant correlation in the transcript levels ofMICA,HCP5andHLA-DQA1, suggesting extensive co-regulation. All three genes were upregulated in HPV16-positive samples. In stratified analyses, rs9272117 was associated withHLA-DQA1levels, specifically in HPV-positive samples, while rs2844511 was associated withMICAandHCP5levels. The risk allele of rs2844511 was required for correlations betweenMICAorHCP5withHLA-DQA1. Altogether, our results support 6p21.32-33 as the first consistent cervical cancer susceptibility locus and provide evidence for a link between genetic risk variants, HPV16 status and transcript levels ofHLA-DQA1,HCP5andMICA, which may contribute to tumor immune evasion.
CRIS-Team WoS Importer:2020-07-24

Association of germline genetic variants with breast cancer-specific survival in patient subgroups defined by clinic-pathological variables related to tumor biology and type of systemic treatment - Morra, Anna; Escala-Garcia, Maria; Beesley, Jonathan; Keeman, Renske; Canisius, Sander; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Auer, Paul L.; Augustinsson, Annelie; Freeman, Laura E. Beane; et al. (BREAST CANCER RES, 2021)
Background Given the high heterogeneity among breast tumors, associations between common germline genetic variants and survival that may exist within specific subgroups could go undetected in an unstratified set of breast cancer patients. Methods We performed genome-wide association analyses within 15 subgroups of breast cancer patients based on prognostic factors, including hormone receptors, tumor grade, age, and type of systemic treatment. Analyses were based on 91,686 female patients of European ancestry from the Breast Cancer Association Consortium, including 7531 breast cancer-specific deaths over a median follow-up of 8.1 years. Cox regression was used to assess associations of common germline variants with 15-year and 5-year breast cancer-specific survival. We assessed the probability of these associations being true positives via the Bayesian false discovery probability (BFDP < 0.15). Results Evidence of associations with breast cancer-specific survival was observed in three patient subgroups, with variant rs5934618 in patients with grade 3 tumors (15-year-hazard ratio (HR) [95% confidence interval (CI)] 1.32 [1.20, 1.45], P = 1.4E-08, BFDP = 0.01, per G allele); variant rs4679741 in patients with ER-positive tumors treated with endocrine therapy (15-year-HR [95% CI] 1.18 [1.11, 1.26], P = 1.6E-07, BFDP = 0.09, per G allele); variants rs1106333 (15-year-HR [95% CI] 1.68 [1.39,2.03], P = 5.6E-08, BFDP = 0.12, per A allele) and rs78754389 (5-year-HR [95% CI] 1.79 [1.46,2.20], P = 1.7E-08, BFDP = 0.07, per A allele), in patients with ER-negative tumors treated with chemotherapy. Conclusions We found evidence of four loci associated with breast cancer-specific survival within three patient subgroups. There was limited evidence for the existence of associations in other patient subgroups. However, the power for many subgroups is limited due to the low number of events. Even so, our results suggest that the impact of common germline genetic variants on breast cancer-specific survival might be limited.
CRIS-Team WoS Importer:2021-09-03

Association of mineral and bone biomarkers with adverse cardiovascular outcomes and mortality in the German Chronic Kidney Disease (GCKD) cohort - Reimer, Katharina Charlotte; Nadal, Jennifer; Meiselbach, Heike; Schmid, Matthias; Schultheiss, Ulla T.; Kotsis, Fruzsina; Stockmann, Helena; Friedrich, Nele; Nauck, Matthias; Krane, Vera; Eckardt, Kai-Uwe; Schneider, Markus; et al. (Bone Research, 2023)
Mineral and bone disorder (MBD) in chronic kidney disease (CKD) is tightly linked to cardiovascular disease (CVD). In this study, we aimed to compare the prognostic value of nine MBD biomarkers to determine those associated best with adverse cardiovascular (CV) outcomes and mortality. In 5 217 participants of the German CKD (GCKD) study enrolled with an estimated glomerular filtration rate (eGFR) between 30–60 mL·min−1 per 1.73 m2 or overt proteinuria, serum osteoprotegerin (OPG), C-terminal fibroblast growth factor-23 (FGF23), intact parathyroid hormone (iPTH), bone alkaline phosphatase (BAP), cross-linked C-telopeptide of type 1 collagen (CTX1), procollagen 1 intact N-terminal propeptide (P1NP), phosphate, calcium, and 25-OH vitamin D were measured at baseline. Participants with missing values among these parameters (n = 971) were excluded, leaving a total of 4 246 participants for analysis. During a median follow-up of 6.5 years, 387 non-CV deaths, 173 CV deaths, 645 nonfatal major adverse CV events (MACEs) and 368 hospitalizations for congestive heart failure (CHF) were observed. OPG and FGF23 were associated with all outcomes, with the highest hazard ratios (HRs) for OPG. In the final Cox regression model, adjusted for CV risk factors, including kidney function and all other investigated biomarkers, each standard deviation increase in OPG was associated with non-CV death (HR 1.76, 95% CI: 1.35–2.30), CV death (HR 2.18, 95% CI: 1.50–3.16), MACE (HR 1.38, 95% CI: 1.12–1.71) and hospitalization for CHF (HR 2.05, 95% CI: 1.56–2.69). Out of the nine biomarkers examined, stratification based on serum OPG best identified the CKD patients who were at the highest risk for any adverse CV outcome and mortality.
CRIS-Team Scopus Importer:2023-11-10

Association of Rare CYP39A1 Variants with Exfoliation Syndrome Involving the Anterior Chamber of the Eye - Li, Zheng; Wang, Zhenxun; Lee, Mei Chin; Zenkel, Matthias; Peh, Esther; Ozaki, Mineo; Topouzis, Fotis; Nakano, Satoko; Chan, Anita; Chen, Shuwen; Williams, Susan E.I.; Orr, Andrew; et al. (Journal of the American Medical Association, 2021)
Importance: Exfoliation syndrome is a systemic disorder characterized by progressive accumulation of abnormal fibrillar protein aggregates manifesting clinically in the anterior chamber of the eye. This disorder is the most commonly known cause of glaucoma and a major cause of irreversible blindness. Objective: To determine if exfoliation syndrome is associated with rare, protein-changing variants predicted to impair protein function. Design, Setting, and Participants: A 2-stage, case-control, whole-exome sequencing association study with a discovery cohort and 2 independently ascertained validation cohorts. Study participants from 14 countries were enrolled between February 1999 and December 2019. The date of last clinical follow-up was December 2019. Affected individuals had exfoliation material on anterior segment structures of at least 1 eye as visualized by slit lamp examination. Unaffected individuals had no signs of exfoliation syndrome. Exposures: Rare, coding-sequence genetic variants predicted to be damaging by bioinformatic algorithms trained to recognize alterations that impair protein function. Main Outcomes and Measures: The primary outcome was the presence of exfoliation syndrome. Exome-wide significance for detected variants was defined as P < 2.5 × 10-6. The secondary outcomes included biochemical enzymatic assays and gene expression analyses. Results: The discovery cohort included 4028 participants with exfoliation syndrome (median age, 78 years [interquartile range, 73-83 years]; 2377 [59.0%] women) and 5638 participants without exfoliation syndrome (median age, 72 years [interquartile range, 65-78 years]; 3159 [56.0%] women). In the discovery cohort, persons with exfoliation syndrome, compared with those without exfoliation syndrome, were significantly more likely to carry damaging CYP39A1 variants (1.3% vs 0.30%, respectively; odds ratio, 3.55 [95% CI, 2.07-6.10]; P = 6.1 × 10-7). This outcome was validated in 2 independent cohorts. The first validation cohort included 2337 individuals with exfoliation syndrome (median age, 74 years; 1132 women; n = 1934 with demographic data) and 2813 individuals without exfoliation syndrome (median age, 72 years; 1287 women; n = 2421 with demographic data). The second validation cohort included 1663 individuals with exfoliation syndrome (median age, 75 years; 587 women; n = 1064 with demographic data) and 3962 individuals without exfoliation syndrome (median age, 74 years; 951 women; n = 1555 with demographic data). Of the individuals from both validation cohorts, 5.2% with exfoliation syndrome carried CYP39A1 damaging alleles vs 3.1% without exfoliation syndrome (odds ratio, 1.82 [95% CI, 1.47-2.26]; P <.001). Biochemical assays classified 34 of 42 damaging CYP39A1 alleles as functionally deficient (median reduction in enzymatic activity compared with wild-type CYP39A1, 94.4% [interquartile range, 78.7%-98.2%] for the 34 deficient variants). CYP39A1 transcript expression was 47% lower (95% CI, 30%-64% lower; P <.001) in ciliary body tissues from individuals with exfoliation syndrome compared with individuals without exfoliation syndrome. Conclusions and Relevance: In this whole-exome sequencing case-control study, presence of exfoliation syndrome was significantly associated with carriage of functionally deficient CYP39A1 sequence variants. Further research is needed to understand the clinical implications of these findings.
CRIS-Team Scopus Importer:2021-03-05

Associations between genetic risk variants for kidney diseases and kidney disease etiology - Wunnenburger, Sebastian; Schultheiss, Ulla T.; Walz, Gerd; Hausknecht, Birgit; Ekici, Arif Bülent; Kronenberg, Florian; Eckardt, Kai-Uwe; Kottgen, Anna; Wuttke, Matthias (Scientific Reports, 2017)
Chronic kidney disease (CKD) is a global health problem with a genetic component. Genome-wide association studies have identified variants associated with specific CKD etiologies, but their genetic overlap has not been well studied. This study examined SNP associations across different CKD etiologies and CKD stages using data from 5,034 CKD patients of the German Chronic Kidney Disease study. In addition to confirming known associations, a systemic lupus erythematosus-associated risk variant at TNXB was also associated with CKD attributed to type 1 diabetes (p = 2.5 × 10(-)(7)), a membranous nephropathy-associated variant at HLA-DQA1 was also associated with CKD attributed to systemic lupus erythematosus (p = 5.9 × 10(-)(6)), and an IgA risk variant at HLA-DRB1 was associated with both CKD attributed to granulomatosis with polyangiitis (p = 2.0 × 10(-4)) and to type 1 diabetes (p = 4.6 × 10(-11)). Associations were independent of additional risk variants in the respective genetic regions. Evaluation of CKD stage showed a significant association of the UMOD risk variant, previously identified in population-based studies for association with kidney function, for advanced (stage >=G3b) compared to early-stage CKD (<=stage G2). Shared genetic associations across CKD etiologies and stages highlight the role of the immune response in CKD. Association studies with detailed information on CKD etiology can reveal shared genetic risk variants.
EVALuna2:4033

Astrogenesis in the murine dentate gyrus is a life-long and dynamic process - Schneider, Julia; Weigel, Johannes; Wittmann, Marie-Theres; Svehla, Pavel; Ehrt, Sebastian; Zheng, Fang; Elmzzahi, Tarek; Karpf, Julian; Paniagua-Herranz, Lucia; Basak, Onur; Ekici, Arif Bülent; Wiesmann da Silva Reis, André; et al. (EMBO Journal, 2022)
Astrocytes are highly abundant in the mammalian brain, and their functions are of vital importance for all aspects of development, adaption, and aging of the central nervous system (CNS). Mounting evidence indicates the important contributions of astrocytes to a wide range of neuropathies. Still, our understanding of astrocyte development significantly lags behind that of other CNS cells. We here combine immunohistochemical approaches with genetic fate-mapping, behavioral paradigms, single-cell transcriptomics, and in vivo two-photon imaging, to comprehensively assess the generation and the proliferation of astrocytes in the dentate gyrus (DG) across the life span of a mouse. Astrogenesis in the DG is initiated by radial glia-like neural stem cells giving rise to locally dividing astrocytes that enlarge the astrocyte compartment in an outside-in-pattern. Also in the adult DG, the vast majority of astrogenesis is mediated through the proliferation of local astrocytes. Interestingly, locally dividing astrocytes were able to adapt their proliferation to environmental and behavioral stimuli revealing an unexpected plasticity. Our study establishes astrocytes as enduring plastic elements in DG circuits, implicating a vital contribution of astrocyte dynamics to hippocampal plasticity.
CRIS-Team WoS Importer:2022-04-29

A syndromic neurodevelopmental disorder caused by rare variants in PPFIA3 - Paul, Maimuna S.; Michener, Sydney L.; Pan, Hongling; Chan, Hiuling; Pfliger, Jessica M.; Rosenfeld, Jill A.; Lerma, Vanesa C.; Tran, Alyssa; Longley, Megan A.; Lewis, Richard A.; Weisz-Hubshman, Monika; Bekheirnia, Mir Reza; et al. (American Journal of Human Genetics, 2024)
PPFIA3 encodes the protein-tyrosine phosphatase, receptor-type, F-polypeptide-interacting-protein-alpha-3 (PPFIA3), which is a member of the LAR-protein-tyrosine phosphatase-interacting-protein (liprin) family involved in synapse formation and function, synaptic vesicle transport, and presynaptic active zone assembly. The protein structure and function are evolutionarily well conserved, but human diseases related to PPFIA3 dysfunction are not yet reported in OMIM. Here, we report 20 individuals with rare PPFIA3 variants (19 heterozygous and 1 compound heterozygous) presenting with developmental delay, intellectual disability, hypotonia, dysmorphisms, microcephaly or macrocephaly, autistic features, and epilepsy with reduced penetrance. Seventeen unique PPFIA3 variants were detected in 18 families. To determine the pathogenicity of PPFIA3 variants in vivo, we generated transgenic fruit flies producing either human wild-type (WT) PPFIA3 or five missense variants using GAL4-UAS targeted gene expression systems. In the fly overexpression assays, we found that the PPFIA3 variants in the region encoding the N-terminal coiled-coil domain exhibited stronger phenotypes compared to those affecting the C-terminal region. In the loss-of-function fly assay, we show that the homozygous loss of fly Liprin-α leads to embryonic lethality. This lethality is partially rescued by the expression of human PPFIA3 WT, suggesting human PPFIA3 function is partially conserved in the fly. However, two of the tested variants failed to rescue the lethality at the larval stage and one variant failed to rescue lethality at the adult stage. Altogether, the human and fruit fly data reveal that the rare PPFIA3 variants are dominant-negative loss-of-function alleles that perturb multiple developmental processes and synapse formation.
CRIS-Team Scopus Importer:2024-01-19
Keywords: active zone protein; fruit flies; Mendelian phenotypes; neurodevelopmental disorder; synaptic protein

Author Correction: A monocyte gene expression signature in the early clinical course of Parkinson’s disease (Scientific Reports, (2018), 8, 1, (10757), 10.1038/s41598-018-28986-7) - Schlachetzki, Johannes; Prots, Iryna; Tao, Jenhan; Chun, Hyun B.; Saijo, Kaoru; Gosselin, David; Winner, Beate; Glass, Christopher K.; Winkler, Jürgen (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-04-17

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

Author Correction: CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language - Blok, Lot Snijders; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance H.; Nowak, Catherine B.; Douglas, Jessica; Swoboda, Kathryn J.; Steeves, Marcie A.; Sahai, Inderneel; et al. (Nature Communications, 2019)
EVALuna2:206986

Autosomal dominant polycystic kidney disease in absence of renal cyst formation illustrates genetic interaction between WT1 and PKD1 - Münch, Johannes; Kirschner, Karin M.; Schlee, Hendrik; Kraus, Cornelia; Schönauer, Ria; Jin, Wenjun; Le Duc, Gabriela Diana; Scholz, Holger; Halbritter, Jan (Journal of Medical Genetics, 2020)
Autosomal dominant polycystic kidney disease (ADPKD), caused by pathogenic variants of either PKD1 or PKD2, is characterised by wide interfamilial and intrafamilial phenotypic variability. This study aimed to determine the molecular basis of marked clinical variability in ADPKD family members and sought to analyse whether alterations of WT1 (Wilms tumour 1), encoding a regulator of gene expression, may have an impact on renal cyst formation. Methods: ADPKD family members underwent clinical and molecular evaluation. Functionally, Pkd1 mRNA and protein expression upon Wt1 knockdown was evaluated in mouse embryonic kidneys and mesonephric M15 cells. Results: By renal gene panel analysis, we identified two pathogenic variants in an individual with maternal history of ADPKD, however, without cystic kidneys but polycystic liver disease: a known PKD1 missense variant (c.8311G>A, p.Glu2771Lys) and a known de novo WT1 splice site variant (c.1432+4C>T). The latter was previously associated with imbalanced +/-KTS isoform ratio of WT1. In ex vivo organ cultures from mouse embryonic kidneys, Wt1 knockdown resulted in decreased Pkd1 expression on mRNA and protein level. Conclusion: While the role of WT1 in glomerulopathies has been well established, this report by illustrating genetic interaction with PKD1 proposes WT1 as potential modifier in ADPKD.
CRIS-Team Scopus Importer:2020-06-02
Keywords: clinical genetics; liver disease; renal medicine

Autosomal-Recessive Intellectual Disability with Cerebellar Atrophy Syndrome Caused by Mutation of the Manganese and Zinc Transporter Gene SLC39A8 - Boycott, Kym M.; Beaulieu, Chandree L.; Kernohan, Kristin D.; Gebril, Ola H.; Mhanni, Aziz; Chudley, Albert E.; Redl, David; Qin, Wen; Hampson, Sarah; Kuery, Sebastien; Tetreault, Martine; Puffenberger, Erik G.; et al. (American Journal of Human Genetics, 2015)
Manganese (Mn) and zinc (Zn) are essential divalent cations used by cells as protein cofactors; various human studies and animal models have demonstrated the importance of Mn and Zn for development. Here we describe an autosomal-recessive disorder in six individuals from the Hutterite community and in an unrelated Egyptian sibpair; the disorder is characterized by intellectual disability, developmental delay, hypotonia, strabismus, cerebellar atrophy, and variable short stature. Exome sequencing in one affected Hutterite individual and the Egyptian family identified the same homozygous variant, c.112G>C (p.Gly38Arg), affecting a conserved residue of SLC39A8. The affected Hutterite and Egyptian individuals did not share an extended common haplotype, suggesting that the mutation arose independently. SLC39A8 is a member of the solute carrier gene family known to import Mn, Zn, and other divalent cations across the plasma membrane. Evaluation of these two metal ions in the affected individuals revealed variably low levels of Mn and Zn in blood and elevated levels in urine, indicating renal wasting. Our findings identify a human Mn and Zn transporter deficiency syndrome linked to SLC39A8, providing insight into the roles of Mn and Zn homeostasis in human health and development.
EVALuna2:9292

Autosomal-Recessive Mutations in the tRNA Splicing Endonuclease Subunit TSEN15 Cause Pontocerebellar Hypoplasia and Progressive Microcephaly - Breuss, Martin W.; Sultan, Tipu; James, Kiely N.; Rosti, Rasim O.; Scott, Eric; Musaev, Damir; Furia, Bansri; Reis, André; Sticht, Heinrich; Al-Owain, Mohammed; Alkuraya, Fowzan S.; Reuter, Miriam; et al. (American Journal of Human Genetics, 2016)
The tRNA splicing endonuclease is a highly evolutionarily conserved protein complex, involved in the cleavage of intron-containing tRNAs. In human it consists of the catalytic subunits TSEN2 and TSEN34, as well as the non-catalytic TSEN54 and TSEN15. Recessive mutations in the corresponding genes of the first three are known to cause pontocerebellar hypoplasia (PCH) types 2A-C, 4, and 5. Here, we report three homozygous TSEN15 variants that cause a milder version of PCH2. The affected individuals showed progressive microcephaly, delayed developmental milestones, intellectual disability, and, in two out of four cases, epilepsy. None, however, displayed the central visual failure seen in PCH case subjects where other subunits of the TSEN are mutated, and only one was affected by the extensive motor defects that are typical in other forms of PCH2. The three amino acid substitutions impacted the protein level of TSEN15 and the stoichiometry of the interacting subunits in different ways, but all resulted in an almost complete loss of in vitro tRNA cleavage activity. Taken together, our results demonstrate that mutations in any known subunit of the TSEN complex can cause PCH and progressive microcephaly, emphasizing the importance of its function during brain development.
EVALuna2:9333

Autosomal recessive Noonan syndrome associated with biallelic LZTR1 variants - Johnston, Jennifer J.; Van Der Smagt, Jasper J.; Rosenfeld, Jill A.; Pagnamenta, Alistair T.; Alswaid, Abdulrahman; Baker, Eva H.; Blair, Edward; Borck, Guntram; Brinkmann, Julia; Craigen, William; Vu Chi Dung,; Emrick, Lisa; et al. (Genetics in Medicine, 2018)
PurposeTo characterize the molecular genetics of autosomal recessive Noonan syndrome.MethodsFamilies underwent phenotyping for features of Noonan syndrome in children and their parents. Two multiplex families underwent linkage analysis. Exome, genome, or multigene panel sequencing was used to identify variants. The molecular consequences of observed splice variants were evaluated by reverse-transcription polymerase chain reaction.ResultsTwelve families with a total of 23 affected children with features of Noonan syndrome were evaluated. The phenotypic range included mildly affected patients, but it was lethal in some, with cardiac disease and leukemia. All of the parents were unaffected. Linkage analysis using a recessive model supported a candidate region in chromosome 22q11, which includes LZTR1, previously shown to harbor mutations in patients with Noonan syndrome inherited in a dominant pattern. Sequencing analyses of 21 live-born patients and a stillbirth identified biallelic pathogenic variants in LZTR1, including putative loss-of-function, missense, and canonical and noncanonical splicing variants in the affected children, with heterozygous, clinically unaffected parents and heterozygous or normal genotypes in unaffected siblings.ConclusionThese clinical and genetic data confirm the existence of a form of Noonan syndrome that is inherited in an autosomal recessive pattern and identify biallelic mutations in LZTR1.Genet Med advance online publication, 22 February 2018; doi:10.1038/gim.2017.249.
EVALuna2:34635

Axon-Specific Mitochondrial Pathology in SPG11 Alpha Motor Neurons - Güner, Fabian; Pozner, Tatyana; Krach, Florian; Prots, Iryna; Loskarn, Sandra; Schlötzer-Schrehardt, Ursula; Winkler, Jürgen; Winner, Beate; Regensburger, Martin (Frontiers in Neuroscience, 2021)
Pathogenic variants in SPG11 are the most frequent cause of autosomal recessive complicated hereditary spastic paraplegia (HSP). In addition to spastic paraplegia caused by corticospinal degeneration, most patients are significantly affected by progressive weakness and muscle wasting due to alpha motor neuron (MN) degeneration. Mitochondria play a crucial role in neuronal health, and mitochondrial deficits were reported in other types of HSPs. To investigate whether mitochondrial pathology is present in SPG11, we differentiated MNs from induced pluripotent stem cells derived from SPG11 patients and controls. MN derived from human embryonic stem cells and an isogenic SPG11 knockout line were also included in the study. Morphological analysis of mitochondria in the MN soma versus neurites revealed specific alterations of mitochondrial morphology within SPG11 neurites, but not within the soma. In addition, impaired mitochondrial membrane potential was indicative of mitochondrial dysfunction. Moreover, we reveal neuritic aggregates further supporting neurite pathology in SPG11. Correspondingly, using a microfluidic-based MN culture system, we demonstrate that axonal mitochondrial transport was significantly impaired in SPG11. Overall, our data demonstrate that alterations in morphology, function, and transport of mitochondria are an important feature of axonal dysfunction in SPG11 MNs.
CRIS-Team Scopus Importer:2021-08-06
Keywords: SPG11; alpha motor neuron; axonal transport; hereditary spastic paraplegia; induced pluripotent stem cells; mitochondria

Bainbridge-Ropers syndrome caused by loss-of-function variants in ASXL3: a recognizable condition - Kuechler, Alma; Czeschik, Johanna Christina; Graf, Elisabeth; Grasshoff, Ute; Hüffmeier, Ulrike; Busa, Tiffany; Beck-Woedl, Stefanie; Faivre, Laurence; Riviere, Jean-Baptiste; Bader, Ingrid; Koch, Johannes; Reis, André; et al. (European journal of human genetics, 2016)
Truncating ASXL3 mutations were first identified in 2013 by Bainbridge et al. as a cause of syndromic intellectual disability in four children with similar phenotypes using whole-exome sequencing. The clinical features - postulated by Bainbridge et al. to be overlapping with Bohring-Opitz syndrome - were developmental delay, severe feeding difficulties, failure to thrive and neurological abnormalities. This condition was included in OMIM as 'Bainbridge-Ropers syndrome' (BRPS, #615485). To date, a total of nine individuals with BRPS have been published in the literature in four reports (Bainbridge et al., Dinwiddie et al, Srivastava et al. and Hori et al.). In this report, we describe six unrelated patients with newly diagnosed heterozygous de novo loss-of-function variants in ASXL3 and concordant clinical features: severe muscular hypotonia with feeding difficulties in infancy, significant motor delay, profound speech impairment, intellectual disability and a characteristic craniofacial phenotype (long face, arched eyebrows with mild synophrys, downslanting palpebral fissures, prominent columella, small alae nasi, high, narrow palate and relatively little facial expression). The majority of key features characteristic for Bohring-Opitz syndrome were absent in our patients (eg, the typical posture of arms, intrauterine growth retardation, microcephaly, trigonocephaly, typical facial gestalt with nevus flammeus of the forehead and exophthalmos). Therefore we emphasize that BRPS syndrome, caused by ASXL3 loss-of-function variants, is a clinically distinct intellectual disability syndrome with a recognizable phenotype distinguishable from that of Bohring-Opitz syndrome.European Journal of Human Genetics advance online publication, 30 November 2016; doi:10.1038/ejhg.2016.165.
EVALuna2:9349

BCL11A intellectual developmental disorder: defining the clinical spectrum and genotype-phenotype correlations - Peron, Angela; D’Arco, Felice; Aldinger, Kimberly A.; Smith-Hicks, Constance; Zweier, Christiane; Gradek, Gyri A.; Bradbury, Kimberley; Accogli, Andrea; Andersen, Erica F.; Au, Ping Yee Billie; Battini, Roberta; Beleford, Daniah; et al. (European Journal of Human Genetics, 2024)
An increasing number of individuals with intellectual developmental disorder (IDD) and heterozygous variants in BCL11A are identified, yet our knowledge of manifestations and mutational spectrum is lacking. To address this, we performed detailed analysis of 42 individuals with BCL11A-related IDD (BCL11A-IDD, a.k.a. Dias-Logan syndrome) ascertained through an international collaborative network, and reviewed 35 additional previously reported patients. Analysis of 77 affected individuals identified 60 unique disease-causing variants (30 frameshift, 7 missense, 6 splice-site, 17 stop-gain) and 8 unique BCL11A microdeletions. We define the most prevalent features of BCL11A-IDD: IDD, postnatal-onset microcephaly, hypotonia, behavioral abnormalities, autism spectrum disorder, and persistence of fetal hemoglobin (HbF), and identify autonomic dysregulation as new feature. BCL11A-IDD is distinguished from 2p16 microdeletion syndrome, which has a higher incidence of congenital anomalies. Our results underscore BCL11A as an important transcription factor in human hindbrain development, identifying a previously underrecognized phenotype of a small brainstem with a reduced pons/medulla ratio. Genotype-phenotype correlation revealed an isoform-dependent trend in severity of truncating variants: those affecting all isoforms are associated with higher frequency of hypotonia, and those affecting the long (BCL11A-L) and extra-long (-XL) isoforms, sparing the short (-S), are associated with higher frequency of postnatal microcephaly. With the largest international cohort to date, this study highlights persistence of fetal hemoglobin as a consistent biomarker and hindbrain abnormalities as a common feature. It contributes significantly to our understanding of BCL11A-IDD through an extensive unbiased multi-center assessment, providing valuable insights for diagnosis, management and counselling, and into BCL11A’s role in brain development.
CRIS-Team Scopus Importer:2024-11-08

BDV Syndrome: An Emerging Syndrome with Profound Obesity and Neurodevelopmental Delay Resembling Prader-Willi Syndrome - Bosch, Elisabeth; Hebebrand, Moritz; Popp, Bernt; Penger, Theresa; Behring, Bettina; Cox, Helen; Towner, Shelley; Kraus, Cornelia; Wilson, William G.; Khan, Shagufta; Krumbiegel, Mandy; Ekici, Arif Bülent; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: CPE encodes carboxypeptidase E, an enzyme that converts proneuropeptides and propeptide hormones to bioactive forms. It is widely expressed in the endocrine and central nervous system. To date, 4 individuals from 2 families with core clinical features including morbid obesity, neurodevelopmental delay, and hypogonadotropic hypogonadism, harboring biallelic loss-of-function (LoF) CPE variants, have been reported. Objective: We describe 4 affected individuals from 3 unrelated consanguineous families, 2 siblings of Syrian, 1 of Egyptian, and 1 of Pakistani descent, all harboring novel homozygous CPE LoF variants. Methods: After excluding Prader-Willi syndrome (PWS), exome sequencing was performed in both Syrian siblings. The variants identified in the other 2 individuals were reported as research variants in a large-scale exome study and in the ClinVar database. Computational modeling of all possible missense alterations allowed assessing CPE tolerance to missense variants. Results: All affected individuals were severely obese with neurodevelopmental delay and other endocrine anomalies. Three individuals from 2 families shared the same CPE homozygous truncating variant c.361Câ€ >â€ T, p.(Arg121∗), while the fourth carried the c.994del, p.(Ser333Alafs∗22) variant. Comparison of clinical features with previously described cases and standardization according to the Human Phenotype Ontology terms indicated a recognizable clinical phenotype, which we termed Blakemore-Durmaz-Vasileiou (BDV) syndrome. Computational analysis indicated high conservation of CPE domains and intolerance to missense changes. Conclusion: Biallelic truncating CPE variants are associated with BDV syndrome, a clinically recognizable monogenic recessive syndrome with childhood-onset obesity, neurodevelopmental delay, hypogonadotropic hypogonadism, and hypothyroidism. BDV syndrome resembles PWS. Our findings suggest missense variants may also be clinically relevant.
CRIS-Team Scopus Importer:2021-12-24
Keywords: BDV syndrome; carboxypeptidase E; CPE; hypogonadotropic hypogonadism; neurodevelopmental disorder; obesity

Benchmarking whole exome sequencing in the German network for personalized medicine - Menzel, Michael; Martis-Thiele, Mihaela; Goldschmid, Hannah; Ott, Alexander; Romanovsky, Eva; Siemanowski-Hrach, Janna; Seillier, Lancelot; Brüchle, Nadina Ortiz; Maurer, Angela; Lehmann, Kjong Van; Begemann, Matthias; Elbracht, Miriam; et al. (European Journal of Cancer, 2024)
Introduction: Whole Exome Sequencing (WES) has emerged as an efficient tool in clinical cancer diagnostics to broaden the scope from panel-based diagnostics to screening of all genes and enabling robust determination of complex biomarkers in a single analysis. Methods: To assess concordance, six formalin-fixed paraffin-embedded (FFPE) tissue specimens and four commercial reference standards were analyzed by WES as matched tumor-normal DNA at 21 NGS centers in Germany, each employing local wet-lab and bioinformatics. Somatic and germline variants, copy-number alterations (CNAs), and complex biomarkers were investigated. Somatic variant calling was performed in 494 diagnostically relevant cancer genes. The raw data were collected and re-analyzed with a central bioinformatic pipeline to separate wet- and dry-lab variability. Results: The mean positive percentage agreement (PPA) of somatic variant calling was 76 % while the positive predictive value (PPV) was 89 % in relation to a consensus list of variants found by at least five centers. Variant filtering was identified as the main cause for divergent variant calls. Adjusting filter criteria and re-analysis increased the PPA to 88 % for all and 97 % for the clinically relevant variants. CNA calls were concordant for 82 % of genomic regions. Homologous recombination deficiency (HRD), tumor mutational burden (TMB), and microsatellite instability (MSI) status were concordant for 94 %, 93 %, and 93 % of calls, respectively. Variability of CNAs and complex biomarkers did not decrease considerably after harmonization of the bioinformatic processing and was hence attributed mainly to wet-lab differences. Conclusion: Continuous optimization of bioinformatic workflows and participating in round robin tests are recommended.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Clinical exome; Molecular pathology; Multi-centric inter-laboratory test; Precision oncology; Whole exome sequencing

Beyond founder and truncting variants in TECPR2-associated disorder - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Brosse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A.; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Biallelic ANKS6 mutations cause late-onset ciliopathy with chronic kidney disease through YAP dysregulation - Schwarz, Hannah; Popp, Bernt; Airik, Rannar; Torabi Sarijalo, Nasrin; Knaup, Karl; Stoeckert, Johanna; Wiech, Thorsten; Amann, Kerstin Ute; Wiesmann da Silva Reis, André; Schiffer, Mario; Schueler, Markus; Wiesener, Michael (Human Molecular Genetics, 2022)
Nephronophthisis-related ciliopathies (NPHP-RC) comprises a group of inherited kidney diseases, caused by mutations in genes encoding proteins localizing to primary cilia. NPHP-RC represents one of the most frequent monogenic causes of renal failure within the first three decades of life, but its molecular disease mechanisms remain unclear. Here, we identified biallelic ANKS6 mutations in two affected siblings with late-onset chronic kidney disease by whole-exome sequencing. We employed patient-derived fibroblasts generating an in vitro model to study the precise biological impact of distinct human ANKS6 mutations, completed by immunohistochemistry studies on renal biopsy samples. Functional studies using patient-derived cells showed an impaired integrity of the ciliary inversin compartment with reduced cilia length. Further analyses demonstrated that ANKS6 deficiency leads to a dysregulation of Hippo-signaling through nuclear yes-associated protein (YAP) imbalance and disrupted ciliary localization of YAP. In addition, an altered transcriptional activity of canonical Wnt target genes and altered expression of non-phosphorylated (active) beta-catenin and phosphorylated glycogen synthase kinase 3 beta were observed. Upon ciliation, ANKS6 deficiency revealed a deranged subcellular localization and expression of components of the endocytic recycling compartment. Our results demonstrate that ANKS6 plays a key role in regulating the Hippo pathway, and ANKS6 deficiency is linked to dysregulation of signaling pathways. Our study provides molecular clues in understanding pathophysiological mechanisms of NPHP-RC and may offer new therapeutic targets.
CRIS-Team WoS Importer:2022-05-13

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

Biallelic intragenic deletion in MASP1 in an adult female with 3MC syndrome - Graul-Neumann, Luitgard M.; Mensah, Martin A.; Klopocki, Eva; Uebe, Steffen; Ekici, Arif Bülent; Thiel, Christian; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2018)
3MC syndrome is a rare autosomal recessive disorder with characteristic craniofacial dysmorphism and multiple anomalies. It is caused by biallelic mutations in one of three genes, MASP1, COLEC11 and COLEC10, all encoding factors of the lectin complement pathway. In MASP1, either truncating mutations or missense variants in exon 12 encoding the C-terminal serine protease domain specific for isoform MASP-3 are causative. By trio exome sequencing we now identified a novel, homozygous 2kb deletion, partially affecting exon 12 in an adult female with the typical facial gestalt of 3MC syndrome and hearing loss, but without the main feature cleft lip/palate, and without intellectual disability, or short stature. We therefore expand the MASP1 associated mutational and clinical spectrum and describe the development of her clinical presentation over a period of 21 years. As the homozygous deletion in our patient was only found by thorough and visual evaluation of the whole exome sequencing data, such deletions might escape detection in some routine diagnostic workflows and might explain a few of the so far molecularly unconfirmed cases of 3MC syndrome.
EVALuna2:34626

Biallelic SEMA3A defects cause a novel type of syndromic short stature - Hofmann, Kristin; Zweier, Markus; Sticht, Heinrich; Zweier, Christiane; Wittmann, Wolfgang; Hoyer, Juliane; Uebe, Steffen; Van Haeringen, Arie; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Rauch, Anita (American Journal of Medical Genetics Part A, 2013)
Chromosomal microarray testing is commonly used to identify disease causing de novo copy number variants in patients with developmental delay and multiple congenital anomalies. In such a patient we now observed an 150 kb deletion on chromosome 7q21.11 affecting the first exon of the axon guidance molecule gene SEMA3A (sema domain, immunoglobulin domain (Ig), short basic domain, secreted, (semaphorin) 3A). This deletion was inherited from the healthy father, but considering the function of SEMA3A and phenotypic similarity to the knock-out mice, we still assumed a pathogenic relevance and tested for a recessive second defect. Sequencing of SEMA3A in the patient indeed revealed the de novo in-frame mutation p.Phe316_Lys317delinsThrSerSerAsnGlu. Cloning of the mutated allele in combination with two informative SNPs confirmed compound heterozygosity in the patient. While the altered protein structure was predicted to be benign, aberrant splicing resulting in a premature stop codon was proven by RT-PCR to occur in about half of the transcripts from this allele. Expression profiling in human fetal and adult cDNA panels, confirmed a high expression of SEMA3A in all brain regions as well as in adult and fetal heart and fetal skeletal muscle. Normal intellectual development in the patient was surprising but may be explained by the remaining 20% of SEMA3A expression level demonstrated by quantitative RT-PCR. We therefore report a novel autosomal recessive syndrome characterized by postnatal short stature with relative macrocephaly, camptodactyly, septal heart defect and several minor anomalies caused by biallelic mutations in SEMA3A.
EVALuna2:9194

Biallelic variants in GTF3C3 result in an autosomal recessive disorder with intellectual disability. - De Hayr, Lachlan; Blok, Laura E.R.; Dias, Kerith Rae; Long, Jingyi; Begemann, Anaïs; Moir, Robyn D.; Willis, Ian M.; Mocera, Martina; Siegel, Gabriele; Steindl, Katharina; Evans, Carey Anne; Zhu, Ying; et al. (Genetics in Medicine, 2025)
PURPOSE: This study details a novel syndromic form of autosomal recessive intellectual disability resulting from recessive variants in GTF3C3, encoding a key component of the DNA-binding transcription factor IIIC, which has a conserved role in RNA polymerase III-mediated transcription. METHODS: Exome sequencing, minigene analysis, molecular modeling, RNA polymerase III reporter gene assays, and Drosophila knockdown models were utilized to characterize GTF3C3 variants. RESULTS: Twelve affected individuals from 7 unrelated families were identified with homozygous or compound heterozygous missense variants in GTF3C3 including c.503C>T p.(Ala168Val), c.1268T>C p.(Leu423Pro), c.1436A>G p.(Tyr479Cys), c.2419C>T p.(Arg807Cys), and c.2420G>A p.(Arg807His). The cohort presented with intellectual disability, variable nonfamilial facial features, motor impairments, seizures, and cerebellar/corpus callosum malformations. Consistent with disruptions in intra- and intermolecular interactions observed in molecular modeling, RNA polymerase III reporter assays confirmed that the majority of missense variants resulted in a loss of function. Minigene analysis of the recurrent c.503C>T p.(Ala168Val) variant confirmed the introduction of a cryptic donor site into exon 4, resulting in mRNA missplicing. Consistent with the clinical features of this cohort, neuronal loss of Gtf3c3 in Drosophila induced seizure-like behavior, motor impairment, and learning deficits. CONCLUSION: These findings confirm that GTF3C3 variants result in an autosomal recessive form of syndromic intellectual disability.
EVALuna2:585156

Bi-allelic Variants in METTL5 Cause Autosomal-Recessive Intellectual Disability and Microcephaly - Richard, Elodie M.; Polla, Daniel L.; Assir, Muhammad Zaman; Contreras, Minerva; Shahzad, Mohsin; Khan, Asma A.; Razzaq, Attia; Akram, Javed; Tarar, Moazzam N.; Blanpied, Thomas A.; Ahmed, Zubair M.; Abou Jamra, Rami; et al. (American Journal of Human Genetics, 2019)
Intellectual disability (ID) is a genetically and clinically heterogeneous disorder, characterized by limited cognitive abilities and impaired adaptive behaviors. In recent years, exome sequencing (ES) has been instrumental in deciphering the genetic etiology of ID. Here, through ES of a large cohort of individuals with ID, we identified two bi-allelic frameshift variants in METTL5, c.344_345delGA (p.Arg115Asnfs∗19) and c.571_572delAA (p.Lys191Valfs∗10), in families of Pakistani and Yemenite origin. Both of these variants were segregating with moderate to severe ID, microcephaly, and various facial dysmorphisms, in an autosomal-recessive fashion. METTL5 is a member of the methyltransferase-like protein family, which encompasses proteins with a seven-beta-strand methyltransferase domain. We found METTL5 expression in various substructures of rodent and human brains and METTL5 protein to be enriched in the nucleus and synapses of the hippocampal neurons. Functional studies of these truncating variants in transiently transfected orthologous cells and cultured hippocampal rat neurons revealed no effect on the localization of METTL5 but alter its level of expression. Our in silico analysis and 3D modeling simulation predict disruption of METTL5 function by both variants. Finally, mettl5 knockdown in zebrafish resulted in microcephaly, recapitulating the human phenotype. This study provides evidence that biallelic variants in METTL5 cause ID and microcephaly in humans and highlights the essential role of METTL5 in brain development and neuronal function.
CRIS-Team Scopus Importer:2019-10-08
Keywords: autosomal recessive intellectual disability; facial dysmorphism; intellectual disability; m6A methyltransferase; METTL5; microcephaly; zebrafish

Blockade of the CD47/SIRPα checkpoint axis potentiates the macrophage-mediated antitumor efficacy of tafasitamab. - Biedermann, Alexander; Patra-Kneuer, Maria; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Mangelberger-Eberl, Doris; Berges, Johannes; Kellner, Christian; Altmeyer, Sarah; Bittenbring, Jörg Thomas; Augsberger, Christian; Ilieva-Babinsky, Kristina; Haskamp, Stefan; et al. (Haematologica, 2024)
Macrophages are one of the key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD19 antibody tafasitamab, approved in combination with lenalidomide for the treatment of relapsed or refractory diffuse large B-cell lymphoma (DLBCL). However, antibody-dependent cellular phagocytosis (ADCP) in the tumor microenvironment can be counteracted by increased expression of the inhibitory receptor SIRPα on macrophages and its ligand, the immune checkpoint molecule CD47, on tumor cells. The aim of this study was to investigate the impact of the CD47-SIRPα axis on tafasitamab- mediated phagocytosis and explore the potential of anti-CD47 blockade to enhance its antitumor activity. Elevated expression of both SIRPα and CD47 was observed in DLBCL patient-derived lymph node biopsies compared to healthy control lymph nodes. CRISPR-mediated CD47 overexpression affected tafasitamab-mediated ADCP in vitro and increased expression of SIRPα on macrophages correlated with decreased ADCP activity of tafasitamab against DLBCL cell lines. A combination of tafasitamab and an anti-CD47 blocking antibody enhanced ADCP activity of in vitro-generated macrophages. Importantly, tafasitamab-mediated phagocytosis was elevated in combination with CD47 blockade using primary DLBCL cells and patient-derived lymphoma-associated macrophages in an autologous setting. Furthermore, lymphoma cells with low CD19 expression were efficiently eliminated by the combination treatment. Finally, combined treatment of tafasitamab and an anti-CD47 antibody resulted in enhanced tumor volume reduction and survival benefit in lymphoma xenograft mouse models. These findings provide evidence that CD47 blockade can enhance the phagocytic potential of tumor-targeting immunotherapies such as tafasitamab and suggest that there is value in exploring the combination in the clinic.
EVALuna2:569373

Blunted transcriptional response to skeletal muscle ischemia in rats with chronic kidney disease: potential role for impaired ischemia-induced angiogenesis - Heiß, Rafael; Fahlbusch, Fabian B.; Jacobi, Johannes; Daniel, Christoph; Ekici, Arif Bülent; Cordasic, Nada; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Hartner, Andrea (Physiological Genomics, 2017)
Chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality. Previous studies indicated an impairment of ischemia-induced angiogenesis in skeletal muscle of rats with CKD. We performed a systematic comparison of early gene expression in response to ischemia in rats with or without CKD to identify potential molecular mechanisms underlying impaired angiogenesis in CKD. CKD was induced in male rats by 5/6 nephrectomy (SNX); control rats were sham operated (sham). Eight weeks later, ischemia of the right limb was induced by ligation and resection of the femoral artery. Rats were sacrificed 24 hours after the onset of ischemia, and RNA was extracted from the musculus soleus of the ischemic and the nonischemic hindlimb. To identify differentially expressed transcripts, RNA was analyzed employing Affymetrix GeneChip Rat Genome 230 2.0 Arrays. RT-PCR analysis of selected genes was performed to validate observed changes. Hindlimb ischemia up-regulated 239 genes in CKD and 299 genes in control rats (66% overlap) whereas only a few genes were down-regulated (14 in CKD and 34 in controls), compared with the non-ischemic limb of the same animals. Comparison between the ischemic limbs of CKD and controls revealed down-regulation of 65 genes in CKD; 37 of these genes were also among the ischemia-induced genes in controls. Analysis of functional groups (other than angiogenesis) pointed to genes involved in leukocyte recruitment and fatty acid metabolism. Transcript expression profiling points to a relatively small number of differentially expressed genes which may underlie the impaired post-ischemic angiogenesis in CKD.
EVALuna2:3946

Body mass index and breast cancer survival: a Mendelian randomization analysis - Guo, Qi; Burgess, Stephen; Turman, Constance; Bolla, Manjeet K.; Wang, Qin; Lush, Michael; Abraham, Jean; Aittomaki, Kristiina; Andrulis, Irene L.; Apicella, Carmel; Arndt, Volker; Barrdahl, Myrto; et al. (International Journal of Epidemiology, 2017)
Background: There is increasing evidence that elevated body mass index (BMI) is associated with reduced survival for women with breast cancer. However, the underlying reasons remain unclear. We conducted a Mendelian randomization analysis to investigate a possible causal role of BMI in survival from breast cancer. Methods: We used individual-level data from six large breast cancer case-cohorts including a total of 36 210 individuals (2475 events) of European ancestry. We created a BMI genetic risk score (GRS) based on genotypes at 94 known BMI-associated genetic variants. Association between the BMI genetic score and breast cancer survival was analysed by Cox regression for each study separately. Study-specific hazard ratios were pooled using fixed-effect meta-analysis. Results: BMI genetic score was found to be associated with reduced breast cancer-specific survival for estrogen receptor (ER)-positive cases [hazard ratio (HR) = 1.11, per one-unit increment of GRS, 95% confidence interval (CI) 1.01-1.22, P = 0.03). We observed no association for ER-negative cases (HR = 1.00, per one-unit increment of GRS, 95% CI 0.89-1.13, P = 0.95). Conclusions: Our findings suggest a causal effect of increased BMI on reduced breast cancer survival for ER-positive breast cancer. There is no evidence of a causal effect of higher BMI on survival for ER-negative breast cancer cases.
EVALuna2:33863

Bone marrow-derived myeloid progenitors in the leptomeninges of adult mice - Koeniger, Tobias; Bell, Luisa; Mifka, Anika; Enders, Michael; Hautnnann, Valentin; Mekala, Subba Rao; Kirchner, Philipp; Ekici, Arif Bülent; Schulz, Christian; Woersdoerfer, Philipp; Mencl, Stine; Kleinschnitz, Christoph; et al. (Stem Cells, 2020)
Although the bone marrow contains most hematopoietic activity during adulthood, hematopoietic stem and progenitor cells can be recovered from various extramedullary sites. Cells with hematopoietic progenitor properties have even been reported in the adult brain under steady-state conditions, but their nature and localization remain insufficiently defined. Here, we describe a heterogeneous population of myeloid progenitors in the leptomeninges of adult C57BL/6 mice. This cell pool included common myeloid, granulocyte/macrophage, and megakaryocyte/erythrocyte progenitors. Accordingly, it gave rise to all major myelo-erythroid lineages in clonogenic culture assays. Brain-associated progenitors persisted after tissue perfusion and were partially inaccessible to intravenous antibodies, suggesting their localization behind continuous blood vessel endothelium such as the blood-arachnoid barrier. Flt3Cre lineage tracing and bone marrow transplantation showed that the precursors were derived from adult hematopoietic stem cells and were most likely continuously replaced via cell trafficking. Importantly, their occurrence was tied to the immunologic state of the central nervous system (CNS) and was diminished in the context of neuroinflammation and ischemic stroke. Our findings confirm the presence of myeloid progenitors at the meningeal border of the brain and lay the foundation to unravel their possible functions in CNS surveillance and local immune cell production.
CRIS-Team Scopus Importer:2020-12-25
Keywords: hematopoietic; meninges; mouse; myeloid; progenitor

BRCA mutations and their influence on pathological complete response and prognosis in a clinical cohort of neoadjuvantly treated breast cancer patients - Wunderle, Marius; Gaß, Paul; Häberle, Lothar; Flesch, Vivien M.; Rauh, Claudia; Bani, Mayada; Hack, Carolin; Schrauder, Michael G.; Jud, Sebastian; Emons, Julius; Erber, Ramona; Ekici, Arif Bülent; et al. (Breast Cancer Research and Treatment, 2018)
PURPOSE: BRCA1/2 mutations influence the molecular characteristics and the effects of systemic treatment of breast cancer. This study investigates the impact of germline BRCA1/2 mutations on pathological complete response and prognosis in patients receiving neoadjuvant systemic chemotherapy. METHODS: Breast cancer patients were tested for a BRCA1/2 mutation in clinical routine work and were treated with anthracycline-based or platinum-based neoadjuvant chemotherapy between 1997 and 2015. These patients were identified in the tumor registry of the Breast Center of the University of Erlangen (Germany). Logistic regression and Cox regression analyses were performed to investigate the associations between BRCA1/2 mutation status, pathological complete response, disease-free survival, and overall survival. RESULTS: Among 355 patients, 59 had a mutation in BRCA1 or in BRCA2 (16.6%), 43 in BRCA1 (12.1%), and 16 in BRCA2 (4.5%). Pathological complete response defined as "ypT0; ypN0" was observed in 54.3% of BRCA1/2 mutation carriers, but only in 22.6% of non-carriers. The adjusted odds ratio was 2.48 (95% CI 1.26-4.91) for BRCA1/2 carriers versus non-carriers. Patients who achieved a pathological complete response had better disease-free survival and overall survival rates compared with those who did not achieve a pathological complete response, regardless of BRCA1/2 mutation status. CONCLUSIONS: BRCA1/2 mutation status leads to better responses to neoadjuvant chemotherapy in breast cancer. Pathological complete response is the main predictor of disease-free survival and overall survival, independently of BRCA1/2 mutation status.
EVALuna2:34606

Breast cancer risk - From genetics to molecular understanding of pathogenesis - Fasching, Peter; Ekici, Arif Bülent; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Schneider, Michael; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors. © Georg Thieme Verlag KG Stuttgart• New York•.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA; breast cancer risk; gene-environment interaction; genetic risk factors; prediction models

Breast Cancer Risk Genes - Association Analysis in More than 113,000 Women - Dorling, Leila; Carvalho, Sara; Allen, Jamie; Gonzalez-Neira, Anna; Luccarini, Craig; Wahlstrom, Cecilia; Pooley, Karen A.; Parsons, Michael T.; Fortuno, Cristina; Wang, Qin; Bolla, Manjeet K.; Dennis, Joe; et al. (New England Journal of Medicine, 2021)
BACKGROUND
CRIS-Team WoS Importer:2021-03-26

Breast cancer risk - Genes, environment and clinics Mammakarzinomrisiko - Gene, Umwelt und Klinik - Fasching, Peter; Ekici, Arif Bülent; Adamietz, B. R.; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2011)
The information available about breast cancer risk factors has increased dramatically during the last 10 years. In particular, studies of low-penetrance genes and mammographic density have improved our understanding of breast cancer risk. In addition, initial steps have been taken in investigating interactions between genes and environmental factors. This review concerns with actual data on this topic. Several genome-wide association studies (GWASs) with a casecontrol design, as well as large-scale validation studies, have identified and validated more than a dozen single nucleotide polymorphisms (SNPs) associated with breast cancer risk. They are located not only in or close to genes known to be involved in cancer pathogenesis, but also in genes not previously associated with breast cancer pathogenesis, or may even not be related to any genes. SNPs have also been identified that alter the lifetime risk in BRCA mutation carriers. With regard to nongenetic risk factors, studies of postmenopausal hormone replacement therapy (HRT) have revealed important information on how to weigh up the risks and benefits of HRT. Mammographic density (MD) has become an accepted and important breast cancer risk factor. Lifestyle and nutritional considerations have become an integral part of most studies of breast cancer risk, and some improvements have been made in this field as well. More than 10 years after the publication of the first breast cancer prevention studies with tamoxifen, other substances such as raloxifene and aromatase inhibitors have been investigated and have also been shown to have preventive potential. Finally, mammographic screening systems have been implemented in most Western countries during the last decade. These may be developed further by including more individualized methods of predicting the patients breast cancer risk. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA (breast cancer antigen); breast; breast feeding; CAM (Complementary and Alternative medicine); cancer registry; estrogen receptor

Breast MRI texture analysis for prediction of BRCA-associated genetic risk - Vasileiou, Georgia; Costa, Maria J.; Long, Christopher; Wetzler, Iris; Hoyer, Juliane; Kraus, Cornelia; Popp, Bernt; Emons, Julius; Wunderle, Marius; Wenkel, Evelyn; Uder, Michael; Beckmann, Matthias; et al. (BMC Medical Imaging, 2020)
BACKGROUND: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. METHODS: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty five controls were included. From each MRI 4225 computer-extracted voxels were analyzed. Non-imaging features including clinical, family cancer history variables and triple negative receptor status (TNBC) were complementarily used. Lasso-principal component regression (L-PCR) analysis was implemented to compare the predictive performance, assessed as area under the curve (AUC), when imaging features were used, and lasso logistic regression or conventional logistic regression for the remaining analyses. RESULTS: Lasso-selected imaging principal components showed the highest predictive value (AUC 0.86), surpassing family cancer history. Clinical variables comprising age at disease onset and bilateral breast cancer yielded a relatively poor AUC ( 0.56). Combination of imaging with the non-imaging variables led to an improvement of predictive performance in all analyses, with TNBC along with the imaging components yielding the highest AUC (0.94). Replacing family history variables with imaging components yielded an improvement of classification performance of 4%, suggesting that imaging compensates the predictive information arising from family cancer structure. CONCLUSIONS: The L-PCR model uncovered evidence for the utility of MRI texture features in distinguishing between BRCA1/2 positive and negative high-risk breast cancer individuals, which may suggest value to diagnostic routine. Integration of computer-extracted texture analysis from MRI modalities in prediction models and inclusion criteria might play a role in reducing false positives or missed cases especially when established risk variables such as family history are missing.
CRIS-Team Scopus Importer:2020-08-07
Keywords: BRCA1/2; Breast cancer; HBOC; L-PCR; MRI; Texture analysis

Brittle-Cornea-Syndrom Typ 1 durch Compound-Heterozygotie zweier Mutationen im ZNF469-Gen - Menzel-Severing, Johannes; Meiller, Ralph; Kraus, Cornelia; Trollmann, Regina; Atalay, Deniz (Ophthalmologe, 2019)
We report the case of a 3-year-old boy presenting with bilateral keratoglobus and blue sclera in addition to hallux valgus, arachnodactyly, small joint hypermobility, mitral valve dysfunction and a history of generalized muscular hypotonia in early infancy. Molecular genetics provided evidence of two pathogenic mutations in the ZNF469 gene (compound heterozygosity) leading to the diagnosis of brittle cornea syndrome type 1. In addition to neuropediatric care, spectacles were prescribed to correct refractive error and for ocular protection. Owing to the thin cornea and sclera, eye injuries are the main cause for irreversible visual loss in this disease.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Blue sclera; Connective tissue disease; Hereditary eye disease; Keratoglobus; Pediatric ophthalmology

CAGn repeat of the androgen receptor is linked to proopiomelanocortin promoter methylation-relevance for craving of male alcohol-dependent patients? - Muschler, Marc Andre Nicolas; Lenz, Bernd; Hillemacher, Thomas; Kraus, Cornelia; Kornhuber, Johannes; Frieling, Helge; Bleich, Stefan (Psychopharmacology, 2014)
Previous findings of the Franconian Alcoholism Research Studies showed that both the CAGn of the androgen receptor (AR) and the promoter methylation of the hypothalamic peptide proopiomelanocortin (POMC) were associated with craving of male alcohol-dependent patients.Based on the strong interactions between the hypothalamic-pituitary-gonadal (HPG) and the hypothalamic-pituitary-adrenal axis (HPA), this study investigated the relationships between the CAGn repeat of the AR, POMC promoter methylation and craving of male alcohol-dependent patients.This analysis covers 84 male patients with a diagnosis of alcohol dependence (DSM-IV). We sequenced the POMC gene promoter using bisulfite modified DNA to display the methylation status. Furthermore, we sequenced the CAGn repeat within exon 1 of the AR gene. Craving was quantified by the Obsessive Compulsive Drinking Scale.We found an inverse correlation between the number of CAGn repeats of the AR and the POMC methylation status in this study. Altogether, the POMC promoter methylation accounted for 33 % of the relationship between CAGn AR polymorphism and craving.This work shows that the AR and the POMC gene might functionally interact with each other and subsequently mediate craving in alcohol-dependent patients. The paper discusses different mechanisms which might underlie our findings involving sex hormones' and sex determining region of Y-gene's regulatory function on DNA-methyltransferase activity. In conclusion, the results give insight in the interaction between HPG and HPA axis. This study is a further step on the way to a better understanding of genetic and non-genetic factors underlying craving for alcohol.
EVALuna2:9197

Calculating Future 10-Year Breast Cancer Risks in Risk-Adapted Surveillance: A Method Comparison and Application in Clinical Practice - Zachariae, Silke; Quante, Anne S.; Kiechle, Marion; Rhiem, Kerstin; Fehm, Tanja N.; Schröder, Jörg Gunther; Horvath, Judit; Leinert, Elena; Dikow, Nicola; Ronez, Joelle; Schönfeld, Mirjam; van Mackelenbergh, Marion T.; et al. (CANCER PREV RES, 2025)
The German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC) has successfully implemented risk-adapted breast cancer surveillance for women at high breast cancer risk in Germany. Women with a family history of breast and ovarian cancer but without pathogenic germline variants in recognized breast cancer risk genes are recommended annual breast imaging if their predicted 10-year breast cancer risk is 5% or higher, using the Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA) breast cancer risk model, as outlined in the current GC-HBOC guideline. However, women who initially do not meet this risk threshold may do so later, even if there is no new cancer in their family. To determine when this threshold is crossed, one could annually repeat BOADICEA calculations using an aging pedigree: the “prediction by aging pedigree” (AP) approach. Alternatively, we propose a simplified and more practical “’conditional probability” (CP) approach, which calculates future risks based on the initial BOADICEA assessment. Using data from 6,661 women registered with GC-HBOC, both methods were compared. Initially, 74% of women, ages 30 to 48 years, had a 10-year breast cancer risk below 5%, but 53% exceeded this threshold at an older age based on the AP approach. Among the women with an initial risk below the threshold, the CP approach revealed that 99% of women exceeded the 5% threshold at the same or an earlier age compared with the AP approach (88% of cases were within the same year or 1 year earlier). The CP approach has been implemented as a user-friendly web application. Prevention Relevance: The German Consortium for Hereditary Breast Cancer recommends annual breast imaging for women if their 10-year breast cancer risk is 5% or higher. Women who initially do not meet this risk threshold may do so later. We propose a simple method to determine future risks based on initial risk assessments.
CRIS-Team Scopus Importer:2025-02-28

CAMTA1-related disorder: Phenotypic and molecular characterization of 26 new individuals and literature review - Al-Kateb, Hussam; Au, P. Y.Billie; Berland, Siren; Cogne, Benjamin; Demurger, Florence; Fluss, Joel; Isidor, Bertrand; Frank, L. Matthew; Varvagiannis, Konstantinos; Koolen, David A.; McDonald, Marie; Montgomery, Sarah; et al. (Clinical Genetics, 2023)
Calmodulin-binding transcriptional activator 1 (CAMTA1) is highly expressed in the brain and plays a role in cell cycle regulation, cell differentiation, regulation of long-term memory, and initial development, maturation, and survival of cerebellar neurons. The existence of human neurological phenotypes, including cerebellar dysfunction with variable cognitive and behavioral abnormalities (CECBA), associated with CAMTA1 variants, has further supported its role in brain functions. In this study, we phenotypically and molecularly characterize the largest cohort of individuals (n = 26) with 23 novel CAMTA1 variants (frameshift-7, nonsense-6, splicing-1, initiation codon-1, missense-5, and intragenic deletions-3) and compare the findings with all previously reported cases (total = 53). We show that the most notable phenotypic findings are developmental delay/intellectual disability, unsteady or uncoordinated gait, hypotonia, behavioral problems, and eye abnormalities. In addition, there is a high incidence of dysarthria, dysgraphia, microcephaly, gastrointestinal abnormalities, sleep difficulties, and nonspecific brain MRI findings; a few of which have been under-reported. More than one third of the variants in this cohort were inherited from an asymptomatic or mildly affected parent suggesting reduced penetrance and variable expressivity. Our cohort provides a comprehensive characterization of the spectrum of phenotypes and genotypes among individuals with CECBA and the large data will facilitate counseling and formulating management plans and surveillance recommendations for these individuals.
CRIS-Team Scopus Importer:2023-12-15
Keywords: behavioral; CAMTA1; CECBA; developmental delay; gait; hypotonia; neurodevelopmental disorder; reduced penetrance; variants

Cancer incidence and spectrum among children with genetically confirmed Beckwith-Wiedemann spectrum in Germany: a retrospective cohort study - Cöktü, Sümeyye; Spix, Claudia; Kaiser, Melanie; Beygo, Jasmin; Kleinle, Stephanie; Bachmann, Nadine; Kohlschmidt, Nicolai; Prawitt, Dirk; Beckmann, Alf; Klaes, Ruediger; Nevinny-Stickel-Hinzpeter, Claudia; Döhnert, Steffi; et al. (British Journal of Cancer, 2020)
Background: Beckwith-Wiedemann syndrome (BWS) is a cancer predisposition syndrome caused by defects on chromosome 11p15.5. The quantitative cancer risks in BWS patients depend on the underlying (epi)genotype but have not yet been assessed in a population-based manner. Methods: We identified a group of 321 individuals with a molecularly confirmed diagnosis of BWS and analysed the cancer incidence up to age 15 years and cancer spectrum by matching their data with the German Childhood Cancer Registry. Results: We observed 13 cases of cancer in the entire BWS cohort vs 0.4 expected. This corresponds to a 33-fold increased risk (standardised incidence ratio (SIR) = 32.6; 95% confidence interval = 17.3-55.7). The specific cancers included hepatoblastoma (n = 6); nephroblastoma (n = 4); astrocytoma (n = 1); neuroblastoma (n = 1) and adrenocortical carcinoma (n = 1). The cancer SIR was highest in patients with a paternal uniparental disomy of 11p15.5 (UPDpat). A high cancer risk remained when cases of cancer diagnosed prior to the BWS diagnosis were excluded. Conclusions: This study confirms an increased cancer risk in children with BWS. Our findings suggest that the highest cancer risk is associated with UPDpat. We were unable to confirm an excessive cancer risk in patients with IC1 gain of methylation (IC1-GOM) and this finding requires further investigation.
CRIS-Team Scopus Importer:2020-06-02

Candidate locus analysis of the TERT-CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Carvajal-Carmona, Luis G.; O'Mara, Tracy A.; Painter, Jodie N.; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Pooley, Karen; Beesley, Jonathan; et al. (Human genetics, 2015)
Several studies have reported associations between multiple cancer types and single-nucleotide polymorphisms (SNPs) on chromosome 5p15, which harbours TERT and CLPTM1L, but no such association has been reported with endometrial cancer. To evaluate the role of genetic variants at the TERT-CLPTM1L region in endometrial cancer risk, we carried out comprehensive fine-mapping analyses of genotyped and imputed SNPs using a custom Illumina iSelect array which includes dense SNP coverage of this region. We examined 396 SNPs (113 genotyped, 283 imputed) in 4,401 endometrial cancer cases and 28,758 controls. Single-SNP and forward/backward logistic regression models suggested evidence for three variants independently associated with endometrial cancer risk (P = 4.9 × 10(-6) to P = 7.7 × 10(-5)). Only one falls into a haplotype previously associated with other cancer types (rs7705526, in TERT intron 1), and this SNP has been shown to alter TERT promoter activity. One of the novel associations (rs13174814) maps to a second region in the TERT promoter and the other (rs62329728) is in the promoter region of CLPTM1L; neither are correlated with previously reported cancer-associated SNPs. Using TCGA RNASeq data, we found significantly increased expression of both TERT and CLPTM1L in endometrial cancer tissue compared with normal tissue (TERT P = 1.5 × 10(-18), CLPTM1L P = 1.5 × 10(-19)). Our study thus reports a novel endometrial cancer risk locus and expands the spectrum of cancer types associated with genetic variation at 5p15, further highlighting the importance of this region for cancer susceptibility.
EVALuna2:9280

Cardiac injury of the newborn mammalian heart accelerates cardiomyocyte terminal differentiation - Zebrowski, David; Jensen, Charlotte H.; Becker, Robert; Ferrazzi, Fulvia; Baun, Christina; Hvidsten, Svend; Sheikh, Soren P.; Polizzotti, Brian D.; Andersen, Ditte C.; Engel, Felix (Scientific Reports, 2017)
After birth cardiomyocytes undergo terminal differentiation, characterized by binucleation and centrosome disassembly, rendering the heart unable to regenerate. Yet, it has been suggested that newborn mammals regenerate their hearts after apical resection by cardiomyocyte proliferation. Thus, we tested the hypothesis that apical resection either inhibits, delays, or reverses cardiomyocyte centrosome disassembly and binucleation. Our data show that apical resection rather transiently accelerates centrosome disassembly as well as the rate of binucleation. Consistent with the nearly 2-fold increased rate of binucleation there was a nearly 2-fold increase in the number of cardiomyocytes in mitosis indicating that the majority of injury-induced cardiomyocyte cell cycle activity results in binucleation, not proliferation. Concurrently, cardiomyocytes undergoing cytokinesis from embryonic hearts exhibited midbody formation consistent with successful abscission, whereas those from 3 day-old cardiomyocytes after apical resection exhibited midbody formation consistent with abscission failure. Lastly, injured hearts failed to fully regenerate as evidenced by persistent scarring and reduced wall motion. Collectively, these data suggest that should a regenerative program exist in the newborn mammalian heart, it is quickly curtailed by developmental mechanisms that render cardiomyocytes post-mitotic.
EVALuna2:9380

Cardiovascular changes in the NZB/W F1 mouse model of lupus nephritis - Böhme, Romy; Daniel, Christoph; Ferrazzi, Fulvia; Angeloni, Miriam; Ekici, Arif Bülent; Winkler, Thomas; Hilgers, Karl Friedrich; Wellmann, Ute; Voll, Reinhard E.; Amann, Kerstin Ute (Frontiers in Cardiovascular Medicine, 2023)
Background: Patients with systemic lupus erythematosus (SLE), an autoimmune disease, have a higher risk of cardiovascular (CV) disease and death. In addition, up to 40%–50% of SLE patients develop lupus nephritis (LN) and chronic kidney disease, which is an additional CV risk factor. Thus, the individual contributions of LN and other SLE-specific factors to CV events are unclear. Methods: In this study, we investigated the effect of LN on the development of CV changes using the female NZBxNZW F1 (NZB/W) mouse model of lupus-like disease, with female NZW mice as controls. Standard serologic, morphologic, immunohistologic, and molecular analyses were performed. In a separate group of NZB/W mice, systolic blood pressure (BP) was measured during the course of the disease using tail plethysmography. Results: Our data show marked CV changes in NZB/W mice, i.e., increased heart weight, hypertrophy of the left ventricle (LV) and septum, and increased wall thickness of the intramyocardial arteries and the aorta, which correlated with the progression of renal damage, but not with the age of the mice. In addition, systolic BP was increased in NZB/W mice only when kidney damage progressed and proteinuria was present. Pathway analysis based on gene expression data revealed a significant upregulation of the response to interferon beta in NZB/W mice with moderate kidney injury compared with NZB mice. Furthermore, IFI202b and IL-6 mRNA expression is correlated with CV changes. Multiple linear regression analysis demonstrated serum urea as a surrogate marker of kidney function and IFI202b expression as an independent predictor for LV wall thickness. In addition, deposition of complement factors CFD and C3c in hearts from NZB/W mice was seen, which correlated with the severity of kidney disease. Conclusions: Thus, we postulate that the pathogenesis of CV disease in SLE is affected by renal impairment, i.e., LN, but it can also be partly influenced by lupus-specific cardiac expression of pro-inflammatory factors and complement deposition.
CRIS-Team Scopus Importer:2023-08-18
Keywords: autoimmune disease; cardiovascular disease; IL-15; interferon-related; renal disease; systemic lupus erythematosus

CD163+ M2c-like macrophages predominate in renal biopsies from patients with lupus nephritis - Olmes, Gregor; Buettner-Herold, Maike; Ferrazzi, Fulvia; Distel, Luitpold; Amann, Kerstin Ute; Daniel, Christoph (Arthritis Research & Therapy, 2015)
The role of macrophages in the pathogenesis of lupus nephritis, in particular their differentiation to a certain subtype (e.g., M1- or M2-like) modulating the inflammatory reaction, is unknown. Here we investigated whether the differentiation in M1- or M2-like macrophages depends on the stage of lupus nephritis and whether this correlates with clinical parameters.Using immunohistochemical analysis we analyzed renal biopsies from 68 patients with lupus nephritis (ISN/RPS classes II-V) for infiltration with M1-like (iNOS+/CD68+), M2a-like (CD206+/CD68+), M2c-like macrophages (CD163+/CD68+), and FoxP3+ regulatory T-cells. In addition, clinical parameters at the time of renal biopsy, i.e., blood pressure, proteinuria and serum urea were correlated with the macrophage infiltration using the Spearman test.The mean number of CD68+ macrophages was related to the diagnosed ISN/RPS class, showing the highest macrophage infiltration in biopsies with diffuse class IV and the lowest number in ISN/RPS class V. In all ISN/RPS classes we detected more M2c-like CD163+/CD68+ than M2a-like CD206+/CD68+ cells, while M1-macrophages played only a minor role. Cluster analysis using macrophage subtype numbers in different renal compartments revealed three main clusters showing cluster 1 dominated by class V. Clusters 2 and 3 were dominated by lupus class IV indicating that this class can be further differentiated by its macrophage population. The number of tubulointerstitial FoxP3+ cells correlated with all investigated macrophage subtypes showing the strongest association to numbers of M2a-like macrophages. Kidney function, as assessed by serum creatinine and serum urea, correlated positively with the number of total CD68+, M2a-like and M2c-like macrophages in the tubulointerstitium. In addition, total CD68+ and M2c-like macrophage numbers highly correlated with Austin activity score. Interestingly, in hypertensive lupus patients only the number of M2a-like macrophages was significantly increased compared to biopsies from normotensive lupus patients.M2-like macrophages are the dominant subpopulation in human lupus nephritis and particularly, M2a subpopulations were associated with disease progression, but their role in disease progression remains unclear.
EVALuna2:9308

CD200+ fibroblasts form a pro-resolving mesenchymal network in arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Soare, Alina; Treutlein, Christoph; Kemble, Samuel; Mahony, Christopher B.; Geisthoff, Manuel; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Xu, Cong; et al. (Nature Immunology, 2024)
Fibroblasts are important regulators of inflammation, but whether fibroblasts change phenotype during resolution of inflammation is not clear. Here we use positron emission tomography to detect fibroblast activation protein (FAP) as a means to visualize fibroblast activation in vivo during inflammation in humans. While tracer accumulation is high in active arthritis, it decreases after tumor necrosis factor and interleukin-17A inhibition. Biopsy-based single-cell RNA-sequencing analyses in experimental arthritis show that FAP signal reduction reflects a phenotypic switch from pro-inflammatory MMP3+/IL6+ fibroblasts (high FAP internalization) to pro-resolving CD200+DKK3+ fibroblasts (low FAP internalization). Spatial transcriptomics of human joints indicates that pro-resolving niches of CD200+DKK3+ fibroblasts cluster with type 2 innate lymphoid cells, whereas MMP3+/IL6+ fibroblasts colocalize with inflammatory immune cells. CD200+DKK3+ fibroblasts stabilized the type 2 innate lymphoid cell phenotype and induced resolution of arthritis via CD200–CD200R1 signaling. Taken together, these data suggest a dynamic molecular regulation of the mesenchymal compartment during resolution of inflammation.
Created from Fastlane, Scopus look-up

Central nervous system anomalies in two females with Borjeson-Forssman-Lehmann syndrome - Kasper, Burkhard; Dörfler, Arnd; Di Donato, Nataliya; Kasper, Ekkehard M.; Wieczorek, Dagmar; Hoyer, Juliane; Zweier, Christiane (Epilepsy and Behavior, 2017)
Borjeson-Forssman-Lehmann syndrome (BFLS) is a rare disorder caused by mutations in the PHF6 gene. It manifests as syndromic X-linked recessive intellectual disability (ID) in males and as sporadic ID due to de novo mutations in females. Clinical features include variable ID and a range of somatic manifestations constituting a distinct phenotype in both males and females, respectively, including seizures in a few. Central nervous system (CNS) imaging data are largely unavailable for BFLS. Here we report on CNS MRI findings from two female individuals with BFLS due to a de novo duplication in PHF6 who presented with typical BFLS and epilepsy. Brain findings encompass an intriguing combination of structural abnormalities including a simplified gyral pattern and aspects resembling subcortical band heterotopia as signs of malformation of cortical development (MCD). This finding is of note, since PHF6 has been suggested to play pivotal roles in CNS development including neuronal migration.
EVALuna2:9368

CERT1 mutations perturb human development by disrupting sphingolipid homeostasis - Gehin, Charlotte; Lone, Museer A.; Lee, Winston; Capolupo, Laura; Ho, Sylvia; Adeyemi, Adekemi M.; Gerkes, Erica H.; Stegmann, Alexander Pa; López-Martín, Estrella; Bermejo-Sánchez, Eva; Martínez-Delgado, Beatriz; Zweier, Christiane; et al. (Journal of Clinical Investigation, 2023)
Neural differentiation, synaptic transmission, and action potential propagation depend on membrane sphingolipids, whose metabolism is tightly regulated. Mutations in the ceramide transporter CERT (CERT1), which is involved in sphingolipid biosynthesis, are associated with intellectual disability, but the pathogenic mechanism remains obscure. Here, we characterize 31 individuals with de novo missense variants in CERT1. Several variants fall into a previously uncharacterized dimeric helical domain that enables CERT homeostatic inactivation, without which sphingolipid production goes unchecked. The clinical severity reflects the degree to which CERT autoregulation is disrupted, and inhibiting CERT pharmacologically corrects morphological and motor abnormalities in a Drosophila model of the disease, which we call ceramide transporter (CerTra) syndrome. These findings uncover a central role for CERT autoregulation in the control of sphingolipid biosynthetic flux, provide unexpected insight into the structural organization of CERT, and suggest a possible therapeutic approach for patients with CerTra syndrome.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cell Biology; Genetics; Lipid rafts; Neurodevelopment

Characterization of germ cell differentiation in the male mouse through single-cell RNA sequencing - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Reports, 2018)
Spermatogenesis in the mouse has been extensively studied for decades. Previous methods, such as histological staining or bulk transcriptome analysis, either lacked resolution at the single-cell level or were focused on a very narrowly defined set of factors. Here, we present the first comprehensive, unbiased single-cell transcriptomic view of mouse spermatogenesis. Our single-cell RNA-seq (scRNA-seq) data on over 2,500 cells from the mouse testis improves upon stage marker detection and validation, capturing the continuity of differentiation rather than artificially chosen stages. scRNA-seq also enables the analysis of rare cell populations masked in bulk sequencing data and reveals new insights into the regulation of sex chromosomes during spermatogenesis. Our data provide the basis for further studies in the field, for the first time providing a high-resolution reference of transcriptional processes during mouse spermatogenesis.
EVALuna2:34135

CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language - Blok, Lot Snijders; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance H.; Nowak, Catherine B.; Douglas, Jessica; Swoboda, Kathryn J.; Steeves, Marcie A.; Sahai, Inderneel; et al. (Nature Communications, 2018)
Chromatin remodeling is of crucial importance during brain development. Pathogenic alterations of several chromatin remodeling ATPases have been implicated in neurodevelopmental disorders. We describe an index case with a de novo missense mutation in CHD3, identified during whole genome sequencing of a cohort of children with rare speech disorders. To gain a comprehensive view of features associated with disruption of this gene, we use a genotype-driven approach, collecting and characterizing 35 individuals with de novo CHD3 mutations and overlapping phenotypes. Most mutations cluster within the ATPase/helicase domain of the encoded protein. Modeling their impact on the three-dimensional structure demonstrates disturbance of critical binding and interaction motifs. Experimental assays with six of the identified mutations show that a subset directly affects ATPase activity, and all but one yield alterations in chromatin remodeling. We implicate de novo CHD3 mutations in a syndrome characterized by intellectual disability, macrocephaly, and impaired speech and language.
EVALuna2:34823

CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language (vol 9, 4619, 2018) - Blok, Lot Snijders; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance H.; Nowak, Catherine B.; Douglas, Jessica; Swoboda, Kathryn J.; Steeves, Marcie A.; Sahai, Inderneel; et al. (Nature Communications, 2019)
EVALuna2:206977

Childhood cancer predisposition syndromes-A concise review and recommendations by the Cancer Predisposition Working Group of the Society for Pediatric Oncology and Hematology - Ripperger, Tim; Bielack, Stefan S.; Borkhardt, Arndt; Brecht, Ines B.; Burkhardt, Birgit; Calaminus, Gabriele; Debatin, Klaus-Michael; Deubzer, Hedwig; Dirksen, Uta; Eckert, Cornelia; Eggert, Angelika; Erlacher, Miriam; et al. (American Journal of Medical Genetics Part A, 2017)
Heritable predisposition is an important cause of cancer in children and adolescents. Although a large number of cancer predisposition genes and their associated syndromes and malignancies have already been described, it appears likely that there are more pediatric cancer patients in whom heritable cancer predisposition syndromes have yet to be recognized. In a consensus meeting in the beginning of 2016, we convened experts in Human Genetics and Pediatric Hematology/Oncology to review the available data, to categorize the large amount of information, and to develop recommendations regarding when a cancer predisposition syndrome should be suspected in a young oncology patient. This review summarizes the current knowledge of cancer predisposition syndromes in pediatric oncology and provides essential information on clinical situations in which a childhood cancer predisposition syndrome should be suspected.
EVALuna2:9370

Choline transporter-like1 (CHER1) is crucial for plasmodesmata maturation in Arabidopsis thaliana - Kraner, Max; Link, Katrin; Melzer, Michael; Ekici, Arif Bülent; Uebe, Steffen; Tarazona, Pablo; Feussner, Ivo; Hofmann, Jörg; Sonnewald, Uwe (Plant Journal, 2016)
Plasmodesmata (PD) are microscopic pores connecting plant cells and enable cell-to-cell transport. Currently, little is known about the molecular mechanisms regulating PD formation and development. To uncover components of PD development we made use of the 17 kDa movement protein (MP17) encoded by the Potato leafroll virus (PLRV). The protein is required for cell-to-cell movement of the virus and localises to complex PD. Forward genetic screening for Arabidopsis mutants with altered PD-binding of MP17 revealed several mutant lines, while molecular genetics, biochemical and microscopic studies allowed further characterisation. Map-based cloning of one mutant revealed a point mutation in the choline transporter-like 1 (CHER1) protein, changing glycine(247) into glutamate. Mutation in CHER1 resulted in a starch excess phenotype and stunted growth. Ultrastructure analysis of shoot apical meristems, developing and fully developed leaves showed reduced PD numbers and the absence of complex PD in fully developed leaves. This indicates that cher1 mutants are impaired in PD formation and development. Global lipid profiling revealed only slight modifications in the overall lipid composition, however, altered composition of PD-associated lipids cannot be ruled out. Thus, cher1 is devoid of complex PD in developed leaves and provides insights into the formation of complex PD at the molecular level. This article is protected by copyright. All rights reserved.
EVALuna2:9344

Chromatin-Remodeling-Factor ARID1B Represses Wnt/?-Catenin Signaling - Vasileiou, Georgia; Ekici, Arif Bülent; Urebe, Steffen; Zweier, Christiane; Hoyer, Juliane; Engels, Hartmut; Behrens, Jürgen; Reis, André; Hadjihannas, Michel (American Journal of Human Genetics, 2015)
The link of chromatin remodeling to both neurodevelopment and cancer has recently been highlighted by the identification of mutations affecting BAF chromatin-remodeling components, such as ARID1B, in individuals with intellectual disability and cancer. However, the underlying molecular mechanism(s) remains unknown. Here, we show that ARID1B is a repressor of Wnt/?-catenin signaling. Through whole-transcriptome analysis, we find that in individuals with intellectual disability and ARID1B loss-of-function mutations, Wnt/?-catenin target genes are upregulated. Using cellular models of low and high Wnt/?-catenin activity, we demonstrate that knockdown of ARID1B activates Wnt/?-catenin target genes and Wnt/?-catenin-dependent transcriptional reporters in a ?-catenin-dependent manner. Reciprocally, forced expression of ARID1B inhibits Wnt/?-catenin signaling downstream of the ?-catenin destruction complex. Both endogenous and exogenous ARID1B associate with ?-catenin and repress Wnt/?-catenin-mediated transcription through the BAF core subunit BRG1. Accordingly, mutations in ARID1B leading to partial or complete deletion of its BRG1-binding domain, as is often observed in intellectual disability and cancers, compromise association with ?-catenin, and the resultant ARID1B mutant proteins fail to suppress Wnt/?-catenin signaling. Finally, knockdown of ARID1B in mouse neuroblastoma cells leads to neurite outgrowth through ?-catenin. The data suggest that aberrations in chromatin-remodeling factors, such as ARID1B, might contribute to neurodevelopmental abnormalities and cancer through deregulation of developmental and oncogenic pathways, such as the Wnt/?-catenin signaling pathway.
EVALuna2:9258

Chromatin-Remodeling Factor SPOC1 Acts as a Cellular Restriction Factor against Human Cytomegalovirus by Repressing the Major Immediate Early Promoter - Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Reuter, Nina; Lukassen, Sören; Kasmapour, Bahram; Schreiner, Sabrina; Cicin-Sain, Luka; Winterpacht, Andreas; Stamminger, Thomas (Journal of Virology, 2018)
The cellular protein SPOC1 (survival time-associated PHD [plant homeodomain] finger protein in ovarian cancer 1) acts as a regulator of chromatin structure and the DNA damage response. It binds H3K4me2/3-containing chromatin and promotes DNA condensation by recruiting corepressors such as KAP-1 and H3K9 methyltransferases. Previous studies identified SPOC1 as a restriction factor against human adenovirus (HAdV) infection that is antagonized by E1B-55K/E4-orf6-dependent proteasomal degradation. Here, we demonstrate that, in contrast to HAdV-infected cells, SPOC1 is transiently upregulated during the early phase of human cytomegalovirus (HCMV) replication. We show that the expression of immediate early protein 1 (IE1) is sufficient and necessary to induce SPOC1. Additionally, we discovered that during later stages of infection, SPOC1 is downregulated in a glycogen synthase kinase 3β (GSK-3β)-dependent manner. We provide evidence that SPOC1 overexpression severely impairs HCMV replication by repressing the initiation of viral immediate early (IE) gene expression. Consistently, we observed that SPOC1-depleted primary human fibroblasts displayed an augmented initiation of viral IE gene expression. This occurs in a multiplicity of infection (MOI)-dependent manner, a defining hallmark of intrinsic immunity. Interestingly, repression requires the presence of high SPOC1 levels at the start of infection, while later upregulation had no negative impact, suggesting distinct temporal roles of SPOC1 during the HCMV replicative cycle. Mechanistically, we observed a highly specific association of SPOC1 with the major immediate early promoter (MIEP), strongly suggesting that SPOC1 inhibits HCMV replication by MIEP binding and the subsequent recruitment of heterochromatin-building factors. Thus, our data add SPOC1 as a novel factor to the endowment of a host cell to restrict cytomegalovirus infections.IMPORTANCE Accumulating evidence indicates that during millennia of coevolution, host cells have developed a sophisticated compilation of cellular factors to restrict cytomegalovirus infections. Defining this equipment is important to understand cellular barriers against viral infection and to develop strategies to utilize these factors for antiviral approaches. So far, constituents of PML nuclear bodies and interferon gamma-inducible protein 16 (IFI16) were known to mediate intrinsic immunity against HCMV. In this study, we identify the chromatin modulator SPOC1 as a novel restriction factor against HCMV. We show that preexisting high SPOC1 protein levels mediate a silencing of HCMV gene expression via a specific association with an important viral cis-regulatory element, the major immediate early promoter. Since SPOC1 expression varies between cell types, this factor may play an important role in tissue-specific defense against HCMV.
EVALuna2:34842

Chronic silencing of subsets of cortical layer 5 pyramidal neurons has a long-term influence on the laminar distribution of parvalbumin interneurons and the perineuronal nets - Szabó, Florina P.; Sigutova, Veronika; Schneider, Anna M.; Hoerder-Suabedissen, Anna; Molnár, Zoltán (Journal of Anatomy, 2024)
Neural networks are established throughout cortical development, which require the right ratios of glutamatergic and GABAergic neurons. Developmental disturbances in pyramidal neuron number and function can impede the development of GABAergic neurons, which can have long-lasting consequences on inhibitory networks. However, the role of deep-layer pyramidal neurons in instructing the development and distribution of GABAergic neurons is still unclear. To unravel the role of deep-layer pyramidal neuron activity in orchestrating the spatial and laminar distribution of parvalbumin neurons, we selectively manipulated subsets of layer 5 projection neurons. By deleting Snap25 selectively from Rbp4-Cre + pyramidal neurons, we abolished regulated vesicle release from subsets of cortical layer 5 projection neurons. Our findings revealed that chronically silencing subsets of layer 5 projection neurons did not change the number and distribution of parvalbumin neurons in the developing brain. However, it did have a long-term impact on the laminar distribution of parvalbumin neurons and their perineuronal nets in the adult primary motor and somatosensory cortices. The laminar positioning of parvalbumin neurons was altered in layer 4 of the primary somatosensory cortex in the adult Snap25 cKO mice. We discovered that the absence of layer 5 activity only had a transient effect on the soma morphology of striatal PV neurons during the third week of postnatal development. We also showed that the relationship between parvalbumin neurons and the perineuronal nets varied across different cortical layers and regions; therefore, their relationship is far more complex than previously described. The current study will help us better understand the bidirectional interaction between deep-layer pyramidal cells and GABAergic neurons, as well as the long-term impact of interrupting pyramidal neuron activity on inhibitory network formation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: cerebral cortex; GABAergic interneurons; layer 5; parvalbumin; perineuronal nets; Rbp4-Cre; Snap25; synaptic transmission

Cis-eQTL analysis and functional validation of candidate susceptibility genes for high-grade serous ovarian cancer - Lawrenson, Kate; Li, Qiyan; Kar, Siddhartha; Seo, Ji-Heui; Tyrer, Jonathan; Spindler, Tassja J.; Lee, Janet; Chen, Yibu; Karst, Alison; Drapkin, Ronny; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Nature Communications, 2015)
Genome-wide association studies have reported 11 regions conferring risk of high-grade serous epithelial ovarian cancer (HGSOC). Expression quantitative trait locus (eQTL) analyses can identify candidate susceptibility genes at risk loci. Here we evaluate cis-eQTL associations at 47 regions associated with HGSOC risk (P<=10(-5)). For three cis-eQTL associations (P<1.4 × 10(-3), FDR<0.05) at 1p36 (CDC42), 1p34 (CDCA8) and 2q31 (HOXD9), we evaluate the functional role of each candidate by perturbing expression of each gene in HGSOC precursor cells. Overexpression of HOXD9 increases anchorage-independent growth, shortens population-doubling time and reduces contact inhibition. Chromosome conformation capture identifies an interaction between rs2857532 and the HOXD9 promoter, suggesting this SNP is a leading causal variant. Transcriptomic profiling after HOXD9 overexpression reveals enrichment of HGSOC risk variants within HOXD9 target genes (P=6 × 10(-10) for risk variants (P<10(-4)) within 10 kb of a HOXD9 target gene in ovarian cells), suggesting a broader role for this network in genetic susceptibility to HGSOC.
EVALuna2:9265

Clinical and experimental evidence suggest a link between KIF7 and C5orf42-related ciliopathies through Sonic Hedgehog signaling - Asadollahi, Reza; Strauss, Justin E.; Zenker, Martin; Beuing, Oliver; Edvardson, Simon; Elpeleg, Orly; Strom, Tim M.; Joset, Pascal; Niedrist, Dunja; Otte, Christine; Oneda, Beatrice; Boonsawat, Paranchai; et al. (European journal of human genetics, 2018)
Acrocallosal syndrome (ACLS) is an autosomal recessive neurodevelopmental disorder caused by KIF7 defects and belongs to the heterogeneous group of ciliopathies related to Joubert syndrome (JBTS). While ACLS is characterized by macrocephaly, prominent forehead, depressed nasal bridge, and hypertelorism, facial dysmorphism has not been emphasized in JBTS cohorts with molecular diagnosis. To evaluate the specificity and etiology of ACLS craniofacial features, we performed whole exome or targeted Sanger sequencing in patients with the aforementioned overlapping craniofacial appearance but variable additional ciliopathy features followed by functional studies. We found (likely) pathogenic variants of KIF7 in 5 out of 9 families, including the original ACLS patients, and delineated 1000 to 4000-year-old Swiss founder alleles. Three of the remaining families had (likely) pathogenic variants in the JBTS gene C5orf42, and one patient had a novel de novo frameshift variant in SHH known to cause autosomal dominant holoprosencephaly. In accordance with the patients' craniofacial anomalies, we showed facial midline widening after silencing of C5orf42 in chicken embryos. We further supported the link between KIF7, SHH, and C5orf42 by demonstrating abnormal primary cilia and diminished response to a SHH agonist in fibroblasts of C5orf42-mutated patients, as well as axonal pathfinding errors in C5orf42-silenced chicken embryos similar to those observed after perturbation of Shh signaling. Our findings, therefore, suggest that beside the neurodevelopmental features, macrocephaly and facial widening are likely more general signs of disturbed SHH signaling. Nevertheless, long-term follow-up revealed that C5orf42-mutated patients showed catch-up development and fainting of facial features contrary to KIF7-mutated patients.
EVALuna2:34140

Clinical and genetic characterization of SPG11: Hereditary Spastic Paraplegia with thin corpus callosum - Winner, Beate; Winkler, Jürgen; Uyanik, Goekhan; Cirak, Sebahattin; Hehr, Ute; et al. (Neuromuscular Disorders, 2006)

Clinical and molecular delineation of spondylocostal dysostosis type 3 - Schuhmann, Sarah; Koller, Heiko; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Thiel, Christian (Clinical Genetics, 2021)
CRIS-Team Scopus Importer:2021-03-26

Clinical and molecular description of 19 patients with GATAD2B-Associated Neurodevelopmental Disorder (GAND) - Vera, Gabriella; Sorlin, Arthur; Delplancq, Geoffroy; Lecoquierre, François; Brasseur-Daudruy, Marie; Petit, Florence; Smol, Thomas; Ziegler, Alban; Bonneau, Dominique; Colin, Estelle; Mercier, Sandra; Cogné, Benjamin; et al. (European Journal of Medical Genetics, 2020)
De novo pathogenic variants in the GATAD2B gene have been associated with a syndromic neurodevelopmental disorder (GAND) characterized by severe intellectual disability (ID), impaired speech, childhood hypotonia, and dysmorphic features. Since its first description in 2013, nine patients have been reported in case reports and a series of 50 patients was recently published, which is consistent with the relative frequency of GATAD2B pathogenic variants in public databases. We report the detailed phenotype of 19 patients from various ethnic backgrounds with confirmed pathogenic GATAD2B variants including intragenic deletions. All individuals presented developmental delay with a median age of 2.5 years for independent walking and of 3 years for first spoken words. GATAD2B variant carriers showed very little subsequent speech progress, two patients over 30 years of age remaining non-verbal. ID was mostly moderate to severe, with one profound and one mild case, which shows a wider spectrum of disease severity than previously reported. We confirm macrocephaly as a major feature in GAND (53%). Most common dysmorphic features included broad forehead, deeply set eyes, hypertelorism, wide nasal base, and pointed chin. Conversely, prenatal abnormalities, non-cerebral malformations, epilepsy, and autistic behavior were uncommon. Other features included feeding difficulties, behavioral abnormalities, and unspecific abnormalities on brain MRI. Improving our knowledge of the clinical phenotype is essential for correct interpretation of the molecular results and accurate patient management.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Developmental delay; GATAD2B; Intellectual disability; Next-generation sequencing

Clinical delineation of the PACS1-related syndrome - Report on 19 patients - Schuurs-Hoeijmakers, Janneke H. M.; Landsverk, Megan L.; Foulds, Nicola; Kukolich, Mary K.; Gavrilova, Ralitza H.; Greville-Heygate, Stephanie; Hanson-Kahn, Andrea; Bernstein, Jonathan A.; Glass, Jennifer; Chitayat, David; Burrow, Thomas A.; Husami, Ammar; et al. (American Journal of Medical Genetics Part A, 2016)
We report on 19 individuals with a recurrent de novo c.607C>T mutation in PACS1. This specific mutation gives rise to a recognizable intellectual disability syndrome. There is a distinctive facial appearance (19/19), characterized by full and arched eyebrows, hypertelorism with downslanting palpebral fissures, long eye lashes, ptosis, low set and simple ears, bulbous nasal tip, wide mouth with downturned corners and a thin upper lip with an unusual "wavy" profile, flat philtrum, and diastema of the teeth. Intellectual disability, ranging from mild to moderate, was present in all. Hypotonia is common in infancy (8/19). Seizures are frequent (12/19) and respond well to anticonvulsive medication. Structural malformations are common, including heart (10/19), brain (12/16), eye (10/19), kidney (3/19), and cryptorchidism (6/12 males). Feeding dysfunction is presenting in infancy with failure to thrive (5/19), gastroesophageal reflux (6/19), and gastrostomy tube placement (4/19). There is persistence of oral motor dysfunction. We provide suggestions for clinical work-up and management and hope that the present study will facilitate clinical recognition of further cases.
EVALuna2:9319

Clinical, neuroimaging, and molecular spectrum of TECPR2-associated hereditary sensory and autonomic neuropathy with intellectual disability - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Broesse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A.; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (Human Mutation, 2021)
Bi-allelic TECPR2 variants have been associated with a complex syndrome with features of both a neurodevelopmental and neurodegenerative disorder. Here, we provide a comprehensive clinical description and variant interpretation framework for this genetic locus. Through international collaboration, we identified 17 individuals from 15 families with bi-allelic TECPR2-variants. We systemically reviewed clinical and molecular data from this cohort and 11 cases previously reported. Phenotypes were standardized using Human Phenotype Ontology terms. A cross-sectional analysis revealed global developmental delay/intellectual disability, muscular hypotonia, ataxia, hyporeflexia, respiratory infections, and central/nocturnal hypopnea as core manifestations. A review of brain magnetic resonance imaging scans demonstrated a thin corpus callosum in 52%. We evaluated 17 distinct variants. Missense variants in TECPR2 are predominantly located in the N- and C-terminal regions containing β-propeller repeats. Despite constituting nearly half of disease-associated TECPR2 variants, classifying missense variants as (likely) pathogenic according to ACMG criteria remains challenging. We estimate a pathogenic variant carrier frequency of 1/1221 in the general and 1/155 in the Jewish Ashkenazi populations. Based on clinical, neuroimaging, and genetic data, we provide recommendations for variant reporting, clinical assessment, and surveillance/treatment of individuals with TECPR2-associated disorder. This sets the stage for future prospective natural history studies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Human Phenotype Ontology; neurodevelopmental disorder; sensory autonomic neuropathy; spastic paraplegia; TECPR2

Clinical relevance of systematic phenotyping and exome sequencing in patients with short stature - Hauer, Nadine; Popp, Bernt; Schoeller, Eva; Schuhmann, Sarah; Heath, Karen E.; Hisado-Oliva, Alfonso; Klinger, Patricia; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; et al. (Genetics in Medicine, 2018)
PurposeShort stature is a common condition of great concern to patients and their families. Mostly genetic in origin, the underlying cause often remains elusive due to clinical and genetic heterogeneity.MethodsWe systematically phenotyped 565 patients where common nongenetic causes of short stature were excluded, selected 200 representative patients for whole-exome sequencing, and analyzed the identified variants for pathogenicity and the affected genes regarding their functional relevance for growth.ResultsBy standard targeted diagnostic and phenotype assessment, we identified a known disease cause in only 13.6% of the 565 patients. Whole-exome sequencing in 200 patients identified additional mutations in known short-stature genes in 16.5% of these patients who manifested only part of the symptomatology. In 15.5% of the 200 patients our findings were of significant clinical relevance. Heterozygous carriers of recessive skeletal dysplasia alleles represented 3.5% of the cases.ConclusionA combined approach of systematic phenotyping, targeted genetic testing, and whole-exome sequencing allows the identification of the underlying cause of short stature in at least 33% of cases, enabling physicians to improve diagnosis, treatment, and genetic counseling. Exome sequencing significantly increases the diagnostic yield and consequently care in patients with short stature.
EVALuna2:34628

Clinical spectrum of females with HCCS mutation: from no clinical signs to a neonatal lethal form of the microphthalmia with linear skin defects (MLS) syndrome - Van Rahden, Vanessa A.; Rau, Isabella; Fuchs, Sigrid; Kosyna, Friederike K.; De Almeida, Hiram Larangeira; Fryssira, Helen; Isidor, Bertrand; Jauch, Anna; Joubert, Madeleine; Lachmeijer, Augusta M. A.; Zweier, Christiane; Moog, Ute; et al. (Orphanet Journal of Rare Diseases, 2014)
Segmental Xp22.2 monosomy or a heterozygous HCCS mutation is associated with the microphthalmia with linear skin defects (MLS) or MIDAS (microphthalmia, dermal aplasia, and sclerocornea) syndrome, an X-linked disorder with male lethality. HCCS encodes the holocytochrome c-type synthase involved in mitochondrial oxidative phosphorylation (OXPHOS) and programmed cell death.We characterized the X-chromosomal abnormality encompassing HCCS or an intragenic mutation in this gene in six new female patients with an MLS phenotype by cytogenetic analysis, fluorescence in situ hybridization, sequencing, and quantitative real-time PCR. The X chromosome inactivation (XCI) pattern was determined and clinical data of the patients were reviewed.Two terminal Xp deletions of >= 11.2 Mb, two submicroscopic copy number losses, one of 850 kb and one of >= 3 Mb, all covering HCCS, 1 nonsense, and one mosaic 2-bp deletion in HCCS are reported. All females had a completely (>98:2) or slightly skewed (82:18) XCI pattern. The most consistent clinical features were microphthalmia/anophthalmia and sclerocornea/corneal opacity in all patients and congenital linear skin defects in 4/6. Additional manifestations included various ocular anomalies, cardiac defects, brain imaging abnormalities, microcephaly, postnatal growth retardation, and facial dysmorphism. However, no obvious clinical sign was observed in three female carriers who were relatives of one patient.Our findings showed a wide phenotypic spectrum ranging from asymptomatic females with an HCCS mutation to patients with a neonatal lethal MLS form. Somatic mosaicism and the different ability of embryonic cells to cope with an OXPHOS defect and/or enhanced cell death upon HCCS deficiency likely underlie the great variability in phenotypes.
EVALuna2:9233

Clinical validation of genetic variants associated with in vitro chemotherapy-related lymphoblastoid cell toxicity - Fasching, Peter; Häberle, Lothar; Rack, Brigitte; Li, Liang; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, Julie M.; Rübner, Matthias; Jenkins, Gergory; Fridley, Brooke; et al. (Oncotarget, 2017)
Hematotoxicity is one of the major side effects of chemotherapy. The aim of this study was to examine the association between single nucleotide polymorphisms (SNPs) and hematotoxicity in breast cancer patients in a subset of patients of the SUCCESS prospective phase III chemotherapy study. All patients (n = 1678) received three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) followed by three cycles of docetaxel or docetaxel/gemcitabine, depending on randomization. Germline DNA was genotyped for 246 SNPs selected from a previous genome-wide association study (GWAS) in a panel of lymphoblastoid cell lines, with gemcitabine toxicity as the phenotype. All SNPs were tested for their value in predicting grade 3 or 4 neutropenic or leukopenic events (NLEs). Their prognostic value in relation to overall survival and disease-free survival was also tested. None of the SNPs was found to be predictive for NLEs during treatment with docetaxel/gemcitabine. Two SNPs in and close to the PIGB gene significantly improved the prediction of NLEs after FEC, in addition to the factors of age and body surface area. The top SNP (rs12050587) had an odds ratio of 1.38 per minor allele (95% confidence interval, 1.17 to 1.62). No associations were identified for predicting disease-free or overall survival. Genetic variance in the PIGB gene may play a role in determining interindividual differences in relation to hematotoxicity after FEC chemotherapy.
EVALuna2:9381

CLP1 founder mutation links tRNA splicing and maturation to cerebellar development and neurodegeneration - Schaffer, Ashleigh E.; Eggens, Veerle R. C.; Caglayan, Ahmet Okay; Reuter, Miriam; Scott, Eric; Coufal, Nicole G.; Silhavy, Jennifer L.; Xue, Yuanchao; Kayserili, Hulya; Yasuno, Katsuhito; Rosti, Rasim Ozgur; Abdellateef, Mostafa; et al. (Cell, 2014)
Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of more than 2,000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit 1 (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA, and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre-tRNA cleavage. Germline clp1 null zebrafish showed cerebellar neurodegeneration that was rescued by wild-type, but not mutant, human CLP1 expression. Patient-derived induced neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated an oxidative stress-induced reduction in cell survival. Our data link tRNA maturation to neuronal development and neurodegeneration through defective CLP1 function in humans.
EVALuna2:9222

Clubbing of Fingers and Nails in Primary Hypertrophic Osteoarthropathy Type 1. - Pauly, Melissa; Hüffmeier, Ulrike; Schmitt-Haendle, Matthias (Deutsches Ärzteblatt international, 2024)
EVALuna2:585165

Combined Associations of a Polygenic Risk Score and Classical Risk Factors With Breast Cancer Risk - Kapoor, Pooja Middha; Mavaddat, Nasim; Choudhury, Parichoy Pal; Wilcox, Amber N.; Lindström, Sara; Behrens, Sabine; Michailidou, Kyriaki; Dennis, Joe; Bolla, Manjeet K.; Wang, Qin; Jung, Audrey; Abu-Ful, Zomoroda; et al. (Journal of the National Cancer Institute, 2021)
We evaluated the joint associations between a new 313-variant PRS (PRS313) and questionnaire-based breast cancer risk factors for women of European ancestry, using 72 284 cases and 80 354 controls from the Breast Cancer Association Consortium. Interactions were evaluated using standard logistic regression and a newly developed case-only method for breast cancer risk overall and by estrogen receptor status. After accounting for multiple testing, we did not find evidence that per-standard deviation PRS313 odds ratio differed across strata defined by individual risk factors. Goodness-of-fit tests did not reject the assumption of a multiplicative model between PRS313 and each risk factor. Variation in projected absolute lifetime risk of breast cancer associated with classical risk factors was greater for women with higher genetic risk (PRS313 and family history) and, on average, 17.5% higher in the highest vs lowest deciles of genetic risk. These findings have implications for risk prevention for women at increased risk of breast cancer.
CRIS-Team Scopus Importer:2021-03-26

Common genetic determinants of intraocular pressure and primary open-angle glaucoma - Van Koolwijk, Leonieke M. E.; Ramdas, Wishal D.; Ikram, M. Kamran; Jansonius, Nomdo M.; Pasutto, Francesca; Hysi, Pirro G.; Macgregor, Stuart; Janssen, Sarah F.; Hewitt, Alex W.; Viswanathan, Ananth C.; Ten Brink, Jacoline B.; Hosseini, S. Mohsen; et al. (PLoS Genetics, 2012)
Intraocular pressure (IOP) is a highly heritable risk factor for primary open-angle glaucoma and is the only target for current glaucoma therapy. The genetic factors which determine IOP are largely unknown. We performed a genome-wide association study for IOP in 11,972 participants from 4 independent population-based studies in The Netherlands. We replicated our findings in 7,482 participants from 4 additional cohorts from the UK, Australia, Canada, and the Wellcome Trust Case-Control Consortium 2/Blue Mountains Eye Study. IOP was significantly associated with rs11656696, located in GAS7 at 17p13.1 (p=1.4×10(-8)), and with rs7555523, located in TMCO1 at 1q24.1 (p=1.6×10(-8)). In a meta-analysis of 4 case-control studies (total N = 1,432 glaucoma cases), both variants also showed evidence for association with glaucoma (p=2.4×10(-2) for rs11656696 and p=9.1×10(-4) for rs7555523). GAS7 and TMCO1 are highly expressed in the ciliary body and trabecular meshwork as well as in the lamina cribrosa, optic nerve, and retina. Both genes functionally interact with known glaucoma disease genes. These data suggest that we have identified two clinically relevant genes involved in IOP regulation.
EVALuna2:9127

Common genetic variants associated with open-angle glaucoma - Ramdas, Wishal D.; Van Koolwijk, Leonieke M. E.; Lemij, Hans G.; Pasutto, Francesca; Cree, Angela J.; Thorleifsson, Gudmar; Janssen, Sarah F.; Jacoline, Ten Brink; Amin, Najaf; Rivadeneira, Fernando; Wolfs, Roger C. W.; Walters, G. Bragi; et al. (Human Molecular Genetics, 2011)
Open-angle glaucoma (glaucoma) is a major eye disorder characterized by optic disc pathology. Recent genome-wide association studies identified new loci associated with clinically relevant optic disc parameters, such as the optic disc area and vertical cup-disc ratio (VCDR). We examined to what extent these loci are involved in glaucoma. The loci studied include ATOH7, CDC7/TGFBR3 and SALL1 for optic disc area, and CDKN2B, SIX1, SCYL1/LTBP3, CHEK2, ATOH7 and DCLK1 for VCDR. We performed a meta-analysis using data from six independent studies including: the Rotterdam Study (n= 5736), Genetic Research in Isolated Populations combined with Erasmus Rucphen Family study (n= 1750), Amsterdam Glaucoma Study (n= 296) and cohorts from Erlangen and Tübingen (n= 1363), Southampton (n= 702) and deCODE (n= 36 151) resulting in a total of 3161 glaucoma cases and 42 837 controls. Of the eight loci, we found significant evidence (P= 1.41 × 10(-8)) for the association of CDKN2B with glaucoma [odds ratio (OR) for those homozygous for the risk allele: 0.76; 95% confidence interval (CI): 0.70-0.84], for the role of ATOH7 (OR: 1.28; 95% CI: 1.12-1.47) and for SIX1 (OR: 1.20; 95% CI: 1.10-1.31) when adjusting for the number of tested loci. Furthermore, there was a borderline significant association of CDC7/TGFBR3 and SALL1 (both P= 0.04) with glaucoma. In conclusion, we found consistent evidence for three common variants (CDKN2B, ATOH7 and SIX1) significantly associated with glaucoma. These findings may shed new light on the pathophysiological protein pathways leading to glaucoma, and point to pathways involved in the growth and development of the optic nerve.
EVALuna2:9086

Common Genetic Variation In Cellular Transport Genes and Epithelial Ovarian Cancer (EOC) Risk - Chornokur, Ganna; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Amankwah, Ernest K.; Qu, Xiaotao; Tsai, Ya-Yu; Jim, Heather S. L.; Chen, Zhihua; Chen, Ann Y.; Permuth-Wey, Jennifer; et al. (PLoS ONE, 2015)
Defective cellular transport processes can lead to aberrant accumulation of trace elements, iron, small molecules and hormones in the cell, which in turn may promote the formation of reactive oxygen species, promoting DNA damage and aberrant expression of key regulatory cancer genes. As DNA damage and uncontrolled proliferation are hallmarks of cancer, including epithelial ovarian cancer (EOC), we hypothesized that inherited variation in the cellular transport genes contributes to EOC risk.In total, DNA samples were obtained from 14,525 case subjects with invasive EOC and from 23,447 controls from 43 sites in the Ovarian Cancer Association Consortium (OCAC). Two hundred seventy nine SNPs, representing 131 genes, were genotyped using an Illumina Infinium iSelect BeadChip as part of the Collaborative Oncological Gene-environment Study (COGS). SNP analyses were conducted using unconditional logistic regression under a log-additive model, and the FDR q<0.2 was applied to adjust for multiple comparisons.The most significant evidence of an association for all invasive cancers combined and for the serous subtype was observed for SNP rs17216603 in the iron transporter gene HEPH (invasive: OR = 0.85, P = 0.00026; serous: OR = 0.81, P = 0.00020); this SNP was also associated with the borderline/low malignant potential (LMP) tumors (P = 0.021). Other genes significantly associated with EOC histological subtypes (p<0.05) included the UGT1A (endometrioid), SLC25A45 (mucinous), SLC39A11 (low malignant potential), and SERPINA7 (clear cell carcinoma). In addition, 1785 SNPs in six genes (HEPH, MGST1, SERPINA, SLC25A45, SLC39A11 and UGT1A) were imputed from the 1000 Genomes Project and examined for association with INV EOC in white-European subjects. The most significant imputed SNP was rs117729793 in SLC39A11 (per allele, OR = 2.55, 95% CI = 1.5-4.35, p = 5.66x10-4).These results, generated on a large cohort of women, revealed associations between inherited cellular transport gene variants and risk of EOC histologic subtypes.
EVALuna2:9283

Common germline polymorphisms associated with breast cancer-specific survival - Pirie, Ailith; Guo, Qi; Kraft, Peter; Canisius, Sander; Eccles, Diana M.; Rahman, Nazneen; Nevanlinna, Heli; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; et al. (Breast Cancer Research, 2015)
Previous studies have identified common germline variants nominally associated with breast cancer survival. These associations have not been widely replicated in further studies. The purpose of this study was to evaluate the association of previously reported SNPs with breast cancer-specific survival using data from a pooled analysis of eight breast cancer survival genome-wide association studies (GWAS) from the Breast Cancer Association Consortium.A literature review was conducted of all previously published associations between common germline variants and three survival outcomes: breast cancer-specific survival, overall survival and disease-free survival. All associations that reached the nominal significance level of P value <0.05 were included. Single nucleotide polymorphisms that had been previously reported as nominally associated with at least one survival outcome were evaluated in the pooled analysis of over 37,000 breast cancer cases for association with breast cancer-specific survival. Previous associations were evaluated using a one-sided test based on the reported direction of effect.Fifty-six variants from 45 previous publications were evaluated in the meta-analysis. Fifty-four of these were evaluated in the full set of 37,954 breast cancer cases with 2,900 events and the two additional variants were evaluated in a reduced sample size of 30,000 samples in order to ensure independence from the previously published studies. Five variants reached nominal significance (P <0.05) in the pooled GWAS data compared to 2.8 expected under the null hypothesis. Seven additional variants were associated (P <0.05) with ER-positive disease.Although no variants reached genome-wide significance (P <5 x 10(-8)), these results suggest that there is some evidence of association between candidate common germline variants and breast cancer prognosis. Larger studies from multinational collaborations are necessary to increase the power to detect associations, between common variants and prognosis, at more stringent significance levels.
EVALuna2:9296

Common non-synonymous SNPs associated with breast cancer susceptibility: findings from the Breast Cancer Association Consortium - Milne, Roger L.; Burwinkel, Barbara; Michailidou, Kyriaki; Arias-Perez, Jose-Ignacio; Pilar Zamora, M.; Menendez-Rodriguez, Primitiva; Hardisson, David; Mendiola, Marta; Gonzalez-Neira, Anna; Pita, Guillermo; Rosario Alonso, M.; Dennis, Joe; et al. (Human Molecular Genetics, 2014)
Candidate variant association studies have been largely unsuccessful in identifying common breast cancer susceptibility variants, although most studies have been underpowered to detect associations of a realistic magnitude. We assessed 41 common non-synonymous single-nucleotide polymorphisms (nsSNPs) for which evidence of association with breast cancer risk had been previously reported. Case-control data were combined from 38 studies of white European women (46 450 cases and 42 600 controls) and analyzed using unconditional logistic regression. Strong evidence of association was observed for three nsSNPs: ATXN7-K264R at 3p21 [rs1053338, per allele OR = 1.07, 95% confidence interval (CI) = 1.04-1.10, P = 2.9 × 10(-6)], AKAP9-M463I at 7q21 (rs6964587, OR = 1.05, 95% CI = 1.03-1.07, P = 1.7 × 10(-6)) and NEK10-L513S at 3p24 (rs10510592, OR = 1.10, 95% CI = 1.07-1.12, P = 5.1 × 10(-17)). The first two associations reached genome-wide statistical significance in a combined analysis of available data, including independent data from nine genome-wide association studies (GWASs): for ATXN7-K264R, OR = 1.07 (95% CI = 1.05-1.10, P = 1.0 × 10(-8)); for AKAP9-M463I, OR = 1.05 (95% CI = 1.04-1.07, P = 2.0 × 10(-10)). Further analysis of other common variants in these two regions suggested that intronic SNPs nearby are more strongly associated with disease risk. We have thus identified a novel susceptibility locus at 3p21, and confirmed previous suggestive evidence that rs6964587 at 7q21 is associated with risk. The third locus, rs10510592, is located in an established breast cancer susceptibility region; the association was substantially attenuated after adjustment for the known GWAS hit. Thus, each of the associated nsSNPs is likely to be a marker for another, non-coding, variant causally related to breast cancer risk. Further fine-mapping and functional studies are required to identify the underlying risk-modifying variants and the genes through which they act.
EVALuna2:9242

Common RUNX3 missense variant contributes to psoriatic arthritis by affecting splicing and modifying signaling, activation and differentiation of T-cells - Hüffmeier, Ulrike; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Bowes, J.; Kirchner, P.; Giardina, E.; Korendowych, E.; Ekici, Arif Bülent; Ho, P.; Behrens, F.; Koehm, M.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Common RUNX3 missense variant contributes to psoriatic arthritis by modifying differentiation of CD8(+) T-cells - Kerker, Iris; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Vasileiou, Georgia; Bowes, John; Kirchner, Philipp; Becker, Ina; Giardina, Emiliano; Korendowych, Eleanor; Ekici, Arif Bülent; Ho, Pauline; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Common variants at the CHEK2 gene locus and risk of epithelial ovarian cancer - Lawrenson, Kate; Iversen, Edwin S.; Tyrer, Jonathan; Weber, Rachel Palmieri; Concannon, Patrick; Hazelett, Dennis J.; Li, Qiyuan; Marks, Jeffrey R.; Berchuck, Andrew; Lee, Janet M.; Aben, Katja K. H.; Anton-Culver, Hoda; et al. (Carcinogenesis, 2015)
Genome-wide association studies have identified 20 genomic regions associated with risk of epithelial ovarian cancer (EOC), but many additional risk variants may exist. Here, we evaluated associations between common genetic variants [single nucleotide polymorphisms (SNPs) and indels] in DNA repair genes and EOC risk. We genotyped 2896 common variants at 143 gene loci in DNA samples from 15 397 patients with invasive EOC and controls. We found evidence of associations with EOC risk for variants at FANCA, EXO1, E2F4, E2F2, CREB5 and CHEK2 genes (P <= 0.001). The strongest risk association was for CHEK2 SNP rs17507066 with serous EOC (P = 4.74 x 10(-7)). Additional genotyping and imputation of genotypes from the 1000 genomes project identified a slightly more significant association for CHEK2 SNP rs6005807 (r (2) with rs17507066 = 0.84, odds ratio (OR) 1.17, 95% CI 1.11-1.24, P = 1.1×10(-7)). We identified 293 variants in the region with likelihood ratios of less than 1:100 for representing the causal variant. Functional annotation identified 25 candidate SNPs that alter transcription factor binding sites within regulatory elements active in EOC precursor tissues. In The Cancer Genome Atlas dataset, CHEK2 gene expression was significantly higher in primary EOCs compared to normal fallopian tube tissues (P = 3.72×10(-8)). We also identified an association between genotypes of the candidate causal SNP rs12166475 (r (2) = 0.99 with rs6005807) and CHEK2 expression (P = 2.70×10(-8)). These data suggest that common variants at 22q12.1 are associated with risk of serous EOC and CHEK2 as a plausible target susceptibility gene.
EVALuna2:9297

Comparison of 6q25 breast cancer hits from Asian and European genome wide association studies in the Breast Cancer Association consortium (BCAC) - Hein, Rebecca; Maranian, Melanie; Hopper, John L.; Kapuscinski, Miroslaw K.; Southey, Melissa C.; Park, Daniel J.; Schmidt, Marjanka K.; Broeks, Annegien; Hogervorst, Frans B. L.; Bueno-De-Mesquit, H. Bas; Muir, Kenneth R.; Lophatananon, Artitaya; et al. (PLoS ONE, 2012)
The 6q25.1 locus was first identified via a genome-wide association study (GWAS) in Chinese women and marked by single nucleotide polymorphism (SNP) rs2046210, approximately 180 Kb upstream of ESR1. There have been conflicting reports about the association of this locus with breast cancer in Europeans, and a GWAS in Europeans identified a different SNP, tagged here by rs12662670. We examined the associations of both SNPs in up to 61,689 cases and 58,822 controls from forty-four studies collaborating in the Breast Cancer Association Consortium, of which four studies were of Asian and 39 of European descent. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI). Case-only analyses were used to compare SNP effects in Estrogen Receptor positive (ER+) versus negative (ER-) tumours. Models including both SNPs were fitted to investigate whether the SNP effects were independent. Both SNPs are significantly associated with breast cancer risk in both ethnic groups. Per-allele ORs are higher in Asian than in European studies [rs2046210: OR (A/G) = 1.36 (95% CI 1.26-1.48), p = 7.6×10-14 in Asians and 1.09 (95% CI 1.07-1.11), p = 6.8×10-18 in Europeans. rs12662670: OR (G/T) = 1.29 (95% CI 1.19-1.41), p = 1.2×10-9 in Asians and 1.12 (95% CI 1.08-1.17), p = 3.8×10-9 in Europeans]. SNP rs2046210 is associated with a significantly greater risk of ER- than ER+ tumours in Europeans [OR (ER-) = 1.20 (95% CI 1.15-1.25), p = 1.8×10-17 versus OR (ER+) = 1.07 (95% CI 1.04-1.1), p = 1.3×10-7, pheterogeneity = 5.1×10-6]. In these Asian studies, by contrast, there is no clear evidence of a differential association by tumour receptor status. Each SNP is associated with risk after adjustment for the other SNP. These results suggest the presence of two variants at 6q25.1 each independently associated with breast cancer risk in Asians and in Europeans. Of these two, the one tagged by rs2046210 is associated with a greater risk of ER- tumours. © 2012 Hein et al.
CRIS-Team Scopus Importer:2021-07-19

Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis - Hübner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif Bülent; Fasching, Peter; Beckmann, Matthias; Rübner, Matthias; Burghaus, Stefanie (Reproductive Biomedicine Online, 2021)
Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method (P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate (P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CcfDNA; Circulating cell-free DNA; Endometriosis; Mitochondrial DNA; Plasma; Quantification

Comprehensive EHMT1 variants analysis broadens genotype-phenotype associations and molecular mechanisms in Kleefstra syndrome - Rots, Dmitrijs; Bouman, Arianne; Yamada, Ayumi; Levy, Michael; Dingemans, Alexander J.M.; de Vries, Bert B.A.; Ruiterkamp-Versteeg, Martina; de Leeuw, Nicole; Ockeloen, Charlotte W.; Pfundt, Rolph; de Boer, Elke; Kummeling, Joost; et al. (American Journal of Human Genetics, 2024)
The shift to a genotype-first approach in genetic diagnostics has revolutionized our understanding of neurodevelopmental disorders, expanding both their molecular and phenotypic spectra. Kleefstra syndrome (KLEFS1) is caused by EHMT1 haploinsufficiency and exhibits broad clinical manifestations. EHMT1 encodes euchromatic histone methyltransferase-1—a pivotal component of the epigenetic machinery. We have recruited 209 individuals with a rare EHMT1 variant and performed comprehensive molecular in silico and in vitro testing alongside DNA methylation (DNAm) signature analysis for the identified variants. We (re)classified the variants as likely pathogenic/pathogenic (molecularly confirming Kleefstra syndrome) in 191 individuals. We provide an updated and broader clinical and molecular spectrum of Kleefstra syndrome, including individuals with normal intelligence and familial occurrence. Analysis of the EHMT1 variants reveals a broad range of molecular effects and their associated phenotypes, including distinct genotype-phenotype associations. Notably, we showed that disruption of the “reader” function of the ankyrin repeat domain by a protein altering variant (PAV) results in a KLEFS1-specific DNAm signature and milder phenotype, while disruption of only “writer” methyltransferase activity of the SET domain does not result in KLEFS1 DNAm signature or typical KLEFS1 phenotype. Similarly, N-terminal truncating variants result in a mild phenotype without the DNAm signature. We demonstrate how comprehensive variant analysis can provide insights into pathogenesis of the disorder and DNAm signature. In summary, this study presents a comprehensive overview of KLEFS1 and EHMT1, revealing its broader spectrum and deepening our understanding of its molecular mechanisms, thereby informing accurate variant interpretation, counseling, and clinical management.
CRIS-Team Scopus Importer:2024-08-09
Keywords: DNA methylation; EHMT1; H3K9; Kleefstra syndrome; NDD; neurodevelopmental disorders

Comprehensive genetic assessment of the ESR1 locus identifies a risk region for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Dennis, Joe; Attia, John; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ashton, Katie; Proietto, Tony; Otton, Geoffrey; et al. (Endocrine-Related Cancer, 2015)
Excessive exposure to estrogen is a well-established risk factor for endometrial cancer (EC), particularly for cancers of endometrioid histology. The physiological function of estrogen is primarily mediated by estrogen receptor alpha, encoded by ESR1. Consequently, several studies have investigated whether variation at the ESR1 locus is associated with risk of EC, with conflicting results. We performed comprehensive fine-mapping analyses of 3633 genotyped and imputed single nucleotide polymorphisms (SNPs) in 6607 EC cases and 37 925 controls. There was evidence of an EC risk signal located at a potential alternative promoter of the ESR1 gene (lead SNP rs79575945, P=1.86×10(-5)), which was stronger for cancers of endometrioid subtype (P=3.76×10(-6)). Bioinformatic analysis suggests that this risk signal is in a functionally important region targeting ESR1, and eQTL analysis found that rs79575945 was associated with expression of SYNE1, a neighbouring gene. In summary, we have identified a single EC risk signal located at ESR1, at study-wide significance. Given SNPs located at this locus have been associated with risk for breast cancer, also a hormonally driven cancer, this study adds weight to the rationale for performing informed candidate fine-scale genetic studies across cancer types.
EVALuna2:9261

Comprehensive screening for mutations associated with colorectal cancer in unselected cases reveals penetrant and nonpenetrant mutations - Kraus, Cornelia; Rau, Tilman; Lux, Philipp; Erlenbach-Wuensch, Katharina; Loehr, Sabine; Krumbiegel, Mandy; Thiel, Christian; Stoehr, Robert; Agaimy, Abbas; Croner, Roland S.; Stürzl, Michael; Hohenberger, Werner; et al. (International Journal of Cancer, 2015)
Germline mutation testing in patients with colorectal cancer (CRC) is offered only to a subset of patients with a clinical presentation or tumor histology suggestive of familial CRC syndromes, probably underestimating familial CRC predisposition. The aim of our study was to determine whether unbiased screening of newly diagnosed CRC cases with next generation sequencing (NGS) increases the overall detection rate of germline mutations. We analyzed 152 consecutive CRC patients for germline mutations in 18 CRC-associated genes using NGS. All patients were also evaluated for Bethesda criteria and all tumors were investigated for microsatellite instability, immunohistochemistry for mismatch repair proteins and the BRAF*V600E somatic mutation. NGS based sequencing identified 27 variants in 9 genes in 23 out of 152 patients studied (18%). Three of them were already reported as pathogenic and 12 were class 3 germline variants with an uncertain prediction of pathogenicity. Only 1 of these patients fulfilled Bethesda criteria and had a microsatellite instable tumor and an MLH1 germline mutation. The others would have been missed with current approaches: 2 with a MSH6 premature termination mutation and 12 uncertain, potentially pathogenic class 3 variants in APC, MLH1, MSH2, MSH6, MSH3 and MLH3. The higher NGS mutation detection rate compared with current testing strategies based on clinicopathological criteria is probably due to the large genetic heterogeneity and overlapping clinical presentation of the various CRC syndromes. It can also identify apparently nonpenetrant germline mutations complicating the clinical management of the patients and their families.
EVALuna2:6598

Confirmation and expansion of the phenotype of the TCEAL1-related neurodevelopmental disorder - Albuainain, Fatimah; Shi, Yuwei; Lor-Zade, Sarah; Hüffmeier, Ulrike; Pauly, Melissa; Reis, André; Faivre, Laurence; Maraval, Julien; Bruel, Ange Line; Them, Frédéric Tran Mau; Haack, Tobias B.; Grasshoff, Ute; et al. (European Journal of Human Genetics, 2024)
Numerous contiguous gene deletion syndromes causing neurodevelopmental disorders have previously been defined using cytogenetics for which only in the current genomic era the disease-causing genes have become elucidated. One such example is deletion at Xq22.2, previously associated with a neurodevelopmental disorder which has more recently been found to be caused by de novo loss-of-function variants in TCEAL1. So far, a single study reported six unrelated individuals with this monogenetic disorder, presenting with syndromic features including developmental delay especially affecting expressive speech, intellectual disability, autistic-like behaviors, hypotonia, gait abnormalities and mild facial dysmorphism, in addition to ocular, gastrointestinal, and immunologic abnormalities. Here we report on four previously undescribed individuals, including two adults, with de novo truncating variants in TCEAL1, identified through trio exome or genome sequencing, further delineating the phenotype of the TCEAL1-related disorder. Whereas overall we identify similar features compared to the original report, we also highlight features in our adult individuals including hyperphagia, obesity, and endocrine abnormalities including hyperinsulinemia, hyperandrogenemia, and polycystic ovarian syndrome. X chromosome inactivation and RNA-seq studies further provide functional insights in the molecular mechanisms. Together this report expands the phenotypic and molecular spectrum of the TCEAL1-related disorder which will be useful for counseling of newly identified individuals and their families.
CRIS-Team Scopus Importer:2024-01-19

Consortium analysis of gene and gene-folate interactions in purine and pyrimidine metabolism pathways with ovarian carcinoma risk - Kelemen, Linda E.; Terry, Kathryn L.; Goodman, Marc T.; Webb, Penelope M.; Bandera, Elisa V.; Mcguire, Valerie; Rossing, Mary Anne; Wang, Qinggang; Dicks, Ed; Tyrer, Jonathan P.; Song, Honglin; Kupryjanczyk, Jolanta; et al. (Molecular Nutrition & Food Research, 2014)
We reevaluated previously reported associations between variants in pathways of one-carbon (1-C) (folate) transfer genes and ovarian carcinoma (OC) risk, and in related pathways of purine and pyrimidine metabolism, and assessed interactions with folate intake.Odds ratios (OR) for 446 genetic variants were estimated among 13,410 OC cases and 22,635 controls, and among 2281 cases and 3444 controls with folate information. Following multiple testing correction, the most significant main effect associations were for dihydropyrimidine dehydrogenase (DPYD) variants rs11587873 (OR = 0.92; p = 6 × 10(-5)) and rs828054 (OR = 1.06; p = 1 × 10(-4)). Thirteen variants in the pyrimidine metabolism genes, DPYD, DPYS, PPAT, and TYMS, also interacted significantly with folate in a multivariant analysis (corrected p = 9.9 × 10(-6)) but collectively explained only 0.2% of OC risk. Although no other associations were significant after multiple testing correction, variants in SHMT1 in 1-C transfer, previously reported with OC, suggested lower risk at higher folate (p(interaction) = 0.03-0.006).Variation in pyrimidine metabolism genes, particularly DPYD, which was previously reported to be associated with OC, may influence risk; however, stratification by folate intake is unlikely to modify disease risk appreciably in these women. SHMT1 SNP-by-folate interactions are plausible but require further validation. Polymorphisms in selected genes in purine metabolism were not associated with OC.
EVALuna2:9231

Correction: Expanded phenotypic spectrum of neurodevelopmental and neurodegenerative disorder Bryant-Li-Bhoj syndrome with 38 additional individuals (European Journal of Human Genetics, (2024), 32, 8, (928-937), 10.1038/s41431-024-01610-1) - Layo-Carris, Dana E.; Lubin, Emily E.; Sangree, Annabel K.; Clark, Kelly J.; Durham, Emily L.; Gonzalez, Elizabeth M.; Smith, Sarina; Angireddy, Rajesh; Wang, Xiao Min; Weiss, Erin; Toutain, Annick; Mendoza-Londono, Roberto; et al. (European Journal of Human Genetics, 2024)
An author was not named. The missing author is: “Annick Toutain” Her affiliation is: 27 Service de Génétique, CHU de Tours, Tours, France. 28 UMR1253, iBrain, Inserm, University of Tours, Tours, France.
CRIS-Team Scopus Importer:2024-08-09

Correction to: The recurrent missense mutation p.(Arg367Trp) in YARS1 causes a distinct neurodevelopmental phenotype (Journal of Molecular Medicine, (2021), 10.1007/s00109-021-02124-9) - Averdunk, Luisa; Sticht, Heinrich; Surowy, Harald; Luedecke, Hermann-Josef; Koch-Hogrebe, Margarete; Alsaif, Hessa S.; Kahrizi, Kimia; Alzaidan, Hamad; Alawam, Bashayer S.; Tohary, Mohamed; Kraus, Cornelia; Endele, Sabine; et al. (Journal of Molecular Medicine, 2021)
In the published original paper, Fig. 1 is incomplete. Only Fig. 1a is shown. This erratum corrects Fig. 1 and adds the missing panel 1 b-f to the article.
CRIS-Team Scopus Importer:2021-10-29

Correction to: Transient receptor potential ankyrin 1 promoter methylation and peripheral pain sensitivity in Crohn’s disease (Clinical Epigenetics, (2020), 12, 1, (1), 10.1186/s13148-019-0796-9) - Gombert, Sara; Rhein, Mathias; Winterpacht, Andreas; Münster, Tino; Hillemacher, Thomas; Leffler, Andreas; Frieling, Helge (Clinical Epigenetics, 2021)
An amendment to this paper has been published and can be accessed via the original article.
CRIS-Team Scopus Importer:2021-04-09

Cost effectiveness of bilateral risk-reducing mastectomy and salpingo-oophorectomy - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Csorba, Roland; Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (European Journal of Medical Research, 2019)
BACKGROUND: Growing demand for risk-reducing surgery in individuals with inherited susceptibility to cancer leads to the question whether these procedures are cost effective for the executing hospitals. This study compared the clinical costs for bilateral risk-reducing mastectomy (BRRM) with and without different types of reconstruction, risk-reducing salpingo-oophorectomy (RRSO), and their combinations with corresponding reimbursements in the statutory health-care system in Germany. PATIENTS AND METHODS: Real total costs of care for BRRM with and without reconstruction, RRSO, and their combinations were calculated as the sum of all personnel and technical costs. These costs calculated in a German University hospital were compared with the sum of all reimbursements in the German DRG-based health-care system. RESULTS: While sole RRSO, BRRM without reconstruction, and BRRM with secondary DIEP (deep inferior epigastric perforator)-reconstruction still result in a small benefit, we even found shortfalls for the hospital with all other prophylactic operations under consideration. The calculated deficits were especially high for BRRM with implant-based breast reconstruction and for combined operations when the risk reduction is achieved with a minimum of separate operations. CONCLUSIONS: Risk-reducing surgery in BRCA-mutation carriers is frequently not cost-covering for the executing hospitals in the German health-care system. Thus, appropriate concepts are required to ensure a nationwide care.
CRIS-Team Scopus Importer:2019-09-24
Keywords: BRCA; Breast cancer; Cost effectiveness; Genetic counseling; Ovarian cancer

Cost-effectiveness of risk-reducing surgeries in preventing hereditary breast and ovarian cancer - Schrauder, Michael G.; Brunel-Geuder, Lisa; Häberle, Lothar; Wunderle, Marius; Hoyer, Juliane; Wiesmann da Silva Reis, André; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lux, Michael P. (BREAST, 2017)
Risk-reducing surgeries are a feasible option for mitigating the risk in individuals with inherited susceptibility to cancer, but are the procedures cost-effective in the current health-care system in Germany? This study compared the health-care costs for bilateral risk-reducing mastectomy (BRRM) and risk-reducing (bilateral) salpingo-oophorectomy (RRSO) with cancer treatment costs that could potentially be prevented.The analysis is based on interdisciplinary consultations with individuals with a high familial risk for breast and ovarian cancer at the University Breast Center for Franconia (Germany) between 2009 and 2013 (370 consultations; 44 patients with BRCA1 mutations and 26 with BRCA2 mutations). Health-care costs for risk-reducing surgeries in BRCA mutation carriers were calculated as reimbursements in the German diagnosis-related groups (DRG) hospital pricing system. These costs for the health-care system were compared with the potential cancer treatment costs that could possibly be prevented by risk-reducing surgeries.Long-term health-care costs can be reduced by risk-reducing surgeries after genetic testing in BRCA mutation carriers. The health-care system in Germany would have saved EUR 136,295 if BRRM had been performed and EUR 791,653 if RRSO had been performed before the development of cancer in only 50% of the 70 mutation carriers seen in our center. Moreover, in patients with combined RRSO and BRRM (without breast reconstruction), one further life-year for a 40-year-old BRCA mutation carrier would cost EUR 2,183.Intensive care, including risk-reducing surgeries in BRCA mutation carriers, is cost-effective from the point of view of the health-care system in Germany.
EVALuna2:9369

CRISPR/Cas9-mediated generation of hESC lines with homozygote and heterozygote p.R331W mutation in CTBP1 to model HADDTS syndrome - Akdas, Enes Yagiz; Turan, Sören; Guhathakurta, Debarpan; Ekici, Arif Bülent; Salar, Seda; Lie, Dieter Chichung; Winner, Beate; Fejtová, Anna (Stem Cell Research, 2023)
C-terminal Binding Protein 1 (CTBP1) is a ubiquitously expressed transcriptional co-repressor and membrane trafficking regulator. A recurrent de novo c.991C>T mutation in CTBP1 leads to expression of p.R331W CTBP1 and causes hypotonia, ataxia, developmental delay, and tooth enamel defects syndrome (HADDTS), a rare early onset neurodevelopmental disorder. We generated hESCs lines with heterozygote and homozygote c.991C>T in CTBP1 using CRISPR/Cas9 genome editing and validated them for genetic integrity, off-target mutations, and pluripotency. They will be useful for investigation of HADDTS pathophysiology and for screening for potential therapeutics.
CRIS-Team Scopus Importer:2023-01-20

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.
CRIS-Team Scopus Importer:2020-07-24

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B(+/-) hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B(+/-) hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome. - Turan, Soeren; Winner, Beate; Winner, Beate; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, Andre; Lie, Dieter Chichung (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

CRISPR/Cas9-mediated knock-out of krasG12D mutated pancreatic cancer cell lines - Lentsch, Eva; Li, Lifei; Pfeffer, Sina; Ekici, Arif Bülent; Taher, Leila; Pilarsky, Christian; Grützmann, Robert (International Journal of Molecular Sciences, 2019)
In 90% of pancreatic ductal adenocarcinoma cases, genetic alteration of the proto-oncogene Kras has occurred, leading to uncontrolled proliferation of cancerous cells. Targeting Kras has proven to be difficult and the battle against pancreatic cancer is ongoing. A promising approach to combat cancer was the discovery of the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) system, which can be used to genetically modify cells. To assess the potential of a CRISPR/CRISPR-associated protein 9 (Cas9) method to eliminate Kras mutations in cells, we aimed to knock-out the c.35G>A (p.G12D) Kras mutation. Therefore, three cell lines with a heterozygous Kras mutation (the human cell lines SUIT-2 and Panc-1 and the cell line TB32047 from a KPC mouse model) were used. After transfection, puromycin selection and single-cell cloning, proteins from two negative controls and five to seven clones were isolated to verify the knock-out and to analyze changes in key signal transduction proteins. Western blots showed a specific knock-out in the KrasG12D protein, but wildtype Kras was expressed by all of the cells. Signal transduction analysis (for Erk, Akt, Stat3, AMPKα, and c-myc) revealed expression levels similar to the wildtype. The results described herein indicate that knocking-out the KrasG12D mutation by CRISPR/Cas9 is possible. Additionally, under regular growth conditions, the knock-out clones resembled wildtype cells.
CRIS-Team Scopus Importer:2019-11-26
Keywords: CRISPR/Cas9 system; G12D; Kras; Panc-1; Suit-2; TB32047

Crnkl1 is a highly selective regulator of intron-retaining HIV-1 and cellular mrnas - Xiao, Han; Wyler, Emanuel; Milek, Miha; Grewe, Bastian; Kirchner, Philipp; Ekici, Arif Bülent; Silva, Ana Beatriz Oliveira Villela; Jungnickl, Doris; Full, Florian; Thomas, Marco; Landthaler, Markus; Enßer, Armin; et al. (mBio, 2021)
The HIV-1 Rev protein is a nuclear export factor for unspliced and incom-pletely spliced HIV-1 RNAs. Without Rev, these intron-retaining RNAs are trapped in the nucleus. A genome-wide screen identified nine proteins of the spliceosome, which all enhanced expression from the HIV-1 unspliced RNA after CRISPR/Cas knockdown. Depletion of DHX38, WDR70, and four proteins of the Prp19-associated complex (ISY1, BUD31, XAB2, and CRNKL1) resulted in a more than 20-fold enhancement of unspliced HIV-1 RNA levels in the cytoplasm. Targeting of CRNKL1, DHX38, and BUD31 affected nuclear export efficiencies of the HIV-1 unspliced RNA to a much larger extent than splicing. Transcriptomic analyses further revealed that CRNKL1 also suppresses cyto-plasmic levels of a subset of cellular mRNAs, including some with selectively retained introns. Thus, CRNKL1-dependent nuclear retention is a novel cellular mechanism for the regulation of cytoplasmic levels of intron-retaining HIV-1 mRNAs, which HIV-1 may have harnessed to direct its complex splicing pattern. IMPORTANCE To regulate its complex splicing pattern, HIV-1 uses the adaptor protein Rev to shuttle unspliced or partially spliced mRNA from the nucleus to the cyto-plasm. In the absence of Rev, these RNAs are retained in the nucleus, but it is unclear why. Here we identify cellular proteins whose depletion enhances cytoplas-mic levels of the HIV-1 unspliced RNA. Depletion of one of them, CRNKL1, also increases cytoplasmic levels of a subset of intron-retaining cellular mRNA, suggesting that CRNKL1-dependent nuclear retention may be a basic cellular mechanism exploited by HIV-1.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Association; CRNKL1; Human immunodeficiency virus; Intron-retaining RNA; Nuclear retention; RNA splicing

Cross-Cancer Genome-Wide Association Study of Endometrial Cancer and Epithelial Ovarian Cancer Identifies Genetic Risk Regions Associated with Risk of Both Cancers - Glubb, Dylan M.; Thompson, Deborah J.; Aben, Katja K. H.; Alsulimani, Ahmad; Amant, Frederic; Annibali, Daniela; Attia, John; Barricarte, Aurelio; Beckmann, Matthias; Berchuck, Andrew; Bermisheva, Marina; Bernardini, Marcus Q.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2021)
Background: Accumulating evidence suggests a relationship between endometrial cancer and ovarian cancer. Independent genome-wide association studies (GWAS) for endometrial cancer and ovarian cancer have identified 16 and 27 risk regions, respectively, four of which overlap between the two cancers. We aimed to identify joint endometrial and ovarian cancer risk loci by performing a meta-analysis of GWAS summary statistics from these two cancers.
CRIS-Team WoS Importer:2021-03-12

CTCF variants in 31 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, N.; Blyth, M.; Prescott, K.; Bouman, A. M.; Brilstra, E. H.; Caliebe, A.; Ibitoye, R.; Chang, V. Y.; Gupta, A.; Le Guyader, G.; Jamra, R. A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2021-10-18

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L.; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genetics in Medicine, 2019)
Purpose: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). Methods: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. Results: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. Conclusion: We significantly broaden the mutational and clinical spectrum of CTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.
Keywords: chromatin organization; CTCF; Drosophila melanogaster; intellectual disability; neurodevelopmental disorders

CYP19A1 fine-mapping and Mendelian randomization: estradiol is causal for endometrial cancer - Thompson, Deborah J.; O'Mara, Tracy A.; Glubb, Dylan M.; Painter, Jodie N.; Cheng, Timothy; Folkerd, Elizabeth; Doody, Deborah; Dennis, Joe; Webb, Penelope M.; Gorman, Maggie; Martin, Lynn; Hodgson, Shirley; et al. (Endocrine-Related Cancer, 2016)
Candidate gene studies have reported CYP19A1 variants to be associated with endometrial cancer and with estradiol (E2) concentrations. We analyzed 2937 single nucleotide polymorphisms (SNPs) in 6608 endometrial cancer cases and 37 925 controls and report the first genome wide-significant association between endometrial cancer and a CYP19A1 SNP (rs727479 in intron 2, P=4.8×10(-11)). SNP rs727479 was also among those most strongly associated with circulating E2 concentrations in 2767 post-menopausal controls (P=7.4×10(-8)). The observed endometrial cancer odds ratio per rs727479 A-allele (1.15, CI=1.11-1.21) is compatible with that predicted by the observed effect on E2 concentrations (1.09, CI=1.03-1.21), consistent with the hypothesis that endometrial cancer risk is driven by E2. From 28 candidate-causal SNPs, 12 co-located with three putative gene-regulatory elements and their risk alleles associated with higher CYP19A1 expression in bioinformatical analyses. For both phenotypes, the associations with rs727479 were stronger among women with a higher BMI (Pinteraction=0.034 and 0.066 respectively), suggesting a biologically plausible gene-environment interaction.
EVALuna2:9315

Cystathionine beta-synthase as novel regulator of lymphangiogenesis - Hatami, Niloofar; Büttner, Christian; Bock, Felix; Simfors, Sara; Reis, André; Cursiefen, Claus; Clahsen, Thomas (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Cystathionine β-synthase as novel endogenous regulator of lymphangiogenesis via modulating VEGF receptor 2 and 3 - Hatami, Niloofar; Büttner, Christian; Bock, Felix; Simfors, Sara; Musial, Gwen; Reis, André; Cursiefen, Claus; Clahsen, Thomas (Communications Biology, 2022)
Lymphangiogenesis is a key player in several diseases such as tumor metastasis, obesity, and graft rejection. Endogenous regulation of lymphangiogenesis is only partly understood. Here we use the normally avascular cornea as a model to identify endogenous regulators of lymphangiogenesis. Quantitative trait locus analysis of a large low-lymphangiogenic BALB/cN x high-lymphangiogenic C57BL/6 N intercross and prioritization by whole-transcriptome sequencing identify a novel gene responsible for differences in lymphatic vessel architecture on chromosome 17, the cystathionine β-synthase (Cbs). Inhibition of CBS in lymphatic endothelial cells results in reduce proliferation, migration, altered tube-formation, and decrease expression of vascular endothelial growth factor (VEGF) receptor 2 (VEGF-R2) and VEGF-R3, but not their ligands VEGF-C and VEGF-D. Also in vivo inflammation-induced lymphangiogenesis is significantly reduce in C57BL/6 N mice after pharmacological inhibition of CBS. The results confirm CBS as a novel endogenous regulator of lymphangiogenesis acting via VEGF receptor 2 and 3-regulation and open new treatment avenues in diseases associated with pathologic lymphangiogenesis.
CRIS-Team Scopus Importer:2022-09-30

DDX3X mutations in two girls with a phenotype overlapping Toriello-Carey syndrome - Dikow, Nicola; Granzow, Martin; Graul-Neumann, Luitgard M.; Karch, Stephanie; Hinderhofer, Katrin; Paramasivam, Nagarajan; Behl, Laura-Jane; Kaufmann, Lilian; Fischer, Christine; Evers, Christina; Schlesner, Matthias; Eils, Roland; et al. (American Journal of Medical Genetics Part A, 2017)
Recently, de novo heterozygous variants in DDX3X have been reported in about 1.5% of 2659 females with previously unexplained intellectual disability (ID). We report on the identification of DDX3X variants in two unrelated girls with clinical features of Toriello-Carey Syndrome (T-CS). In patient 1, the recurrent variant c.1703C>T; p.(P568L) was identified when reconsidering X-linked de novo heterozygous variants in exome sequencing data. In patient 2, the DDX3X variant c.1600C>G; p.(R534G) was also detected by exome sequencing. Based on these data, de novo heterozygous DDX3X variants should be considered not only in females with unexplained ID, but also in individuals with a clinical diagnosis of T-CS.
EVALuna2:9360

Decoding Parkinson's disease – iPSC-derived models in the OMICs era - Krach, Florian; Bogiongko, Marios Evangelos; Winner, Beate (Molecular and Cellular Neuroscience, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the loss of dopaminergic neurons in the midbrain. In recent years, researchers have started studying PD using induced pluripotent stem cell (iPSC) models of the disease. Surprisingly, few studies have combined iPSC-technology with the so-called powerful ‘omics’ approaches. Here, we review the current state of omics applications used in combination with iPSC-derived models to study PD. Our focus is on studies investigating transcriptional changes and publications using proteomics applications. Lastly, we discuss current caveats in the field and identify potential future directions to obtain novel insights into PD pathology.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Disease modeling; iPSC; Parkinson's disease; Proteomics; RNA-seq; Transcriptomics

Decoding Parkinson's disease - iPSC-derived models in the OMICs era. - Winner, Beate; Krach, Florian; Marios-Evangelos, Bogiongko (Molecular and Cellular Neuroscience, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the loss of dopaminergic neurons in the midbrain. In recent years, researchers have started studying PD using induced pluripotent stem cell (iPSC) models of the disease. Surprisingly, few studies have combined iPSC-technology with the so-called powerful 'omics' approaches. Here, we review the current state of omics applications used in combination with iPSC-derived models to study PD. Our focus is on studies investigating transcriptional changes and publications using proteomics applications. Lastly, we discuss current caveats in the field and identify potential future directions to obtain novel insights into PD pathology.
Keywords: Disease modeling; Parkinson's disease; Proteomics; RNA-seq; Transcriptomics; iPSC

Defects in ER-endosome contacts impact lysosome function in hereditary spastic paraplegia - Allison, Rachel; Edgar, James R.; Pearson, Guy; Rizo, Tania; Newton, Timothy; Guenther, Sven; Berner, Fiamma; Hague, Jennifer; Connell, James W.; Winkler, Jürgen; Lippincott-Schwartz, Jennifer; Beetz, Christian; et al. (The Journal of Cell Biology, 2017)
Contacts between endosomes and the endoplasmic reticulum (ER) promote endosomal tubule fission, but the mechanisms involved and consequences of tubule fission failure are incompletely understood. We found that interaction between the microtubule-severing enzyme spastin and the ESCRT protein IST1 at ER-endosome contacts drives endosomal tubule fission. Failure of fission caused defective sorting of mannose 6-phosphate receptor, with consequently disrupted lysosomal enzyme trafficking and abnormal lysosomal morphology, including in mouse primary neurons and human stem cell-derived neurons. Consistent with a role for ER-mediated endosomal tubule fission in lysosome function, similar lysosomal abnormalities were seen in cellular models lacking the WASH complex component strumpellin or the ER morphogen REEP1. Mutations in spastin, strumpellin, or REEP1 cause hereditary spastic paraplegia (HSP), a disease characterized by axonal degeneration. Our results implicate failure of the ER-endosome contact process in axonopathy and suggest that coupling of ER-mediated endosomal tubule fission to lysosome function links different classes of HSP proteins, previously considered functionally distinct, into a unifying pathway for axonal degeneration.
EVALuna2:9354

Deletion 7q31.2q31.31 segregating in a family with speech and language deficiencies - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Deletions in the 3' part of the NFIX gene including a recurrent Alu-mediated deletion of exon 6 and 7 account for previously unexplained cases of Marshall-Smith syndrome - Schanze, Denny; Neubauer, Dorothee; Cormier-Daire, Valerie; Delrue, Marie-Ange; Dieux-Coeslier, Anne; Hasegawa, Tomonobu; Holmberg, Eva E.; Koenig, Rainer; Krueger, Gabriele; Schanze, Ina; Seemanova, Eva; Shaw, Adam C.; et al. (Human Mutation, 2014)
Marshall-Smith syndrome (MSS) is a very rare malformation syndrome characterized by typical craniofacial anomalies, abnormal osseous maturation, developmental delay, failure to thrive, and respiratory difficulties. Mutations in the nuclear factor 1/X gene (NFIX) were recently identified as the cause of MSS. In our study cohort of 17 patients with a clinical diagnosis of MSS, conventional sequencing of NFIX revealed frameshift and splice-site mutations in 10 individuals. Using multiplex ligation-dependent probe amplification analysis, we identified a recurrent deletion of NFIX exon 6 and 7 in five individuals. We demonstrate this recurrent deletion is the product of a recombination between AluY elements located in intron 5 and 7. Two other patients had smaller deletions affecting exon 6. These findings show that MSS is a genetically homogeneous Mendelian disorder. RT-PCR experiments with newly identified NFIX mutations including the recurrent exon 6 and 7 deletion confirmed previous findings indicating that MSS-associated mutant mRNAs are not cleared by nonsense-mediated mRNA decay. Predicted MSS-associated mutant NFIX proteins consistently have a preserved DNA binding and dimerization domain, whereas they grossly vary in their C-terminal portion. This is in line with the hypothesis that MSS-associated mutations encode dysfunctional proteins that act in a dominant negative manner.
EVALuna2:9229

Delineation of MidXq28-duplication syndrome distal to MECP2 and proximal to RAB39B genes - Sinibaldi, Lorenzo; Parisi, Valentina; Lanciotti, Silvia; Fontana, Paolo; Kuechler, Alma; Baujat, Genevieve; Torres, Barbara; Koetting, Judith; Splendiani, Alessandra; Postorivo, Diana; Beygo, Jasmin; Garaci, Francesco G.; et al. (Clinical Genetics, 2019)
Two distinct genomic disorders have been linked to Xq28-gains, namely Xq28-duplications including MECP2 and Int22h1/Int22h2-mediated duplications involving RAB39B. Here, we describe six unrelated patients, five males and one female, with Xq28-gains distal to MECP2 and proximal to the Int22h1/Int22h2 low copy repeats. Comparison with patients carrying overlapping duplications in the literature defined the MidXq28-duplication syndrome featuring intellectual disability, language impairment, structural brain malformations, microcephaly, seizures and minor craniofacial features. The duplications overlapped for 108 kb including FLNA, RPL10 and GDI1 genes, highly expressed in brain and candidates for the neurologic phenotype.
CRIS-Team Scopus Importer:2019-06-28
Keywords: corpus callosum and cerebellar vermis hypoplasia; developmental delay/intellectual disability; microcephaly; Xq28-duplication

Delineation of the adult phenotype of Coffin–Siris syndrome in 35 individuals - Schmetz, Ariane; Lüdecke, Hermann Josef; Surowy, Harald; Sivalingam, Sugirtahn; Bruel, Ange Line; Caumes, Roseline; Charles, Perrine; Chatron, Nicolas; Chrzanowska, Krystyna; Codina-Solà, Marta; Colson, Cindy; Cuscó, Ivon; et al. (Human genetics, 2023)
Coffin–Siris syndrome (CSS) is a rare multisystemic autosomal dominant disorder. Since 2012, alterations in genes of the SWI/SNF complex were identified as the molecular basis of CSS, studying largely pediatric cohorts. Therefore, there is a lack of information on the phenotype in adulthood, particularly on the clinical outcome in adulthood and associated risks. In an international collaborative effort, data from 35 individuals ≥ 18 years with a molecularly ascertained CSS diagnosis (variants in ARID1B, ARID2, SMARCA4, SMARCB1, SMARCC2, SMARCE1, SOX11, BICRA) using a comprehensive questionnaire was collected. Our results indicate that overweight and obesity are frequent in adults with CSS. Visual impairment, scoliosis, and behavioral anomalies are more prevalent than in published pediatric or mixed cohorts. Cognitive outcomes range from profound intellectual disability (ID) to low normal IQ, with most individuals having moderate ID. The present study describes the first exclusively adult cohort of CSS individuals. We were able to delineate some features of CSS that develop over time and have therefore been underrepresented in previously reported largely pediatric cohorts, and provide recommendations for follow-up.
CRIS-Team Scopus Importer:2023-12-29

Delineation of the clinical phenotype caused by de novo CLTC variants - Sa, M. J. Nabais; Venselaar, H.; Wiel, L.; Trimouille, A.; Lasseaux, E.; Naudion, S.; Lacombe, D.; Piton, A.; Vincent-Delorme, C.; Zweier, Christiane; Wiesmann da Silva Reis, André; Trollmann, Regina; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Demonstration of brain region-specific neuronal vulnerability in human iPSC-based model of familial Parkinson's disease - Brazdis, Razvan Marius; Alecu, Julian E.; Marsch, Daniel; Dahms, Annika; Simmnacher, Katrin; Lörentz, Sandra; Brendler, Anna; Schneider, Yanni; Marxreiter, Franz; Roybon, Laurent; Winner, Beate; Xiang, Wei; et al. (Human Molecular Genetics, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein inclusions mostly composed of aggregated forms of α-synuclein (α-Syn) and by the progressive degeneration of midbrain dopaminergic neurons (mDANs), resulting in motor symptoms. While other brain regions also undergo pathologic changes in PD, the relevance of α-Syn aggregation for the preferential loss of mDANs in PD pathology is not completely understood yet. To elucidate the mechanisms of the brain region-specific neuronal vulnerability in PD, we modeled human PD using human-induced pluripotent stem cells (iPSCs) from familial PD cases with a duplication (Dupl) of the α-Syn gene (SNCA) locus. Human iPSCs from PD Dupl patients and a control individual were differentiated into mDANs and cortical projection neurons (CPNs). SNCA dosage increase did not influence the differentiation efficiency of mDANs and CPNs. However, elevated α-Syn pathology, as revealed by enhanced α-Syn insolubility and phosphorylation, was determined in PD-derived mDANs compared with PD CPNs. PD-derived mDANs exhibited higher levels of reactive oxygen species and protein nitration levels compared with CPNs, which might underlie elevated α-Syn pathology observed in mDANs. Finally, increased neuronal death was observed in PD-derived mDANs compared to PD CPNs and to control mDANs and CPNs. Our results reveal, for the first time, a higher α-Syn pathology, oxidative stress level, and neuronal death rate in human PD mDANs compared with PD CPNs from the same patient. The finding implies the contribution of pathogenic α-Syn, probably induced by oxidative stress, to selective vulnerability of substantia nigra dopaminergic neurons in human PD.
CRIS-Team Scopus Importer:2020-05-26

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder - Mirzaa, Ghayda M.; Chong, Jessica X.; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A.; Sajan, Samin A.; Tang, Sha; et al. (Genetics in Medicine, 2019)
Purpose: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). Methods: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype–phenotype relationships. Results: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. Conclusion: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
CRIS-Team Scopus Importer:2019-11-26
Keywords: autism spectrum disorders; exome sequencing; intellectual disability; next-generation sequencing; ZNF292

De novo CLTC variants are associated with a variable phenotype from mild to severe intellectual disability, microcephaly, hypoplasia of the corpus callosum, and epilepsy - Nabais Sá, Maria J.; Venselaar, Hanka; Wiel, Laurens; Trimouille, Aurélien; Lasseaux, Eulalie; Naudion, Sophie; Lacombe, Didier; Piton, Amélie; Vincent-Delorme, Catherine; Zweier, Christiane; Reis, André; Trollmann, Regina; et al. (Genetics in Medicine, 2019)
Purpose: To delineate the genotype–phenotype correlation in individuals with likely pathogenic variants in the CLTC gene. Methods: We describe 13 individuals with de novo CLTC variants. Causality of variants was determined by using the tolerance landscape of CLTC and computer-assisted molecular modeling where applicable. Phenotypic abnormalities observed in the individuals identified with missense and in-frame variants were compared with those with nonsense or frameshift variants in CLTC. Results: All de novo variants were judged to be causal. Combining our data with that of 14 previously reported affected individuals (n = 27), all had intellectual disability (ID), ranging from mild to moderate/severe, with or without additional neurologic, behavioral, craniofacial, ophthalmologic, and gastrointestinal features. Microcephaly, hypoplasia of the corpus callosum, and epilepsy were more frequently observed in individuals with missense and in-frame variants than in those with nonsense and frameshift variants. However, this difference was not significant. Conclusions: The wide phenotypic variability associated with likely pathogenic CLTC variants seems to be associated with allelic heterogeneity. The detailed clinical characterization of a larger cohort of individuals with pathogenic CLTC variants is warranted to support the hypothesis that missense and in-frame variants exert a dominant-negative effect, whereas the nonsense and frameshift variants would result in haploinsufficiency.
CRIS-Team Scopus Importer:2019-12-10
Keywords: CLTC; intellectual disability; neurodevelopmental disorder

De novo coding variants in the AGO1 gene cause a neurodevelopmental disorder with intellectual disability - Schalk, Audrey; Cousin, Margot A.; Challman, Thomas D.; Wain, Karen E.; Powis, Zoe; Minks, Kelly; Trimouille, Aurelien; Lasseaux, Eulalie; Lacombre, Didier; Angelini, Chloe; Michaud, Vincent; Van-Gils, Julien; et al. (Journal of Medical Genetics, 2021)
Background High-impact pathogenic variants in more than a thousand genes are involved in Mendelian forms of neurodevelopmental disorders (NDD). Methods This study describes the molecular and clinical characterisation of 28 probands with NDD harbouring heterozygous AGO1 coding variants, occurring de novo for all those whose transmission could have been verified (26/28). Results A total of 15 unique variants leading to amino acid changes or deletions were identified: 12 missense variants, two in-frame deletions of one codon, and one canonical splice variant leading to a deletion of two amino acid residues. Recurrently identified variants were present in several unrelated individuals: p.(Phe180del), p.(Leu190Pro), p.(Leu190Arg), p.(Gly199Ser), p.(Val254Ile) and p.(Glu376del). AGO1 encodes the Argonaute 1 protein, which functions in gene-silencing pathways mediated by small non-coding RNAs. Three-dimensional protein structure predictions suggest that these variants might alter the flexibility of the AGO1 linker domains, which likely would impair its function in mRNA processing. Affected individuals present with intellectual disability of varying severity, as well as speech and motor delay, autistic behaviour and additional behavioural manifestations. Conclusion Our study establishes that de novo coding variants in AGO1 are involved in a novel monogenic form of NDD, highly similar to the recently reported AGO2-related NDD.
CRIS-Team WoS Importer:2021-12-24

De novo missense mutations in the NAA10 gene cause severe non-syndromic developmental delay in males and females - Popp, Bernt; Stove, Svein I.; Endele, Sabine; Myklebust, Line M.; Hoyer, Juliane; Sticht, Heinrich; Azzarello-Burri, Silvia; Rauch, Anita; Arnesen, Thomas; Reis, André (European journal of human genetics, 2015)
Recent studies revealed the power of whole-exome sequencing to identify mutations in sporadic cases with non-syndromic intellectual disability. We now identified de novo missense variants in NAA10 in two unrelated individuals, a boy and a girl, with severe global developmental delay but without any major dysmorphism by trio whole-exome sequencing. Both de novo variants were predicted to be deleterious, and we excluded other variants in this gene. This X-linked gene encodes N-alpha-acetyltransferase 10, the catalytic subunit of the NatA complex involved in multiple cellular processes. A single hypomorphic missense variant p.(Ser37Pro) was previously associated with Ogden syndrome in eight affected males from two different families. This rare disorder is characterized by a highly recognizable phenotype, global developmental delay and results in death during infancy. In an attempt to explain the discrepant phenotype, we used in vitro N-terminal acetylation assays which suggested that the severity of the phenotype correlates with the remaining catalytic activity. The variant in the Ogden syndrome patients exhibited a lower activity than the one seen in the boy with intellectual disability, while the variant in the girl was the most severe exhibiting only residual activity in the acetylation assays used. We propose that N-terminal acetyltransferase deficiency is clinically heterogeneous with the overall catalytic activity determining the phenotypic severity.
EVALuna2:9247

De novo missense variants in FBXO11 alter its protein expression and subcellular localization - Gregor, Anne; Meerbrei, Tanja; Gerstner, Thorsten; Toutain, Annick; Lynch, Sally Ann; Stals, Karen; Maxton, Caroline; Lemke, Johannes R.; Bernat, John A.; Bombei, Hannah M.; Foulds, Nicola; Hunt, David; et al. (Human Molecular Genetics, 2022)
Recently, others and we identified de novo FBXO11 (F-Box only protein 11) variants as causative for a variable neurodevelopmental disorder (NDD). We now assembled clinical and mutational information on 23 additional individuals. The phenotypic spectrum remains highly variable, with developmental delay and/or intellectual disability as the core feature and behavioral anomalies, hypotonia and various facial dysmorphism as frequent aspects. The mutational spectrum includes intragenic deletions, likely gene disrupting and missense variants distributed across the protein. To further characterize the functional consequences of FBXO11 missense variants, we analyzed their effects on protein expression and localization by overexpression of 17 different mutant constructs in HEK293 and HeLa cells. We found that the majority of missense variants resulted in subcellular mislocalization and/or reduced FBXO11 protein expression levels. For instance, variants located in the nuclear localization signal and the N-terminal F-Box domain lead to altered subcellular localization with exclusion from the nucleus or the formation of cytoplasmic aggregates and to reduced protein levels in western blot. In contrast, variants localized in the C-terminal Zn-finger UBR domain lead to an accumulation in the cytoplasm without alteration of protein levels. Together with the mutational data, our functional results suggest that most missense variants likely lead to a loss of the original FBXO11 function and thereby highlight haploinsufficiency as the most likely disease mechanism for FBXO11-associated NDDs.
CRIS-Team Scopus Importer:2022-03-04

De novo missense variants in RHOBTB2 cause a developmental and epileptic encephalopathy in humans, and altered levels cause neurological defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, A.; Bok, L. A.; Cho, M. T.; Crawford, H. P.; Dubbs, H.; Douglas, G.; Jobling, R.; Johnson, D.; Krock, B.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Kuechler, Alma; Willemsen, Marjolein H.; Albrecht, Beate; Bacino, Carlos A.; Bartholomew, Dennis W.; Van Bokhoven, Hans; Van Den Boogaard, Marie Jose H.; Bramswig, Nuria; Büttner, Christian; Cremer, Kirsten; Czeschik, Johanna Christina; Engels, Hartmut; et al. (Human genetics, 2015)
Recently, de novo heterozygous loss-of-function mutations in beta-catenin (CTNNB1) were described for the first time in four individuals with intellectual disability (ID), microcephaly, limited speech and (progressive) spasticity, and functional consequences of CTNNB1 deficiency were characterized in a mouse model. Beta-catenin is a key downstream component of the canonical Wnt signaling pathway. Somatic gain-of-function mutations have already been found in various tumor types, whereas germline loss-of-function mutations in animal models have been shown to influence neuronal development and maturation. We report on 16 additional individuals from 15 families in whom we newly identified de novo loss-of-function CTNNB1 mutations (six nonsense, five frameshift, one missense, two splice mutation, and one whole gene deletion). All patients have ID, motor delay and speech impairment (both mostly severe) and abnormal muscle tone (truncal hypotonia and distal hypertonia/spasticity). The craniofacial phenotype comprised microcephaly (typically -2 to -4 SD) in 12 of 16 and some overlapping facial features in all individuals (broad nasal tip, small alae nasi, long and/or flat philtrum, thin upper lip vermillion). With this detailed phenotypic characterization of 16 additional individuals, we expand and further establish the clinical and mutational spectrum of inactivating CTNNB1 mutations and thereby clinically delineate this new CTNNB1 haploinsufficiency syndrome.
EVALuna2:9250

De novo mutations in MSL3 cause an X-linked syndrome marked by impaired histone H4 lysine 16 acetylation - Basilicata, M. Felicia; Bruel, Ange-Line; Semplicio, Giuseppe; Valsecchi, Claudia Isabelle Keller; Aktas, Tugce; Duffourd, Yannis; Rumpf, Tobias; Morton, Jenny; Bache, Iben; Szymanski, Witold G.; Gilissen, Christian; Vanakker, Olivier; et al. (Nature Genetics, 2018)
The etiological spectrum of ultra-rare developmental disorders remains to be fully defined. Chromatin regulatory mechanisms maintain cellular identity and function, where misregulation may lead to developmental defects. Here, we report pathogenic variations in MSL3, which encodes a member of the chromatin-associated male-specific lethal (MSL) complex responsible for bulk histone H4 lysine 16 acetylation (H4K16ac) in flies and mammals. These variants cause an X-linked syndrome affecting both sexes. Clinical features of the syndrome include global developmental delay, progressive gait disturbance, and recognizable facial dysmorphism. MSL3 mutations affect MSL complex assembly and activity, accompanied by a pronounced loss of H4K16ac levels in vivo. Patient-derived cells display global transcriptome alterations of pathways involved in morphogenesis and cell migration. Finally, we use histone deacetylase inhibitors to rebalance acetylation levels, alleviating some of the molecular and cellular phenotypes of patient cells. Taken together, we characterize a syndrome that allowed us to decipher the developmental importance of MSL3 in humans.
EVALuna2:34825

De novo mutations in the genome organizer CTCF cause intellectual disability - Gregor, Anne; Oti, Martin; Kouwenhoven, Evelyn N.; Hoyer, Juliane; Sticht, Heinrich; Ekici, Arif Bülent; Kjaergaard, Susanne; Rauch, Anita; Stunnenberg, Hendrik G.; Uebe, Steffen; Vasileiou, Georgia; Reis, André; et al. (American Journal of Human Genetics, 2013)
An increasing number of genes involved in chromatin structure and epigenetic regulation has been implicated in a variety of developmental disorders, often including intellectual disability. By trio exome sequencing and subsequent mutational screening we now identified two de novo frameshift mutations and one de novo missense mutation in CTCF in individuals with intellectual disability, microcephaly, and growth retardation. Furthermore, an individual with a larger deletion including CTCF was identified. CTCF (CCCTC-binding factor) is one of the most important chromatin organizers in vertebrates and is involved in various chromatin regulation processes such as higher order of chromatin organization, enhancer function, and maintenance of three-dimensional chromatin structure. Transcriptome analyses in all three individuals with point mutations revealed deregulation of genes involved in signal transduction and emphasized the role of CTCF in enhancer-driven expression of genes. Our findings indicate that haploinsufficiency of CTCF affects genomic interaction of enhancers and their regulated gene promoters that drive developmental processes and cognition.
EVALuna2:9184

De novo mutations in the X-linked TFE3 gene cause intellectual disability with pigmentary mosaicism and storage disorder-like features - Lehalle, Daphné; Vabres, Pierre; Sorlin, Arthur; Bierhals, Tatjana; Avila, Magali; Carmignac, Virginie; Chevarin, Martin; Torti, Erin; Abe, Yuichi; Bartolomaeus, Tobias; Clayton-Smith, Jill; Cogné, Benjamin; et al. (Journal of Medical Genetics, 2020)
Introduction: Pigmentary mosaicism (PM) manifests by pigmentation anomalies along Blaschko's lines and represents a clue toward the molecular diagnosis of syndromic intellectual disability (ID). Together with new insights on the role for lysosomal signalling in embryonic stem cell differentiation, mutations in the X-linked transcription factor 3 (TFE3) have recently been reported in five patients. Functional analysis suggested these mutations to result in ectopic nuclear gain of functions. Materials and methods: Subsequent data sharing allowed the clustering of de novo TFE3 variants identified by exome sequencing on DNA extracted from leucocytes in patients referred for syndromic ID with or without PM. Results: We describe the detailed clinical and molecular data of 17 individuals harbouring a de novo TFE3 variant, including the patients that initially allowed reporting TFE3 as a new disease-causing gene. The 12 females and 5 males presented with pigmentation anomalies on Blaschko's lines, severe ID, epilepsy, storage disorder-like features, growth retardation and recognisable facial dysmorphism. The variant was at a mosaic state in at least two male patients. All variants were missense except one splice variant. Eleven of the 13 variants were localised in exon 4, 2 in exon 3, and 3 were recurrent variants. Conclusion: This series further delineates the specific storage disorder-like phenotype with PM ascribed to de novo TFE3 mutation in exons 3 and 4. It confirms the identification of a novel X-linked human condition associated with mosaicism and dysregulation within the mechanistic target of rapamycin (mTOR) pathway, as well as a link between lysosomal signalling and human development.
CRIS-Team Scopus Importer:2020-06-02
Keywords: intellectual disability; lysosomal metabolism; pigmentary mosaicism; storage disorder; TFE3

De Novo Splice-Site Variant in DKC1 in a Female With Clinical Features of Hoyeraal–Hreidarsson Syndrome - Braun, Dominique; Gregor, Anne; Haubitz, Monika; Baerlocher, Gabriela M.; Kraus, Cornelia; Rieubland, Claudine; Zweier, Christiane (American Journal of Medical Genetics Part A, 2025)
The dyskerin encoding gene DKC1 plays an important role in telomerase activity and telomere maintenance. Pathogenic variants in DKC1 cause an X-linked multiorgan disease called dyskeratosis congenita (DC), the most severe form of which is Hoyeraal–Hreidarsson syndrome (HHS). HHS due to DKC1 variants has so far only been reported in hemizygous males and is associated with severe neurological impairment and progressive bone marrow failure, often causing lethality in early childhood. Heterozygous carrier females are often phenotypically normal. Here, we report a young adult female carrying a de novo splice-site variant in DKC1 and presenting with clinical features overlapping with HHS, such as intrauterine and postnatal growth retardation, microcephaly, intellectual disability, and recurrent infections, while lacking other typical aspects such as dermatological manifestations, cerebellar hypoplasia, or bone marrow failure. Aberrant splicing was confirmed with an in vitro assay, and further analysis revealed very short telomere lengths in the individual, supporting a causative role of the DKC1 variant. Our observations therefore suggest that heterozygous splice-site variants in DKC1 leading to loss of function might result in a phenotype overlapping with but not being typical for HHS in females, supporting a potential genotype–phenotype correlation.
CRIS-Team Scopus Importer:2025-05-02
Keywords: carrier; de novo; DKC1; female; splice; telomere; X-chromosomal

De novo variants in MED12 cause X-linked syndromic neurodevelopmental disorders in 18 females - Polla, D. L.; Bhoj, E. J.; Verheij, J. B.G.M.; Wassink-Ruiter, J. S.Klein; Reis, André; Deshpande, C.; Gregor, Anne; Hill-Karfe, K.; Silfhout, A. T.Vulto van; Pfundt, R.; Bongers, E. M.H.F.; Hakonarson, H.; et al. (Genetics in Medicine, 2020)
Purpose: MED12 is a subunit of the Mediator multiprotein complex with a central role in RNA polymerase II transcription and regulation of cell growth, development, and differentiation. This might underlie the variable phenotypes in males carrying missense variants in MED12, including X-linked recessive Ohdo, Lujan, and FG syndromes. Methods: By international matchmaking we assembled variant and clinical data on 18 females presenting with variable neurodevelopmental disorders (NDDs) and harboring de novo variants in MED12. Results: Five nonsense variants clustered in the C-terminal region, two splice variants were found in the same exon 8 splice acceptor site, and 11 missense variants were distributed over the gene/protein. Protein truncating variants were associated with a severe, syndromic phenotype consisting of intellectual disability (ID), facial dysmorphism, short stature, skeletal abnormalities, feeding difficulties, and variable other abnormalities. De novo missense variants were associated with a less specific, but homogeneous phenotype including severe ID, autistic features, limited speech and variable other anomalies, overlapping both with females with truncating variants as well as males with missense variants. Conclusion: We establish de novo truncating variants in MED12 as causative for a distinct NDD and de novo missense variants as causative for a severe, less specific NDD in females.
CRIS-Team Scopus Importer:2020-12-04

De Novo Variants in the F-Box Protein FBXO11 in 20 Individuals with a Variable Neurodevelopmental Disorder - Gregor, Anne; Sadleir, Lynette G.; Asadollahi, Reza; Azzarello-Burri, Silvia; Battaglia, Agatino; Ousager, Lilian Bomme; Boonsawat, Paranchai; Bruel, Ange-Line; Buchert, Rebecca; Calpena, Eduardo; Cogne, Benjamin; Dallapiccola, Bruno; et al. (American Journal of Human Genetics, 2018)
Next-generation sequencing combined with international data sharing has enormously facilitated identification of new disease-associated genes and mutations. This is particularly true for genetically extremely heterogeneous entities such as neurodevelopmental disorders (NDDs). Through exome sequencing and world-wide collaborations, we identified and assembled 20 individuals with de novo variants in FBXO11. They present with mild to severe developmental delay associated with a range of features including short (4/20) or tall (2/20) stature, obesity (5/20), microcephaly (4/19) or macrocephaly (2/19), behavioral problems (17/20), seizures (5/20), cleft lip or palate or bifid uvula (3/20), and minor skeletal anomalies. FBXO11 encodes a member of the F-Box protein family, constituting a subunit of an E3-ubiquitin ligase complex. This complex is involved in ubiquitination and proteasomal degradation and thus in controlling critical biological processes by regulating protein turnover. The identified de novo aberrations comprise two large deletions, ten likely gene disrupting variants, and eight missense variants distributed throughout FBXO11. Structural modeling for missense variants located in the CASH or the Zinc-finger UBR domains suggests destabilization of the protein. This, in combination with the observed spectrum and localization of identified variants and the lack of apparent genotype-phenotype correlations, is compatible with loss of function or haploinsufficiency as an underlying mechanism. We implicate de novo missense and likely gene disrupting variants in FBXO11 in a neurodevelopmental disorder with variable intellectual disability and various other features.
EVALuna2:34619

De novo variants predicting haploinsufficiency for DIP2C are associated with expressive speech delay - Ha, Thoa; Morgan, Angela; Bartos, Meghan N.; Beatty, Katelyn; Cogné, Benjamin; Braun, Dominique; Gerber, Céline B.; Gaspar, Harald; Kopps, Anna M.; Rieubland, Claudine; Hurst, Anna C.E.; Amor, David J.; et al. (American Journal of Medical Genetics Part A, 2024)
The disconnected (disco)-interacting protein 2 (DIP2) gene was first identified in D. melanogaster and contains a DNA methyltransferase-associated protein 1 (DMAP1) binding domain, Acyl-CoA synthetase domain and AMP-binding sites. DIP2 regulates axonal bifurcation of the mushroom body neurons in D. melanogaster and is required for axonal regeneration in the neurons of C. elegans. The DIP2 homologues in vertebrates, Disco-interacting protein 2 homolog A (DIP2A), Disco-interacting protein 2 homolog B (DIP2B), and Disco-interacting protein 2 homolog C (DIP2C), are highly conserved and expressed widely in the central nervous system. Although there is evidence that DIP2C plays a role in cognition, reports of pathogenic variants in these genes are rare and their significance is uncertain. We present 23 individuals with heterozygous DIP2C variants, all manifesting developmental delays that primarily affect expressive language and speech articulation. Eight patients had de novo variants predicting loss-of-function in the DIP2C gene, two patients had de novo missense variants, three had paternally inherited loss of function variants and six had maternally inherited loss-of-function variants, while inheritance was unknown for four variants. Four patients had cardiac defects (hypertrophic cardiomyopathy, atrial septal defects, and bicuspid aortic valve). Minor facial anomalies were inconsistent but included a high anterior hairline with a long forehead, broad nasal tip, and ear anomalies. Brainspan analysis showed elevated DIP2C expression in the human neocortex at 10–24 weeks after conception. With the cases presented herein, we provide phenotypic and genotypic data supporting the association between loss-of-function variants in DIP2C with a neurocognitive phenotype.
CRIS-Team Scopus Importer:2024-03-15
Keywords: developmental delay; DIP2; DIP2C; intellectual disability; speech articulation; speech delay

Dense genotyping of immune-related susceptibility loci reveals new insights into the genetics of psoriatic arthritis - Bowes, John; Budu-Aggrey, Ashley; Hüffmeier, Ulrike; Uebe, Steffen; Steel, Kathryn; Hebert, Harry L.; Wallace, Chris; Massey, Jonathan; Bruce, Ian N.; Bluett, James; Feletar, Marie; Morgan, Ann W.; et al. (Nature Communications, 2015)
Psoriatic arthritis (PsA) is a chronic inflammatory arthritis associated with psoriasis and, despite the larger estimated heritability for PsA, the majority of genetic susceptibility loci identified to date are shared with psoriasis. Here, we present results from a case-control association study on 1,962 PsA patients and 8,923 controls using the Immunochip genotyping array. We identify eight loci passing genome-wide significance, secondary independent effects at three loci and a distinct PsA-specific variant at the IL23R locus. We report two novel loci and evidence of a novel PsA-specific association at chromosome 5q31. Imputation of classical HLA alleles, amino acids and SNPs across the MHC region highlights three independent associations to class I genes. Finally, we find an enrichment of associated variants to markers of open chromatin in CD8(+) memory primary T cells. This study identifies key insights into the genetics of PsA that could begin to explain fundamental differences between psoriasis and PsA.
EVALuna2:9282

Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09

Detecting tandem repeat variants in coding regions using code-adVNTR - Park, Jonghun; Bakhtiari, Mehrdad; Popp, Bernt; Wiesener, Michael; Bafna, Vineet (iScience, 2022)
The human genome contains more than one million tandem repeats (TRs), DNA sequences containing multiple approximate copies of a motif repeated contiguously. TRs account for significant genetic variation, with 50 + diseases attributed to changes in motif number. A few diseases have been to be caused by small indels in variable number tandem repeats (VNTRs) including poly-cystic kidney disease type 1 (MCKD1) and monogenic type 1 diabetes. However, small indels in VNTRs are largely unexplored mainly due to the long and complex structure of VNTRs with multiple motifs. We developed a method, code-adVNTR, that utilizes multi-motif hidden Markov models to detect both, motif count variation and small indels, within VNTRs. In simulated data, code-adVNTR outperformed GATK-HaplotypeCaller in calling small indels within large VNTRs. We used code-adVNTR to characterize coding VNTRs in the 1000 genomes data identifying many population-specific variants, and to reliably call MUC1 mutations for MCKD1.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Genetics; Genomics; Human genetics; Molecular genetics

Detection rate and re-analysis of exome sequencing data in a cohort of 207 individuals with neurodevelopmental disorders - Hebebrand, Moritz; Thiel, C. T.; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

DGCR8 deficiency impairs macrophage growth and unleashes the interferon response to mycobacteria - Killy, Barbara; Bodendorfer, Barbara; Mages, Jörg; Ritter, Kristina; Schreiber, Jonathan; Hölscher, Christoph; Pracht, Katharina; Ekici, Arif Bülent; Jäck, Hans-Martin; Lang, Roland (Life Science Alliance, 2021)
The mycobacterial cell wall glycolipid trehalose-6,6-dimycolate (TDM) activates macrophages through the C-type lectin receptor MINCLE. Regulation of innate immune cells relies on miRNAs, which may be exploited by mycobacteria to survive and replicate in macrophages. Here, we have used macrophages deficient in the microprocessor component DGCR8 to investigate the impact of miRNA on the response to TDM. Deletion of DGCR8 in bone marrow progenitors reduced macrophage yield, but did not block macrophage differentiation. DGCR8-deficient macrophages showed reduced constitutive and TDM-inducible miRNA expression. RNAseq analysis revealed that they accumulated primary miRNA transcripts and displayed a modest type I IFN signature at baseline. Stimulation with TDM in the absence of DGCR8 induced overshooting expression of IFNβ and IFN-induced genes, which was blocked by antibodies to type I IFN. In contrast, signaling and transcriptional responses to recombinant IFNβ were unaltered. Infection with live Mycobacterium bovis Bacille Calmette-Guerin replicated the enhanced IFN response. Together, our results reveal an essential role for DGCR8 in curbing IFNβ expression macrophage reprogramming by mycobacteria.
CRIS-Team Scopus Importer:2021-04-16

Diagnostics of rare diseases with next generation sequencing—arrived at the patients or rejected? Diagnostik seltener Erkrankungen mit „next generation sequencing“ – angekommen oder abgewehrt? - Abicht, Angela; Neuhann, Teresa; Mehnert, Laura; Rost, Imma; Wiesmann da Silva Reis, André; Zweier, Christiane; Holinski-Feder, Elke (Medizinische Genetik, 2019)
In genetic diagnostics, the path goes from single-gene testing to gene-panel analyses, especially for rare genetic diseases. In July 2016, an amendment to the EBM (Einheitlicher Bewertungsmaßstab, Regulations on Fees for Statutory Health Insurance) introduced the possibility of performing genetic analyses using next-generation sequencing (NGS) on patients with rare diseases. However, the mutation search in a sequence encoding more than 25 kilobases (kb) was subject to approval by the health insurance funds and was further restricted over time by a billing exclusion for a previous analysis of individual genes of less than 25 kb. We report from the diagnostic laboratories of the Bavarian State Association of the BVDH (Berufsverband Deutscher Humangenetiker e. V.) on the experiences we have gained with the application procedures, the objections, the approval rate, the reasons for rejection and the diagnostic outcome in the analysis of large gene panels for various rare disorders. In the survey period of seven quarters, a total of 314 applications were prepared in four diagnostic laboratories to justify an application according to GOP (Gebührenordnungsposition, fee schedule position) 11514, all of which were reviewed by the MDK (Medizinischer Dienst der Krankenkassen; Medical Service to Health Insurance Funds). 71% of the applications were rejected. A total of 95 applications (29%) were approved, but in some cases only after up to five objections. The rejections were based on both socio-medical and formal criteria, whereby in most cases a therapeutic relevance considered to be lacking was used as a socio-medical argument. The approved comprehensive NGS analyses made it possible to make a genetic diagnosis in more than 30% of the patients examined, which was relevant to treatment in two thirds of the cases. In summary, the conditional approval of an NGS analysis according to GOP 11514 and the resulting obstacles hinder the medically necessary and useful diagnostics in the care of patients with rare diseases.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Application procedure “large panel”; Gene panel; Panel diagnostics; Scale of charges position 11514; Uniform assessment benchmark

Diagnostic Yield and Novel Candidate Genes by Exome Sequencing in 152 Consanguineous Families With Neurodevelopmental Disorders - Reuter, Miriam; Tawamie, Hasan; Buchert, Rebecca; Gebril, Ola Hosny; Froukh, Tawfiq; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Zweier, Christiane; Hoyer, Juliane; Eberlein, Karolin; et al. (JAMA Psychiatry, 2017)
Autosomal recessive inherited neurodevelopmental disorders are highly heterogeneous, and many, possibly most, of the disease genes are still unknown.To promote the identification of disease genes through confirmation of previously described genes and presentation of novel candidates and provide an overview of the diagnostic yield of exome sequencing in consanguineous families.Autozygosity mapping in families and exome sequencing of index patients were performed in 152 consanguineous families (the parents descended from a same ancestor) with at least 1 offspring with intellectual disability (ID). The study was conducted from July 1, 2008, to June 30, 2015, and data analysis was conducted from July 1, 2015, to August 31, 2016.Of the 152 consanguineous families enrolled, 1 child (in 45 families [29.6%]) or multiple children (107 families [70.4%]) had ID; additional features were present in 140 of the families (92.1%). The mean (SD) age of the children was 10.3 (9.0) years, and 171 of 297 (57.6%) were male. In 109 families (71.7%), potentially protein-disrupting and clinically relevant variants were identified. Of these, a clear clinical genetic diagnosis was made in 56 families (36.8%) owing to 57 (likely) pathogenic variants in 50 genes already established in neurodevelopmental disorders (46 autosomal recessive, 2 X-linked, and 2 de novo) or in 7 previously proposed recessive candidates. In 5 of these families, potentially treatable disorders were diagnosed (mutations in PAH, CBS, MTHFR, CYP27A1, and HIBCH), and in 1 family, 2 disease-causing homozygous variants in different genes were identified. In another 48 families (31.6%), 52 convincing recessive variants in candidate genes that were not previously reported in regard to neurodevelopmental disorders were identified. Of these, 14 were homozygous and truncating in GRM7, STX1A, CCAR2, EEF1D, GALNT2, SLC44A1, LRRIQ3, AMZ2, CLMN, SEC23IP, INIP, NARG2, FAM234B, and TRAP1. The diagnostic yield was higher in individuals with severe ID (35 of 77 [45.5%]), in multiplex families (42 of 107 [39.3%]), in patients with additional features (30 of 70 [42.9%]), and in those with remotely related parents (15 of 34 [44.1%]).Because of the high diagnostic yield of 36.8% and the possibility of identifying treatable diseases or the coexistence of several disease-causing variants, using exome sequencing as a first-line diagnostic approach in consanguineous families with neurodevelopmental disorders is recommended. Furthermore, the literature is enriched with 52 convincing candidate genes that are awaiting confirmation in independent families.
EVALuna2:9388

Differential Coassembly of α1-GABAARs Associated with Epileptic Encephalopathy - Hannan, Saad; Affandi, Aida H. B.; Minere, Marielle; Jones, Charlotte; Goh, Pollyanna; Warnes, Gary; Popp, Bernt; Trollmann, Regina; Nizetic, Dean; Smart, Trevor G. (The Journal of Neuroscience, 2020)
GABAA receptors (GABAARs) are profoundly important for controlling neuronal excitability. Spontaneous and familial mutations to these receptors feature prominently in excitability disorders and neurodevelopmental deficits following disruption to GABA-mediated inhibition. Recent genotyping of an individual with severe epilepsy and Williams-Beuren syndrome identified a frameshifting de novo variant in a major GABAAR gene, GABRA1 This truncated the α1 subunit between the third and fourth transmembrane domains and introduced 24 new residues forming the mature protein, α1Lys374Serfs*25 Cell surface expression of mutant murine GABAARs is severely impaired compared with WT, due to retention in the endoplasmic reticulum. Mutant receptors were differentially coexpressed with β3, but not with β2, subunits in mammalian cells. Reduced surface expression was reflected by smaller IPSCs, which may underlie the induction of seizures. The mutant does not have a dominant-negative effect on native neuronal GABAAR expression since GABA current density was unaffected in hippocampal neurons, although mutant receptors exhibited limited GABA sensitivity. To date, the underlying mechanism is unique for epileptogenic variants and involves differential β subunit expression of GABAAR populations, which profoundly affected receptor function and synaptic inhibition.SIGNIFICANCE STATEMENT GABAARs are critical for controlling neural network excitability. They are ubiquitously distributed throughout the brain, and their dysfunction underlies many neurologic disorders, especially epilepsy. Here we report the characterization of an α1-GABAAR variant that results in severe epilepsy. The underlying mechanism is structurally unusual, with the loss of part of the α1 subunit transmembrane domain and part-replacement with nonsense residues. This led to compromised and differential α1 subunit cell surface expression with β subunits resulting in severely reduced synaptic inhibition. Our study reveals that disease-inducing variants can affect GABAAR structure, and consequently subunit assembly and cell surface expression, critically impacting on the efficacy of synaptic inhibition, a property that will orchestrate the extent and duration of neuronal excitability.
CRIS-Team Scopus Importer:2020-07-31
Keywords: epilepsy; GABA-A receptor; inhibition; synaptic transmission; α subunit variant

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

Differential Effects of Very-Low-Volume Exercise Modalities on Telomere Length, Inflammation, and Cardiometabolic Health in Obese Metabolic Syndrome Patients: A Subanalysis from Two Randomized Controlled Trials - Reljic, Dejan; Koller, Adriana; Herrmann, Hans J.; Ekici, Arif Bülent; Neurath, Markus; Zopf, Yurdagül (Antioxidants, 2023)
Oxidative stress (OS) and inflammation are features of metabolic syndrome (MetS) that can contribute to the shortening of telomere length (TL), a marker of cellular ageing. Research indicates that exercise can positively influence MetS-associated conditions and TL. However, the effects of low-volume exercise types on TL are still unknown. We investigated the impact of very-low-volume high-intensity interval training (LV-HIIT), one-set resistance training (1-RT), and whole-body electromyostimulation (WB-EMS) on TL, inflammation, and cardiometabolic indices in 167 MetS patients. Data were derived from two randomized controlled trials where patients were allocated to an exercise group (2 sessions/week, for 12 weeks) or a control group. All groups received standard-care nutritional weight loss counselling. TL was determined as the T/S ratio (telomere to single-copy gene amount). All groups significantly reduced body weight (p < 0.05), but the T/S-ratio (p < 0.001) only increased with LV-HIIT. OS-related inflammatory markers (C-reactive protein, interleukin-6, and lipopolysaccharide-binding protein) only decreased (p < 0.05) following LV-HIIT. The MetS severity z-score improved with LV-HIIT (p < 0.001) and 1-RT (p = 0.014) but not with WB-EMS. In conclusion, very-low-volume exercise modalities have differential effects on telomeres, inflammation, and cardiometabolic health. Only LV-HIIT but not strength-based low-volume exercise increased TL in MetS patients, presumably due to superior effects on OS-related inflammatory markers.
CRIS-Team Scopus Importer:2023-11-10
Keywords: anti-aging; cellular age; electromyostimulation; high-intensity interval training; inflammatory markers; metabolic diseases; oxidative stress; resistance training; telomeres

Differential vulnerability of adult neurogenic niches to dosage of the neurodevelopmental-disorder linked gene Foxg1 - Schäffner, Iris; Wittmann, Marie-Theres; Vogel, Tanja; Lie, Dieter Chichung (Molecular Psychiatry, 2022)
The transcription factor FOXG1 serves pleiotropic functions in brain development ranging from the regulation of precursor proliferation to the control of cortical circuit formation. Loss-of-function mutations and duplications of FOXG1 are associated with neurodevelopmental disorders in humans illustrating the importance of FOXG1 dosage for brain development. Aberrant FOXG1 dosage has been found to disrupt the balanced activity of glutamatergic and GABAergic neurons, but the underlying mechanisms are not fully understood. We report that FOXG1 is expressed in the main adult neurogenic niches in mice, i.e. the hippocampal dentate gyrus and the subependymal zone/olfactory bulb system, where neurogenesis of glutamatergic and GABAergic neurons persists into adulthood. These niches displayed differential vulnerability to increased FOXG1 dosage: high FOXG1 levels severely compromised survival and glutamatergic dentate granule neuron fate acquisition in the hippocampal neurogenic niche, but left neurogenesis of GABAergic neurons in the subependymal zone/olfactory bulb system unaffected. Comparative transcriptomic analyses revealed a significantly higher expression of the apoptosis-linked nuclear receptor Nr4a1 in FOXG1-overexpressing hippocampal neural precursors. Strikingly, pharmacological interference with NR4A1 function rescued FOXG1-dependent death of hippocampal progenitors. Our results reveal differential vulnerability of neuronal subtypes to increased FOXG1 dosage and suggest that activity of a FOXG1/NR4A1 axis contributes to such subtype-specific response.
CRIS-Team WoS Importer:2022-04-08

Different MAPT haplotypes influence expression of total MAPT in postmortem brain tissue - Tauber, Christina V.; Schwarz, Sigrid C.; Rösler, Thomas W.; Arzberger, Thomas; Gentleman, Steve; Windl, Otto; Krumbiegel, Mandy; Reis, André; Ruf, Viktoria C.; Herms, Jochen; Höglinger, Günter U. (Acta Neuropathologica Communications, 2023)
The MAPT gene, encoding the microtubule-associated protein tau on chromosome 17q21.31, is result of an inversion polymorphism, leading to two allelic variants (H1 and H2). Homozygosity for the more common haplotype H1 is associated with an increased risk for several tauopathies, but also for the synucleinopathy Parkinson’s disease (PD). In the present study, we aimed to clarify whether the MAPT haplotype influences expression of MAPT and SNCA, encoding the protein α-synuclein (α-syn), on mRNA and protein levels in postmortem brains of PD patients and controls. We also investigated mRNA expression of several other MAPT haplotype-encoded genes. Postmortem tissues from cortex of fusiform gyrus (ctx-fg) and of the cerebellar hemisphere (ctx-cbl) of neuropathologically confirmed PD patients (n = 95) and age- and sex-matched controls (n = 81) were MAPT haplotype genotyped to identify cases homozygous for either H1 or H2. Relative expression of genes was quantified using real-time qPCR; soluble and insoluble protein levels of tau and α-syn were determined by Western blotting. Homozygosity for H1 versus H2 was associated with increased total MAPT mRNA expression in ctx-fg regardless of disease state. Inversely, H2 homozygosity was associated with markedly increased expression of the corresponding antisense MAPT-AS1 in ctx-cbl. PD patients had higher levels of insoluble 0N3R and 1N4R tau isoforms regardless of the MAPT genotype. The increased presence of insoluble α-syn in PD patients in ctx-fg validated the selected postmortem brain tissue. Our findings in this small, but well controlled cohort of PD and controls support a putative biological relevance of tau in PD. However, we did not identify any link between the disease-predisposing H1/H1 associated overexpression of MAPT with PD status. Further studies are required to gain a deeper understanding of the potential regulatory role of MAPT-AS1 and its association to the disease-protective H2/H2 condition in the context of PD.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Gene expression; H1 and H2 haplotype; MAPT; Parkinson’s disease; Postmortem human brain; Protein level; Synucleins; Tau protein

Discovering a new part of the phenotypic spectrum of Coffin-Siris syndrome in a fetal cohort - van der Sluijs, Pleuntje J.; Joosten, Marieke; Alby, Caroline; Attié-Bitach, Tania; Gilmore, Kelly; Dubourg, Christele; Fradin, Mélanie; Wang, Tianyun; Kurtz-Nelson, Evangeline C.; Ahlers, Kaitlyn P.; Arts, Peer; Barnett, Christopher P.; et al. (Genetics in Medicine, 2022)
Purpose: Genome-wide sequencing is increasingly being performed during pregnancy to identify the genetic cause of congenital anomalies. The interpretation of prenatally identified variants can be challenging and is hampered by our often limited knowledge of prenatal phenotypes. To better delineate the prenatal phenotype of Coffin-Siris syndrome (CSS), we collected clinical data from patients with a prenatal phenotype and a pathogenic variant in one of the CSS-associated genes. Methods: Clinical data was collected through an extensive web-based survey. Results: We included 44 patients with a variant in a CSS-associated gene and a prenatal phenotype; 9 of these patients have been reported before. Prenatal anomalies that were frequently observed in our cohort include hydrocephalus, agenesis of the corpus callosum, hypoplastic left heart syndrome, persistent left vena cava, diaphragmatic hernia, renal agenesis, and intrauterine growth restriction. Anal anomalies were frequently identified after birth in patients with ARID1A variants (6/14, 43%). Interestingly, pathogenic ARID1A variants were much more frequently identified in the current prenatal cohort (16/44, 36%) than in postnatal CSS cohorts (5%-9%). Conclusion: Our data shed new light on the prenatal phenotype of patients with pathogenic variants in CSS genes.
CRIS-Team Scopus Importer:2022-06-03
Keywords: ARID1A; ARID1B BAFopathy; BAF-complex; Fetal; SMARCA4; SMARCB1

Disease Modeling of Neuropsychiatric Brain Disorders Using Human Stem Cell-Based Neural Models - Kaindl, Johanna; Winner, Beate (Behavioral Neurogenomics, 2019)
Human pluripotent stem (PS) cells are a relevant platform to model human-specific neurological disorders. In this chapter, we focus on human stem cell models for neuropsychiatric disorders including induced pluripotent stem (iPS) cell-derived neural precursor cells (NPCs), neurons and cerebral organoids. We discuss crucial steps for planning human disease modeling experiments. We introduce the different strategies of human disease modeling including transdifferentiation, human embryonic stem (ES) cell-based models, iPS cell-based models and genome editing options. Analysis of disease-relevant phenotypes is discussed. In more detail, we provide exemplary insight into modeling of the neurodevelopmental defects in autism spectrum disorder (ASD) and the process of neurodegeneration in Alzheimer's disease (AD). Besides monogenic diseases, iPS cell-derived models also generated data from idiopathic and sporadic cases.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Disease modeling; hiPSC-derived neurons; hiPSCs; Neuropsychiatric disorders; Organoids

Disruption of RFX family transcription factors causes autism, attention-deficit/hyperactivity disorder, intellectual disability, and dysregulated behavior - Harris, Holly K.; Nakayama, Tojo; Lai, Jenny; Zhao, Boxun; Argyrou, Nikoleta; Gubbels, Cynthia S.; Soucy, Aubrie; Genetti, Casie A.; Suslovitch, Victoria; Rodan, Lance H.; Tiller, George E.; Lesca, Gaetan; et al. (Genetics in Medicine, 2021)
Purpose: We describe a novel neurobehavioral phenotype of autism spectrum disorder (ASD), intellectual disability, and/or attention-deficit/hyperactivity disorder (ADHD) associated with de novo or inherited deleterious variants in members of the RFX family of genes. RFX genes are evolutionarily conserved transcription factors that act as master regulators of central nervous system development and ciliogenesis. Methods: We assembled a cohort of 38 individuals (from 33 unrelated families) with de novo variants in RFX3, RFX4, and RFX7. We describe their common clinical phenotypes and present bioinformatic analyses of expression patterns and downstream targets of these genes as they relate to other neurodevelopmental risk genes. Results: These individuals share neurobehavioral features including ASD, intellectual disability, and/or ADHD; other frequent features include hypersensitivity to sensory stimuli and sleep problems. RFX3, RFX4, and RFX7 are strongly expressed in developing and adult human brain, and X-box binding motifs as well as RFX ChIP-seq peaks are enriched in the cis-regulatory regions of known ASD risk genes. Conclusion: These results establish a likely role of deleterious variation in RFX3, RFX4, and RFX7 in cases of monogenic intellectual disability, ADHD and ASD, and position these genes as potentially critical transcriptional regulators of neurobiological pathways associated with neurodevelopmental disease pathogenesis.
CRIS-Team Scopus Importer:2021-03-26

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

Distinct Effects of Chronic Dopaminergic Stimulation on Hippocampal Neurogenesis and Striatal Doublecortin Expression in Adult Mice - Salvi, Rachele; Steigleder, Tobias; Schlachetzki, Johannes; Waldmann, Elisabeth; Schwab, Stefan; Winner, Beate; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Neuroscience, 2016)
While adult neurogenesis is considered to be restricted to the hippocampal dentate gyrus (DG) and the subventricular zone (SVZ), recent studies in humans and rodents provide evidence for newly generated neurons in regions generally considered as non-neurogenic, e.g., the striatum. Stimulating dopaminergic neurotransmission has the potential to enhance adult neurogenesis in the SVZ and the DG most likely via D2/D3 dopamine (DA) receptors. Here, we investigated the effect of two distinct preferential D2/D3 DA agonists, Pramipexole (PPX), and Ropinirole (ROP), on adult neurogenesis in the hippocampus and striatum of adult naïve mice. To determine newly generated cells in the DG incorporating 5-bromo-2'-deoxyuridine (BrdU) a proliferation paradigm was performed in which two BrdU injections (100 mg/kg) were applied intraperitoneally within 12 h after a 14-days-DA agonist treatment. Interestingly, PPX, but not ROP significantly enhanced the proliferation in the DG by 42% compared to phosphate buffered saline (PBS)-injected control mice. To analyze the proportion of newly generated cells differentiating into mature neurons, we quantified cells co-expressing BrdU and Neuronal Nuclei (NeuN) 32 days after the last of five BrdU injections (50 mg/kg) applied at the beginning of 14-days DA agonist or PBS administration. Again, PPX only enhanced neurogenesis in the DG significantly compared to ROP- and PBS-injected mice. Moreover, we explored the pro-neurogenic effect of both DA agonists in the striatum by quantifying neuroblasts expressing doublecortin (DCX) in the entire striatum, as well as in the dorsal and ventral sub-regions separately. We observed a significantly higher number of DCX(+) neuroblasts in the dorsal compared to the ventral sub-region of the striatum in PPX-injected mice. These results suggest that the stimulation of hippocampal and dorsal striatal neurogenesis may be up-regulated by PPX. The increased generation of neural cells, both in constitutively active and quiescent neurogenic niches, might be related to the proportional higher D3 receptor affinity of PPX, non-dopaminergic effects of PPX, or altered motor behavior.
EVALuna2:5538

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

DLG4-related synaptopathy: a new rare brain disorder - Rodriguez-Palmero, Agusti; Boerrigter, Melissa Maria; Gomez-Andres, David; Aldinger, Kimberly A.; Marcos-Alcalde, Inigo; Popp, Bernt; Everman, David B.; Lovgren, Alysia Kern; Arpin, Stephanie; Bahrambeigi, Vahid; Beunders, Gea; Bisgaard, Anne-Marie; et al. (Genetics in Medicine, 2021)
Purpose: Postsynaptic density protein-95 (PSD-95), encoded by DLG4, regulates excitatory synaptic function in the brain. Here we present the clinical and genetic features of 53 patients (42 previously unpublished) with DLG4 variants. Methods: The clinical and genetic information were collected through GeneMatcher collaboration. All the individuals were investigated by local clinicians and the gene variants were identified by clinical exome/genome sequencing. Results: The clinical picture was predominated by early onset global developmental delay, intellectual disability, autism spectrum disorder, and attention deficit–hyperactivity disorder, all of which point to a brain disorder. Marfanoid habitus, which was previously suggested to be a characteristic feature of DLG4-related phenotypes, was found in only nine individuals and despite some overlapping features, a distinct facial dysmorphism could not be established. Of the 45 different DLG4 variants, 39 were predicted to lead to loss of protein function and the majority occurred de novo (four with unknown origin). The six missense variants identified were suggested to lead to structural or functional changes by protein modeling studies. Conclusion: The present study shows that clinical manifestations associated with DLG4 overlap with those found in other neurodevelopmental disorders of synaptic dysfunction; thus, we designate this group of disorders as DLG4-related synaptopathy. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05

DNA methylation episignature and comparative epigenomic profiling for Pitt-Hopkins syndrome caused by TCF4 variants - van der Laan, Liselot; Lauffer, Peter; Rooney, Kathleen; Silva, Ananília; Haghshenas, Sadegheh; Relator, Raissa; Levy, Michael A.; Trajkova, Slavica; Huisman, Sylvia A.; Bijlsma, Emilia K.; Kleefstra, Tjitske; van Bon, Bregje W.; et al. (Human Genetics and Genomics Advances, 2024)
Pitt-Hopkins syndrome (PTHS) is a neurodevelopmental disorder caused by pathogenic variants in TCF4, leading to intellectual disability, specific morphological features, and autonomic nervous system dysfunction. Epigenetic dysregulation has been implicated in PTHS, prompting the investigation of a DNA methylation (DNAm) “episignature” specific to PTHS for diagnostic purposes and variant reclassification and functional insights into the molecular pathophysiology of this disorder. A cohort of 67 individuals with genetically confirmed PTHS and three individuals with intellectual disability and a variant of uncertain significance (VUS) in TCF4 were studied. The DNAm episignature was developed with an Infinium Methylation EPIC BeadChip array analysis using peripheral blood cells. Support vector machine (SVM) modeling and clustering methods were employed to generate a DNAm classifier for PTHS. Validation was extended to an additional cohort of 11 individuals with PTHS. The episignature was assessed in relation to other neurodevelopmental disorders and its specificity was examined. A specific DNAm episignature for PTHS was established. The classifier exhibited high sensitivity for TCF4 haploinsufficiency and missense variants in the basic-helix-loop-helix domain. Notably, seven individuals with TCF4 variants exhibited negative episignatures, suggesting complexities related to mosaicism, genetic factors, and environmental influences. The episignature displayed degrees of overlap with other related disorders and biological pathways. This study defines a DNAm episignature for TCF4-related PTHS, enabling improved diagnostic accuracy and VUS reclassification. The finding that some cases scored negatively underscores the potential for multiple or nested episignatures and emphasizes the need for continued investigation to enhance specificity and coverage across PTHS-related variants.
CRIS-Team Scopus Importer:2024-05-10
Keywords: CNV; DNA methylation; episignature; neurodevelopmental disorder; Pitt-Hopkins syndrome; PTHS; TCF4; VUS

DNA methylation mediates genotype and smoking interaction in the development of anti-citrullinated peptide antibody-positive rheumatoid arthritis - Meng, Weida; Zhu, Zaihua; Jiang, Xia; Too, Chun Lai; Uebe, Steffen; Jagodic, Maja; Kockum, Ingrid; Murad, Shahnaz; Ferrucci, Luigi; Alfredsson, Lars; Zou, Hejian; Klareskog, Lars; et al. (Arthritis Research & Therapy, 2017)
Multiple factors, including interactions between genetic and environmental risks, are important in susceptibility to rheumatoid arthritis (RA). However, the underlying mechanism is not fully understood. This study was undertaken to evaluate whether DNA methylation can mediate the interaction between genotype and smoking in the development of anti-citrullinated peptide antibody (ACPA)-positive RA.We investigated the gene-smoking interactions in DNA methylation using 393 individuals from the Epidemiological Investigation of Rheumatoid Arthritis (EIRA). The interaction between rs6933349 and smoking in the risk of developing ACPA-positive RA was further evaluated in a larger portion of the EIRA (1119 controls and 944 ACPA-positive patients with RA), and in the Malaysian Epidemiological Investigation of Rheumatoid Arthritis (MyEIRA) (1556 controls and 792 ACPA-positive patients with RA). Finally, mediation analysis was performed to investigate whether DNA methylation of cg21325723 mediates this gene-environment interaction on the risk of developing of ACPA-positive RA.We identified and replicated one significant gene-environment interaction between rs6933349 and smoking in DNA methylation of cg21325723. This gene-smoking interaction is a novel interaction in the risk of developing ACPA-positive in both Caucasian (multiplicative P value = 0.056; additive P value = 0.016) and Asian populations (multiplicative P value = 0.035; additive P value = 0.00027), and it is mediated through DNA methylation of cg21325723.We showed that DNA methylation of cg21325723 can mediate the gene-environment interaction between rs6933349 and smoking, impacting the risk of developing ACPA-positive RA, thus being a potential regulator that integrates both internal genetic and external environmental risk factors.
EVALuna2:9383

Dominantly acting variants in ATP6V1C1 and ATP6V1B2 cause a multisystem phenotypic spectrum by altering lysosomal and/or autophagosome function. - Carpentieri, Giovanna; Cecchetti, Serena; Bocchinfuso, Gianfranco; Radio, Francesca Clementina; Leoni, Chiara; Onesimo, Roberta; Calligari, Paolo; Pietrantoni, Agostina; Ciolfi, Andrea; Ferilli, Marco; Calderan, Cristina; Cappuccio, Gerarda; et al. (Human Genetics and Genomics Advances, 2024)
The vacuolar H+-ATPase (V-ATPase) is a functionally conserved multimeric complex localized at the membranes of many organelles where its proton-pumping action is required for proper lumen acidification. The V-ATPase complex is composed of several subunits, some of which have been linked to human disease. We and others previously reported pathogenic dominantly acting variants in ATP6V1B2, the gene encoding the V1B2 subunit, as underlying a clinically variable phenotypic spectrum including dominant deafness-onychodystrophy (DDOD) syndrome, Zimmermann-Laband syndrome (ZLS), and deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures (DOORS) syndrome. Here, we report on an individual with features fitting DOORS syndrome caused by dysregulated ATP6V1C1 function, expand the clinical features associated with ATP6V1B2 pathogenic variants, and provide evidence that these ATP6V1C1/ATP6V1B2 amino acid substitutions result in a gain-of-function mechanism upregulating V-ATPase function that drives increased lysosomal acidification. We demonstrate a disruptive effect of these ATP6V1B2/ATP6V1C1 variants on lysosomal morphology, localization, and function, resulting in a defective autophagic flux and accumulation of lysosomal substrates. We also show that the upregulated V-ATPase function affects cilium biogenesis, further documenting pleiotropy. This work identifies ATP6V1C1 as a new gene associated with a neurodevelopmental phenotype resembling DOORS syndrome, documents the occurrence of a phenotypic continuum between ZLS, and DDOD and DOORS syndromes, and classify these conditions as lysosomal disorders.
EVALuna2:572917

Dominant variants in major spliceosome U4 and U5 small nuclear RNA genes cause neurodevelopmental disorders through splicing disruption - Nava, Caroline; Cogne, Benjamin; Santini, Amandine; Leitão, Elsa; Lecoquierre, François; Chen, Yuyang; Stenton, Sarah L.; Besnard, Thomas; Heide, Solveig; Baer, Sarah; Jakhar, Abhilasha; Neuser, Sonja; et al. (Nature Genetics, 2025)
The major spliceosome contains five small nuclear RNAs (snRNAs; U1, U2, U4, U5 and U6) essential for splicing. Variants in RNU4-2, encoding U4, cause a neurodevelopmental disorder called ReNU syndrome. We investigated de novo variants in 50 snRNA-encoding genes in a French cohort of 23,649 individuals with rare disorders and gathered additional cases through international collaborations. Altogether, we identified 145 previously unreported probands with (likely) pathogenic variants in RNU4-2 and 21 individuals with de novo and/or recurrent variants in RNU5B-1 and RNU5A-1, encoding U5. Pathogenic variants typically arose de novo on the maternal allele and cluster in regions critical for splicing. RNU4-2 variants mainly localize to two structures, the stem III and T-loop/quasi-pseudoknot, which position the U6 ACAGAGA box for 5′ splice site recognition and associate with different phenotypic severity. RNU4-2 variants result in specific defects in alternative 5′ splice site usage and methylation patterns (episignatures) that correlate with variant location and clinical severity. This study establishes RNU5B-1 as a neurodevelopmental disorder gene, suggests RNU5A-1 as a strong candidate and highlights the role of de novo variants in snRNAs.
CRIS-Team Scopus Importer:2025-05-23

Dopaminergic lesioning impairs adult hippocampal neurogenesis by distinct modification of α-synuclein - Schlachetzki, Johannes; Grimm, Thomas; Schlachetzki, Zinayida; Ben Abdallah, Nada M. B.; Ettle, Benjamin; Voehringer, Patrizia; Ferger, Boris; Winner, Beate; Nuber, Silke; Winkler, Jürgen (Journal of Neuroscience Research, 2016)
Nonmotor symptoms of cognitive and affective nature are present in premotor and motor stages of Parkinson's disease (PD). Neurogenesis, the generation of new neurons, persists throughout the mammalian life span in the hippocampal dentate gyrus. Adult hippocampal neurogenesis may be severely affected in the course of PD, accounting for some of the neuropsychiatric symptoms such as depression and cognitive impairment. Two important PD-related pathogenic factors have separately been attributed to contribute to both PD and adult hippocampal neurogenesis: dopamine depletion and accumulation of alpha-synuclein (alpha-syn). In the acute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model, altered neurogenesis has been linked merely to a reduced dopamine level. Here, we seek to determine whether a distinct endogenous alpha-syn expression pattern is associated, possibly contributing to the hippocampal neurogenic deficit. We observed a persistent reduction of striatal dopamine and a loss of tyrosine hydroxylase-expressing neurons in the substantia nigra pars compacta in contrast to a complete recovery of tyrosine hydroxylase-immunoreactive dopaminergic fibers within the striatum. However, dopamine levels in the hippocampus were significantly decreased. Survival of newly generated neurons was significantly reduced and paralleled by an accumulation of truncated, membrane-associated, insoluble alpha-syn within the hippocampus. Specifically, the presence of truncated alpha-syn species was accompanied by increased activity of calpain-1, a calcium-dependent protease. Our results further substantiate the broad effects of dopamine loss in PD-susceptible brain nuclei, gradually involved in the PD course. Our findings also indicate a detrimental synergistic interplay between dopamine depletion and posttranslational modification of alpha-syn, contributing to impaired hippocampal plasticity in PD. (C) 2015 Wiley Periodicals, Inc.
EVALuna2:25336
Keywords: MPTP; C-terminal-cleaved alpha-synuclein; calpain-1

Do telomeres have a higher plasticity than thought? Results from the German Chronic Kidney Disease (GCKD) study as a high-risk population - Raschenberger, Julia; Kollerits, Barbara; Titze, Stephanie; Koettgen, Anna; Bärthlein, Barbara; Ekici, Arif Bülent; Forer, Lukas; Schoenherr, Sebastian; Weissensteiner, Hansi; Haun, Margot; Wanner, Christoph; Eckardt, Kai-Uwe; et al. (Experimental Gerontology, 2015)
Telomere length is considered as a biological marker for aging. It is expected that telomeres shorten with age and with conditions associated with oxidative stress and inflammation. Both are present in patients with chronic kidney disease (CKD) who have a very high cardiovascular risk. We investigated whether CKD duration is associated with relative telomere length (RTL) in 4802 patients from the German Chronic Kidney Disease (GCKD) study. We measured RTL in each sample in quadruplicates using a quantitative polymerase chain reaction (qPCR). We observed a U-shaped association of RTL with CKD duration: the longest RTL was found in those 339 patients who reported the shortest disease duration (<6months) and shorter RTL in 2108 patients with duration between 6months and less than 5years. Most importantly, those 2331 patients who reported a CKD duration of 5years and more had significantly longer RTL compared to those with intermediate CKD duration (6months to less than 5years): mean 0.954, 95%CI 0.946-0.961 versus 0.937, 95%CI 0.929-0.944, p=0.002). Due to the cross-sectional nature of the study these surprising results have to be considered with caution and as hypothesis-generating. Whether the longer RTL in patients with long-lasting disease is caused by an activation of telomerase to counteract the shortening of RTL due to oxidative stress and inflammation or whether they are caused by a survival bias needs to be investigated in longitudinal studies. Our data are in support of a higher plasticity of shortening and elongations of RTL as until recently anticipated.
EVALuna2:138

Do the exome: A case of Williams-Beuren syndrome with severe epilepsy due to a truncating de novo variant in GABRA1 - Popp, Bernt; Trollmann, Regina; Büttner, Christian; Caliebe, Almuth; Thiel, Christian; Hüffmeier, Ulrike; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2016)
Williams-Beuren syndrome (WBS) is a relatively common, clinically recognizable microdeletion syndrome. In most cases the typical heterozygous deletion of 1.5 Mb on chromosome 7q11.23 spanning about 26 genes can be identified. Also some larger or smaller atypical deletions have been reported and associated with additional or atypical phenotypic aspects. We report on an individual with typical WBS due to the common deletion and with refractory infantile spasms. Using trio-exome sequencing, we identified a de novo truncating variant c.1200del, p (Lys401Serfs*25) in GABRA1 as the likely cause of the early onset epilepsy. This unique case not only allows to further define the phenotypic spectrum of infantile epileptic encephalopathy associated with rare de novo GABRA1 variants but exemplifies the need for a sensitive review of unclear associations in clinically defined syndromes and for extended diagnostic work-up in individuals with unusual presentations of a genetically confirmed diagnosis.
EVALuna2:9310

Druggable transcriptomic pathways revealed in Parkinson’s patient-derived midbrain neurons - van den Hurk, Mark; Lau, Shong; Marchetto, Maria C.; Mertens, Jerome; Stern, Shani; Corti, Olga; Brice, Alexis; Winner, Beate; Winkler, Jürgen; Gage, Fred H.; Bardy, Cedric (npj Parkinson’s Disease, 2022)
Complex genetic predispositions accelerate the chronic degeneration of midbrain substantia nigra neurons in Parkinson’s disease (PD). Deciphering the human molecular makeup of PD pathophysiology can guide the discovery of therapeutics to slow the disease progression. However, insights from human postmortem brain studies only portray the latter stages of PD, and there is a lack of data surrounding molecular events preceding the neuronal loss in patients. We address this gap by identifying the gene dysregulation of live midbrain neurons reprogrammed in vitro from the skin cells of 42 individuals, including sporadic and familial PD patients and matched healthy controls. To minimize bias resulting from neuronal reprogramming and RNA-seq methods, we developed an analysis pipeline integrating PD transcriptomes from different RNA-seq datasets (unsorted and sorted bulk vs. single-cell and Patch-seq) and reprogramming strategies (induced pluripotency vs. direct conversion). This PD cohort’s transcriptome is enriched for human genes associated with known clinical phenotypes of PD, regulation of locomotion, bradykinesia and rigidity. Dysregulated gene expression emerges strongest in pathways underlying synaptic transmission, metabolism, intracellular trafficking, neural morphogenesis and cellular stress/immune responses. We confirmed a synaptic impairment with patch-clamping and identified pesticides and endoplasmic reticulum stressors as the most significant gene-chemical interactions in PD. Subsequently, we associated the PD transcriptomic profile with candidate pharmaceuticals in a large database and a registry of current clinical trials. This study highlights human transcriptomic pathways that can be targeted therapeutically before the irreversible neuronal loss. Furthermore, it demonstrates the preclinical relevance of unbiased large transcriptomic assays of reprogrammed patient neurons.
CRIS-Team Scopus Importer:2022-10-28

Dual Function of the Retinoic Acid Catabolizing Enzyme CYP26C1-Underlying Idiopathic Short Stature and Modifying Disease Severity in SHOX Deficiency - Montalbano, Antonino; Juergensen, Lonny; Fukami, Maki; Thiel, Christian; Hauer, Nadine; Fricke-Otto, Susanne; Binder, Gerhard; Naiki, Y.; Ogata, Tsutomu; Hassel, David; Rappold, Gudrun A. (2018)
EVALuna2:34829

Dual role of the mycobacterial cord factor TDM in cross-regulation of macrophage responses to IFN gamma - Killy, Barbara; Huber, Angelika; Ekici, Arif Bülent; Wirtz, Stefan; Dalpke, A.; Lang, Roland (2017)
EVALuna2:33888

Duchenne muscular dystrophy and malignant hyperthermia: a genetic study of the ryanodine receptor in 47 patients - Rohde, Doris; Schmitt, Heike; Winterpacht, Andreas; Münster, Tino (European Journal of Anaesthesiology, 2014)
EVALuna2:9224

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Dysfunction of spatacsin leads to axonal pathology in SPG11-linked hereditary spastic paraplegia - Perez-Branguli, Francesc; Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Saul, Domenica; Rummel, Christine; Dorca-Arevalo, Jonatan; Regensburger, Martin; Graef, Daniela; Sock, Elisabeth; Blasi, Juan; et al. (Human Molecular Genetics, 2014)
Hereditary spastic paraplegias are a group of inherited motor neuron diseases characterized by progressive paraparesis and spasticity. Mutations in the spastic paraplegia gene SPG11, encoding spatacsin, cause an autosomal-recessive disease trait; however, the precise knowledge about the role of spatacsin in neurons is very limited. We for the first time analyzed the expression and function of spatacsin in human forebrain neurons derived from human pluripotent stem cells including lines from two SPG11 patients and two controls. SPG11 patients'-derived neurons exhibited downregulation of specific axonal-related genes, decreased neurite complexity and accumulation of membranous bodies within axonal processes. Altogether, these data point towards axonal pathologies in human neurons with SPG11 mutations. To further corroborate spatacsin function, we investigated human pluripotent stem cell-derived neurons and mouse cortical neurons. In these cells, spatacsin was located in axons and dendrites. It colocalized with cytoskeletal and synaptic vesicle (SV) markers and was present in synaptosomes. Knockdown of spatacsin in mouse cortical neurons evidenced that the loss of function of spatacsin leads to axonal instability by downregulation of acetylated tubulin. Finally, time-lapse assays performed in SPG11 patients'-derived neurons and spatacsin-silenced mouse neurons highlighted a reduction in the anterograde vesicle trafficking indicative of impaired axonal transport. By employing SPG11 patient-derived forebrain neurons and mouse cortical neurons, this study provides the first evidence that SPG11 is implicated in axonal maintenance and cargo trafficking. Understanding the cellular functions of spatacsin will allow deciphering mechanisms of motor cortex dysfunction in autosomal-recessive hereditary spastic paraplegia.
EVALuna2:4956

Early and late genome-wide gastric epithelial transcriptome response during infection with the human carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Ekici, Arif Bülent; Vieth, Michael; Backert, Steffen; Linz, Bodo (Cell Insight, 2022)
Infection of the stomach by Helicobacter pylori is a major risk factor for the development of gastric cancer. Colonization of the gastric epithelium leads to the activation of multiple disease-related signaling pathways. Serine protease HtrA represents an important secreted virulence factor that mediates cleavage of cellular junctions. However, its potential role in nuclear responses is unknown. Here, we performed a genome-wide RNA-seq analysis of polarized gastric epithelial cells infected by wild-type (wt) and ΔhtrA mutant bacteria. Fluorescence microscopy showed that H. pylori wt, but not ΔhtrA bacteria, preferably localized at cellular junctions. Our results pinpointed early (2 h) and late (6 h) transcriptional responses, with most differentially expressed genes at 6 h post infection. The transcriptomes revealed HtrA-dependent targeting of genes associated with inflammation and apoptosis (e.g. IL8, ZFP36, TNF). Accordingly, infection with the ΔhtrA mutant induced increased apoptosis rates in host cells, which was associated with reduced H. pylori CagA expression. In contrast, transcription of various carcinogenesis-associated genes (e.g. DKK1, DOCK8) was affected by H. pylori independent of HtrA. These findings suggest that H. pylori disturbs previously unknown molecular pathways in an HtrA-dependent and HtrA-independent manner, and provide valuable new insights of this significant pathogen in humans and thus potential targets for better controlling the risk of malignant transformation.<br
Keywords: Helicobacter; Cancer; RNA-seq; HtrA; Apoptosis; Inflammation

Early effects of aldosterone on Na+ transport and the transcriptome of cultured mouse cortical collecting duct cells (mCCDcl1) - Afonso, Sara; Bertog, Marko; Ilyaskin, Alexandr; Büttner, Clara; Ekici, Arif Bülent; Korbmacher, Christoph (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Early-onset parkinsonism in PPP2R5D-related neurodevelopmental disorder - Hetzelt, Katalin; Kerling, Frank; Kraus, Cornelia; Rauch, Christophe; Thiel, Christian; Winterholler, Martin; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2021)
PPP2R5D-related neurodevelopmental disorder (NDD) is a rare autosomal-dominant disease with developmental delay and mild to severe intellectual disability. So far, fewer than 30 affected individuals with mostly recurrent, de novo missense variants in PPP2R5D were reported. Recently, parkinsonism with an onset between 20 and 40 years was reported in four adult individuals with the same p.(Glu200Lys) variant in PPP2R5D. By trio exome sequencing we now identified the variant p.(Glu198Lys) in a 29 year old woman presenting with typical clinical manifestations of PPP2R5D-related neurodevelopmental disorder and additionally with motor decline and levodopa responsive, early-onset parkinsonism from her mid-twenties on. Accordingly, a clear reduction of dopamine transporter in the striatum on both sides was revealed by brain scintigraphy. Our findings further expand the molecular and clinical spectrum of PPP2R5D-related NDD and confirm the association with parkinsonism in early adulthood. This has marked implications for prognosis of PPP2R5D-related NDDs and for the therapeutic management of motor decline and parkinson-like symptoms in affected individuals.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Neurodevelopmental disorder; Parkinson's disease; Parkinsonism; PPP2R5D

Editorial: Intracellular Mechanisms of α-Synuclein Processing. - Zunke, Friederike; Winner, Beate; Richter, Franziska; Caraveo, Gabriela (Frontiers in Cell and Developmental Biology, 2021)
CRIS-Team Scopus Importer:2021-10-08
Keywords: alpha-synuclein; lysosomes; neurodegeneration; protein misfolding; spread; synucleinopathies

Effects of Anti-Integrin Treatment With Vedolizumab on Immune Pathways and Cytokines in Inflammatory Bowel Diseases - Rath, Timo; Billmeier, Ulrike; Ferrazzi, Fulvia; Ekici, Arif Bülent; Neurath, Markus; Atreya, Raja; Vieth, Michael (Frontiers in Immunology, 2018)
Background and aims: Despite proven clinical efficacy of vedolizumab (VDZ) for inducing and maintaining remission in patients with Crohn's disease (CD) and ulcerative colitis (UC), subgroups of patients have no therapeutic benefit from anti-α4β7 integrin therapy with VDZ. Within this study, we aimed to identify genetic, cellular, and immunological mechanisms that define response and failure to VDZ treatment. Methods: Intestinal RNA sequencing was performed in UC and CD patients before and at week 14 of VDZ therapy. α4β7 expression on peripheral and mucosal immune cells was assessed by flow cytometry and immunohistochemistry. Cellular modes of VDZ-mediated action were analyzed ex vivo and in VDZ-treated inflammatory bowel disease patients. Results: Transcriptome analysis showed an impairment of signaling cascades associated with adhesion, diapedesis, and migration of granulocytes and agranulocytes upon VDZ therapy. In non-remitters to VDZ therapy, a tissue destructive and leukocyte-mediated inflammatory activity with activation of TNF-dependent pathways was present, all of which were inhibited in remitters to VDZ. Clinical remission was associated with a significant reduction of α4β7 expression on Th2 and Th17 polarized mucosal CD4+ T cells at week 14 of VDZ therapy and with significantly higher numbers of α4β7-expressing mucosal cells prior to the initiation of VDZ therapy compared with non-remitters. Conclusion: Intestinal α4β7 expression prior to VDZ therapy might represent a biomarker that predicts therapeutic response to subsequent VDZ treatment. Due to high activation of TNF signaling in VDZ non-remitters, anti-TNF treatment might represent a promising therapeutic strategy in VDZ refractory patients.
EVALuna2:34622

Efficacy and safety of guselkumab in European patients with palmoplantar pustulosis: A multi-center, single-arm clinical trial (GAP study) - Wilsmann-Theis, Dagmar; Patt, Selina; Pinter, Andreas; Gerdes, Sascha; Magnolo, Nina; Németh, Robert; Schmitz, Jennifer; Paul, Cornelia; Augustin, Matthias; Staubach, Petra; Weyergraf, Ansgar; Hüffmeier, Ulrike; et al. (JAAD International, 2025)
Background: Palmoplantar pustulosis (PPP) is a chronic inflammatory skin disorder that affects palms and soles. Patients suffer significant pain, itching, and daily activity impairment. Guselkumab, an interleukin-23 inhibitor, has been approved for PPP treatment in Japan. However, there is no effective therapy licensed for PPP in Europe and the USA. Objective: To explore the efficacy and safety of guselkumab in patients with moderate-to-severe PPP in the Caucasian population. Methods: A multicenter, single-arm, phase II study involving 50 patients with moderate-to-severe PPP treated with 100 mg guselkumab subcutaneously for 24 weeks was conducted (GAP). Primary endpoint was the reduction of palmoplantar-pustulosis psoriasis area and severity index (PPPASI) at week 24 compared to baseline. Secondary endpoints included physician-assessed and patient-reported measures. Serum samples were taken for exploratory studies. Results: The primary endpoint was met with a significant median PPPASI reduction by 59.6% at week 24 compared to baseline (P < .001). The proportions of patients achieving PPPASI-50 and PPPASI-75 at week 24 were 66.0% and 34.0%, respectively. Median dermatology life quality index dropped from 15 at baseline to 5 at week 24 (P < .001). Week 4 changes in interleukin-19 serum levels predicted week 24 clinical response. Conclusion: Guselkumab may be a promising therapeutic option for PPP in Caucasian patients.
CRIS-Team Scopus Importer:2024-11-22
Keywords: guselkumab; IL-23; interleukin-19; multicenter trial; palmoplantar pustular psoriasis; palmoplantar pustulosis; PPPASI; smoking

Efficient and Easy Conversion of Human iPSCs into Functional Induced Microglia-like Cells - Lanfer, Jonas; Winner, Beate; Kaindl, Johanna; Krumm, Laura; Acera, Miguel Gonzalez; Neurath, Markus; Regensburger, Martin; Krach, Florian (International Journal of Molecular Sciences, 2022)
Current protocols converting human induced pluripotent stem cells (iPSCs) into induced microglia-like cells (iMGL) are either dependent on overexpression of transcription factors or require substantial experience in stem-cell technologies. Here, we developed an easy-to-use two-step protocol to convert iPSCs into functional iMGL via: (1) highly efficient differentiation of hematopoietic progenitor cells (HPCs) from iPSCs, and (2) optimized maturation of HPCs to iMGL. A sequential harvesting approach led to an increased HPC yield. The protocol implemented a freezing step, thus allowing HPC biobanking and flexible timing of differentiation into iMGL. Our iMGL responded adequately to the inflammatory stimuli LPS, and iMGL RNAseq analysis matched those of other frequently used protocols. Comparing three different coating modalities, we increased the iMGL yield by culturing on uncoated glass surfaces, thereby retaining differentiation efficiency and functional hallmarks of iMGL. In summary, we provide a high-quality, easy-to-use protocol, rendering generation and functional studies on iMGL an accessible lab resource.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cell differentiation; immunology; microglia; neurology; pluripotent stem cells

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

EIF3F-related neurodevelopmental disorder: refining the phenotypic and expanding the molecular spectrum - Hüffmeier, Ulrike; Kraus, Cornelia; Reuter, Miriam; Uebe, Steffen; Abbott, Mary-Alice; Ahmed, Syed A.; Rawson, Kristyn L.; Barr, Eileen; Li, Hong; Bruel, Ange-Line; Faivre, Laurence; Mau-Them, Frederic Tran; et al. (Orphanet Journal of Rare Diseases, 2021)
Background: An identical homozygous missense variant in EIF3F, identified through a large-scale genome-wide sequencing approach, was reported as causative in nine individuals with a neurodevelopmental disorder, characterized by variable intellectual disability, epilepsy, behavioral problems and sensorineural hearing-loss. To refine the phenotypic and molecular spectrum of EIF3F-related neurodevelopmental disorder, we examined independent patients. Results: 21 patients were homozygous and one compound heterozygous for c.694T>G/p.(Phe232Val) in EIF3F. Haplotype analyses in 15 families suggested that c.694T>G/p.(Phe232Val) was a founder variant. All affected individuals had developmental delays including delayed speech development. About half of the affected individuals had behavioral problems, altered muscular tone, hearing loss, and short stature. Moreover, this study suggests that microcephaly, reduced sensitivity to pain, cleft lip/palate, gastrointestinal symptoms and ophthalmological symptoms are part of the phenotypic spectrum. Minor dysmorphic features were observed, although neither the individuals’ facial nor general appearance were obviously distinctive. Symptoms in the compound heterozygous individual with an additional truncating variant were at the severe end of the spectrum in regard to motor milestones, speech delay, organic problems and pre- and postnatal growth of body and head, suggesting some genotype–phenotype correlation. Conclusions: Our study refines the phenotypic and expands the molecular spectrum of EIF3F-related syndromic neurodevelopmental disorder.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Altered muscular tone; Behavioral difficulties; Deafness; EIF3F gene; Neurodevelopmental disorder; Short stature

EIF3F-related neurodevelopmental disorder: refining the phenotypic and expanding the molecular spectrum - Hüffmeier, Ulrike; Kraus, Cornelia; Reuter, Miriam; Uebe, Steffen; Abbott, Mary-Alice; Ahmed, Syed A.; Rawson, Kristyn L.; Barr, Eileen; Li, Hong; Bruel, Ange-Line; Faivre, Laurence; Them, Frederic Tran Mau; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Eight further individuals with intellectual disability and epilepsy carrying bi-allelic CNTNAP2 aberrations allow delineation of the mutational and phenotypic spectrum - Smogavec, Mateja; Cleall, Alison; Hoyer, Juliane; Lederer, Damien; Nassogne, Marie-Cecile; Palmer, Elizabeth E.; Deprez, Marie; Benoit, Valerie; Maystadt, Isabelle; Noakes, Charlotte; Leal-Esquivel, Alejandro; Shaw, Marie; et al. (Journal of Medical Genetics, 2016)
Heterozygous copy number variants (CNVs) or sequence variants in the contactin-associated protein 2 gene CNTNAP2 have been discussed as risk factors for a wide spectrum of neurodevelopmental and neuropsychiatric disorders. Bi-allelic aberrations in this gene are causative for an autosomal-recessive disorder with epilepsy, severe intellectual disability (ID) and cortical dysplasia (CDFES). As the number of reported individuals is still limited, we aimed at a further characterisation of the full mutational and clinical spectrum.Targeted sequencing, chromosomal microarray analysis or multigene panel sequencing was performed in individuals with severe ID and epilepsy.We identified homozygous mutations, compound heterozygous CNVs or CNVs and mutations in CNTNAP2 in eight individuals from six unrelated families. All aberrations were inherited from healthy, heterozygous parents and are predicted to be deleterious for protein function. Epilepsy occurred in all affected individuals with onset in the first 3.5 years of life. Further common aspects were ID (severe in 6/8), regression of speech development (5/8) and behavioural anomalies (7/8). Interestingly, cognitive impairment in one of two affected brothers was, in comparison, relatively mild with good speech and simple writing abilities. Cortical dysplasia that was previously reported in CDFES was not present in MRIs of six individuals and only suspected in one.By identifying novel homozygous or compound heterozygous, deleterious CNVs and mutations in eight individuals from six unrelated families with moderate-to-severe ID, early onset epilepsy and behavioural anomalies, we considerably broaden the mutational and clinical spectrum associated with bi-allelic aberrations in CNTNAP2.
EVALuna2:9347

Encephalopathies with KCNC1 variants: genotype-phenotype-functional correlations - Cameron, Jillian M.; Maljevic, Snezana; Nair, Umesh; Aung, Ye Htet; Cogne, Benjamin; Bezieau, Stephane; Blair, Edward; Isidor, Bertrand; Zweier, Christiane; Reis, André; Koenig, Mary Kay; Maarup, Timothy; et al. (Annals of Clinical and Translational Neurology, 2019)
Objective To analyze clinical phenotypes associated with KCNC1 variants other than the Progressive Myoclonus Epilepsy-causing variant p.Arg320His, determine the electrophysiological functional impact of identified variants and explore genotype-phenotype-physiological correlations. Methods Ten cases with putative pathogenic variants in KCNC1 were studied. Variants had been identified via whole-exome sequencing or gene panel testing. Clinical phenotypic data were analyzed. To determine functional impact of variants detected in the K(v)3.1 channel encoded by KCNC1, Xenopus laevis oocyte expression system and automated two-electrode voltage clamping were used. Results Six unrelated patients had a Developmental and Epileptic Encephalopathy and a recurrent de novo variant p.Ala421Val (c.1262C > T). Functional analysis of p.Ala421Val revealed loss of function through a significant reduction in whole-cell current, but no dominant-negative effect. Three patients had a contrasting phenotype of Developmental Encephalopathy without seizures and different KCNC1 variants, all of which caused loss of function with reduced whole-cell currents. Evaluation of the variant p.Ala513Val (c.1538C > T) in the tenth case, suggested it was a variant of uncertain significance. Interpretation These are the first reported cases of Developmental and Epileptic Encephalopathy due to KCNC1 mutation. The spectrum of phenotypes associated with KCNC1 is now broadened to include not only a Progressive Myoclonus Epilepsy, but an infantile onset Developmental and Epileptic Encephalopathy, as well as Developmental Encephalopathy without seizures. Loss of function is a key feature, but definitive electrophysiological separation of these phenotypes has not yet emerged.
CRIS-Team WoS Importer:2019-07-16

Endometriosis as a risk factor for ovarian or endometrial cancer - results of a hospital-based case-control study - Burghaus, Stefanie; Haeberle, Lothar; Schrauder, Michael G.; Heusinger, Katharina; Thiel, Falk; Hein, Alexander; Wachter, David; Strehl, Johanna; Hartmann, Arndt; Ekici, Arif Bülent; Renner, Stefan; Beckmann, Matthias; et al. (BMC Cancer, 2015)
No screening programs are available for ovarian or endometrial cancer. One reason for this is the low incidence of the conditions, resulting in low positive predictive values for tests, which are not very specific. One way of addressing this problem might be to use risk factors to define subpopulations with a higher incidence. The aim of this study was to investigate the extent to which a medical history of endometriosis can serve as a risk factor for ovarian or endometrial cancer.In a hospital-based case-control analysis, the cases represented patients with endometrial or ovarian cancer who were participating in studies aimed at assessing the risk for these diseases. The controls were women between the age of 40 and 85 who were invited to take part via a newspaper advertisement. A total of 289 cases and 1016 controls were included. Using logistic regression models, it was tested whether self-reported endometriosis is a predictor of case-control status in addition to age, body mass index (BMI), number of pregnancies and previous oral contraceptive (OC) use.Endometriosis was reported in 2.1 % of the controls (n = 21) and 4.8 % of the cases (n = 14). Endometriosis was a relevant predictor for case-control status in addition to other predictive factors (OR 2.63; 95 % CI, 1.28 to 5.41).This case-control study found that self-reported endometriosis may be a risk factor for endometrial or ovarian cancer in women between 40 and 85 years. There have been very few studies addressing this issue, and incorporating it into a clinical prediction model would require a more precise characterization of the risk factor of endometriosis.
EVALuna2:6731

Enhanced meta-analysis and replication studies identify five new psoriasis susceptibility loci - Tsoi, Lam C.; Spain, Sarah L.; Ellinghaus, Eva; Stuart, Philip E.; Capon, Francesca; Knight, Jo; Tejasvi, Trilokraj; Kang, Hyun M.; Allen, Michael H.; Lambert, Sylviane; Stoll, Stefan W.; Weidinger, Stephan; et al. (Nature Communications, 2015)
Psoriasis is a chronic autoimmune disease with complex genetic architecture. Previous genome-wide association studies (GWAS) and a recent meta-analysis using Immunochip data have uncovered 36 susceptibility loci. Here, we extend our previous meta-analysis of European ancestry by refined genotype calling and imputation and by the addition of 5,033 cases and 5,707 controls. The combined analysis, consisting of over 15,000 cases and 27,000 controls, identifies five new psoriasis susceptibility loci at genome-wide significance (P<5 × 10(-8)). The newly identified signals include two that reside in intergenic regions (1q31.1 and 5p13.1) and three residing near PLCL2 (3p24.3), NFKBIZ (3q12.3) and CAMK2G (10q22.2). We further demonstrate that NFKBIZ is a TRAF3IP2-dependent target of IL-17 signalling in human skin keratinocytes, thereby functionally linking two strong candidate genes. These results further integrate the genetics and immunology of psoriasis, suggesting new avenues for functional analysis and improved therapies.
EVALuna2:9272

Enriched environment ameliorates adult hippocampal neurogenesis deficits in Tcf4 haploinsufficient mice - Braun, Kristina; Häberle, Benjamin; Wittmann, Marie-Theres; Lie, Dieter Chichung (BMC Neuroscience, 2020)
Background: Transcription factor 4 (TCF4) has been linked to human neurodevelopmental disorders such as intellectual disability, Pitt-Hopkins Syndrome (PTHS), autism, and schizophrenia. Recent work demonstrated that TCF4 participates in the control of a wide range of neurodevelopmental processes in mammalian nervous system development including neural precursor proliferation, timing of differentiation, migration, dendritogenesis and synapse formation. TCF4 is highly expressed in the adult hippocampal dentate gyrus – one of the few brain regions where neural stem / progenitor cells generate new functional neurons throughout life. Results: We here investigated whether TCF4 haploinsufficiency, which in humans causes non-syndromic forms of intellectual disability and PTHS, affects adult hippocampal neurogenesis, a process that is essential for hippocampal plasticity in rodents and potentially in humans. Young adult Tcf4 heterozygote knockout mice showed a major reduction in the level of adult hippocampal neurogenesis, which was at least in part caused by lower stem/progenitor cell numbers and impaired maturation and survival of adult-generated neurons. Interestingly, housing in an enriched environment was sufficient to enhance maturation and survival of new neurons and to substantially augment neurogenesis levels in Tcf4 heterozygote knockout mice. Conclusion: The present findings indicate that haploinsufficiency for the intellectual disability- and PTHS-linked transcription factor TCF4 not only affects embryonic neurodevelopment but impedes neurogenesis in the hippocampus of adult mice. These findings suggest that TCF4 haploinsufficiency may have a negative impact on hippocampal function throughout adulthood by impeding hippocampal neurogenesis.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Adult neurogenesis; Enriched environment; Hippocampus; Intellectual disability; PTHS; Tcf4

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Kuhns, Victoria L. Halperin; et al. (Nature Communications, 2021)
Serum urate concentration can be studied in large datasets to find genetic and epigenetic loci that may be related to cardiometabolic traits. Here the authors identify and replicate 100 urate-associated CpGs, which provide insights into urate GWAS loci and shared CpGs of urate and cardiometabolic traits.
CRIS-Team WoS Importer:2021-12-17

Epithelial-Mesenchymal Transition (EMT) Gene Variants and Epithelial Ovarian Cancer (EOC) Risk - Amankwah, Ernest K.; Lin, Hui-Yi; Tyrer, Jonathan P.; Lawrenson, Kate; Dennis, Joe; Chornokur, Ganna; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bruinsma, Fiona; Bandera, Elisa V.; Bean, Yukie T.; et al. (Genetic Epidemiology, 2015)
Epithelial-mesenchymal transition (EMT) is a process whereby epithelial cells assume mesenchymal characteristics to facilitate cancer metastasis. However, EMT also contributes to the initiation and development of primary tumors. Prior studies that explored the hypothesis that EMT gene variants contribute to epithelial ovarian carcinoma (EOC) risk have been based on small sample sizes and none have sought replication in an independent population. We screened 15,816 single-nucleotide polymorphisms (SNPs) in 296 genes in a discovery phase using data from a genome-wide association study of EOC among women of European ancestry (1,947 cases and 2,009 controls) and identified 793 variants in 278 EMT-related genes that were nominally (P < 0.05) associated with invasive EOC. These SNPs were then genotyped in a larger study of 14,525 invasive-cancer patients and 23,447 controls. A P-value <0.05 and a false discovery rate (FDR) <0.2 were considered statistically significant. In the larger dataset, GPC6/GPC5 rs17702471 was associated with the endometrioid subtype among Caucasians (odds ratio (OR) = 1.16, 95% CI = 1.07-1.25, P = 0.0003, FDR = 0.19), whereas F8 rs7053448 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), F8 rs7058826 (OR = 1.69, 95% CI = 1.27-2.24, P = 0.0003, FDR = 0.12), and CAPN13 rs1983383 (OR = 0.79, 95% CI = 0.69-0.90, P = 0.0005, FDR = 0.12) were associated with combined invasive EOC among Asians. In silico functional analyses revealed that GPC6/GPC5 rs17702471 coincided with DNA regulatory elements. These results suggest that EMT gene variants do not appear to play a significant role in the susceptibility to EOC.
EVALuna2:9299

Estimating the effect size of the 15Q11.2 BP1-BP2 deletion and its contribution to neurodevelopmental symptoms: recommendations for practice - Jønch, Aia Elise; Douard, Elise; Moreau, Clara; Van Dijck, Anke; Passeggeri, Marzia; Kooy, Frank; Puechberty, Jacques; Campbell, Carolyn; Sanlaville, Damien; Lefroy, Henrietta; Richetin, Sonia; Pain, Aurelie; et al. (Journal of Medical Genetics, 2019)
Background: The 15q11.2 deletion is frequently identified in the neurodevelopmental clinic. Case-control studies have associated the 15q11.2 deletion with neurodevelopmental disorders, and clinical case series have attempted to delineate a microdeletion syndrome with considerable phenotypic variability. The literature on this deletion is extensive and confusing, which is a challenge for genetic counselling. The aim of this study was to estimate the effect size of the 15q11.2 deletion and quantify its contribution to neurodevelopmental disorders. Methods: We performed meta-analyses on new and previously published case-control studies and used statistical models trained in unselected populations with cognitive assessments. We used new (n=241) and previously published (n=150) data from a clinically referred group of deletion carriers. 15q11.2 duplications (new n=179 and previously published n=35) were used as a neutral control variant. Results: The deletion decreases IQ by 4.3 points. The estimated ORs and respective frequencies in deletion carriers for intellectual disabilities, schizophrenia and epilepsy are 1.7 (3.4%), 1.5 (2%) and 3.1 (2.1%), respectively. There is no increased risk for heart malformations and autism. In the clinically referred group, the frequency and nature of symptoms in deletions are not different from those observed in carriers of the 15q11.2 duplication suggesting that most of the reported symptoms are due to ascertainment bias. Conclusions: We recommend that the deletion should be classified as € pathogenic of mild effect size'. Since it explains only a small proportion of the phenotypic variance in carriers, it is not worth discussing in the developmental clinic or in a prenatal setting.
CRIS-Team Scopus Importer:2019-09-27
Keywords: 15q11.2 copy-number variants; congenital heart disease; epilepsy; loss-of-function intolerance; neurodevelopmental disorders

Estrogen receptor beta rs1271572 polymorphism and invasive ovarian carcinoma risk: Pooled analysis within the ovarian cancer association consortium - Lurie, Galina; Wilkens, Lynne R.; Thompson, Pamela J.; Shvetsov, Yurii B.; Matsuno, Rayna K.; Carney, Michael E.; Palmieri, Rachel T.; Wu, Anna H.; Pike, Malcolm C.; Pearce, Celeste L.; Menon, Usha; Gentry-Maharaj, Aleksandra; et al. (PLoS ONE, 2011)
The association of ovarian carcinoma risk with the polymorphism rs1271572 in the estrogen receptor beta (ESR2) gene was examined in 4946 women with primary invasive ovarian carcinoma and 6582 controls in a pooled analysis of ten case-control studies within the Ovarian Cancer Association Consortium (OCAC). All participants were non-Hispanic white women. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using unconditional logistic regression adjusted for site and age. Women with the TT genotype were at increased risk of ovarian carcinoma compared to carriers of the G allele (OR = 1.10; 95%; CI: 1.01-1.21; p = 0.04); the OR was 1.09 (CI: 0.99-1.20; p = 0.07) after excluding data from the center (Hawaii) that nominated this SNP for OCAC genotyping A stronger association of rs1271572 TT versus GT/GG with risk was observed among women aged ≤50 years versus older women (OR = 1.35; CI: 1.12-1.62; p = 0.002; p for interaction = 0.02) that remained statistically significant after excluding Hawaii data (OR = 1.34; CI: 1.11-1.61; p = 0.009). No heterogeneity of the association was observed by study, menopausal status, gravidity, parity, use of contraceptive or menopausal hormones, tumor histological type, or stage at diagnosis. This pooled analysis suggests that rs1271572 might influence the risk of ovarian cancer, in particular among younger women. © 2011 Lurie et al.
CRIS-Team Scopus Importer:2021-07-19

Evaluating the ovarian cancer gonadotropin hypothesis: a candidate gene study - Lee, Alice W.; Tyrer, Jonathan P.; Doherty, Jennifer A.; Stram, Douglas A.; Kupryjanczyk, Jolanta; Dansonka-Mieszkowska, Agnieszka; Plisiecka-Halasa, Joanna; Spiewankiewicz, Beata; Myers, Emily J.; Chenevix-Trench, Georgia; Fasching, Peter A.; Beckmann, Matthias; et al. (Gynecologic Oncology, 2015)
Ovarian cancer is a hormone-related disease with a strong genetic basis. However, none of its high-penetrance susceptibility genes and GWAS-identified variants to date are known to be involved in hormonal pathways. Given the hypothesized etiologic role of gonadotropins, an assessment of how variability in genes involved in the gonadotropin signaling pathway impacts disease risk is warranted.Genetic data from 41 ovarian cancer study sites were pooled and unconditional logistic regression was used to evaluate whether any of the 2185 SNPs from 11 gonadotropin signaling pathway genes was associated with ovarian cancer risk. A burden test using the admixture likelihood (AML) method was also used to evaluate gene-level associations.We did not find any genome-wide significant associations between individual SNPs and ovarian cancer risk. However, there was some suggestion of gene-level associations for four gonadotropin signaling pathway genes: INHBB (p=0.045, mucinous), LHCGR (p=0.046, high-grade serous), GNRH (p=0.041, high-grade serous), and FSHB (p=0.036, overall invasive). There was also suggestive evidence for INHA (p=0.060, overall invasive).Ovarian cancer studies have limited sample numbers, thus fewer genome-wide susceptibility alleles, with only modest associations, have been identified relative to breast and prostate cancers. We have evaluated the majority of ovarian cancer studies with biological samples, to our knowledge, leaving no opportunity for replication. Using both our understanding of biology and powerful gene-level tests, we have identified four putative ovarian cancer loci near INHBB, LHCGR, GNRH, and FSHB that warrant a second look if larger sample sizes and denser genotype chips become available.
EVALuna2:9278

Evaluation of variation in the phosphoinositide-3-kinase catalytic subunit alpha oncogene and breast cancer risk - Stevens, K. N.; Garcia-Closas, Montserrat; Fredericksen, Z.; Kosel, M.; Pankratz, V. S.; Hopper, J. L.; Dite, G. S.; Apicella, C.; Southey, M. C.; Schmidt, M. K.; Broeks, A.; Van 'T Veer, L. J.; et al. (British Journal of Cancer, 2011)
Background: Somatic mutations in phosphoinositide-3-kinase catalytic subunit alpha (PIK3CA) are frequent in breast tumours and have been associated with oestrogen receptor (ER) expression, human epidermal growth factor receptor-2 overexpression, lymph node metastasis and poor survival. The goal of this study was to evaluate the association between inherited variation in this oncogene and risk of breast cancer. Methods: A single-nucleotide polymorphism from the PIK3CA locus that was associated with breast cancer in a study of Caucasian breast cancer cases and controls from the Mayo Clinic (MCBCS) was genotyped in 5436 cases and 5280 controls from the Cancer Genetic Markers of Susceptibility (CGEMS) study and in 30 949 cases and 29 788 controls from the Breast Cancer Association Consortium (BCAC). Results: Rs1607237 was significantly associated with a decreased risk of breast cancer in MCBCS, CGEMS and all studies of white Europeans combined (odds ratio (OR)=0.97, 95% confidence interval (CI) 0.95-0.99, P=4.6 × 10 3), but did not reach significance in the BCAC replication study alone (OR=0.98, 95% CI 0.96-1.01, P=0.139).Conclusion: Common germline variation in PIK3CA does not have a strong influence on the risk of breast cancer. © 2011 Cancer Research UK All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Association study; Genetic susceptibility; Neoplasms

Evidence for genetic overlap between adult onset Still's disease and hereditary periodic fever syndromes - Sighart, Regina; Rech, J.; Hueber, Axel; Blank, N.; Löhr, S.; Reis, André; Sticht, Heinrich; Hüffmeier, Ulrike (Rheumatology International, 2017)
Adult onset Still's disease (AOSD) is a severe, autoimmune disease that can be challenging to treat with conventional therapeutics and biologicals in a considerable number of cases. Therefore, there is a high need to understand its pathogenesis better. As major clinical symptoms overlap between AOSD and hereditary periodic fever syndromes (HPFS), we analysed four known HPFS genes in AOSD.We performed Sanger sequencing and quantitative analysis of all coding regions of MEFV, TNFRSF1A, MVK and NLRP3 in 40 AOSD patients. All rare coding variants (n = 6) were evaluated for several aspects to classify them as benign to pathogenic variants. Statistical analysis was performed to analyse whether variants classified as (likely) pathogenic were associated with AOSD.We identified three rare variants in MEFV, one previously not described. Association to the three likely pathogenic MEFV variants was significant (p c = 2.34E- 03), and two of the three carriers had a severe course of disease. We observed strong evidence for significant association to mutations in TNFRSF1A (p c = 2.40E- 04), as 5% of patients (2/40) carried a (likely) pathogenic variant in this gene. Both of them received a biological for treatment.Our results indicate TNFRSF1A as a relevant gene in AOSD, especially in patients with a more challenging course of disease, while causal variants remain to be identified in the majority of patients.
EVALuna2:9382

Evidence for RPGRIP1 gene as risk factor for primary open angle glaucoma - Fernández Martinez, Lorena; Letteboer, Stef; Mardin, Christian Y.; Weisschuh, Nicole; Gramer, Eugen; Weber, Bernhard H. F.; Rautenstrauß, Bernd; Ferreira, Paulo A.; Kruse, Friedrich; Reis, André; Roepman, Ronald; Pasutto, Francesca (European journal of human genetics, 2011)
Glaucoma is a genetically heterogeneous disorder and is the second cause of blindness worldwide owing to the progressive degeneration of retinal ganglion neurons. Very few genes causing glaucoma were identified to this date. In this study, we screened 10 candidate genes of glaucoma between the D14S261 and D14S121 markers of chromosome 14q11, a critical region previously linked to primary open-angle glaucoma (POAG). Mutation analyses of two large cohorts of patients with POAG, normal tension glaucoma (NTG) and juvenile open-angle glaucoma (JOAG), and control subjects, found only association of non-synonymous heterozygous variants of the retinitis pigmentosa GTPase regulator-interacting protein 1 (RPGRIP1) with POAG, NTG and JOAG. The 20 non-synonymous variants identified in RPGRIP1 were all distinct from variants causing photoreceptor dystrophies and were found throughout all but one domain (RPGR-interacting domain) of RPGRIP1. Among them, 14 missense variants clustered within or around the C2 domains of RPGRIP1. Yeast two-hybrid analyses of a subset of the missense mutations within the C2 domains of RPGRIP1 shows that five of them (p.R598Q, p.A635G, p.T806I, p.A837G and p.I838V) decrease the association of the C2 domains with nephrocystin-4 (NPHPH). When considering only these five confirmed C2-domain mutations, the association remains statistically significant (P=0.001). Altogether, the data support that heterozygous non-synonymous variants of RPGRIP1 may cause or increase the susceptibility to various forms of glaucoma and that among other factors, physical impairment of the interaction of RPGRIP1with different proteins may contribute to the pathogenesis of forms of glaucoma.
EVALuna2:9085

Evidence that breast cancer risk at the 2q35 locus is mediated through IGFBP5 regulation - Ghoussaini, Maya; Edwards, Stacey L.; Michailidou, Kyriaki; Nord, Silje; Lari, Richard Cowper-Sal; Desai, Kinjal; Kar, Siddhartha; Hillman, Kristine M.; Kaufmann, Susanne; Glubb, Dylan M.; Beesley, Jonathan; Dennis, Joe; et al. (Nature Communications, 2014)
GWAS have identified a breast cancer susceptibility locus on 2q35. Here we report the fine mapping of this locus using data from 101,943 subjects from 50 case-control studies. We genotype 276 SNPs using the 'iCOGS' genotyping array and impute genotypes for a further 1,284 using 1000 Genomes Project data. All but two, strongly correlated SNPs (rs4442975 G/T and rs6721996 G/A) are excluded as candidate causal variants at odds against >100:1. The best functional candidate, rs4442975, is associated with oestrogen receptor positive (ER+) disease with an odds ratio (OR) in Europeans of 0.85 (95% confidence interval=0.84-0.87; P=1.7 × 10(-43)) per t-allele. This SNP flanks a transcriptional enhancer that physically interacts with the promoter of IGFBP5 (encoding insulin-like growth factor-binding protein 5) and displays allele-specific gene expression, FOXA1 binding and chromatin looping. Evidence suggests that the g-allele confers increased breast cancer susceptibility through relative downregulation of IGFBP5, a gene with known roles in breast cell biolog
EVALuna2:9236

Evolutionary conserved networks of human height identify multiple Mendelian causes of short stature - Hauer, Nadine; Popp, Bernt; Taher, Leila; Vogl, Carina; Dhandapany, Perundurai S.; Büttner, Christian; Uebe, Steffen; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, Alessandro; Klinger, Patricia; et al. (European journal of human genetics, 2019)
Height is a heritable and highly heterogeneous trait. Short stature affects 3% of the population and in most cases is genetic in origin. After excluding known causes, 67% of affected individuals remain without diagnosis. To identify novel candidate genes for short stature, we performed exome sequencing in 254 unrelated families with short stature of unknown cause and identified variants in 63 candidate genes in 92 (36%) independent families. Based on systematic characterization of variants and functional analysis including expression in chondrocytes, we classified 13 genes as strong candidates. Whereas variants in at least two families were detected for all 13 candidates, two genes had variants in 6 (UBR4) and 8 (LAMA5) families, respectively. To facilitate their characterization, we established a clustered network of 1025 known growth and short stature genes, which yielded 29 significantly enriched clusters, including skeletal system development, appendage development, metabolic processes, and ciliopathy. Eleven of the candidate genes mapped to 21 of these clusters, including CPZ, EDEM3, FBRS, IFT81, KCND1, PLXNA3, RASA3, SLC7A8, UBR4, USP45, and ZFHX3. Fifty additional growth-related candidates we identified await confirmation in other affected families. Our study identifies Mendelian forms of growth retardation as an important component of idiopathic short stature.
CRIS-Team Scopus Importer:2019-05-24

Exome Pool-Seq in neurodevelopmental disorders - Popp, Bernt; Ekici, Arif Bülent; Thiel, Christian; Hoyer, Juliane; Wiesener, Antje; Kraus, Cornelia; Reis, André; Zweier, Christiane (European journal of human genetics, 2017)
High throughput sequencing has greatly advanced disease gene identification, especially in heterogeneous entities. Despite falling costs this is still an expensive and laborious technique, particularly when studying large cohorts. To address this problem we applied Exome Pool-Seq as an economic and fast screening technology in neurodevelopmental disorders (NDDs). Sequencing of 96 individuals can be performed in eight pools of 12 samples on less than one Illumina sequencer lane. In a pilot study with 96 cases we identified 27 variants, likely or possibly affecting function. Twenty five of these were identified in 923 established NDD genes (based on SysID database, status November 2016) (ACTB, AHDC1, ANKRD11, ATP6V1B2, ATRX, CASK, CHD8, GNAS, IFIH1, KCNQ2, KMT2A, KRAS, MAOA, MED12, MED13L, RIT1, SETD5, SIN3A, TCF4, TRAPPC11, TUBA1A, WAC, ZBTB18, ZMYND11), two in 543 (SysID) candidate genes (ZNF292, BPTF), and additionally a de novo loss-of-function variant in LRRC7, not previously implicated in NDDs. Most of them were confirmed to be de novo, but we also identified X-linked or autosomal-dominantly or autosomal-recessively inherited variants. With a detection rate of 28%, Exome Pool-Seq achieves comparable results to individual exome analyses but reduces costs by >85%. Compared with other large scale approaches using Molecular Inversion Probes (MIP) or gene panels, it allows flexible re-analysis of data. Exome Pool-Seq is thus well suited for large-scale, cost-efficient and flexible screening in characterized but heterogeneous entities like NDDs.
EVALuna2:9387

Exome Pool-Seq Reloaded - Popp, B.; Vasileiou, G.; Zweier, M.; Ekici, Arif Bülent; Moortgat, S.; Lederer, D.; Maystadt, I.; Destree, A.; Drunat, S.; Verloes, A.; Rauch, A.; Steindl, K.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Exome sequencing unravels unexpected differential diagnoses in individuals with the tentative diagnosis of Coffin-Siris and Nicolaides-Baraitser syndromes - Bramswig, Nuria C.; Luedecke, Hermann-Josef; Alanay, Yasemin; Albrecht, Beate; Barthelmie, Alexander; Boduroglu, Koray; Braunholz, Diana; Caliebe, Almuth; Chrzanowska, Krystyna H.; Czeschik, Johanna Christina; Endele, Sabine; Graf, Elisabeth; et al. (Human genetics, 2015)
Coffin-Siris syndrome (CSS) and Nicolaides-Baraitser syndrome (NCBRS) are rare intellectual disability/congenital malformation syndromes that represent distinct entities but show considerable clinical overlap. They are caused by mutations in genes encoding members of the BRG1- and BRM-associated factor (BAF) complex. However, there are a number of patients with the clinical diagnosis of CSS or NCBRS in whom the causative mutation has not been identified. In this study, we performed trio-based whole-exome sequencing (WES) in ten previously described but unsolved individuals with the tentative diagnosis of CSS or NCBRS and found causative mutations in nine out of ten individuals. Interestingly, our WES analysis disclosed overlapping differential diagnoses including Wiedemann-Steiner, Kabuki, and Adams-Oliver syndromes. In addition, most likely causative de novo mutations were identified in GRIN2A and SHANK3. Moreover, trio-based WES detected SMARCA2 and SMARCA4 deletions, which had not been annotated in a previous Haloplex target enrichment and next-generation sequencing of known CSS/NCBRS genes emphasizing the advantages of WES as a diagnostic tool. In summary, we discuss the phenotypic and diagnostic challenges in clinical genetics, establish important differential diagnoses, and emphasize the cardinal features and the broad clinical spectrum of BAF complex disorders and other disorders caused by mutations in epigenetic landscapers.
EVALuna2:9264

Exome-wide association study reveals novel psoriasis susceptibility locus at TNFSF15 and rare protective alleles in genes contributing to type I IFN signalling - Dand, Nick; Mucha, Soeren; Tsoi, Lam C.; Mahil, Satveer K.; Stuart, Philip E.; Arnold, Andreas; Baurecht, Hansjoerg; Burden, A. David; Duffin, Kristina Callis; Chandran, Vinod; Curtis, Charles J.; Das, Sayantan; et al. (Human Molecular Genetics, 2017)
Psoriasis is a common inflammatory skin disorder for which multiple genetic susceptibility loci have been identified, but few resolved to specific functional variants. In this study, we sought to identify common and rare psoriasis-associated gene-centric variation. Using exome arrays we genotyped four independent cohorts, totalling 11 861 psoriasis cases and 28 610 controls, aggregating the dataset through statistical meta-analysis. Single variant analysis detected a previously unreported risk locus at TNFSF15 (rs6478108; P = 1.50 × 10-8, OR = 1.10), and association of common protein-altering variants at 11 loci previously implicated in psoriasis susceptibility. We validate previous reports of protective low-frequency protein-altering variants within IFIH1 (encoding an innate antiviral receptor) and TYK2 (encoding a Janus kinase), in each case establishing a further series of protective rare variants (minor allele frequency < 0.01) via gene-wide aggregation testing (IFIH1: pburden = 2.53 × 10-7, OR = 0.707; TYK2: pburden = 6.17 × 10-4, OR = 0.744). Both genes play significant roles in type I interferon (IFN) production and signalling. Several of the protective rare and low-frequency variants in IFIH1 and TYK2 disrupt conserved protein domains, highlighting potential mechanisms through which their effect may be exerted.
EVALuna2:9384

Expanded phenotypic spectrum of neurodevelopmental and neurodegenerative disorder Bryant-Li-Bhoj syndrome with 38 additional individuals - Layo-Carris, Dana E.; Lubin, Emily E.; Sangree, Annabel K.; Clark, Kelly J.; Durham, Emily L.; Gonzalez, Elizabeth M.; Smith, Sarina; Angireddy, Rajesh; Wang, Xiao Min; Weiss, Erin; Toutain, Annick; Mendoza-Londono, Roberto; et al. (European Journal of Human Genetics, 2024)
Bryant-Li-Bhoj syndrome (BLBS), which became OMIM-classified in 2022 (OMIM: 619720, 619721), is caused by germline variants in the two genes that encode histone H3.3 (H3-3A/H3F3A and H3-3B/H3F3B) [1–4]. This syndrome is characterized by developmental delay/intellectual disability, craniofacial anomalies, hyper/hypotonia, and abnormal neuroimaging [1, 5]. BLBS was initially categorized as a progressive neurodegenerative syndrome caused by de novo heterozygous variants in either H3-3A or H3-3B [1–4]. Here, we analyze the data of the 58 previously published individuals along 38 unpublished, unrelated individuals. In this larger cohort of 96 people, we identify causative missense, synonymous, and stop-loss variants. We also expand upon the phenotypic characterization by elaborating on the neurodevelopmental component of BLBS. Notably, phenotypic heterogeneity was present even amongst individuals harboring the same variant. To explore the complex phenotypic variation in this expanded cohort, the relationships between syndromic phenotypes with three variables of interest were interrogated: sex, gene containing the causative variant, and variant location in the H3.3 protein. While specific genotype-phenotype correlations have not been conclusively delineated, the results presented here suggest that the location of the variants within the H3.3 protein and the affected gene (H3-3A or H3-3B) contribute more to the severity of distinct phenotypes than sex. Since these variables do not account for all BLBS phenotypic variability, these findings suggest that additional factors may play a role in modifying the phenotypes of affected individuals. Histones are poised at the interface of genetics and epigenetics, highlighting the potential role for gene-environment interactions and the importance of future research.
CRIS-Team Scopus Importer:2024-05-10

Expanding the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and functional proof of aberrant WRC-mediated actin dynamics - Begemann, A.; Sticht, Heinrich; Mcwalter, K.; Vitobello, A.; Faivre, L.; Alhaddad, B.; Banka, S.; Becker, J.; Bierhals, T.; Brown, K.; Bruel, A.; Brunet, T.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Expanding the clinical and mutational spectrum of Kaufman oculocerebrofacial syndrome with biallelic UBE3B mutations - Basel-Vanagaite, Lina; Yilmaz, Rustem; Tang, Sha; Reuter, Miriam; Rahner, Nils; Grange, Dorothy K.; Mortenson, Megan; Koty, Patrick; Feenstra, Heather; Gonzalez, Kelly D. Farwell; Sticht, Heinrich; Boddaert, Nathalie; et al. (Human genetics, 2014)
Biallelic mutations of UBE3B have recently been shown to cause Kaufman oculocerebrofacial syndrome (also reported as blepharophimosis-ptosis-intellectual disability syndrome), an autosomal recessive condition characterized by hypotonia, developmental delay, intellectual disability, congenital anomalies, characteristic facial dysmorphic features, and low cholesterol levels. To date, six patients with either missense mutations affecting the UBE3B HECT domain or truncating mutations have been described. Here, we report on the identification of homozygous or compound heterozygous UBE3B mutations in six additional patients from five unrelated families using either targeted UBE3B sequencing in individuals with suggestive facial dysmorphic features, or exome sequencing. Our results expand the clinical and mutational spectrum of the UBE3B-related disorder in several ways. First, we have identified UBE3B mutations in individuals who previously received distinct clinical diagnoses: two sibs with Toriello-Carey syndrome as well as the patient reported to have a "new" syndrome by Buntinx and Majewski in 1990. Second, we describe the adult phenotype and clinical variability of the syndrome. Third, we report on the first instance of homozygous missense alterations outside the HECT domain of UBE3B, observed in a patient with mildly dysmorphic facial features. We conclude that UBE3B mutations cause a clinically recognizable and possibly underdiagnosed syndrome characterized by distinct craniofacial features, hypotonia, failure to thrive, eye abnormalities, other congenital malformations, low cholesterol levels, and severe intellectual disability. We review the UBE3B-associated phenotypes, including forms that can mimick Toriello-Carey syndrome, and suggest the single designation "Kaufman oculocerebrofacial syndrome".
EVALuna2:9227

Expanding the clinical spectrum of COL1A1 mutations in different forms of glaucoma - Mauri, Lucia; Uebe, Steffen; Sticht, Heinrich; Vossmerbaeumer, Urs; Weisschuh, Nicole; Manfredini, Emanuela; Maselli, Edoardo; Patrosso, Mariacristina; Weinreb, Robert N.; Penco, Silvana; Reis, André; Pasutto, Francesca (Orphanet Journal of Rare Diseases, 2016)
Primary congenital glaucoma (PCG) and early onset glaucomas are one of the major causes of children and young adult blindness worldwide. Both autosomal recessive and dominant inheritance have been described with involvement of several genes including CYP1B1, FOXC1, PITX2, MYOC and PAX6. However, mutations in these genes explain only a small fraction of cases suggesting the presence of further candidate genes.To elucidate further genetic causes of these conditions whole exome sequencing (WES) was performed in an Italian patient, diagnosed with PCG and retinal detachment, and his unaffected parents. Sanger sequencing of the complete coding region of COL1A1 was performed in a total of 26 further patients diagnosed with PCG or early onset glaucoma. Exclusion of pathogenic variations in known glaucoma genes as CYP1B1, MYOC, FOXC1, PITX2 and PAX6 was additionally done per Sanger sequencing and Multiple Ligation-dependent Probe Amplification (MLPA) analysis.In the patient diagnosed with PCG and retinal detachment, analysis of WES data identified compound heterozygous variants in COL1A1 (p.Met264Leu; p.Ala1083Thr). Targeted COL1A1 screening of 26 additional patients detected three further heterozygous variants (p.Arg253*, p.Gly767Ser and p.Gly154Val) in three distinct subjects: two of them diagnosed with early onset glaucoma and mild form of osteogenesis imperfecta (OI), one patient with a diagnosis of PCG at age 4 years. All five variants affected evolutionary, highly conserved amino acids indicating important functional restrictions. Molecular modeling predicted that the heterozygous variants are dominant in effect and affect protein stability and thus the amount of available protein, while the compound heterozygous variants act as recessive alleles and impair binding affinity to two main COL1A1 binding proteins: Hsp47 and fibronectin.Dominant inherited mutations in COL1A1 are known causes of connective tissues disorders such as OI. These disorders are also associated with different ocular abnormalities, although recognition of the common pathology for both features is seldom being recognized. Our results expand the role of COL1A1 mutations in different forms of early-onset glaucoma with and without signs of OI. Thus, we suggest including COL1A1 mutation screening in the genetic work-up of glaucoma cases and detailed ophthalmic examinations with fundus analysis in patients with OI.
EVALuna2:9324

Expanding the Phenotype Associated with NAA10-Related N-Terminal Acetylation Deficiency - Saunier, Chloe; Stove, Svein Isungset; Popp, Bernt; Gerard, Benedicte; Blenski, Marina; Ahmew, Nicholas; De Bie, Charlotte; Goldenberg, Paula; Isidor, Bertrand; Keren, Boris; Leheup, Bruno; Lampert, Laetitia; et al. (Human Mutation, 2016)
N-terminal acetylation is a common protein modification in eukaryotes associated with numerous cellular processes. Inherited mutations in NAA10, encoding the catalytic subunit of the major N-terminal acetylation complex NatA have been associated with diverse, syndromic X-linked recessive disorders, whereas de novo missense mutations have been reported in one male and one female individual with severe intellectual disability but otherwise unspecific phenotypes. Thus, the full genetic and clinical spectrum of NAA10 deficiency is yet to be delineated. We identified three different novel and one known missense mutation in NAA10, de novo in 11 females, and due to maternal germ line mosaicism in another girl and her more severely affected and deceased brother. In vitro enzymatic assays for the novel, recurrent mutations p.(Arg83Cys) and p.(Phe128Leu) revealed reduced catalytic activity. X-inactivation was random in five females. The core phenotype of X-linked NAA10-related N-terminal-acetyltransferase deficiency in both males and females includes developmental delay, severe intellectual disability, postnatal growth failure with severe microcephaly, and skeletal or cardiac anomalies. Genotype-phenotype correlations within and between both genders are complex and may include various factors such as location and nature of mutations, enzymatic stability and activity, and X-inactivation in females.
EVALuna2:9314

Expanding the phenotype of 12q21 deletions: A role of BTG1 in speech development? - Blum, Katalin; Krumbiegel, Mandy; Kraus, Cornelia; Reis, André; Hüffmeier, Ulrike (European Journal of Medical Genetics, 2023)
We report on a female individual with feeding difficulties, constipation, poor overall growth, periventricular lesions resembling gliosis in brain MRI, recurrent otitis media with palsy of facial nerve, distinct facial features, and pronounced delay in speech development. The latter was the most prominent feature. Molecular karyotyping revealed a heterozygous de novo deletion of 4.353 Mb at chromosome 12q21.33q22. This report expands the number of described individuals with heterozygous deletions at 12q21.33, their clinical spectrum and highlights the clinical variability, even in individuals with deletion of the same genes. Furthermore, our findings indicate a role of BTG1 (OMIM *109580) in speech development.
CRIS-Team Scopus Importer:2023-02-24
Keywords: 12q21.33; Microdeletion; Speech developmental delay

Expanding the spectrum of WDR62 mutations : description of new cases - Ruaud, L.; Drunat, S.; Ernault, A.; Capri, Y.; Van Maldergem, L.; Engel, C.; Altuzarra, C.; Bayat, A.; Moortgart, S.; Maystadt, I.; Abramowicz, M.; Zweier, Christiane; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Experimental epileptogenesis in a cell culture model of primary neurons from rat brain: A temporal multi‐scale study - Jablonski, Janos; Hoffmann, Lucas; Blümcke, Ingmar; Fejtová, Anna; Uebe, Steffen; Ekici, Arif Bülent; Gnatkovsky, Vadym; Kobow, Katja (Cells, 2021)
Understanding seizure development requires an integrated knowledge of different scales of organization of epileptic networks. We developed a model of “epilepsy‐in‐a‐dish” based on dissociated primary neuronal cells from neonatal rat hippocampus. We demonstrate how a single application of glutamate stimulated neurons to generate spontaneous synchronous spiking activity with further progression into spontaneous seizure‐like events after a distinct latency period. By computational analysis, we compared the observed neuronal activity in vitro with intracranial electroencephalography (EEG) data recorded from epilepsy patients and identified strong similarities, including a related sequence of events with defined onset, progression, and termination. Next, a link between the neurophysiological changes with network composition and cellular structure down to molecular changes was established. Temporal development of epileptiform network activity correlated with increased neurite outgrowth and altered branching, increased ratio of glutamatergic over GABAergic synapses, and loss of calbindin‐positive interneurons, as well as genome‐wide alterations in DNA methylation. Differentially methylated genes were engaged in various cellular activities related to cellular structure, intracellular signaling, and regulation of gene expression. Our data provide evidence that a single short‐term excess of glutamate is sufficient to induce a cascade of events covering different scales from molecule‐ to network‐level, all of which jointly contribute to seizure development.
CRIS-Team Scopus Importer:2021-11-12
Keywords: DNA methylation; Epigenetic; Epilepsy; In vitro

Exploring the phenotypical spectrum of BRD4 defects - Hauer, Nadine; Vogl, C.; Popp, Bernt; Buettner, C.; Uebe, S.; Sticht, Heinrich; Ekici, Arif Bülent; Klinger, Patricia; Kraus, Cornelia; Krumbiegel, M.; Wiesener, A.; Dörr, Helmuth-Günther; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Ex Vivo Chromosomal Radiosensitivity Testing in Patients with Pathological Germline Variants in Breast Cancer High-Susceptibility Genes BReast CAncer 1 and BReast CAncer 2 - Zuhair Kassem, Tara; Wunderle, Marius; Kuhlmann, Lukas; Rübner, Matthias; Hübner, Hanna; Hoyer, Juliane; Reis, André; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Current Issues in Molecular Biology, 2023)
Background: Individual radiosensitivity is an important factor in the occurrence of undesirable consequences of radiotherapy. The potential for increased radiosensitivity has been linked to highly penetrant heterozygous mutations in DNA repair genes such as BRCA1 and BRCA2. By studying the chromosomal radiosensitivity of BRCA1/2 mutation carriers compared to the general population, we study whether increased chromosomal radiation sensitivity is observed in patients with BRCA1/2 variants. Methods: Three-color-fluorescence in situ hybridization was performed on ex vivo-irradiated peripheral blood lymphocytes from 64 female patients with a heterozygous germline BRCA1 or BRCA2 mutation. Aberrations in chromosomes #1, #2 and #4 were analyzed. Mean breaks per metaphase (B/M) served as the parameter for chromosomal radiosensitivity. The results were compared with chromosomal radiosensitivity in a cohort of generally healthy individuals and patients with rectal cancer or breast cancer. Results: Patients with BRCA1/2 mutations (n = 64; B/M 0.47) overall showed a significantly higher chromosomal radiosensitivity than general healthy individuals (n = 211; B/M 0.41) and patients with rectal cancer (n = 379; B/M 0.44) and breast cancer (n = 147; B/M 0.45) without proven germline mutations. Chromosomal radiosensitivity varied depending on the locus of the BRCA1/2 mutation. Conclusions: BRCA1/2 mutations result in slightly increased chromosomal sensitivity to radiation. A few individual patients have a marked increase in radiation sensitivity. Therefore, these patients are at a higher risk for adverse therapeutic consequences.
CRIS-Team Scopus Importer:2023-09-08
Keywords: BRCA1; BRCA2; breast cancer; chromosomal radiosensitivity; FISH assay; radiation oncology; radiation sensitivity testing; radiotherapy

EZH2 specifically regulates ISL1 during embryonic urinary tract formation - Mingardo, Enrico; Kalanithy, Jeshurun C.; Dworschak, Gabriel; Ishorst, Nina; Yilmaz, Öznur; Lindenberg, Tobias; Hollstein, Ronja; Felger, Tim; Angrand, Pierre-Olivier; Reutter, Heiko M.; Reutter, Heiko Martin; Odermatt, Benjamin (Scientific Reports, 2024)
Isl1 has been described as an embryonic master control gene expressed in the pericloacal mesenchyme. Deletion of Isl1 from the genital mesenchyme in mice leads to an ectopic urethral opening and epispadias-like phenotype. Using genome wide association methods, we identified ISL1 as the key susceptibility gene for classic bladder exstrophy (CBE), comprising epispadias and exstrophy of the urinary bladder. The most significant marker (rs6874700) identified in our recent GWAS meta-analysis achieved a p value of 1.48 × 10- 24 within the ISL1 region. In silico analysis of rs6874700 and all other genome-wide significant markers in Linkage Disequilibrium (LD) with rs6874700 (D' = 1.0; R2 > 0.90) revealed marker rs2303751 (p value 8.12 × 10- 20) as the marker with the highest regulatory effect predicted. Here, we describe a novel 1.2 kb intragenic promoter residing between 6.2 and 7.4 kb downstream of the ISL1 transcription starting site, which is located in the reverse DNA strand and harbors a binding site for EZH2 at the exact region of marker rs2303751. We show, that EZH2 silencing in HEK cells reduces ISL1 expression. We show that ezh2-/- knockout (KO) zebrafish larvae display tissues specificity of ISL1 regulation with reduced expression of Isl1 in the pronephric region of zebrafish larvae. In addition, a shorter and malformed nephric duct is observed in ezh2-/- ko zebrafish Tg(wt1ß:eGFP) reporter lines. Our study shows, that Ezh2 is a key regulator of Isl1 during urinary tract formation and suggests tissue specific ISL1 dysregulation as an underlying mechanism for CBE formation.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Classic bladder exstrophy; EZH2; Gene regulation; HEK293; ISL1; Promoter; Zebrafish

FAM13A is associated with non-small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival - Eisenhut, Felix; Heim, Lisanne; Trump, Sonja; Mittler, Susanne; Sopel, Nina; Andreev, Katerina; Ferrazzi, Fulvia; Ekici, Arif Bülent; Rieker, Ralf; Springel, Rebekka; Assmann, Vera Elisabeth; Lechmann, Matthias; et al. (OncoImmunology, 2017)
Genome-wide association studies (GWAS) associated Family with sequence similarity 13, member A (FAM13A) with non-small cell lung cancer (NSCLC) occurrence. Here, we found increased numbers of FAM13A protein expressing cells in the tumoral region of lung tissues from a cohort of patients with NSCLC. Moreover, FAM13A inversely correlated with CTLA4 but directly correlated with HIF1? levels in the control region of these patients. Consistently, FAM13A RhoGAP was found to be associated with T cell effector molecules like HIF1? and Tbet and was downregulated in immunosuppressive CD4(+)CD25(+)Foxp3(+)CTLA4(+) T cells. TGF?, a tumor suppressor factor, as well as siRNA to FAM13A, suppressed both isoforms of FAM13A and inhibited tumor cell proliferation. RNA-Seq analysis confirmed this finding. Moreover, siRNA to FAM13A induced TGF? levels. Finally, in experimental tumor cell migration, FAM13A was induced and TGF? accelerated this process by inducing cell migration, HIF1?, and the FAM13A RhoGAP isoform. Furthermore, siRNA to FAM13A inhibited tumor cell proliferation and induced cell migration without affecting HIF1?. In conclusion, FAM13A is involved in tumor cell proliferation and downstream of TGF? and HIF1?, FAM13A RhoGAP is associated with Th1 gene expression and lung tumor cell migration. These findings identify FAM13A as key regulator of NSCLC growth and progression.
EVALuna2:6835

Familial acute aortic dissection associated with a novel ACTA2 germline variant - Strecker, Thomas; Wiesmueller, Felix; Rudnik-Schoeneborn, Sabine; Hoyer, Juliane; Wiesmann da Silva Reis, André; Weyand, Michael; Agaimy, Abbas (Virchows Archiv, 2022)
Aortic dissection is a life-threatening cardiovascular disease. Hereditary disorders are responsible for a small percentage of cases. Nonetheless, it is important to identify genetic causes, as they are often autosomal dominantly inherited and are of life-saving importance if we can identify persons at risk. Mutations of the ACTA2 gene are the most common cause of non-syndromic familial aortic disease. Exploration of the genetic background in suspected familial cases and determination of the exact etiology are mandatory for management and establishing appropriate follow-up strategies due to the risk of fatal recurrences. Herein, we present a 21-year-old male with a familial acute aortic dissection associated with novel ACTA2 germline variant and discuss the management and surveillance considerations.
CRIS-Team WoS Importer:2022-08-05

FcγRIIa genotype is associated with acute coronary syndromes as first manifestation of coronary artery disease - Raaz, Dorette; Herrmann, Martin; Ekici, Arif Bülent; Klinghammer, Lutz; Lausen, Berthold; Voll, Reinhard E.; Leusen, Jeanette H.W.; van de Winkel, Jan G.J.; Daniel, Werner; Reis, André; Garlichs, Christoph (Atherosclerosis, 2009)
Objective: Identification of clinically relevant determinants for acute coronary syndromes (ACS) promises reduction of ACS-associated mortality. C-reactive protein (CRP) has proved to be useful identifying people at risk for cardiovascular events. However, it is unknown whether genetic variants at Fcγ receptor IIa (FcγRIIa), the main receptor for CRP, are involved in CRP-related cardiovascular risk. We evaluated the potential impact of FcγRIIa through a genetic association study in patients with ACS. Methods and results: We conducted a genetic association study among 701 consecutive patients with first event of ACS compared to 467 patients with stable angina pectoris. All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa, where the arginine (R) allele results in an increased signal transduction upon CRP binding. In our study, the R/R131 genotype was significantly associated with ACS as the first manifestation of coronary artery disease (P = 1.2 × 10-9, odds ratio 2.86, 95% CI: 2.06-3.99) compared to the non-R/R131 genotype. Conclusions: Our data show a genetic association of the FcγRIIa R/R131 genotype with a more frequent occurrence of ACS as the first manifestation of coronary artery disease, probably mediated via its interaction with CRP. Genotyping of this FcγRIIa variant could help to improve risk stratification in the course of coronary disease in the future. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute coronary syndrome; Fcγ receptor IIa; Gene polymorphism; Inflammation

FGF receptor genes and breast cancer susceptibility: results from the Breast Cancer Association Consortium - Agarwal, D.; Pineda, S.; Michailidou, K.; Herranz, J.; Pita, G.; Moreno, L. T.; Alonso, M. R.; Dennis, J.; Wang, Q.; Bolla, M. K.; Meyer, K. B.; Menendez-Rodriguez, P.; et al. (British Journal of Cancer, 2014)
Breast cancer is one of the most common malignancies in women. Genome-wide association studies have identified FGFR2 as a breast cancer susceptibility gene. Common variation in other fibroblast growth factor (FGF) receptors might also modify risk. We tested this hypothesis by studying genotyped single-nucleotide polymorphisms (SNPs) and imputed SNPs in FGFR1, FGFR3, FGFR4 and FGFRL1 in the Breast Cancer Association Consortium.Data were combined from 49 studies, including 53 835 cases and 50 156 controls, of which 89 050 (46 450 cases and 42 600 controls) were of European ancestry, 12 893 (6269 cases and 6624 controls) of Asian and 2048 (1116 cases and 932 controls) of African ancestry. Associations with risk of breast cancer, overall and by disease sub-type, were assessed using unconditional logistic regression.Little evidence of association with breast cancer risk was observed for SNPs in the FGF receptor genes. The strongest evidence in European women was for rs743682 in FGFR3; the estimated per-allele odds ratio was 1.05 (95% confidence interval=1.02-1.09, P=0.0020), which is substantially lower than that observed for SNPs in FGFR2.Our results suggest that common variants in the other FGF receptors are not associated with risk of breast cancer to the degree observed for FGFR2.
EVALuna2:9221

Fine-mapping identifies two additional breast cancer susceptibility loci at 9q31.2 - Orr, Nick; Dudbridge, Frank; Dryden, Nicola; Maguire, Sarah; Novo, Daniela; Perrakis, Eleni; Johnson, Nichola; Ghoussaini, Maya; Hopper, John L.; Southey, Melissa C.; Apicella, Carmel; Stone, Jennifer; et al. (Human Molecular Genetics, 2015)
We recently identified a novel susceptibility variant, rs865686, for estrogen-receptor positive breast cancer at 9q31.2. Here, we report a fine-mapping analysis of the 9q31.2 susceptibility locus using 43 160 cases and 42 600 controls of European ancestry ascertained from 52 studies and a further 5795 cases and 6624 controls of Asian ancestry from nine studies. Single nucleotide polymorphism (SNP) rs676256 was most strongly associated with risk in Europeans (odds ratios [OR] = 0.90 [0.88-0.92]; P-value = 1.58 × 10(-25)). This SNP is one of a cluster of highly correlated variants, including rs865686, that spans 14.5 kb. We identified two additional independent association signals demarcated by SNPs rs10816625 (OR = 1.12 [1.08-1.17]; P-value = 7.89 × 10(-09)) and rs13294895 (OR = 1.09 [1.06-1.12]; P-value = 2.97 × 10(-11)). SNP rs10816625, but not rs13294895, was also associated with risk of breast cancer in Asian individuals (OR = 1.12 [1.06-1.18]; P-value = 2.77 × 10(-05)). Functional genomic annotation using data derived from breast cancer cell-line models indicates that these SNPs localise to putative enhancer elements that bind known drivers of hormone-dependent breast cancer, including ER-?, FOXA1 and GATA-3. In vitro analyses indicate that rs10816625 and rs13294895 have allele-specific effects on enhancer activity and suggest chromatin interactions with the KLF4 gene locus. These results demonstrate the power of dense genotyping in large studies to identify independent susceptibility variants. Analysis of associations using subjects with different ancestry, combined with bioinformatic and genomic characterisation, can provide strong evidence for the likely causative alleles and their functional basi
EVALuna2:9279

Fine-mapping of the HNF1B multicancer locus identifies candidate variants that mediate endometrial cancer risk - Painter, Jodie N.; O'Mara, Tracy A.; Batra, Jyotsna; Cheng, Timothy; Lose, Felicity A.; Dennis, Joe; Michailidou, Kyriaki; Tyrer, Jonathan P.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; Kaufmann, Susanne; et al. (Human Molecular Genetics, 2015)
Common variants in the hepatocyte nuclear factor 1 homeobox B (HNF1B) gene are associated with the risk of Type II diabetes and multiple cancers. Evidence to date indicates that cancer risk may be mediated via genetic or epigenetic effects on HNF1B gene expression. We previously found single-nucleotide polymorphisms (SNPs) at the HNF1B locus to be associated with endometrial cancer, and now report extensive fine-mapping and in silico and laboratory analyses of this locus. Analysis of 1184 genotyped and imputed SNPs in 6608 Caucasian cases and 37 925 controls, and 895 Asian cases and 1968 controls, revealed the best signal of association for SNP rs11263763 (P = 8.4 × 10(-14), odds ratio = 0.86, 95% confidence interval = 0.82-0.89), located within HNF1B intron 1. Haplotype analysis and conditional analyses provide no evidence of further independent endometrial cancer risk variants at this locus. SNP rs11263763 genotype was associated with HNF1B mRNA expression but not with HNF1B methylation in endometrial tumor samples from The Cancer Genome Atlas. Genetic analyses prioritized rs11263763 and four other SNPs in high-to-moderate linkage disequilibrium as the most likely causal SNPs. Three of these SNPs map to the extended HNF1B promoter based on chromatin marks extending from the minimal promoter region. Reporter assays demonstrated that this extended region reduces activity in combination with the minimal HNF1B promoter, and that the minor alleles of rs11263763 or rs8064454 are associated with decreased HNF1B promoter activity. Our findings provide evidence for a single signal associated with endometrial cancer risk at the HNF1B locus, and that risk is likely mediated via altered HNF1B gene expression.
EVALuna2:9243

Fine-scale mapping of the 5q11.2 breast cancer locus reveals at least three independent risk variants regulating MAP3K1 - Glubb, Dylan M.; Maranian, Mel J.; Michailidou, Kyriaki; Pooley, Karen A.; Meyer, Kerstin B.; Kar, Siddhartha; Carlebur, Saskia; O'Reilly, Martin; Betts, Joshua A.; Hillman, Kristine M.; Kaufmann, Susanne; Beesley, Jonathan; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies (GWASs) have revealed SNP rs889312 on 5q11.2 to be associated with breast cancer risk in women of European ancestry. In an attempt to identify the biologically relevant variants, we analyzed 909 genetic variants across 5q11.2 in 103,991 breast cancer individuals and control individuals from 52 studies in the Breast Cancer Association Consortium. Multiple logistic regression analyses identified three independent risk signals: the strongest associations were with 15 correlated variants (iCHAV1), where the minor allele of the best candidate, rs62355902, associated with significantly increased risks of both estrogen-receptor-positive (ER(+): odds ratio [OR] = 1.24, 95% confidence interval [CI] = 1.21-1.27, ptrend = 5.7 × 10(-44)) and estrogen-receptor-negative (ER(-): OR = 1.10, 95% CI = 1.05-1.15, ptrend = 3.0 × 10(-4)) tumors. After adjustment for rs62355902, we found evidence of association of a further 173 variants (iCHAV2) containing three subsets with a range of effects (the strongest was rs113317823 [pcond = 1.61 × 10(-5)]) and five variants composing iCHAV3 (lead rs11949391; ER(+): OR = 0.90, 95% CI = 0.87-0.93, pcond = 1.4 × 10(-4)). Twenty-six percent of the prioritized candidate variants coincided with four putative regulatory elements that interact with the MAP3K1 promoter through chromatin looping and affect MAP3K1 promoter activity. Functional analysis indicated that the cancer risk alleles of four candidates (rs74345699 and rs62355900 [iCHAV1], rs16886397 [iCHAV2a], and rs17432750 [iCHAV3]) increased MAP3K1 transcriptional activity. Chromatin immunoprecipitation analysis revealed diminished GATA3 binding to the minor (cancer-protective) allele of rs17432750, indicating a mechanism for its action. We propose that the cancer risk alleles act to increase MAP3K1 expression in vivo and might promote breast cancer cell surviva
EVALuna2:9276

Five endometrial cancer risk loci identified through genome-wide association analysis - Cheng, Timothy H. T.; Thompson, Deborah J.; O'Mara, Tracy A.; Painter, Jodie N.; Glubb, Dylan M.; Flach, Susanne; Lewis, Annabelle; French, Juliet D.; Freeman-Mills, Luke; Church, David; Gorman, Maggie; Martin, Lynn; et al. (Nature Genetics, 2016)
We conducted a meta-analysis of three endometrial cancer genome-wide association studies (GWAS) and two follow-up phases totaling 7,737 endometrial cancer cases and 37,144 controls of European ancestry. Genome-wide imputation and meta-analysis identified five new risk loci of genome-wide significance at likely regulatory regions on chromosomes 13q22.1 (rs11841589, near KLF5), 6q22.31 (rs13328298, in LOC643623 and near HEY2 and NCOA7), 8q24.21 (rs4733613, telomeric to MYC), 15q15.1 (rs937213, in EIF2AK4, near BMF) and 14q32.33 (rs2498796, in AKT1, near SIVA1). We also found a second independent 8q24.21 signal (rs17232730). Functional studies of the 13q22.1 locus showed that rs9600103 (pairwise r(2) = 0.98 with rs11841589) is located in a region of active chromatin that interacts with the KLF5 promoter region. The rs9600103[T] allele that is protective in endometrial cancer suppressed gene expression in vitro, suggesting that regulation of the expression of KLF5, a gene linked to uterine development, is implicated in tumorigenesis. These findings provide enhanced insight into the genetic and biological basis of endometrial cancer.
EVALuna2:9326

Fluoxetine rescues impaired hippocampal neurogenesis in a transgenic A53T synuclein mouse model. - Kohl, Zacharias; Winner, Beate; Ubhi, Kiren; Rockenstein, Edward; Mante, Michael; Muench, Martina; Barlow, Carolee; Carter, Todd; Masliah, Eliezer; Winkler, Jürgen (European Journal of Neuroscience, 2012)
The accumulation of alpha-synuclein in Lewy bodies and Lewy neurites of different neuronal populations is one of the neuropathological hallmarks in Parkinson disease (PD). Overexpression of human wildtype or mutant alpha-synuclein affects the generation of new neurons in the adult dentate gyrus (DG) of the hippocampus in models of PD. Hippocampal dysfunction with reduced neurogenesis plays an important role in the pathogenesis of depression, an important non-motor symptom in PD. Moreover, effective antidepressant treatment is still an unmet need in PD. The present study explored if impaired hippocampal neurogenesis in the A53T transgenic animal model of PD may be restored by chronic oral application of the selective serotonin reuptake inhibitor (SSRI) fluoxetine. First, we determined the expression pattern of transgenic mutant A53T synuclein in developing DG neurons and showed early expression of the transgene linked to a severely impaired neurogenesis. After chronic fluoxetine treatment we observed an increased adult neurogenesis in the hippocampus of more than threefold in treated A53T mice compared with controls. The pro-neurogenic effect of chronic fluoxetine application is predominantly related to an increased proliferation of neural precursor cells in the DG, and to a lesser extent by induction of differentiation into mature neurons. Analysis of the underlying mechanisms revealed an induction of brain-derived and glial cell-derived neurotrophic factor levels as a result of fluoxetine treatment. This study underlines the large potential of SSRI-dependent mechanisms to stimulate adult hippocampal neurogenesis in alpha-synuclein models and may lead to novel means to improve neuropsychiatric symptoms in PD.
EVALuna2:25298

FoxO Function Is Essential for Maintenance of Autophagic Flux and Neuronal Morphogenesis in Adult Neurogenesis - Schäffner, Iris; Minakaki, Georgia; Khan, M. Amir; Balta, Elli-Anna; Schlötzer-Schrehardt, Ursula; Schwarz, Tobias J.; Beckervordersandforth, Ruth; Winner, Beate; Webb, Ashley E.; Depinho, Ronald A.; Paik, Jihye; Wurst, Wolfgang; et al. (Neuron, 2018)
Autophagy is a conserved catabolic pathway with emerging functions in mammalian neurodevelopment and human neurodevelopmental diseases. The mechanisms controlling autophagy in neuronal development are not fully understood. Here, we found that conditional deletion of the Forkhead Box O transcription factors FoxO1, FoxO3, and FoxO4 strongly impaired autophagic flux in developing neurons of the adult mouse hippocampus. Moreover, FoxO deficiency led to altered dendritic morphology, increased spine density, and aberrant spine positioning in adult-generated neurons. Strikingly, pharmacological induction of autophagy was sufficient to correct abnormal dendrite and spine development of FoxO-deficient neurons. Collectively, these findings reveal a novel link between FoxO transcription factors, autophagic flux, and maturation of developing neurons.
EVALuna2:34732

FOXP2 variants in 14 individuals with developmental speech and language disorders broaden the mutational and clinical spectrum - Reuter, Miriam; Riess, Angelika; Moog, Ute; Briggs, Tracy A.; Chandler, Kate E.; Rauch, Anita; Stampfer, Miriam; Steindl, Katharina; Glaeser, Dieter; Joset, Pascal; Krumbiegel, Mandy; Rabe, Harald; et al. (Journal of Medical Genetics, 2017)
Disruptions of the FOXP2 gene, encoding a forkhead transcription factor, are the first known monogenic cause of a speech and language disorder. So far, mainly chromosomal rearrangements such as translocations or larger deletions affecting FOXP2 have been reported. Intragenic deletions or convincingly pathogenic point mutations in FOXP2 have up to date only been reported in three families. We thus aimed at a further characterisation of the mutational and clinical spectrum.Chromosomal microarray testing, trio exome sequencing, multigene panel sequencing and targeted sequencing of FOXP2 were performed in individuals with variable developmental disorders, and speech and language deficits.We identified four different truncating mutations, two novel missense mutations within the forkhead domain and an intragenic deletion in FOXP2 in 14 individuals from eight unrelated families. Mutations occurred de novo in four families and were inherited from an affected parent in the other four. All index patients presented with various manifestations of language and speech impairment. Apart from two individuals with normal onset of speech, age of first words was between 4 and 7 years. Articulation difficulties such as slurred speech, dyspraxia, stuttering and poor pronunciation were frequently noted. Motor development was normal or only mildly delayed. Mild cognitive impairment was reported for most individuals.By identifying intragenic deletions or mutations in 14 individuals from eight unrelated families with variable developmental delay/cognitive impairment and speech and language deficits, we considerably broaden the mutational and clinical spectrum associated with aberrations in FOXP2.
EVALuna2:9348

Fra-2 regulates B cell development by enhancing IRF4 and Foxo1 transcription - Ubieta, Kenia; Garcia, Mireia; Groetsch, Bettina; Uebe, Steffen; Stein, Merle; Ekici, Arif Bülent; Schett, Georg; Mielenz, Dirk; Bozec, Aline; Weber, Georg (Journal of Experimental Medicine, 2017)
The role of AP-1 transcription factors in early B cell development and function is still incompletely characterized. Here we address the role of Fra-2 in B cell differentiation. Deletion of Fra-2 leads to impaired B cell proliferation in the bone marrow. In addition, IL-7-stimulated pro-B cell cultures revealed a reduced differentiation from large pre-B cells to small B cells and immature B cells. Gene profiling and chromatin immunoprecipitation sequencing analyses unraveled a transcriptional reduction of the transcription factors Foxo1, Irf4, Ikaros, and Aiolos in Fra-2-deficient B cells. Moreover, expression of IL7R? and Rag 1/2, downstream targets of Irf4 and Foxo1, were also reduced in the absence of Fra-2. Pro-B cell proliferation and small pre-B cell differentiation were fully rescued by expression of Foxo1 and Irf4 in Fra-2-deficient pro-B cells. Hence, Fra-2 is a key upstream regulator of Foxo1 and Irf4 expression and influences proliferation and differentiation of B cells at multiple stages.
EVALuna2:9366

From basic mechanisms to clinical applications in heart protection, new players in cardiovascular diseases and cardiac theranostics: meeting report from the third international symposium on "New frontiers in cardiovascular research" - Cabrera-Fuentes, Hector A.; Aragones, Julian; Bernhagen, Juergen; Boening, Andreas; Boisvert, William A.; Botker, Hans E.; Bulluck, Heerajnarain; Cook, Stuart; Di Lisa, Fabio; Engel, Felix; Engelmann, Bernd; Ferrazzi, Fulvia; et al. (Basic Research in Cardiology, 2016)
In this meeting report, particularly addressing the topic of protection of the cardiovascular system from ischemia/reperfusion injury, highlights are presented that relate to conditioning strategies of the heart with respect to molecular mechanisms and outcome in patients' cohorts, the influence of co-morbidities and medications, as well as the contribution of innate immune reactions in cardioprotection. Moreover, developmental or systems biology approaches bear great potential in systematically uncovering unexpected components involved in ischemia-reperfusion injury or heart regeneration. Based on the characterization of particular platelet integrins, mitochondrial redox-linked proteins, or lipid-diol compounds in cardiovascular diseases, their targeting by newly developed theranostics and technologies opens new avenues for diagnosis and therapy of myocardial infarction to improve the patients' outcome.
EVALuna2:9341

Fruits of Genomic Match-making: De Novo Variants in PRR12 are Associated with a Spectrum of Eye and Neurodevelopmental Anomalies - Balci, T. B.; Wang, L.; Lalani, S.; Heide, S.; Keren, B.; Mignot, C.; Morley, G.; Walia, J.; Wheeler, P.; Lemons, J.; Buritica, D. Rodriguez; Riberi, E.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Functional Analysis and Fine Mapping of the 9p22.2 Ovarian Cancer Susceptibility Locus - Buckley, Melissa A.; Woods, Nicholas T.; Tyrer, Jonathan P.; Mendoza-Fandino, Gustavo; Lawrenson, Kate; Hazelett, Dennis J.; Najafabadi, Hamed S.; Gjyshi, Anxhela; Carvalho, Renato S.; Lyra, Paulo C.; Coetzee, Simon G.; Shen, Howard C.; et al. (Cancer Research, 2019)
Genome-wide association studies have identified 40 ovarian cancer risk loci. However, the mechanisms underlying these associations remain elusive. In this study, we conducted a two-pronged approach to identify candidate causal SNPs and assess underlying biological mechanisms at chromosome 9p22.2, the first and most statistically significant associated locus for ovarian cancer susceptibility. Three transcriptional regulatory elements with allele-specific effects and a scaffold/matrix attachment region were characterized and, through physical DNA interactions, BNC2 was established as the most likely target gene. We determined the consensus binding sequence for BNC2 in vitro, verified its enrichment in BNC2 ChIP-seq regions, and validated a set of its downstream target genes. Fine-mapping by dense regional genotyping in over 15,000 ovarian cancer cases and 30,000 controls identified SNPs in the scaffold/ matrix attachment region as among the most likely causal variants. This study reveals a comprehensive regulatory landscape at 9p22.2 and proposes a likely mechanism of susceptibility to ovarian cancer.
CRIS-Team WoS Importer:2019-02-21

Functional characterization of a novel CFTR mutation P67S identified in a patient with atypical cystic fibrosis - Kraus, Cornelia; Reis, André; Naehrlich, Lutz; Dötsch, Jörg; Korbmacher, Christoph; Rauh, Robert (Cellular Physiology and Biochemistry, 2007)
Cystic fibrosis (CF) is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. CFTR serves as a cAMP-stimulated chloride channel in a wide range of epithelial tissues and its dysfunction is a hallmark of CF. Over 1400 mutations in the CFTR gene are known, but functional data exist only for a minority of the mutant channels. The aim of the present study was to functionally characterize a novel CFTR mutation identified in a patient with atypical CF. Full length sequencing of the patient's CFTR gene revealed a homozygous C to T transition at nucleotide position 331 (CCT>TCT), which results in a P67S amino acid substitution. Mutant and wild-type CFTR were heterologously expressed in Xenopus laevis oocytes. CFTR whole-cell currents were studied using the two-electrode voltage-clamp technique. Channel surface expression was assessed by a chemiluminescence assay. Expression of P67S-CFTR resulted in functional CFTR chloride channels. However, the CFTR chloride conductance observed in oocytes expressing the mutant channel averaged only 24% of that in oocytes expressing wild-type CFTR. Similarly, surface expression of the mutant channel was reduced. In contrast, the mutation did not alter the anion selectivity of the channel, and Western blot analysis indicated a similar protein expression level of mutant and wild-type CFTR. Our findings indicate that the P67S mutation reduces CFTR chloride channel function by reducing channel surface expression. The mild disease phenotype of the patient indicates that the residual function of the mutant channel is sufficient to prevent the development of severe CF symptoms. Copyright © 2007 S. Karger AG.
UnivIS-Import:2015-04-14:Pub.2007.med.IPK.LPVP.functi
Keywords: CFTR; Chloride channel; Cystic fibrosis; Electrophysiology; P67S mutation; Pancreatic insufficiency; Surface expression; Xenopus laevis oocytes

Functional implication of the pseudoexfoliation-associated rare variant p.Y407F at LOXL1 - Berner, Daniel; Hoja, Ursula; Zenkel, Matthias; Pasutto, Francesca; Lee, Mei Chin; Aung, Tin; Khor, Chiea Chuen; Reis, André; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Functional missense and splicing variants in the retinoic acid catabolizing enzyme CYP26C1 in idiopathic short stature - Montalbano, Antonino; Juergensen, Lonny; Fukami, Maki; Thiel, Christian; Hauer, Nadine; Roeth, Ralph; Weiss, Birgit; Naiki, Yasuhiro; Ogata, Tsutomu; Hassel, David; Rappold, Gudrun A. (European journal of human genetics, 2018)
Height is a complex quantitative trait with a high heritability. Short stature is diagnosed when height is significantly below the average of the general population for that person's age and sex. We have recently found that the retinoic acid degrading enzyme CYP26C1 modifies SHOX deficiency phenotypes toward more severe clinical manifestations. Here, we asked whether damaging variants in CYP26C1 alone could lead to short stature. We performed exome and Sanger sequencing to analyze 856 individuals with short stature where SHOX deficiency was previously excluded. Three different damaging missense variants and one splicing variant were identified in six independent individuals; the functional significance of the identified variants was tested in vitro or in vivo using zebrafish as a model. The genetic and functional data reported here indicate that CYP26C1 represents a novel gene underlying growth disorders and that damaging variants in the absence of SHOX variants can lead to short stature.
EVALuna2:34621

Functional missense and splicing variants in the retinoic acid catabolizing enzyme CYP26C1 in idiopathic short stature - Rappold, G. A.; Montalbano, A.; Juergensen, L.; Fukami, M.; Thiel, Christian; Hauer, Nadine; Roeth, R.; Weiss, B.; Naiki, Y.; Ogata, T.; Hassel, D. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Functional null mutations in the gonosomal homologue gene TBL1Y are associated with non-syndromic coarctation of the aorta - Tagariello, Andreas; Breuer, C.; Birkner, Y.; Schmidt, Stefan; Koch, Anna Maria; Cesnjevar, Robert; Rueffer, A.; Dittrich, Sven; Schneider, H.; Winterpacht, Andreas; Sticht, Heinrich; Doetsch, J.; et al. (Current Molecular Medicine, 2012)
In patients with congenital heart defects, chromosomal anomalies are 100 times more frequent than in control subjects. Coarctation of the aorta can be detected in 15-20% of patients with Ullrich-Turner syndrome. By extensively reviewing literature involving breakpoint analysis of gonosomal deletions in Ullrich- Turner syndrome patients with and without coarctation of the aorta, we identified several gonosomal homolgous gene pairs of interest. Four of these homologous gene pairs were investigated by standard DNA sequencing in a cohort of 83 patients with non-syndromic coarctation of the aorta. Subsequently stability of mutant RNA and protein was analyzed to verify functional relevance of detected mutations. We identified two unreported missense mutations in Exon 8 (p.D69H) and 9 (p.R176W) of TBL1Y. Bioinformatic analysis and 3D modelling predicted that both mutations lead to TBL1Y loss of function. In RT-PCR and Western blot analyses of HEK293 cells transfected with a vector carrying the full-length TBL1Y (wild-type and mutant), we documented the predicted protein instability by showing protein decay for both mutant proteins. TBL1Y is similar to its gonosomal homologue, TBL1X, and its autosomal homologue, TBLR1, on chromosome 3. Both genes are part of co-repressor machineries and required for transcriptional activation by transcription factors that involve CtBP1/2, which contributes to Notch signaling. Several studies have shown that Notch signalling is important for proper development of the left ventricular outflow tract. Our findings suggest that TBL1Y is involved in the genesis of non-syndromic coarctation of the aorta.
EVALuna2:9136

Further characterization of Borjeson-Forssman-Lehmann syndrome in females due to de novo variants in PHF6 - Gerber, Celine B.; Fliedner, Anna; Bartsch, Oliver; Berland, Siren; Dewenter, Malin; Haug, Marte; Hayes, Ian; Marin-Reina, Purificacion; Mark, Paul R.; Martinez-Castellano, Francisco; Maystadt, Isabelle; Karadurmus, Deniz; et al. (Clinical Genetics, 2022)
While inherited hemizygous variants in PHF6 cause X-linked recessive Borjeson-Forssman-Lehmann syndrome (BFLS) in males, de novo heterozygous variants in females are associated with an overlapping but distinct phenotype, including moderate to severe intellectual disability, characteristic facial dysmorphism, dental, finger and toe anomalies, and linear skin pigmentation. By personal communication with colleagues, we assembled 11 additional females with BFLS due to variants in PHF6. We confirm the distinct phenotype to include variable intellectual disability, recognizable facial dysmorphism and other anomalies. We observed skewed X-inactivation in blood and streaky skin pigmentation compatible with functional mosaicism. Variants occurred de novo in 10 individuals, of whom one was only mildly affected and transmitted it to her more severely affected daughter. The mutational spectrum comprises a two-exon deletion, five truncating, one splice-site and three missense variants, the latter all located in the PHD2 domain and predicted to severely destabilize the domain structure. This observation supports the hypothesis of more severe variants in females contributing to gender-specific phenotypes in addition to or in combination with effects of X-inactivation and functional mosaicism. Therefore, our findings further delineate the clinical and mutational spectrum of female BFLS and provide further insights into possible genotype-phenotype correlations between females and males.
CRIS-Team WoS Importer:2022-06-24
Keywords: Borjeson-Forssman-Lehmann syndrome; de novo; PHF6; X-chromosomal

Further clinical and molecular delineation of Alazami syndrome associated with variants in LARP7 - Gumuslu, E.; Karaer, K.; Gumus, E.; Ekici, Arif Bülent; Kraus, Cornelia; Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Further clinical and molecular delineation of spondylocostal dysostosis type 3 - Schuhmann, Sarah; Koller, H.; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Further delineation of the female phenotype with KDM5C disease causing variants: 19 new individuals and review of the literature - Carmignac, Virginie; Nambot, Sophie; Lehalle, Daphne; Callier, Patrick; Moortgat, Stephanie; Benoit, Valerie; Ghoumid, Jamal; Delobel, Bruno; Smol, Thomas; Thuillier, Caroline; Zordan, Cecile; Naudion, Sophie; et al. (Clinical Genetics, 2020)
X-linked intellectual disability (XLID) is a genetically heterogeneous condition involving more than 100 genes. To date, 35 pathogenic variants have been reported in the lysine specific demethylase 5C (KDM5C) gene. KDM5C variants are one of the major causes of moderate to severe XLID. Affected males present with short stature, distinctive facial features, behavioral disorders, epilepsy, and spasticity. For most of these variants, related female carriers have been reported, but phenotypic descriptions were poor. Here, we present clinical and molecular features of 19 females carrying 10 novel heterozygous variants affecting KDM5C function, including five probands with de novo variants. Four heterozygous females were asymptomatic. All affected individuals presented with learning disabilities or ID (mostly moderate), and four also had a language impairment mainly affecting expression. Behavioral disturbances were frequent, and endocrine disorders were more frequent in females. In conclusion, our findings provide evidence of the role of KDM5C in ID in females highlighting the increasing implication of XLID genes in females, even in sporadic affected individuals. Disease expression of XLID in females should be taken into consideration for genetic counseling.
CRIS-Team Scopus Importer:2020-06-09
Keywords: data-sharing; exome; females; KDM5C; X-linked intellectual disability

Further delineation of the SCAF4-associated neurodevelopmental disorder - Schmid, Cosima M.; Gregor, Anne; Ruiz, Anna; Manso Bazús, Carmen; Herman, Isabella; Ammouri, Farah; Kotzaeridou, Urania; McNiven, Vanda; Dupuis, Lucie; Steindl, Katharina; Begemann, Anaïs; Rauch, Anita; et al. (European Journal of Human Genetics, 2024)
While mostly de novo truncating variants in SCAF4 were recently identified in 18 individuals with variable neurodevelopmental phenotypes, knowledge on the molecular and clinical spectrum is still limited. We assembled data on 50 novel individuals with SCAF4 variants ascertained via GeneMatcher and personal communication. With detailed evaluation of clinical data, in silico predictions and structural modeling, we further characterized the molecular and clinical spectrum of the autosomal dominant SCAF4-associated neurodevelopmental disorder. The molecular spectrum comprises 25 truncating, eight splice-site and five missense variants. While all other truncating variants were classified as pathogenic/likely pathogenic, significance of one C-terminal truncating variant, one splice-site variant and the missense variants remained unclear. Three missense variants in the CTD-interacting domain of SCAF4 were predicted to destabilize the domain. Twenty-three variants occurred de novo, and variants were inherited in 13 cases. Frequent clinical findings were mild developmental delay with speech impairment, seizures, and skeletal abnormalities such as clubfoot, scoliosis or hip dysplasia. Cognitive abilities ranged from normal IQ to severe intellectual disability (ID), with borderline to mild ID in the majority of individuals. Our study confirms the role of SCAF4 variants in neurodevelopmental disorders and further delineates the associated clinical phenotype.
CRIS-Team Scopus Importer:2025-02-04

Gain-of-function and loss-of-function variants in GRIA3 lead to distinct neurodevelopmental phenotypes. - Rinaldi, Berardo; Bayat, Allan; Zachariassen, Linda G.; Sun, Jia Hui; Ge, Yu Han; Zhao, Dan; Bonde, Kristine; Madsen, Laura H.; Awad, Ilham Abdimunim Ali; Bagiran, Duygu; Sbeih, Amal; Shah, Syeda Maidah; et al. (Brain, 2024)
AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptors (AMPARs) mediate fast excitatory neurotransmission in the brain. AMPARs form by homo- or heteromeric assembly of subunits encoded by the GRIA1-GRIA4 genes, of which only GRIA3 is X-chromosomal. Increasing numbers of GRIA3 missense variants are reported in patients with neurodevelopmental disorders (NDD), but only a few have been examined functionally. Here, we evaluated the impact on AMPAR function of one frameshift and 43 rare missense GRIA3 variants identified in patients with NDD by electrophysiological assays. Thirty-one variants alter receptor function and show loss-of-function or gain-of-function properties, whereas 13 appeared neutral. We collected detailed clinical data from 25 patients (from 23 families) harbouring 17 of these variants. All patients had global developmental impairment, mostly moderate (9/25) or severe (12/25). Twelve patients had seizures, including focal motor (6/12), unknown onset motor (4/12), focal impaired awareness (1/12), (atypical) absence (2/12), myoclonic (5/12) and generalized tonic-clonic (1/12) or atonic (1/12) seizures. The epilepsy syndrome was classified as developmental and epileptic encephalopathy in eight patients, developmental encephalopathy without seizures in 13 patients, and intellectual disability with epilepsy in four patients. Limb muscular hypotonia was reported in 13/25, and hypertonia in 10/25. Movement disorders were reported in 14/25, with hyperekplexia or non-epileptic erratic myoclonus being the most prevalent feature (8/25). Correlating receptor functional phenotype with clinical features revealed clinical features for GRIA3-associated NDDs and distinct NDD phenotypes for loss-of-function and gain-of-function variants. Gain-of-function variants were associated with more severe outcomes: patients were younger at the time of seizure onset (median age: 1 month), hypertonic and more often had movement disorders, including hyperekplexia. Patients with loss-of-function variants were older at the time of seizure onset (median age: 16 months), hypotonic and had sleeping disturbances. Loss-of-function and gain-of-function variants were disease-causing in both sexes but affected males often carried de novo or hemizygous loss-of-function variants inherited from healthy mothers, whereas affected females had mostly de novo heterozygous gain-of-function variants.
EVALuna2:555553

Gene dosage-dependent rescue of HSP neurite defects in SPG4 patients' neurons - Havlicek, Steven; Kohl, Zacharias; Mishra, Himanshu Kumar; Prots, Iryna; Eberhardt, Esther; Denguir, Naime; Wend, Holger; Ploetz, Sonja; Boyer, Leah; Marchetto, Maria C. N.; Aigner, Stefan; Sticht, Heinrich; et al. (Human Molecular Genetics, 2014)
The hereditary spastic paraplegias (HSPs) are a heterogeneous group of motorneuron diseases characterized by progressive spasticity and paresis of the lower limbs. Mutations in Spastic Gait 4 (SPG4), encoding spastin, are the most frequent cause of HSP. To understand how mutations in SPG4 affect human neurons, we generated human induced pluripotent stem cells (hiPSCs) from fibroblasts of two patients carrying a c.1684C>T nonsense mutation and from two controls. These SPG4 and control hiPSCs were able to differentiate into neurons and glia at comparable efficiency. All known spastin isoforms were reduced in SPG4 neuronal cells. The complexity of SPG4 neurites was decreased, which was paralleled by an imbalance of axonal transport with less retrograde movement. Prominent neurite swellings with disrupted microtubules were present in SPG4 neurons at an ultrastructural level. While some of these swellings contain acetylated and detyrosinated tubulin, these tubulin modifications were unchanged in total cell lysates of SPG4 neurons. Upregulation of another microtubule-severing protein, p60 katanin, may partially compensate for microtubuli dynamics in SPG4 neurons. Overexpression of the M1 or M87 spastin isoforms restored neurite length, branching, numbers of primary neurites and reduced swellings in SPG4 neuronal cells. We conclude that neurite complexity and maintenance in HSP patient-derived neurons are critically sensitive to spastin gene dosage. Our data show that elevation of single spastin isoform levels is sufficient to restore neurite complexity and reduce neurite swellings in patient cells. Furthermore, our human model offers an ideal platform for pharmacological screenings with the goal to restore physiological spastin levels in SPG4 patients.
EVALuna2:2420

Gene-Environment Interactions Relevant to Estrogen and Risk of Breast Cancer: Can Gene-Environment Interactions Be Detected Only among Candidate SNPs from Genome-Wide Association Studies? - Park, Jooyong; Choi, Ji-Yeob; Choi, Jaesung; Chung, Seokang; Song, Nan; Park, Sue K.; Han, Wonshik; Noh, Dong-Young; Ahn, Sei-Hyun; Lee, Jong Won; Kim, Mi Kyung; Jee, Sun Ha; et al. (Cancers, 2021)
Simple Summary
CRIS-Team WoS Importer:2021-06-04

Gene network analysis: from heart development to cardiac therapy - Ferrazzi, Fulvia; Bellazzi, Riccardo; Engel, Felix (Thrombosis and Haemostasis, 2015)
Networks offer a flexible framework to represent and analyse the complex interactions between components of cellular systems. In particular gene networks inferred from expression data can support the identification of novel hypotheses on regulatory processes. In this review we focus on the use of gene network analysis in the study of heart development. Understanding heart development will promote the elucidation of the aetiology of congenital heart disease and thus possibly improve diagnostics. Moreover, it will help to establish cardiac therapies. For example, understanding cardiac differentiation during development will help to guide stem cell differentiation required for cardiac tissue engineering or to enhance endogenous repair mechanisms. We introduce different methodological frameworks to infer networks from expression data such as Boolean and Bayesian networks. Then we present currently available temporal expression data in heart development and discuss the use of network-based approaches in published studies. Collectively, our literature-based analysis indicates that gene network analysis constitutes a promising opportunity to infer therapy-relevant regulatory processes in heart development. However, the use of network-based approaches has so far been limited by the small amount of samples in available datasets. Thus, we propose to acquire high-resolution temporal expression data to improve the mathematical descriptions of regulatory processes obtained with gene network inference methodologies. Especially probabilistic methods that accommodate the intrinsic variability of biological systems have the potential to contribute to a deeper understanding of heart development.
EVALuna2:9255

Gene panel sequencing in familial breast/ovarian cancer patients identifies multiple novel mutations also in genes others than BRCA1/2 - Kraus, Cornelia; Hoyer, Juliane; Vasileiou, Georgia; Wunderle, Marius; Lux, Michael P.; Fasching, Peter; Krumbiegel, Mandy; Uebe, Steffen; Reuter, Miriam; Beckmann, Matthias; Reis, André (International Journal of Cancer, 2017)
Breast and ovarian cancer (BC/OC) predisposition has been attributed to a number of high- and moderate to low-penetrance susceptibility genes. With the advent of next generation sequencing (NGS) simultaneous testing of these genes has become feasible. In this monocentric study, we report results of panel-based screening of 14 BC/OC susceptibility genes (BRCA1, BRCA2, RAD51C, RAD51D, CHEK2, PALB2, ATM, NBN, CDH1, TP53, MLH1, MSH2, MSH6 and PMS2) in a group of 581 consecutive individuals from a German population with BC and/or OC fulfilling diagnostic criteria for BRCA1 and BRCA2 testing including 179 with a triple-negative tumor. Altogether we identified 106 deleterious mutations in 105 (18%) patients in 10 different genes, including seven different exon deletions. Of these 106 mutations, 16 (15%) were novel and only six were found in BRCA1/2. To further characterize mutations located in or nearby splicing consensus sites we performed RT-PCR analysis which allowed confirmation of pathogenicity in 7 of 9 mutations analyzed. In PALB2, we identified a deleterious variant in six cases. All but one were associated with early onset BC and a positive family history indicating that penetrance for PALB2 mutations is comparable to BRCA2. Overall, extended testing beyond BRCA1/2 identified a deleterious mutation in further 6% of patients. As a downside, 89 variants of uncertain significance were identified highlighting the need for comprehensive variant databases. In conclusion, panel testing yields more accurate information on genetic cancer risk than assessing BRCA1/2 alone and wide-spread testing will help improve penetrance assessment of variants in these risk genes.
EVALuna2:9340

Generation and characterization of an endogenously tagged SPG11-human iPSC line by CRISPR/Cas9 mediated knock-in - Winner, Beate; Krumm, Laura; Pozner, Tatyana; Kaindl, Johanna; Regensburger, Martin; Günther, Claudia; Turan, Sören; Asadollahi, Reza; Rauch, Anita (Stem Cell Research, 2021)
Pathogenic bi-allelic variants in the SPG11 gene result in rare motor neuron disorders such as Hereditary Spastic Paraplegia type 11, Charcot-Marie Tooth, and Juvenile Amyotrophic Lateral Sclerosis-5. The main challenge in SPG11-linked disease research is the lack of antibodies against SPG11 encoded spatacsin. Here, we describe the CRISPR/Cas9 mediated generation and validation of an endogenously tagged SPG11- human iPSC line that contains an HA tag at the C-terminus of SPG11. The line exhibits multi-lineage differentiation potential and holds promise for studying the role of spatacsin and for the elucidation of SPG11-associated pathogenesis. Resource Table.

Generation and Validation of Human Pluripotent Stern Cell Disease Models Using CRISPR/Cas9 Genome Engineering - Turan, S.; Kavyanifar, Atria; Wend, H.; Pozner, Tatyana; Loskam, S.; Kaindl, J.; Lanfer, Jonas; Rizo, Tania; Riedlberger, J. (International Conference on CRISPR Technologies 2019, 2019)
CRIS-Team Scopus Importer:2024-12-16

Generation of a homozygous and a heterozygous SNCA gene knockout human-induced pluripotent stem cell line by CRISPR/Cas9 mediated allele-specific tuning of SNCA expression - Schneider, Yanni; Turan, Soeren; Koller, Aron; Krumbiegel, Mandy; Farrell, Michaela; Plotz, Sonja; Winkler, Jürgen; Xiang, Wei (Stem Cell Research, 2022)
Aggregation of alpha-synuclein (aSyn) is closely linked to Parkinson's disease, probably due to the loss of physiological functions and/or gain of toxic functions of aggregated aSyn. Significant efforts have been made elucidating the physiological structure and function of aSyn, however, with limited success thus far in human -derived cells, partly because of restricted resources. Here, we developed two human-induced pluripotent stem cell lines using CRISPR/Cas9-mediated allele-specific frame-shift deletion of the aSyn encoding gene SNCA, resulting in homo-and heterozygous SNCA knockout. The generated cell lines are promising cellular tools for studying aSyn dosage-dependent functions and structural alterations in human neural cells.
CRIS-Team WoS Importer:2022-11-18

Gene-specific facial dysmorphism in Axenfeld-Rieger syndrome caused by FOXC1 and PITX2 variants - Souzeau, Emmanuelle; Siggs, Owen M.; Pasutto, Francesca; Knight, Lachlan S. W.; Perez-Jurado, Luis A.; Mcgregor, Lesley; Le Blanc, Shannon; Barnett, Christopher P.; Liebelt, Jan; Craig, Jamie E. (American Journal of Medical Genetics Part A, 2020)
Axenfeld-Rieger syndrome is a genetic condition characterized by ocular and systemic features and is most commonly caused by variants in the FOXC1 or PITX2 genes. Facial dysmorphism is part of the syndrome but the differences between both genes have never been systematically assessed. Here, 11 facial traits commonly reported in Axenfeld-Rieger syndrome were assessed by five clinical geneticists blinded to the molecular diagnosis. Individuals were drawn from the Australian and New Zealand Registry of Advanced Glaucoma in Australia or recruited through the Genetic and Ophthalmology Unit of l'Azienda Socio-Sanitaria Territoriale Grande Ospedale Metropolitano Niguarda in Italy. Thirty-four individuals from 18 families were included. FOXC1 variants were present in 64.7% of individuals and PITX2 variants in 35.3% of individuals. A thin upper lip (55.9%) and a prominent forehead (41.2%) were common facial features shared between both genes. Hypertelorism/telecanthus (81.8% vs 25.0%, p = 0.002) and low-set ears (31.8% vs 0.0%, p = 0.036) were significantly more prevalent in individuals with FOXC1 variants compared with PITX2 variants. These findings may assist clinicians in reaching correct clinical and molecular diagnoses, and providing appropriate genetic counseling.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Axenfeld-Rieger syndrome; facial dysmorphism; FOXC1; PITX2

Genetically Single Generation and characterization of an endogenously tagged SPG11-human iPSC line by CRISPR/Cas9 mediated knock-in - Krumm, Laura; Pozner, Tatyana; Kaindl, Johanna; Regensburger, Martin; Günther, Claudia; Turan, Sören; Asadollahi, Reza; Rauch, Anita; Winner, Beate (Stem Cell Research, 2021)
Pathogenic bi-allelic variants in the SPG11 gene result in rare motor neuron disorders such as Hereditary Spastic Paraplegia type 11, Charcot-Marie Tooth, and Juvenile Amyotrophic Lateral Sclerosis-5. The main challenge in SPG11-linked disease research is the lack of antibodies against SPG11 encoded spatacsin. Here, we describe the CRISPR/Cas9 mediated generation and validation of an endogenously tagged SPG11- human iPSC line that contains an HA tag at the C-terminus of SPG11. The line exhibits multi-lineage differentiation potential and holds promise for studying the role of spatacsin and for the elucidation of SPG11-associated pathogenesis.
CRIS-Team Scopus Importer:2021-09-10

Genetic Analysis of MPO Variants in Four Psoriasis Subtypes in Patients from Germany - Haskamp, Stefan; Horowitz, Joseph; Oji, Vinzenz; Philipp, Sandra; Sticherling, Michael; Schäkel, Knut; Schuhmann, Sarah; Prinz, Jörg C.; Burkhardt, Harald; Behrens, Frank; Böhm, Beate; Köhm, Michaela; et al. (Journal of Investigative Dermatology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Genetic and neurodevelopmental spectrum of SYNGAP1-associated intellectual disability and epilepsy - Mignot, Cyril; Von Stuelpnagel, Celina; Nava, Caroline; Ville, Dorothee; Sanlaville, Damien; Lesca, Gaetan; Rastetter, Agnes; Gachet, Benoit; Marie, Yannick; Korenke, G. Christoph; Borggraefe, Ingo; Hoffmann-Zacharska, Dorota; et al. (Journal of Medical Genetics, 2016)
We aimed to delineate the neurodevelopmental spectrum associated with SYNGAP1 mutations and to investigate genotype-phenotype correlations.We sequenced the exome or screened the exons of SYNGAP1 in a total of 251 patients with neurodevelopmental disorders. Molecular and clinical data from patients with SYNGAP1 mutations from other centres were also collected, focusing on developmental aspects and the associated epilepsy phenotype. A review of SYNGAP1 mutations published in the literature was also performed.We describe 17 unrelated affected individuals carrying 13 different novel loss-of-function SYNGAP1 mutations. Developmental delay was the first manifestation of SYNGAP1-related encephalopathy; intellectual disability became progressively obvious and was associated with autistic behaviours in eight patients. Hypotonia and unstable gait were frequent associated neurological features. With the exception of one patient who experienced a single seizure, all patients had epilepsy, characterised by falls or head drops due to atonic or myoclonic seizures, (myoclonic) absences and/or eyelid myoclonia. Triggers of seizures were frequent (n=7). Seizures were pharmacoresistant in half of the patients. The severity of the epilepsy did not correlate with the presence of autistic features or with the severity of cognitive impairment. Mutations were distributed throughout the gene, but spared spliced 3' and 5' exons. Seizures in patients with mutations in exons 4-5 were more pharmacoresponsive than in patients with mutations in exons 8-15.SYNGAP1 encephalopathy is characterised by early neurodevelopmental delay typically preceding the onset of a relatively recognisable epilepsy comprising generalised seizures (absences, myoclonic jerks) and frequent triggers.
EVALuna2:9321

Genetic and phenotypic spectrum associated with IFIH1 gain-of-function - Rice, Gillian; Park, Sehoon; Gavazzi, Francesco; Adang, Laura A.; Ayuk, Loveline A.; Van Eyck, Lien; Seabra, Luis; Barrea, Christophe; Battini, Roberta; Belot, Alexandre; Berg, Stefan; De Villemeur, Thierry Billette; et al. (Human Mutation, 2020)
IFIH1 gain-of-function has been reported as a cause of a type I interferonopathy encompassing a spectrum of autoinflammatory phenotypes including Aicardi-Goutieres syndrome and Singleton Merten syndrome. Ascertaining patients through a European and North American collaboration, we set out to describe the molecular, clinical and interferon status of a cohort of individuals with pathogenic heterozygous mutations in IFIH1. We identified 74 individuals from 51 families segregating a total of 27 likely pathogenic mutations in IFIH1. Ten adult individuals, 13.5% of all mutation carriers, were clinically asymptomatic (with seven of these aged over 50 years). All mutations were associated with enhanced type I interferon signaling, including six variants (22%) which were predicted as benign according to multiple in silico pathogenicity programs. The identified mutations cluster close to the ATP binding region of the protein. These data confirm variable expression and nonpenetrance as important characteristics of the IFIH1 genotype, a consistent association with enhanced type I interferon signaling, and a common mutational mechanism involving increased RNA binding affinity or decreased efficiency of ATP hydrolysis and filament disassembly rate.
CRIS-Team WoS Importer:2020-01-28

Genetic association study of exfoliation syndrome identifies a protective rare variant at LOXL1 and five new susceptibility loci - Aung, Tin; Ozaki, Mineo; Lee, Mei Chin; Schlötzer-Schrehardt, Ursula; Thorleifsson, Gudmar; Mizoguchi, Takanori; Igo, Robert P.; Haripriya, Aravind; Williams, Susan E.; Astakhov, Yury S.; Orr, Andrew C.; Burdon, Kathryn P.; et al. (Nature Genetics, 2017)
Exfoliation syndrome (XFS) is the most common known risk factor for secondary glaucoma and a major cause of blindness worldwide. Variants in two genes, LOXL1 and CACNA1A, have previously been associated with XFS. To further elucidate the genetic basis of XFS, we collected a global sample of XFS cases to refine the association at LOXL1, which previously showed inconsistent results across populations, and to identify new variants associated with XFS. We identified a rare protective allele at LOXL1 (p.Phe407, odds ratio (OR) = 25, P = 2.9 × 10(-14)) through deep resequencing of XFS cases and controls from nine countries. A genome-wide association study (GWAS) of XFS cases and controls from 24 countries followed by replication in 18 countries identified seven genome-wide significant loci (P < 5 × 10(-8)). We identified association signals at 13q12 (POMP), 11q23.3 (TMEM136), 6p21 (AGPAT1), 3p24 (RBMS3) and 5q23 (near SEMA6A). These findings provide biological insights into the pathology of XFS and highlight a potential role for naturally occurring rare LOXL1 variants in disease biolog
EVALuna2:9376

Genetic Breast Cancer Susceptibility Variants and Prognosis in the Prospectively Randomized SUCCESS A Study - Hein, Alexander; Rack, B.; Li, L.; Ekici, Arif Bülent; Reis, André; Lux, Michael P.; Cunningham, J. M.; Rübner, Matthias; Fridley, B. L.; Schneeweiss, A.; Tesch, H.; Lichtenegger, W.; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Large-scale genotyping studies have identified over 70 single nucleotide polymorphisms (SNPs) associated with breast cancer (BC) risk. However, knowledge regarding genetic risk factors associated with the prognosis is limited. The aim of this study was therefore to investigate the prognostic effect of nine known breast cancer risk SNPs. BC patients (n = 1687) randomly sampled in an adjuvant, randomized phase III trial (SUCCESS A study) were genotyped for nine BC risk SNPs: rs17468277 (CASP8) , rs2981582 (FGFR2) , rs13281615(8q24), rs3817198 (LSP1) , rs889312 (MAP3K1) , rs3803662 (TOX3) , rs13387042(2q35), rs4973768 (SLC4A7) , rs6504950 (COX11) . Cox proportional hazards models were used to test the SNPs' association with overall survival (OS) and progression-free survival (PFS). Additional analyses were carried out for molecular subgroups. rs3817198 in LSP1 (lymphocyte-specific protein 1) was the only SNP that significantly influenced OS (p = 0.01) and PFS (p < 0.01) in the likelihood ratio test comparing the genetic survival model with the clinical survival model. In the molecular subgroups, triple-negative patients with two minor alleles in rs3817198 had a much better prognosis relative to OS (adjusted HR 0.03; 95% CI 0.002 - 0.279) and PFS (HR 0.09; 95% CI 0.02 - 0.36) than patients with the common alleles. The same effect on PFS was shown for patients with luminal A tumors (HR 0.19; 95% CI 0.05 - 0.84), whereas patients with luminal B tumors had a poorer PFS with two minor alleles (HR 2.13; 95% CI 1.02 - 4.40). The variant in rs3817198 has a prognostic effect particularly in the subgroup of patients with triple-negative BC, suggesting a possible link with immunomodulation and BC.
EVALuna2:9355

Genetic diagnostic yield in a large cohort of patients with developmental and epileptic encephalopathy from Latin America: a preliminary report - De Moraes, Helena Tadiello; Urquia-Osorio, Hebel; Cavalcante, Charlington M.; Guerreiro, Marilisa M.; Montenegro, Maria Augusta; Coan, Ana Carolina; Medina, Marco T.; Caraballo, Roberto; Wiesmann da Silva Reis, André; Thiel, Christian; Uebe, Steffen; Lopes-Cendes, Iscia (EPILEPSIA, 2021)
CRIS-Team WoS Importer:2021-11-26

Genetic interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Gregor, Anne; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, Christine; Ekici, Arif Bülent; Ferrazzi, Fulvia; Zweier, Christiane (Scientific Reports, 2020)
Neurodevelopmental disorders (NDDs) are clinically and genetically extremely heterogeneous with shared phenotypes often associated with genes from the same networks. Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of NDDs with severe intellectual disability, epilepsy and microcephaly. To characterize potential functional links between these genes/proteins, we screened for genetic interactions in Drosophila melanogaster. We induced ubiquitous or tissue specific knockdown or overexpression of each single orthologous gene (Da, Mef2, Ube3a, Zfh1, XNP) and in pairwise combinations. Subsequently, we assessed parameters such as lethality, wing and eye morphology, neuromuscular junction morphology, bang sensitivity and climbing behaviour in comparison between single and pairwise dosage manipulations. We found most stringent evidence for genetic interaction between Ube3a and Mef2 as simultaneous dosage manipulation in different tissues including glia, wing and eye resulted in multiple phenotype modifications. We subsequently found evidence for physical interaction between UBE3A and MEF2C also in human cells. Systematic pairwise assessment of the Drosophila orthologues of five genes implicated in clinically overlapping, severe NDDs and subsequent confirmation in a human cell line revealed interactions between UBE3A/Ube3a and MEF2C/Mef2, thus contributing to the characterization of the underlying molecular commonalities.<br
Keywords: Genetic interaction; Medical genetics; Molecular medicine; Neurodevelopmental disorders

Genetic Interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, C.; Ekici, Arif Bülent; Ferrazzi, Fulvia; Gregor, Anne; Zweier, Christiane (52nd Conference of the European-Society-of-Human-Genetics (ESHG), 2019)
CRIS-Team WoS Importer:2019-10-25

Genetic overlap between endometriosis and endometrial cancer: evidence from cross-disease genetic correlation and GWAS meta-analyses - Painter, Jodie N.; O'Mara, Tracy A.; Morris, Andrew P.; Cheng, Timothy H. T.; Gorman, Maggie; Martin, Lynn; Hodson, Shirley; Jones, Angela; Martin, Nicholas G.; Gordon, Scott; Henders, Anjali K.; Attia, John; et al. (Cancer Medicine, 2018)
Epidemiological, biological, and molecular data suggest links between endometriosis and endometrial cancer, with recent epidemiological studies providing evidence for an association between a previous diagnosis of endometriosis and risk of endometrial cancer. We used genetic data as an alternative approach to investigate shared biological etiology of these two diseases. Genetic correlation analysis of summary level statistics from genomewide association studies (GWAS) using LD Score regression revealed moderate but significant genetic correlation (rg = 0.23, P = 9.3 × 10-3 ), and SNP effect concordance analysis provided evidence for significant SNP pleiotropy (P = 6.0 × 10-3 ) and concordance in effect direction (P = 2.0 × 10-3 ) between the two diseases. Cross-disease GWAS meta-analysis highlighted 13 distinct loci associated at P ≤ 10-5 with both endometriosis and endometrial cancer, with one locus (SNP rs2475335) located within PTPRD associated at a genomewide significant level (P = 4.9 × 10-8 , OR = 1.11, 95% CI = 1.07-1.15). PTPRD acts in the STAT3 pathway, which has been implicated in both endometriosis and endometrial cancer. This study demonstrates the value of cross-disease genetic analysis to support epidemiological observations and to identify biological pathways of relevance to multiple diseases.
EVALuna2:34631

Genetic predictors of chemotherapy-related amenorrhea in women with breast cancer - Ruddy, Kathryn J.; Schaid, Daniel J.; Partridge, A. H.; Larson, Nicholas B.; Batzler, Anthony; Häberle, Lothar; Dittrich, Ralf; Widschwendter, P.; Fink, Visnja; Bauer, Emanuel; Schwitulla, Judith; Rübner, Matthias; et al. (Fertility and Sterility, 2019)
Objective: To study how genetics may play a role in determining risk of chemotherapy-related amenorrhea (CRA) in young women with breast cancer. Design: Genome-wide association study. Setting: Not applicable. Patient(s): Premenopausal women ≤45 years of age enrolled in one of these three trials were included if they had at least one menstrual case report form after chemotherapy ended and if they were of European ancestry. Forms during and up to 3 months after receipt of GnRH agonist were excluded. Intervention(s): None. Main Outcome Measure(s): The association of single-nucleotide polymorphisms with post-chemotherapy menstruation adjusted for trial and arm, age, tamoxifen use, and nodal status. Result(s): The median age of the 1,168 women was 41 years (range 19–45). Among these, 457 (39%) never resumed menses after chemotherapy. Older age, tamoxifen use, and node-negative disease were associated with increased risk of CRA. Adjusting for these, rs147451859, in an intron of PPCDC (phosphopantothenoylcysteine decarboxylase), and rs17587029, located 5′ upstream of RPS20P11 (ribosomal protein S20 pseudogene 11), were associated with post-chemotherapy menstruation. Conclusion(s): Genetic variation may contribute to risk of CRA. Better prediction of who will experience CRA may inform reproductive and treatment decision making in young women with cancer.
CRIS-Team Scopus Importer:2019-08-06
Keywords: amenorrhea; Breast neoplasms; drug therapy; toxicity

Genetic predisposition to in situ and invasive lobular carcinoma of the breast - Sawyer, Elinor; Roylance, Rebecca; Petridis, Christos; Brook, Mark N.; Nowinski, Salpie; Papouli, Efterpi; Fletcher, Olivia; Pinder, Sarah; Hanby, Andrew; Kohut, Kelly; Gorman, Patricia; Caneppele, Michele; et al. (PLoS Genetics, 2014)
Invasive lobular breast cancer (ILC) accounts for 10-15% of all invasive breast carcinomas. It is generally ER positive (ER+) and often associated with lobular carcinoma in situ (LCIS). Genome-wide association studies have identified more than 70 common polymorphisms that predispose to breast cancer, but these studies included predominantly ductal (IDC) carcinomas. To identify novel common polymorphisms that predispose to ILC and LCIS, we pooled data from 6,023 cases (5,622 ILC, 401 pure LCIS) and 34,271 controls from 36 studies genotyped using the iCOGS chip. Six novel SNPs most strongly associated with ILC/LCIS in the pooled analysis were genotyped in a further 516 lobular cases (482 ILC, 36 LCIS) and 1,467 controls. These analyses identified a lobular-specific SNP at 7q34 (rs11977670, OR (95%CI) for ILC = 1.13 (1.09-1.18), P = 6.0 × 10(-10); P-het for ILC vs IDC ER+ tumors = 1.8 × 10(-4)). Of the 75 known breast cancer polymorphisms that were genotyped, 56 were associated with ILC and 15 with LCIS at P<0.05. Two SNPs showed significantly stronger associations for ILC than LCIS (rs2981579/10q26/FGFR2, P-het = 0.04 and rs889312/5q11/MAP3K1, P-het = 0.03); and two showed stronger associations for LCIS than ILC (rs6678914/1q32/LGR6, P-het = 0.001 and rs1752911/6q14, P-het = 0.04). In addition, seven of the 75 known loci showed significant differences between ER+ tumors with IDC and ILC histology, three of these showing stronger associations for ILC (rs11249433/1p11, rs2981579/10q26/FGFR2 and rs10995190/10q21/ZNF365) and four associated only with IDC (5p12/rs10941679; rs2588809/14q24/RAD51L1, rs6472903/8q21 and rs1550623/2q31/CDCA7). In conclusion, we have identified one novel lobular breast cancer specific predisposition polymorphism at 7q34, and shown for the first time that common breast cancer polymorphisms predispose to LCIS. We have shown that many of the ER+ breast cancer predisposition loci also predispose to ILC, although there is some heterogeneity between ER+ lobular and ER+ IDC tumors. These data provide evidence for overlapping, but distinct etiological pathways within ER+ breast cancer between morphological subtypes.
EVALuna2:9234

Genetic risk factors for ovarian cancer and their role for endometriosis risk - Burghaus, Stefanie; Fasching, Peter; Haeberle, Lothar; Rübner, Matthias; Buechner, Kathrin; Blum, Simon; Engel, Anne; Ekici, Arif Bülent; Hartmann, Arndt; Hein, Alexander; Beckmann, Matthias; Renner, Stefan (Gynecologic Oncology, 2017)
Several genetic variants have been validated as risk factors for ovarian cancer. Endometriosis has also been described as a risk factor for ovarian cancer. Identifying genetic risk factors that are common to the two diseases might help improve our understanding of the molecular pathogenesis potentially linking the two conditions.In a hospital-based case-control analysis, 12 single nucleotide polymorphisms (SNPs), validated by the Ovarian Cancer Association Consortium (OCAC) and the Collaborative Oncological Gene-environment Study (COGS) project, were genotyped using TaqMan® OpenArray(TM) analysis. The cases consisted of patients with endometriosis, and the controls were healthy individuals without endometriosis. A total of 385 cases and 484 controls were analyzed. Odds ratios and P values were obtained using simple logistic regression models, as well as from multiple logistic regression models with adjustment for clinical predictors.rs11651755 in HNF1B was found to be associated with endometriosis in this case-control study. The OR was 0.66 (95% CI, 0.51 to 0.84) and the P value after correction for multiple testing was 0.01. None of the other genotypes was associated with a risk for endometriosis.As rs11651755 in HNF1B modified both the ovarian cancer risk and also the risk for endometriosis, HNF1B may be causally involved in the pathogenetic pathway leading from endometriosis to ovarian cancer.
EVALuna2:6871

Genetic Risk Score Mendelian Randomization Shows that Obesity Measured as Body Mass Index, but not Waist:Hip Ratio, Is Causal for Endometrial Cancer - Painter, Jodie N.; O'Mara, Tracy A.; Marquart, Louise; Webb, Penelope M.; Attia, John; Medland, Sarah E.; Cheng, Timothy; Dennis, Joe; Holliday, Elizabeth G.; Mcevoy, Mark; Scott, Rodney J.; Ahmed, Shahana; et al. (Cancer Epidemiology Biomarkers & Prevention, 2016)
The strongest known risk factor for endometrial cancer is obesity. To determine whether SNPs associated with increased body mass index (BMI) or waist-hip ratio (WHR) are associated with endometrial cancer risk, independent of measured BMI, we investigated relationships between 77 BMI and 47 WHR SNPs and endometrial cancer in 6,609 cases and 37,926 country-matched controls.Logistic regression analysis and fixed effects meta-analysis were used to test for associations between endometrial cancer risk and (i) individual BMI or WHR SNPs, (ii) a combined weighted genetic risk score (wGRS) for BMI or WHR. Causality of BMI for endometrial cancer was assessed using Mendelian randomization, with BMIwGRS as instrumental variable.The BMIwGRS was significantly associated with endometrial cancer risk (P = 3.4 × 10(-17)). Scaling the effect of the BMIwGRS on endometrial cancer risk by its effect on BMI, the endometrial cancer OR per 5 kg/m(2) of genetically predicted BMI was 2.06 [95% confidence interval (CI), 1.89-2.21], larger than the observed effect of BMI on endometrial cancer risk (OR = 1.55; 95% CI, 1.44-1.68, per 5 kg/m(2)). The association attenuated but remained significant after adjusting for BMI (OR = 1.22; 95% CI, 1.10-1.39; P = 5.3 × 10(-4)). There was evidence of directional pleiotropy (P = 1.5 × 10(-4)). BMI SNP rs2075650 was associated with endometrial cancer at study-wide significance (P < 4.0 × 10(-4)), independent of BMI. Endometrial cancer was not significantly associated with individual WHR SNPs or the WHRwGRS.BMI, but not WHR, is causally associated with endometrial cancer risk, with evidence that some BMI-associated SNPs alter endometrial cancer risk via mechanisms other than measurable BMI.The causal association between BMI SNPs and endometrial cancer has possible implications for endometrial cancer risk modeling. Cancer Epidemiol Biomarkers Prev; 25(11); 1503-10. ©2016 AACR.
EVALuna2:9342

Genetic risk variants for membranous nephropathy: extension of and association with other chronic kidney disease aetiologies - Sekula, Peggy; Li, Yong; Stanescu, Horia C.; Wuttke, Matthias; Ekici, Arif Bülent; Bockenhauer, Detlef; Walz, Gerd; Powis, Stephen H.; Kielstein, Jan T.; Brenchley, Paul; Eckardt, Kai-Uwe; Kronenberg, Florian; et al. (Nephrology Dialysis Transplantation, 2016)
Membranous nephropathy (MN) is a common cause of nephrotic syndrome in adults. Previous genome-wide association studies (GWAS) of 300 000 genotyped variants identified MN-associated loci at HLA-DQA1 and PLA2R1.We used a combined approach of genotype imputation, GWAS, human leucocyte antigen (HLA) imputation and extension to other aetiologies of chronic kidney disease (CKD) to investigate genetic MN risk variants more comprehensively. GWAS using 9 million high-quality imputed genotypes and classical HLA alleles were conducted for 323 MN European-ancestry cases and 345 controls. Additionally, 4960 patients with different CKD aetiologies in the German Chronic Kidney Disease (GCKD) study were genotyped for risk variants at HLA-DQA1 and PLA2R1.In GWAS, lead variants in known loci [rs9272729, HLA-DQA1, odds ratio (OR) = 7.3 per risk allele, P = 5.9 × 10(-27) and rs17830558, PLA2R1, OR = 2.2, P = 1.9 × 10(-8)] were significantly associated with MN. No novel signals emerged in GWAS of X-chromosomal variants or in sex-specific analyses. Classical HLA alleles (DRB1*0301-DQA1*0501-DQB1*0201 haplotype) were associated with MN but provided little additional information beyond rs9272729. Associations were replicated in 137 GCKD patients with MN (HLA-DQA1: P = 6.4 × 10(-24); PLA2R1: P = 5.0 × 10(-4)). MN risk increased steeply for patients with high-risk genotype combinations (OR > 79). While genetic variation in PLA2R1 exclusively associated with MN across 19 CKD aetiologies, the HLA-DQA1 risk allele was also associated with lupus nephritis (P = 2.8 × 10(-6)), type 1 diabetic nephropathy (P = 6.9 × 10(-5)) and focal segmental glomerulosclerosis (P = 5.1 × 10(-5)), but not with immunoglobulin A nephropathy.PLA2R1 and HLA-DQA1 are the predominant risk loci for MN detected by GWAS. While HLA-DQA1 risk variants show an association with other CKD aetiologies, PLA2R1 variants are specific to MN.
EVALuna2:160

Genetic screening confirms heterozygous mutations in ACAN as a major cause of idiopathic short stature - Hauer, Nadine; Sticht, Heinrich; Boppudi, Sangamitra; Büttner, Christian; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; Abou Jamra, Rami; Wieczorek, Dagmar; Kelkel, Jaqueline; et al. (Scientific Reports, 2017)
Short stature is a common pediatric disorder affecting 3% of the population. However, the clinical variability and genetic heterogeneity prevents the identification of the underlying cause in about 80% of the patients. Recently, heterozygous mutations in the ACAN gene coding for the proteoglycan aggrecan, a main component of the cartilage matrix, were associated with idiopathic short stature. To ascertain the prevalence of ACAN mutations and broaden the phenotypic spectrum in patients with idiopathic short stature we performed sequence analyses in 428 families. We identified heterozygous nonsense mutations in four and potentially disease-causing missense variants in two families (1.4%). These patients presented with a mean of -3.2 SDS and some suggestive clinical characteristics. The results suggest heterozygous mutations in ACAN as a common cause of isolated as well as inherited idiopathic short stature.
EVALuna2:9379

Genetics of serum urate concentrations and gout in a high-risk population, patients with chronic kidney disease - Jing, Jiaojiao; Ekici, Arif Bülent; Sitter, Thomas; Schaeffnert, Elke; Li, Yong; Kronenberg, Florian; Koettgen, Anna; Schultheiss, Ulla T.; Eckardt, Kai-Uwe (Scientific Reports, 2018)
We evaluated genetics of hyperuricemia and gout, their interaction with kidney function and medication intake in chronic kidney disease (CKD) patients. Genome-wide association studies (GWAS) of urate and gout were performed in 4941 CKD patients in the German Chronic Kidney Disease (GCKD) study. Effect estimates of 26 known urate-associated population-based single nucleotide polymorphisms (SNPs) were examined. Interactions of urate-associated variants with urate-altering medications and clinical characteristics of gout were evaluated. Genome-wide significant associations with serum urate and gout were identified for known loci at SLC2A9 and ABCG2, but not for novel loci. Effects of the 26 known SNPs were of similar magnitude in CKD patients compared to population-based individuals, except for SNPs at ABCG2 that showed greater effects in CKD. Gene-medication interactions were not significant when accounting for multiple testing. Associations with gout in specific joints were significant for SLC2A9 rs12498742 in wrists and midfoot joints. Known genetic variants in SLC2A9 and ABCG2 were associated with urate and gout in a CKD cohort, with effect sizes for ABCG2 significantly greater in CKD compared to the general population. CKD patients are at high risk of gout due to reduced kidney function, diuretics intake and genetic predisposition, making treatment to target challenging.
EVALuna2:34616

Genetic studies of paired metabolomes reveal enzymatic and transport processes at the interface of plasma and urine - Schlosser, Pascal; Scherer, Nora; Grundner-Culemann, Franziska; Monteiro-Martins, Sara; Haug, Stefan; Steinbrenner, Inga; Uluvar, Burulça; Wuttke, Matthias; Cheng, Yurong; Ekici, Arif Bülent; Gyimesi, Gergely; Karoly, Edward D.; et al. (Nature Genetics, 2023)
The kidneys operate at the interface of plasma and urine by clearing molecular waste products while retaining valuable solutes. Genetic studies of paired plasma and urine metabolomes may identify underlying processes. We conducted genome-wide studies of 1,916 plasma and urine metabolites and detected 1,299 significant associations. Associations with 40% of implicated metabolites would have been missed by studying plasma alone. We detected urine-specific findings that provide information about metabolite reabsorption in the kidney, such as aquaporin (AQP)-7-mediated glycerol transport, and different metabolomic footprints of kidney-expressed proteins in plasma and urine that are consistent with their localization and function, including the transporters NaDC3 (SLC13A3) and ASBT (SLC10A2). Shared genetic determinants of 7,073 metabolite–disease combinations represent a resource to better understand metabolic diseases and revealed connections of dipeptidase 1 with circulating digestive enzymes and with hypertension. Extending genetic studies of the metabolome beyond plasma yields unique insights into processes at the interface of body compartments.
CRIS-Team Scopus Importer:2023-06-16

Genetic studies of urinary metabolites illuminate mechanisms of detoxification and excretion in humans - Schlosser, Pascal; Li, Yong; Sekula, Peggy; Raffler, Johannes; Grundner-Culemann, Franziska; Pietzner, Maik; Cheng, Yurong; Wuttke, Matthias; Steinbrenner, Inga; Schultheiss, Ulla T.; Kotsis, Fruzsina; Kacprowski, Tim; et al. (Nature Genetics, 2020)
The kidneys integrate information from continuous systemic processes related to the absorption, distribution, metabolism and excretion (ADME) of metabolites. To identify underlying molecular mechanisms, we performed genome-wide association studies of the urinary concentrations of 1,172 metabolites among 1,627 patients with reduced kidney function. The 240 unique metabolite–locus associations (metabolite quantitative trait loci, mQTLs) that were identified and replicated highlight novel candidate substrates for transport proteins. The identified genes are enriched in ADME-relevant tissues and cell types, and they reveal novel candidates for biotransformation and detoxification reactions. Fine mapping of mQTLs and integration with single-cell gene expression permitted the prioritization of causal genes, functional variants and target cell types. The combination of mQTLs with genetic and health information from 450,000 UK Biobank participants illuminated metabolic mediators, and hence, novel urinary biomarkers of disease risk. This comprehensive resource of genetic targets and their substrates is informative for ADME processes in humans and is relevant to basic science, clinical medicine and pharmaceutical research.
CRIS-Team Scopus Importer:2020-02-04

Genetic underpinnings of the psoriatic spectrum - Hüffmeier, Ulrike; Klima, Janine; Hayatu, Mohammad Deen (Medizinische Genetik, 2023)
The psoriatic field includes both rare and common subtypes. Common complex forms include psoriasis vulgaris and psoriatic arthritis. In these subtypes, certain HLA alleles remain the most relevant genetic factors, although genome-wide association studies lead to the detection of more than 80 susceptibility loci. They mainly affect innate and adaptive immunity and explain over 28 % of the heritability. Pustular psoriasis comprises a group of rarer subtypes. Using exome sequencing, several disease genes were identified for mainly generalized pustular psoriasis, and an oligogenic inheritance is likely. Treatment studies based on the affected IL-36 pathway indicate a high response rate in this subtype further supporting the pathophysiological relevance of the affected gene products.
CRIS-Team Scopus Importer:2023-05-26
Keywords: HLA; IL36RN; Psoriasis vulgaris; psoriatic arthritis; pustular psoriasis

Genetic variability of lymphangiogenesis in Collaborative Cross mice: a powerful tool to identify novel endogenous regulators of lymphangiogenesis - Clahsen, Thomas; Büttner, Christian; Hatami, Niloofar; Nuest, Felix; Gabriel, Tim; Reis, André; Cursiefen, Claus (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Genetic variants and cellular stressors associated with exfoliation syndrome modulate promoter activity of a lncRNA within the LOXL1 locus - Hauser, Michael A.; Aboobakar, Inas F.; Liu, Yutao; Miura, Shiroh; Whigham, Benjamin T.; Challa, Pratap; Wheeler, Joshua; Williams, Andrew; Santiago-Turla, Cecelia; Qin, Xuejun; Rautenbach, Robyn M.; Ziskind, Ari; et al. (Human Molecular Genetics, 2015)
Exfoliation syndrome (XFS) is a common, age-related, systemic fibrillinopathy. It greatly increases risk of exfoliation glaucoma (XFG), a major worldwide cause of irreversible blindness. Coding variants in the lysyl oxidase-like 1 (LOXL1) gene are strongly associated with XFS in all studied populations, but a functional role for these variants has not been established. To identify additional candidate functional variants, we sequenced the entire LOXL1 genomic locus ( 40 kb) in 50 indigenous, black South African XFS cases and 50 matched controls. The variants with the strongest evidence of association were located in a well-defined 7-kb region bounded by the 3'-end of exon 1 and the adjacent region of intron 1 of LOXL1. We replicated this finding in US Caucasian (91 cases/1031 controls), German (771 cases/1365 controls) and Japanese (1484 cases/1188 controls) populations. The region of peak association lies upstream of LOXL1-AS1, a long non-coding RNA (lncRNA) encoded on the opposite strand of LOXL1. We show that this region contains a promoter and, importantly, that the strongly associated XFS risk alleles in the South African population are functional variants that significantly modulate the activity of this promoter. LOXL1-AS1 expression is also significantly altered in response to oxidative stress in human lens epithelial cells and in response to cyclic mechanical stress in human Schlemm's canal endothelial cells. Taken together, these findings support a functional role for the LOXL1-AS1 lncRNA in cellular stress response and suggest that dysregulation of its expression by genetic risk variants plays a key role in XFS pathogenesis.
EVALuna2:9211

Genetic variants in FBLIM1 gene do not contribute to SAPHO syndrome and chronic recurrent multifocal osteomyelitis in typical patient groups - Assmann, Gunter; Köhm, Michaela; Schuster, Volker; Behrens, Frank; Mössner, Rotraut; Magnolo, Nina; Oji, Vinzenz; Burkhardt, Harald; Hüffmeier, Ulrike (Bmc Medical Genetics, 2020)
BACKGROUND: Syndrome of synovitis acne pustulosis hyperostosis osteitis (SAPHO) and chronic recurrent multifocal osteomyelitis (CRMO) present two diseases of a dermatologic and rheumatologic spectrum that are variable in manifestation und therapeutic response. Genetic risk factors have long been assumed in both diseases, but no single reliable factor has been identified yet. Therefore, we aimed to clinically characterize a patient group with syndrome of synovitis acne pustulosis hyperostosis osteitis (SAPHO) (n = 47) and chronic recurrent multifocal osteomyelitis (CRMO)/ chronic non-bacterial osteomyelitis (CNO) (n = 9) and analyze a CRMO candidate gene. METHODS: Clinical data of all patients were collected and assessed for different combinations of clinical symptoms. SAPHO patients were grouped into categories according to the acronym; disease-contribution by pathogens was evaluated. We sequenced coding exons of FBLIM1. RESULTS: Palmoplantar pustular psoriasis (PPP) was the most common skin manifestation in CRMO/CNO and SAPHO patients; most SAPHO patients had sterno-costo-clavicular hyperostosis. The most common clinical category of the acronym was S_PHO (n = 26). Lack of pathogen detection from bone biopsies was more common than microbial isolation. We did not identify autosomal-recessive FBLIM1 variants. CONCLUSIONS: S_PHO is the most common combination of symptoms of its acronym. Genetic analyses of FBLIM1 did not provide evidence that this gene is relevant in our patient group. Our study indicates the need to elucidate SAPHO's and CRMO/CNO's pathogenesis.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Association; Chronic non-bacterial osteomyelitis (CNO); Chronic recurrent multifocal osteomyelitis (CRMO); Coding variants; Syndrome of synovitis acne pustulosis hyperostosis osteitis (SAPHO (syndrome))

Genetic variants in the genes of the sex steroid hormone metabolism and depressive symptoms during and after pregnancy - Schneider, Michael; Pretscher, Jutta; Goecke, Tamme; Häberle, Lothar; Engel, Anne; Kornhuber, Johannes; Eichler, Anna; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aim of this study was to conduct an association analysis of depressive symptoms and polymorphisms in the ESR1, PGR, CYP19A1, and COMT genes in pregnant and postpartum women. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for assessment of maternal and fetal health. The German version of the 10-item Edinburgh Postnatal Depression Scale (EPDS) was completed at three time points in this prospective cohort study. Visit 1 was at study entry in the third trimester of pregnancy, visit 2 was shortly after birth, and visit 3 was 6–8 months after birth. Germline DNA and depression measurements from 361 pregnant women were available for analysis. Six single nucleotide polymorphisms (SNPs) in the above-mentioned genes were genotyped. After reconstruction of haplotypes for PGR (rs1042838 and rs10895068) and CYP19A1 (rs10046 and rs4646), a multifactorial linear mixed model was applied to the data to describe the association between haplotypes and depression values. The single SNPs for ESR1 (rs488133) and COMT (rs4680) were analyzed separately using linear mixed models analogously. Results: The mean antepartum EPDS measurement was 5.1, the mean postpartal measurement after 48–72 h was 3.5, and the mean value 6–8 months postpartum was 4.2. The SNPs in PGR were reconstructed into three haplotypes. The most common haplotype was GG, with 63.43% of patients carrying two copies and 33.52% carrying one copy. For haplotype GA, the group of carriers of two copies (0.28%) was combined with the carriers of one copy (9.70%). Haplotype reconstruction using CYP19A1 SNPs resulted in three haplotypes. The most common haplotype was TC, with 25.48% of patients carrying two copies and 51.52% one copy. None of the haplotype blocks and neither of the two single SNPs showed any significant associations with EPDS values. Conclusions: The candidate haplotypes analyzed in PGR and CYP19A1 and single SNPs in ESR1 and COMT did not show any association with depression scores as assessed by EPDS in this cohort of healthy unselected pregnant women.
CRIS-Team Scopus Importer:2022-06-17
Keywords: COMT; CYP19A1; Depression; EPDS; ESR1; PGR; Single nucleotide polymorphisms

Genetic variants in the glucocorticoid pathway genes and birth weight - Schneider, Michael; Hübner, Theresa; Pretscher, Jutta; Goecke, Tamme W.; Schwitulla, Judith; Häberle, Lothar; Kornhuber, Johannes; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: The aim of this study was to examine associations between single nucleotide polymorphisms (SNPs) that tag genetic variation in the glucocorticoid pathways (particularly in maternal genes FKBP5, NR3C1, and CRHR1) and birth weight. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health. Germline DNA was collected from 375 pregnant women. Nine SNPs in the above-mentioned genes were genotyped. After reconstruction of haplotypes for each gene, a linear regression model was applied to the data to describe the association between haplotypes and birth weight. Results: Female sex in the newborn (compared to male) was associated with lower birth weight, whereas a later week of gestation, higher body mass index pre-pregnancy, and higher parity were associated with higher birth weight. No association with birthweight was shown for the haplotypes of the selected SNPs. Conclusions: In this cohort of healthy unselected pregnant women, the analyzed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show any association with birth weight. This might be in line with several other studies that have found no influence of fetal polymorphisms in the glucocorticoid receptor gene or triggers of the maternal HPA axis such as stress and psychosocial problems on birth weight. However, the small sample size in this study and the lack of consideration of individual risk factors and levels of stress in this cohort needs to be taken into account when interpreting the results.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Birth weight; CRHR1; FKBP5; NR3C1; Single nucleotide polymorphisms

Genetic variants in VEGF pathway genes in neoadjuvant breast cancer patients receiving bevacizumab: Results from the randomized phase III GeparQuinto study - Hein, Alexander; Lambrechts, Diether; Von Minckwitz, Gunter; Haeberle, Lothar; Eidtmann, Holger; Tesch, Hans; Untch, Michael; Hilfrich, Joern; Schem, Christian; Rezai, Mahdi; Gerber, Bernd; Costa, Serban Dan; et al. (International Journal of Cancer, 2015)
Studies assessing the effect of bevacizumab (BEV) on breast cancer (BC) outcome have shown different effects on progression-free and overall survival, suggesting that a subgroup of patients may benefit from this treatment. Unfortunately, no biomarkers exist to identify these patients. Here, we investigate whether single nucleotide polymorphisms (SNPs) in VEGF pathway genes correlate with pathological complete response (pCR) in the neoadjuvant GeparQuinto trial. HER2-negative patients were randomized into treatment arms receiving either BEV combined with standard chemotherapy or chemotherapy alone. In a pre-planned biomarker study, DNA was collected from 729 and 724 patients, respectively from both treatment arms, and genotyped for 125 SNPs. Logistic regression assessed interaction between individual SNPs and both treatment arms to predict pCR. Five SNPs may be associated with a better response to BEV, but none of them remained significant after correction for multiple testing. The two SNPs most strongly associated, rs833058 and rs699947, were located upstream of the VEGF-A promoter. Odds ratios for the homozygous common, heterozygous and homozygous rare rs833058 genotypes were 2.36 (95% CI, 1.49-3.75), 1.20 (95% CI, 0.88-1.64) and 0.61 (95% CI, 0.34-1.12). Notably, some SNPs in VEGF-A exhibited a more pronounced effect in the triple-negative subgroup. Several SNPs in VEGF-A may be associated with improved pCR when receiving BEV in the neoadjuvant setting. Although none of the observed effects survived correction for multiple testing, our observations are consistent with previous studies on BEV efficacy in BC. Further research is warranted to clarify the predictive value of these markers.
EVALuna2:9285

Genetic variation at CYP3A is associated with age at menarche and breast cancer risk: a case-control study - Johnson, Nichola; Dudbridge, Frank; Orr, Nick; Gibson, Lorna; Jones, Michael E.; Schoemaker, Minouk J.; Folkerd, Elizabeth J.; Haynes, Ben P.; Hopper, John L.; Southey, Melissa C.; Dite, Gillian S.; Apicella, Carmel; et al. (Breast Cancer Research, 2014)
We have previously shown that a tag single nucleotide polymorphism (rs10235235), which maps to the CYP3A locus (7q22.1), was associated with a reduction in premenopausal urinary estrone glucuronide levels and a modest reduction in risk of breast cancer in women age <=50 years.We further investigated the association of rs10235235 with breast cancer risk in a large case control study of 47,346 cases and 47,570 controls from 52 studies participating in the Breast Cancer Association Consortium. Genotyping of rs10235235 was conducted using a custom Illumina Infinium array. Stratified analyses were conducted to determine whether this association was modified by age at diagnosis, ethnicity, age at menarche or tumor characteristics.We confirmed the association of rs10235235 with breast cancer risk for women of European ancestry but found no evidence that this association differed with age at diagnosis. Heterozygote and homozygote odds ratios (ORs) were OR = 0.98 (95% CI 0.94, 1.01; P = 0.2) and OR = 0.80 (95% CI 0.69, 0.93; P = 0.004), respectively (P(trend) = 0.02). There was no evidence of effect modification by tumor characteristics. rs10235235 was, however, associated with age at menarche in controls (P(trend) = 0.005) but not cases (P(trend) = 0.97). Consequently the association between rs10235235 and breast cancer risk differed according to age at menarche (P(het) = 0.02); the rare allele of rs10235235 was associated with a reduction in breast cancer risk for women who had their menarche age >=15 years (OR(het) = 0.84, 95% CI 0.75, 0.94; OR(hom) = 0.81, 95% CI 0.51, 1.30; P(trend) = 0.002) but not for those who had their menarche age <=11 years (OR(het) = 1.06, 95% CI 0.95, 1.19, OR(hom) = 1.07, 95% CI 0.67, 1.72; P(trend) = 0.29).To our knowledge rs10235235 is the first single nucleotide polymorphism to be associated with both breast cancer risk and age at menarche consistent with the well-documented association between later age at menarche and a reduction in breast cancer risk. These associations are likely mediated via an effect on circulating hormone levels.
EVALuna2:9240

Genetic variation in mitotic regulatory pathway genes is associated with breast tumor grade - Purrington, Kristen S.; Slettedahl, Seth; Bolla, Manjeet K.; Michailidou, Kyriaki; Czene, Kamila; Nevanlinna, Heli; Bojesen, Stig E.; Andrulis, Irene L.; Cox, Angela; Hall, Per; Carpenter, Jane; Yannoukakos, Drakoulis; et al. (Human Molecular Genetics, 2014)
Mitotic index is an important component of histologic grade and has an etiologic role in breast tumorigenesis. Several small candidate gene studies have reported associations between variation in mitotic genes and breast cancer risk. We measured associations between 2156 single nucleotide polymorphisms (SNPs) from 194 mitotic genes and breast cancer risk, overall and by histologic grade, in the Breast Cancer Association Consortium (BCAC) iCOGS study (n = 39 067 cases; n = 42 106 controls). SNPs in TACC2 [rs17550038: odds ratio (OR) = 1.24, 95% confidence interval (CI) 1.16-1.33, P = 4.2 × 10(-10)) and EIF3H (rs799890: OR = 1.07, 95% CI 1.04-1.11, P = 8.7 × 10(-6)) were significantly associated with risk of low-grade breast cancer. The TACC2 signal was retained (rs17550038: OR = 1.15, 95% CI 1.07-1.23, P = 7.9 × 10(-5)) after adjustment for breast cancer risk SNPs in the nearby FGFR2 gene, suggesting that TACC2 is a novel, independent genome-wide significant genetic risk locus for low-grade breast cancer. While no SNPs were individually associated with high-grade disease, a pathway-level gene set analysis showed that variation across the 194 mitotic genes was associated with high-grade breast cancer risk (P = 2.1 × 10(-3)). These observations will provide insight into the contribution of mitotic defects to histological grade and the etiology of breast cancer.
EVALuna2:6629

Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)

Genome sequencing in families with congenital limb malformations - Elsner, Jonas; Mensah, Martin A.; Holtgrewe, Manuel; Hertzberg, Jakob; Bigoni, Stefania; Busche, Andreas; Coutelier, Marie; de Silva, Deepthi C.; Elçioglu, Nursel; Filges, Isabel; Gerkes, Erica; Girisha, Katta M.; et al. (Human genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13. In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2, establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.
CRIS-Team Scopus Importer:2021-07-02

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T.; Traglia, Michela; Ahluwalia, Tarunveer S.; Akiyama, Masato; Appel, Emil Vincent R.; Arking, Dan E.; et al. (Nature Communications, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.
EVALuna2:34824

Genome-wide Analysis Identifies Novel Loci Associated with Ovarian Cancer Outcomes: Findings from the Ovarian Cancer Association Consortium - Johnatty, Sharon E.; Tyrer, Jonathan P.; Kar, Siddhartha; Beesley, Jonathan; Lu, Yi; Gao, Bo; Fasching, Peter; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Lambrechts, Diether; Van Nieuwenhuysen, Els; et al. (Clinical Cancer Research, 2015)
Chemotherapy resistance remains a major challenge in the treatment of ovarian cancer. We hypothesize that germline polymorphisms might be associated with clinical outcome.We analyzed approximately 2.8 million genotyped and imputed SNPs from the iCOGS experiment for progression-free survival (PFS) and overall survival (OS) in 2,901 European epithelial ovarian cancer (EOC) patients who underwent first-line treatment of cytoreductive surgery and chemotherapy regardless of regimen, and in a subset of 1,098 patients treated with >=4 cycles of paclitaxel and carboplatin at standard doses. We evaluated the top SNPs in 4,434 EOC patients, including patients from The Cancer Genome Atlas. In addition, we conducted pathway analysis of all intragenic SNPs and tested their association with PFS and OS using gene set enrichment analysis.Five SNPs were significantly associated (P <= 1.0 × 10(-5)) with poorer outcomes in at least one of the four analyses, three of which, rs4910232 (11p15.3), rs2549714 (16q23), and rs6674079 (1q22), were located in long noncoding RNAs (lncRNAs) RP11-179A10.1, RP11-314O13.1, and RP11-284F21.8, respectively (P <= 7.1 × 10(-6)). ENCODE ChIP-seq data at 1q22 for normal ovary show evidence of histone modification around RP11-284F21.8, and rs6674079 is perfectly correlated with another SNP within the super-enhancer MEF2D, expression levels of which were reportedly associated with prognosis in another solid tumor. YAP1- and WWTR1 (TAZ)-stimulated gene expression and high-density lipoprotein (HDL)-mediated lipid transport pathways were associated with PFS and OS, respectively, in the cohort who had standard chemotherapy (pGSEA <=6 × 10(-3)).We have identified SNPs in three lncRNAs that might be important targets for novel EOC therapies. Clin Cancer Res; 21(23); 5264-76. ©2015 AACR.
EVALuna2:9298

Genome-wide association analyses define pathogenic signaling pathways and prioritize drug targets for IgA nephropathy - Kiryluk, Krzysztof; Sanchez-Rodriguez, Elena; Zhou, Xu Jie; Zanoni, Francesca; Liu, Lili; Mladkova, Nikol; Khan, Atlas; Marasa, Maddalena; Zhang, Jun Y.; Balderes, Olivia; Sanna-Cherchi, Simone; Bomback, Andrew S.; et al. (Nature Genetics, 2023)
IgA nephropathy (IgAN) is a progressive form of kidney disease defined by glomerular deposition of IgA. Here we performed a genome-wide association study of 10,146 kidney-biopsy-diagnosed IgAN cases and 28,751 controls across 17 international cohorts. We defined 30 genome-wide significant risk loci explaining 11% of disease risk. A total of 16 loci were new, including TNFSF4/TNFSF18, REL, CD28, PF4V1, LY86, LYN, ANXA3, TNFSF8/TNFSF15, REEP3, ZMIZ1, OVOL1/RELA, ETS1, IGH, IRF8, TNFRSF13B and FCAR. The risk loci were enriched in gene orthologs causing abnormal IgA levels when genetically manipulated in mice. We also observed a positive genetic correlation between IgAN and serum IgA levels. High polygenic score for IgAN was associated with earlier onset of kidney failure. In a comprehensive functional annotation analysis of candidate causal genes, we observed convergence of biological candidates on a common set of inflammatory signaling pathways and cytokine ligand–receptor pairs, prioritizing potential new drug targets.
CRIS-Team Scopus Importer:2023-06-30

Genome-wide association analysis identifies three new breast cancer susceptibility loci - Ghoussaini, Maya; Fletcher, Olivia; Michailidou, Kyriaki; Turnbull, Clare; Schmidt, Marjanka K.; Dicks, Ed; Dennis, Joe; Wang, Qin; Humphreys, Manjeet K.; Luccarini, Craig; Baynes, Caroline; Conroy, Don; et al. (Nature Genetics, 2012)
Breast cancer is the most common cancer among women. To date, 22 common breast cancer susceptibility loci have been identified accounting for 8% of the heritability of the disease. We attempted to replicate 72 promising associations from two independent genome-wide association studies (GWAS) in 70,000 cases and 68,000 controls from 41 case-control studies and 9 breast cancer GWAS. We identified three new breast cancer risk loci at 12p11 (rs10771399; P = 2.7 × 10(-35)), 12q24 (rs1292011; P = 4.3 × 10(-19)) and 21q21 (rs2823093; P = 1.1 × 10(-12)). rs10771399 was associated with similar relative risks for both estrogen receptor (ER)-negative and ER-positive breast cancer, whereas the other two loci were associated only with ER-positive disease. Two of the loci lie in regions that contain strong plausible candidate genes: PTHLH (12p11) has a crucial role in mammary gland development and the establishment of bone metastasis in breast cancer, and NRIP1 (21q21) encodes an ER cofactor and has a role in the regulation of breast cancer cell growth.
EVALuna2:9145

Genome-wide Association Analysis of Psoriatic Arthritis and Cutaneous Psoriasis Reveals Differences in Their Genetic Architecture - Stuart, Philip E.; Nair, Rajan P.; Tsoi, Lam C.; Tejasvi, Trilokraj; Das, Sayantan; Kang, Hyun Min; Ellinghaus, Eva; Chandran, Vinod; Callis-Duffin, Kristina; Ike, Robert; Li, Yanming; Wen, Xiaoquan; et al. (American Journal of Human Genetics, 2015)
Psoriasis vulgaris (PsV) is a common inflammatory and hyperproliferative skin disease. Up to 30% of people with PsV eventually develop psoriatic arthritis (PsA), an inflammatory musculoskeletal condition. To discern differences in genetic risk factors for PsA and cutaneous-only psoriasis (PsC), we carried out a genome-wide association study (GWAS) of 1,430 PsA case subjects and 1,417 unaffected control subjects. Meta-analysis of this study with three other GWASs and two targeted genotyping studies, encompassing a total of 9,293 PsV case subjects, 3,061 PsA case subjects, 3,110 PsC case subjects, and 13,670 unaffected control subjects of European descent, detected 10 regions associated with PsA and 11 with PsC at genome-wide (GW) significance. Several of these association signals (IFNLR1, IFIH1, NFKBIA for PsA; TNFRSF9, LCE3C/B, TRAF3IP2, IL23A, NFKBIA for PsC) have not previously achieved GW significance. After replication, we also identified a PsV-associated SNP near CDKAL1 (rs4712528, odds ratio [OR] = 1.16, p = 8.4 × 10(-11)). Among identified psoriasis risk variants, three were more strongly associated with PsC than PsA (rs12189871 near HLA-C, p = 5.0 × 10(-19); rs4908742 near TNFRSF9, p = 0.00020; rs10888503 near LCE3A, p = 0.0014), and two were more strongly associated with PsA than PsC (rs12044149 near IL23R, p = 0.00018; rs9321623 near TNFAIP3, p = 0.00022). The PsA-specific variants were independent of previously identified psoriasis variants near IL23R and TNFAIP3. We also found multiple independent susceptibility variants in the IL12B, NOS2, and IFIH1 regions. These results provide insights into the pathogenetic similarities and differences between PsC and PsA.
EVALuna2:9293

Genome-wide association and targeted analysis of copy number variants with psoriatic arthritis in German patients - Uebe, Steffen; Ehrlicher, Maria; Ekici, Arif Bülent; Behrens, Frank; Boehm, Beate; Homuth, Georg; Schurmann, Claudia; Voelker, Uwe; Juenger, Michael; Nauck, Matthias; Voelzke, Henry; Traupe, Heiko; et al. (Bmc Medical Genetics, 2017)
Psoriatic Arthritis (PsA) is a chronic inflammatory disease of the joints. PsA is etiologically complex, and 11 susceptibility loci have been identified so far. Most of these overlap with loci associated with psoriasis vulgaris (PsV), the most common psoriatic skin manifestation which is also frequently seen in PsA patients. In addition, two copy number variants (CNVs) are associated with PsV, one of which, located within the LCE3 gene cluster, is also associated with PsA. Finally, an intergenic deletion has been reported as a PsA-specific CNV.We performed a genome-wide association study (GWAS) of CNVs in PsA and assessed the contribution to disease risk by CNVs at known psoriasis susceptibility loci.After stringent quality assessment and validation of CNVs of the GWAS with an alternative quantitative method, two significantly associated CNVs remained, one near UXS1, the other one at the TRB locus. However, MLPA analysis did not confirm the CN state in 1/3 of individuals, and an analysis of an independent case-control-study failed to confirm the initial associations. Furthermore, detailed PCR-based analysis of the sequence at TRB revealed the existence of a more complex genomic sequence most accurately represented by freeze hg18 which accordingly failed to confirm the hg19 sequence. Only rare CNVs were detected at psoriasis susceptibility loci. At three of 12 susceptibility loci with CNVs (CSMD1, IL12B, RYR2), CN variability was confirmed independently by MLPA. Overall, the rate of CNV confirmation by MLPA was strongly dependent upon CNV type, CNV size and the number of array markers involved in a CNV.Although we identified PsA associations at several loci and confirmed that the common CNVs at these sites were real, 1/3 of the common CNV states could not be reproduced. Furthermore, replication analysis failed to confirm the original association. Furthermore, SNP array-based analyses of CNVs were found to be more reliable for deletions than duplications, independent of the respective CNV allele frequency. CNVs are thus good candidate disease variants, while the methods to detect them should be applied cautiously and reproduced by an independent method.
EVALuna2:9358

Genome-Wide Association Studies of Metabolites in Patients with CKD Identify Multiple Loci and Illuminate Tubular Transport Mechanisms - Li, Yong; Sekula, Peggy; Wuttke, Matthias; Wahrheit, Judith; Hausknecht, Birgit; Schultheiss, Ulla T.; Gronwald, Wolfram; Schlosser, Pascal; Tucci, Sara; Ekici, Arif Bülent; Spiekerkoetter, Ute; Kronenberg, Florian; et al. (Journal of the American Society of Nephrology, 2018)
Background The kidneys have a central role in the generation, turnover, transport, and excretion of metabolites, and these functions can be altered in CKD. Genetic studies of metabolite concentrations can identify proteins performing these functions.Methods We conducted genome-wide association studies and aggregate rare variant tests of the concentrations of 139 serum metabolites and 41 urine metabolites, as well as their pairwise ratios and fractional excretions in up to 1168 patients with CKD.Results After correction for multiple testing, genome-wide significant associations were detected for 25 serum metabolites, two urine metabolites, and 259 serum and 14 urinary metabolite ratios. These included associations already known from population-based studies. Additional findings included an association for the uremic toxin putrescine and variants upstream of an enzyme catalyzing the oxidative deamination of polyamines (AOC1, P-min=2.4×10-12), a relatively high carrier frequency (2%) for rare deleterious missense variants in ACADM that are collectively associated with serum ratios of medium-chain acylcarnitines (P-burden=6.6×10-16), and associations of a common variant in SLC7A9 with several ratios of lysine to neutral amino acids in urine, including the lysine/glutamine ratio (P=2.2×10-23). The associations of this SLC7A9 variant with ratios of lysine to specific neutral amino acids were much stronger than the association with lysine concentration alone. This finding is consistent with SLC7A9 functioning as an exchanger of urinary cationic amino acids against specific intracellular neutral amino acids at the apical membrane of proximal tubular cells.Conclusions Metabolomic indices of specific kidney functions in genetic studies may provide insight into human renal physiology.
EVALuna2:34530

Genome-wide association study identifies 25 known breast cancer susceptibility loci as risk factors for triple-negative breast cancer - Purrington, Kristen S.; Slager, Susan; Eccles, Diana; Yannoukakos, Drakoulis; Fasching, Peter A.; Miron, Penelope; Carpenter, Jane; Chang-Claude, Jenny; Martin, Nicholas G.; Montgomery, Grant W.; Kristensen, Vessela; Anton-Culver, Hoda; et al. (Carcinogenesis, 2014)
Triple-negative (TN) breast cancer is an aggressive subtype of breast cancer associated with a unique set of epidemiologic and genetic risk factors. We conducted a two-stage genome-wide association study of TN breast cancer (stage 1: 1529 TN cases, 3399 controls; stage 2: 2148 cases, 1309 controls) to identify loci that influence TN breast cancer risk. Variants in the 19p13.1 and PTHLH loci showed genome-wide significant associations (P < 5 × 10(-) (8)) in stage 1 and 2 combined. Results also suggested a substantial enrichment of significantly associated variants among the single nucleotide polymorphisms (SNPs) analyzed in stage 2. Variants from 25 of 74 known breast cancer susceptibility loci were also associated with risk of TN breast cancer (P < 0.05). Associations with TN breast cancer were confirmed for 10 loci (LGR6, MDM4, CASP8, 2q35, 2p24.1, TERT-rs10069690, ESR1, TOX3, 19p13.1, RALY), and we identified associations with TN breast cancer for 15 additional breast cancer loci (P < 0.05: PEX14, 2q24.1, 2q31.1, ADAM29, EBF1, TCF7L2, 11q13.1, 11q24.3, 12p13.1, PTHLH, NTN4, 12q24, BRCA2, RAD51L1-rs2588809, MKL1). Further, two SNPs independent of previously reported signals in ESR1 [rs12525163 odds ratio (OR) = 1.15, P = 4.9 × 10(-) (4)] and 19p13.1 (rs1864112 OR = 0.84, P = 1.8 × 10(-) (9)) were associated with TN breast cancer. A polygenic risk score (PRS) for TN breast cancer based on known breast cancer risk variants showed a 4-fold difference in risk between the highest and lowest PRS quintiles (OR = 4.03, 95% confidence interval 3.46-4.70, P = 4.8 × 10(-) (69)). This translates to an absolute risk for TN breast cancer ranging from 0.8% to 3.4%, suggesting that genetic variation may be used for TN breast cancer risk prediction.
EVALuna2:6530

Genome-wide association study identifies a common variant associated with risk of endometrial cancer - Spurdle, Amanda B.; Thompson, Deborah J.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; O'Mara, Tracy; Walker, Logan C.; Montgomery, Stephen B.; Dermitzakis, Emmanouil T.; Fahey, Paul; Montgomery, Grant W.; Webb, Penelope M.; et al. (Nature Genetics, 2011)
Endometrial cancer is the most common malignancy of the female genital tract in developed countries. To identify genetic variants associated with endometrial cancer risk, we performed a genome-wide association study involving 1,265 individuals with endometrial cancer (cases) from Australia and the UK and 5,190 controls from the Wellcome Trust Case Control Consortium. We compared genotype frequencies in cases and controls for 519,655 SNPs. Forty seven SNPs that showed evidence of association with endometrial cancer in stage 1 were genotyped in 3,957 additional cases and 6,886 controls. We identified an endometrial cancer susceptibility locus close to HNF1B at 17q12 (rs4430796, P = 7.1 × 10-10) that is also associated with risk of prostate cancer and is inversely associated with risk of type 2 diabetes. © 2011 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19

Genome-wide association study identifies five new susceptibility loci for primary angle closure glaucoma - Khor, Chiea Chuen; Do, Tan; Jia, Hongyan; Nakano, Masakazu; George, Ronnie; Abu-Amero, Khaled; Duvesh, Roopam; Chen, Li Jia; Li, Zheng; Nongpiur, Monisha E.; Perera, Shamira A.; Qiao, Chunyan; et al. (Nature Genetics, 2016)
Primary angle closure glaucoma (PACG) is a major cause of blindness worldwide. We conducted a genome-wide association study (GWAS) followed by replication in a combined total of 10,503 PACG cases and 29,567 controls drawn from 24 countries across Asia, Australia, Europe, North America, and South America. We observed significant evidence of disease association at five new genetic loci upon meta-analysis of all patient collections. These loci are at EPDR1 rs3816415 (odds ratio (OR) = 1.24, P = 5.94 × 10(-15)), CHAT rs1258267 (OR = 1.22, P = 2.85 × 10(-16)), GLIS3 rs736893 (OR = 1.18, P = 1.43 × 10(-14)), FERMT2 rs7494379 (OR = 1.14, P = 3.43 × 10(-11)), and DPM2-FAM102A rs3739821 (OR = 1.15, P = 8.32 × 10(-12)). We also confirmed significant association at three previously described loci (P < 5 × 10(-8) for each sentinel SNP at PLEKHA7, COL11A1, and PCMTD1-ST18), providing new insights into the biology of PACG.
EVALuna2:9323

Genome-wide association study of germline variants and breast cancer-specific mortality - Escala-Garcia, Maria; Guo, Qi; Doerk, Thilo; Canisius, Sander; Keeman, Renske; Dennis, Joe; Beesley, Jonathan; Lecarpentier, Julie; Bolla, Manjeet K.; Wang, Qin; Abraham, Jean; Andrulis, Irene L.; et al. (British Journal of Cancer, 2019)
BACKGROUND: We examined the associations between germline variants and breast cancer mortality using a large meta-analysis of women of European ancestry.
CRIS-Team WoS Importer:2019-03-29

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Earp, Madalene A.; Kelemen, Linda E.; Magliocco, Anthony M.; Swenerton, Kenneth D.; Chenevix-Trench, Georgia; Lu, Yi; Hein, Alexander; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Lambrechts, Diether; Despierre, Evelyn; et al. (Human genetics, 2014)
Epithelial ovarian cancer (EOC) is a heterogeneous cancer with both genetic and environmental risk factors. Variants influencing the risk of developing the less-common EOC subtypes have not been fully investigated. We performed a genome-wide association study (GWAS) of EOC according to subtype by pooling genomic DNA from 545 cases and 398 controls of European descent, and testing for allelic associations. We evaluated for replication 188 variants from the GWAS [56 variants for mucinous, 55 for endometrioid and clear cell, 53 for low-malignant potential (LMP) serous, and 24 for invasive serous EOC], selected using pre-defined criteria. Genotypes from 13,188 cases and 23,164 controls of European descent were used to perform unconditional logistic regression under the log-additive genetic model; odds ratios (OR) and 95 % confidence intervals are reported. Nine variants tagging six loci were associated with subtype-specific EOC risk at P < 0.05, and had an OR that agreed in direction of effect with the GWAS results. Several of these variants are in or near genes with a biological rationale for conferring EOC risk, including ZFP36L1 and RAD51B for mucinous EOC (rs17106154, OR = 1.17, P = 0.029, n = 1,483 cases), GRB10 for endometrioid and clear cell EOC (rs2190503, P = 0.014, n = 2,903 cases), and C22orf26/BPIL2 for LMP serous EOC (rs9609538, OR = 0.86, P = 0.0043, n = 892 cases). In analyses that included the 75 GWAS samples, the association between rs9609538 (OR = 0.84, P = 0.0007) and LMP serous EOC risk remained statistically significant at P < 0.0012 adjusted for multiple testing. Replication in additional samples will be important to verify these results for the less-common EOC subtypes.
EVALuna2:9208

Genome-wide association study with DNA pooling identifies variants at CNTNAP2 associated with pseudoexfoliation syndrome - Krumbiegel, Mandy; Pasutto, Francesca; Schlötzer-Schrehardt, Ursula; Uebe, Steffen; Zenkel, Matthias; Mardin, Christian Y.; Weisschuh, Nicole; Paoli, Daniela; Gramer, Eugen; Becker, Christian; Ekici, Arif Bülent; Weber, Bernhard H. F.; et al. (European journal of human genetics, 2011)
Genetic and nongenetic factors contribute to development of pseudoexfoliation (PEX) syndrome, a complex, age-related, generalized matrix process frequently associated with glaucoma. To identify specific genetic variants underlying its etiology, we performed a genome-wide association study (GWAS) using a DNA-pooling approach. Therefore, equimolar amounts of DNA samples of 80 subjects with PEX syndrome, 80 with PEX glaucoma (PEXG) and 80 controls were combined into separate pools and hybridized to 500K SNP arrays (Affymetrix). Array probe intensity data were analyzed and visualized with expressly developed software tools GPFrontend and GPGraphics in combination with GenePool software. For replication, independent German cohorts of 610 unrelated patients with PEX/PEXG and 364 controls as well as Italian cohorts of 249 patients and 190 controls were used. Of 19, 17 SNPs showing significant allele frequency difference in DNA pools were confirmed by individual genotyping. Further single genotyping at CNTNAP2 locus revealed association between PEX/PEXG for two SNPs, which was confirmed in an independent German but not the Italian cohort. Both SNPs remained significant in the combined German cohorts even after Bonferroni correction (rs2107856: P(c)=0.0108, rs2141388: P(c)=0.0072). CNTNAP2 was found to be ubiquitously expressed in all human ocular tissues, particularly in retina, and localized to cell membranes of epithelial, endothelial, smooth muscle, glial and neuronal cells. Confirming efficiency of GWAS with DNA-pooling approach by detection of the known LOXL1 locus, our study data show evidence for association of CNTNAP2 with PEX syndrome and PEXG in German patients.
EVALuna2:9084

Genome-wide cooperation of EMT transcription factor ZEB1 with YAP and AP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Bönisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and the EMT-inducing transcription factor ZEB1 is a crucial stimulator of these processes. While work on ZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wide ZEB1 binding study in triple-negative breast cancer cells. We identified ZEB1 as a novel interactor of the AP-1 factors FOSL1 and JUN and show that, together with the Hippo pathway effector YAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression of ZEB1, YAP, FOSL1 and JUN marks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors: ZEB1, AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team Scopus Importer:2020-07-31
Keywords: AP-1; breast cancer; epithelial to mesenchymal transition; ZEB1

Genome-wide cooperation ofEMTtranscription factorZEB1 withYAPandAP-1 in breast cancer - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A.; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Boenisch, Ulrike; Lukassen, Sören; Eccles, Rebecca; et al. (EMBO Journal, 2020)
Invasion, metastasis and therapy resistance are the major cause of cancer-associated deaths, and theEMT-inducing transcription factorZEB1 is a crucial stimulator of these processes. While work onZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome-wideZEB1 binding study in triple-negative breast cancer cells. We identifiedZEB1 as a novel interactor of theAP-1 factorsFOSL1 andJUNand show that, together with the Hippo pathway effectorYAP, they form a transactivation complex, predominantly activating tumour-promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression ofZEB1,YAP,FOSL1 andJUNmarks the aggressive claudin-low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour-promoting transcription factors:ZEB1,AP-1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types.
CRIS-Team WoS Importer:2020-09-25

Genome-Wide Meta-Analyses of Breast, Ovarian, and Prostate Cancer Association Studies Identify Multiple New Susceptibility Loci Shared by at Least Two Cancer Types - Kar, Siddhartha P.; Beesley, Jonathan; Al Olama, Ali Amin; Michailidou, Kyriaki; Tyrer, Jonathan; Kote-Jarai, Zsofi A.; Lawrenson, Kate; Lindstrom, Sara; Ramus, Susan J.; Thompson, Deborah J.; Kibel, Adam S.; Dansonka-Mieszkowska, Agnieszka; et al. (Cancer Discovery, 2016)
Breast, ovarian, and prostate cancers are hormone-related and may have a shared genetic basis, but this has not been investigated systematically by genome-wide association (GWA) studies. Meta-analyses combining the largest GWA meta-analysis data sets for these cancers totaling 112,349 cases and 116,421 controls of European ancestry, all together and in pairs, identified at P < 10(-8) seven new cross-cancer loci: three associated with susceptibility to all three cancers (rs17041869/2q13/BCL2L11; rs7937840/11q12/INCENP; rs1469713/19p13/GATAD2A), two breast and ovarian cancer risk loci (rs200182588/9q31/SMC2; rs8037137/15q26/RCCD1), and two breast and prostate cancer risk loci (rs5013329/1p34/NSUN4; rs9375701/6q23/L3MBTL3). Index variants in five additional regions previously associated with only one cancer also showed clear association with a second cancer type. Cell-type-specific expression quantitative trait locus and enhancer-gene interaction annotations suggested target genes with potential cross-cancer roles at the new loci. Pathway analysis revealed significant enrichment of death receptor signaling genes near loci with P < 10(-5) in the three-cancer meta-analysis.We demonstrate that combining large-scale GWA meta-analysis findings across cancer types can identify completely new risk loci common to breast, ovarian, and prostate cancers. We show that the identification of such cross-cancer risk loci has the potential to shed new light on the shared biology underlying these hormone-related cancers. Cancer Discov; 6(9); 1052-67. ©2016 AACR.This article is highlighted in the In This Issue feature, p. 932.
EVALuna2:9322

Genome-wide UPD screening in patients with intellectual disability - Schroeder, Christopher; Ekici, Arif Bülent; Moog, Ute; Grasshoff, Ute; Mau-Holzmann, Ulrike; Sturm, Marc; Vosseler, Vanessa; Poths, Sven; Rappold, Gudrun; Riess, Angelika; Riess, Olaf; Dufke, Andreas; et al. (European journal of human genetics, 2014)
Uniparental disomy (UPD) describes the inheritance of a pair of chromosomes from only one parent. It may occur as isodisomy, heterodisomy or a combination of both and may involve only chromosome segments. UPD can affect each chromosome. The incidence is estimated to be around 1:3500 in live births. Some parts of chromosomes are subject to 'parent-of-origin imprinting' and the phenotypic effect in UPD syndromes is mainly due to functional imbalance of imprinted genes. Isodisomy can result in mutation homozygosity in autosomal-recessive inherited diseases. UPD causes several well-defined imprinting syndromes associated with intellectual disability (ID). Although knowledge on frequency and size of UPDs in patients with unexplained ID remains largely unknown as no efficient genome-wide screening technique was available for detection of both isodisomic and heterodisomic UPDs. SNP microarrays have been proven to be capable to detect UPDs through Mendelian errors. The correct subclassification of UPD requires child-parent trio experiments. To further elucidate the role of UPD in patients with unexplained ID, we analyzed a total of 322 child-parent trios. We were not able to detect UPDs (isodisomies and heterodisomies) within our cohort spanning whole chromosomes or chromosomal segments. We conclude that UPD is rare in patients with unexplained ID.
EVALuna2:9225

Genotype–phenotype correlations and novel molecular insights into the DHX30-associated neurodevelopmental disorders - Mannucci, Ilaria; Dang, Nghi D. P.; Huber, Hannes; Murry, Jaclyn B.; Abramson, Jeff; Althoff, Thorsten; Banka, Siddharth; Baynam, Gareth; Bearden, David; Beleza-Meireles, Ana; Benke, Paul J.; Berland, Siren; et al. (Genome Medicine, 2021)
Background: We aimed to define the clinical and variant spectrum and to provide novel molecular insights into the DHX30-associated neurodevelopmental disorder. Methods: Clinical and genetic data from affected individuals were collected through Facebook-based family support group, GeneMatcher, and our network of collaborators. We investigated the impact of novel missense variants with respect to ATPase and helicase activity, stress granule (SG) formation, global translation, and their effect on embryonic development in zebrafish. SG formation was additionally analyzed in CRISPR/Cas9-mediated DHX30-deficient HEK293T and zebrafish models, along with in vivo behavioral assays. Results: We identified 25 previously unreported individuals, ten of whom carry novel variants, two of which are recurrent, and provide evidence of gonadal mosaicism in one family. All 19 individuals harboring heterozygous missense variants within helicase core motifs (HCMs) have global developmental delay, intellectual disability, severe speech impairment, and gait abnormalities. These variants impair the ATPase and helicase activity of DHX30, trigger SG formation, interfere with global translation, and cause developmental defects in a zebrafish model. Notably, 4 individuals harboring heterozygous variants resulting either in haploinsufficiency or truncated proteins presented with a milder clinical course, similar to an individual harboring a de novo mosaic HCM missense variant. Functionally, we established DHX30 as an ATP-dependent RNA helicase and as an evolutionary conserved factor in SG assembly. Based on the clinical course, the variant location, and type we establish two distinct clinical subtypes. DHX30 loss-of-function variants cause a milder phenotype whereas a severe phenotype is caused by HCM missense variants that, in addition to the loss of ATPase and helicase activity, lead to a detrimental gain-of-function with respect to SG formation. Behavioral characterization of dhx30-deficient zebrafish revealed altered sleep-wake activity and social interaction, partially resembling the human phenotype. Conclusions: Our study highlights the usefulness of social media to define novel Mendelian disorders and exemplifies how functional analyses accompanied by clinical and genetic findings can define clinically distinct subtypes for ultra-rare disorders. Such approaches require close interdisciplinary collaboration between families/legal representatives of the affected individuals, clinicians, molecular genetics diagnostic laboratories, and research laboratories.
CRIS-Team Scopus Importer:2021-06-11

Germline polymorphisms in an enhancer of PSIP1 are associated with progression-free survival in epithelial ovarian cancer - French, Juliet D.; Johnatty, Sharon E.; Lu, Yi; Beesley, Jonathan; Gao, Bo; Kalimutho, Murugan; Henderson, Michelle J.; Russell, Amanda J.; Kar, Siddhartha; Chen, Xiaoqing; Hillman, Kristine M.; Kaufmann, Susanne; et al. (Oncotarget, 2016)
Women with epithelial ovarian cancer (EOC) are usually treated with platinum/taxane therapy after cytoreductive surgery but there is considerable inter-individual variation in response. To identify germline single-nucleotide polymorphisms (SNPs) that contribute to variations in individual responses to chemotherapy, we carried out a multi-phase genome-wide association study (GWAS) in 1,244 women diagnosed with serous EOC who were treated with the same first-line chemotherapy, carboplatin and paclitaxel. We identified two SNPs (rs7874043 and rs72700653) in TTC39B (best P=7x10-5, HR=1.90, for rs7874043) associated with progression-free survival (PFS). Functional analyses show that both SNPs lie in a putative regulatory element (PRE) that physically interacts with the promoters of PSIP1, CCDC171 and an alternative promoter of TTC39B. The C allele of rs7874043 is associated with poor PFS and showed increased binding of the Sp1 transcription factor, which is critical for chromatin interactions with PSIP1. Silencing of PSIP1 significantly impaired DNA damage-induced Rad51 nuclear foci and reduced cell viability in ovarian cancer lines. PSIP1 (PC4 and SFRS1 Interacting Protein 1) is known to protect cells from stress-induced apoptosis, and high expression is associated with poor PFS in EOC patients. We therefore suggest that the minor allele of rs7874043 confers poor PFS by increasing PSIP1 expression.
EVALuna2:9320

Germline variants and breast cancer survival in patients with distant metastases at primary breast cancer diagnosis - Escala-Garcia, Maria; Canisius, Sander; Keeman, Renske; Beesley, Jonathan; Anton-Culver, Hoda; Arndt, Volker; Augustinsson, Annelie; Becher, Heiko; Beckmann, Matthias; Behrens, Sabine; Bermisheva, Marina; Bojesen, Stig E.; et al. (Scientific Reports, 2021)
Breast cancer metastasis accounts for most of the deaths from breast cancer. Identification of germline variants associated with survival in aggressive types of breast cancer may inform understanding of breast cancer progression and assist treatment. In this analysis, we studied the associations between germline variants and breast cancer survival for patients with distant metastases at primary breast cancer diagnosis. We used data from the Breast Cancer Association Consortium (BCAC) including 1062 women of European ancestry with metastatic breast cancer, 606 of whom died of breast cancer. We identified two germline variants on chromosome 1, rs138569520 and rs146023652, significantly associated with breast cancer-specific survival (P = 3.19 x 10(-8) and 4.42 x 10(-8)). In silico analysis suggested a potential regulatory effect of the variants on the nearby target genes SDE2 and H3F3A. However, the variants showed no evidence of association in a smaller replication dataset. The validation dataset was obtained from the SNPs to Risk of Metastasis (StoRM) study and included 293 patients with metastatic primary breast cancer at diagnosis. Ultimately, larger replication studies are needed to confirm the identified associations.
CRIS-Team WoS Importer:2021-10-15

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

GWAS meta-analysis and replication identifies three new susceptibility loci for ovarian cancer - Pharoah, Paul D. P.; Tsai, Ya-Yu; Ramus, Susan J.; Phelan, Catherine M.; Goode, Ellen L.; Lawrenson, Kate; Buckley, Melissa; Fridley, Brooke L.; Tyrer, Jonathan P.; Shen, Howard; Weber, Rachel; Karevan, Rod; et al. (Nature Genetics, 2013)
Genome-wide association studies (GWAS) have identified four susceptibility loci for epithelial ovarian cancer (EOC), with another two suggestive loci reaching near genome-wide significance. We pooled data from a GWAS conducted in North America with another GWAS from the UK. We selected the top 24,551 SNPs for inclusion on the iCOGS custom genotyping array. We performed follow-up genotyping in 18,174 individuals with EOC (cases) and 26,134 controls from 43 studies from the Ovarian Cancer Association Consortium. We validated the two loci at 3q25 and 17q21 that were previously found to have associations close to genome-wide significance and identified three loci newly associated with risk: two loci associated with all EOC subtypes at 8q21 (rs11782652, P = 5.5 × 10-9) and 10p12 (rs1243180, P = 1.8 × 10-8) and another locus specific to the serous subtype at 17q12 (rs757210, P = 8.1 × 10-10). An integrated molecular analysis of genes and regulatory regions at these loci provided evidence for functional mechanisms underlying susceptibility and implicated CHMP4C in the pathogenesis of ovarian cancer.
CRIS-Team Scopus Importer:2021-07-19

Habituation Learning Is a Widely Affected Mechanism in Drosophila Models of Intellectual Disability and Autism Spectrum Disorders - Fenckova, Michaela; Blok, Laura E.R.; Asztalos, Lenke; Goodman, David P.; Cizek, Pavel; Singgih, Euginia L.; Glennon, Jeffrey C.; IntHout, Joanna; Zweier, Christiane; Eichler, Evan E.; von Reyn, Catherine R.; Bernier, Raphael A.; et al. (Biological Psychiatry, 2019)
Background: Although habituation is one of the most ancient and fundamental forms of learning, its regulators and its relevance for human disease are poorly understood. Methods: We manipulated the orthologs of 286 genes implicated in intellectual disability (ID) with or without comorbid autism spectrum disorder (ASD) specifically in Drosophila neurons, and we tested these models in light-off jump habituation. We dissected neuronal substrates underlying the identified habituation deficits and integrated genotype–phenotype annotations, gene ontologies, and interaction networks to determine the clinical features and molecular processes that are associated with habituation deficits. Results: We identified >100 genes required for habituation learning. For 93 of these genes, a role in habituation learning was previously unknown. These genes characterize ID disorders with macrocephaly and/or overgrowth and comorbid ASD. Moreover, individuals with ASD from the Simons Simplex Collection carrying damaging de novo mutations in these genes exhibit increased aberrant behaviors associated with inappropriate, stereotypic speech. At the molecular level, ID genes required for normal habituation are enriched in synaptic function and converge on Ras/mitogen-activated protein kinase (Ras/MAPK) signaling. Both increased Ras/MAPK signaling in gamma-aminobutyric acidergic (GABAergic) neurons and decreased Ras/MAPK signaling in cholinergic neurons specifically inhibit the adaptive habituation response. Conclusions: Our work supports the relevance of habituation learning to ASD, identifies an unprecedented number of novel habituation players, supports an emerging role for inhibitory neurons in habituation, and reveals an opposing, circuit-level-based mechanism for Ras/MAPK signaling. These findings establish habituation as a possible, widely applicable functional readout and target for pharmacologic intervention in ID/ASD.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Autism spectrum disorder; Drosophila; GABAergic neurons; Habituation learning; Intellectual disability; Ras/MAPK

Haploinsufficiency of NR4A2 is associated with a neurodevelopmental phenotype with prominent language impairment - Reuter, Miriam; Krumbiegel, Mandy; Schlueter, Gregor; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2017)
Non-recurrent deletions in 2q24.1, minimally overlapping two genes, NR4A2 and GPD2, were recently described in individuals with language impairment and behavioral and cognitive symptoms. We herewith report on a female patient with a similar phenotype of severe language and mild cognitive impairment, in whom we identified a de novo deletion covering only NR4A2. NR4A2 encodes a transcription factor highly expressed in brain regions critical for speech and language and implicated in dopaminergic neuronal development. Our findings of a de novo deletion of NR4A2 in an individual with mild intellectual disability and prominent speech and language impairment provides further evidence for NR4A2 haploinsufficiency being causative for neurodevelopmental and particularly language phenotypes.
EVALuna2:9359

Haploinsufficiency of PRR12 causes a spectrum of neurodevelopmental, eye, and multisystem abnormalities - Chowdhury, Fuad; Wang, Lei; Al-Raqad, Mohammed; Amor, David J.; Baxová, Alice; Bendová, Šárka; Biamino, Elisa; Brusco, Alfredo; Caluseriu, Oana; Cox, Nancy J.; Froukh, Tawfiq; Gunay-Aygun, Meral; et al. (Genetics in Medicine, 2021)
Purpose: Proline Rich 12 (PRR12) is a gene of unknown function with suspected DNA-binding activity, expressed in developing mice and human brains. Predicted loss-of-function variants in this gene are extremely rare, indicating high intolerance of haploinsufficiency. Methods: Three individuals with intellectual disability and iris anomalies and truncating de novo PRR12 variants were described previously. We add 21 individuals with similar PRR12 variants identified via matchmaking platforms, bringing the total number to 24. Results: We observed 12 frameshift, 6 nonsense, 1 splice-site, and 2 missense variants and one patient with a gross deletion involving PRR12. Three individuals had additional genetic findings, possibly confounding the phenotype. All patients had developmental impairment. Variable structural eye defects were observed in 12/24 individuals (50%) including anophthalmia, microphthalmia, colobomas, optic nerve and iris abnormalities. Additional common features included hypotonia (61%), heart defects (52%), growth failure (54%), and kidney anomalies (35%). PrediXcan analysis showed that phecodes most strongly associated with reduced predicted PRR12 expression were enriched for eye- (7/30) and kidney- (4/30) phenotypes, such as wet macular degeneration and chronic kidney disease. Conclusion: These findings support PRR12 haploinsufficiency as a cause for a novel disorder with a wide clinical spectrum marked chiefly by neurodevelopmental and eye abnormalities.
CRIS-Team Scopus Importer:2021-04-16

Haploinsufficiency of the Chromatin Remodeler BPTF Causes Syndromic Developmental and Speech Delay, Postnatal Microcephaly, and Dysmorphic Features - Stankiewicz, Pawel; Khan, Tahir N.; Szafranski, Przemyslaw; Slattery, Leah; Streff, Haley; Vetrini, Francesco; Bernstein, Jonathan A.; Brown, Chester W.; Rosenfeld, Jill A.; Rednam, Surya; Scollon, Sarah; Bergstrom, Katie L.; et al. (American Journal of Human Genetics, 2017)
Bromodomain PHD finger transcription factor (BPTF) is the largest subunit of nucleosome remodeling factor (NURF), a member of the ISWI chromatin-remodeling complex. However, the clinical consequences of disruption of this complex remain largely uncharacterized. BPTF is required for anterior-posterior axis formation of the mouse embryo and was shown to promote posterior neuroectodermal fate by enhancing Smad2-activated wnt8 expression in zebrafish. Here, we report eight loss-of-function and two missense variants (eight de novo and two of unknown origin) in BPTF on 17q24.2. The BPTF variants were found in unrelated individuals aged between 2.1 and 13 years, who manifest variable degrees of developmental delay/intellectual disability (10/10), speech delay (10/10), postnatal microcephaly (7/9), and dysmorphic features (9/10). Using CRISPR-Cas9 genome editing of bptf in zebrafish to induce a loss of gene function, we observed a significant reduction in head size of F0 mutants compared to control larvae. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and phospho-histone H3 (PH3) staining to assess apoptosis and cell proliferation, respectively, showed a significant increase in cell death in F0 mutants compared to controls. Additionally, we observed a substantial increase of the ceratohyal angle of the craniofacial skeleton in bptf F0 mutants, indicating abnormal craniofacial patterning. Taken together, our data demonstrate the pathogenic role of BPTF haploinsufficiency in syndromic neurodevelopmental anomalies and extend the clinical spectrum of human disorders caused by ablation of chromatin remodeling complexes.
EVALuna2:9361

Height and Breast Cancer Risk: Evidence From Prospective Studies and Mendelian Randomization - Zhang, Ben; Shu, Xiao-Ou; Delahanty, Ryan J.; Zeng, Chenjie; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Wen, Wanqing; Long, Jirong; Li, Chun; Dunning, Alison M.; et al. (Journal of the National Cancer Institute, 2015)
Epidemiological studies have linked adult height with breast cancer risk in women. However, the magnitude of the association, particularly by subtypes of breast cancer, has not been established. Furthermore, the mechanisms of the association remain unclear.We performed a meta-analysis to investigate associations between height and breast cancer risk using data from 159 prospective cohorts totaling 5216302 women, including 113178 events. In a consortium with individual-level data from 46325 case patients and 42482 control patients, we conducted a Mendelian randomization analysis using a genetic score that comprised 168 height-associated variants as an instrument. This association was further evaluated in a second consortium using summary statistics data from 16003 case patients and 41335 control patients.The pooled relative risk of breast cancer was 1.17 (95% confidence interval [CI] = 1.15 to 1.19) per 10cm increase in height in the meta-analysis of prospective studies. In Mendelian randomization analysis, the odds ratio of breast cancer per 10cm increase in genetically predicted height was 1.22 (95% CI = 1.13 to 1.32) in the first consortium and 1.21 (95% CI = 1.05 to 1.39) in the second consortium. The association was found in both premenopausal and postmenopausal women but restricted to hormone receptor-positive breast cancer. Analyses of height-associated variants identified eight new loci associated with breast cancer risk after adjusting for multiple comparisons, including three loci at 1q21.2, DNAJC27, and CCDC91 at genome-wide significance level P < 5×10(-8).Our study provides strong evidence that adult height is a risk factor for breast cancer in women and certain genetic factors and biological pathways affecting adult height have an important role in the etiology of breast cancer.
EVALuna2:9301

HER2 and TOP2A amplification in a hospital-based cohort of breast cancer patients: associations with patient and tumor characteristics - Fasching, Peter A.; Weihbrecht, Sebastian; Haeberle, Lothar; Gasparyan, Armen; Villalobos, Ivonne E.; Ma, Yanling; Ekici, Arif Bülent; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Press, Michael F. (Breast Cancer Research and Treatment, 2014)
Gene amplification is an important factor for altered gene expression in breast cancers. TOP2A-amplification often occurs concomitantly with HER2 amplification, and it has been suggested to be predictive for the response to anthracycline chemotherapy. This study assessed the correlation between HER2 status and TOP2A co-amplification, the possible association of TOP2A single-nucleotide polymorphisms with the frequency of this co-amplification as well as confirmation of association with outcome. HER2 and TOP2A amplification were analyzed in a tissue microarray from a clinical cohort study. Additionally, a common genetic variant (rs13695) in the TOP2A gene was genotyped in germline DNA. HER2 gene amplification was compared with HER2-IHC findings assessed during clinical routine work, and the association between all the biomarkers analyzed and the clinical outcome was determined. As an exploratory aim, rs13695 genotypes were compared with TOP2A amplification status. HER2 amplification was seen in 101 of 628 (16.1 %) and TOP2A amplification in 32 (5.1 %) cancers. No TOP2A amplification occurred without HER2 co-amplification. HER2 amplification was found in 8, 13.6, and 55.1 % of patients with HER2-IHC 0/1+, 2+, and 3+ tumors, respectively. HER2-IHC was not associated with an effect on the prognosis, but HER2-FISH was. There was an association between the rs13695 genotype and TOP2A amplification status (P = 0.03). Although there was a significant correlation between HER2 status determined by IHC and HER2 by FISH, only HER2 gene amplification status by FISH was correlated with outcome indicating greater utility for FISH in routine clinical settings.
EVALuna2:6613

Heterozygous UBR5 variants result in a neurodevelopmental syndrome with developmental delay, autism, and intellectual disability - Sabeh, Pascale; Dumas, Samantha A.; Maios, Claudia; Daghar, Hiba; Korzeniowski, Marek; Rousseau, Justine; Lines, Matthew; Guerin, Andrea; Millichap, John J.; Landsverk, Megan; Grebe, Theresa; Lindstrom, Kristin; et al. (American Journal of Human Genetics, 2025)
E3 ubiquitin ligases have been linked to developmental diseases including autism, Angelman syndrome (UBE3A), and Johanson-Blizzard syndrome (JBS) (UBR1). Here, we report variants in the E3 ligase UBR5 in 29 individuals presenting with a neurodevelopmental syndrome that includes developmental delay, autism, intellectual disability, epilepsy, movement disorders, and/or genital anomalies. Their phenotype is distinct from JBS due to the absence of exocrine pancreatic insufficiency and the presence of autism, epilepsy, and, in some probands, a movement disorder. E3 ubiquitin ligases are responsible for transferring ubiquitin to substrate proteins to regulate a variety of cellular functions, including protein degradation, protein-protein interactions, and protein localization. Knocking out ubr-5 in C. elegans resulted in a lower movement score compared to the wild type, supporting a role for UBR5 in neurodevelopment. Using an in vitro autoubiquitination assay and confocal microscopy for the human protein, we found decreased ubiquitination activity and altered cellular localization in several variants found in our cohort compared to the wild type. In conclusion, we found that variants in UBR5 cause a neurodevelopmental syndrome that can be associated with a movement disorder, reinforcing the role of the UBR protein family in a neurodevelopmental disease that differs from previously described ubiquitin-ligase-related syndromes. We also provide evidence for the pathogenic potential loss of UBR5 function with functional experiments in C. elegans and in vitro ubiquitination assays.
CRIS-Team Scopus Importer:2025-01-31
Keywords: autism; autosomal dominant; developmental disease; epilepsy; intellectual disability; Mendelian phenotype; movement disorders; ubiquitin; UBR5

Heterozygous variants in MYH10 associated with neurodevelopmental disorders and congenital anomalies with evidence for primary cilia-dependent defects in Hedgehog signaling - Holtz, Alexander M.; VanCoillie, Rachel; Vansickle, Elizabeth A.; Carere, Deanna Alexis; Withrow, Kara; Torti, Erin; Juusola, Jane; Millan, Francisca; Person, Richard; Guillen Sacoto, Maria J.; Si, Yue; Wentzensen, Ingrid M.; et al. (Genetics in Medicine, 2022)
Purpose: Nonmuscle myosin II complexes are master regulators of actin dynamics that play essential roles during embryogenesis with vertebrates possessing 3 nonmuscle myosin II heavy chain genes, MYH9, MYH10, and MYH14. As opposed to MYH9 and MYH14, no recognizable disorder has been associated with MYH10. We sought to define the clinical characteristics and molecular mechanism of a novel autosomal dominant disorder related to MYH10. Methods: An international collaboration identified the patient cohort. CAS9-mediated knockout cell models were used to explore the mechanism of disease pathogenesis. Results: We identified a cohort of 16 individuals with heterozygous MYH10 variants presenting with a broad spectrum of neurodevelopmental disorders and variable congenital anomalies that affect most organ systems and were recapitulated in animal models of altered MYH10 activity. Variants were typically de novo missense changes with clustering observed in the motor domain. MYH10 knockout cells showed defects in primary ciliogenesis and reduced ciliary length with impaired Hedgehog signaling. MYH10 variant overexpression produced a dominant-negative effect on ciliary length. Conclusion: These data presented a novel genetic cause of isolated and syndromic neurodevelopmental disorders related to heterozygous variants in the MYH10 gene with implications for disrupted primary cilia length control and altered Hedgehog signaling in disease pathogenesis.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Hedgehog signaling; MYH10; Neurodevelopmental disorder; Nonmuscle myosin; Primary cilia

HIBCH deficiency in a patient with phenotypic characteristics of mitochondrial disorders - Reuter, Miriam; Sass, Joern Oliver; Leis, Thomas; Koehler, Julia; Mayr, Johannes A.; Feichtinger, Rene G.; Rauh, Manfred; Schanze, Ina; Baehr, Luzy; Trollmann, Regina; Uebe, Steffen; Ekici, Arif Bülent; et al. (American Journal of Medical Genetics Part A, 2014)
HIBCH (3-hydroxyisobutyryl-CoA hydrolase) deficiency (MIM #250620) is a rare autosomal recessive inborn error of metabolism, leading to a block in the catabolic pathway of the amino acid valine and presumably to accumulation of toxic valine metabolites in mitochondria. Only three families with HIBCH deficiency and biallelic HIBCH mutations have been described. We report on a further patient, first child of healthy consanguineous parents, with severe developmental delay, seizures, hyperintensities of the basal ganglia on magnetic resonance imaging (MRI), progressive brain atrophy, optic nerve atrophy, repeatedly elevated blood lactate, and respiratory chain complexes I, I + III and cytochrome c oxidase deficiencies with borderline depletion of mitochondrial DNA in muscle tissue. Laboratory findings in blood and skeletal muscle were inconsistent and did not allow a definite diagnosis, but supported the hypothesis of mitochondrial dysfunction. Homozygosity mapping and whole-exome sequencing revealed a homozygous one-base pair insertion in HIBCH. Deficiency of enzyme activity was confirmed in cultured fibroblasts. Although relatively unspecific, the clinical features were similar to those of the previously reported cases. Given the clinical variability and large number of differential diagnoses, the prevalence of HIBCH deficiency is probably underestimated. Next-generation sequencing approaches are an effective tool for identifying the underlying genetic basis in patients suspected of mitochondrial disorders. © 2014 Wiley Periodicals, Inc.
EVALuna2:9220

High resolution chromosomal microarray analysis in paediatric obsessive-compulsive disorder - Grünblatt, Edna; Oneda, Beatrice; Ekici, Arif Bülent; Ball, Juliane; Geissler, Julia; Uebe, Steffen; Romanos, Marcel; Rauch, Anita; Walitza, Susanne (Bmc Medical Genomics, 2017)
Obsessive-Compulsive Disorder (OCD) is a common and chronic disorder in which a person has uncontrollable, reoccurring thoughts and behaviours. It is a complex genetic condition and, in case of early onset (EO), the patients manifest a more severe phenotype, and an increased heritability. Large (>500 kb) copy number variations (CNVs) previously associated with autism and schizophrenia have been reported in OCD. Recently, rare CNVs smaller than 500 kb overlapping risk loci for other neurodevelopmental conditions have also been reported in OCD, stressing the importance of examining CNVs of any size range. The aim of this study was to further investigate the role of rare and small CNVs in the aetiology of EO-OCD.We performed high-resolution chromosomal microarray analysis in 121 paediatric OCD patients and in 124 random controls to identify rare CNVs (>50 kb) which might contribute to EO-OCD.The frequencies and the size of the observed rare CNVs in the patients did not differ from the controls. However, we observed a significantly higher frequency of rare CNVs affecting brain related genes, especially deletions, in the patients (OR = 1.98, 95% CI 1.02-3.84; OR = 3.61, 95% CI 1.14-11.41, respectively). Similarly, enrichment-analysis of CNVs gene content, performed with three independent methods, confirmed significant clustering of predefined genes involved in synaptic/brain related functional pathways in the patients but not in the controls. In two patients we detected de-novo CNVs encompassing genes previously associated with different neurodevelopmental disorders (NRXN1, ANKS1B, UHRF1BP1).Our results further strengthen the role of small rare CNVs, particularly deletions, as susceptibility factors for paediatric OCD.
EVALuna2:9389

High stroma T-cell infiltration is associated with better survival in stage pT1 bladder cancer - Hülsen, Sabine; Lippolis, Eleonora; Ferrazzi, Fulvia; Otto, Wolfgang; Distel, Luitpold; Fietkau, Rainer; Denzinger, Stefan; Breyer, Johannes; Burger, Maximilian; Bertz, Simone; Eckstein, Markus; Ebner, Annette; et al. (International Journal of Molecular Sciences, 2020)
Stage pT1 bladder cancer (BC) shows highly diverse outcomes. Predictive markers are required to stratify patients for personalized treatment. The present study aimed to validate immune response quantification as a prognostic marker. Patients with pT1 BC (n = 167) treated by transurethral resection of the bladder (TURB) were enrolled. Formaldehyde-fixed paraffin-embedded material was stained for CD3 and CD8. Corresponding T cells were counted in three regions with the highest immune response. Numbers of tertiary lymphoid structures (TLS) and lymphocyte aggregates (LA) were quantified. High CD3+ stroma T-cell infiltration was associated with improved survival (p = 0.045), especially in the G3 subgroup (p = 0.01). Cluster with higher immune response showed less recurrence (p = 0.034) and favorable overall survival (OS) (p = 0.019). In contrast, higher CD3+ and CD8+ tumor T-cell infiltration seemed to have a negative impact on prognosis. TLS and LA were more frequently observed in G3 tumors, indicating an increased antitumoral immune response. We proved the role of immune cell infiltration and showed that higher infiltration numbers of CD3+ (not CD8+) lymphocytes in the stroma are associated with favorable outcome. Immune cell quantification could be used as a marker to help stratify patients’ risk and therefore, to optimize patients’ management and follow-up examination as well as possible therapies.
CRIS-Team Scopus Importer:2020-11-20
Keywords: CD8; Immunoscore; Progression; PT1 bladder cancer; Survival; Tumor-infiltrating lymphocytes (TILs); CD3

Histopathological proof of the pathogenicity of a rare GFAP mutation in a patient with flaccid paraparesis - Brackmann, Florian; Coras, Roland; Rössler, Karl; Kraus, Cornelia; Rompel, Oliver; Trollmann, Regina (Brain & Development, 2017)
Infantile Alexander disease is a rare progressive leukodystrophy caused by autosomal dominant mutations in the (GFAP) gene typically presenting with psychomotor retardation, progressive macrocephaly and refractory epilepsy. Neuroradiological hallmarks are extensive white matter lesions with frontal preponderance as well as signal intensity changes of basal ganglia and medulla oblongata with variable contrast enhancement. Here, we report an atypical manifestation in a 21-month-old boy presenting with flaccid paraparesis and areflexia. Cognitive, visual as well as fine motor skills and muscular strength of the upper extremities were appropriate for age. Weight and height as well as head circumference were within normal range. Clinical or electroencephalographic signs of seizures were absent. Cranial MRI demonstrated bifrontal cystic tumorous lesions with partial contrast rims, as well as space-occupying focal lesions of the caudate nuclei. Spinal MRI revealed swelling of the lumbar and cervical spinal cord. CSF and blood chemistry showed normal results. Histopathology of a subcortical lesion showed large amounts of Rosenthal fibers and protein droplets characteristic of Alexander disease. Sequencing detected a heterozygous mutation of the GFAP gene (c.205G > A; p.(Glu69Lys)) that has been reported before as probably pathogenetic in another case of lower spinal involvement. This well documented case draws attention to atypical spinal manifestations of Alexander disease and gives histopathological proof of the pathogenetic role of a rare GFAP mutation with marked spinal involvement.
EVALuna2:9396

HLA-G and HLA-F protein isoform expression in breast cancer patients receiving neoadjuvant treatment - Würfel, Franziska; Hübner, Hanna; Häberle, Lothar; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Hack, Carolin; Wunderle, Marius; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; Ekici, Arif Bülent; et al. (Scientific Reports, 2020)
The immunosuppressive human leukocyte antigens HLA-G and HLA-F are expressed on trophoblast and malignant cells. Four membrane-bound and three soluble HLA-G protein isoforms have been described, which have different immunosuppressive potentials. HLA-F has three transcript variants, resulting in three different protein isoforms. The aim of this study was to evaluate the prognostic and predictive value of HLA-G and HLA-F protein isoform expression patterns in patients with breast cancer. Core biopsies were taken at diagnosis in patients with HER2+ (n = 28), luminal B-like (n = 49) and triple-negative (n = 38) breast cancers who received neoadjuvant chemotherapy. Expression levels of HLA-F and -G were correlated with the pathological complete response (pCR). Protein expression was determined by Western blot analysis, using two antibodies for each HLA, specific for different isoforms. The protein expression of HLA isoforms did not significantly differ between breast cancer subtypes. However, some initial indications were found for an association between the soluble HLA-G6 protein isoform and pCR in HER2+ breast cancer. The study provides preliminary evidence for the evaluation of HLA-G isoform expression, in particular HLA-G6, as a possible new marker for pCR in HER2+ breast cancer.
CRIS-Team Scopus Importer:2020-10-02

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Human Induced Pluripotent Stem Cell-Derived Pericytes as Scalable and Editable Source to Study Direct Lineage Reprogramming Into Induced Neurons - Menon, Radhika; Petrucci, Linda; Lohrer, Benjamin; Zhang, Jingzhong; Schulze, Markus; Schichor, Christian; Winner, Beate; Winkler, Jürgen; Riemenschneider, Markus J.; Kühn, Ralf; Falk, Sven; Karow, Marisa (Cellular Reprogramming, 2023)
Studying human somatic cell-to-neuron conversion using primary brain-derived cells as starting cell source is hampered by limitations and variations in human biopsy material. Thus, delineating the molecular variables that allow changing the identity of somatic cells, permit adoption of neuronal phenotypes, and foster maturation of induced neurons (iNs) is challenging. Based on our previous results that pericytes derived from the adult human cerebral cortex can be directly converted into iNs (Karow et al., 2018; Karow et al., 2012), we here introduce human induced pluripotent stem cell (hiPSC)-derived pericytes (hiPSC-pericytes) as a versatile and more uniform tool to study the pericyte-to-neuron conversion process. This strategy enables us to derive scalable cell numbers and allows for engineering of the starting cell population such as introducing reporter tools before differentiation into hiPSC-pericytes and subsequent iN conversion. Harvesting the potential of this approach, we established hiPSC-derived human-human neuronal cocultures that not only allow for independent manipulation of each coculture partner but also resulted in morphologically more mature iNs. In summary, we exploit hiPSC-based methods to facilitate the analysis of human somatic cell-to-neuron conversion.
CRIS-Team Scopus Importer:2023-11-03
Keywords: direct lineage reprogramming; induced neurons; organoids; pericytes

Human-induced pluripotent stem cells pave the road for a better understanding of motor neuron disease - Winner, Beate; Marchetto, Maria C.; Winkler, Jürgen; Gage, Fred H. (Human Molecular Genetics, 2014)
While motor neuron diseases are currently incurable, induced pluripotent stem cell research has uncovered some disease-relevant phenotypes. We will discuss strategies to model different aspects of motor neuron disease and the specific neurons involved in the disease. We will then describe recent progress to investigate common forms of motor neuron disease: amyotrophic lateral sclerosis, hereditary spastic paraplegia and spinal muscular atrophy.
EVALuna2:25333

Human sensory neurons derived from pluripotent stem cells for disease modelling and personalized medicine - Lampert, Angelika; Bennett, David L.; McDermott, Lucy A.; Neureiter, Anika; Eberhardt, Esther; Winner, Beate; Zenke, Martin (Neurobiology of pain (Cambridge, Mass.), 2020)
In this concise Mini-Review we will summarize ongoing developments of new techniques to study physiology and pathophysiology of the peripheral sensory nervous system in human stem cell derived models. We will focus on recent developments of reprogramming somatic cells into induced pluripotent stem cells, neural differentiation towards neuronal progenitors and human sensory neurons. We will sum up the high potential of this new technique for disease modelling of human neuropathies with a focus on genetic pain syndromes, such as gain- and loss-of-function mutations in voltage-gated sodium channels. The stem cell derived human sensory neurons are used for drug testing and we will summarize their usefulness for individualized treatment identification in patients with neuropathic pain. The review will give an outlook on potential application of this technique as companion diagnostics and for personalized medicine.
Created from Fastlane, Scopus look-up
Keywords: Disease modelling; iPSC; Pain; Peripheral neuron; Stem cell differentiation

Human SPG11 cerebral organoids reveal cortical neurogenesis impairment - Pérez-Brangulí, Francesc; Buchsbaum, Isabel; Pozner, Tatyana; Regensburger, Martin; Fan, Wenqiang; Schray, Annika; Börstler, Tom; Mishra, Himanshu Kumar; Gräf, Daniela; Kohl, Zacharias; Winkler, Jürgen; Berninger, Benedikt; et al. (Human Molecular Genetics, 2018)
SPG11 linked hereditary spastic paraplegia is a complex monogenic neurodegenerative disease that in addition to spastic paraplegia is characterized by childhood onset cognitive impairment, thin corpus callosum and enlarged ventricles. We have previously shown impaired proliferation of SPG11 neural progenitor cells (NPCs). For delineation of potential defect in SPG11 brain development we employ 2D culture systems and 3D human brain organoids derived from SPG11 patients' iPSC and controls. We reveal that an increased rate of asymmetric divisions of neural progenitor cells leads to proliferation defect, causing premature neurogenesis. Correspondingly, SPG11 organoids appeared smaller than controls and had larger ventricles as well as thinner germinal wall. Premature neurogenesis and organoid size were rescued by GSK3-inhibititors including the FDA-approved tideglusib. These findings shed light on the neurodevelopmental mechanisms underlying disease pathology.
EVALuna2:36370

Hyperandrogenemia and high prolactin in congenital utero-vaginal aplasia patients - Oppelt, Patricia; Mueller, Andreas; Stephan, Liana; Dittrich, Ralf; Lermann, Johannes; Büttner, Christian; Ekici, Arif Bülent; Conzelmann, Gabi; Seeger, Harald; Schoeller, Dorit; Rall, Katharina; Beckmann, Matthias; et al. (Reproduction, 2017)
Patients with the Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) have a congenital utero-vaginal cervical aplasia, but normal or hypoplastic adnexa and develop with normal female phenotype. Some reports mostly demonstrated regular steroid hormone levels in small MRKH cohorts including single MRKH patients with hyperandrogenemia and a clinical presentationof hirsutism and acne has also been shown. Genetically a correlation of WNT4 mutations with singular MRKH patients and hyperandrogenemia was noted. This study analyzed the hormone status of 215 MRKH patients by determining the levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), estradiol, 17-OH progesterone, testosterone, dehydroepiandrosterone sulfate (DHEAS), sex hormone-binding globulin (SHBG) and prolactin to determine the incidence of hyperandrogenemia and hyperprolactinemia in MRKH patients. Additional calculations and a ratio of free androgen index and biologically active testosterone revealed a hyperandrogenemia rate of 48.3%, hyperprolactinemia of 9.8% and combined hyperandrogenemia and hyperprolactinemia of 4.2% in MRKH patients. The rates of hirsutism, acne and especially polycystic ovary syndrome (PCOS) were in the normal range of the population and showed no correlation with hyperandrogenemia. A weekly hormone assessment over 30 days comparing 5 controls and 7 MRKH patients revealed high androgen and prolactin, but lower LH/FSH and SHBG levels with MRKH patients. The sequencing of WNT4, WNT5A, WNT7A and WNT9B demonstrated no significant mutations correlating with hyperandrogenemia. Taken together, this study shows that over 52% of MRKH patients have hyperandrogenemia without clinical presentation and 14% hyperprolactinemia, which appeals for general hormone assessment and adjustments of MRKH patients.
EVALuna2:9378

Hypomorphic Pathogenic Variants in TAF13 Are Associated with Autosomal-Recessive Intellectual Disability and Microcephaly - Tawamie, Hasan; Martianov, Igor; Wohlfahrt, Natalie; Buchert, Rebecca; Mengus, Gabrielle; Uebe, Steffen; Janiri, Luigi; Hirsch, Franz Wolfgang; Schumacher, Johannes; Ferrazzi, Fulvia; Sticht, Heinrich; Reis, André; et al. (American Journal of Human Genetics, 2017)
In two independent consanguineous families each with two children affected by mild intellectual disability and microcephaly, we identified two homozygous missense variants (c.119T>A [p.Met40Lys] and c.92T>A [p.Leu31His]) in TATA-box-binding-protein-associated factor 13 (TAF13). Molecular modeling suggested a pathogenic effect of both variants through disruption of the interaction between TAF13 and TAF11. These two proteins form a histone-like heterodimer that is essential for their recruitment into the general RNA polymerase II transcription factor IID (TFIID) complex. Co-immunoprecipitation in HeLa cells transfected with plasmids encoding TAF11 and TAF13 revealed that both variants indeed impaired formation of the TAF13-TAF11 heterodimer, thus confirming the protein modeling analysis. To further understand the functional role of TAF13, we performed RNA sequencing of neuroblastoma cell lines upon TAF13 knockdown. The transcriptional profile showed significant deregulation of gene expression patterns with an emphasis on genes related to neuronal and skeletal functions and those containing E-box motives in their promoters. Here, we expand the spectrum of TAF-associated phenotypes and highlight the importance of TAF13 in neuronal functions.
EVALuna2:9362

Identification and characterization of a GLMN splice site variant in a family with glomuvenous malformations - Skowronek, Dariush; Hebebrand, Moritz; Erber, Ramona; Agaimy, Abbas; Zweier, Christiane; Felbor, Ute; Rath, Matthias (European Journal of Dermatology, 2020)
CRIS-Team Scopus Importer:2020-06-26

Identification and characterization of a GLMN splice site variant in a three-generation-family with glomuvenous malformations - Skowronek, D.; Hebebrand, Moritz; Erber, Ramona; Agaimy, Abbas; Zweier, Christiane; Felbor, U.; Rath, M. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Identification and characterization of novel associations in the CASP8/ALS2CR12 region on chromosome 2 with breast cancer risk - Lin, Wei-Yu; Camp, Nicola J.; Ghoussaini, Maya; Beesley, Jonathan; Michailidou, Kyriaki; Hopper, John L.; Apicella, Carmel; Southey, Melissa C.; Stone, Jennifer; Schmidt, Marjanka K.; Broeks, Annegien; Van'T Veer, Laura J.; et al. (Human Molecular Genetics, 2015)
Previous studies have suggested that polymorphisms in CASP8 on chromosome 2 are associated with breast cancer risk. To clarify the role of CASP8 in breast cancer susceptibility, we carried out dense genotyping of this region in the Breast Cancer Association Consortium (BCAC). Single-nucleotide polymorphisms (SNPs) spanning a 1 Mb region around CASP8 were genotyped in 46 450 breast cancer cases and 42 600 controls of European origin from 41 studies participating in the BCAC as part of a custom genotyping array experiment (iCOGS). Missing genotypes and SNPs were imputed and, after quality exclusions, 501 typed and 1232 imputed SNPs were included in logistic regression models adjusting for study and ancestry principal components. The SNPs retained in the final model were investigated further in data from nine genome-wide association studies (GWAS) comprising in total 10 052 case and 12 575 control subjects. The most significant association signal observed in European subjects was for the imputed intronic SNP rs1830298 in ALS2CR12 (telomeric to CASP8), with per allele odds ratio and 95% confidence interval [OR (95% confidence interval, CI)] for the minor allele of 1.05 (1.03-1.07), P = 1 × 10(-5). Three additional independent signals from intronic SNPs were identified, in CASP8 (rs36043647), ALS2CR11 (rs59278883) and CFLAR (rs7558475). The association with rs1830298 was replicated in the imputed results from the combined GWAS (P = 3 × 10(-6)), yielding a combined OR (95% CI) of 1.06 (1.04-1.08), P = 1 × 10(-9). Analyses of gene expression associations in peripheral blood and normal breast tissue indicate that CASP8 might be the target gene, suggesting a mechanism involving apoptosi
EVALuna2:9254

Identification of 12 new susceptibility loci for different histotypes of epithelial ovarian cancer - Phelan, Catherine M.; Kuchenbaecker, Karoline B.; Tyrer, Jonathan P.; Kar, Siddhartha P.; Lawrenson, Kate; Winham, Stacey J.; Dennis, Joe; Pirie, Ailith; Riggan, Marjorie J.; Chornokur, Ganna; Earp, Madalene A.; Lyra, Paulo C.; et al. (Nature Genetics, 2017)
To identify common alleles associated with different histotypes of epithelial ovarian cancer (EOC), we pooled data from multiple genome-wide genotyping projects totaling 25,509 EOC cases and 40,941 controls. We identified nine new susceptibility loci for different EOC histotypes: six for serous EOC histotypes (3q28, 4q32.3, 8q21.11, 10q24.33, 18q11.2 and 22q12.1), two for mucinous EOC (3q22.3 and 9q31.1) and one for endometrioid EOC (5q12.3). We then performed meta-analysis on the results for high-grade serous ovarian cancer with the results from analysis of 31,448 BRCA1 and BRCA2 mutation carriers, including 3,887 mutation carriers with EOC. This identified three additional susceptibility loci at 2q13, 8q24.1 and 12q24.31. Integrated analyses of genes and regulatory biofeatures at each locus predicted candidate susceptibility genes, including OBFC1, a new candidate susceptibility gene for low-grade and borderline serous EOC.
EVALuna2:9375

Identification of four novel susceptibility loci for oestrogen receptor negative breast cancer - Couch, Fergus J.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Mendoza-Fandino, Gustavo A.; Nord, Silje; Lilyquist, Janna; Olswold, Curtis; Hallberg, Emily; Agata, Simona; Ahsan, Habibul; Aittomaeki, Kristiina; Ambrosone, Christine; et al. (Nature Communications, 2016)
Common variants in 94 loci have been associated with breast cancer including 15 loci with genome-wide significant associations (P<5 × 10(-8)) with oestrogen receptor (ER)-negative breast cancer and BRCA1-associated breast cancer risk. In this study, to identify new ER-negative susceptibility loci, we performed a meta-analysis of 11 genome-wide association studies (GWAS) consisting of 4,939 ER-negative cases and 14,352 controls, combined with 7,333 ER-negative cases and 42,468 controls and 15,252 BRCA1 mutation carriers genotyped on the iCOGS array. We identify four previously unidentified loci including two loci at 13q22 near KLF5, a 2p23.2 locus near WDR43 and a 2q33 locus near PPIL3 that display genome-wide significant associations with ER-negative breast cancer. In addition, 19 known breast cancer risk loci have genome-wide significant associations and 40 had moderate associations (P<0.05) with ER-negative disease. Using functional and eQTL studies we implicate TRMT61B and WDR43 at 2p23.2 and PPIL3 at 2q33 in ER-negative breast cancer aetiology. All ER-negative loci combined account for 11% of familial relative risk for ER-negative disease and may contribute to improved ER-negative and BRCA1 breast cancer risk prediction.
EVALuna2:9317

Identification of new genetic susceptibility Loci for breast cancer through consideration of gene-environment interactions - Schoeps, Anja; Rudolph, Anja; Seibold, Petra; Dunning, Alison M.; Milne, Roger L.; Bojesen, Stig E.; Swerdlow, Anthony; Andrulis, Irene; Brenner, Hermann; Behrens, Sabine; Orr, Nicholas; Jones, Michael; et al. (Genetic Epidemiology, 2014)
Genes that alter disease risk only in combination with certain environmental exposures may not be detected in genetic association analysis. By using methods accounting for gene-environment (G × E) interaction, we aimed to identify novel genetic loci associated with breast cancer risk. Up to 34,475 cases and 34,786 controls of European ancestry from up to 23 studies in the Breast Cancer Association Consortium were included. Overall, 71,527 single nucleotide polymorphisms (SNPs), enriched for association with breast cancer, were tested for interaction with 10 environmental risk factors using three recently proposed hybrid methods and a joint test of association and interaction. Analyses were adjusted for age, study, population stratification, and confounding factors as applicable. Three SNPs in two independent loci showed statistically significant association: SNPs rs10483028 and rs2242714 in perfect linkage disequilibrium on chromosome 21 and rs12197388 in ARID1B on chromosome 6. While rs12197388 was identified using the joint test with parity and with age at menarche (P-values = 3 × 10(-07) ), the variants on chromosome 21 q22.12, which showed interaction with adult body mass index (BMI) in 8,891 postmenopausal women, were identified by all methods applied. SNP rs10483028 was associated with breast cancer in women with a BMI below 25 kg/m(2) (OR = 1.26, 95% CI 1.15-1.38) but not in women with a BMI of 30 kg/m(2) or higher (OR = 0.89, 95% CI 0.72-1.11, P for interaction = 3.2 × 10(-05) ). Our findings confirm comparable power of the recent methods for detecting G × E interaction and the utility of using G × E interaction analyses to identify new susceptibility loci.
EVALuna2:9203

Identification of nine new susceptibility loci for endometrial cancer - O'Mara, Tracy A.; Glubb, Dylan M.; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Bolla, Manjeet K.; Brauch, Hiltrud; Brenner, Hermann; et al. (Nature Communications, 2018)
Endometrial cancer is the most commonly diagnosed cancer of the female reproductive tract in developed countries. Through genome-wide association studies (GWAS), we have previously identified eight risk loci for endometrial cancer. Here, we present an expanded meta-analysis of 12,906 endometrial cancer cases and 108,979 controls (including new genotype data for 5624 cases) and identify nine novel genome-wide significant loci, including a locus on 12q24.12 previously identified by meta-GWAS of endometrial and colorectal cancer. At five loci, expression quantitative trait locus (eQTL) analyses identify candidate causal genes; risk alleles at two of these loci associate with decreased expression of genes, which encode negative regulators of oncogenic signal transduction proteins (SH2B3 (12q24.12) and NF1 (17q11.2)). In summary, this study has doubled the number of known endometrial cancer risk loci and revealed candidate causal genes for future study.
EVALuna2:34618

Identification of novel candidate genes for idiopathic short stature using whole exome sequencing - Thiel, Christian; Hauer, Nadine; Vogl, C.; Ahmadian, R.; Dhandapany, P. S.; Popp, Bernt; Buettner, C.; Ube, S.; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Identification of novel genetic markers of breast cancer survival - Guo, Qi; Schmidt, Marjanka K.; Kraft, Peter; Canisius, Sander; Chen, Constance; Khan, Sofia; Tyrer, Jonathan; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Michailidou, Kyriaki; Lush, Michael; et al. (Journal of the National Cancer Institute, 2015)
Survival after a diagnosis of breast cancer varies considerably between patients, and some of this variation may be because of germline genetic variation. We aimed to identify genetic markers associated with breast cancer-specific survival.We conducted a large meta-analysis of studies in populations of European ancestry, including 37954 patients with 2900 deaths from breast cancer. Each study had been genotyped for between 200000 and 900000 single nucleotide polymorphisms (SNPs) across the genome; genotypes for nine million common variants were imputed using a common reference panel from the 1000 Genomes Project. We also carried out subtype-specific analyses based on 6881 estrogen receptor (ER)-negative patients (920 events) and 23059 ER-positive patients (1333 events). All statistical tests were two-sided.We identified one new locus (rs2059614 at 11q24.2) associated with survival in ER-negative breast cancer cases (hazard ratio [HR] = 1.95, 95% confidence interval [CI] = 1.55 to 2.47, P = 1.91 x 10(-8)). Genotyping a subset of 2113 case patients, of which 300 were ER negative, provided supporting evidence for the quality of the imputation. The association in this set of case patients was stronger for the observed genotypes than for the imputed genotypes. A second locus (rs148760487 at 2q24.2) was associated at genome-wide statistical significance in initial analyses; the association was similar in ER-positive and ER-negative case patients. Here the results of genotyping suggested that the finding was less robust.This is currently the largest study investigating genetic variation associated with breast cancer survival. Our results have potential clinical implications, as they confirm that germline genotype can provide prognostic information in addition to standard tumor prognostic factors.
EVALuna2:9260

Identification of six new susceptibility loci for invasive epithelial ovarian cancer - Kuchenbaecker, Karoline B.; Ramus, Susan J.; Tyrer, Jonathan; Lee, Andrew; Shen, Howard C.; Beesley, Jonathan; Lawrenson, Kate; Mcguffog, Lesley; Healey, Sue; Lee, Janet M.; Spindler, Tassja J.; Lin, Yvonne G.; et al. (Nature Genetics, 2015)
Genome-wide association studies (GWAS) have identified 12 epithelial ovarian cancer (EOC) susceptibility alleles. The pattern of association at these loci is consistent in BRCA1 and BRCA2 mutation carriers who are at high risk of EOC. After imputation to 1000 Genomes Project data, we assessed associations of 11 million genetic variants with EOC risk from 15,437 cases unselected for family history and 30,845 controls and from 15,252 BRCA1 mutation carriers and 8,211 BRCA2 mutation carriers (3,096 with ovarian cancer), and we combined the results in a meta-analysis. This new study design yielded increased statistical power, leading to the discovery of six new EOC susceptibility loci. Variants at 1p36 (nearest gene, WNT4), 4q26 (SYNPO2), 9q34.2 (ABO) and 17q11.2 (ATAD5) were associated with EOC risk, and at 1p34.3 (RSPO1) and 6p22.1 (GPX6) variants were specifically associated with the serous EOC subtype, all with P < 5 × 10(-8). Incorporating these variants into risk assessment tools will improve clinical risk predictions for BRCA1 and BRCA2 mutation carriers.
EVALuna2:9273

Identification of ten variants associated with risk of estrogen-receptor-negative breast cancer - Milne, Roger L.; Kuchenbaecker, Karoline B.; Michailidou, Kyriaki; Beesley, Jonathan; Kar, Siddhartha; Lindstrom, Sara; Hui, Shirley; Lemacon, Audrey; Soucy, Penny; Dennis, Joe; Jiang, Xia; Rostamianfar, Asha; et al. (Nature Genetics, 2017)
Most common breast cancer susceptibility variants have been identified through genome-wide association studies (GWAS) of predominantly estrogen receptor (ER)-positive disease. We conducted a GWAS using 21,468 ER-negative cases and 100,594 controls combined with 18,908 BRCA1 mutation carriers (9,414 with breast cancer), all of European origin. We identified independent associations at P < 5 × 10-8 with ten variants at nine new loci. At P < 0.05, we replicated associations with 10 of 11 variants previously reported in ER-negative disease or BRCA1 mutation carrier GWAS and observed consistent associations with ER-negative disease for 105 susceptibility variants identified by other studies. These 125 variants explain approximately 16% of the familial risk of this breast cancer subtype. There was high genetic correlation (0.72) between risk of ER-negative breast cancer and breast cancer risk for BRCA1 mutation carriers. These findings may lead to improved risk prediction and inform further fine-mapping and functional work to better understand the biological basis of ER-negative breast cancer.
EVALuna2:9391

Identification of the deregulated NEK1 protein network in skeletal ciliopathies - Vogl, C.; Keßler, Kristin; Gießl, Andreas; Kirchner, P.; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Identification of Two Genetic Loci Associated with Leukopenia after Chemotherapy in Patients with Breast Cancer - Fasching, Peter; Liu, Duan; Scully, Steve; Ingle, James N.; Lyra, Paulo C.; Rack, Brigitte; Hein, Alexander; Ekici, Arif Bülent; Reis, André; Schneeweiss, Andreas; Tesch, Hans; Fehm, Tanja N.; et al. (Clinical Cancer Research, 2022)
Purpose: To identify molecular predictors of grade 3/4 neutropenic or leukopenic events (NLE) after chemotherapy using a genome-wide association study (GWAS). Experimental Design: A GWAS was performed on patients in the phase III chemotherapy study SUCCESS-A (n = 3,322). Genotyping was done using the Illumina HumanOmniExpress-12v1 array. Findings were functionally validated with cell culture models and the genotypes and gene expression of possible causative genes were correlated with clinical treatment response and prognostic outcomes. Results: One locus on chromosome 16 (rs4784750; NLRC5; P = 1.56E-8) and another locus on chromosome 13 (rs16972207; TNFSF13B; P = 3.42E-8) were identified at a genome-wide significance level. Functional validation revealed that expression of these two genes is altered by genotype-dependent and chemotherapy-dependent activity of two transcription factors. Genotypes also showed an association with disease-free survival in patients with an NLE. Conclusions: Two loci in NLRC5 and TNFSF13B are associated with NLEs. The involvement of theMHCI regulator NLRC5 implies the possible involvement of immuno-oncological pathways.
CRIS-Team Scopus Importer:2022-08-19

Identifying Genes that Underlie Exfoliation Syndrome using Genetically Determined Gene Expression - Hirbo, Jibril; Pasutto, Francesca; Pawar, Priyanka; Sealock, Julia; Evans, Patrick; Gamazon, Eric; Tao, Ran; Reis, Andre; Berner, Daniel; Schlötzer-Schrehardt, Ursula; Brantley, Milam A.; Khor, Chiea Chuen; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2016)
We analysed the influence of rhinovirus (RV) in nasopharyngeal fluid (NPF) on type I and III interferon (IFN) responses (e.g. IFN-? and IFN -: ?) and their signal transduction, at baseline and during disease exacerbation, in cohorts of pre-school children with and without asthma.At the time of recruitment into the Europe-wide study PreDicta, and during symptoms, NPF was collected and the local RV colonisation was analysed. Peripheral blood mononuclear cells (PBMCs) were challenged in vitro with RV or not. RNA was analysed by quantitative real-time PCR and gene arrays. Serum was analysed with ELISA for IFNs and C-reactive protein.We found that PBMCs from asthmatic children infected in vitro with the RV1b serotype upregulated MYD88, IRF1, STAT1 and STAT2 mRNA, whereas MYD88, IRF1, STAT1 and IRF9 were predominantly induced in control children. Moreover, during symptomatic visits because of disease exacerbation associated with RV detection in NPF, IFN-? production was found increased, while IFN-? secretion was already induced by RV in asthmatic children at baseline.During asthma exacerbations associated with RV, asthmatic children can induce IFN-? secretion, indicating a hyperactive immune response to repeated respiratory virus infection.
EVALuna2:9365

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma - Bergauer, Annika; Sopel, Nina; Kross, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna:34061

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

IL-3 receptor signalling suppresses chronic intestinal inflammation by controlling mechanobiology and tissue egress of regulatory T cells. - Ullrich, Karen; Derdau, Julia; Baltes, Carsten; Battistella, Alice; Rosso, Gonzalo; Uderhardt, Stefan; Schulze, Lisa; Liu, Lijuan; Dedden, Mark; Spocinska, Marta; Kainka, Lucina; Kubánková, Markéta; et al. (Gut, 2023)
IL-3 has been reported to be involved in various inflammatory disorders, but its role in inflammatory bowel disease (IBD) has not been addressed so far. Here, we determined IL-3 expression in samples from patients with IBD and studied the impact of Il3 or Il3r deficiency on T cell-dependent experimental colitis. We explored the mechanical, cytoskeletal and migratory properties of Il3r -/- and Il3r +/+ T cells using real-time deformability cytometry, atomic force microscopy, scanning electron microscopy, fluorescence recovery after photobleaching and in vitro and in vivo cell trafficking assays. We observed that, in patients with IBD, the levels of IL-3 in the inflamed mucosa were increased. In vivo, experimental chronic colitis on T cell transfer was exacerbated in the absence of Il-3 or Il-3r signalling. This was attributable to Il-3r signalling-induced changes in kinase phosphorylation and actin cytoskeleton structure, resulting in increased mechanical deformability and enhanced egress of Tregs from the inflamed colon mucosa. Similarly, IL-3 controlled mechanobiology in human Tregs and was associated with increased mucosal Treg abundance in patients with IBD. Collectively, our data reveal that IL-3 signaling exerts an important regulatory role at the interface of biophysical and migratory T cell features in intestinal inflammation and suggest that this might be an interesting target for future intervention.
EVALuna2:539503

IL-7 Abrogates the Immunosuppressive Function of Human Double-Negative T Cells by Activating Akt/mTOR Signaling - Allgäuer, Andrea; Schreiner, Elisabeth; Ferrazzi, Fulvia; Ekici, Arif Bülent; Gerbitz, Armin; Mackensen, Andreas; Voelkl, Simon (Journal of Immunology, 2015)
Recently, a novel subset of TCR??(+) CD4(-) CD8(-) double-negative (DN) T cells was described to suppress immune responses in both mice and humans. Moreover, in murine models, infusion and/or activation of DN T cells specifically suppressed alloreactive T cells and prevented the development of graft-versus-host disease after allogeneic hematopoietic stem cell transplantation. We demonstrated that human DN T cells, like their murine counterparts, are highly potent suppressor cells of both CD4(+) and CD8(+) T cell responses. After hematopoietic stem cell transplantation and other lymphopenic conditions, IL-7 plays an important role in the reconstitution, survival, and homeostasis of the T cell compartment. Because IL-7 was shown to interfere with T cell functionality, we asked whether IL-7 affects the functionality of human DN T cells. Intriguingly, IL-7 diminished the suppressive activity of DN T cells toward allogeneic CD4(+) effector T cells. Of interest, our studies revealed that IL-7 activates the Akt/mechanistic target of rapamycin (mTOR) pathway in human DN T cells. Importantly, selective inhibition of the protein kinases Akt or mTOR reversed the IL-7 effect, thereby restoring the functionality of DN T cells, whereas inhibition of other central T cell signaling pathways did not. Further analyses suggest that the IL-7/Akt/mTOR signaling cascade downregulates anergy-associated genes and upregulates activation- and proliferation-associated factors that may be crucial for DN T cell functionality. These findings indicate that IL-7 and Akt/mTOR signaling are critical factors for the suppressive capacity of DN T cells. Targeting of these pathways by pharmacological agents may restore and/or enhance DN T cell functionality in graft-versus-host disease.
EVALuna2:9259

IMPACT OF INTERLEUKIN 17 BLOCKING AGENT ON CLINICAL OUTCOME IN SAPHO PATIENTS - Assmann, Gunter; Bittenbring, Joerg Thomas; Wagner, Annette D.; Schreiber, Martin; Christofyllakis, Konstantinos; Hüffmeier, Ulrike; Pfoehler, Claudia; Neumann, Frank (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Impact of Microbiome–Brain Communication on Neuroinflammation and Neurodegeneration - Stolzer, Iris; Scherer, Eveline; Süß, Patrick; Rothhammer, Veit; Winner, Beate; Neurath, Markus; Günther, Claudia (International Journal of Molecular Sciences, 2023)
The gut microbiome plays a pivotal role in maintaining human health, with numerous studies demonstrating that alterations in microbial compositions can significantly affect the development and progression of various immune-mediated diseases affecting both the digestive tract and the central nervous system (CNS). This complex interplay between the microbiota, the gut, and the CNS is referred to as the gut–brain axis. The role of the gut microbiota in the pathogenesis of neurodegenerative diseases has gained increasing attention in recent years, and evidence suggests that gut dysbiosis may contribute to disease development and progression. Clinical studies have shown alterations in the composition of the gut microbiota in multiple sclerosis patients, with a decrease in beneficial bacteria and an increase in pro-inflammatory bacteria. Furthermore, changes within the microbial community have been linked to the pathogenesis of Parkinson’s disease and Alzheimer’s disease. Microbiota–gut–brain communication can impact neurodegenerative diseases through various mechanisms, including the regulation of immune function, the production of microbial metabolites, as well as modulation of host-derived soluble factors. This review describes the current literature on the gut–brain axis and highlights novel communication systems that allow cross-talk between the gut microbiota and the host that might influence the pathogenesis of neuroinflammation and neurodegeneration.
CRIS-Team Scopus Importer:2023-11-03
Keywords: gut–brain-axis; microbial dysbiosis; neurodegenerative diseases

Impact of single nucleotide polymorphisms in the VEGFR2 gene on endothelial cell activation under non‑uniform shear stress - Schacher, Nora; Raaz-Schrauder, Dorette; Pasutto, Francesca; Stumpfe, Florian M.; Tauchi, Miyuki; Dietel, Barbara; Achenbach, Stephan; Urschel, Katharina (International Journal of Molecular Medicine, 2019)
Single nucleotide polymorphisms (SNPs) in vascular endothelial growth factor receptor 2 (VEGFR2) are associated with coronary artery disease, hypertension and myocardial infarction. However, their association with atherosclerosis remains to be fully elucidated. The purpose of the present study was to determine whether SNPs are involved in atherogenesis, by analyzing their impact on human umbilical vein endothelial cells (HUVECs) under laminar and non-uniform shear stress in a well-established in vitro model that simulates shear stress-induced proatherogenic processes at vessel bifurcations. All experiments were performed using freshly isolated HUVECs. Three SNPs in the VEGFR2 gene (rs1870377 T>A, rs2071559 A>G and rs2305948 C>T) were genotyped and the expression levels of VEGFR2 were semi-quantitatively determined using western blotting. Subsequently, the HUVECs were seeded in bifurcating flow‑through cell culture slides and flow (9.6 ml/min) was applied for 19 h, including tumor necrosis factor-α stimulation during the final 2 h of flow. The protein expression levels of VCAM-1, E-selectin and VEGFR2 and the adhesion of THP-1 cells were analyzed in laminar and non-uniform shear stress regions. Data were analyzed for associations with the respective SNPs. The total expression of VEGFR2 was significantly lower under non‑uniform shear stress than under laminar shear stress conditions, independent of the genotype. The expression of VEGFR2 between the different shear stress patterns was not significantly altered by the different SNPs. The expression levels of VCAM-1 and E-selectin were lower in the A/A genotype compared with those in other genotypes in rs1870377 T>A and rs2071559 A>G. In conclusion, the results suggested that SNPs within the VEGFR2 gene have a significant impact on shear stress‑related endothelial activation.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Adhesion molecules; Atherosclerosis; Endothelial dysfunction; Shear stress; Single nucleotide polymorphism; Vascular endothelial growth factor receptor 2

IMPACT OF SINGLE NUCLEOTIDE POLYMORPHISMS RS1870377 A > T AND RS2305948 C > T ON ENDOTHELIAL CELL ACTIVATION UNDER NON-UNIFORM SHEAR STRESS - Urschel, Katharina; Schacher, Nora; Pasutto, Francesca; Achenbach, Stephan; Raaz-Schrauder, Dorette; Schrauder, Michael G.; Stumpfe, Florian; Dietel, Barbara (2017)
EVALuna2:9363

Impact of Siponimod on Enteric and Central Nervous System Pathology in Late-Stage Experimental Autoimmune Encephalomyelitis - Weier, Alicia; Enders, Michael; Kirchner, Philipp; Ekici, Arif Bülent; Bigaud, Marc; Kapitza, Christopher; Wörl, Jürgen; Kuerten, Stefanie (International Journal of Molecular Sciences, 2022)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS). Although immune modulation and suppression are effective during relapsing-remitting MS, secondary progressive MS (SPMS) requires neuroregenerative therapeutic options that act on the CNS. The sphingosine-1-phosphate receptor modulator siponimod is the only approved drug for SPMS. In the pivotal trial, siponimod reduced disease progression and brain atrophy compared with placebo. The enteric nervous system (ENS) was recently identified as an additional autoimmune target in MS. We investigated the effects of siponimod on the ENS and CNS in the experimental autoimmune encephalomyelitis model of MS. Mice with late-stage disease were treated with siponimod, fingolimod, or sham. The clinical disease was monitored daily, and treatment success was verified using mass spectrometry and flow cytometry, which revealed peripheral lymphopenia in siponimod- and fingolimod-treated mice. We evaluated the mRNA expression, ultrastructure, and histopathology of the ENS and CNS. Single-cell RNA sequencing revealed an upregulation of proinflammatory genes in spinal cord astrocytes and ependymal cells in siponimod-treated mice. However, differences in CNS and ENS histopathology and ultrastructural pathology between the treatment groups were absent. Thus, our data suggest that siponimod and fingolimod act on the peripheral immune system and do not have pronounced direct neuroprotective effects.
CRIS-Team Scopus Importer:2022-12-09
Keywords: central nervous system; enteric nervous system; experimental autoimmune encephalomyelitis; fingolimod; multiple sclerosis; siponimod

Impact of Superparamagnetic Iron Oxide Nanoparticles on Vocal Fold Fibroblasts: Cell Behavior and Cellular Iron Kinetics - Poettler, Marina; Fliedner, Anna; Schreiber, Eveline; Janko, Christina; Friedrich, Ralf P.; Bohr, Christopher; Döllinger, Michael; Alexiou, Christoph; Dürr, Stephan (Nanoscale Research Letters, 2017)
PURPOSE: The voice is the most important instrument of communication. Tissue defects in the vocal fold (VF) area lead to serious reduction in quality of life, but thus far, no satisfactory VF implant exists. Therefore, we aim to establish a functional VF implant in a rabbit model by magnetic tissue engineering (MTE) using superparamagnetic iron oxide nanoparticles (SPION). Hence, iron quantification over time as well as cell behavior studies upon SPION treatment are of great importance. METHODS: Rabbit VF fibroblasts (VFF) were treated with different concentrations of SPIONs (20, 40, and 80 μg/cm2), and iron content was examined for up to 40 days using microwave plasma-atom emission spectroscopy. The effects of SPION treatment on VFF (adhesion, spreading, and migration), which are important for the formation of 3D structures, were tested. RESULTS: Cellular SPION quantification revealed that there was no residual iron remaining in VFFs after 40 days. SPIONs had a dose-dependent effect on cell adhesion, with good tolerability observed up to 20 μg/cm2. Migration and spreading were not significantly influenced by SPION treatment up to 80 μg/cm2. DISCUSSION AND CONCLUSION: To develop 3D structures, cell behavior should not be affected by SPION uptake. After 40 days, cells were free of iron as a result of metabolism or rarefication during cell division. Cell functions including adhesion, spreading, and migration were proven to be intact in a dose-dependent manner after SPION treatment, suggesting a safe usage of MTE for voice rehabilitation. Our results thus constitute a solid basis for a successful transfer of this technique into 3D constructs, in order to provide an individual and personalized human VF implant in the future.
EVALuna2:33203

Impact of Swiprosin-1/Efhd2 on Adult Hippocampal Neurogenesis - Regensburger, Martin; Prots, Iryna; Reimer, Dorothea; Brachs, Sebastian; Loskarn, Sandra; Lie, Dieter Chichung; Mielenz, Dirk; Winner, Beate (Stem Cell Reports, 2018)
Swiprosin-1/Efhd2 (Efhd2) is highly expressed in the CNS during development and in the adult. EFHD2 is regulated by Ca2+ binding, stabilizes F-actin, and promotes neurite extension. Previous studies indicated a dysregulation of EFHD2 in human Alzheimer's disease brains. We hypothesized a detrimental effect of genetic ablation of Efhd2 on hippocampal integrity and specifically investigated adult hippocampal neurogenesis. Efhd2 was expressed throughout adult neuronal development and in mature neurons. We observed a severe reduction of the survival of adult newborn neurons in Efhd2 knockouts, starting at the early neuroblast stage. Spine formation and dendrite growth of newborn neurons were compromised in full Efhd2 knockouts, but not upon cell-autonomous Efhd2 deletion. Together with our finding of severe hippocampal tauopathy in Efhd2 knockout mice, these data connect Efhd2 to impaired synaptic plasticity as present in Alzheimer's disease and identify a role of Efhd2 in neuronal survival and synaptic integration in the adult hippocampus.
EVALuna2:34019

Impact of the Voltage-Gated Calcium Channel Antagonist Nimodipine on the Development of Oligodendrocyte Precursor Cells - Enders, Michael; Weier, Alicia; Chunder, Rittika; An, Young; Bremm, Franziska; Feigenspan, Andreas; Büttner, Christian; Ekici, Arif Bülent; Mingardo, Enrico; Odermatt, Benjamin; Kuerten, Stefanie (International Journal of Molecular Sciences, 2023)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS). While most of the current treatment strategies focus on immune cell regulation, except for the drug siponimod, there is no therapeutic intervention that primarily aims at neuroprotection and remyelination. Recently, nimodipine showed a beneficial and remyelinating effect in experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. Nimodipine also positively affected astrocytes, neurons, and mature oligodendrocytes. Here we investigated the effects of nimodipine, an L-type voltage-gated calcium channel antagonist, on the expression profile of myelin genes and proteins in the oligodendrocyte precursor cell (OPC) line Oli-Neu and in primary OPCs. Our data indicate that nimodipine does not have any effect on myelin-related gene and protein expression. Furthermore, nimodipine treatment did not result in any morphological changes in these cells. However, RNA sequencing and bioinformatic analyses identified potential micro (mi)RNA that could support myelination after nimodipine treatment compared to a dimethyl sulfoxide (DMSO) control. Additionally, we treated zebrafish with nimodipine and observed a significant increase in the number of mature oligodendrocytes (* p≤ 0.05). Taken together, nimodipine seems to have different positive effects on OPCs and mature oligodendrocytes.
CRIS-Team Scopus Importer:2023-03-10
Keywords: dihydropyridines; MS; myelination; neuroprotection; nimodipine; Oli-Neu; OPC; zebrafish

Impaired ATF3 signaling involves SNAP25 in SOD1 mutant ALS patients - Yazar, Volkan; Kühlwein, Julia K.; Knehr, Antje; Grozdanov, Veselin; Ekici, Arif Bülent; Ludolph, Albert C.; Danzer, Karin M. (Scientific Reports, 2023)
Epigenetic remodeling is emerging as a critical process for several neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Genetics alone fails to explain the etiology of ALS, the investigation of the epigenome might therefore provide novel insights into the molecular mechanisms of the disease. In this study, we interrogated the epigenetic landscape in peripheral blood mononuclear cells (PBMCs) of familial ALS (fALS) patients with either chromosome 9 open reading frame 72 (C9orf72) or superoxide dismutase 1 (SOD1) mutation and aimed to identify key epigenetic footprints of the disease. To this end, we used an integrative approach that combines chromatin immunoprecipitation targeting H3K27me3 (ChIP-Seq) with the matching gene expression data to gain new insights into the likely impact of blood-specific chromatin remodeling on ALS-related molecular mechanisms. We demonstrated that one of the hub molecules that modulates changes in PBMC transcriptome in SOD1-mutant ALS patients is ATF3, which has been previously reported in an SOD1 G93A mouse model. We also identified potential suppression of SNAP25, with impaired ATF3 signaling in SOD1-mutant ALS blood. Together, our study shed light on the mechanistic underpinnings of SOD1 mutations in ALS.
CRIS-Team Scopus Importer:2023-08-04

Impaired olfactory bulb neurogenesis depends on the presence of human wild-type alpha-synuclein - May, Verena Elisabeth Luise; Nuber, S.; Marxreiter, Franz; Riess, O.; Winner, Beate; Winkler, Jürgen (Neuroscience, 2012)
Synucleinopathies including Parkinson's disease (PD) are characterized by the accumulation of alpha-synuclein (?-syn) within neural cell bodies and their processes. Transgenic mice overexpressing human wild-type or mutant forms of ?-syn under the control of different promoters were developed to analyse the underlying neuropathology of PD. One of the earliest clinical symptoms associated with PD is olfactory impairment. The generation of new neurons persists up to adulthood in mammals, in particular the olfactory bulb (OB). In order to assess this process in relation to ?-syn accumulation, we used mice overexpressing human wild-type ?-syn under the regulatable control (tet-off) of the calcium/calmodulin-dependent protein kinase II?-promoter (CaMKII). We observed a decrease in OB neurogenesis in transgenic animals compared to controls using 5-bromo-2'-deoxyuridine (BrdU) to label newly generated cells (neuron-specific nuclear protein; NeuN). After cessation of transgene expression we detected an increase in newly generated cells both in granular (GCL) and glomerular (GLOM) layers of the OB. This led to a rescue of newly generated neurons (BrdU(+)/NeuN(+)) within the GLOM with a distinct specificity for the dopaminergic subpopulation. In contrast, we did not detect a cell-specific rescue of neuronal cells in the GCL suggesting diverse effects of alpha-synucleinopathy in both interneuronal layers of the OB. Colabelling of BrdU with glial markers showed that a differentiation into neither astroglia nor microglia attributed to the observed phenotype in the GCL. In particular, BrdU(+) particles located within microglial cells were predominantly associated close to the membrane therefore the resembling phagocytosed nuclear fragments of BrdU(+) cells. Thus, our study further contributes insights into ?-syn accumulation as a causative player in the impairment of adult neurogenesis and emphasizes its diverse role in cell renewal of distinct OB cell layers.
EVALuna2:22048

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Increased PD-1 Expression on Circulating T Cells Correlates with Inferior Outcome after Autologous Stem Cell Transplantation - Richter, Silja; Böttcher, Martin; Stoll, Andrej; Zeremski, Vanja; Völkl, Simon; Mackensen, Andreas; Ekici, Arif Bülent; Jacobs, Benedikt; Mougiakakos, Dimitrios (Transplantation and Cellular Therapy, 2024)
High-dose chemotherapy followed by autologous stem cell transplantation (auto-SCT) is a well-established treatment option for multiple myeloma and malignant lymphoma patients. It is able to induce long-term progression-free survival (PFS) in both patient groups and even provide a cure in patients with aggressive lymphoma. However, relapse is common and has been associated with the pace and quality of immunologic reconstitution after transplantation, as well as with immune cell exhaustion and immunometabolic defects. We aimed to analyze the dynamics of the prototypical exhaustion marker PD-1 on immune cells during reconstitution on high-dose chemotherapy followed by auto-SCT and its impact on PFS. We performed a comprehensive analysis of exhaustion and metabolic markers on immune cells from myeloma and lymphoma patients undergoing auto-SCT using flow cytometry and NanoString technologies. The expression levels of PD-1 were increased during early reconstitution after transplantation on T cells and natural killer (NK) cells, as well as on monocytes. However, while PD-1 expression in NK cells and monocytes normalized over time, PD-1 expression on T cells demonstrated a variable course. Of note, lymphoma patients with continuously increasing PD-1 expression on T cells after auto-SCT had an inferior median PFS of only 146 days, whereas the median PFS was not reached in the lymphoma patients without such a PD-1 expression pattern. T cells from patients with increased PD-1 expression after auto-SCT exhibited an immunometabolic (over)activation and exhausted phenotype compared to T cells from patients with a low PD-1 expression after transplantation, including higher levels of the glycolytic pacemaker enzyme hexokinase 2 and the inhibitory receptor CTLA-4. In addition, proliferating Ki-67+ T cells were more abundant in patients with high PD-1 expression on T cells compared to those with low expression after auto-SCT (11.9% versus 4.2%). PD-1 expression on T cells might serve as an adverse biomarker for lymphoma patients undergoing auto-SCT; however, further validation by larger prospective studies is required.
CRIS-Team Scopus Importer:2024-04-12
Keywords: auto-SCT; exhaustion; PD-1; T cells

In-depth characterisation of a cohort of individuals with missense and loss-of-function variants disrupting FOXP2 - Morison, Lottie D.; Meffert, Elisabeth; Stampfer, Miriam; Steiner-Wilke, Irene; Vollmer, Brigitte; Schulze, Katrin; Briggs, Tracy; Braden, Ruth; Vogel, Adam; Thompson-Lake, Daisy; Patel, Chirag; Blair, Edward; et al. (Journal of Medical Genetics, 2022)
BackgroundHeterozygous disruptions of FOXP2 were the first identified molecular cause for severe speech disorder: childhood apraxia of speech (CAS), and yet few cases have been reported, limiting knowledge of the condition. MethodsHere we phenotyped 28 individuals from 17 families with pathogenic FOXP2-only variants (12 loss-of-function, five missense variants; 14 males; aged 2 to 62 years). Health and development (cognitive, motor, social domains) were examined, including speech and language outcomes with the first cross-linguistic analysis of English and German. ResultsSpeech disorders were prevalent (23/25, 92%) and CAS was most common (22/25, 88%), with similar speech presentations across English and German. Speech was still impaired in adulthood, and some speech sounds (eg, 'th', 'r', 'ch', 'j') were never acquired. Language impairments (21/25, 84%) ranged from mild to severe. Comorbidities included feeding difficulties in infancy (10/27, 37%), fine (13/26, 50%) and gross (13/26, 50%) motor impairment, anxiety (5/27, 19%), depression (6/27, 22%) and sleep disturbance (11/15, 44%). Physical features were common (22/27, 81%) but with no consistent pattern. Cognition ranged from average to mildly impaired and was incongruent with language ability; for example, seven participants with severe language disorder had average non-verbal cognition. ConclusionsAlthough we identify an increased prevalence of conditions like anxiety, depression and sleep disturbance, we confirm that the consequences of FOXP2 dysfunction remain relatively specific to speech disorder, as compared with other recently identified monogenic conditions associated with CAS. Thus, our findings reinforce that FOXP2 provides a valuable entry point for examining the neurobiological bases of speech disorder.
CRIS-Team WoS Importer:2022-11-25

Infection and Predictors of Outcome of Cirrhotic Patients after Emergency Care Hospital Admission - Safi, Wajima; Elnegouly, Mayada; Schellnegger, Raphael; Umgelter, Katrin; Geisler, Fabian; Reindl, Wolfgang; Saugel, Bernd; Hapfelmeier, Alexander; Umgelter, Andreas (Annals of Hepatology, 2018)
Introduction and aims. We aimed to explore the impact of infection diagnosed upon admission and of other clinical baseline parameters on mortality of cirrhotic patients with emergency admissions. Material and methods. We performed a prospective observational monocentric study in a tertiary care center. The association of clinical parameters and established scoring systems with short-term mortality up to 90 days was assessed by univariate and multivariable Cox regression analysis. Akaike's Information Criterion (AIC) was used for automated variable selection. Statistical interaction effects with infection were also taken into account. Results. 218 patients were included. 71.2% were male, mean age was 61.1 +/- 10.5 years. Mean MELD score was 16.2 +/- 6.5, CLIF-consortium Acute on Chronic Liver Failure-score was 34 +/- 11. At 28, 90 and 365 days, 9.6%, 26.0% and 40.6% of patients had died, respectively. In multivariable analysis, respiratory organ failure [Hazard Ratio (HR) = 0.15], albumin substitution (HR = 2.48), non-HCC-malignancy (HR = 4.93), CLIF-C-ACLF (HR = 1.10), HCC (HR = 3.70) and first episode of ascites (HR = 0.11) were significantly associated with 90-day mortality. Patients with infection had a significantly higher 90-day mortality (36.3 vs. 20.1%, p = 0.007). Cultures were positive in 32 patients with resistance to cephalosporins or quinolones in 10, to ampicillin/sulbactam in 14 and carbapenems in 6 patients. Conclusion. Infection is common in cirrhotic ED admissions and increases mortality. The proportion of resistant microorganisms is high. The predictive capacity of established scoring systems in this setting was low to moderate.
CRIS-Team WoS Importer:2019-03-22

Infiltrating T lymphocytes reduce myeloid phagocytosis activity in synucleinopathy model - Sommer, Annika; Fadler, Tanja; Dorfmeister, Eva; Hoffmann, Anna-Carin; Xiang, Wei; Winner, Beate; Prots, Iryna (Journal of Neuroinflammation, 2016)
Synucleinopathies comprise a group of neurodegenerative diseases associated with abnormal accumulation of ?-synuclein. One of the key factors that contribute to the progression of synucleinopathies is neuroinflammation. However, the role of lymphocytes in synucleinopathies like Parkinson's disease (PD) remains largely unclear.To investigate how lymphocytes impact synucleinopathies, human wild-type ?-synuclein (WTS) transgenic mice were crossed with mice lacking mature lymphocytes (Rag2(-/-)). In this in vivo model, we quantified ?-synuclein aggregation in the substantia nigra (SN) and striatum and determined the numbers of innate and adaptive immune cells in the central nervous system (CNS). The activation state of resident and infiltrated CNS myeloid cells (M1 vs. M2) was further classified by gene and protein expression analyses. The impact of T and B lymphocytes on the phagocytic activity of microglia in the presence of ?-synuclein aggregates was addressed in BV2 microglia in vitro.Compared to WTS(+) Rag2(+/+) mice, where T but not B lymphocytes infiltrated the CNS, decreased amounts of ?-synuclein aggregates were found in WTS(+) Rag2(-/-) mice devoid of mature lymphocytes. The presence of T lymphocytes did not alter the number of Iba1(+) microglia but increased the frequency of the CD11b(+) CD45(hi) population in the CNS, indicative of an increased number of infiltrated macrophages. Moreover, the M1 phenotype was more prominent in WTS(+) Rag2(+/+) mice, whereas the M2 activation state was dominating in the absence of lymphocytes in WTS(+) Rag2(-/-) mice. In vitro, in the presence of T but not B lymphocytes, significantly less ?-synuclein was phagocytosed by BV2 microglia, further supporting the prevalence of the M1 phenotype in the presence of T lymphocytes.Peripheral T lymphocytes strongly contribute to increased ?-synuclein pathology via modulation of CNS myeloid cell function. In the presence of T lymphocytes, microglia phagocytosis of aggregated ?-synuclein is reduced, which increases the severity of synucleinopathy.
EVALuna2:4741

Inflammation-induced glycolytic switch controls suppressivity of mesenchymal stem cells via STAT1 glycosylation - Jitschin, R.; Böttcher, Martin; Saul, D.; Lukassen, Sören; Bruns, Heiko; Loschinski, Romy; Ekici, Arif Bülent; Reis, André; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2019)
Mesenchymal stem cells (MSCs) represent key contributors to tissue homeostasis and promising therapeutics for hyperinflammatory conditions including graft-versus-host disease. Their immunomodulatory effects are controlled by microenvironmental signals. The MSCs' functional response towards inflammatory cues is known as MSC-"licensing" and includes indoleamine 2,3-dioxygenase (IDO) upregulation. MSCs use tryptophan-depleting IDO to suppress T-cells. Increasing evidence suggests that several functions are (co-)determined by the cells' metabolic commitment. MSCs are capable of both, high levels of glycolysis and of oxidative phosphorylation. Although several studies have addressed alterations of the immune regulatory phenotype elicited by inflammatory priming metabolic mechanisms controlling this process remain unknown. We demonstrate that inflammatory MSC-licensing causes metabolic shifts including enhanced glycolysis and increased fatty acid oxidation. Yet, only interfering with glycolysis impacts IDO upregulation and impedes T-cell-suppressivity. We identified the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 pathway as a regulator of both glycolysis and IDO, and show that enhanced glucose turnover is linked to abundant STAT1 glycosylation. Inhibiting the responsible O-acetylglucosamine (O-GlcNAc) transferase abolishes STAT1 activity together with IDO upregulation. Our data suggest that STAT1-O-GlcNAcylation increases its stability towards degradation thus sustaining downstream effects. This pathway could represent a target for interventions aiming to enhance the MSCs' immunoregulatory potency.
EVALuna2:35805

Informal caregiving in amyotrophic lateral sclerosis (Als): A high caregiver burden and drastic consequences on caregivers’ lives - Schischlevskij, Pavel; Cordts, Isabell; Günther, René; Stolte, Benjamin; Zeller, Daniel; Schröter, Carsten; Weyen, Ute; Regensburger, Martin; Wolf, Joachim; Schneider, Ilka; Hermann, Andreas; Metelmann, Moritz; et al. (Brain Sciences, 2021)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that causes progressive autonomy loss and need for care. This does not only affect patients themselves, but also the patients’ informal caregivers (CGs) in their health, personal and professional lives. The big efforts of this multi-center study were not only to evaluate the caregivers’ burden and to identify its predictors, but it also should provide a specific understanding of the needs of ALS patients’ CGs and fill the gap of knowledge on their personal and work lives. Using standardized questionnaires, primary data from patients and their main informal CGs (n = 249) were collected. Patients’ functional status and disease severity were evaluated using the Barthel Index, the revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) and the King’s Stages for ALS. The caregivers’ burden was recorded by the Zarit Burden Interview (ZBI). Comorbid anxiety and depression of caregivers were assessed by the Hospital Anxiety and Depression Scale. Additionally, the EuroQol Five Dimension Five Level Scale evaluated their health-related quality of life. The caregivers’ burden was high (mean ZBI = 26/88, 0 = no burden, _24 = highly burdened) and correlated with patients’ functional status (rp = -0.555, p < 0.001, n = 242). It was influenced by the CGs’ own mental health issues due to caregiving (+11.36, 95% CI [6.84; 15.87], p < 0.001), patients’ wheelchair dependency (+9.30, 95% CI [5.94; 12.66], p < 0.001) and was interrelated with the CGs’ depression (rp = 0.627, p < 0.001, n = 234), anxiety (rp = 0.550, p < 0.001, n = 234), and poorer physical condition (rp = -0.362, p < 0.001, n = 237). Moreover, female CGs showed symptoms of anxiety more often, which also correlated with the patients’ impairment in daily routine (rs = -0.280, p < 0.001, n = 169). As increasing disease severity, along with decreasing autonomy, was the main predictor of caregiver burden and showed to create relevant (negative) implications on CGs’ lives, patient care and supportive therapies should address this issue. Moreover, in order to preserve the mental and physical health of the CGs, new concepts of care have to focus on both, on not only patients but also their CGs and gender-associated specific issues. As caregiving in ALS also significantly influences the socioeconomic status by restrictions in CGs’ work lives and income, and the main reported needs being lack of psychological support and a high bureaucracy, the situation of CGs needs more attention. Apart from their own multi-disciplinary medical and psychological care, more support in care and patient management issues is required.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Amyotrophic lateral sclerosis (ALS); Anxiety; Caregiver burden; Decreasing autonomy; Depression; Functional status; Health-related quality of life; Informal caregiving; Psychological support; Socioeconomic status

Inherited mutations in 17 breast cancer susceptibility genes among a large triple-negative breast cancer cohort unselected for family history of breast cancer - Couch, Fergus J.; Hart, Steven N.; Sharma, Priyanka; Toland, Amanda Ewart; Wang, Xianshu; Miron, Penelope; Olson, Janet E.; Godwin, Andrew K.; Pankratz, V. Shane; Olswold, Curtis; Slettedahl, Seth; Hallberg, Emily; et al. (Journal of Clinical Oncology, 2015)
Recent advances in DNA sequencing have led to the development of breast cancer susceptibility gene panels for germline genetic testing of patients. We assessed the frequency of mutations in 17 predisposition genes, including BRCA1 and BRCA2, in a large cohort of patients with triple-negative breast cancer (TNBC) unselected for family history of breast or ovarian cancer to determine the utility of germline genetic testing for those with TNBC.Patients with TNBC (N = 1,824) unselected for family history of breast or ovarian cancer were recruited through 12 studies, and germline DNA was sequenced to identify mutations.Deleterious mutations were identified in 14.6% of all patients. Of these, 11.2% had mutations in the BRCA1 (8.5%) and BRCA2 (2.7%) genes. Deleterious mutations in 15 other predisposition genes were detected in 3.7% of patients, with the majority observed in genes involved in homologous recombination, including PALB2 (1.2%) and BARD1, RAD51D, RAD51C, and BRIP1 (0.3% to 0.5%). Patients with TNBC with mutations were diagnosed at an earlier age (P < .001) and had higher-grade tumors (P = .01) than those without mutations.Deleterious mutations in predisposition genes are present at high frequency in patients with TNBC unselected for family history of cancer. Mutation prevalence estimates suggest that patients with TNBC, regardless of age at diagnosis or family history of cancer, should be considered for germline genetic testing of BRCA1 and BRCA2. Although mutations in other predisposition genes are observed among patients with TNBC, better cancer risk estimates are needed before these mutations are used for clinical risk assessment in relatives.
EVALuna2:9246

Inherited pain: sodium channel Nav1.7 A1632T mutation causes erythromelalgia due to a shift of fast inactivation - Eberhardt, Mirjam; Nakajima, Julika; Klinger, Alexandra; Neacsu, Cristian; Hühne, Kathrin; o' Reilly, Andrias; Kist, Andreas; Lampe, Anne K.; Fischer, Kerstin; Gibson, Jane; Nau, Carla; Winterpacht, Andreas; et al. (Journal of Biological Chemistry, 2014)
Inherited erythromelalgia (IEM) causes debilitating episodic neuropathic pain characterized by burning in the extremities. Inherited "paroxysmal extreme pain disorder" (PEPD) differs in its clinical picture and affects proximal body areas like the rectal, ocular, or jaw regions. Both pain syndromes have been linked to mutations in the voltage-gated sodium channel Nav1.7. Electrophysiological characterization shows that IEM-causing mutations generally enhance activation, whereas mutations leading to PEPD alter fast inactivation. Previously, an A1632E mutation of a patient with overlapping symptoms of IEM and PEPD was reported (Estacion, M., Dib-Hajj, S. D., Benke, P. J., Te Morsche, R. H., Eastman, E. M., Macala, L. J., Drenth, J. P., and Waxman, S. G. (2008) NaV1.7 Gain-of-function mutations as a continuum. A1632E displays physiological changes associated with erythromelalgia and paroxysmal extreme pain disorder mutations and produces symptoms of both disorders. J. Neurosci. 28, 11079-11088), displaying a shift of both activation and fast inactivation. Here, we characterize a new mutation of Nav1.7, A1632T, found in a patient suffering from IEM. Although transfection of A1632T in sensory neurons resulted in hyperexcitability and spontaneous firing of dorsal root ganglia (DRG) neurons, whole-cell patch clamp of transfected HEK cells revealed that Nav1.7 activation was unaltered by the A1632T mutation but that steady-state fast inactivation was shifted to more depolarized potentials. This is a characteristic normally attributed to PEPD-causing mutations. In contrast to the IEM/PEPD crossover mutation A1632E, A1632T failed to slow current decay (i.e. open-state inactivation) and did not increase resurgent currents, which have been suggested to contribute to high-frequency firing in physiological and pathological conditions. Reduced fast inactivation without increased resurgent currents induces symptoms of IEM, not PEPD, in the new Nav1.7 mutation, A1632T. Therefore, persistent and resurgent currents are likely to determine whether a mutation in Nav1.7 leads to IEM or PEPD.
EVALuna2:2419

Inherited variants in the inner centromere protein (INCENP) gene of the chromosomal passenger complex contribute to the susceptibility of ER-negative breast cancer - Kabisch, Maria; Bermejo, Justo Lorenzo; Duennebier, Thomas; Ying, Shibo; Michailidou, Kyriaki; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Shah, Mitul; Perkins, Barbara J.; Czene, Kamila; Darabi, Hatef; et al. (Carcinogenesis, 2015)
The chromosomal passenger complex (CPC) plays a pivotal role in the regulation of cell division. Therefore, inherited CPC variability could influence tumor development. The present candidate gene approach investigates the relationship between single nucleotide polymorphisms (SNPs) in genes encoding key CPC components and breast cancer risk. Fifteen SNPs in four CPC genes (INCENP, AURKB, BIRC5 and CDCA8) were genotyped in 88 911 European women from 39 case-control studies of the Breast Cancer Association Consortium. Possible associations were investigated in fixed-effects meta-analyses. The synonymous SNP rs1675126 in exon 7 of INCENP was associated with overall breast cancer risk [per A allele odds ratio (OR) 0.95, 95% confidence interval (CI) 0.92-0.98, P = 0.007] and particularly with estrogen receptor (ER)-negative breast tumors (per A allele OR 0.89, 95% CI 0.83-0.95, P = 0.0005). SNPs not directly genotyped were imputed based on 1000 Genomes. The SNPs rs1047739 in the 3' untranslated region and rs144045115 downstream of INCENP showed the strongest association signals for overall (per T allele OR 1.03, 95% CI 1.00-1.06, P = 0.0009) and ER-negative breast cancer risk (per A allele OR 1.06, 95% CI 1.02-1.10, P = 0.0002). Two genotyped SNPs in BIRC5 were associated with familial breast cancer risk (top SNP rs2071214: per G allele OR 1.12, 95% CI 1.04-1.21, P = 0.002). The data suggest that INCENP in the CPC pathway contributes to ER-negative breast cancer susceptibility in the European population. In spite of a modest contribution of CPC-inherited variants to the total burden of sporadic and familial breast cancer, their potential as novel targets for breast cancer treatment should be further investigated.
EVALuna2:9268

Inhibited Arginase-1 Expression by Fra-1 in Myeloid Cells Enhance Rheumatoid Arthritis Inflammation - Hannemann, Nicole; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Reid, Stephen; Sonnewald, Sophia; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (2017)
EVALuna2:33310

Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

INHIBITION OF ARGINASE-1 EXPRESSION BY THE TRANSCRIPTION FACTOR FRA-1 IN MACROPHAGES EXACERBATES RHEUMATOID ARTHRITIS INFLAMMATION - Hannemann, Nicole; Cao, Shan; Schnelzer, A.; Jordan, J.; Eberhardt, Martin; Schleicher, Ulrike; Uebe, Steffen; Ekici, Arif Bülent; Rech, Jürgen; Bäuerle, Tobias; Bogdan, Christian; Vera, Julio; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Inhibition of RAS activation due to a homozygous ezrin variant in patients with profound intellectual disability - Riecken, Lars Bjoern; Tawamie, Hasan; Dornblut, Carsten; Buchert, Rebecca; Ismayel, Amina; Schulz, Alexander; Schumacher, Johannes; Sticht, Heinrich; Pohl, Katja J.; Cui, Yan; Reis, André; Morrison, Helen; et al. (Human Mutation, 2015)
Gain-of-function alterations in several components and modulators of the Ras-MAPK pathway lead to dysregulation of the pathway and cause a broad spectrum of autosomal dominant developmental disorders, collectively known as RASopathies. These findings demonstrate the importance of tight multilevel Ras regulation to safeguard signaling output and prevent aberrant activity. We have recently identified ezrin as a novel regulatory element required for Ras activation. Homozygosity mapping and exome sequencing have now revealed the first presumably disease-causing variant in the coding gene EZR in two siblings with a profound intellectual disability. Localization and membrane targeting of the altered ezrin protein appeared normal but molecular modeling suggested protein interaction surfaces to be disturbed. Functional analysis revealed that the altered ezrin protein is no longer able to bind Ras and facilitate its activation. Furthermore, expression of the altered ezrin protein in different cell lines resulted in abnormal cellular processes, including reduced proliferation and neuritogenesis, thus revealing a possible mechanism for its phenotype in humans. To our knowledge, this is the first report of an autosomal recessively inherited loss-of-function mutation causing reduced Ras activity and thus extends and complements the pathogenicity spectrum of known Ras-MAPK pathway disturbances.
EVALuna2:9253

Integrative bioinformatics analysis characterizing the role of EDC3 in mRNA decay and its association to intellectual disability - Scheller, Ute; Pfisterer, Kathrin; Uebe, Steffen; Ekici, Arif Bülent; Reis, André; Jamra, Rami; Ferrazzi, Fulvia (Bmc Medical Genomics, 2018)
BACKGROUND: Decapping of mRNA is an important step in the regulation of mRNA turnover and therefore of gene expression, which is a key process controlling development and homeostasis of all organisms. It has been shown that EDC3 plays a role in mRNA decapping, however its function is not well understood. Previously, we have associated a homozygous variant in EDC3 with autosomal recessive intellectual disability. Here, we investigate the functional role of EDC3. METHODS: We performed transcriptome analyses in patients' samples. In addition, we established an EDC3 loss-of-function model using siRNA-based knockdown in the human neuroblastoma cell line SKNBE and carried out RNA sequencing. Integrative bioinformatics analyses were performed to identify EDC3-dependent candidate genes and/or pathways. RESULTS: Our analyses revealed that 235 genes were differentially expressed in patients versus controls. In addition, AU-rich element (ARE)-containing mRNAs, whose degradation in humans has been suggested to involve EDC3, had higher fold changes than non-ARE-containing genes. The analysis of RNA sequencing data from the EDC3 in vitro loss-of-function model confirmed the higher fold changes of ARE-containing mRNAs compared to non-ARE-containing mRNAs and further showed an upregulation of long non-coding and coding RNAs. In total, 764 genes were differentially expressed. Integrative bioinformatics analyses of these genes identified dysregulated candidate pathways, including pathways related to synapses/coated vesicles and DNA replication/cell cycle. CONCLUSION: Our data support the involvement of EDC3 in mRNA decay, including ARE-containing mRNAs, and suggest that EDC3 might be preferentially involved in the degradation of long coding and non-coding RNAs. Furthermore, our results associate ECD3 loss-of-function with synapses-related pathways. Collectively, our data provide novel information that might help elucidate the molecular mechanisms underlying the association of intellectual disability with the dysregulation of mRNA degradation.
EVALuna2:34136

Intellectual disability and autism spectrum disorders 'on the fly': insights from Drosophila - Coll-Tane, Mireia; Krebbers, Alina; Castells-Nobau, Anna; Zweier, Christiane; Schenck, Annette (Disease Models & Mechanisms, 2019)
Intellectual disability (ID) and autism spectrum disorders (ASD) are frequently co-occurring neurodevelopmental disorders and affect 2-3% of the population. Rapid advances in exome and genome sequencing have increased the number of known implicated genes by threefold, to more than a thousand. The main challenges in the field are now to understand the various pathomechanisms associated with this bewildering number of genetic disorders, to identify new genes and to establish causality of variants in still-undiagnosed cases, and to work towards causal treatment options that so far are available only for a few metabolic conditions. To meet these challenges, the research community needs highly efficient model systems. With an increasing number of relevant assays and rapidly developing novel methodologies, the fruit fly Drosophila melanogaster is ideally positioned to change gear in ID and ASD research. The aim of this Review is to summarize some of the exciting work that already has drawn attention to Drosophila as a model for these disorders. We highlight well-established ID-and ASD-relevant fly phenotypes at the (sub) cellular, brain and behavioral levels, and discuss strategies of how this extraordinarily efficient and versatile model can contribute to 'next generation' medical genomics and to a better understanding of these disorders.
CRIS-Team WoS Importer:2019-06-21

Interaction of Alpha Synuclein and Microtubule Organization Is Linked to Impaired Neuritic Integrity in Parkinson’s Patient-Derived Neuronal Cells - Schneider, Yanni; Drobny, Alice; Prots, Iryna; Zunke, Friederike; Xiang, Wei; Seebauer, Lukas; Schneider, Yanni; Drobny, Alice; Ploetz, Sonja; Koudelka, Tomas; Tholey, Andreas; Prots, Iryna; et al. (International Journal of Molecular Sciences, 2022)
Parkinson’s disease (PD) is neuropathologically characterized by the loss of dopaminergic neurons and the deposition of aggregated alpha synuclein (aSyn). Mounting evidence suggests that neuritic degeneration precedes neuronal loss in PD. A possible underlying mechanism could be the interference of aSyn with microtubule organization in the neuritic development, as implied by sev-eral studies using cell-free model systems. In this study, we investigate the impact of aSyn on mi-crotubule organization in aSyn overexpressing H4 neuroglioma cells and midbrain dopaminergic neuronal cells (mDANs) generated from PD patient-derived human induced pluripotent stem cells (hiPSCs) carrying an aSyn gene duplication (SNCADupl). An unbiased mass spectrometric analysis reveals a preferential binding of aggregated aSyn conformers to a number of microtubule elements. We confirm the interaction of aSyn with beta tubulin III in H4 and hiPSC-derived mDAN cell model systems, and demonstrate a remarkable redistribution of tubulin isoforms from the soluble to insoluble fraction, accompanied by a significantly increased insoluble aSyn level. Concordantly, SNCA-Dupl mDANs show impaired neuritic phenotypes characterized by perturbations in neurite initiation and outgrowth. In summary, our findings suggest a mechanistic pathway, through which aSyn aggregation interferes with microtubule organization and induces neurite impairments.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alpha-synuclein; IPSC; Microtubule; Neurite; Neurodegeneration; Parkinson’s disease; SNCA duplication

Interspecies Single-Cell RNA-Seq Analysis Reveals the Novel Trajectory of Osteoclast Differentiation and Therapeutic Targets - Omata, Yasunori; Okada, Hiroyuki; Uebe, Steffen; Izawa, Naohiro; Ekici, Arif Bülent; Sarter-Zaiss, Kerstin; Saito, Taku; Schett, Georg; Tanaka, Sakae; Zaiss, Mario (JBMR Plus, 2022)
Bone turnover is finely tuned by cells in the bone milieu, including osteoblasts, osteoclasts, and osteocytes. Osteoclasts are multinucleated giant cells with a bone-resorbing function that play a critical role in regulating skeletal homeostasis. Osteoclast differentiation is characterized by dramatic changes in morphology and gene expression following receptor activator of nuclear factor-kappa-Beta ligand (RANKL) stimulation. We performed single-cell RNA-sequencing analyses of human and murine osteoclast-lineage cells (OLCs) and found that OLCs in the mitotic phase do not differentiate into mature osteoclasts. We also identified a guanosine triphosphatase (GTPase) family member, RAB38, as a highly expressed molecule in both human and murine osteoclast clusters; RAB38 gene expression is associated with dynamic changes in histone modification and transcriptional regulation. Silencing Rab38 expression by using short hairpin RNA (shRNA) inhibited osteoclast differentiation and maturation. In summary, we established an integrated fate map of human and murine osteoclastogenesis; this will help identify therapeutic targets in bone diseases. (c) 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.
CRIS-Team WoS Importer:2022-05-27

Intracellular A53T Mutant α-Synuclein Impairs Adult Hippocampal Newborn Neuron Integration - Regensburger, Martin; Stemick, Judith; Masliah, Eliezer; Kohl, Zacharias; Winner, Beate (Frontiers in Cell and Developmental Biology, 2020)
Dendritic dysfunction is an early event in α-synuclein (α-syn) mediated neurodegeneration. Altered postsynaptic potential and loss of dendritic spines have been observed in different in vitro and in vivo models of synucleinopathies. The integration of newborn neurons into the hippocampus offers the possibility to study dendrite and spine formation in an adult environment. Specifically, survival of hippocampal adult newborn neurons is regulated by synaptic input and was reduced in a mouse model transgenic for human A53T mutant α-syn. We thus hypothesized that dendritic integration of newborn neurons is impaired in the adult hippocampus of A53T mice. We analyzed dendritic morphology of adult hippocampal neurons 1 month after retroviral labeling. Dendrite length was unchanged in the dentate gyrus of A53T transgenic mice. However, spine density and mushroom spine density of newborn neurons were severely decreased. In this mouse model, transgenic α-syn was expressed both within newborn neurons and within their environment. To specifically determine the cell autonomous effects, we analyzed cell-intrinsic overexpression of A53T α-syn using a retrovirus. Since A53T α-syn overexpressing newborn neurons exhibited decreased spine density 1 month after labeling, we conclude that cell-intrinsic A53T α-syn impairs postsynaptic integration of adult hippocampal newborn neurons. Our findings further support the role of postsynaptic degeneration as an early feature in synucleinopathies and provide a model system to study underlying mechanisms.
CRIS-Team Scopus Importer:2020-12-04
Keywords: A53T alpha-synuclein; adult neurogenesis; cell autonomous; hippocampus; spines

Intracellular alpha-synuclein affects early maturation of primary oligodendrocyte progenitor cells - Ettle, Benjamin; Reiprich, Simone; Deußer, Janina; Schlachetzki, Johannes; Xiang, Wei; Prots, Iryna; Masliah, Eliezer; Winner, Beate; Wegner, Michael; Winkler, Jürgen (Molecular and Cellular Neuroscience, 2014)
Myelin loss is a widespread neuropathological hallmark of the atypical parkinsonian disorder multiple system atrophy (MSA). On a cellular level, MSA is characterized by alpha-synuclein (aSyn)-positive glial cytoplasmic inclusions (GCIs) within mature oligodendrocytes leading to demyelination as well as axonal and neuronal loss. Oligodendrocyte progenitor cells (OPCs) represent a proliferative cell population distributed throughout the adult mammalian central nervous system. During remyelination, OPCs are recruited to sites of demyelination, differentiate, and finally replace dysfunctional mature oligodendrocytes. However, comprehensive studies investigating OPCs and remyelination processes in MSA are lacking. In the present study, we therefore investigate the effect of human aSyn (h-aSyn) on early primary rat OPC maturation. Upon lentiviral transduction, h-aSyn expressing OPCs exhibit fewer and shorter primary processes at the initiation of differentiation. Until day 4 of a 6day differentiation paradigm, h-aSyn expressing OPCs further show a severely delayed maturation evidenced by reduced myelin gene expression and increased levels of the progenitor marker platelet derived growth factor receptor-alpha (PDGFR?). Matching these results, OPCs that take up extracellular recombinant h-aSyn exhibit a similar delayed differentiation. In both experimental setups however, myelin gene expression is restored at day 6 of differentiation paralleled by decreased intracellular h-aSyn levels indicating a reverse correlation of h-aSyn and the differentiation potential of OPCs. Taken together, these findings suggest a tight link between the intracellular level of h-aSyn and maturation capacity of primary OPCs.
EVALuna2:4696

Intrafamilial neurological phenotypic variability due to either biallelic or monoallelic pathogenic variants in CACNA1A - Mammadova, Dilbar; Kraus, Cornelia; Leis, Thomas; Popp, Bernt; Zweier, Christiane; Reis, André; Trollmann, Regina (Frontiers in Neurology, 2024)
Pathogenic heterozygous variants in CACNA1A are associated with familial hemiplegic migraine, episodic ataxia type 2 and spinocerebellar ataxia type 6, and more recently, neurodevelopmental disorders. We describe a severe, early-onset phenotype including severe muscular hypotonia, early-onset epileptic seizures, apnoea, optic atrophy and dysphagia in three siblings carrying compound heterozygous frameshift variants in CACNA1A. Two male patients died at the age of 5 or 14 months of suspected SIDS or severe developmental epileptic encephalopathy (DEE) with refractory seizures and apnoea. A male child (index patient) developed severe early-onset DEE including seizures and ictal apnoea at the age of 4 weeks. Another male child developed generalized epilepsy and mild intellectual impairment in late infancy, and his mother and his maternal uncle were identified as carriers of a known CACNA1A pathogenic variant [c.2602delG heterozygous, p. (Ala868Profs*24)] with a diagnosis of episodic ataxia type 2. This maternal pathogenic variant c.2602delG was detected in the index patient and child 2. Trio-Exome sequencing identified an additional heterozygous pathogenic variant in the CACNA1A gene, c.5476delC, p.(His1826Thrfs*30) in the index patient and child 2, which was inherited from the asymptomatic father. In conclusion, the novel compound heterozygosity for two frameshift pathogenic variants, maternally [c.2602delG, p.(Ala868Profs*24)] and paternally [c.5476delC, p.(His1826Thrfs*3)] is associated with a severe phenotype of early-onset DEE. This observation highlights the necessity of additional analyses to clarify unusual phenotypes even if a pathogenic variant has already been identified, and expands the clinical spectrum of CACNA1A-related disorders.
CRIS-Team Scopus Importer:2024-10-25
Keywords: apneic spells; burst suppression; developmental epileptic encephalopathy; early-onset epileptic encephalopathy; generalized epilepsy; optic nerve atrophy

Investigating consanguineous families from Turkey to identify autosomal recessive neurodevelopmental disorders - Gumuslu, Esen; Guemues, Evren; Oz, Ozlem; Ozkan, Melis; Karaer, Kadri; Ekici, Arif Bülent; Yildiz, Edibe Pembegul; Aydinli, Nur; Wiesmann da Silva Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Investigating PHF13 induced infertility through single cell transcriptomics and non-vertebrate model organisms - Bosch, Elisabeth; Lukassen, S.; Gregor, Anne; Ekici, Arif Bülent; Zweier, Christiane; Winterpacht, Andreas (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Investigating the role of the fibrillar layer in Fuchs endothelial corneal dystrophy - Matthaei, Mario; Clahsen, Thomas; Büttner, Christian; Siebelmann, Sebastian; Heindl, Ludwig; Bachmann, Bjoern; Cursiefen, Claus; Hribek, Agathe (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Investigation of gene-environment interactions between 47 newly identified breast cancer susceptibility loci and environmental risk factors - Rudolph, Anja; Milne, Roger L.; Truong, Therese; Knight, Julia A.; Seibold, Petra; Flesch-Janys, Dieter; Behrens, Sabine; Eilber, Ursula; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; et al. (International Journal of Cancer, 2015)
A large genotyping project within the Breast Cancer Association Consortium (BCAC) recently identified 41 associations between single nucleotide polymorphisms (SNPs) and overall breast cancer (BC) risk. We investigated whether the effects of these 41 SNPs, as well as six SNPs associated with estrogen receptor (ER) negative BC risk are modified by 13 environmental risk factors for BC. Data from 22 studies participating in BCAC were pooled, comprising up to 26,633 cases and 30,119 controls. Interactions between SNPs and environmental factors were evaluated using an empirical Bayes-type shrinkage estimator. Six SNPs showed interactions with associated p-values (pint ) <1.1 × 10(-3) . None of the observed interactions was significant after accounting for multiple testing. The Bayesian False Discovery Probability was used to rank the findings, which indicated three interactions as being noteworthy at 1% prior probability of interaction. SNP rs6828523 was associated with increased ER-negative BC risk in women >=170 cm (OR = 1.22, p = 0.017), but inversely associated with ER-negative BC risk in women <160 cm (OR = 0.83, p = 0.039, pint = 1.9 × 10(-4) ). The inverse association between rs4808801 and overall BC risk was stronger for women who had had four or more pregnancies (OR = 0.85, p = 2.0 × 10(-4) ), and absent in women who had had just one (OR = 0.96, p = 0.19, pint = 6.1 × 10(-4) ). SNP rs11242675 was inversely associated with overall BC risk in never/former smokers (OR = 0.93, p = 2.8 × 10(-5) ), but no association was observed in current smokers (OR = 1.07, p = 0.14, pint = 3.4 × 10(-4) ). In conclusion, recently identified BC susceptibility loci are not strongly modified by established risk factors and the observed potential interactions require confirmation in independent studies.
EVALuna2:9245

In vivo demonstration that alpha-synuclein oligomers are toxic. - Winner, Beate; Jappelli, Roberto; Maji, Samir K.; Desplats, Paula A.; Boyer, Leah; Aigner, Stefan; Hetzer, Claudia; Loher, Thomas; Vilar, Marcal; Campioni, Silvia; Tzitzilonis, Christos; Soragni, Alice; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
The aggregation of proteins into oligomers and amyloid fibrils is characteristic of several neurodegenerative diseases, including Parkinson disease (PD). In PD, the process of aggregation of ?-synuclein (?-syn) from monomers, via oligomeric intermediates, into amyloid fibrils is considered the disease-causative toxic mechanism. We developed ?-syn mutants that promote oligomer or fibril formation and tested the toxicity of these mutants by using a rat lentivirus system to investigate loss of dopaminergic neurons in the substantia nigra. The most severe dopaminergic loss in the substantia nigra is observed in animals with the ?-syn variants that form oligomers (i.e., E57K and E35K), whereas the ?-syn variants that form fibrils very quickly are less toxic. We show that ?-syn oligomers are toxic in vivo and that ?-syn oligomers might interact with and potentially disrupt membranes.
EVALuna2:26218

In Vivo Protein Complementation Demonstrates Presynaptic α-Synuclein Oligomerization and Age-Dependent Accumulation of 8–16-mer Oligomer Species - Kiechle, Martin; von Einem, Bjoern; Höfs, Lennart; Voehringer, Patrizia; Grozdanov, Veselin; Markx, Daniel; Parlato, Rosanna; Wiesner, Diana; Mayer, Benjamin; Sakk, Olena; Baumann, Bernd; Lukassen, Sören; et al. (Cell Reports, 2019)
Kiechle et al. present two transgenic mouse models that allow direct quantitative and spatial detection of α-synuclein (α-syn) oligomers in vivo. They demonstrate α-syn aggregation at the synapse, age-dependent accumulation of 8–16-mer α-syn oligomer species, and trans-cellular oligomer spreading from forebrain to hindbrain neurons.
CRIS-Team Scopus Importer:2019-12-03
Keywords: aging; alpha-synuclein; neurodegeneration; oligomerization; Parkinson's disease; progressive phenotype; protein-fragment complementation; spreading; synaptic oligomers; transgenic mouse model

Ischemic stroke and dose adjustment of oral Factor Xa inhibitors in patients with atrial fibrillation - Stoll, Svenja; Macha, Kosmas; Marsch, Armin; Gerner, Stefan; Siedler, Gabriela; Fröhlich, Kilian; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Neurology, 2020)
Background: Oral Factor Xa inhibitors for the prevention of stroke in atrial fibrillation require dose adjustment based on certain clinical criteria, but the off-label use of the reduced doses is common. Methods: Data from an observational registry including patients admitted with acute cerebral ischemia while taking oral Factor Xa inhibitors for atrial fibrillation between April 2016 and December 2018 were investigated. The dose regimen of the Xa inhibitor was classified as “appropriate”, “underdosed” and “overdosed” in conformity with the European Medicines Agency labelling. The effect of underdosing on the functional factor Xa plasma level on admission, the clinical stroke severity and the functional outcome after 3 months were investigated. Results: 254 patients with cerebral ischemia while on Factor Xa inhibitors were included. The dose regimen of the Factor Xa inhibitor was appropriate in 166 patients (65%), underdosed in 67 patients (26%) and overdosed in 21 patients (8%). Underdosing was associated with female sex, diabetes mellitus and higher CHA2DS2–Vasc scores. Underdosing independently predicted lower anti-Xa plasma levels on admission [median 69.4 ng/ml (IQR 0.0–121.6) vs. 129.2 ng/ml (65.5–207.2); p < 0.001], was associated with higher NIHSS scores on admission [median 5 (IQR 1–10) vs. 3 (1–7); p = 0.041] and worse functional outcome after 3 months (favorable outcome 26.9% vs. 46.9%; p = 0.025). Conclusion: One in three patients with ischemic stroke during treatment with oral Xa inhibitors used inappropriate dose regimens. Underdosing was associated with lower functional plasma levels, higher clinical stroke severity and worse functional outcome.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atrial fibrillation; Direct oral anticoagulants; Dose reduction; Plasma levels; Stroke

Is MED13L-related intellectual disability a recognizable syndrome? - Tørring, Pernille Mathiesen; Larsen, Martin Jakob; Brasch-Andersen, Charlotte; Krogh, Lotte Nylandsted; Kibæk, Maria; Laulund, Lone; Illum, Niels; Dunkhase-Heinl, Ulrike; Wiesener, Antje; Popp, Bernt; Marangi, Giuseppe; Hjortshøj, Tina Duelund; et al. (European Journal of Medical Genetics, 2018)
INTRODUCTION: MED13L-related intellectual disability is characterized by moderate intellectual disability (ID), speech impairment, and dysmorphic facial features. We present 8 patients with MED13L-related intellectual disability and review the literature for phenotypical and genetic aspects of previously described patients. MATERIALS AND METHODS: In the search for genetic aberrations in individuals with ID, two of the patients were identified by chromosomal microarray analysis, and five by exome sequencing. One of the individuals, suspected of MED13L-related intellectual disability, based on clinical features, was identified by Sanger sequencing. RESULTS: All 8 individuals had de novo MED13L aberrations, including two intragenic microdeletions, two frameshift, three nonsense variants, and one missense variant. Phenotypically, they all had intellectual disability, speech and motor delay, and features of the mouth (open mouth appearance, macroglossia, and/or macrostomia). Two individuals were diagnosed with autism, and one had autistic features. One had complex congenital heart defect, and one had persistent foramen ovale. The literature was reviewed with respect to clinical and dysmorphic features, and genetic aberrations. CONCLUSIONS: Even if most clinical features of MED13L-related intellectual disability are rather non-specific, the syndrome may be suspected in some individuals based on the association of developmental delay, speech impairment, bulbous nasal tip, and macroglossia, macrostomia, or open mouth appearance.
EVALuna2:34847

Janus-faced spatacsin (SPG11): involvement in neurodevelopment and multisystem neurodegeneration - Pozner, Tatyana; Regensburger, Martin; Engelhorn, Tobias; Winkler, Jürgen; Winner, Beate (Brain, 2020)
Hereditary spastic paraplegia (HSP) is a heterogeneous group of rare motor neuron disorders characterized by progressive weakness and spasticity of the lower limbs. HSP type 11 (SPG11-HSP) is linked to pathogenic variants in the SPG11 gene and it represents the most frequent form of complex autosomal recessive HSP. The majority of SPG11-HSP patients exhibit additional neurological symptoms such as cognitive decline, thin corpus callosum, and peripheral neuropathy. Yet, the mechanisms of SPG11-linked spectrum diseases are largely unknown. Recent findings indicate that spatacsin, the 280 kDa protein encoded by SPG11, may impact the autophagy-lysosomal machinery. In this update, we summarize the current knowledge of SPG11-HSP. In addition to clinical symptoms and differential diagnosis, our work aims to link the different clinical manifestations with the respective structural abnormalities and cellular in vitro phenotypes. Moreover, we describe the impact of localization and function of spatacsin in different neuronal systems. Ultimately, we propose a model in which spatacsin bridges between neurodevelopmental and neurodegenerative phenotypes of SPG11-linked disorders.
CRIS-Team Scopus Importer:2020-09-04
Keywords: autophagy; hereditary spastic paraplegia; neurodegeneration; neurodevelopment; SPG11

Kdm6b and Pmepa1 as Targets of Bioelectrically and Behaviorally Induced Activin A Signaling - Link, Andrea; Kurinna, Svitlana; Havlicek, Steven; Lehnert, Sandra; Reichel, Martin; Kornhuber, Johannes; Winner, Beate; Huth, Tobias; Zheng, Fang; Werner, Sabine; Alzheimer, Christian (Molecular Neurobiology, 2016)
The transforming growth factor-? (TGF-?) family member activin A exerts multiple neurotrophic and protective effects in the brain. Activin also modulates cognitive functions and affective behavior and is a presumed target of antidepressant therapy. Despite its important role in the injured and intact brain, the mechanisms underlying activin effects in the CNS are still largely unknown. Our goal was to identify the first target genes of activin signaling in the hippocampus in vivo. Electroconvulsive seizures, a rodent model of electroconvulsive therapy in humans, were applied to C57BL/6J mice to elicit a strong increase in activin A signaling. Chromatin immunoprecipitation experiments with hippocampal lysates subsequently revealed that binding of SMAD2/3, the intracellular effectors of activin signaling, was significantly enriched at the Pmepa1 gene, which encodes a negative feedback regulator of TGF-? signaling in cancer cells, and at the Kdm6b gene, which encodes an epigenetic regulator promoting transcriptional plasticity. Underlining the significance of these findings, activin treatment also induced PMEPA1 and KDM6B expression in human forebrain neurons generated from embryonic stem cells suggesting interspecies conservation of activin effects in mammalian neurons. Importantly, physiological stimuli such as provided by environmental enrichment proved already sufficient to engender a rapid and significant induction of activin signaling concomitant with an upregulation of Pmepa1 and Kdm6b expression. Taken together, our study identified the first target genes of activin signaling in the brain. With the induction of Kdm6b expression, activin is likely to gain impact on a presumed epigenetic regulator of activity-dependent neuronal plasticity.
EVALuna2:2488

KIF3A and IL-4 are disease-specific biomarkers for psoriatic arthritis susceptibility - Cascella, Raffaella; Strafella, Claudia; Ragazzo, Michele; Manzo, Laura; Costanza, Gaetana; Bowes, John; Hueffmeier, Ulrike; Potenza, Saverio; Sangiuolo, Federica; Reis, André; Barton, Anne; Novelli, Giuseppe; et al. (Oncotarget, 2017)
To date, the genes associated with Psoriatic Arthritis (PsA) are principally involved in inflammation, immune response and epidermal differentiation, without any information about the relationship between disease and bone metabolism genes. Our work was focused on 5q31 locus, which contains several genetic variants significantly associated with PsA. The study involved 1526 subjects (500 PsA, 426 PsV, 600 controls). The region was evaluated by selecting and genotyping the SNPs of interest by Real Time PCR and direct sequencing. The results were subjected to biostatistic and bioinformatic analysis. The case-control study highlighted a significant association between KIF3A/IL-4 and PsA, but not with PsV (Psoriasis Vulgaris) patients. In addition, the haplotype analysis revealed two haplotypes significantly associated with PsA susceptibility. The Linkage Disequilibrium (LD) study showed the presence of a specific block in high LD within 132,692,628-132,737,638 bp of 5q31, giving additional evidence of specific association of the 5q31 region in PsA patients. Moreover, KIF3A expression was assessed by immunohistochemistry assays which showed a marked and significant difference of KIF3A expression between pathological and normal tissues. Our analysis described KIF3A and IL-4 as novel susceptibility genes for PsA, suggesting a clear implication of bone metabolism genes in the disease etiopathogenesis.
EVALuna2:9386

KNOCK-OUT OF THE HUMAN ENDOGENOUS RETROVIRUS ERV3 USING CRISPR/CAS9 TECHNOLOGY - Hübner, Hanna; Fahlbusch, Fabian B.; Ekici, Arif Bülent; Vasileiou, Georgia; Beckmann, Matthias; Strick, Reiner; Rübner, Matthias (2016)
EVALuna2:9327

L- and M-cone driven temporal contrast sensitivity is reduced at low frequencies in patients with Stargardt's disease - Huchzermeyer, Cord; Pasutto, Francesca; Wiesmann da Silva Reis, André; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

Large-scale evaluation of common variation in regulatory T cell-related genes and ovarian cancer outcome - Charbonneau, Bridget; Moysich, Kirsten B.; Kalli, Kimberly R.; Oberg, Ann L.; Vierkant, Robert A.; Fogarty, Zachary C.; Block, Matthew S.; Maurer, Matthew J.; Goergen, Krista M.; Fridley, Brooke L.; Cunningham, Julie M.; Rider, David N.; et al. (Cancer Immunology Research, 2014)
The presence of regulatory T cells (Treg) in solid tumors is known to play a role in patient survival in ovarian cancer and other malignancies. We assessed inherited genetic variations via 749 tag single-nucleotide polymorphisms (SNP) in 25 Treg-associated genes (CD28, CTLA4, FOXP3, IDO1, IL10, IL10RA, IL15, 1L17RA, IL23A, IL23R, IL2RA, IL6, IL6R, IL8, LGALS1, LGALS9, MAP3K8, STAT5A, STAT5B, TGFB1, TGFB2, TGFB3, TGFBR1, TGRBR2, and TGFBR3) in relation to ovarian cancer survival. We analyzed genotype and overall survival in 10,084 women with invasive epithelial ovarian cancer, including 5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous carcinoma cases of European descent across 28 studies from the Ovarian Cancer Association Consortium (OCAC). The strongest associations were found for endometrioid carcinoma and IL2RA SNPs rs11256497 [HR, 1.42; 95% confidence interval (CI), 1.22-1.64; P = 5.7 × 10(-6)], rs791587 (HR, 1.36; 95% CI, 1.17-1.57; P = 6.2 × 10(-5)), rs2476491 (HR, = 1.40; 95% CI, 1.19-1.64; P = 5.6 × 10(-5)), and rs10795763 (HR, 1.35; 95% CI, 1.17-1.57; P = 7.9 × 10(-5)), and for clear cell carcinoma and CTLA4 SNP rs231775 (HR, 0.67; 95% CI, 0.54-0.82; P = 9.3 × 10(-5)) after adjustment for age, study site, population stratification, stage, grade, and oral contraceptive use. The rs231775 allele associated with improved survival in our study also results in an amino acid change in CTLA4 and previously has been reported to be associated with autoimmune conditions. Thus, we found evidence that SNPs in genes related to Tregs seem to play a role in ovarian cancer survival, particularly in patients with clear cell and endometrioid epithelial ovarian cance
EVALuna2:9223

Large scale meta-analysis characterizes genetic architecture for common psoriasis associated variants - Tsoi, Lam C.; Stuart, Philip E.; Tian, Chao; Gudjonsson, Johann E.; Das, Sayantan; Zawistowski, Matthew; Ellinghaus, Eva; Barker, Jonathan N.; Chandran, Vinod; Dand, Nick; Duffin, Kristina Callis; Enerback, Charlotta; et al. (Nature Communications, 2017)
Psoriasis is a complex disease of skin with a prevalence of about 2%. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for psoriasis to date, including data from eight different Caucasian cohorts, with a combined effective sample size >39,000 individuals. We identified 16 additional psoriasis susceptibility loci achieving genome-wide significance, increasing the number of identified loci to 63 for European-origin individuals. Functional analysis highlighted the roles of interferon signalling and the NF?B cascade, and we showed that the psoriasis signals are enriched in regulatory elements from different T cells (CD8(+) T-cells and CD4(+) T-cells including TH0, TH1 and TH17). The identified loci explain 28% of the genetic heritability and generate a discriminatory genetic risk score (AUC=0.76 in our sample) that is significantly correlated with age at onset (p=2 × 10(-89)). This study provides a comprehensive layout for the genetic architecture of common variants for psoriasis.
EVALuna2:9373

Latent tuberculous infection: ethical considerations in formulating public health policy - Denholm, J. T.; Matteelli, Alberto; Reis, André (International Journal of Tuberculosis and Lung Disease, 2015)
There is increasing interest in the introduction of public health policies relating to latent tuberculous infection (LTBI). However, there has been little previous systematic engagement with LTBI from an ethical perspective. This article offers a general overview of ethical issues in relation to LTBI, with particular focus on those aspects relevant to the development and implementation of public health policy. Key characteristics of LTBI are discussed from an ethical perspective, with examples of challenging situations for policy makers.
EVALuna2:5665

Leukemogenic MLL-ENL Fusions Induce Alternative Chromatin States to Drive a Functionally Dichotomous Group of Target Genes - Garcia-Cuellar, Maria-Paz; Büttner, Christian; Bartenhagen, Christoph; Dugas, Martin; Slany, Robert (Cell Reports, 2016)
MLL fusions are leukemogenic transcription factors that enhance transcriptional elongation through modification of chromatin and RNA Pol II. Global transcription rates and chromatin changes accompanying the transformation process induced by MLL-ENL were monitored by nascent RNA-seq and ChIP-seq, revealing 165 direct target genes separated into two distinct clades. ME5 genes bound MLL-ENL at the promoter, relied on DOT1L-mediated histone methylation, and coded preferentially for transcription factors, including many homeobox genes. A distinct ME3 group accumulated MLL-ENL beyond the termination site, was dependent on P-TEFb-mediated phosphorylation of RNA Pol II for transcription, and translated mainly into proteins involved in RNA biology and ribosome assembly. This dichotomy was reflected by a differential sensitivity toward small molecule inhibitors, suggesting the possibility of a combinatorial strategy for treatment of MLL-induced leukemia.
Keywords: Chromatin; DOT1L; Inhibitors; Leukemia; MLL-ENL; P-TEFb

LHX2 haploinsufficiency causes a variable neurodevelopmental disorder - Schmid, Cosima M.; Gregor, Anne; Costain, Gregory; Morel, Chantal F.; Massingham, Lauren; Schwab, Jennifer; Quélin, Chloé; Faoucher, Marie; Kaplan, Julie; Procopio, Rebecca; Saunders, Carol J.; Cohen, Ana S.A.; et al. (Genetics in Medicine, 2023)
Purpose: LHX2 encodes the LIM homeobox 2 transcription factor (LHX2), which is highly expressed in brain and well conserved across species, but it has not been clearly linked to neurodevelopmental disorders (NDDs) to date. Methods: Through international collaboration, we identified 19 individuals from 18 families with variable neurodevelopmental phenotypes, carrying a small chromosomal deletion, likely gene-disrupting or missense variants in LHX2. Functional consequences of missense variants were investigated in cellular systems. Results: Affected individuals presented with developmental and/or behavioral abnormalities, autism spectrum disorder, variable intellectual disability, and microcephaly. We observed nucleolar accumulation for 2 missense variants located within the DNA-binding HOX domain, impaired interaction with co-factor LDB1 for another variant located in the protein-protein interaction–mediating LIM domain, and impaired transcriptional activation by luciferase assay for 4 missense variants. Conclusion: We implicate LHX2 haploinsufficiency by deletion and likely gene-disrupting variants as causative for a variable NDD. Our findings suggest a loss-of-function mechanism also for likely pathogenic LHX2 missense variants. Together, our observations underscore the importance of LHX2 in the nervous system and for variable neurodevelopmental phenotypes.
CRIS-Team Scopus Importer:2023-07-07
Keywords: ASD; Intellectual disability; LHX2; Microcephaly; NDD; Neurodevelopmental disorder

Lifetime ovulatory years and risk of epithelial ovarian cancer: a multinational pooled analysis - Fu, Zhuxuan; Brooks, Maria Mori; Irvin, Sarah; Jordan, Susan; Aben, Katja K. H.; Anton-Culver, Hoda; Bandera, Elisa; Beckmann, Matthias; Berchuck, Andrew; Brooks-Wilson, Angela; Chang-Claude, Jenny; Cook, Linda S.; et al. (Journal of the National Cancer Institute, 2023)
Background The role of ovulation in epithelial ovarian cancer (EOC) is supported by the consistent protective effects of parity and oral contraceptive use. Whether these factors protect through anovulation alone remains unclear. We explored the association between lifetime ovulatory years (LOY) and EOC. Methods LOY was calculated using 12 algorithms. Odds ratios (ORs) and 95% confidence intervals (CIs) estimated the association between LOY or LOY components and EOC among 26 204 control participants and 21 267 case patients from 25 studies. To assess whether LOY components act through ovulation suppression alone, we compared beta coefficients obtained from regression models with expected estimates assuming 1 year of ovulation suppression has the same effect regardless of source. Results LOY was associated with increased EOC risk (OR per year increase = 1.014, 95% CI = 1.009 to 1.020 to OR per year increase = 1.044, 95% CI = 1.041 to 1.048). Individual LOY components, except age at menarche, also associated with EOC. The estimated model coefficient for oral contraceptive use and pregnancies were 4.45 times and 12- to 15-fold greater than expected, respectively. LOY was associated with high-grade serous, low-grade serous, endometrioid, and clear cell histotypes (ORs per year increase = 1.054, 1.040, 1.065, and 1.098, respectively) but not mucinous tumors. Estimated coefficients of LOY components were close to expected estimates for high-grade serous but larger than expected for low-grade serous, endometrioid, and clear cell histotypes. Conclusions LOY is positively associated with nonmucinous EOC. Differences between estimated and expected model coefficients for LOY components suggest factors beyond ovulation underlie the associations between LOY components and EOC in general and for non-HGSOC.
CRIS-Team WoS Importer:2023-04-21

Limitations in next-generation sequencing-based genotyping of breast cancer polygenic risk score loci - Baumann, Alexandra; Ruckert, Christian; Meier, Christoph; Hutschenreiter, Tim; Remy, Robert; Schnur, Benedikt; Döbel, Marvin; Fankep, Rudel Christian Nkouamedjo; Skowronek, Dariush; Kutz, Oliver; Arnold, Norbert; Katzke, Anna Lena; et al. (European Journal of Human Genetics, 2024)
Considering polygenic risk scores (PRSs) in individual risk prediction is increasingly implemented in genetic testing for hereditary breast cancer (BC) based on next-generation sequencing (NGS). To calculate individual BC risks, the Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA) with the inclusion of the BCAC 313 or the BRIDGES 306 BC PRS is commonly used. The PRS calculation depends on accurately reproducing the variant allele frequencies (AFs) and, consequently, the distribution of PRS values anticipated by the algorithm. Here, the 324 loci of the BCAC 313 and the BRIDGES 306 BC PRS were examined in population-specific database gnomAD and in real-world data sets of five centers of the German Consortium for Hereditary Breast and Ovarian Cancer (GC-HBOC), to determine whether these expected AFs can be reproduced by NGS-based genotyping. Four PRS loci were non-existent in gnomAD v3.1.2 non-Finnish Europeans, further 24 loci showed noticeably deviating AFs. In real-world data, between 11 and 23 loci were reported with noticeably deviating AFs, and were shown to have effects on final risk prediction. Deviations depended on the sequencing approach, variant caller and calling mode (forced versus unforced) employed. Therefore, this study demonstrates the necessity to apply quality assurance not only in terms of sequencing coverage but also observed AFs in a sufficiently large cohort, when implementing PRSs in a routine diagnostic setting. Furthermore, future PRS design should be guided by the technical reproducibility of expected AFs across commonly used genotyping methods, especially NGS, in addition to the observed effect sizes.
CRIS-Team Scopus Importer:2024-09-06

Linking the Neuropsychiatric Disease Gene TCF4 to Neuronal Activity-Dependent Regulatory Networks - Wittmann, Marie-Theres; Häberle, Benjamin (The Journal of Neuroscience, 2018)
EVALuna2:34134

Locally renewing resident synovial macrophages provide a protective barrier for the joint - Culemann, Stephan; Grüneboom, Anika; Nicolás-Ávila, José Ángel; Weidner, Daniela; Lämmle, Katrin Franziska; Rothe, Tobias; Quintana, Juan A.; Kirchner, Philipp; Krljanac, Branislav; Eberhardt, Martin; Ferrazzi, Fulvia; Kretzschmar, Elke; et al. (Nature, 2019)
Macrophages are considered to contribute to chronic inflammatory diseases such as rheumatoid arthritis1. However, both the exact origin and the role of macrophages in inflammatory joint disease remain unclear. Here we use fate-mapping approaches in conjunction with three-dimensional light-sheet fluorescence microscopy and single-cell RNA sequencing to perform a comprehensive spatiotemporal analysis of the composition, origin and differentiation of subsets of macrophages within healthy and inflamed joints, and study the roles of these macrophages during arthritis. We find that dynamic membrane-like structures, consisting of a distinct population of CX3CR1+ tissue-resident macrophages, form an internal immunological barrier at the synovial lining and physically seclude the joint. These barrier-forming macrophages display features that are otherwise typical of epithelial cells, and maintain their numbers through a pool of locally proliferating CX3CR1− mononuclear cells that are embedded into the synovial tissue. Unlike recruited monocyte-derived macrophages, which actively contribute to joint inflammation, these epithelial-like CX3CR1+ lining macrophages restrict the inflammatory reaction by providing a tight-junction-mediated shield for intra-articular structures. Our data reveal an unexpected functional diversification among synovial macrophages and have important implications for the general role of macrophages in health and disease.
CRIS-Team Scopus Importer:2019-08-16

Loss of function of SVBP leads to autosomal recessive intellectual disability, microcephaly, ataxia, and hypotonia - Iqbal, Zafar; Tawamie, Hasan; Ba, Wei; Reis, André; Halak, Bassam Al; Sticht, Heinrich; Uebe, Steffen; Kasri, Nael Nadif; Riazuddin, Sheikh; van Bokhoven, Hans; Abou Jamra, Rami (Genetics in Medicine, 2019)
Purpose: Identifying and characterizing novel causes of autosomal recessive intellectual disability based on systematic clinical and genetic evaluation, followed by functional experiments. Methods: Clinical examinations, genome-wide positional mapping, and sequencing were followed by quantitative polymerase chain reaction and western blot of the protein SVBP and its interaction partners. We then knocked down the gene in rat primary hippocampal neurons and evaluated the consequences on synapses. Results: We identified a founder, homozygous stop-gain variant in SVBP (c.82C>T; p.[Gln28*]) in four affected individuals from two independent families with intellectual disability, microcephaly, ataxia, and muscular hypotonia. SVBP encodes a small chaperone protein that transports and stabilizes two angiogenesis regulators, VASH1 and VASH2. The altered protein is unstable and nonfunctional since transfected HeLa cells with mutant SVBP did not reveal evidence for immunoreactive SVBP protein fragments and cotransfection with VASH1 showed a severe reduction of VASH1 in medium and cell lysate. Knocking down Svbp in rat primary hippocampal neurons led to a significant decrease in the number of excitatory synapses. Conclusion: SVBP is not only involved in angiogenesis, but also has vital functions in the central nervous system. Biallelic loss-of-function variants in SVBP lead to intellectual disability.
CRIS-Team Scopus Importer:2019-07-09
Keywords: CCD23; hippocampal neurons; intellectual disability; NGS; VASH1

Loss-of-function variants in HIVEP2 are a cause of intellectual disability - Srivastava, Siddharth; Engels, Hartmut; Schanze, Ina; Cremer, Kirsten; Wieland, Thomas; Menzel, Moritz; Schubach, Max; Biskup, Saskia; Kreiss, Martina; Endele, Sabine; Strom, Tim M.; Wieczorek, Dagmar; et al. (European journal of human genetics, 2016)
Intellectual disability (ID) affects 2-3% of the population. In the past, many genetic causes of ID remained unidentified due to its vast heterogeneity. Recently, whole exome sequencing (WES) studies have shown that de novo variants underlie a significant portion of sporadic cases of ID. Applying WES to patients with ID or global developmental delay at different centers, we identified three individuals with distinct de novo variants in HIVEP2 (human immunodeficiency virus type I enhancer binding protein), which belongs to a family of zinc-finger-containing transcriptional proteins involved in growth and development. Two of the variants were nonsense changes, and one was a 1 bp deletion resulting in a premature stop codon that was reported previously without clinical detail. In silico prediction programs suggest loss-of-function in the mutated allele leading to haploinsufficiency as a putative mechanism in all three individuals. All three patients presented with moderate-to-severe ID, minimal structural brain anomalies, hypotonia, and mild dysmorphic features. Growth parameters were in the normal range except for borderline microcephaly at birth in one patient. Two of the patients exhibited behavioral anomalies including hyperactivity and aggression. Published functional data suggest a neurodevelopmental role for HIVEP2, and several of the genes regulated by HIVEP2 are implicated in brain development, for example, SSTR-2, c-Myc, and genes of the NF-?B pathway. In addition, HIVEP2-knockout mice exhibit several working memory deficits, increased anxiety, and hyperactivity. On the basis of the genotype-phenotype correlation and existing functional data, we propose HIVEP2 as a causative ID gene.
EVALuna2:9305

Loss-of-function variants in SRRM2 cause a neurodevelopmental disorder - Cuinat, Silvestre; Nizon, Mathilde; Isidor, Bertrand; Stegmann, Alexander; van Jaarsveld, Richard H.; van Gassen, Koen L.; van der Smagt, Jasper J.; Volker-Touw, Catharina M.L.; Holwerda, Sjoerd J.B.; Terhal, Paulien A.; Schuhmann, Sarah; Vasileiou, Georgia; et al. (Genetics in Medicine, 2022)
Purpose: SRRM2 encodes the SRm300 protein, a splicing factor of the SR-related protein family characterized by its serine- and arginine-enriched domains. It promotes interactions between messenger RNA and the spliceosome catalytic machinery. This gene, predicted to be highly intolerant to loss of function (LoF) and very conserved through evolution, has not been previously reported in constitutive human disease. Methods: Among the 1000 probands studied with developmental delay and intellectual disability in our database, we found 2 patients with de novo LoF variants in SRRM2. Additional families were identified through GeneMatcher. Results: Here, we report on 22 patients with LoF variants in SRRM2 and provide a description of the phenotype. Molecular analysis identified 12 frameshift variants, 8 nonsense variants, and 2 microdeletions of 66 kb and 270 kb. The patients presented with a mild developmental delay, predominant speech delay, autistic or attention-deficit/hyperactivity disorder features, overfriendliness, generalized hypotonia, overweight, and dysmorphic facial features. Intellectual disability was variable and mild when present. Conclusion: We established SRRM2 as a gene responsible for a rare neurodevelopmental disease.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Intellectual disability; Molecular genetics; Neurodevelopment; Spliceosome; SRRM2

Loss-of-function variants of SETD5 cause intellectual disability and the core phenotype of microdeletion 3p25.3 syndrome - Kuechler, Alma; Zink, Alexander M.; Wieland, Thomas; Luedecke, Hermann-Josef; Cremer, Kirsten; Salviati, Leonardo; Magini, Pamela; Najafi, Kimia; Zweier, Christiane; Czeschik, Johanna Christina; Aretz, Stefan; Endele, Sabine; et al. (European journal of human genetics, 2015)
Intellectual disability (ID) has an estimated prevalence of 2-3%. Due to its extreme heterogeneity, the genetic basis of ID remains elusive in many cases. Recently, whole exome sequencing (WES) studies revealed that a large proportion of sporadic cases are caused by de novo gene variants. To identify further genes involved in ID, we performed WES in 250 patients with unexplained ID and their unaffected parents and included exomes of 51 previously sequenced child-parents trios in the analysis. Exome analysis revealed de novo intragenic variants in SET domain-containing 5 (SETD5) in two patients. One patient carried a nonsense variant, and the other an 81 bp deletion located across a splice-donor site. Chromosomal microarray diagnostics further identified four de novo non-recurrent microdeletions encompassing SETD5. CRISPR/Cas9 mutation modelling of the two intragenic variants demonstrated nonsense-mediated decay of the resulting transcripts, pointing to a loss-of-function (LoF) and haploinsufficiency as the common disease-causing mechanism of intragenic SETD5 sequence variants and SETD5-containing microdeletions. In silico domain prediction of SETD5, a predicted SET domain-containing histone methyltransferase (HMT), substantiated the presence of a SET domain and identified a novel putative PHD domain, strengthening a functional link to well-known histone-modifying ID genes. All six patients presented with ID and certain facial dysmorphisms, suggesting that SETD5 sequence variants contribute substantially to the microdeletion 3p25.3 phenotype. The present report of two SETD5 LoF variants in 301 patients demonstrates a prevalence of 0.7% and thus SETD5 variants as a relatively frequent cause of ID.
EVALuna2:9248

Loss of MTUS1/ATIP expression is associated with adverse outcome in advanced bladder carcinomas: data from a retrospective study - Rogler, Anja; Hoja, Sabine; Giedl, Josef; Ekici, Arif Bülent; Wach, Sven; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; et al. (BMC Cancer, 2014)
Seventy percent of all bladder tumours tend to recur and need intensive surveillance, and a subset of tumours progress to muscle-invasive and metastatic disease. However, it is still difficult to find the adequate treatment for every individual patient as it is a very heterogeneous disease and reliable biomarkers are still missing. In our study we searched for new target genes in the critical chromosomal region 8p and investigated the potential tumour suppressor gene candidate MTUS1/ATIP in bladder cancer.MTUS1 was identified to be the most promising deleted target gene at 8p in aCGH analysis with 19 papillary bladder tumours. A correlation with bladder cancer was further validated using immunohistochemistry of 85 papillary and 236 advanced bladder tumours and in functional experiments. Kaplan-Meier analysis and multivariate Cox-regression addressed overall survival (OS) and disease-specific survival (DSS) as a function of MTUS1/ATIP expression. Bivariate correlations investigated associations between MTUS1/ATIP expression, patient characteristics and histopathology. MTUS1 expression was analysed in cell lines and overexpressed in RT112, where impact on viability, proliferation and migration was measured.MTUS1 protein expression was lost in almost 50% of all papillary and advanced bladder cancers. Survival, however, was only influenced in advanced carcinomas, where loss of MTUS1 was associated with adverse OS and DSS. In this cohort, there was also a significant correlation of MTUS1 expression and histological subtype: positive expression was detected in all micropapillary tumours and aberrant nuclear staining was detected in a subset of plasmocytoid urothelial carcinomas. MTUS1 was expressed in all investigated bladder cell lines and overexpression in RT112 led to significantly decreased viability.MTUS1 is a tumour suppressor gene in cultured bladder cancer cells and in advanced bladder tumours. It might represent one new target gene at chromosome 8p and can be used as an independent prognostic factor for advanced bladder cancer patients. The limitation of the study is the retrospective data analysis. Thus, findings should be validated with a prospective advanced bladder tumour cohort.
EVALuna2:6624

Loss of PHF6 leads to aberrant development of human neuron-like cells - Fliedner, Anna; Gregor, Anne; Ferrazzi, Fulvia; Ekici, Arif Bülent; Sticht, Heinrich; Zweier, Christiane (Scientific Reports, 2020)
Pathogenic variants in PHD finger protein 6 (PHF6) cause Borjeson–Forssman–Lehmann syndrome (BFLS), a rare X-linked neurodevelopmental disorder, which manifests variably in both males and females. To investigate the mechanisms behind overlapping but distinct clinical aspects between genders, we assessed the consequences of individual variants with structural modelling and molecular techniques. We found evidence that de novo variants occurring in females are more severe and result in loss of PHF6, while inherited variants identified in males might be hypomorph or have weaker effects on protein stability. This might contribute to the different phenotypes in male versus female individuals with BFLS. Furthermore, we used CRISPR/Cas9 to induce knockout of PHF6 in SK-N-BE (2) cells which were then differentiated to neuron-like cells in order to model nervous system related consequences of PHF6 loss. Transcriptome analysis revealed a broad deregulation of genes involved in chromatin and transcriptional regulation as well as in axon and neuron development. Subsequently, we could demonstrate that PHF6 is indeed required for proper neuron proliferation, neurite outgrowth and migration. Impairment of these processes might therefore contribute to the neurodevelopmental and cognitive dysfunction in BFLS.
CRIS-Team Scopus Importer:2020-11-13

LOXL1 deficiency in the lamina cribrosa as candidate susceptibility factor for a pseudoexfoliation-specific risk of glaucoma - Schlötzer-Schrehardt, Ursula; Hammer, Christian; Krysta, Anita W.; Hofmann-Rummelt, Carmen; Pasutto, Francesca; Sasaki, Takako; Kruse, Friedrich; Zenkel, Matthias (Ophthalmology, 2012)
To test the hypothesis that a primary disturbance in lysyl oxidase-like 1 (LOXL1) and elastin metabolism in the lamina cribrosa of eyes with pseudoexfoliation syndrome constitutes an independent risk factor for glaucoma development and progression.Observational, consecutive case series.Posterior segment tissues obtained from 37 donors with early and late stages of pseudoexfoliation syndrome without glaucoma, 37 normal age-matched control subjects, 5 eyes with pseudoexfoliation-associated open-angle glaucoma, and 5 eyes with primary open-angle glaucoma (POAG).Protein and mRNA expression of major elastic fiber components (elastin, fibrillin-1, fibulin-4), collagens (types I, III, and IV), and lysyl oxidase crosslinking enzymes (LOX, LOXL1, LOXL2) were assessed in situ by quantitative real-time polymerase chain reaction, (immuno)histochemistry, and light and electron microscopy. Lysyl oxidase-dependent elastin fiber assembly was assessed by primary optic nerve head astrocytes in vitro.Expression levels of elastic proteins, collagens, and lysyl oxidases in the lamina cribrosa.Lysyl oxidase-like 1 proved to be the major lysyl oxidase isoform in the normal lamina cribrosa in association with a complex elastic fiber network. Compared with normal and POAG specimens, lamina cribrosa tissues obtained from early and late stages of pseudoexfoliation syndrome without and with glaucoma consistently revealed a significant coordinated downregulation of LOXL1 and elastic fiber constituents on mRNA and protein level. In contrast, expression levels of collagens and other lysyl oxidase isoforms were not affected. Dysregulated expression of LOXL1 and elastic proteins was associated with pronounced (ultra)structural alterations of the elastic fiber network in the laminar beams of pseudoexfoliation syndrome eyes. Inhibition of LOXL1 interfered with elastic fiber assembly by optic nerve head astrocytes in vitro.The findings provide evidence for a pseudoexfoliation-specific elastinopathy of the lamina cribrosa resulting from a primary disturbance in LOXL1 regulation and elastic fiber homeostasis, possibly rendering pseudoexfoliation syndrome eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development and progression.
EVALuna2:1645

LRRK2 knockout mice have an intact dopaminergic system but display alterations in exploratory and motor co-ordination behaviors. - Winner, Beate; Prots, Iryna; Hinkle, Kelly M; Yue, Mei; Bahareh, Behrouz; Dächsel, Justus C; Lincoln, Sarah J; Bowles, Erin E; Beevers, Joel E; Dugger, Brittany; Kent, Caroline B; Nishioka, Kenya; et al. (Molecular Neurodegeneration, 2012)
Mutations in the LRRK2 gene are the most common cause of genetic Parkinson's disease. Although the mechanisms behind the pathogenic effects of LRRK2 mutations are still not clear, data emerging from in vitro and in vivo models suggests roles in regulating neuronal polarity, neurotransmission, membrane and cytoskeletal dynamics and protein degradation.We created mice lacking exon 41 that encodes the activation hinge of the kinase domain of LRRK2. We have performed a comprehensive analysis of these mice up to 20 months of age, including evaluation of dopamine storage, release, uptake and synthesis, behavioral testing, dendritic spine and proliferation/neurogenesis analysis.Our results show that the dopaminergic system was not functionally comprised in LRRK2 knockout mice. However, LRRK2 knockout mice displayed abnormal exploratory activity in the open-field test. Moreover, LRRK2 knockout mice stayed longer than their wild type littermates on the accelerated rod during rotarod testing. Finally, we confirm that loss of LRRK2 caused degeneration in the kidney, accompanied by a progressive enhancement of autophagic activity and accumulation of autofluorescent material, but without evidence of biphasic changes.
EVALuna2:26219
Keywords: Parkinson’s disease; Knockout; Dopamine; Microdialysis; Neuropathology; Open-field; Motor co-ordination; Kidney; Autophagy

Lymphocyte Immune Response and T Cell Differentiation in Fontan Patients with protein-losing enteropathy - Moosmann, Julia; Toka, Okan; Lukassen, Sören; Ekici, Arif Bülent; Mackensen, Andreas; Dittrich, Sven; Völkl, Simon (Thoracic and Cardiovascular Surgeon, Supplement, 2021)
Background Protein-losing enteropathy (PLE) is a severe complication of the Fontan circulation. There is increasing discussion about whether lymphatic dysregulation is involved as pathomechanism of PLE. This investigation focuses on the interplay between alteration of lymphatic cells and immunologic pathway alterations. Methods Micro-ribonucleic acid (miRNA) expression profiling was performed in 49 patients (n = 10 Fontan patients with PLE, n = 30 Fontan patients without PLE, and n = 9 patients with dextro-transposition of the great arteries (dTGA). miRNA pathway analysis was performed to identify significantly enriched pathways. To determine lymphocyte populations and subtypes multiparameter flow cytometry was used. Results miRNAs pathway analysis of Fontan patients with PLE revealed 20 significantly changed networks of which four of the ten largest were associated with immunologic processes. This finding is supported by significant T cell deficiency with decreased CD4+ count (p = 0.0002), altered CD4 +/CD8+ ratio, and significantly modified CD4+ (p < 0.0001) and CD8+ (p = 0.0002) T cell differentiation toward effector and terminal differentiated T cells in Fontan patients with PLE. Analyses of CD4+ T cell subsets demonstrated significantly increased frequencies of CD4+ CD25+ CD127- regulatory T cells (Treg) in Fontan patients with PLE (p = 0.0011). Conclusion PLE in Fontan patients is associated with severe lymphopenia, T cell deficiency, significant alterations of T cell differentiation, and increased Treg frequency reflecting an immune status of chronic inflammation and shortened protection against pathogens and autoimmunity. These cellular alterations seemed to be dysregulated by several miRNA controlled immunological pathways.
CRIS-Team Scopus Importer:2021-03-05
Keywords: congenital heart disease (CHD); genetics; genomics; inflammation; systemic

Macrophage migration inhibitory factor is regulated by HIF-1α and cAMP and promotes renal cyst cell proliferation in a macrophage-independent manner - Safi, Wajima; Kraus, Andre; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (Journal of Molecular Medicine, 2020)
Abstract: Progressive cyst growth leads to decline of renal function in polycystic kidney disease. Macrophage migration inhibitory factor (MIF) was found to be upregulated in cyst-lining cells in a mouse model of polycystic kidney disease and to promote cyst growth. In addition, MIF can be secreted by tubular cells and may contribute to cyst growth in an autocrine manner. However, the underlying mechanisms leading to induction of MIF in cyst-lining cells remained elusive. Here, we demonstrate that hypoxia-inducible transcription factor (HIF) 1α upregulates MIF in cyst-lining cells in a tubule-specific PKD1 knockout mouse. Pharmacological stabilization of HIF-1α resulted in significant increase of MIF in cyst epithelial cells whereas tubule-specific knockout of HIF-1α prevented MIF upregulation. Identical regulation could be found for ABCA1, which has been shown to act as a transport protein for MIF. Furthermore, we show that MIF and ABCA1 are direct target genes of HIF-1α in human primary tubular cells. Next to HIF-1α and hypoxia, we found MIF being additionally regulated by cAMP which is a strong promotor of cyst growth. In line with these findings, HIF-1α- and cAMP-dependent in vitro cyst growth could be decreased by the MIF-inhibitor ISO-1 which resulted in reduced cyst cell proliferation. In conclusion, HIF-1α and cAMP regulate MIF in primary tubular cells and cyst-lining epithelial cells, and MIF promotes cyst growth in the absence of macrophages. In line with these findings, the MIF inhibitor ISO-1 attenuates HIF-1α- and cAMP-dependent in vitro cyst enlargement. Key messages: • MIF is upregulated in cyst-lining cells in a polycystic kidney disease mouse model. • MIF upregulation is mediated by hypoxia-inducible transcription factor (HIF) 1α. • ABCA1, transport protein for MIF, is also regulated by HIF-1α in vitro and in vivo. • MIF is additionally regulated by cAMP, a strong promotor of cyst growth. • MIF-inhibitor ISO-1 reduces HIF-1α- and cAMP-dependent cyst growth.
CRIS-Team Scopus Importer:2020-09-11
Keywords: cAMP; Hypoxia-inducible factor 1α; Macrophage migration inhibitory factor; Polycystic kidney disease

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Magnetic Tissue Engineering of the Vocal Fold Using Superparamagnetic Iron Oxide Nanoparticles - Poettler, Marina; Fliedner, Anna; Bergmann, Julia; Bui, Linh Katrin; Mühlberger, Marina; Braun, Christian; Graw, Matthias; Janko, Christina; Friedrich, Oliver; Alexiou, Christoph; Lyer, Stefan (Tissue Engineering: Parts A, B, and C, 2019)
Losing one's ability to speak, because of tissue deficiency at the vocal fold (VF), leads to serious impairment in the quality of life. Until now, there is no successful approach for regenerating the VF. The aim of this study was to show the advantage of magnetic nanoparticles in the generation of scaffold-free three-dimensional (3D) VF cell constructs by magnetic tissue engineering (MTE). Rabbit VF fibroblasts were used to establish MTE: after cellular uptake of superparamagnetic iron oxide nanoparticles (SPIONs), cells can be controlled with a magnetic field thereby forming solid 3D cell structures. To transfer this method into human cells, SPIONs were adapted accordingly and tested for their influence on human VF (hVF) cells and for their ability to perform MTE with hVF cells. Of interest, the cell number and the magnet's shape influence the form of the rabbit VF cell construct. After successful characterization of hVF cells, biocompatibility analyses revealed no significant influence of SPIONs on them, thus 3D hVF cell constructs could be successfully generated by MTE. These basic results are important to develop MTE as an innovative method to regenerate functional VFs. We expect that in vivo studies, including MTE as an elegant, far-field controlled and touchless technology, will translate MTE VF bioconstructs into reconstructive laryngeal medicine. Impact Statement This study aims at nanotechnology for regenerative medicine by magnetic tissue engineering (MTE). New approaches for vocal fold (VF) reconstruction are desperately needed. Superparamagnetic iron oxide nanoparticles offer innovative, scaffold-free potentials for tissue engineering: MTE. By using MTE we could generate functional multilayered human VF cell constructs, which can consequently be used to regenerate the voice in patients with VF injuries.
CRIS-Team WoS Importer:2019-05-14

MAN1B1 Mutation Leads to a Recognizable Phenotype: A Case Report and Future Prospects - Hoffjan, Sabine; Epplen, Jörg T.; Reis, André; Abou Jamra, Rami (Molecular Syndromology, 2015)
Intellectual disability (ID) is one of the most common reasons for referral to genetic counseling. Nevertheless, in over 50% of the cases no diagnosis can be made. Here, we present how exome sequencing in combination with medical genetics evaluation led to the identification of a known pathogenic homozygous mutation in MAN1B1 in a consanguineous Turkish family. The phenotype comprised mild ID, truncal obesity and facial dysmorphism, comparable to that of the patients in the 3 recent publications on mutations in this gene. Clinically, the majority of patients in the literature showed congenital disorder of glycosylation syndrome type 2. In this study, we summarize the current knowledge about MAN1B1 mutations from the literature as well as databases and suggest that exome sequencing should be implemented in a larger scale in routine diagnostics, since autosomal recessive ID has proven to be extremely heterogeneous. Even syndromic patterns may only become recognizable retrospectively.
EVALuna2:9262

MANAGEMENT OF INSUFFICIENT FUNCTIONAL ANTITHROMBOTIC ACTIVITY DURING TREATMENT WITH DIRECT ORAL ANTICOAGULANTS FOR STROKE PREVENTION - Macha, Kosmas; Stoll, Svenja; Siedler, Gabriela; Volbers, Bastian; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Manifestation of epilepsy in a patient with EED-related overgrowth (Cohen-Gibson syndrome) - Hetzelt, Katalin; Winterholler, Martin; Kerling, Frank; Rauch, Christophe; Ekici, Arif Bülent; Winterpacht, Andreas; Vasileiou, Georgia; Uebe, Steffen; Thiel, Christian; Kraus, Cornelia; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2021)
Cohen-Gibson syndrome is a rare genetic disorder, characterized by fetal or early childhood overgrowth and mild to severe intellectual disability. It is caused by heterozygous aberrations in EED, which encodes an evolutionary conserved polycomb group (PcG) protein that forms the polycomb repressive complex-2 (PRC2) together with EZH2, SUZ12, and RBBP7/4. In total, 11 affected individuals with heterozygous pathogenic variants in EED were reported, so far. All variants affect a few key residues within the EED WD40 repeat domain. By trio exome sequencing, we identified the heterozygous missense variant c.581A > G, p.(Asn194Ser) in exon 6 of the EED-gene in an individual with moderate intellectual disability, overgrowth, and epilepsy. The same pathogenic variant was detected in 2 of the 11 previously reported cases. Epilepsy, however, was only diagnosed in one other individual with Cohen-Gibson syndrome before. Our findings further confirm that the WD40 repeat domain represents a mutational hotspot; they also expand the clinical spectrum of Cohen-Gibson syndrome and highlight the clinical variability even in individuals with the same pathogenic variant. Furthermore, they indicate a possible association between Cohen-Gibson syndrome and epilepsy.
CRIS-Team WoS Importer:2021-09-24

Mannan-induced Nos2 in macrophages enhances IL-17-driven psoriatic arthritis by innate lymphocytes - Zhong, Jianghong; Scholz, Tatjana; Yau, Anthony C. Y.; Guerard, Simon; Hüffmeier, Ulrike; Burkhardt, Harald; Holmdahl, Rikard (Science Advances, 2018)
Previous identification of the inducible nitric oxide synthase (NOS2) gene as a risk allele for psoriasis (Ps) and psoriatic arthritis (PsA) suggests a possible pathogenic role of nitric oxide (NO). Using a mouse model of mannan-induced Ps and PsA (MIP), where macrophages play a regulatory role by releasing reactive oxygen species (ROS), we found that NO was detectable before disease onset in mice, independent of a functional nicotinamide adenine dinucleotide phosphate oxidase 2 complex. MIP was suppressed by either deletion of Nos2 or inhibition of NO synthases with NG-nitro-l-arginine methyl ester, demonstrating that Nos2-derived NO is pathogenic. NOS2 expression was also up-regulated in lipopolysaccharide- and interferon-γ-stimulated monocyte subsets from patients with PsA compared to healthy controls. Nos2-dependent interleukin-1α (IL-1α) release from skin macrophages was essential for arthritis development by promoting IL-17 production of innate lymphoid cells. We conclude that Nos2-derived NO by tissue macrophages promotes MIP, in contrast to the protective effect by ROS.
EVALuna2:34636

MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244

Matrilin-1 is essential for zebrafish development by facilitating collagen II secretion - Neacsu, Cristian Dan; Ko, Ya-Ping; Tagariello, Andreas; Karlsen, Kristina Rokenes; Neiss, Wolfram Friedrich; Paulsson, Mats; Wagener, Raimund (Journal of Biological Chemistry, 2014)
Matrilin-1 is the prototypical member of the matrilin protein family and is highly expressed in cartilage. However, gene targeting of matrilin-1 in mouse did not lead to pronounced phenotypes. Here we used the zebrafish as an alternative model to study matrilin function in vivo. Matrilin-1 displays a multiphasic expression during zebrafish development. In an early phase, with peak expression at about 15 h post-fertilization, matrilin-1 is present throughout the zebrafish embryo with exception of the notochord. Later, when the skeleton develops, matrilin-1 is expressed mainly in cartilage. Morpholino knockdown of matrilin-1 results both in overall growth defects and in disturbances in the formation of the craniofacial cartilage, most prominently loss of collagen II deposition. In fish with mild phenotypes, certain cartilage extracellular matrix components were present, but the tissue did not show features characteristic for cartilage. The cells showed endoplasmic reticulum aberrations but no activation of XBP-1, a marker for endoplasmic reticulum stress. In severe phenotypes nearly all chondrocytes died. During the early expression phase the matrilin-1 knockdown had no effects on cell morphology, but increased cell death was observed. In addition, the broad deposition of collagen II was largely abolished. Interestingly, the early phenotype could be rescued by the co-injection of mRNA coding for the von Willebrand factor C domain of collagen II?1a, indicating that the functional loss of this domain occurs as a consequence of matrilin-1 deficiency. The results show that matrilin-1 is indispensible for zebrafish cartilage formation and plays a role in the early collagen II-dependent developmental events.
EVALuna2:9239

Mechanism of KMT5B haploinsufficiency in neurodevelopment in humans and mice - Sheppard, Sarah E.; Bryant, Laura; Wickramasekara, Rochelle N.; Vaccaro, Courtney; Robertson, Brynn; Hallgren, Jodi; Hulen, Jason; Watson, Cynthia J.; Faundes, Victor; Duffourd, Yannis; Lee, Pearl; Celeste Simon, M.; et al. (Science Advances, 2023)
Pathogenic variants in KMT5B, a lysine methyltransferase, are associated with global developmental delay, macrocephaly, autism, and congenital anomalies (OMIM# 617788). Given the relatively recent discovery of this disorder, it has not been fully characterized. Deep phenotyping of the largest (n = 43) patient cohort to date identified that hypotonia and congenital heart defects are prominent features that were previously not associated with this syndrome. Both missense variants and putative loss-of-function variants resulted in slow growth in patient-derived cell lines. KMT5B homozygous knockout mice were smaller in size than their wild-type littermates but did not have significantly smaller brains, suggesting relative macrocephaly, also noted as a prominent clinical feature. RNA sequencing of patient lymphoblasts and Kmt5b haploinsufficient mouse brains identified differentially expressed pathways associated with nervous system development and function including axon guidance signaling. Overall, we identified additional pathogenic variants and clinical features in KMT5Brelated neurodevelopmental disorder and provide insights into the molecular mechanisms of the disorder using multiple model systems.
CRIS-Team Scopus Importer:2023-03-24

Mechanistic basis of an epistatic interaction reducing age at onset in hereditary spastic paraplegia - Newton, Timothy; Allison, Rachel; Edgar, James R.; Lumb, Jennifer H.; Rodger, Catherine E.; Manna, Paul T.; Rizo, Tania; Kohl, Zacharias; Nygren, Anders O. H.; Arning, Larissa; Schuele, Rebecca; Depienne, Christel; et al. (Brain, 2018)
Many genetic neurological disorders exhibit variable expression within affected families, often exemplified by variations in disease age at onset. Epistatic effects (i.e. effects of modifier genes on the disease gene) may underlie this variation, but the mechanistic basis for such epistatic interactions is rarely understood. Here we report a novel epistatic interaction between SPAST and the contiguous gene DPY30, which modifies age at onset in hereditary spastic paraplegia, a genetic axonopathy. We found that patients with hereditary spastic paraplegia caused by genomic deletions of SPAST that extended into DPY30 had a significantly younger age at onset. We show that, like spastin, the protein encoded by SPAST, the DPY30 protein controls endosomal tubule fission, traffic of mannose 6-phosphate receptors from endosomes to the Golgi, and lysosomal ultrastructural morphology. We propose that additive effects on this pathway explain the reduced age at onset of hereditary spastic paraplegia in patients who are haploinsufficient for both genes.
EVALuna2:35784

Mendelian randomization analyses suggest a role for cholesterol in the development of endometrial cancer - Kho, Pik Fang; Amant, Frederic; Annibali, Daniela; Ashton, Katie; Attia, John; Auer, Paul L.; Beckmann, Matthias; Black, Amanda; Brinton, Louise; Buchanan, Daniel D.; Chanock, Stephen J.; Chen, Chu; et al. (International Journal of Cancer, 2020)
Blood lipids have been associated with the development of a range of cancers, including breast, lung and colorectal cancer. For endometrial cancer, observational studies have reported inconsistent associations between blood lipids and cancer risk. To reduce biases from unmeasured confounding, we performed a bidirectional, two-sample Mendelian randomization analysis to investigate the relationship between levels of three blood lipids (low-density lipoprotein [LDL] and high-density lipoprotein [HDL] cholesterol, and triglycerides) and endometrial cancer risk. Genetic variants associated with each of these blood lipid levels (P < 5 × 10−8) were identified as instrumental variables, and assessed using genome-wide association study data from the Endometrial Cancer Association Consortium (12 906 cases and 108 979 controls) and the Global Lipids Genetic Consortium (n = 188 578). Mendelian randomization analyses found genetically raised LDL cholesterol levels to be associated with lower risks of endometrial cancer of all histologies combined, and of endometrioid and non-endometrioid subtypes. Conversely, higher genetically predicted HDL cholesterol levels were associated with increased risk of non-endometrioid endometrial cancer. After accounting for the potential confounding role of obesity (as measured by genetic variants associated with body mass index), the association between genetically predicted increased LDL cholesterol levels and lower endometrial cancer risk remained significant, especially for non-endometrioid endometrial cancer. There was no evidence to support a role for triglycerides in endometrial cancer development. Our study supports a role for LDL and HDL cholesterol in the development of non-endometrioid endometrial cancer. Further studies are required to understand the mechanisms underlying these findings.
CRIS-Team Scopus Importer:2020-08-14
Keywords: endometrial cancer risk; HDL cholesterol; LDL cholesterol; Mendelian randomization; triglycerides

Meta-analyses identify DNA methylation associated with kidney function and damage - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Adeyemo, Adebowale A.; et al. (Nature Communications, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
CRIS-Team WoS Importer:2021-12-17

Meta-analysis of genome-wide association studies identifies common susceptibility polymorphisms for colorectal and endometrial cancer near SH2B3 and TSHZ1 - Cheng, Timothy H. T.; Thompson, Deborah; Painter, Jodie; O'Mara, Tracy; Gorman, Maggie; Martin, Lynn; Palles, Claire; Jones, Angela; Buchanan, Daniel D.; Win, Aung Ko; Hopper, John; Jenkins, Mark; et al. (Scientific Reports, 2015)
High-risk mutations in several genes predispose to both colorectal cancer (CRC) and endometrial cancer (EC). We therefore hypothesised that some lower-risk genetic variants might also predispose to both CRC and EC. Using CRC and EC genome-wide association series, totalling 13,265 cancer cases and 40,245 controls, we found that the protective allele [G] at one previously-identified CRC polymorphism, rs2736100 near TERT, was associated with EC risk (odds ratio (OR) = 1.08, P = 0.000167); this polymorphism influences the risk of several other cancers. A further CRC polymorphism near TERC also showed evidence of association with EC (OR = 0.92; P = 0.03). Overall, however, there was no good evidence that the set of CRC polymorphisms was associated with EC risk, and neither of two previously-reported EC polymorphisms was associated with CRC risk. A combined analysis revealed one genome-wide significant polymorphism, rs3184504, on chromosome 12q24 (OR = 1.10, P = 7.23 × 10(-9)) with shared effects on CRC and EC risk. This polymorphism, a missense variant in the gene SH2B3, is also associated with haematological and autoimmune disorders, suggesting that it influences cancer risk through the immune response. Another polymorphism, rs12970291 near gene TSHZ1, was associated with both CRC and EC (OR = 1.26, P = 4.82 × 10(-8)), with the alleles showing opposite effects on the risks of the two cancers.
EVALuna2:9303

Metabolic rewiring controlled by HIF-1α tunes IgA-producing B-cell differentiation and intestinal inflammation - Meng, Xianyi; Asadi Asadabad, Sahar; Cao, Shan; Song, Rui; Lin, Zhen; Safhi, Mohammed; Qin, Yi; Tcheumi Tactoum, Estelle Manuella; Taudte, Verena; Ekici, Arif Bülent; Mielenz, Dirk; Wirtz, Stefan; et al. (Cellular & Molecular Immunology, 2024)
Germinal centers where B cells undergo clonal expansion and antibody affinity maturation are hypoxic microenvironments. However, the function of hypoxia-inducible factor (HIF)-1α in immunoglobulin production remains incompletely characterized. Here, we demonstrated that B cells lacking HIF-1α exhibited significantly lower glycolytic metabolism and impaired IgA production. Loss of HIF-1α in B cells affects IgA-producing B-cell differentiation and exacerbates dextran sodium sulfate (DSS)-induced colitis. Conversely, promoting HIF-1α stabilization via a PHD inhibitor roxadustat enhances IgA class switching and alleviates intestinal inflammation. Mechanistically, HIF-1α facilitates IgA class switching through acetyl-coenzyme A (acetyl-CoA) accumulation, which is essential for histone H3K27 acetylation at the Sα region. Consequently, supplementation with acetyl-CoA improved defective IgA production in Hif1a-deficient B cells and limited experimental colitis. Collectively, these findings highlight the critical importance of HIF-1α in IgA class switching and the potential for targeting the HIF-1α-dependent metabolic‒epigenetic axis to treat inflammatory bowel diseases and other inflammatory disorders.
CRIS-Team Scopus Importer:2024-11-22
Keywords: B cells; HIF-1α; Hypoxia; IgA; Intestinal inflammation

Microdeletions at 19p13.11 in four individuals with neurodevelopmental delay - Rieger, Melissa; Moutton, Sebastien; Verheyen, Sarah; Speicher, Michael; Leheup, Bruno; Bonnet, Celine; Steindl, Katharina; Boneda, Beatrice; Rauch, Anita; Krumbiegel, Mandy; Reis, André; Hüffmeier, Ulrike (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Microdeletions at 19p13.11p12 in five individuals with neurodevelopmental delay - Rieger, Melissa; Moutton, Sébastien; Verheyen, Sarah; Steindl, Katharina; Popp, Bernt; Leheup, Bruno; Bonnet, Céline; Oneda, Beatrice; Rauch, Anita; Reis, André; Krumbiegel, Mandy; Hüffmeier, Ulrike (European Journal of Medical Genetics, 2023)
Only few copy number variants at chromosome 19p13.11 have been reported, thus associated clinical information is scarce. Proximal to these copy number losses, we now identified deletions in five unrelated individuals with neurodevelopmental disorders. They presented with psychomotor delay as well as behavioral and sleeping disorders, while complex cardiovascular, skeletal, and various other malformations were more variable. Dysmorphic features were rather unspecific and not considered as a recognizable gestalt. Neither of the analyzed parents carried their offsprings' deletions, indicating de novo occurrence. The deletion sizes ranged between 0.7 and 5.2 Mb, were located between 18 and 24 megabases from the telomere, and contained a variable number of protein-coding genes (n = 25–68). Although not all microdeletions shared a common region, the smallest common overlap of some of the deletions provided interesting insights in the chromosomal region 19p13.11p12. Diligent literature review using OMIM and Pubmed did not identify a satisfying candidate gene for neurodevelopmental disorders. In the literature, a de novo in-frame deletion in MAU2 was considered pathogenic in an individual with Cornelia de Lange syndrome. Therefore, the clinical differential diagnosis of this latter syndrome in one individual and the encompassment of MAU2 in three individuals' deletions suggest clinical and genetic overlap with this specific syndrome. Three of the four here reported individuals with deletion encompassing GDF1 had different congenital heart defects, suggesting that this gene's haploinsufficiency might contribute to the cardiovascular phenotype, however, with reduced penetrance. Our findings indicate an association of microdeletions at 19p13.11/ 19p13.11p12 with neurodevelopmental disorders, variable symptoms, and malformations, and delineate the phenotypic spectrum of deletions within this genomic region.
CRIS-Team Scopus Importer:2022-12-16
Keywords: 19p13.11p12; Deletion; GDF1; Malformation; MAU2; NDD

Microphthalmia is not a mandatory finding in X-linked recessive syndromic microphthalmia caused by the recurrent BCOR variant p.Pro85Leu - Kraus, Cornelia; Uebe, Steffen; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2018)
Mutations in BCOR cause X-linked dominant and X-linked recessive forms of syndromic microphthalmia. By exome sequencing, we identified the recurrent BCOR mutation p.Pro85Leu in two brothers and their unaffected mother. While the older brother's phenotype completely fits the described phenotypic spectrum of X-linked recessive BCOR-associated Lenz microphthalmia syndrome, the younger brother showed developmental delay, microcephaly, and skeletal anomalies, but not the key feature of microphthalmia. In contrast to the previously published families, our findings demonstrate a large variability of BCOR-associated, syndromic phenotypes, indicating incomplete penetrance of p.Pro85Leu with regards to microphthalmia in males.
EVALuna2:34843

MicroRNA Related Polymorphisms and Breast Cancer Risk - Khan, Sofia; Greco, Dario; Michailidou, Kyriaki; Milne, Roger L.; Muranen, Taru A.; Heikkinen, Tuomas; Aaltonen, Kirsimari; Dennis, Joe; Bolla, Manjeet K.; Liu, Jianjun; Hall, Per; Irwanto, Astrid; et al. (PLoS ONE, 2014)
Genetic variations, such as single nucleotide polymorphisms (SNPs) in microRNAs (miRNA) or in the miRNA binding sites may affect the miRNA dependent gene expression regulation, which has been implicated in various cancers, including breast cancer, and may alter individual susceptibility to cancer. We investigated associations between miRNA related SNPs and breast cancer risk. First we evaluated 2,196 SNPs in a case-control study combining nine genome wide association studies (GWAS). Second, we further investigated 42 SNPs with suggestive evidence for association using 41,785 cases and 41,880 controls from 41 studies included in the Breast Cancer Association Consortium (BCAC). Combining the GWAS and BCAC data within a meta-analysis, we estimated main effects on breast cancer risk as well as risks for estrogen receptor (ER) and age defined subgroups. Five miRNA binding site SNPs associated significantly with breast cancer risk: rs1045494 (odds ratio (OR) 0.92; 95% confidence interval (CI): 0.88-0.96), rs1052532 (OR 0.97; 95% CI: 0.95-0.99), rs10719 (OR 0.97; 95% CI: 0.94-0.99), rs4687554 (OR 0.97; 95% CI: 0.95-0.99, and rs3134615 (OR 1.03; 95% CI: 1.01-1.05) located in the 3' UTR of CASP8, HDDC3, DROSHA, MUSTN1, and MYCL1, respectively. DROSHA belongs to miRNA machinery genes and has a central role in initial miRNA processing. The remaining genes are involved in different molecular functions, including apoptosis and gene expression regulation. Further studies are warranted to elucidate whether the miRNA binding site SNPs are the causative variants for the observed risk effects.
EVALuna2:9235

Midkine is a tumor cell survival factor that displays metastatic and therapeutic resistance functions in uveal melanoma - Karg, Margarete; John, Lukas; Refaian, Narin; Büttner, Christian; Rottmar, Tanja; Sommer, Jonas; Bock, Barbara; Resheq, Yazid; Ksander, Bruce; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Midkine Promotes Metastasis and Therapeutic Resistance via mTOR/RPS6 in Uveal Melanoma. - Karg, Margarete; John, Lukas; Refaian, Nasrin; Büttner, Christian; Rottmar, Tanja; Sommer, Jonas; Bock, Barbara; Resheq, Yazid; Ksander, Bruce R.; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Molecular Cancer Research, 2022)
Uveal melanoma is a rare form of melanoma that originates in the eye, exerts widespread therapeutic resistance, and displays an inherent propensity for hepatic metastases. Because metastatic disease is characterized by poor survival, there is an unmet clinical need to identify new therapeutic targets in uveal melanoma. Here, we show that the pleiotropic cytokine midkine is expressed in uveal melanoma. Midkine expression in primary uveal melanoma significantly correlates with poor survival and is elevated in patients that develop metastatic disease. Monosomy 3 and histopathologic staging parameters are associated with midkine expression. In addition, we demonstrate that midkine promotes survival, migration across a barrier of hepatic sinusoid endothelial cells and resistance to AKT/mTOR inhibition. Furthermore, midkine is secreted and mediates mTOR activation by maintaining phosphorylation of the mTOR target RPS6 in uveal melanoma cells. Therefore, midkine is identified as a uveal melanoma cell survival factor that drives metastasis and therapeutic resistance, and could be exploited as a biomarker as well as a new therapeutic target. IMPLICATIONS: Midkine is identified as a survival factor that drives liver metastasis and therapeutic resistance in melanoma of the eye.
EVALuna2:503899

MiR-29 related deposition of extracellular matrix in Fuchs endothelial corneal dystrophy - Matthaei, Mario; Clahsen, Thomas; Büttner, Christian; Ekici, Arif Bülent; Siebelmann, Sebastian; Heindl, Ludwig M.; Bachmann, Bjoern; Cursiefen, Claus; Hribek, Agathe (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Missense variants in NDD-associated FBXO11 impair its localization and Fbxo11 deficiency leads to neuronal impairment in Drosophila melanogaster - Gregor, Anne; Meerbrei, T.; Distel, Luitpold; Gerstner, T.; Gupta, A.; Toutain, A.; Lynch, S. A.; Maxton, C.; Lemke, J. R.; Bernat, J. A.; Bombei, H. M.; Foulds, N.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Missense Variants in RHOBTB2 Cause a Developmental and Epileptic Encephalopathy in Humans, and Altered Levels Cause Neurological Defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, Annick; Bok, Levinus A.; Cho, Megan T.; Crawford, Heather P.; Dubbs, Holly; Douglas, Ganka; Jobling, Rebekah; Johnson, Diana; Krock, Bryan; et al. (American Journal of Human Genetics, 2018)
Although the role of typical Rho GTPases and other Rho-linked proteins in synaptic plasticity and cognitive function and dysfunction is widely acknowledged, the role of atypical Rho GTPases (such as RHOBTB2) in neurodevelopment has barely been characterized. We have now identified de novo missense variants clustering in the BTB-domain-encoding region of RHOBTB2 in ten individuals with a similar phenotype, including early-onset epilepsy, severe intellectual disability, postnatal microcephaly, and movement disorders. Three of the variants were recurrent. Upon transfection of HEK293 cells, we found that mutant RHOBTB2 was more abundant than the wild-type, most likely because of impaired degradation in the proteasome. Similarly, elevated amounts of the Drosophila ortholog RhoBTB in vivo were associated with seizure susceptibility and severe locomotor defects. Knockdown of RhoBTB in the Drosophila dendritic arborization neurons resulted in a decreased number of dendrites, thus suggesting a role of RhoBTB in dendritic development. We have established missense variants in the BTB-domain-encoding region of RHOBTB2 as causative for a developmental and epileptic encephalopathy and have elucidated the role of atypical Rho GTPase RhoBTB in Drosophila neurological function and possibly dendrite development.
EVALuna2:33715

Mitochondrial DNA copy number is associated with mortality and infections in a large cohort of patients with chronic kidney disease - Fazzini, Federica; Lamina, Claudia; Fendt, Liane; Schultheiss, Ulla T.; Kotsis, Fruzsina; Hicks, Andrew A.; Meiselbach, Heike; Weissensteiner, Hansi; Forer, Lukas; Krane, Vera; Eckardt, Kai-Uwe; Köttgen, Anna; et al. (Kidney International, 2019)
Damage of mitochondrial DNA (mtDNA) with reduction in copy number has been proposed as a biomarker for mitochondrial dysfunction and oxidative stress. Chronic kidney disease (CKD) is associated with increased mortality and risk of cardiovascular disease, but the underlying mechanisms remain incompletely understood. Here we investigated the prognostic role of mtDNA copy number for cause-specific mortality in 4812 patients from the German Chronic Kidney Disease study, an ongoing prospective observational national cohort study of patients with CKD stage G3 and A1-3 or G1-2 with overt proteinuria (A3) at enrollment. MtDNA was quantified in whole blood using a plasmid-normalized PCR-based assay. At baseline, 1235 patients had prevalent cardiovascular disease. These patients had a significantly lower mtDNA copy number than patients without cardiovascular disease (fully-adjusted model: odds ratio 1.03, 95% confidence interval [CI] 1.01-1.05 per 10 mtDNA copies decrease). After four years of follow-up, we observed a significant inverse association between mtDNA copy number and all-cause mortality, adjusted for kidney function and cardiovascular disease risk factors (hazard ratio 1.37, 95% CI 1.09-1.73 for quartile 1 compared to quartiles 2-4). When grouped by causes of death, estimates pointed in the same direction for all causes but in a fully-adjusted model decreased copy numbers were significantly lower only in infection-related death (hazard ratio 1.82, 95% CI 1.08-3.08). A similar association was observed for hospitalizations due to infections in 644 patients (hazard ratio 1.19, 95% CI 1.00-1.42 in the fully-adjusted model). Thus, our data support a role of mitochondrial dysfunction in increased cardiovascular disease and mortality risks as well as susceptibility to infections in patients with CKD.
CRIS-Team Scopus Importer:2019-07-02
Keywords: chronic kidney disease; infections; mitochondrial DNA copy number; mortality

Modeling Cell-Cell Interactions in Parkinson's Disease Using Human Stem Cell-Based Models. - Rizo Garza, Tania; Simmnacher, Katrin; Lanfer, Jonas; Rizo, Tania; Kaindl, Johanna; Winner, Beate (Frontiers in Cellular Neuroscience, 2019)
models of PD, focusing on those phenotypes that have been detected in genetic and sporadic PD models. An additional point covered in this review will be the use of induced pluripotent stem cell (iPSC)-derived technologies to model cell-cell interactions in PD.

Modeling Cell-Cell Interactions in Parkinson’s Disease Using Human Stem Cell-Based Models - Simmnacher, Katrin; Lanfer, Jonas; Rizo, Tania; Kaindl, Johanna; Winner, Beate (Frontiers in Cellular Neuroscience, 2020)
Parkinson’s disease (PD) is the most frequently occurring movement disorder, with an increasing incidence due to an aging population. For many years, the post-mortem brain was regarded as the gold standard for the analysis of the human pathology of this disease. However, modern stem cell technologies, including the analysis of patient-specific neurons and glial cells, have opened up new avenues for dissecting the pathologic mechanisms of PD. Most data on morphological changes, such as cell death or changes in neurite complexity, or functional deficits were acquired in 2D and few in 3D models. This review will examine the prerequisites for human disease modeling in PD, covering the generation of midbrain neurons, 3D organoid midbrain models, the selection of controls including genetically engineered lines, and the study of cell-cell interactions. We will present major disease phenotypes in human in vitro models of PD, focusing on those phenotypes that have been detected in genetic and sporadic PD models. An additional point covered in this review will be the use of induced pluripotent stem cell (iPSC)-derived technologies to model cell-cell interactions in PD.
CRIS-Team Scopus Importer:2020-02-14
Keywords: disease modeling; dopaminergic neuron; glia; inflammation; iPSC; neurodegeneration; organoid; Parkinson’s disease

Modelling human neurodegeneration using induced pluripotent stem cells - Prots, Iryna; Winner, Beate; Winkler, Jürgen (The Matrix of Stem Cell Research. An Approach to Rethinking Science in Society, 2019)
Neurodegeneration is a process of neuronal damage and death. A progressive loss of neurons is a common pathological feature of many neurodegenerative diseases, including motor neuron diseases (MND) and Parkinson's disease (PD). Neurodegenerative diseases are incurable and the only therapies possible are to this date symptomatic. Discovering the mechanisms that either lead to the disease occurrence or that influence the disease progression (together called 'pathomechanisms') would open up possibilities for developing new therapeutic approaches. Cellular material for research in the field of human neurodegeneration is very limited and mostly available as a post-mortem tissue derivate. Therefore, stem cells, as a source of different types of somatic cells, are a very promising tool for developing suitable human models to investigate neurodegeneration. With the discovery of induced pluripotent stem cells (iPSC), researchers now have access to otherwise difficult-to-obtain patient-specific cellular material to investigate the mechanisms that cause neuronal loss and that lead to the development of a neurodegenerative disease. In other words, iPSC-based technology allows the retrieving of disease-specific neurons and thereby allows the observation of the disease development in a dish. In this article, we first describe the symptomatic and current management of two big groups of neurodegenerative diseases: MND and PD. We next explain the advantages of using iPSC technology for the investigation of human neurodegeneration. Then, we highlight a number of pathomechanisms underlying neuronal degeneration in MND and PD, which have been uncovered in iPSC-based models. We finally show that some disease-related phenotypes could already be rescued on a cellular level in the laboratory and discuss the iPSC-based research as a promising tool, fuelling hope that new successful therapies for neurodegenerative disorders can be developed.
CRIS-Team Scopus Importer:2024-08-07
Keywords: Bioscience; Humanities; Medicine; Dentistry; Nursing & Allied Health; Social Sciences

Model Testing of PluriTest with Next-Generation Sequencing Data - Schulze, Markus; Hoja, Sabine; Winner, Beate; Winkler, Jürgen; Edenhofer, Frank; Riemenschneider, Markus J. (Stem Cells and Development, 2016)
EVALuna2:26227

Molecular diagnosis of kidney transplant failure based on urine - Wiesener, Antje; Knaup, Karl; Büttner-Herold, Maike; Dieterle, Anne; Stoeckert, Johanna; Riedl, Bernhard; Morath, Christian; Wald, Alexandra; Vondran, Florian; Braun, Felix; Schödel, Johannes; Schüler, Markus; et al. (American Journal of Transplantation, 2020)
In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerous cysts of different sizes. Clinical workup excluded the most frequent causes of chronic transplant failure. The filed allocation documents mentioned the donor's disease of oral-facial-digital syndrome, a rare ciliopathy, which can also affect the kidney. Molecular diagnosis was performed by culturing donor tubular cells from the recipient ' s urine more than 10 years after transplantation. Next-generation panel sequencing with DNA from tubular urinary cells revealed a novel truncating mutation in OFD1, which sufficiently explains the features of the kidney transplants, also found in the second kidney allograft. Despite this severe donor disease, lifesaving transplantation with good long-term outcome was enabled for 5 recipients.
CRIS-Team WoS Importer:2020-01-31

MOLECULAR DIAGNOSIS OF KIDNEY TRANSPLANT FAILURE BY THE URINE - Knaup, Karl; Wiesener, A.; Buettner-Herold, M.; Dieterle, A.; Morath, C.; Vondran, F. W. R.; Wald, A.; Braun, F.; Schüler, Markus; Schödel, Johannes; Schiffer, Mario; Reis, André; et al. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Monitoring of direct oral anticoagulants plasma levels for secondary stroke prevention - Siedler, Gabriela; Macha, Kosmas; Stoll, Svenja; Plechschmidt, Johannes; Wang, Ruihao; Gerner, Stefan; Strasser, Erwin; Schwab, Stefan; Kallmünzer, Bernd (Journal of Thrombosis and Haemostasis, 2022)
Background: Patients with atrial fibrillation have a relevant risk for ischemic stroke despite the recommended use of direct oral anticoagulants (DOAC). The risk correlates with the functional DOAC plasma levels in clinical trials, but the value of their measurement in community use remains undetermined. Objectives: We aim to investigate the clinical implications and the prognostic value of DOAC plasma level measurement during steady state. Methods: In this observational clinical cohort study among patients with ischemic stroke and atrial fibrillation, 397 individuals on oral anticoagulants for secondary stroke prevention were included between 2016 and 2020. The functional DOAC plasma levels were measured during steady state. Early stroke recurrence within 3 months was recorded as the main outcome parameter. Results: Three hundred ninety-seven patients (201 female, mean age 78 [±9] years, median CHA2DS2VASc-Score 6 [interquartile range 5–7]) were included. Mean DOAC plasma trough level was 95.9 (±66.9) ng/ml. A high glomerular filtration rate (GFR) was an independent predictor of lower levels in a multivariate model (R coefficient: −0.174, P =.014). During follow-up, 10 patients (3%) suffered from early ischemic stroke recurrence despite the use of DOAC, while 10 clinically relevant bleeding complications occurred (3%). Ischemic stroke recurrence was associated with numerical lower plasma levels for patients on apixaban and dabigatran after propensity score matching. Conclusions: Monitoring of DOAC plasma levels could help to identify patients with increased risk for stroke recurrence and should be considered for certain subgroups, including patients with high GFR.
CRIS-Team Scopus Importer:2022-03-18
Keywords: atrial fibrillation; cardioembolic stroke; direct oral anticoagulants; ischemic stroke; secondary prevention

Mono-allelic deleterious variants in autosomal recessive skeletal dysplasia genes are strongly associated with idiopathic short stature - Thiel, C. T.; Hauer, Nadine; Vogl, C.; Uebe, Steffen; Sticht, Heinrich; Ekici, Arif Bülent; Kraus, Cornelia; Dörr, Helmuth-Günther; Reis, André (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Multitrait analysis of glaucoma identifies new risk loci and enables polygenic prediction of disease susceptibility and progression - Craig, Jamie E.; Han, Xikun; Qassim, Ayub; Hassall, Mark; Bailey, Jessica N. Cooke; Kinzy, Tyler G.; Khawaja, Anthony P.; An, Jiyuan; Marshall, Henry; Gharahkhani, Puya; Igo, Robert P.; Graham, Stuart L.; et al. (Nature Genetics, 2020)
Glaucoma, a disease characterized by progressive optic nerve degeneration, can be prevented through timely diagnosis and treatment. We characterize optic nerve photographs of 67,040 UK Biobank participants and use a multitrait genetic model to identify risk loci for glaucoma. A glaucoma polygenic risk score (PRS) enables effective risk stratification in unselected glaucoma cases and modifies penetrance of the MYOC variant encoding p.Gln368Ter, the most common glaucoma-associated myocilin variant. In the unselected glaucoma population, individuals in the top PRS decile reach an absolute risk for glaucoma 10 years earlier than the bottom decile and are at 15-fold increased risk of developing advanced glaucoma (top 10% versus remaining 90%, odds ratio = 4.20). The PRS predicts glaucoma progression in prospectively monitored, early manifest glaucoma cases (P = 0.004) and surgical intervention in advanced disease (P = 3.6 × 10− 6). This glaucoma PRS will facilitate the development of a personalized approach for earlier treatment of high-risk individuals, with less intensive monitoring and treatment being possible for lower-risk groups.
CRIS-Team Scopus Importer:2020-02-04

Mutant RAMP2 causes primary open-angle glaucoma via the CRLR-cAMP axis - Gong, Bo; Zhang, Houbin; Huang, Lulin; Chen, Yuhong; Shi, Yi; Tam, Pancy Oi Sin; Zhu, Xianjun; Huang, Yi; Lei, Bo; Sundaresan, Periasamy; Li, Xi; Jiang, Linxin; et al. (Genetics in Medicine, 2019)
Purpose: Primary open-angle glaucoma (POAG) is the leading cause of irreversible blindness worldwide and mutations in known genes can only explain 5–6% of POAG. This study was conducted to identify novel POAG-causing genes and explore the pathogenesis of this disease. Methods: Exome sequencing was performed in a Han Chinese cohort comprising 398 sporadic cases with POAG and 2010 controls, followed by replication studies by Sanger sequencing. A heterozygous Ramp2 knockout mouse model was generated for in vivo functional study. Results: Using exome sequencing analysis and replication studies, we identified pathogenic variants in receptor activity-modifying protein 2 (RAMP2) within three genetically diverse populations (Han Chinese, German, and Indian). Six heterozygous RAMP2 pathogenic variants (Glu39Asp, Glu54Lys, Phe103Ser, Asn113Lysfs*10, Glu143Lys, and Ser171Arg) were identified among 16 of 4763 POAG patients, whereas no variants were detected in any exon of RAMP2 in 10,953 control individuals. Mutant RAMP2s aggregated in transfected cells and resulted in damage to the AM-RAMP2/CRLR-cAMP signaling pathway. Ablation of one Ramp2 allele led to cAMP reduction and retinal ganglion cell death in mice. Conclusion: This study demonstrated that disruption of RAMP2/CRLR-cAMP axis could cause POAG and identified a potential therapeutic intervention for POAG.
CRIS-Team Scopus Importer:2019-05-02
Keywords: exome sequencing; heterozygous pathogenic variant; primary open-angle glaucoma (POAG); receptor activity-modifying protein 2 (RAMP2); retinal ganglion cell (RGC)

Mutations affecting the SAND domain of DEAF1 cause intellectual disability with severe speech impairment and behavioral problems - Vulto-Van Silfhout, Anneke T.; Rajamanickam, Shivakumar; Jensik, Philip J.; Vergult, Sarah; De Rocker, Nina; Newhall, Kathryn J.; Raghavan, Ramya; Reardon, Sara N.; Jarrett, Kelsey; Mcintyre, Tara; Bulinski, Joseph; Ownby, Stacy L.; et al. (American Journal of Human Genetics, 2014)
Recently, we identified in two individuals with intellectual disability (ID) different de novo mutations in DEAF1, which encodes a transcription factor with an important role in embryonic development. To ascertain whether these mutations in DEAF1 are causative for the ID phenotype, we performed targeted resequencing of DEAF1 in an additional cohort of over 2,300 individuals with unexplained ID and identified two additional individuals with de novo mutations in this gene. All four individuals had severe ID with severely affected speech development, and three showed severe behavioral problems. DEAF1 is highly expressed in the CNS, especially during early embryonic development. All four mutations were missense mutations affecting the SAND domain of DEAF1. Altered DEAF1 harboring any of the four amino acid changes showed impaired transcriptional regulation of the DEAF1 promoter. Moreover, behavioral studies in mice with a conditional knockout of Deaf1 in the brain showed memory deficits and increased anxiety-like behavior. Our results demonstrate that mutations in DEAF1 cause ID and behavioral problems, most likely as a result of impaired transcriptional regulation by DEAF1.
EVALuna2:9219

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer -Association With Patient and Disease Characteristics and Effect on Prognosis - Fasching, Peter; Yadav, Siddhartha; Hu, Chunling; Wunderle, Marius; Häberle, Lothar; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Lee, Kun Y.; Gnanaolivu, Rohan D.; Hadji, Peyman; Hübner, Hanna; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS: Germline DNA from 2,595 patients with mBC enrolled in the prospective PRAEGNANT registry was evaluated for mutations in cancer predisposition genes. The frequencies of mutations in known BC predisposition genes were compared with results from a prospective registry of patients with nonmetastatic BC sequenced using the same QIAseq method and with public reference controls. Associations between mutation status and tumor characteristics, progression-free survival, and overall survival were assessed. RESULTS: Germline mutations in 12 established BC predisposition genes (including BRCA1 and BRCA2) were detected in 271 (10.4%) patients. A mutation in BRCA1 or BRCA2 was seen in 129 patients (5.0%). BRCA1 mutation carriers had a higher proportion of brain metastasis (27.1%) compared with nonmutation carriers (12.8%). Mutations were significantly enriched in PRAEGNANT patients with mBC compared with patients with nonmetastatic BC (10.4% v 6.6%, P < .01). Mutations did not significantly modify progression-free survival or overall survival for patients with mBC. CONCLUSION: Multigene panel testing may be considered in all patients with mBC because of the high frequency of germline mutations in BRCA1/2 and other BC predisposition genes. Although the prognosis of mutation carriers and nonmutation carriers with mBC was similar, differences observed in tumor characteristics have implications for treatment and for future studies of targeted therapies.
CRIS-Team Scopus Importer:2021-06-04

Mutations in DCPS and EDC3 in autosomal recessive intellectual disability indicate a crucial role for mRNA decapping in neurodevelopment - Ahmed, Iltaf; Buchert, Rebecca; Zhou, Mi; Jiao, Xinfu; Mittal, Kirti; Sheikh, Taimoor I.; Scheller, Ute; Vasli, Nasim; Rafiq, Muhammad Arshad; Brohi, M. Qasim; Mikhailov, Anna; Ayaz, Muhammad; et al. (Human Molecular Genetics, 2015)
There are two known mRNA degradation pathways, 3' to 5' and 5' to 3'. We identified likely pathogenic variants in two genes involved in these two pathways in individuals with intellectual disability. In a large family with multiple branches, we identified biallelic variants in DCPS in three affected individuals; a splice site variant (c.636+1G>A) that results in an in-frame insertion of 45 nucleotides and a missense variant (c.947C>T; p.Thr316Met). DCPS decaps the cap structure generated by 3' to 5' exonucleolytic degradation of mRNA. In vitro decapping assays showed an ablation of decapping function for both variants in DCPS. In another family, we identified a homozygous mutation (c.161T>C; p.Phe54Ser) in EDC3 in two affected children. EDC3 stimulates DCP2, which decaps mRNAs at the beginning of the 5' to 3' degradation pathway. In vitro decapping assays showed that altered EDC3 is unable to enhance DCP2 decapping at low concentrations and even inhibits DCP2 decapping at high concentration. We show that individuals with biallelic mutations in these genes of seemingly central functions are viable and that these possibly lead to impairment of neurological functions linking mRNA decapping to normal cognition. Our results further affirm an emerging theme linking aberrant mRNA metabolism to neurological defects.
EVALuna2:9274

Mutations in IL36RN in patients with generalized pustular psoriasis - Koerber, Andreas; Moessner, Rotraut; Renner, Regina; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Schulz, Peter; Sticherling, Michael; Traupe, Heiko; Hüffmeier, Ulrike (Journal of Investigative Dermatology, 2013)
EVALuna2:9180

Mutations in KEOPS-complex genes cause nephritic syndrome with primary microcephaly - Braun, Daniela A.; Rao, Jia; Mollet, Geraldine; Schapiro, David; Daugeron, Marie-Claire; Tan, Weizhen; Gribouval, Olivier; Boyer, Olivia; Revy, Patrick; Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Lawson, Jennifer A.; et al. (Nature Genetics, 2017)
Galloway-Mowat syndrome (GAMOS) is an autosomalrecessive disease characterized by the combination of earlyonset nephrotic syndrome (SRNS) and microcephaly with brain anomalies. Here we identified recessive mutations in OSGEP, TP53RK, TPRKB, and LAGE3, genes encoding the four subunits of the KEOPS complex, in 37 individuals from 32 families with GAMOS. CRISPR-Cas9 knockout in zebrafish and mice recapitulated the human phenotype of primary microcephaly and resulted in early lethality. Knockdown of OSGEP, TP53RK, or TPRKB inhibited cell proliferation, which human mutations did not rescue. Furthermore, knockdown of these genes impaired protein translation, caused endoplasmic reticulum stress, activated DNA-damage-response signaling, and ultimately induced apoptosis. Knockdown of OSGEP or TP53RK induced defects in the actin cytoskeleton and decreased the migration rate of human podocytes, an established intermediate phenotype of SRNS. We thus identified four new monogenic causes of GAMOS, describe a link between KEOPS function and human disease, and delineate potential pathogenic mechanisms.
Created from Fastlane, Scopus look-up

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features - Johansen, Anide; Rosti, Rasim O.; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Caglayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (American Journal of Human Genetics, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
EVALuna2:9331

Mutations in PIK3C2A cause syndromic short stature, skeletal abnormalities, and cataracts associated with ciliary dysfunction - Tiosano, Dov; Baris, Hagit N.; Chen, Anlu; Hitzert, Marrit M.; Schüler, Markus; Gulluni, Federico; Wiesener, Antje; Bergua, Antonio; Mory, Adi; Copeland, Brett; Gleeson, Joseph G.; Rump, Patrick; et al. (PLoS Genetics, 2019)
PIK3C2A is a class II member of the phosphoinositide 3-kinase (PI3K) family that catalyzes the phosphorylation of phosphatidylinositol (PI) into PI(3)P and the phosphorylation of PI(4)P into PI(3,4)P2. At the cellular level, PIK3C2A is critical for the formation of cilia and for receptor mediated endocytosis, among other biological functions. We identified homozygous loss-of-function mutations in PIK3C2A in children from three independent consanguineous families with short stature, coarse facial features, cataracts with secondary glaucoma, multiple skeletal abnormalities, neurological manifestations, among other findings. Cellular studies of patient-derived fibroblasts found that they lacked PIK3C2A protein, had impaired cilia formation and function, and demonstrated reduced proliferative capacity. Collectively, the genetic and molecular data implicate mutations in PIK3C2A in a new Mendelian disorder of PI metabolism, thereby shedding light on the critical role of a class II PI3K in growth, vision, skeletal formation and neurological development. In particular, the considerable phenotypic overlap, yet distinct features, between this syndrome and Lowe's syndrome, which is caused by mutations in the PI-5-phosphatase OCRL, highlight the key role of PI metabolizing enzymes in specific developmental processes and demonstrate the unique non-redundant functions of each enzyme. This discovery expands what is known about disorders of PI metabolism and helps unravel the role of PIK3C2A and class II PI3Ks in health and disease.
CRIS-Team Scopus Importer:2019-05-28

Mutations in the BAF-Complex Subunit DPF2 Are Associated with Coffin-Siris Syndrome - Vasileiou, Georgia; Vergarajauregui, Silvia; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, Marion; Bramswig, Nuria C.; Albrecht, Beate; Clayton-Smith, Jill; Morton, Jenny; Tomkins, Susan; et al. (American Journal of Human Genetics, 2018)
Variants affecting the function of different subunits of the BAF chromatin-remodelling complex lead to various neurodevelopmental syndromes, including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental-delay disorders. Here, we report eight heterozygous de novo variants (one frameshift, two splice site, and five missense) in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome, including coarse facial features, global developmental delay, intellectual disability, speech impairment, and hypoplasia of fingernails and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Pull-down assays of recombinant proteins and histone peptides revealed that a subset of the identified missense variants abolish or impaire DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD finger structural integrity and cohesion and most likely an aberrant recognition of histone modifications. Furthermore, the overexpression of these variants in HEK293 and COS7 cell lines was associated with the formation of nuclear aggregates and the recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in the affected individuals indicated that the aberrant transcripts escape nonsense-mediated decay. Altogether, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant-negative mechanism of pathogenicity.

Mutations in the BAF-complex subunit DPF2 are associated with Coffin-Siris syndrome - Vasileiou, G.; Vergarajauregui, S.; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, M.; Bramswig, N. C.; Albrecht, B.; Clayton-Smith, J.; Morton, J.; Tomkins, S.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Mutations in the histone methyltransferase gene KMT2B cause complex early-onset dystonia - Meyer, Esther; Carss, Keren J.; Rankin, Julia; Nichols, John M. E.; Grozeva, Detelina; Joseph, Agnel P.; Mencacci, Niccolo E.; Papandreou, Apostolos; Ng, Joanne; Barra, Serena; Ngoh, Adeline; Ben-Pazi, Hilla; et al. (Nature Genetics, 2016)
Histone lysine methylation, mediated by mixed-lineage leukemia (MLL) proteins, is now known to be critical in the regulation of gene expression, genomic stability, cell cycle and nuclear architecture. Despite MLL proteins being postulated as essential for normal development, little is known about the specific functions of the different MLL lysine methyltransferases. Here we report heterozygous variants in the gene KMT2B (also known as MLL4) in 27 unrelated individuals with a complex progressive childhood-onset dystonia, often associated with a typical facial appearance and characteristic brain magnetic resonance imaging findings. Over time, the majority of affected individuals developed prominent cervical, cranial and laryngeal dystonia. Marked clinical benefit, including the restoration of independent ambulation in some cases, was observed following deep brain stimulation (DBS). These findings highlight a clinically recognizable and potentially treatable form of genetic dystonia, demonstrating the crucial role of KMT2B in the physiological control of voluntary movement.
EVALuna2:9343

Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

Mycobacterial Cord Factor Reprograms the Macrophage Response to IFN-γ towards Enhanced Inflammation yet Impaired Antigen Presentation and Expression of GBP1 - Huber, Alexandra; Killy, Barbara; Grummel, Nadine; Bodendorfer, Barbara; Paul, Sushmita; Wiesmann, Veit; Naschberger, Elisabeth; Zimmer, Jana; Wirtz, Stefan; Schleicher, Ulrike; Vera, Julio; Ekici, Arif Bülent; et al. (Journal of Immunology, 2020)
Mycobacteria survive in macrophages despite triggering pattern recognition receptors and T cell-derived IFN-γ production. Mycobacterial cord factor trehalose-6,6-dimycolate (TDM) binds the C-type lectin receptor MINCLE and induces inflammatory gene expression. However, the impact of TDM on IFN-γ-induced macrophage activation is not known. In this study, we have investigated the cross-regulation of the mouse macrophage transcriptome by IFN-γ and by TDM or its synthetic analogue trehalose-6,6-dibehenate (TDB). As expected, IFN-γ induced genes involved in Ag presentation and antimicrobial defense. Transcriptional programs induced by TDM and TDB were highly similar but clearly distinct from the response to IFN-γ. The glycolipids enhanced expression of a subset of IFN-γ-induced genes associated with inflammation. In contrast, TDM/TDB exerted delayed inhibition of IFN-γ-induced genes, including pattern recognition receptors, MHC class II genes, and IFN-γ-induced GTPases, with antimicrobial function. TDM downregulated MHC class II cell surface expression and impaired T cell activation by peptide-pulsed macrophages. Inhibition of the IFN-γ-induced GTPase GBP1 occurred at the level of transcription by a partially MINCLE-dependent mechanism that may target IRF1 activity. Although activation of STAT1 was unaltered, deletion of Socs1 relieved inhibition of GBP1 expression by TDM. Nonnuclear Socs1 was sufficient for inhibition, suggesting a noncanonical, cytoplasmic mechanism. Taken together, unbiased analysis of transcriptional reprogramming revealed a significant degree of negative regulation of IFN-γ-induced Ag presentation and antimicrobial gene expression by the mycobacterial cord factor that may contribute to mycobacterial persistence.
CRIS-Team Scopus Importer:2020-09-18

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Myogenin controls via AKAP6 non-centrosomal microtubule-organizing center formation at the nuclear envelope - Becker, Robert; Vergarajauregui, Silvia; Billing, Florian; Sharkova, Maria; Lippolis, Eleonora; Mamchaoui, Kamel; Ferrazzi, Fulvia; Engel, Felix (eLife, 2021)
Non-centrosomal microtubule-organizing centers (MTOCs) are pivotal for the function of multiple cell types, but the processes initiating their formation are unknown. Here, we find that the transcription factor myogenin is required in murine myoblasts for the localization of MTOC proteins to the nuclear envelope. Moreover, myogenin is sufficient in fibroblasts for nuclear envelope MTOC (NE-MTOC) formation and centrosome attenuation. Bioinformatics combined with loss- and gain-of-function experiments identified induction of AKAP6 expression as one central mechanism for myogenin-mediated NE-MTOC formation. Promoter studies indicate that myogenin preferentially induces the transcription of muscle- and NE-MTOC-specific isoforms of Akap6 and Syne1, which encodes nesprin-1 alpha, the NE-MTOC anchor protein in muscle cells. Overexpression of AKAP6 beta and nesprin-1 alpha was sufficient to recruit endogenous MTOC proteins to the nuclear envelope of myoblasts in the absence of myogenin. Taken together, our results illuminate how mammals transcriptionally control the switch from a centrosomal MTOC to an NE-MTOC and identify AKAP6 as a novel NE-MTOC component in muscle cells.
CRIS-Team WoS Importer:2021-11-05

Nachruf John M. Opitz, geboren in Hamburg am 15.08.1935, verstorben 31. Oktober 2023 in Salt Lake City, Utah, U. S. A. - Rauch, Anita; Reis, André (Medizinische Genetik, 2024)
EVALuna2:585171

Nanomaterial-based ophthalmic therapies - Unterweger, Harald; Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Tietze, Rainer; Friedrich, Bernhard; Alexiou, Christoph (Nanomedicine, 2023)
CRIS-Team Scopus Importer:2023-09-01
Keywords: age-related macular degeneration; diabetic retinopathy; eye infections; glaucoma; keratitis; nanoparticles

Nanoparticles for the treatment of inflammatory conditions - Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2024)
CRIS-Team Scopus Importer:2024-02-16
Keywords: cytokine storm; drug delivery; hypertension; inflammation; ischemia–reperfusion injury; nanosystems; periodontitis; pneumonia

Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Ploetz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif Bülent; Asadollahi, Reza; et al. (Scientific Reports, 2018)
Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.
EVALuna2:34839

Negative selection on human genes underlying inborn errors depends on disease outcome and both the mode and mechanism of inheritance - Rapaport, Franck; Boisson, Bertrand; Gregor, Anne; Béziat, Vivien; Boisson-Dupuis, Stéphanie; Bustamante, Jacinta; Jouanguy, Emmanuelle; Puel, Anne; Rosain, Jérémie; Zhang, Qian; Zhang, Shen Ying; Gleeson, Joseph G.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Genetic variants underlying life-threatening diseases, being unlikely to be transmitted to the next generation, are gradually and selectively eliminated from the population through negative selection. We study the determinants of this evolutionary process in human genes underlying monogenic diseases by comparing various negative selection scores and an integrative approach, CoNeS, at 366 loci underlying inborn errors of immunity (IEI). We find that genes underlying autosomal dominant (AD) or X-linked IEI have stronger negative selection scores than those underlying autosomal recessive (AR) IEI, whose scores are not different from those of genes not known to be disease causing. Nevertheless, genes underlying AR IEI that are lethal before reproductive maturity with complete penetrance have stronger negative selection scores than other genes underlying AR IEI. We also show that genes underlying AD IEI by loss of function have stronger negative selection scores than genes underlying AD IEI by gain of function, while genes underlying AD IEI by haploinsufficiency are under stronger negative selection than other genes underlying AD IEI. These results are replicated in 1,140 genes underlying inborn errors of neurodevelopment. Finally, we propose a supervised classifier, SCoNeS, which predicts better than state-of-the-art approaches whether a gene is more likely to underlie an AD or AR disease. The clinical outcomes of monogenic inborn errors, together with their mode and mechanisms of inheritance, determine the levels of negative selection at their corresponding loci. Integrating scores of negative selection may facilitate the prioritization of candidate genes and variants in patients suspected to carry an inborn error.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Immunodeficiency | selection | evolution | genetics | method

Neonatal nephron loss during active nephrogenesis results in altered expression of renal developmental genes and markers of kidney injury - Raming, Roman; Cordasic, Nada; Kirchner, Philipp; Ekici, Arif Bülent; Fahlbusch, Fabian; Wölfle, Joachim; Hilgers, Karl Friedrich; Hartner, Andrea; Menendez-Castro, Carlos (Physiological Genomics, 2021)
Preterm neonates are at a high risk for nephron loss under adverse clinical conditions. Renal damage potentially collides with postnatal nephrogenesis. Recent animal studies suggest that nephron loss within this vulnerable phase leads to renal damage later in life. Nephrogenic pathways are commonly reactivated after kidney injury supporting renal regeneration. We hypothesized that nephron loss during nephrogenesis affects renal development, which, in turn, impairs tissue repair after secondary injury. Neonates prior to 36 wk of gestation show an active nephrogenesis. In rats, nephrogenesis is ongoing until day 10 after birth. Mimicking the situation of severe nephron loss during nephrogenesis, male pups were uninephrectomized at day 1 of life (UNXd1). A second group of males was uninephrectomized at postnatal day 14 (UNXd14), after terminated nephrogenesis. Agematched controls were sham operated. Three days after uninephrectomy transcriptional changes in the right kidney were analyzed by RNA-sequencing, followed by functional pathway analysis. In UNXd1, 1,182 genes were differentially regulated, but only 143 genes showed a regulation both in UNXd1 and UNXd14. The functional groups “renal development” and “kidney injury” were among the most differentially regulated groups and revealed distinctive alterations. Reduced expression of candidate genes concerning renal development (Bmp7, Gdnf, Pdgf-B, Wt1) and injury (nephrin, podocin, Tgf-b 1) were detected. The downregulation of Bmp7 and Gdnf persisted until day 28. In UNXd14, Six2 was upregulated and Pax2 was downregulated. We conclude that nephron loss during nephrogenesis affects renal development and induces a specific regulation of genes that might hinder tissue repair after secondary kidney injury.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Neonatal nephron loss; Neonatal uninephrectomy; Nephrogenesis; Renal regeneration; RNA-sequencing

Network- and systems-based re-engineering of dendritic cells with non-coding RNAs for cancer immunotherapy - Lai, Xin; Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Gerer, Kerstin F.; Jaitly, Tanushree; Uebe, Steffen; Lischer, Christopher; Ekici, Arif Bülent; Wittmann, Jürgen; Jäck, Hans-Martin; Schaft, Niels; et al. (Theranostics, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells that induce and regulate adaptive immunity by presenting antigens to T cells. Due to their coordinative role in adaptive immune responses, DCs have been used as cell-based therapeutic vaccination against cancer. The capacity of DCs to induce a therapeutic immune response can be enhanced by re-wiring of cellular signalling pathways with microRNAs (miRNAs). Methods: Since the activation and maturation of DCs is controlled by an interconnected signalling network, we deploy an approach that combines RNA sequencing data and systems biology methods to delineate miRNA-based strategies that enhance DC-elicited immune responses. Results: Through RNA sequencing of IKKβ-matured DCs that are currently being tested in a clinical trial on therapeutic anti-cancer vaccination, we identified 44 differentially expressed miRNAs. According to a network analysis, most of these miRNAs regulate targets that are linked to immune pathways, such as cytokine and interleukin signalling. We employed a network topology-oriented scoring model to rank the miRNAs, analysed their impact on immunogenic potency of DCs, and identified dozens of promising miRNA candidates, with miR-15a and miR-16 as the top ones. The results of our analysis are presented in a database that constitutes a tool to identify DC-relevant miRNA-gene interactions with therapeutic potential (www.synmirapy.net/dc-optimization). Conclusions: Our approach enables the systematic analysis and identification of functional miRNA-gene interactions that can be experimentally tested for improving DC immunogenic potenc
CRIS-Team WoS Importer:2020-12-11
Keywords: dendritic cell; therapeutic vaccination in cancer; systems biology; network biology; microRNAs: bioinformatics

Network-Based Integration of GWAS and Gene Expression Identifies a HOX-Centric Network Associated with Serous Ovarian Cancer Risk - Kar, Siddhartha P.; Tyrer, Jonathan P.; Li, Qiyuan; Lawrenson, Kate; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Chenevix-Trench, Georgia; Baker, Helen; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
Genome-wide association studies (GWAS) have so far reported 12 loci associated with serous epithelial ovarian cancer (EOC) risk. We hypothesized that some of these loci function through nearby transcription factor (TF) genes and that putative target genes of these TFs as identified by coexpression may also be enriched for additional EOC risk associations.We selected TF genes within 1 Mb of the top signal at the 12 genome-wide significant risk loci. Mutual information, a form of correlation, was used to build networks of genes strongly coexpressed with each selected TF gene in the unified microarray dataset of 489 serous EOC tumors from The Cancer Genome Atlas. Genes represented in this dataset were subsequently ranked using a gene-level test based on results for germline SNPs from a serous EOC GWAS meta-analysis (2,196 cases/4,396 controls).Gene set enrichment analysis identified six networks centered on TF genes (HOXB2, HOXB5, HOXB6, HOXB7 at 17q21.32 and HOXD1, HOXD3 at 2q31) that were significantly enriched for genes from the risk-associated end of the ranked list (P < 0.05 and FDR < 0.05). These results were replicated (P < 0.05) using an independent association study (7,035 cases/21,693 controls). Genes underlying enrichment in the six networks were pooled into a combined network.We identified a HOX-centric network associated with serous EOC risk containing several genes with known or emerging roles in serous EOC development.Network analysis integrating large, context-specific datasets has the potential to offer mechanistic insights into cancer susceptibility and prioritize genes for experimental characterization. Cancer Epidemiol Biomarkers Prev; 24(10); 1574-84. ©2015 AACR.
EVALuna2:9287

Neuroinflammatory disease signatures in SPG11-related hereditary spastic paraplegia patients. - Krumm, Laura; Pozner, Tatyana; Zagha, Naime; Coras, Roland; Arnold, Philipp; Tsaktanis, Thanos; Scherpelz, Kathryn; Davis, Marie Y.; Kaindl, Johanna; Stolzer, Iris; Süß, Patrick; Khundadze, Mukhran; et al. (Acta Neuropathologica, 2024)
Biallelic loss of SPG11 function constitutes the most frequent cause of complicated autosomal recessive hereditary spastic paraplegia (HSP) with thin corpus callosum, resulting in progressive multisystem neurodegeneration. While the impact of neuroinflammation is an emerging and potentially treatable aspect in neurodegenerative diseases and leukodystrophies, the role of immune cells in SPG11-HSP patients is unknown. Here, we performed a comprehensive immunological characterization of SPG11-HSP, including examination of three human postmortem brain donations, immunophenotyping of patients' peripheral blood cells and patient-specific induced pluripotent stem cell-derived microglia-like cells (iMGL). We delineate a previously unknown role of innate immunity in SPG11-HSP. Neuropathological analysis of SPG11-HSP patient brain tissue revealed profound microgliosis in areas of neurodegeneration, downregulation of homeostatic microglial markers and cell-intrinsic accumulation of lipids and lipofuscin in IBA1+ cells. In a larger cohort of SPG11-HSP patients, the ratio of peripheral classical and intermediate monocytes was increased, along with increased serum levels of IL-6 that correlated with disease severity. Stimulation of patient-specific iMGLs with IFNγ led to increased phagocytic activity compared to control iMGL as well as increased upregulation and release of proinflammatory cytokines and chemokines, such as CXCL10. On a molecular basis, we identified increased STAT1 phosphorylation as mechanism connecting IFNγ-mediated immune hyperactivation and SPG11 loss of function. STAT1 expression was increased both in human postmortem brain tissue and in an Spg11-/- mouse model. Application of an STAT1 inhibitor decreased CXCL10 production in SPG11 iMGL and rescued their toxic effect on SPG11 neurons. Our data establish neuroinflammation as a novel disease mechanism in SPG11-HSP patients and constitute the first description of myeloid cell/ microglia activation in human SPG11-HSP. IFNγ/ STAT1-mediated neurotoxic effects of hyperreactive microglia upon SPG11 loss of function indicate that immunomodulation strategies may slow down disease progression.
EVALuna2:552646

Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity

Neutral sphingomyelinase mediates the co-morbidity trias of alcohol abuse, major depression and bone defects - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Molecular Psychiatry, 2021)
Mental disorders are highly comorbid and occur together with physical diseases, which are often considered to arise from separate pathogenic pathways. We observed in alcohol-dependent patients increased serum activity of neutral sphingomyelinase. A genetic association analysis in 456,693 volunteers found associations of haplotypes of SMPD3 coding for NSM-2 (NSM) with alcohol consumption, but also with affective state, and bone mineralisation. Functional analysis in mice showed that NSM controls alcohol consumption, affective behaviour, and their interaction by regulating hippocampal volume, cortical connectivity, and monoaminergic responses. Furthermore, NSM controlled bone–brain communication by enhancing osteocalcin signalling, which can independently supress alcohol consumption and reduce depressive behaviour. Altogether, we identified a single gene source for multiple pathways originating in the brain and bone, which interlink disorders of a mental–physical co-morbidity trias of alcohol abuse—depression/anxiety—bone disorder. Targeting NSM and osteocalcin signalling may, thus, provide a new systems approach in the treatment of a mental–physical co-morbidity trias.
CRIS-Team Scopus Importer:2021-10-08

New insights into the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and impairment of the WRC-mediated actin dynamics - Begemann, Anaïs; Sticht, Heinrich; Begtrup, Amber; Vitobello, Antonio; Faivre, Laurence; Banka, Siddharth; Alhaddad, Bader; Asadollahi, Reza; Becker, Jessica; Bierhals, Tatjana; Brown, Kathleen E.; Bruel, Ange Line; et al. (Genetics in Medicine, 2020)
Purpose: A few de novo missense variants in the cytoplasmic FMRP-interacting protein 2 (CYFIP2) gene have recently been described as a novel cause of severe intellectual disability, seizures, and hypotonia in 18 individuals, with p.Arg87 substitutions in the majority. Methods: We assembled data from 19 newly identified and all 18 previously published individuals with CYFIP2 variants. By structural modeling and investigation of WAVE-regulatory complex (WRC)-mediated actin polymerization in six patient fibroblast lines we assessed the impact of CYFIP2 variants on the WRC. Results: Sixteen of 19 individuals harbor two previously described and 11 novel (likely) disease-associated missense variants. We report p.Asp724 as second mutational hotspot (4/19 cases). Genotype–phenotype correlation confirms a consistently severe phenotype in p.Arg87 patients but a more variable phenotype in p.Asp724 and other substitutions. Three individuals with milder phenotypes carry putative loss-of-function variants, which remain of unclear pathogenicity. Structural modeling predicted missense variants to disturb interactions within the WRC or impair CYFIP2 stability. Consistent with its role in WRC-mediated actin polymerization we substantiate aberrant regulation of the actin cytoskeleton in patient fibroblasts. Conclusion: Our study expands the clinical and molecular spectrum of CYFIP2-related neurodevelopmental disorder and provides evidence for aberrant WRC-mediated actin dynamics as contributing cellular pathomechanism.
CRIS-Team Scopus Importer:2020-11-13
Keywords: CYFIP2; epilepsy; intellectual disability; WASF; WAVE-regulatory complex (WRC)

New Therapeutic Approaches in Inflammatory Diseases of the Eye - Targeting Lymphangiogenesis and Cellular Immunity: Research Unit FOR 2240 Presents Itself - Cursiefen, Claus; Bock, Felix; Clahsen, Thomas; Regenfuss, Birgit; Reis, André; Steven, Philipp; Heindl, Ludwig M.; Bosch, Jacobus J.; Hos, Deniz; Eming, Sabine; Grajewski, Rafael; Heiligenhaus, Arnd; et al. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Ophthalmology, principally, is a very successful subdiscipline in medicine. Nonetheless, there are still unmet medical needs which necessitate translational research. Methods The funding instrument of a Research Unit (RU) of the German Research Foundation (DFG) is presented as exemplified by the RU 2240 at the Department of Ophthalmology at the University of Cologne. Results The Research Unit integrates different research groups working on pathologic ocular inflammation, macrophages/microglia and (lymph)angiogenesis to collaborate in a synergistic way. Rotation positions allow young clinicians to rotate into research labs for a defined period of time. A Research Unit is also a powerful strategic tool to strengthen clinical and experimental ophthalmology at individual medical faculties. Conclusions The funding instrument of a Research Unit is highly suitable for fostering translational research in a medical subdiscipline such as ophthalmology, supporting the next generation of (clinician) scientists in ophthalmology and finding new cures for our patients.
EVALuna2:9372

Nimodipine Exerts Beneficial Effects on the Rat Oligodendrocyte Cell Line OLN-93 - Boltz, Felix; Enders, Michael; Feigenspan, Andreas; Kirchner, Philipp; Ekici, Arif Bülent; Kürten, Stefanie (Brain Sciences, 2022)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS). Therapy is currently limited to drugs that interfere with the immune system; treatment options that primarily mediate neuroprotection and prevent neurodegeneration are not available. Here, we studied the effects of nimodipine on the rat cell line OLN-93, which resembles young mature oligodendrocytes. Nimodipine is a dihydropyridine that blocks the voltage-gated L-type calcium channel family members Cav1.2 and Cav1.3. Our data show that the treatment of OLN-93 cells with nimodipine induced the upregulation of myelin genes, in particular of proteolipid protein 1 (Plp1), which was confirmed by a significantly greater expression of PLP1 in immunofluorescence analysis and the presence of myelin structures in the cytoplasm at the ultrastructural level. Whole-genome RNA sequencing additionally revealed the upregulation of genes that are involved in neuroprotection, remyelination, and antioxidation pathways. Interestingly, the observed effects were independent of Cav1.2 and Cav1.3 because OLN-93 cells do not express these channels, and there was no measurable response pattern in patch-clamp analysis. Taking into consideration previous studies that demonstrated a beneficial effect of nimodipine on microglia, our data support the notion that nimodipine is an interesting drug candidate for the treatment of MS and other demyelinating diseases.
CRIS-Team Scopus Importer:2022-05-06
Keywords: dihydropyridines; MS; myelination; neuroprotection; nimodipine; OLN-93

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

No clinical utility of KRAS variant rs61764370 for ovarian or breast cancer - Hollestelle, Antoinette; Van Der Baan, Frederieke H.; Berchuck, Andrew; Johnatty, Sharon E.; Aben, Katja K.; Agnarsson, Bjarni A.; Aittomaki, Kristiina; Alducci, Elisa; Andrulis, Irene L.; Anton-Culver, Hoda; Antonenkova, Natalia N.; Antoniou, Antonis C.; et al. (Gynecologic Oncology, 2016)
Clinical genetic testing is commercially available for rs61764370, an inherited variant residing in a KRAS 3' UTR microRNA binding site, based on suggested associations with increased ovarian and breast cancer risk as well as with survival time. However, prior studies, emphasizing particular subgroups, were relatively small. Therefore, we comprehensively evaluated ovarian and breast cancer risks as well as clinical outcome associated with rs61764370.Centralized genotyping and analysis were performed for 140,012 women enrolled in the Ovarian Cancer Association Consortium (15,357 ovarian cancer patients; 30,816 controls), the Breast Cancer Association Consortium (33,530 breast cancer patients; 37,640 controls), and the Consortium of Modifiers of BRCA1 and BRCA2 (14,765 BRCA1 and 7904 BRCA2 mutation carriers).We found no association with risk of ovarian cancer (OR=0.99, 95% CI 0.94-1.04, p=0.74) or breast cancer (OR=0.98, 95% CI 0.94-1.01, p=0.19) and results were consistent among mutation carriers (BRCA1, ovarian cancer HR=1.09, 95% CI 0.97-1.23, p=0.14, breast cancer HR=1.04, 95% CI 0.97-1.12, p=0.27; BRCA2, ovarian cancer HR=0.89, 95% CI 0.71-1.13, p=0.34, breast cancer HR=1.06, 95% CI 0.94-1.19, p=0.35). Null results were also obtained for associations with overall survival following ovarian cancer (HR=0.94, 95% CI 0.83-1.07, p=0.38), breast cancer (HR=0.96, 95% CI 0.87-1.06, p=0.38), and all other previously-reported associations.rs61764370 is not associated with risk of ovarian or breast cancer nor with clinical outcome for patients with these cancers. Therefore, genotyping this variant has no clinical utility related to the prediction or management of these cancers.
EVALuna2:9251

Novel co-culture model of T cells and midbrain organoids for investigating neurodegeneration in Parkinson’s disease - Gerasimova, Elizaveta; Beenen, Amke; Kachkin, Daniil; Regensburger, Martin; Zundler, Sebastian; Blumenthal, David B.; Lutzny-Geier, Gloria; Winner, Beate; Prots, Iryna (npj Parkinson’s Disease, 2025)

Novel loci for non-syndromic coarctation of the aorta in sporadic and familial cases - Moosmann, Julia; Uebe, Steffen; Dittrich, Sven; Rueffer, Andre; Ekici, Arif Bülent; Toka, Okan (PLoS ONE, 2015)
Coarctation of the aorta (CoA) accounts for 5-8% of all congenital heart defects. CoA can be detected in up to 20% of patients with Ullrich-Turner syndrome (UTS), in which a part or all of one of the X chromosomes is absent. The etiology of non-syndromic CoA is poorly understood. In the present work, we test the hypothesis that rare copy number variation (CNV) especially on the gonosomes, contribute to the etiology of non-syndromic CoA.We performed high-resolution genome-wide CNV analysis using the Affymetrix SNP 6.0 microarray platform for 70 individuals with sporadic CoA, 3 families with inherited CoA (n=13) and 605 controls. Our analysis comprised genome wide association, CNV burden and linkage. CNV was validated by multiplex ligation-dependent probe amplification.We identified a significant abundance of large (>100 kb) CNVs on the X chromosome in males with CoA (p=0.005). 11 out of 51 ( 22%) male cases had these large CNVs. Association analysis in the sporadic cohort revealed 14 novel loci for CoA. The locus on 21q22.3 in the sporadic CoA cohort overlapped with a gene locus identified in all familial cases of CoA (candidate gene TRPM2). We identified one CNV locus within a locus with high multipoint LOD score from a linkage analysis of the familial cases (SEPT9); another locus overlapped with a region implicated in Kabuki syndrome. In the familial cases, we identified a total of 7 CNV loci that were exclusively present in cases but not in unaffected family members.Of all candidate loci identified, the TRPM2 locus was the most frequently implicated autosomal locus in sporadic and familial cases. However, the abundance of large CNVs on the X chromosome of affected males suggests that gonosomal aberrations are not only responsible for syndromic CoA but also involved in the development of sporadic and non-syndromic CoA and their male dominance.
EVALuna2:9256

Novel STRA6 null mutations in the original family described with Matthew-Wood syndrome - Pasutto, Francesca; Flinter, Frances; Rauch, Anita; Reis, André (American Journal of Medical Genetics Part A, 2017)
EVALuna2:9392

Novel truncating mutation in CACNA1F in a young male patient diagnosed with optic atrophy - Pasutto, Francesca; Ekici, Arif Bülent; Reis, André; Kremers, Jan; Huchzermeyer, Cord (Ophthalmic Genetics, 2018)
BACKGROUND: Low vision in children can be accompanied by pallor of the optic disc with little or no characteristic morphologic changes of the retina. A variety of diseases can be the underlying cause, including hereditary optic atrophy, Leber's congenital amaurosis (LCA), achromatopsia, and calcium channel, voltage-dependent, L-type, alpha-1F subunit gene (CACNA1F)-associated retinopathy (most widely known as incomplete congenital stationary night blindness: iCSNB). Differentiation at early age is desirable due to large differences in prognosis, but may be difficult because phenotypes overlap and electrophysiological testing is challenging in young patients. We present the case of a 6-year-old boy with unexplained low vision and pallor of the optic disc who originally had been diagnosed with hereditary optic atrophy in the absence of recordable full-field electroretinography (ERG) due to poor patient cooperation. MATERIALS AND METHODS: Standard Sanger sequencing excluded mutations in the OPA1 gene (autosomal-dominant optic atrophy). To identify the underlying genetic cause, whole-exome sequencing was performed on patient's DNA. Recording of the full-field ERG was successfully performed 6 months later. RESULTS: We identified a novel truncating mutation in CACNA1F gene (NM_001256789: c.3895C > T in exon 33) which led to the correct diagnosis of CACNA1F-associated retinopathy in the young boy. ERG recordings showed a negative scotopic mixed response with preserved oscillatory potentials and a flicker ERG with reduced amplitude and biphasic waveform, compatible with a CACNA1F-asssociated phenotype. CONCLUSIONS: We show that genetic testing may help to differentiate between optic atrophy, LCA, and CACNA1F-associated retinopathy at a much earlier age, in absence of electrophysiological examination and by widely overlapping phenotypes.
EVALuna2:34838

NPT100-18A rescues mitochondrial oxidative stress and neuronal degeneration in human iPSC-based Parkinson's model. - Alecu, Julian; Sigutova, Veronika; Brazdis, Razvan Marius; Lörentz, Sandra; Marios-Evangelos, Bogiongko; Nursaitova, Anara; Regensburger, Martin; Roybon, Laurent; Galler, Kerstin Martina; Wrasidlo, Wolfgang; Winner, Beate; Prots, Iryna (BMC Neuroscience, 2025)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein aggregates mostly consisting of misfolded alpha-synuclein (αSyn). Progressive degeneration of midbrain dopaminergic neurons (mDANs) and nigrostriatal projections results in severe motor symptoms. While the preferential loss of mDANs has not been fully understood yet, the cell type-specific vulnerability has been linked to a unique intracellular milieu, influenced by dopamine metabolism, high demand for mitochondrial activity, and increased level of oxidative stress (OS). These factors have been shown to adversely impact αSyn aggregation. Reciprocally, αSyn aggregates, in particular oligomers, can impair mitochondrial functions and exacerbate OS. Recent drug-discovery studies have identified a series of small molecules, including NPT100-18A, which reduce αSyn oligomerization by preventing misfolding and dimerization. NPT100-18A and structurally similar compounds (such as NPT200-11/UCB0599, currently being assessed in clinical studies) point towards a promising new approach for disease-modification. METHODS: Induced pluripotent stem cell (iPSC)-derived mDANs from PD patients with a monoallelic SNCA locus duplication and unaffected controls were treated with NPT100-18A. αSyn aggregation was evaluated biochemically and reactive oxygen species (ROS) levels were assessed in living mDANs using fluorescent dyes. Adenosine triphosphate (ATP) levels were measured using a luminescence-based assay, and neuronal cell death was evaluated by immunocytochemistry. RESULTS: Compared to controls, patient-derived mDANs exhibited higher cytoplasmic and mitochondrial ROS probe levels, reduced ATP-related signals, and increased activation of caspase-3, reflecting early neuronal cell death. NPT100-18A-treatment rescued cleaved caspase-3 levels to control levels and, importantly, attenuated mitochondrial oxidative stress probe levels in a compartment-specific manner and, at higher concentrations, increased ATP signals. CONCLUSIONS: Our findings demonstrate that NPT100-18A limits neuronal degeneration in a human in vitro model of PD. In addition, we provide first mechanistic insights into how a compartment-specific antioxidant effect in mitochondria might contribute to the neuroprotective effects of NPT100-18A.
EVALuna2:586322
Keywords: iPSC; Dopaminergic neurons; Alpha-synuclein; Aggregation; Parkinson’s disease; Oxidative stress; NPT100-18A; Mitochondria; ROS

Null mutation in PGAP1 impairing Gpi-anchor maturation in patients with intellectual disability and encephalopathy - Murakami, Yoshiko; Tawamie, Hasan; Maeda, Yusuke; Büttner, Christian; Buchert, Rebecca; Radwan, Farah; Sticht, Heinrich; Aigner, Michael; Reis, André; Kinoshita, Taroh; Abou Jamra, Rami; et al. (PLoS Genetics, 2014)
Many eukaryotic cell-surface proteins are anchored to the membrane via glycosylphosphatidylinositol (GPI). There are at least 26 genes involved in biosynthesis and remodeling of GPI anchors. Hypomorphic coding mutations in seven of these genes have been reported to cause decreased expression of GPI anchored proteins (GPI-APs) on the cell surface and to cause autosomal-recessive forms of intellectual disability (ARID). We performed homozygosity mapping and exome sequencing in a family with encephalopathy and non-specific ARID and identified a homozygous 3 bp deletion (p.Leu197del) in the GPI remodeling gene PGAP1. PGAP1 was not described in association with a human phenotype before. PGAP1 is a deacylase that removes an acyl-chain from the inositol of GPI anchors in the endoplasmic reticulum immediately after attachment of GPI to proteins. In silico prediction and molecular modeling strongly suggested a pathogenic effect of the identified deletion. The expression levels of GPI-APs on B lymphoblastoid cells derived from an affected person were normal. However, when those cells were incubated with phosphatidylinositol-specific phospholipase C (PI-PLC), GPI-APs were cleaved and released from B lymphoblastoid cells from healthy individuals whereas GPI-APs on the cells from the affected person were totally resistant. Transfection with wild type PGAP1 cDNA restored the PI-PLC sensitivity. These results indicate that GPI-APs were expressed with abnormal GPI structure due to a null mutation in the remodeling gene PGAP1. Our results add PGAP1 to the growing list of GPI abnormalities and indicate that not only the cell surface expression levels of GPI-APs but also the fine structure of GPI-anchors is important for the normal neurological developmen
EVALuna2:9210

Nutritional and hormonal regulation of lysyl oxidase-like 1 and elastic proteins involved in pseudoexfoliation syndrome/glaucoma - Zenkel, Matthias; Berner, Daniel; Hoja, Ursula; Pasutto, Francesca; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (2018)
EVALuna2:34739

Oligodendrocytes regulate the adhesion molecule ICAM-1 in neuroinflammation - Alvarado, M. N. Gonzalez; Aprato, J.; Baumeister, M.; Ekici, Arif Bülent; Kirchner, P.; Hoffmann, Alana; Winkler, Jürgen; Wegner, M.; Haase, S.; Linker, R. (Glia, 2021)
Recently, oligodendrocytes (Ol) have been attributed potential immunomodulatory effects. Yet, the exact mode of interaction with pathogenic CNS infiltrating lymphocytes remains unclear. Here, we attempt to dissect mechanisms of Ol modulation during neuroinflammation and characterize the interaction of Ol with pathogenic T cells. RNA expression analysis revealed an upregulation of immune-modulatory genes and adhesion molecules (AMs), ICAM-1 and VCAM-1, in Ol when isolated from mice undergoing experimental autoimmune encephalomyelitis (EAE). To explore whether AMs are involved in the interaction of Ol with infiltrating T cells, we performed co-culture studies on mature Ol and Th1 cells. Live cell imaging analysis showed direct interaction between both cell types. Eighty percentage of Th1 cells created contacts with Ol that lasted longer than 15 min, which may be regarded as physiologically relevant. Exposure of Ol to Th1 cells or their supernatant resulted in a significant extension of Ol processes, and upregulation of AMs as well as other immunomodulatory genes. Our observations indicate that blocking of oligodendroglial ICAM-1 can reduce the number of Th1 cells initially contacting the Ol. These results suggest that AMs may play a role in the interaction between Ol and Th1 cells. We identified Ol interacting with CD4+ cells in vivo in spinal cord tissue of EAE diseased mice indicating that our in vitro findings are of interest to further scientific research in this field. Further characterization and understanding of Ol interaction with infiltrating cells may lead to new therapeutic strategies enhancing Ol protection and remyelination potential. Oligodendrocytes regulate immune modulatory genes and adhesion molecules during autoimmune neuroinflammation Oligodendrocytes interact with Th1 cells in vitro in a physiologically relevant manner Adhesion molecules may be involved in Ol-Th1 cell interaction.
CRIS-Team WoS Importer:2021-07-16
Keywords: adhesion molecules; autoimmune neuroinflammation; EAE; oligodendrocytes; Th1 cells

Oligomer-prone E57K-mutant alpha-synuclein exacerbates integration deficit of adult hippocampal newborn neurons in transgenic mice - Regensburger, Martin; Schreglmann, Sebastian R.; Stoll, Svenja; Rockenstein, Edward; Loskarn, Sandra; Xiang, Wei; Masliah, Eliezer; Winner, Beate (Brain Structure & Function, 2017)
In the adult mammalian hippocampus, new neurons are constantly added to the dentate gyrus. Adult neurogenesis is impaired in several neurodegenerative mouse models including ?-synuclein (a-syn) transgenic mice. Among different a-syn species, a-syn oligomers were reported to be the most toxic species for neurons. Here, we studied the impact of wild-type vs. oligomer-prone a-syn on neurogenesis. We compared the wild-type a-syn transgenic mouse model (Thy1-WTS) to its equivalent transgenic for oligomer-prone E57K-mutant a-syn (Thy1-E57K). Transgenic a-syn was highly expressed within the hippocampus of both models, but was not present within adult neural stem cells and neuroblasts. Proliferation and survival of newly generated neurons were unchanged in both transgenic models. Thy1-WTS showed a minor integration deficit regarding mushroom spine density of newborn neurons, whereas Thy1-E57K exhibited a severe reduction of all spines. We conclude that cell-extrinsic a-syn impairs mushroom spine formation of adult newborn neurons and that oligomer-prone a-syn exacerbates this integration deficit. Moreover, our data suggest that a-syn reduces the survival of newborn neurons by a cell-intrinsic mechanism during the early neuroblast development. The finding of increased spine pathology in Thy1-E57K is a new pathogenic function of oligomeric a-syn and precedes overt neurodegeneration. Thus, it may constitute a readout for therapeutic approaches.
EVALuna2:4766

Oral Anticoagulants in the Oldest Old with Recent Stroke and Atrial Fibrillation - Polymeris, Alexandros A.; Macha, Kosmas; Paciaroni, Maurizio; Wilson, Duncan; Koga, Masatoshi; Cappellari, Manuel; Schaedelin, Sabine; Zietz, Annaelle; Peters, Nils; Seiffge, David J.; Haupenthal, David; Gaßmann, Luise; et al. (Annals of Neurology, 2021)
Objective To investigate the safety and effectiveness of direct oral anticoagulants (DOAC) versus vitamin K antagonists (VKA) after recent stroke in patients with atrial fibrillation (AF) aged >= 85 years. Methods Individual patient data analysis from seven prospective stroke cohorts. We compared DOAC versus VKA treatment among patients with AF and recent stroke (<3 months) aged >= 85 versus <85 years. Primary outcome was the composite of recurrent stroke, intracranial hemorrhage (ICH) and all-cause death. We used simple, adjusted, and weighted Cox regression to account for confounders. We calculated the net benefit of DOAC versus VKA by balancing stroke reduction against the weighted ICH risk. Results In total, 5,984 of 6,267 (95.5%) patients were eligible for analysis. Of those, 1,380 (23%) were aged >= 85 years and 3,688 (62%) received a DOAC. During 6,874 patient-years follow-up, the impact of anticoagulant type (DOAC versus VKA) on the hazard for the composite outcome did not differ between patients aged >= 85 (HR >= 85y = 0.65, 95%-CI [0.52, 0.81]) and < 85 years (HR<85y = 0.79, 95%-CI [0.66, 0.95]) in simple (p(interaction) = 0.129), adjusted (p(interaction) = 0.094) or weighted (p(interaction) = 0.512) models. Analyses on recurrent stroke, ICH and death separately were consistent with the primary analysis, as were sensitivity analyses using age dichotomized at 90 years and as a continuous variable. DOAC had a similar net clinical benefit in patients aged >= 85 (+1.73 to +2.66) and < 85 years (+1.90 to +3.36 events/100 patient-years for ICH-weights 1.5 to 3.1). Interpretation The favorable profile of DOAC over VKA in patients with AF and recent stroke was maintained in the oldest old. ANN NEUROL 2021
CRIS-Team WoS Importer:2021-12-10

Orally administered nanoparticles for gastrointestinal applications - Tietze, Rainer; Unterweger, Harald; Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Alexiou, Christoph (Nanomedicine, 2023)
CRIS-Team WoS Importer:2023-03-24

Organoids in gastrointestinal diseases: from experimental models to clinical translation - Günther, Claudia; Winner, Beate; Neurath, Markus; Stappenbeck, Thaddeus S. (Gut, 2022)
We are entering an era of medicine where increasingly sophisticated data will be obtained from patients to determine proper diagnosis, predict outcomes and direct therapies. We predict that the most valuable data will be produced by systems that are highly dynamic in both time and space. Three-dimensional (3D) organoids are poised to be such a highly valuable system for a variety of gastrointestinal (GI) diseases. In the lab, organoids have emerged as powerful systems to model molecular and cellular processes orchestrating natural and pathophysiological human tissue formation in remarkable detail. Preclinical studies have impressively demonstrated that these organs-in-a-dish can be used to model immunological, neoplastic, metabolic or infectious GI disorders by taking advantage of patient-derived material. Technological breakthroughs now allow to study cellular communication and molecular mechanisms of interorgan cross-talk in health and disease including communication along for example, the gut-brain axis or gut-liver axis. Despite considerable success in culturing classical 3D organoids from various parts of the GI tract, some challenges remain to develop these systems to best help patients. Novel platforms such as organ-on-a-chip, engineered biomimetic systems including engineered organoids, micromanufacturing, bioprinting and enhanced rigour and reproducibility will open improved avenues for tissue engineering, as well as regenerative and personalised medicine. This review will highlight some of the established methods and also some exciting novel perspectives on organoids in the fields of gastroenterology. At present, this field is poised to move forward and impact many currently intractable GI diseases in the form of novel diagnostics and therapeutics.
CRIS-Team WoS Importer:2022-06-17
Keywords: gastrointestinal pathology; gastrointestinal physiology; intestinal stem cell; stem cells

P2RX7 gene variants associate with altered inflammasome assembly and reduced pyroptosis in chronic nonbacterial osteomyelitis (CNO). - Charras, Amandine; Hofmann, Sigrun R.; Cox, Allison; Schulze, Felix; Russ, Susanne; Northey, Sarah; Liu, Xuan; Fang, Yongxiang; Haldenby, Sam; Hartmann, Hella; Bassuk, Alexander G.; Carvalho, Ana; et al. (Journal of Autoimmunity, 2024)
Chronic nonbacterial osteomyelitis (CNO), an autoinflammatory bone disease primarily affecting children, can cause pain, hyperostosis and fractures, affecting quality-of-life and psychomotor development. This study investigated CNO-associated variants in P2RX7, encoding for the ATP-dependent trans-membrane K+ channel P2X7, and their effects on NLRP3 inflammasome assembly. Whole exome sequencing in two related transgenerational CNO patients, and target sequencing of P2RX7 in a large CNO cohort (N = 190) were conducted. Results were compared with publicly available datasets and regional controls (N = 1873). Findings were integrated with demographic and clinical data. Patient-derived monocytes and genetically modified THP-1 cells were used to investigate potassium flux, inflammasome assembly, pyroptosis, and cytokine release. Rare presumably damaging P2RX7 variants were identified in two related CNO patients. Targeted P2RX7 sequencing identified 62 CNO patients with rare variants (32.4%), 11 of which (5.8%) carried presumably damaging variants (MAF <1%, SIFT "deleterious", Polyphen "probably damaging", CADD >20). This compared to 83 of 1873 controls (4.4%), 36 with rare and presumably damaging variants (1.9%). Across the CNO cohort, rare variants unique to one (Median: 42 versus 3.7) or more (≤11 patients) participants were over-represented when compared to 190 randomly selected controls. Patients with rare damaging variants more frequently experienced gastrointestinal symptoms and lymphadenopathy while having less spinal, joint and skin involvement (psoriasis). Monocyte-derived macrophages from patients, and genetically modified THP-1-derived macrophages reconstituted with CNO-associated P2RX7 variants exhibited altered potassium flux, inflammasome assembly, IL-1β and IL-18 release, and pyroptosis. Damaging P2RX7 variants occur in a small subset of CNO patients, and rare P2RX7 variants may represent a CNO risk factor. Observations argue for inflammasome inhibition and/or cytokine blockade and may allow future patient stratification and individualized care.
EVALuna2:558175

Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

PALB2, CHEK2 and ATM rare variants and cancer risk: data from COGS - Southey, Melissa C.; Goldgar, David E.; Winqvist, Robert; Pylkas, Katri; Couch, Fergus; Tischkowitz, Marc; Foulkes, William D.; Dennis, Joe; Michailidou, Kyriaki; Van Rensburg, Elizabeth J.; Heikkinen, Tuomas; Nevanlinna, Heli; et al. (Journal of Medical Genetics, 2016)
The rarity of mutations in PALB2, CHEK2 and ATM make it difficult to estimate precisely associated cancer risks. Population-based family studies have provided evidence that at least some of these mutations are associated with breast cancer risk as high as those associated with rare BRCA2 mutations. We aimed to estimate the relative risks associated with specific rare variants in PALB2, CHEK2 and ATM via a multicentre case-control study.We genotyped 10 rare mutations using the custom iCOGS array: PALB2 c.1592delT, c.2816T>G and c.3113G>A, CHEK2 c.349A>G, c.538C>T, c.715G>A, c.1036C>T, c.1312G>T, and c.1343T>G and ATM c.7271T>G. We assessed associations with breast cancer risk (42 671 cases and 42 164 controls), as well as prostate (22 301 cases and 22 320 controls) and ovarian (14 542 cases and 23 491 controls) cancer risk, for each variant.For European women, strong evidence of association with breast cancer risk was observed for PALB2 c.1592delT OR 3.44 (95% CI 1.39 to 8.52, p=7.1×10(-5)), PALB2 c.3113G>A OR 4.21 (95% CI 1.84 to 9.60, p=6.9×10(-8)) and ATM c.7271T>G OR 11.0 (95% CI 1.42 to 85.7, p=0.0012). We also found evidence of association with breast cancer risk for three variants in CHEK2, c.349A>G OR 2.26 (95% CI 1.29 to 3.95), c.1036C>T OR 5.06 (95% CI 1.09 to 23.5) and c.538C>T OR 1.33 (95% CI 1.05 to 1.67) (p<=0.017). Evidence for prostate cancer risk was observed for CHEK2 c.1343T>G OR 3.03 (95% CI 1.53 to 6.03, p=0.0006) for African men and CHEK2 c.1312G>T OR 2.21 (95% CI 1.06 to 4.63, p=0.030) for European men. No evidence of association with ovarian cancer was found for any of these variants.This report adds to accumulating evidence that at least some variants in these genes are associated with an increased risk of breast cancer that is clinically important.
EVALuna2:6832

Palmoplantar Pustular Psoriasis Is Associated with Missense Variants in CARD14, but Not with Loss-of-Function Mutations in IL36RN in European Patients - Moessner, Rotraut; Frambach, Yvonne; Wilsmann-Theis, Dagmar; Loehr, Sabine; Jacobi, Arnd; Weyergraf, Ansgar; Mueller, Michael; Philipp, Sandra; Renner, Regina; Traupe, Heiko; Burkhardt, Harald; Kingo, Kuelli; et al. (Journal of Investigative Dermatology, 2015)
EVALuna2:9269

Paradoxical antidepressant effects of alcohol are related to acid sphingomyelinase and its control of sphingolipid homeostasis - Müller, Christiane; Kalinichenko, Liubov; Tiesel, Jens; Witt, Matthias; Stöckl, Thomas; Sprenger, Eva; Fuchser, Jens; Beckmann, Janine; Praetner, Marc; Huber, Sabine; Amato, Davide; Mühle, Christiane; et al. (Acta Neuropathologica, 2016)
Alcohol is a widely consumed drug that can lead to addiction and severe brain damage. However, alcohol is also used as self-medication for psychiatric problems, such as depression, frequently resulting in depression-alcoholism comorbidity. Here, we identify the first molecular mechanism for alcohol use with the goal to self-medicate and ameliorate the behavioral symptoms of a genetically induced innate depression. An induced over-expression of acid sphingomyelinase (ASM), as was observed in depressed patients, enhanced the consumption of alcohol in a mouse model of depression. ASM hyperactivity facilitates the establishment of the conditioned behavioral effects of alcohol, and thus drug memories. Opposite effects on drinking and alcohol reward learning were observed in animals with reduced ASM function. Importantly, free-choice alcohol drinking-but not forced alcohol exposure-reduces depression-like behavior selectively in depressed animals through the normalization of brain ASM activity. No such effects were observed in normal mice. ASM hyperactivity caused sphingolipid and subsequent monoamine transmitter hypo-activity in the brain. Free-choice alcohol drinking restores nucleus accumbens sphingolipid- and monoamine homeostasis selectively in depressed mice. A gene expression analysis suggested strong control of ASM on the expression of genes related to the regulation of pH, ion transmembrane transport, behavioral fear response, neuroprotection and neuropeptide signaling pathways. These findings suggest that the paradoxical antidepressant effects of alcohol in depressed organisms are mediated by ASM and its control of sphingolipid homeostasis. Both emerge as a new treatment target specifically for depression-induced alcoholism.
EVALuna2:3919

Parkinson's disease or multiple system atrophy: potential separation by quantitative susceptibility mapping - Marxreiter, Franz; Lambrecht, Vera; Mennecke, Angelika; Hanspach, Jannis; Jukic, Jelena; Regensburger, Martin; Herrler, Jürgen; German, Alexander; Kassubek, Jan; Groen, Georg; Mueller, Hans-Peter; Laun, Frederik Bernd; et al. (Therapeutic Advances in Neurological Disorders, 2023)
Background:Due to the absence of robust biomarkers, and the low sensitivity and specificity of routine imaging techniques, the differential diagnosis between Parkinson's disease (PD) and multiple system atrophy (MSA) is challenging. High-field magnetic resonance imaging (MRI) opened up new possibilities regarding the analysis of pathological alterations associated with neurodegenerative processes. Recently, we have shown that quantitative susceptibility mapping (QSM) enables visualization and quantification of two major histopathologic hallmarks observed in MSA: reduced myelin density and iron accumulation in the basal ganglia of a transgenic murine model of MSA. It is therefore emerging as a promising imaging modality on the differential diagnosis of Parkinsonian syndromes. Objectives:To assess QSM on high-field MRI for the differential diagnosis of PD and MSA. Methods:We assessed 23 patients (nine PDs and 14 MSAs) and nine controls using QSM on 3T and 7T MRI scanners at two academic centers. Results:We observed increased susceptibility in MSA at 3T in prototypical subcortical and brainstem regions. Susceptibility measures of putamen, pallidum, and substantia nigra reached excellent diagnostic accuracy to separate both synucleinopathies. Increase toward 100% sensitivity and specificity was achieved using 7T MRI in a subset of patients. Magnetic susceptibility correlated with age in all groups, but not with disease duration in MSA. Sensitivity and specificity were particularly high for possible MSA, and reached 100% in the putamen. Conclusion:Putaminal susceptibility measures, in particular on ultra-high-field MRI, may distinguish MSA patients from both, PD and controls, allowing an early and sensitive diagnosis of MSA.
CRIS-Team WoS Importer:2023-03-17

Pathogenic PHIP Variants are Variably Associated With CAKUT - de Fallois, Jonathan; Sieckmann, Tobias; Schönauer, Ria; Petzold, Friederike; Münch, Johannes; Pauly, Melissa; Vasileiou, Georgia; Findeisen, Christin; Kampmeier, Antje; Kuechler, Alma; Reis, André; Decker, Eva; et al. (Kidney International Reports, 2024)
Introduction: Congenital anomalies of the kidney and urinary tract (CAKUT) represent the most common cause of chronic kidney disease in children. Although only 20% of cases can be genetically explained, the majority remain without an identified underlying etiology. The neurodevelopmental disorder Chung-Jansen syndrome (CHUJANS) is caused by haploinsufficiency of Pleckstrin homology domain-interacting protein (PHIP) and was previously associated with genital malformations. Anecdotal coincidence of CHUJANS and CAKUT prompted us to investigate whether urorenal malformations are part of the phenotypic spectrum of CHUJANS. Methods: Analysis of existing CHUJANS and CAKUT cohorts, consulting matchmaking platforms, and systematic literature review to look for additional patients with both CHUJANS and CAKUT. Prenatal expression studies in murine and human renal tissues to investigate the role for PHIP in kidney development. Results: We identified 4 novel and 8 published cases, indicating variable expressivity with a urorenogenital trait frequency of 5% to 35%. The prenatal expression studies supported a role for PHIP in normal kidney and urinary tract development. Conclusion: Pathogenic PHIP gene variants should be considered as causative in patients with syndromal CAKUT. Conversely, patients with CHUJANS should be clinically evaluated for urorenogenital manifestations. Because neurodevelopmental disorders are often associated with kidney phenotypes, an interdisciplinary re-evaluation offers promise in identifying incompletely penetrant kidney associations and uncovering novel molecular mechanisms of disturbed nephrogenesis.
CRIS-Team Scopus Importer:2024-06-21
Keywords: CAKUT; Chung-Jansen syndrome (CHUJANS); PHIP

Pathogenic SCN2A variants cause early-stage dysfunction in patient-derived neurons - Asadollahi, Reza; Delvendahl,; Muff, R.; Tan, G.; Rodrieguez, D. G.; Turan, Sören; Russo, M.; Oneda, B.; Joset, P.; Boonsawat, P.; Masood, R.; Mocera, M.; et al. (Human Molecular Genetics, 2023)
Pathogenic heterozygous variants in SCN2A, which encodes the neuronal sodium channel Na(V)1.2, cause different types of epilepsy or intellectual disability (ID)/autism without seizures. Previous studies using mouse models or heterologous systems suggest that Na(V)1.2 channel gain-of-function typically causes epilepsy, whereas loss-of-function leads to ID/autism. How altered channel biophysics translate into patient neurons remains unknown. Here, we investigated iPSC-derived early-stage cortical neurons from ID patients harboring diverse pathogenic SCN2A variants [p.(Leu611Valfs*35); p.(Arg937Cys); p.(Trp1716*)] and compared them with neurons from an epileptic encephalopathy (EE) patient [p.(Glu1803Gly)] and controls. ID neurons consistently expressed lower Na(V)1.2 protein levels. In neurons with the frameshift variant, Na(V)1.2 mRNA and protein levels were reduced by similar to 50%, suggesting nonsense-mediated decay and haploinsufficiency. In other ID neurons, only protein levels were reduced implying Na(V)1.2 instability. Electrophysiological analysis revealed decreased sodium current density and impaired action potential (AP) firing in ID neurons, consistent with reduced Na(V)1.2 levels. In contrast, epilepsy neurons displayed no change in Na(V)1.2 levels or sodium current density, but impaired sodium channel inactivation. Single-cell transcriptomics identified dysregulation of distinct molecular pathways including inhibition of oxidative phosphorylation in neurons with SCN2A haploinsufficiency and activation of calcium signaling and neurotransmission in epilepsy neurons. Together, our patient iPSC-derived neurons reveal characteristic sodium channel dysfunction consistent with biophysical changes previously observed in heterologous systems. Additionally, our model links the channel dysfunction in ID to reduced Na(V)1.2 levels and uncovers impaired AP firing in early-stage neurons. The altered molecular pathways may reflect a homeostatic response to Na(V)1.2 dysfunction and can guide further investigations.
CRIS-Team WoS Importer:2023-05-26

Patients with unstable angina pectoris show an increased frequency of the Fc gamma RIIa R131 allele - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Munoz, Luis Enrique; Klinghammer, Lutz; Voll, Reinhard E.; Leusen, Jeanette H.W.; Van De Winkel, Jan G.J.; Reis, André; Schett, Georg; Garlichs, Christoph; Herrmann, Martin (Autoimmunity, 2012)
Patients with Systemic Lupus Erythematosus (SLE) carry an increased risk for the development of coronary artery disease (CAD). The R131 allele of the Fc gamma receptor IIa (FcγRIIa) is associated with SLE incidence and disease severity but also with CAD. Compared to stable angina pectoris (SAP) the unstable angina (UAP), as a manifestation of destabilizing CAD, is associated with increased risk of persistent instability, myocardial infarction, and death. Identification of clinically relevant determinants for unstable angina promises reduction of UAP-associated mortality in patients with SLE. We conducted a clinical study among 553 consecutive patients with stable angina pectoris (n 330) and unstable angina pectoris (n 223). All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa. UAP, but not SAP was significantly associated with the R/R131 genotype (P < 0.001). In troponin-negative patients with angina carrying the R/R131 genotype the odds ratio for suffering from UAP was 4.02 (95% confidence interval, 2.526.41) compared to those with non-R/R131 genotypes. In a multivariable analysis, the R/R131 genotype independently predicted the risk for development of UAP in a model adjusted for classical atherogenic risk factors. Our data imply that risk stratification of SLE- and other high risk patients with troponin-negative angina could be significantly improved by FcγRIIa genotyping. © Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Allele R131; Coronary disease; Fc gamma receptor IIa; SLE; Stable; Unstable angina pectoris

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465

PAX5 biallelic genomic alterations define a novel subgroup of B-cell precursor acute lymphoblastic leukemia - Bastian, Lorenz; Schroeder, Michael P.; Eckert, Cornelia; Schlee, Cornelia; Tanchez, Jutta Ortiz; Kämpf, Sebastian; Wagner, Dimitrios L.; Schulze, Veronika; Isaakidis, Konstandina; Lázaro-Navarro, Juan; Hänzelmann, Sonja; James, Alva Rani; et al. (Leukemia, 2019)
Chromosomal rearrangements and specific aneuploidy patterns are initiating events and define subgroups in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). Here we analyzed 250 BCP-ALL cases and identified a novel subgroup (‘PAX5-plus’, n = 19) by distinct DNA methylation and gene expression profiles. All patients in this subgroup harbored mutations in the B-lineage transcription factor PAX5, with p.P80R as hotspot. Mutations either affected two independent codons, consistent with compound heterozygosity, or suffered LOH predominantly through chromosome 9p aberrations. These biallelic events resulted in disruption of PAX5 transcriptional programs regulating B-cell differentiation and tumor suppressor functions. Homozygous CDKN2A/B deletions and RAS-activating hotspot mutations were highly enriched as cooperating events in the genomic profile of PAX5-plus ALL. Together, this defined a specific pattern of triple alterations, exclusive to the novel subgroup. PAX5-plus ALL was observed in pediatric and adult patients. Although restricted by the limited sample size, a tendency for more favorable clinical outcome was observed, with 10 of 12 adult PAX5-plus patients achieving long-term survival. PAX5-plus represents the first BCP-ALL subgroup defined by sequence alterations in contrast to gross chromosomal events and exemplifies how deregulated differentiation (PAX5), impaired cell cycle control (CDKN2A/B) and sustained proliferative signaling (RAS) cooperatively drive leukemogenesis.
CRIS-Team Scopus Importer:2019-07-26

PEDF Is Associated with the Termination of Chondrocyte Phenotype and Catabolism of Cartilage Tissue - Klinger, Patricia; Lukassen, Sören; Ferrazzi, Fulvia; Ekici, Arif Bülent; Hotfiel, Thilo; Swoboda, Bernd; Aigner, T.; Gelse, Kolja (BioMed Research International, 2017)
Objective. To investigate the expression and target genes of pigment epithelium-derived factor (PEDF) in cartilage and chondrocytes, respectively. Methods. We analyzed the expression pattern of PEDF in different human cartilaginous tissues including articular cartilage, osteophytic cartilage, and fetal epiphyseal and growth plate cartilage, by immunohistochemistry and quantitative real-time (qRT) PCR. Transcriptome analysis after stimulation of human articular chondrocytes with rhPEDF was performed by RNA sequencing (RNA-Seq) and confirmed by qRT-PCR. Results. Immunohistochemically, PEDF could be detected in transient cartilaginous tissue that is prone to undergo endochondral ossification, including epiphyseal cartilage, growth plate cartilage, and osteophytic cartilage. In contrast, PEDF was hardly detected in healthy articular cartilage and in the superficial zone of epiphyses, regions that are characterized by a permanent stable chondrocyte phenotype. RNA-Seq analysis and qRT-PCR demonstrated that rhPEDF significantly induced the expression of a number of matrix-degrading factors including SAA1, MMP1, MMP3, and MMP13. Simultaneously, a number of cartilage-specific genes including COL2A1, COL9A2, COMP, and LECT were among the most significantly downregulated genes. Conclusions. PEDF represents a marker for transient cartilage during all neonatal and postnatal developmental stages and promotes the termination of cartilage tissue by upregulation of matrix-degrading factors and downregulation of cartilage-specific genes. These data provide the basis for novel strategies to stabilize the phenotype of articular cartilage and prevent its degradation.
EVALuna2:9364

Percent mammographic density and dense area as risk factors for breast cancer - Rauh, C.; Hack, Caroline; Häberle, Lothar; Hein, Alexander; Engel, Anne; Schrauder, Michael G.; Fasching, Peter; Jud, Sebastian; Ekici, Arif Bülent; Loehberg, C. R.; Meier-Meitinger, Martina; Ozan-Mergner, Sevil Julia; et al. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-based patients with a diagnosis of invasive breast cancer and healthy women as controls. A total of 561 patients and 376 controls with available mammographic density were included into this study. We describe the differences concerning the common risk factors BMI, parital status, use of hormone replacement therapy (HRT) and menopause between cases and controls and estimate the odds ratios for PMD and DA, adjusted for the mentioned risk factors. Furthermore we compare the prediction models with each other to find out whether the addition of DA improves the model. Results: Mammographic density and DA were highly correlated with each other. Both variables were as well correlated to the commonly known risk factors with an expected direction and strength, however PMD (ρ = 0.56) was stronger correlated to BMI than DA (ρ = 0.11). The group of women within the highest quartil of PMD had an OR of 2.12 (95 % CI: 1.25-3.62). This could not be seen for the fourth quartile concerning DA. However the assessment of breast cancer risk could be improved by including DA in a prediction model in addition to common risk factors and PMD. Conclusions: The inclusion of the parameter DA into a prediction model for breast cancer in addition to established risk factors and PMD could improve the breast cancer risk assessment. As DA is measured together with PMD in the process of computer-assisted assessment of PMD it might be considered to include it as one additional breast cancer risk factor that is obtained from breast imaging. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: breast cancer; mammographic density; risk

Perifoveal cone- And rod-mediated temporal contrast sensitivities in stargardt disease/fundus flavimaculatus - Fars, Julien; Pasutto, Francesca; Kremers, Jan; Huchzermeyer, Cord (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. The purpose of this study was to compare L-cone–driven, S-cone–driven, and rod-driven temporal contrast sensitivities (tCSs) in patients with Stargardt disease 1/fundus flavimaculatus (STGD1/FF). METHODS. Fourteen patients (eight male, six female; mean age, 43.21 ± 13.18 years) with genetically confirmed STGD1/FF participated in this study. A dedicated light-emitting diode stimulator was used to measure perifoveal tCSs in an annular test field (1°–6° of visual eccentricity) at temporal frequencies between 1 and 20 Hz. Photoreceptor classes were isolated with the triple silent substitution technique. To compare functional damage among photoreceptor classes, sensitivity deviations (decibels) were calculated based on age-related normal values and then averaged across those frequencies where perception is mediated by the same post-receptoral pathway (L-cone red–green opponent pathway: 1, 2, 4 Hz; luminance pathway: 12, 16, 20 Hz; S-cone pathway: 1, 2, 4 Hz; fast rod pathway: 8, 10, 12 Hz). Sensitivity deviations were compared with infrared scanning laser ophthalmoscopy (IR-SLO) and standard automated perimetry (SAP). RESULTS. Photoreceptor-driven tCSs were generally lower in patients with STGD1/FF than in normal subjects but were without systematic differences among photoreceptors. Although sensitivity deviations were significantly correlated between each other, only luminance-driven L-cone sensitivity deviations were significantly correlated with the IR-SLO area of hyporeflectance (AoH) and SAP central mean deviation within 6° eccentricity (MD6deg). CONCLUSIONS. No systematic differences between photoreceptor classes were detected; however, our data suggest that temporal contrasts detected by the luminance pathway were closely correlated with other clinical parameters (AoH and MD6deg) and might be most useful as functional biomarkers in clinical trials.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Fundus flavimaculatus; Perifovea; Photoreceptors; Stargardt disease; Temporal contrast sensitivity

PERIPHERAL PULSE MEASUREMENTS FOR THE DETECTION OF SILENT ATRIAL FIBRILLATION: RESULTS FROM THE PROSPECTIVE, CONTROLLED TRIAL "KNOW YOUR PULSE POST STROKE" - Kallmünzer, Bernd; Macha, Kosmas; Wang, Ruihao; Siedler, Gabriela; Stoll, Svenja; Marsch, Armin; Gerner, Stefan; Winder, Klemens; Koehn, J.; Schwab, Stefan; Koehrmann, M. (INTERNATIONAL JOURNAL OF STROKE, 2020)
CRIS-Team WoS Importer:2021-01-22

Phenotype and genotype of 87 patients with Mowat-Wilson syndrome and recommendations for care - Ivanovski, Ivan; Djuric, Olivera; Caraffi, Stefano Giuseppe; Santodirocco, Daniela; Pollazzon, Marzia; Rosato, Simonetta; Cordelli, Duccio Maria; Abdalla, Ebtesam; Accorsi, Patrizia; Adam, Margaret P.; Ajmone, Paola Francesca; Badura-Stronka, Magdalena; et al. (Genetics in Medicine, 2018)
PURPOSE: Mowat-Wilson syndrome (MWS) is a rare intellectual disability/multiple congenital anomalies syndrome caused by heterozygous mutation of the ZEB2 gene. It is generally underestimated because its rarity and phenotypic variability sometimes make it difficult to recognize. Here, we aimed to better delineate the phenotype, natural history, and genotype-phenotype correlations of MWS. METHODS: In a collaborative study, we analyzed clinical data for 87 patients with molecularly confirmed diagnosis. We described the prevalence of all clinical aspects, including attainment of neurodevelopmental milestones, and compared the data with the various types of underlying ZEB2 pathogenic variations. RESULTS: All anthropometric, somatic, and behavioral features reported here outline a variable but highly consistent phenotype. By presenting the most comprehensive evaluation of MWS to date, we define its clinical evolution occurring with age and derive suggestions for patient management. Furthermore, we observe that its severity correlates with the kind of ZEB2 variation involved, ranging from ZEB2 locus deletions, associated with severe phenotypes, to rare nonmissense intragenic mutations predicted to preserve some ZEB2 protein functionality, accompanying milder clinical presentations. CONCLUSION: Knowledge of the phenotypic spectrum of MWS and its correlation with the genotype will improve its detection rate and the prediction of its features, thus improving patient care.
EVALuna2:34827

PHENOTYPE OF VULNERABLE ATHEROSCLEROTIC PLAQUES SHOWS STRONG ASSOCIATION WITH SINGLE NUCLEOTIDE POLYMORPHISM ALLELES OF COMMON RISK VARIANTS FOR CORONARY ARTERY DISEASE - Furtmair, R.; Kühn, Charlotte; Koenig, C.; Ekici, Arif Bülent; Klinghammer, Lutz; Achenbach, Stephan; Reis, André; Tauchi, M.; Dietel, B. (2016)
EVALuna2:33679

Phenotypic variability in a large Czech family with a Dynamin 2-associated Charcot-Marie-Tooth neuropathy - Haberlova, J.; Mazanec, R.; Ridzon, P.; Barankova, L.; Nuernberg, G.; Nuernberg, P.; Sticht, Heinrich; Hühne, Kathrin; Seeman, P.; Rautenstrauss, Bernd (Journal of Neurogenetics, 2011)
Mutations in the Dynamin 2 gene (DNM2) cause autosomal dominant centronuclear myopathy or autosomal dominant (AD) Charcot-Marie-Tooth (CMT) disease. Here the authors report one large Czech family with 15 members affected with an AD CMT phenotype of extraordinary variability. Genetic linkage analysis using SNP arrays revealed a locus of about 9.6 Mb on chromosome 19p13.1-13.2. In this critical interval, 373 genes were located. The only gene herein known to be associated with an intermediate type of CMT was Dynamin 2 (DNM2). Subsequent sequence analysis of the DNM2 gene in the index patient revealed a novel missense mutation p.Met580Thr. This missense mutation segregated with the neuropathy, indicating the causal character of this mutation. The phenotype of CMT in this family shows mild to moderate impairment with relatively preserved upper limbs and a very broad range of the onset of clinical symptoms from an early onset around the age of 12 to the late onset during the fifth decade. Electrophysiology showed an intermediate type of peripheral neuropathy. The motor median nerve conduction velocity varied from 36 m/s to normal values with signs of asymmetrical affection of peripheral nerves. No additional symptoms such as cranial nerve involvement, cataract, and signs of neutropenia or myopathy syndrome were observed in any member of the family yet. The progression was slow with no loss of ambulation. The authors suggest that the characterization of clinical variability in a single family may help to direct the genetic analysis directly to the rarely observed DNM2 mutations.
EVALuna2:26266

Phosphorylation Modulates the Subcellular Localization of SOX11 - Balta, Elli-Anna; Wittmann, Marie-Theres; Jung, Matthias; Sock, Elisabeth; Häberle, Benjamin; Heim, Birgit; Von Zweydorf, Felix; Heppt, Jana; von Wittgenstein, Julia; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Frontiers in Molecular Neuroscience, 2018)
SOX11 is a key Transcription Factor (TF) in the regulation of embryonic and adult neurogenesis, whose mutation has recently been linked to an intellectual disability syndrome in humans. SOX11's transient activity during neurogenesis is critical to ensure the precise execution of the neurogenic program. Here, we report that SOX11 displays differential subcellular localizations during the course of neurogenesis. Western-Blot analysis of embryonic mouse brain lysates indicated that SOX11 is post-translationally modified by phosphorylation. Using Mass Spectrometry, we found 10 serine residues in the SOX11 protein that are putatively phosphorylated. Systematic analysis of phospho-mutant SOX11 resulted in the identification of the S30 residue, whose phosphorylation promotes nuclear over cytoplasmic localization of SOX11. Collectively, these findings uncover phosphorylation as a novel layer of regulation of the intellectual disability gene Sox11.
EVALuna2:35742

Phosphorylation of the neurogenic transcription factor SOX11 on serine 133 modulates neuronal morphogenesis - Balta, Elli-Anna; Schäffner, Iris; Wittmann, Marie-Theres; Sock, Elisabeth; Von Zweydorf, Felix; von Wittgenstein, Julia; Steib, Kathrin; Heim, Birgit; Kremmer, Elisabeth; Häberle, Benjamin; Ueffing, Marius; Lie, Dieter Chichung; et al. (Scientific Reports, 2018)
The intellectual disability gene, Sox11, encodes for a critical neurodevelopmental transcription factor with functions in precursor survival, neuronal fate determination, migration and morphogenesis. The mechanisms regulating SOX11's activity remain largely unknown. Mass spectrometric analysis uncovered that SOX11 can be post-translationally modified by phosphorylation. Here, we report that phosphorylatable serines surrounding the high-mobility group box modulate SOX11's transcriptional activity. Through Mass Spectrometry (MS), co-immunoprecipitation assays and in vitro phosphorylation assays followed by MS we verified that protein kinase A (PKA) interacts with SOX11 and phosphorylates it on S133. In vivo replacement of SoxC factors in developing adult-generated hippocampal neurons with SOX11 S133 phospho-mutants indicated that phosphorylation on S133 modulates dendrite development of adult-born dentate granule neurons, while reporter assays suggested that S133 phosphorylation fine-tunes the activation of select target genes. These data provide novel insight into the control of the critical neurodevelopmental regulator SOX11 and imply SOX11 as a mediator of PKA-regulated neuronal development.
EVALuna2:35738

Plasma Neurofilaments: Potential Biomarkers of SPG11-Related Hereditary Spastic Paraplegia - Krumm, Laura; Winkler, Jürgen; Winner, Beate; Regensburger, Martin (Movement Disorders, 2024)
CRIS-Team Scopus Importer:2024-03-08

Plectin-related scapuloperoneal myopathy with treatment-responsive myasthenic syndrome - Argente-Escrig, H.; Schultheis, D.; Kamm, L.; Schowalter, M.; Thiel, C.; Türk, M.; Clemen, C. S.; Muelas, N.; Castañón, M. J.; Wiche, G.; Herrmann, H.; Vilchez, J. J.; et al. (Neuropathology and Applied Neurobiology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Pluripotent stem cells in neurodegenerative and neurodevelopmental diseases. - Winner, Beate; Marchetto, Maria C. N.; Gage, Fred H. (Human Molecular Genetics, 2010)
Most of our current knowledge about cellular phenotypes in neurodevelopmental and neurodegenerative diseases in humans was gathered from studies in postmortem brain tissues. These samples often represent the end-stage of the disease and therefore are not always a fair representation of how the disease developed. Moreover, under these circumstances, the pathology observed could be a secondary effect rather than the authentic disease cellular phenotype. Likewise, the rodent models available do not always recapitulate the pathology from human diseases. In this review, we will examine recent literature on the use of induced pluripotent stem cells to model neurodegenerative and neurodevelopmental diseases. We highlight the characteristics of diseases like spinal muscular atrophy and familial dysautonomia that allowed partial modeling of the disease phenotype. We review human stem cell literature on common neurodegenerative late-onset diseases such as Parkinson's disease and amyotrophic lateral sclerosis where patients' cells have been successfully reprogrammed but a disease phenotype has not yet been described. So far, the technique is of great interest for early onset monogenetic neurodevelopmental diseases. We speculate about potential further experimental requirements and settings for reprogrammed neurons for in vitro disease modeling and drug discovery.

Polygenic Risk Scores for Prediction of Breast Cancer and Breast Cancer Subtypes - Mavaddat, Nasim; Michailidou, Kyriaki; Dennis, Joe; Lush, Michael; Fachal, Laura; Lee, Andrew; Tyrer, Jonathan P.; Chen, Ting-Huei; Wang, Qin; Bolla, Manjeet K.; Yang, Xin; Adank, Muriel A.; et al. (American Journal of Human Genetics, 2019)
Stratification of women according to their risk of breast cancer based on polygenic risk scores (PRSs) could improve screening and prevention strategies. Our aim was to develop PRSs, optimized for prediction of estrogen receptor (ER)-specific disease, from the largest available genome-wide association dataset and to empirically validate the PRSs in prospective studies. The development dataset comprised 94,075 case subjects and 75,017 control subjects of European ancestry from 69 studies, divided into training and validation sets. Samples were genotyped using genome-wide arrays, and single-nucleotide polymorphisms (SNPs) were selected by stepwise regression or lasso penalized regression. The best performing PRSs were validated in an independent test set comprising 11,428 case subjects and 18,323 control subjects from 10 prospective studies and 190,040 women from UK Biobank (3,215 incident breast cancers). For the best PRSs (313 SNPs), the odds ratio for overall disease per 1 standard deviation in ten prospective studies was 1.61 (95%CI: 1.57-1.65) with area under receiver-operator curve (AUC) = 0.630 (95%CI: 0.628-0.651). The lifetime risk of overall breast cancer in the top centile of the PRSs was 32.6%. Compared with women in the middle quintile, those in the highest 1% of risk had 4.37- and 2.78-fold risks, and those in the lowest 1% of risk had 0.16- and 0.27-fold risks, of developing ER-positive and ER-negative disease, respectively. Goodness-of-fit tests indicated that this PRS was well calibrated and predicts disease risk accurately in the tails of the distribution. This PRS is a powerful and reliable predictor of breast cancer risk that may improve breast cancer prevention programs.
EVALuna2:35122

Polyhydroxyphenylvalerate/polycaprolactone nanofibers improve the life-span and mechanoresponse of human IPSC-derived cortical neuronal cells - Cerrone, Federico; Pozner, Tatyana; Siddiqui, Aarif; Ceppi, Paolo; Winner, Beate; Rajendiran, Murugan; Babu, Ramesh; Ibrahim, Hossam S.; Rodriguez, Brian J.; Winkler, Jürgen; Murphy, Keith J.; O'Connor, Kevin E. (Materials Science and Engineering C, 2020)
The physico-chemical characteristics of the extracellular matrix (ECM) cause mechanical cues that could elicit responses in the survival rate of cortical neuronal cells. Efficient neurite outgrowth in vitro, is critical for successful cultivation of cortical neuronal cells and the potential for attempts at regeneration of the central nervous system (CNS) in vivo. Relatively soft and hydrophilic, microbially synthesized aromatic polyester, polyhydroxyphenylvalerate (PHPV) was blended 50:50 with the stiff and hydrophobic polycaprolactone (PCL) and electrospun in microfibers for use in a 3D (CellCrown™) configuration and in a 2D coverslip coated configuration. This blend allows a 2.3-fold increase in the life-span of human induced pluripotent stem derived cortical neuronal cells (hiPS) compared to pure PCL fibers. HiPS-derived cortical neuronal cells grown on PHPV/PCL fibers show a 3.8-fold higher cumulative neurite elaboration compared to neurites grown on PCL fibers only. 96% of cortical neuronal cells die after 8 days of growth when plated on PCL fibers alone while >83% and 55% are alive on PHPV/PCL fibers on day 8 and day 17, respectively. An increased migration rate of cortical neuronal cells is also promoted by the blend compared to the PCL fibers alone. The critical survival rate improvement of hiPS derived cortical neuronal cells on PHPV/PCL blend holds promise in using these biocompatible nanofibers as implantable materials for regenerative purposes of an active cortical neuronal population after full maturation in vitro.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cortical neurons; Electrospinning; HiPSC; Mechanoresponse; Neuroregeneration; Polyhydroxyalkanoates

Polymorphisms in a Putative Enhancer at the 10q21.2 Breast Cancer Risk Locus Regulate NRBF2 Expression - Darabi, Hatef; Mccue, Karen; Beesley, Jonathan; Michailidou, Kyriaki; Nord, Silje; Kar, Siddhartha; Humphreys, Keith; Thompson, Deborah; Ghoussaini, Maya; Bolla, Manjeet K.; Dennis, Joe; Wang, Qin; et al. (American Journal of Human Genetics, 2015)
Genome-wide association studies have identified SNPs near ZNF365 at 10q21.2 that are associated with both breast cancer risk and mammographic density. To identify the most likely causal SNPs, we fine mapped the association signal by genotyping 428 SNPs across the region in 89,050 European and 12,893 Asian case and control subjects from the Breast Cancer Association Consortium. We identified four independent sets of correlated, highly trait-associated variants (iCHAVs), three of which were located within ZNF365. The most strongly risk-associated SNP, rs10995201 in iCHAV1, showed clear evidence of association with both estrogen receptor (ER)-positive (OR = 0.85 [0.82-0.88]) and ER-negative (OR = 0.87 [0.82-0.91]) disease, and was also the SNP most strongly associated with percent mammographic density. iCHAV2 (lead SNP, chr10: 64,258,684:D) and iCHAV3 (lead SNP, rs7922449) were also associated with ER-positive (OR = 0.93 [0.91-0.95] and OR = 1.06 [1.03-1.09]) and ER-negative (OR = 0.95 [0.91-0.98] and OR = 1.08 [1.04-1.13]) disease. There was weaker evidence for iCHAV4, located 5' of ADO, associated only with ER-positive breast cancer (OR = 0.93 [0.90-0.96]). We found 12, 17, 18, and 2 candidate causal SNPs for breast cancer in iCHAVs 1-4, respectively. Chromosome conformation capture analysis showed that iCHAV2 interacts with the ZNF365 and NRBF2 (more than 600 kb away) promoters in normal and cancerous breast epithelial cells. Luciferase assays did not identify SNPs that affect transactivation of ZNF365, but identified a protective haplotype in iCHAV2, associated with silencing of the NRBF2 promoter, implicating this gene in the etiology of breast cancer.
EVALuna2:9266

Polymorphisms in inflammation pathway genes and endometrial cancer risk - Delahanty, Ryan J.; Xiang, Yong-Bing; Spurdle, Amanda; Beeghly-Fadiel, Alicia; Long, Jirong; Thompson, Deborah; Tomlinson, Ian; Yu, Herbert; Lambrechts, Diether; Doerk, Thilo; Goodman, Marc T.; Zheng, Ying; et al. (Cancer Epidemiology Biomarkers & Prevention, 2013)
Background: Experimental and epidemiologic evidence have suggested that chronic inflammation may play a critical role in endometrial carcinogenesis. Methods: To investigate this hypothesis, a two-stage study was carried out to evaluate single-nucleotide polymorphisms (SNP) in inflammatory pathway genes in association with endometrial cancer risk. In stage I, 64 candidate pathway genes were identified and 4,542 directly genotyped or imputed SNPs were analyzed among 832 endometrial cancer cases and 2,049 controls, using data from the Shanghai Endometrial Cancer Genetics Study. Linkage disequilibrium of stage I SNPs significantly associated with endometrial cancer (P < 0.05) indicated that the majority of associations could be linked to one of 24 distinct loci. One SNP from each of the 24 loci was then selected for follow-up genotyping. Of these, 21 SNPs were successfully designed and genotyped in stage II, which consisted of 10 additional studies including 6,604 endometrial cancer cases and 8,511 controls. Results: Five of the 21 SNPs had significant allelic odds ratios (ORs) and 95% confidence intervals (CI) as follows: FABP1, 0.92 (0.85-0.99); CXCL3, 1.16 (1.05-1.29); IL6, 1.08 (1.00-1.17); MSR1, 0.90 (0.82-0.98); and MMP9, 0.91 (0.87-0.97). Two of these polymorphisms were independently significant in the replication sample (rs352038 in CXCL3 and rs3918249 in MMP9). The association for the MMP9 polymorphism remained significant after Bonferroni correction and showed a significant association with endometrial cancer in both Asian- and European-ancestry samples. Conclusions: These findings lend support to the hypothesis that genetic polymorphisms in genes involved in the inflammatory pathway may contribute to genetic susceptibility to endometrial cancer. Impact statement: This study adds to the growing evidence that inflammation plays an important role in endometrial carcinogenesis. © 2012 American Association for Cancer Research.
CRIS-Team Scopus Importer:2021-07-19

Polymorphisms in the RANK/RANKL genes and their effect on bone specific prognosis in breast cancer patients - Hein, Alexander; Bayer, Christian M.; Schrauder, Michael G.; Haeberle, Lothar; Heusinger, Katharina; Strick, Reiner; Ruebner, Matthias; Lux, Michael P.; Renner, Stefan; Schulz-Wendtland, Rüdiger; Ekici, Arif Bülent; Hartmann, Arndt; et al. (BioMed Research International, 2014)
The receptor activator of NF-?B (RANK) pathway is involved in bone health as well as breast cancer (BC) pathogenesis and progression. Whereas the therapeutic implication of this pathway is established for the treatment of osteoporosis and bone metastases, the application in adjuvant BC is currently investigated. As genetic variants in this pathway have been described to influence bone health, aim of this study was the prognostic relevance of genetic variants in RANK and RANKL. Single nucleotide polymorphisms in RANK(L) (rs1054016/rs1805034/rs35211496) were genotyped and analyzed with regard to bone metastasis-free survival (BMFS), disease-free survival, and overall survival for a retrospective cohort of 1251 patients. Cox proportional hazard models were built to examine the prognostic influence in addition to commonly established prognostic factors. The SNP rs1054016 seems to influence BMFS. Patients with two minor alleles had a more favorable prognosis than patients with at least one common allele (HR 0.37 (95% CI: 0.17, 0.84)), whereas other outcome parameters remained unaffected. rs1805034 and rs35211496 had no prognostic relevance. The effect of rs1054016(RANKL) adds to the evidence that the RANK pathway plays a role in BC pathogenesis and progression with respect to BMFS, emphasizing the connection between BC and bone health.
EVALuna2:6628

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

Posttranscriptional Regulation of LOXL1 Expression Via Alternative Splicing and Nonsense-Mediated mRNA Decay as an Adaptive Stress Response - Berner, Daniel; Zenkel, Matthias; Pasutto, Francesca; Hoja, Ursula; Liravi, Panah; Gusek-Schneider, Gabriele C.; Kruse, Friedrich; Schödel, Johannes; Reis, André; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2017)
Alternative mRNA splicing coupled to nonsense-mediated decay (NMD) is a common mRNA surveillance pathway also known to dynamically modulate gene expression in response to cellular stress. Here, we investigated the involvement of this pathway in the regulation of lysyl oxidase-like 1 (LOXL1) expression in response to pseudoexfoliation (PEX)-associated pathophysiologic factors.Transcript levels of LOXL1 isoforms were determined in ocular tissues obtained from donor eyes without and with PEX syndrome. Pseudoexfoliation-relevant cell types, including human Tenon's capsule fibroblasts (hTCF) and trabecular meshwork cells (hTMC), were exposed to puromycin, caffeine, TGF-?1, homocysteine, IL-6, retinoic acid, UV-B radiation, oxidative stress, and mechanical stress for up to 48 hours. Western blot analysis was carried out using antibodies against LOXL1, (phosphorylated-) eukaryotic initiation factor 2-? (eIF2-?), and regulator of nonsense transcripts 2 (UPF2). RNA interference was used to knockdown UPF1-3 and Serine/threonine-protein kinase (SMG1).Constitutive expression of wild-type LOXL1 and alternatively spliced LOXL1-a transcripts was detected in all ocular tissues showing highest levels in trabecular meshwork and differential expression between PEX and control specimens. LOXL1-a transcripts were upregulated in hTCF and hTMC by NMD inhibitors puromycin and caffeine (>=6-fold; P < 0.01) or after knockdown of NMD core factors (>=2-fold; P < 0.05), whereas mRNA and protein levels of LOXL1 were reduced (<=0.8 fold; P < 0.05). Exposure of cells to various PEX-associated (stress) factors, including TGF-?1, UV-B light, oxidative stress, mechanical stress, and retinoic acid enhanced LOXL1-a transcript levels (>=1.5-fold; P < 0.05), while partially downregulating LOXL1 levels (<=0.7-fold; P < 0.05). Stress-induced inhibition of NMD was dependent on phosphorylation of eIF2?.These findings provide evidence for a functional role of alternative splicing coupled to NMD in the posttranscriptional regulation of LOXL1 gene expression and suggest this mechanism to represent a dynamic mode of adapting LOXL1 expression to PEX-associated environmental and nutritional cues.
EVALuna2:9393

Predicting Triple-Negative Breast Cancer Subtype Using Multiple Single Nucleotide Polymorphisms for Breast Cancer Risk and Several Variable Selection Methods - Häberle, Lothar; Hein, Alexander; Rübner, Matthias; Schneider, Michael; Ekici, Arif Bülent; Gaß, Paul; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lo, Wing-Yee; Schroth, Werner; Brauch, Hiltrud; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Studies of triple-negative breast cancer have recently been extending the inclusion criteria and incorporating additional molecular markers into the selection criteria, opening up scope for targeted therapies. The screening phases required for studies of this type are often prolonged, since the process of determining the molecular subtype and carrying out additional biomarker assessment is time-consuming. Parameters such as germline genotypes capable of predicting the molecular subtype before it becomes available from pathology might be helpful for treatment planning and optimizing the timing and cost of screening phases. This appears to be feasible, as rapid and low-cost genotyping methods are becoming increasingly available. The aim of this study was to identify single nucleotide polymorphisms (SNPs) for breast cancer risk capable of predicting triple negativity, in addition to clinical predictors, in breast cancer patients.This cross-sectional observational study included 1271 women with invasive breast cancer who were treated at a university hospital. A total of 76 validated breast cancer risk SNPs were successfully genotyped. Univariate associations between each SNP and triple negativity were explored using logistic regression analyses. Several variable selection and regression techniques were applied to identify a set of SNPs that together improve the prediction of triple negativity in addition to the clinical predictors of age at diagnosis and body mass index (BMI). The most accurate prediction method was determined by cross-validation.The SNP rs10069690 (TERT, CLPTM1L) was the only significant SNP (corrected p = 0.02) after correction of p values for multiple testing in the univariate analyses. This SNP and three additional SNPs from the genes RAD51B, CCND1, and FGFR2 were selected for prediction of triple negativity. The addition of these SNPs to clinical predictors increased the cross-validated area under the curve (AUC) from 0.618 to 0.625. Age at diagnosis was the strongest predictor, stronger than any genetic characteristics.Prediction of triple-negative breast cancer can be improved if SNPs associated with breast cancer risk are added to a prediction rule based on age at diagnosis and BMI. This finding could be used for prescreening purposes in complex molecular therapy studies for triple-negative breast cancer.
EVALuna2:6850

Prediction of breast cancer risk based on profiling with common genetic variants - Mavaddat, Nasim; Pharoah, Paul D. P.; Michailidou, Kyriaki; Tyrer, Jonathan; Brook, Mark N.; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Dunning, Alison M.; Shah, Mitul; Luben, Robert; Brown, Judith; et al. (Journal of the National Cancer Institute, 2015)
Data for multiple common susceptibility alleles for breast cancer may be combined to identify women at different levels of breast cancer risk. Such stratification could guide preventive and screening strategies. However, empirical evidence for genetic risk stratification is lacking.We investigated the value of using 77 breast cancer-associated single nucleotide polymorphisms (SNPs) for risk stratification, in a study of 33 673 breast cancer cases and 33 381 control women of European origin. We tested all possible pair-wise multiplicative interactions and constructed a 77-SNP polygenic risk score (PRS) for breast cancer overall and by estrogen receptor (ER) status. Absolute risks of breast cancer by PRS were derived from relative risk estimates and UK incidence and mortality rates.There was no strong evidence for departure from a multiplicative model for any SNP pair. Women in the highest 1% of the PRS had a three-fold increased risk of developing breast cancer compared with women in the middle quintile (odds ratio [OR] = 3.36, 95% confidence interval [CI] = 2.95 to 3.83). The ORs for ER-positive and ER-negative disease were 3.73 (95% CI = 3.24 to 4.30) and 2.80 (95% CI = 2.26 to 3.46), respectively. Lifetime risk of breast cancer for women in the lowest and highest quintiles of the PRS were 5.2% and 16.6% for a woman without family history, and 8.6% and 24.4% for a woman with a first-degree family history of breast cancer.The PRS stratifies breast cancer risk in women both with and without a family history of breast cancer. The observed level of risk discrimination could inform targeted screening and prevention strategies. Further discrimination may be achievable through combining the PRS with lifestyle/environmental factors, although these were not considered in this repor
EVALuna2:9271

Premature Osteoarthritis as Presenting Sign of Type II Collagenopathy: A Case Report and Literature Review - Husar-Memmer, Emma; Ekici, Arif Bülent; Al Kaissi, Ali; Sticht, Heinrich; Manger, Bernhard; Schett, Georg; Zwerina, Jochen (Seminars in Arthritis and Rheumatism, 2013)
Osteoarthritis (OA) is a frequent, chronic, and often disabling disease. Early-onset OA should prompt rheumatologists to search for underlying causes. We describe the clinical presentation and diagnosis of a patient with severe premature OA.We report a patient with severe polyarticular OA starting in young adulthood due to a heterozygous mutation in the COL2A1 gene. We discuss the clinical features, diagnosis, and known mutations of previously reported cases identified through a PubMed literature review.A 43-year-old Caucasian woman of normal stature presented with a 24-year history of symmetrical polyarticular OA involving both large and small joints. At the time of presentation, the patient already underwent 6 joint replacement surgeries. Family history was unremarkable. Clinical, serologic, radiographic, and histologic studies did not reveal any specific cause for this unusual clinical presentation. Genetic analysis revealed a heterozygous COL2A1 mutation (R519C) consistent with the clinical phenotype. Reviewing the literature, we discuss the clinical spectrum of type II collagenopathies emphasizing premature OA as the sole clinical manifestation.Unusual clinical presentations of OA should prompt investigations to search for an underlying cause. Type II collagenopathy should be considered in young adults with severe symmetrical OA even in the absence of other clinical features. A correct diagnosis allows classification and genetic counseling of the patient.
EVALuna2:9163

Prenatal androgen receptor activation determines adult alcohol and water drinking in a sex-specific way - Huber, Sabine; Zoicas, Iulia; Reichel, Martin; Mühle, Christiane; Büttner, Christian; Ekici, Arif Bülent; Eulenburg, Volker; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (Addiction Biology, 2017)
Alcohol use disorders are major psychiatric disorders. Correlational studies in humans suggested organizational hormonal effects during embryonic development as a risk factor for adult alcohol dependence. Permanent changes can be induced by the activity of sex hormones, like testosterone. Here, we demonstrate a relationship between prenatal androgen receptor (AR)-activation and adult alcohol as well as water drinking in mice in a sex-dependent fashion. Prenatal AR inhibition using the antagonist flutamide decreased adult male alcohol consumption. In contrast, prenatal AR activation by dihydrotestosterone (DHT) led to an increase in adult alcohol consumption in females. These effects were different in adult water drinking, flutamide increased water consumption in females and DHT increased water consumption in males. Prenatal flutamide reduced locomotion and anxiety in adult males but was ineffective in females. We found that prenatal AR activation controls adult levels of monoaminergic modulatory transmitters in the brain and blood hormone levels in a sex-specific way. RNA-Seq analysis confirmed a prenatal AR mediated control of adult expression of alcohol drinking-related genes like Bdnf and Per2. These findings demonstrate that prenatal androgen activity is a risk factor for the establishment of alcohol consumption in adults by its organizational effects.
EVALuna2:4035

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Prevalence of FOXC1 Variants in Individuals With a Suspected Diagnosis of Primary Congenital Glaucoma - Siggs, Owen M.; Souzeau, Emmanuelle; Pasutto, Francesca; Dubowsky, Andrew; Smith, James E. H.; Taranath, Deepa; Pater, John; Rait, Julian L.; Narita, Andrew; Mauri, Lucia; Del Longo, Alessandra; Reis, André; et al. (JAMA Ophthalmology, 2019)
IMPORTANCE Both primary and secondary forms of childhood glaucoma have many distinct causative mechanisms, and in many cases a cause is not immediately clear. The broad phenotypic spectrum of secondary glaucoma, particularly in individuals with variants in FOXC1 or PITX2 genes associated with Axenfeld-Rieger syndrome, makes it more difficult to diagnose patients with milder phenotypes. These cases are occasionally classified and managed as primary congenital glaucoma.
CRIS-Team WoS Importer:2019-04-25

Prevalence of hereditary tubulointerstitial kidney diseases in the German Chronic Kidney Disease study - Popp, Bernt; Ekici, Arif Bülent; Knaup, Karl; Schneider, Karen; Uebe, Steffen; Park, Jonghun; Bafna, Vineet; Meiselbach, Heike; Eckardt, Kai-Uwe; Schiffer, Mario; Wiesmann da Silva Reis, André; Kraus, Cornelia; et al. (European Journal of Human Genetics, 2022)
Hereditary chronic kidney disease (CKD) appears to be more frequent than the clinical perception. Exome sequencing (ES) studies in CKD cohorts could identify pathogenic variants in similar to 10% of individuals. Tubulointerstitial kidney diseases, showing no typical clinical/histologic finding but tubulointerstitial fibrosis, are particularly difficult to diagnose. We used a targeted panel (29 genes) and MUC1-SNaPshot to sequence 271 DNAs, selected in defined disease entities and age cutoffs from 5217 individuals in the German Chronic Kidney Disease cohort. We identified 33 pathogenic variants. Of these 27 (81.8%) were in COL4A3/4/5, the largest group being 15 COL4A5 variants with nine unrelated individuals carrying c.1871G>A, p.(Gly624Asp). We found three cysteine variants in UMOD, a novel missense and a novel splice variant in HNF1B and the homoplastic MTTF variant m.616T>C. Copy-number analysis identified a heterozygous COL4A5 deletion, and a HNF1B duplication/deletion, respectively. Overall, pathogenic variants were present in 12.5% (34/271) and variants of unknown significance in 9.6% (26/271) of selected individuals. Bioinformatic predictions paired with gold standard diagnostics for MUC1 (SNaPshot) could not identify the typical cytosine duplication ("c.428dupC") in any individual, implying that ADTKD-MUC1 is rare. Our study shows that >10% of selected individuals carry disease-causing variants in genes partly associated with tubulointerstitial kidney diseases. COL4A3/4/5 genes constitute the largest fraction, implying they are regularly overlooked using clinical Alport syndrome criteria and displaying the existence of phenocopies. We identified variants easily missed by some ES pipelines. The clinical filtering criteria applied enriched for an underlying genetic disorder.
CRIS-Team WoS Importer:2022-09-23

PRICKLE2 revisited—further evidence implicating PRICKLE2 in neurodevelopmental disorders - Bayat, Allan; Iqbal, Sumaiya; Borredy, Kim; Amiel, Jeanne; Zweier, Christiane; Barcia, Guilia; Kraus, Cornelia; Weyhreter, Heike; Bassuk, Alexander G.; Chopra, Maya; Rubboli, Guido; Moller, Rikke S. (European journal of human genetics, 2021)
PRICKLE2 encodes a member of a highly conserved family of proteins that are involved in the non-canonical Wnt and planar cell polarity signaling pathway. Prickle2 localizes to the post-synaptic density, and interacts with post-synaptic density protein 95 and the NMDA receptor. Loss-of-function variants in prickle2 orthologs cause seizures in flies and mice but evidence for the role of PRICKLE2 in human disease is conflicting. Our goal is to provide further evidence for the role of this gene in humans and define the phenotypic spectrum of PRICKLE2-related disorders. We report a cohort of six subjects from four unrelated families with heterozygous rare PRICKLE2 variants (NM_198859.4). Subjects were identified through an international collaboration. Detailed phenotypic and genetic assessment of the subjects were carried out and in addition, we assessed the variant pathogenicity using bioinformatic approaches. We identified two missense variants (c.122 C > T; p.(Pro41Leu), c.680 C > G; p.(Thr227Arg)), one nonsense variant (c.214 C > T; p.(Arg72*) and one frameshift variant (c.1286_1287delGT; p.(Ser429Thrfs*56)). While the p.(Ser429Thrfs*56) variant segregated with disease in a family with three affected females, the three remaining variants occurred de novo. Subjects shared a mild phenotype characterized by global developmental delay, behavioral difficulties ± epilepsy, autistic features, and attention deficit hyperactive disorder. Computational analysis of the missense variants suggest that the altered amino acid residues are likely to be located in protein regions important for function. This paper demonstrates that PRICKLE2 is involved in human neuronal development and that pathogenic variants in PRICKLE2 cause neurodevelopmental delay, behavioral difficulties and epilepsy in humans.
CRIS-Team Scopus Importer:2021-06-18

Primary cilia and SHH signaling impairments in human and mouse models of Parkinson's disease - Schmidt, Sebastian; Luecken, Malte D.; Truembach, Dietrich; Hembach, Sina; Niedermeier, Kristina M.; Wenck, Nicole; Pfluegler, Klaus; Stautner, Constantin; Boettcher, Anika; Lickert, Heiko; Ramirez-Suastegui, Ciro; Ahmad, Ruhel; et al. (Nature Communications, 2022)
Parkinson's disease (PD) as a progressive neurodegenerative disorder arises from multiple genetic and environmental factors. However, underlying pathological mechanisms remain poorly understood. Using multiplexed single-cell transcriptomics, we analyze human neural precursor cells (hNPCs) from sporadic PD (sPD) patients. Alterations in gene expression appear in pathways related to primary cilia (PC). Accordingly, in these hiPSC-derived hNPCs and neurons, we observe a shortening of PC. Additionally, we detect a shortening of PC in PINK1-deficient human cellular and mouse models of familial PD. Furthermore, in sPD models, the shortening of PC is accompanied by increased Sonic Hedgehog (SHH) signal transduction. Inhibition of this pathway rescues the alterations in PC morphology and mitochondrial dysfunction. Thus, increased SHH activity due to ciliary dysfunction may be required for the development of pathoetiological phenotypes observed in sPD like mitochondrial dysfunction. Inhibiting overactive SHH signaling may be a potential neuroprotective therapy for sPD.
CRIS-Team WoS Importer:2022-08-26

Progressive Kidney Failure by Angiotensinogen Inactivation in the Germline - Wopperer, Florian; Olinger, Eric; Wiesener, Antje; Broeker, Katharina A.E.; Knaup, Karl; Schaefer, Jan Thomas; Galiano, Matthias; Schneider, Karen; Schiffer, Mario; Büttner-Herold, Maike; Reis, André; Schmieder, Roland; et al. (Hypertension, 2024)
BACKGROUND: Autosomal recessive renal tubular dysgenesis is a rare, usually fatal inherited disorder of the REN (renin)angiotensin system. Herein, we report an adolescent individual experiencing an unknown chronic kidney disease and aim to provide novel insights into disease mechanisms. METHODS: Exome sequencing for a gene panel associated with renal disease was performed. The REN-angiotensin system was assessed by comprehensive biochemical analysis in blood. REN expression was determined in primary tubular cells by quantitative polymerase chain reaction and in situ hybridization on kidney biopsy samples. Allele frequencies of heterozygous and biallelic deleterious variants were determined by analysis of the Genomics England 100,000 Genomes Project. RESULTS: The patient was delivered prematurely after oligohydramnios was detected during pregnancy. Postnatally, he recovered from third-degree acute kidney injury but developed chronic kidney disease stage G3b over time. Exome sequencing revealed a previously reported pathogenic homozygous missense variant, p.(Arg375Gln), in the AGT (angiotensinogen) gene. Blood AGT concentrations were low, but plasma REN concentration and gene expression in kidney biopsy, vascular, and tubular cells revealed strong upregulation of REN. Angiotensin II and aldosterone in blood were not abnormally elevated. CONCLUSIONS: Renal tubular dysgenesis may present as chronic kidney disease with a variable phenotype, necessitating broad genetic analysis for diagnosis. Functional analysis of the renin-angiotensin system in a patient with AGT mutation revealed novel insights regarding compensatory upregulation of REN in vascular and tubular cells of the kidney and in plasma in response to depletion of AGT substrate as a source of Ang II (similarly observed with hepatic AGT silencing for the treatment of hypertension).
CRIS-Team Scopus Importer:2024-07-26
Keywords: angiotensinogen; exome; mass spectrometry; mutation; renin-angiotensin system

Pseudoexfoliation associated protective variant, rs7173049, reveals a novel regulatory region downstream of LOXL1 - Berner, Daniel; Pasutto, Francesca; Hoja, Ursula; Zenkel, Matthias; Ozaki, Mineo; Williams, Susan; Ramsay, Michele; Carmichael, Trevor R.; Kruse, Friedrich; Aung, Tin; Khor, Chiea Chuen; Reis, André; et al. (2018)
EVALuna2:34734

Pseudoexfoliation syndrome-associated genetic variants affect transcription factor binding and alternative splicing of LOXL1 - Pasutto, Francesca; Zenkel, Matthias; Hoja, Ursula; Berner, Daniel; Uebe, Steffen; Ferrazzi, Fulvia; Schödel, Johannes; Liravi, Panah; Ozaki, Mineo; Paoli, Daniela; Frezzotti, Paolo; Mizoguchi, Takanori; et al. (Nature Communications, 2017)
Although lysyl oxidase-like 1 (LOXL1) is known as the principal genetic risk factor for pseudoexfoliation (PEX) syndrome, a major cause of glaucoma and cardiovascular complications, no functional variants have been identified to date. Here, we conduct a genome-wide association scan on 771 German PEX patients and 1,350 controls, followed by independent testing of associated variants in Italian and Japanese data sets. We focus on a 3.5-kb four-component polymorphic locus positioned spanning introns 1 and 2 of LOXL1 with enhancer-like chromatin features. We find that the rs11638944:C>G transversion exerts a cis-acting effect on the expression levels of LOXL1, mediated by differential binding of the transcription factor RXR? (retinoid X receptor alpha) and by modulating alternative splicing of LOXL1, eventually leading to reduced levels of LOXL1 mRNA in cells and tissues of risk allele carriers. These findings uncover a functional mechanism by which common noncoding variants influence LOXL1 expression.
EVALuna2:9367

Psychiatric Disorders and Distal 21q Deletion-A Case Report - Briegel, Wolfgang; Hoyer, Juliane (International Journal of Environmental Research and Public Health, 2020)
Partial deletion of chromosome 21q is a very rare genetic condition with highly variable phenotypic features including heart defects, high or cleft palate, brain malformations (e.g., cerebral atrophy), developmental delay and intellectual disability. So far, there is very limited knowledge about psychiatric disorders and their effective treatment in this special population. To fill this gap, the authors present the case of an initially five-year-old girl with distal deletion (del21q22.2) and comorbid oppositional defiant disorder (main psychiatric diagnosis) covering a period of time of almost four years comprising initial psychological/psychiatric assessment, subsequent treatment with Parent-Child Interaction Therapy (PCIT), and follow-up assessments. Post-intervention results including a 19-month follow-up indicated good overall efficacy of PCIT and high parental satisfaction with the treatment. This case report makes a substantial contribution to enhancing knowledge on psychiatric comorbidity and its effective treatment in patients with terminal 21q deletion. Moreover, it emphasizes the necessity of multidisciplinarity in diagnosis and treatment due to the variety of anomalies associated with 21q deletion. Regular screenings for psychiatric disorders and (if indicated) thorough psychological and psychiatric assessment seem to be reasonable in most affected children, as children with developmental delays are at increased risk of developing psychiatric disorders. As demonstrated with this case report, PCIT seems to be a good choice to effectively reduce disruptive behaviors in young children with partial deletion of chromosome 21q.
CRIS-Team Scopus Importer:2020-05-15
Keywords: 21q22.2-q22.3; attention deficit/hyperactivity disorder; case report; chromosome 21; distal deletion; oppositional defiant disorder; Parent–Child Interaction Therapy (PCIT)

PTPN22 is associated with susceptibility to psoriatic arthritis but not psoriasis: evidence for a further PsA-specific risk locus - Bowes, John; Loehr, Sabine; Budu-Aggrey, Ashley; Uebe, Steffen; Bruce, Ian N.; Feletar, Marie; Marzo-Ortega, Helena; Helliwell, Philip; Ryan, Anthony W.; Kane, David; Korendowych, Eleanor; Alenius, Gerd-Marie; et al. (Annals of the Rheumatic Diseases, 2015)
Psoriatic arthritis (PsA) is a chronic inflammatory arthritis associated with psoriasis; it has a higher estimated genetic component than psoriasis alone, however most genetic susceptibility loci identified for PsA to date are also shared with psoriasis. Here we attempt to validate novel single nucleotide polymorphisms selected from our recent PsA Immunochip study and determine specificity to PsA.A total of 15 single nucleotide polymorphisms were selected (PImmunochip <1×10(-4)) for validation genotyping in 1177 cases and 2155 controls using TaqMan. Meta-analysis of Immunochip and validation data sets consisted of 3139 PsA cases and 11 078 controls. Novel PsA susceptibility loci were compared with data from two large psoriasis studies (WTCCC2 and Immunochip) to determine PsA specificity.We found genome-wide significant association to rs2476601, mapping to PTPN22 (p=1.49×10(-9), OR=1.32), but no evidence for association in the psoriasis cohort (p=0.34) and the effect estimates were significantly different between PsA and psoriasis (p=3.2×10(-4)). Additionally, we found genome-wide significant association to the previously reported psoriasis risk loci; NOS2 (rs4795067, p=5.27×10(-9)).For the first time, we report genome-wide significant association of PTPN22 (rs2476601) to PsA susceptibility, but no evidence for association to psoriasis.
EVALuna2:9275

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Rare deleterious mutations of HNRNP genes result in shared neurodevelopmental disorders - Gillentine, Madelyn A.; Wang, Tianyun; Hoekzema, Kendra; Rosenfeld, Jill; Liu, Pengfei; Guo, Hui; Kim, Chang N.; De Vries, Bert B. A.; Vissers, Lisenka E. L. M.; Nordenskjold, Magnus; Kvarnung, Malin; Lindstrand, Anna; et al. (Genome Medicine, 2021)
Background With the increasing number of genomic sequencing studies, hundreds of genes have been implicated in neurodevelopmental disorders (NDDs). The rate of gene discovery far outpaces our understanding of genotype-phenotype correlations, with clinical characterization remaining a bottleneck for understanding NDDs. Most disease-associated Mendelian genes are members of gene families, and we hypothesize that those with related molecular function share clinical presentations. Methods We tested our hypothesis by considering gene families that have multiple members with an enrichment of de novo variants among NDDs, as determined by previous meta-analyses. One of these gene families is the heterogeneous nuclear ribonucleoproteins (hnRNPs), which has 33 members, five of which have been recently identified as NDD genes (HNRNPK, HNRNPU, HNRNPH1, HNRNPH2, and HNRNPR) and two of which have significant enrichment in our previous meta-analysis of probands with NDDs (HNRNPU and SYNCRIP). Utilizing protein homology, mutation analyses, gene expression analyses, and phenotypic characterization, we provide evidence for variation in 12 HNRNP genes as candidates for NDDs. Seven are potentially novel while the remaining genes in the family likely do not significantly contribute to NDD risk. Results We report 119 new NDD cases (64 de novo variants) through sequencing and international collaborations and combined with published clinical case reports. We consider 235 cases with gene-disruptive single-nucleotide variants or indels and 15 cases with small copy number variants. Three hnRNP-encoding genes reach nominal or exome-wide significance for de novo variant enrichment, while nine are candidates for pathogenic mutations. Comparison of HNRNP gene expression shows a pattern consistent with a role in cerebral cortical development with enriched expression among radial glial progenitors. Clinical assessment of probands (n = 188-221) expands the phenotypes associated with HNRNP rare variants, and phenotypes associated with variation in the HNRNP genes distinguishes them as a subgroup of NDDs. Conclusions Overall, our novel approach of exploiting gene families in NDDs identifies new HNRNP-related disorders, expands the phenotypes of known HNRNP-related disorders, strongly implicates disruption of the hnRNPs as a whole in NDDs, and supports that NDD subtypes likely have shared molecular pathogenesis. To date, this is the first study to identify novel genetic disorders based on the presence of disorders in related genes. We also perform the first phenotypic analyses focusing on related genes. Finally, we show that radial glial expression of these genes is likely critical during neurodevelopment. This is important for diagnostics, as well as developing strategies to best study these genes for the development of therapeutics.
CRIS-Team WoS Importer:2021-05-21

Rare frameshift mutation in SERPINA3 contributes to generalized pustular psoriasis - Hüffmeier, Ulrike; Sticht, Heinrich; Wenzel, J.; Wilsmann-Theis, D.; Wolff, K.; Löhr, Sabine; Frey, Benjamin; Hahn, M.; Ekici, Arif Bülent; Uebe, S.; Thiel, Christian; Wiesmann da Silva Reis, André; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Rare Loss-of-Function Mutation in SERPINA3 in Generalized Pustular Psoriasis - Frey, Silke; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Gerschütz, Anne; Wolf, Katharina; Löhr, Sabine; Haskamp, Stefan; Frey, Benjamin; Hahn, Madelaine; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; et al. (Journal of Investigative Dermatology, 2020)
CRIS-Team Scopus Importer:2020-03-06

Recombinant pro-CTSD (cathepsin D) enhances SNCA/α-Synuclein degradation in α-Synucleinopathy models. - Huarcaya, Alice Prieto; Drobny, Susy; Marques, Andre R. A.; Di Spiezio, Alessandro; Dobert, Jan; Balta, Denise; Werner, Christian; Rizo Garza, Tania; Gallwitz, Lisa; Bub, Simon; Stojkovska, Iva; Belur, Nandkishore R.; et al. (Autophagy, 2022)
Parkinson disease (PD) is a neurodegenerative disorder characterized by the abnormal intracellular accumulation of SNCA/α-synuclein. While the exact mechanisms underlying SNCA pathology are not fully understood, increasing evidence suggests the involvement of autophagy as well as lysosomal deficiencies. Because CTSD (cathepsin D) has been proposed to be the major lysosomal protease involved in SNCA degradation, its deficiency has been linked to the presence of insoluble SNCA conformers in the brain of mice and humans as well as to the transcellular transmission of SNCA aggregates. We here postulate that SNCA degradation can be enhanced by the application of the recombinant human proform of CTSD (rHsCTSD). Our results reveal that rHsCTSD is efficiently endocytosed by neuronal cells, correctly targeted to lysosomes and matured to an enzymatically active protease. In dopaminergic neurons derived from induced pluripotent stem cells (iPSC) of PD patients harboring the A53T mutation within the SNCA gene, we confirm the reduction of insoluble SNCA after treatment with rHsCTSD. Moreover, we demonstrate a decrease of pathological SNCA conformers in the brain and within primary neurons of a ctsd-deficient mouse model after dosing with rHsCTSD. Boosting lysosomal CTSD activity not only enhanced SNCA clearance in human and murine neurons as well as tissue, but also restored endo-lysosome and autophagy function. Our findings indicate that CTSD is critical for SNCA clearance and function. Thus, enzyme replacement strategies utilizing CTSD may also be of therapeutic interest for the treatment of PD and other synucleinopathies aiming to decrease the SNCA burden.Abbreviations: aa: amino acid; SNCA/α-synuclein: synuclein alpha; APP: amyloid beta precursor protein; BBB: blood brain barrier; BF: basal forebrain; CBB: Coomassie Brilliant Blue; CLN: neuronal ceroid lipofuscinosis; CNL10: neuronal ceroid lipofuscinosis type 10; Corr.: corrected; CTSD: cathepsin D; CTSB: cathepsin B; DA: dopaminergic; DA-iPSn: induced pluripotent stem cell-derived dopaminergic neurons; dox: doxycycline; ERT: enzyme replacement therapy; Fx: fornix, GBA/β-glucocerebrosidase: glucosylceramidase beta; h: hour; HC: hippocampus; HT: hypothalamus; i.c.: intracranially; IF: immunofluorescence; iPSC: induced pluripotent stem cell; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LSDs: lysosomal storage disorders; MAPT: microtubule associated protein tau; M6P: mannose-6-phosphate; M6PR: mannose-6-phosphate receptor; MB: midbrain; mCTSD: mature form of CTSD; neurofil.: neurofilament; PD: Parkinson disease; proCTSD: proform of CTSD; PRNP: prion protein; RFU: relative fluorescence units; rHsCTSD: recombinant human proCTSD; SAPC: Saposin C; SIM: structured illumination microscopy; T-insol: Triton-insoluble; T-sol: Triton-soluble; TEM: transmission electron microscopy, TH: tyrosine hydroxylase; Thal: thalamus.
Keywords: alpha-synuclein; cathepsin D; lysosomal degradation; lysosomal storage disorders; parkinson disease; synucleinopathies

Recurrent null mutation in SPG20 leads to Troyer syndrome - Tawamie, Hasan; Wohlleber, Eva; Uebe, Steffen; Schmael, Christine; Noethen, Markus M.; Abou Jamra, Rami (Molecular and Cellular Probes, 2015)
Troyer syndrome is an autosomal recessive form of complex hereditary spastic paraplegia. To date, the disorder has only been described in the Amish and in kindred from Oman. In Amish, all affected individuals have a homozygous one nucleotide deletion; c.1110delA. In the Omani kindred, all affected have a homozygous two nucleotides deletion; c.364_365delTA (p.Met122ValfsTer2). Here we report the results of homozygosity mapping and whole exome sequencing in two siblings of a consanguineous Turkish family with mild intellectual disability, spastic paraplegia, and muscular dystrophy. We identified the same deletion that has been identified in the Omani kindred, but haplotype analysis suggests a recurrent event, and not a founder mutation. We summarize current knowledge of Troyer syndrome, and propose wider use of whole exome sequencing in routine diagnostics. This applies in particular to nonspecific phenotypes with high heterogeneity, such as spastic paraplegia, intellectual disability, and muscular dystrophy, since in such cases the assignment of a definite diagnosis is frequently delayed.
EVALuna2:9263

Reduced synaptic activity and dysregulated extracellular matrix pathways in midbrain neurons from Parkinson’s disease patients - Stern, Shani; Lau, Shong; Manole, Andreea; Rosh, Idan; Percia, Menachem Mendel; Ben Ezer, Ran; Shokhirev, Maxim N.; Qiu, Fan; Schafer, Simon; Mansour, Abed Alfatah; Mangan, Kile P.; Stern, Tchelet; et al. (npj Parkinson’s Disease, 2022)
Several mutations that cause Parkinson’s disease (PD) have been identified over the past decade. These account for 15–25% of PD cases; the rest of the cases are considered sporadic. Currently, it is accepted that PD is not a single monolithic disease but rather a constellation of diseases with some common phenotypes. While rodent models exist for some of the PD-causing mutations, research on the sporadic forms of PD is lagging due to a lack of cellular models. In our study, we differentiated PD patient-derived dopaminergic (DA) neurons from the induced pluripotent stem cells (iPSCs) of several PD-causing mutations as well as from sporadic PD patients. Strikingly, we observed a common neurophysiological phenotype: neurons derived from PD patients had a severe reduction in the rate of synaptic currents compared to those derived from healthy controls. While the relationship between mutations in genes such as the SNCA and LRRK2 and a reduction in synaptic transmission has been investigated before, here we show evidence that the pathogenesis of the synapses in neurons is a general phenotype in PD. Analysis of RNA sequencing results displayed changes in gene expression in different synaptic mechanisms as well as other affected pathways such as extracellular matrix-related pathways. Some of these dysregulated pathways are common to all PD patients (monogenic or idiopathic). Our data, therefore, show changes that are central and convergent to PD and suggest a strong involvement of the tetra-partite synapse in PD pathophysiology.
CRIS-Team Scopus Importer:2022-08-26

Refined histopathological predictors of BRCA1 and BRCA2 mutation status: a large-scale analysis of breast cancer characteristics from the BCAC, CIMBA, and ENIGMA consortia - Spurdle, Amanda B.; Couch, Fergus J.; Parsons, Michael T.; Mcguffog, Lesley; Barrowdale, Daniel; Bolla, Manjeet K.; Wang, Qin; Healey, Sue; Schmutzler, Rita Katharina; Wappenschmidt, Barbara; Rhiem, Kerstin; Hahnen, Eric; et al. (Breast Cancer Research, 2014)
The distribution of histopathological features of invasive breast tumors in BRCA1 or BRCA2 germline mutation carriers differs from that of individuals with no known mutation. Histopathological features thus have utility for mutation prediction, including statistical modeling to assess pathogenicity of BRCA1 or BRCA2 variants of uncertain clinical significance. We analyzed large pathology datasets accrued by the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) and the Breast Cancer Association Consortium (BCAC) to reassess histopathological predictors of BRCA1 and BRCA2 mutation status, and provide robust likelihood ratio (LR) estimates for statistical modeling.Selection criteria for study/center inclusion were estrogen receptor (ER) status or grade data available for invasive breast cancer diagnosed younger than 70 years. The dataset included 4,477 BRCA1 mutation carriers, 2,565 BRCA2 mutation carriers, and 47,565 BCAC breast cancer cases. Country-stratified estimates of the likelihood of mutation status by histopathological markers were derived using a Mantel-Haenszel approach.ER-positive phenotype negatively predicted BRCA1 mutation status, irrespective of grade (LRs from 0.08 to 0.90). ER-negative grade 3 histopathology was more predictive of positive BRCA1 mutation status in women 50 years or older (LR = 4.13 (3.70 to 4.62)) versus younger than 50 years (LR = 3.16 (2.96 to 3.37)). For BRCA2, ER-positive grade 3 phenotype modestly predicted positive mutation status irrespective of age (LR = 1.7-fold), whereas ER-negative grade 3 features modestly predicted positive mutation status at 50 years or older (LR = 1.54 (1.27 to 1.88)). Triple-negative tumor status was highly predictive of BRCA1 mutation status for women younger than 50 years (LR = 3.73 (3.43 to 4.05)) and 50 years or older (LR = 4.41 (3.86 to 5.04)), and modestly predictive of positive BRCA2 mutation status in women 50 years or older (LR = 1.79 (1.42 to 2.24)).These results refine likelihood-ratio estimates for predicting BRCA1 and BRCA2 mutation status by using commonly measured histopathological features. Age at diagnosis is an important variable for most analyses, and grade is more informative than ER status for BRCA2 mutation carrier prediction. The estimates will improve BRCA1 and BRCA2 variant classification and inform patient mutation testing and clinical management.
EVALuna2:9304

Regulation of Lysyl Oxidase-like 1 (LOXL1) and Elastin-Related Genes by Pathogenic Factors Associated with Pseudoexfoliation Syndrome - Zenkel, Matthias; Krysta, Anita; Pasutto, Francesca; Jünemann, Anselm; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2011)
Purpose. Pseudoexfoliation (PEX) syndrome/glaucoma is a complex, late-onset disorder of the elastic fiber system. Strong genetic risk is conferred by the lysyl oxidase-like 1 (LOXL1) gene, but additional comodulating factors are necessary for the manifestation of the disease. The aim of this study was to analyze the effect of various PEX-associated pathogenic factors on the genotype-correlated expression of LOXL1 and elastin-related genes. Methods. Cultured human Tenon's capsule fibroblasts with high- and low-risk LOXL1 haplotypes were exposed to transforming growth factor (TGF)-?1, interleukin (IL)-6, homocysteine, oxidative stress, hypoxia, or ultraviolet (UV) radiation. Changes in the expression of LOXL1 and elastic constituents of PEX material and TGF-?1 were assessed by quantitative real-time PCR, Western blotting, immunohistochemistry, and electron microscopy. Results. Treatment of fibroblasts with TGF-?1, oxidative stress, UV light, and hypoxia induced a significant increase in expression levels of LOXL1 and elastic proteins, whereas the effect of IL-6 was limited to induction of elastic constituents. Immunohistochemistry and electron microscopy confirmed an upregulation of LOXL1 and elastic fiber proteins and their assembly into extracellular microfibrillar networks with focal aggregation of microfibrils into PEX-like fibrils on stimulation with TGF-?1 and oxidative stress. Basal and stimulated expression of LOXL1 mRNA and protein was slightly decreased in cells carrying the high-risk compared with the low-risk haplotype of LOXL1, but the differences between groups were statistically not significant. Conclusions. The findings support the notion that both genetic and nongenetic fibrogenic factors, particularly TGF-?1 and oxidative stress, may cooperate in the stable accumulation of PEX aggregates.
EVALuna2:9087

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

Replication of a distinct psoriatic arthritis risk variant at the IL23R locus - Budu-Aggrey, Ashley; Bowes, John; Loehr, Sabine; Uebe, Steffen; Zervou, Maria I.; Helliwell, Philip; Ryan, Anthony W.; Kane, David; Korendowych, Eleanor; Giardina, Emiliano; Packham, Jonathan; Mcmanus, Ross; et al. (Annals of the Rheumatic Diseases, 2016)
EVALuna2:9332

Reset of inflammatory priming of joint tissue and reduction of the severity of arthritis flares by bromodomain inhibition - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al. (Arthritis and Rheumatology, 2023)
Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extra-terminal motif (BET) proteins translate epigenetic changes into transcription. Here we used a BET inhibitor to target inflammatory tissue priming and reduce flare severity in experimental arthritis. Methods: BALB/c mice were treated intraperitoneally or locally into the paw with I-BET151, which blocks interaction of BET proteins with acetylated histones. Effect of I-BET151 on acute arthritis and/or inflammatory tissue priming was assessed in a model of repeated injections of monosodium urate crystals or zymosan into the paw. I-BET151 was given either from before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. Transcriptomic (RNA-Seq), epigenomic (ATAC-Seq) and functional analysis (invasion, cytokine production, migration, senescence, metabolic flux) was performed on murine and human SFs treated with I-BET151 in vitro or in vivo. Results: Systemic I-BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I-BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, which makes them promising therapeutic targets for preventing arthritis flares in previously affected joints.
CRIS-Team Scopus Importer:2023-01-27

Residual homing of alpha 4 beta 7-expressing beta 1(+)PI16(+) regulatory T cells with potent suppressive activity correlates with exposure-efficacy of vedolizumab - Becker, Emily; Dedden, Mark; Gall, Christine; Wiendl, Maximilian; Ekici, Arif Bülent; Schulz-Kuhnt, Anja; Schweda, Anna; Bosch-Voskens, Caroline; Hegazy, Ahmed; Vitali, Francesco; Atreya, Raja; Müller, Tanja; et al. (Gut, 2021)
Objective The anti-alpha 4 beta 7 integrin antibody vedolizumab is administered at a fixed dose for the treatment of IBDs. This leads to a wide range of serum concentrations in patients and previous studies had suggested that highest exposure levels are associated with suboptimal clinical response. We aimed to determine the mechanisms underlying these non-linear exposure-efficacy characteristics of vedolizumab. Design We characterised over 500 samples from more than 300 subjects. We studied the binding of vedolizumab to T cells and investigated the functional consequences for dynamic adhesion, transmigration, gut homing and free binding sites in vivo. Employing single-cell RNA sequencing, we characterised alpha 4 beta 7 integrin-expressing T cell populations 'resistant' to vedolizumab and validated our findings in vitro and in samples from vedolizumab-treated patients with IBD. We also correlated our findings with a post-hoc analysis of the Gemini II and III studies. Results Regulatory T (T-Reg) cells exhibited a right-shifted vedolizumab binding profile compared with effector T (T-Eff) cells. Consistently, in a certain concentration range, the residual adhesion, transmigration, homing of and availability of functional alpha 4 beta 7 on T-Reg cells in vivo was higher than that of/on T-Eff cells. We identified a vedolizumab-'resistant' alpha 4 beta 7-expressing beta 1(+)PI16(+) T-Reg cell subset with pronounced regulatory properties as the substrate for this effect. Our observations correlated with exposure-efficacy data from Gemini II and III trials. Conclusion Completely blocking T-Eff cell trafficking with vedolizumab, while simultaneously permitting residual homing of powerful T-Reg cells in an optimal 'therapeutic window' based on target exposure levels might be a strategy to optimise treatment outcomes in patients with IBD.
CRIS-Team WoS Importer:2021-12-10

Restricted expression of mGCMa in kidney ind thymus - Hashemolhosseini, Said; Hadjihannas, Michel; Haase, Christian; Amann, Kerstin Ute; Wegner, Michael (Mechanisms of Development, 2002)
UnivIS-Import:2015-04-14:Pub.2002.forsch.sonder.sfb423.restri

Rhinovirus inhibits IL-17A and the downstream immune responses in allergic asthma - Graser, Anna; Ekici, Arif Bülent; Sopel, Nina; Melichar, V. O.; Zimmermann, Theodor; Papadopoulos, N. G.; Taka, S.; Ferrazzi, Fulvia; Vuorinen, T.; Finotto, Susetta (Mucosal Immunology, 2016)
The proinflammatory cytokine interleukin-17A (IL-17A) is known to mediate antimicrobial activity, but its role during rhinovirus (RV) infections and in asthma needs further investigation. Therefore, we addressed the role of IL-17A during allergic asthma and antiviral immune response in human and murine immunocompetent cells. In this study we found that asthmatic children with a RV infection in their upper airways have upregulated mRNA levels of the antiviral cytokine interferon type I (IFN)-? and the transcription factor T-box 21 (TBX21) and reduced levels of IL-17A protein in their peripheral blood mononuclear cells (PBMCs). We also found that IL-17A inhibited RV1b replication in infected human lung epithelial cells A549. Furthermore, by using gene array analysis we discovered that targeted deletion of Il17a in murine lung CD4(+) T cells impaired Oas1g mRNA downstream of Ifn?, independently from RV infection. Additionally, in PBMCs of children with a RV infection in their nasalpharyngeal fluid OAS1 gene expression was found downregulated. Finally RV1b inhibited IL-17A production in lung CD4(+) T cells in a setting of experimental asthma. These results indicate that the RV1b inhibits IL-17A in T helper type 17 cells and IL-17A clears RV1b infection in epithelial cells. In both cases IL-17A contributes to fend off RV1b infection by inducing genes downstream of interferon type I pathway.
EVALuna2:9312

Rhinovirus species/genotypes and interferon-λ: subtypes, receptor and polymorphisms - missing pieces of the puzzle of childhood asthma? - Bergauer, Annika; Sopel, Nina; Kro, Bettina; Vuorinen, Tytti; Xepapadaki, Paraskevi; Weiss, Scott T.; Blau, Ashley; Sharma, Himanshu; Kraus, Cornelia; Springel, Rebekka; Rauh, Manfred; Mittler, Susanne; et al. (European Respiratory Journal, 2017)
EVALuna2:25986

Risk of Ovarian Cancer and the NF-?B Pathway: Genetic Association with IL1A and TNFSF10 - Charbonneau, Bridget; Block, Matthew S.; Bamlet, William R.; Vierkant, Robert A.; Kalli, Kimberly R.; Fogarty, Zachary; Rider, David N.; Sellers, Thomas A.; Tworoger, Shelley S.; Poole, Elizabeth; Risch, Harvey A.; Salvesen, Helga B.; et al. (Cancer Research, 2014)
A missense single-nucleotide polymorphism (SNP) in the immune modulatory gene IL1A has been associated with ovarian cancer risk (rs17561). Although the exact mechanism through which this SNP alters risk of ovarian cancer is not clearly understood, rs17561 has also been associated with risk of endometriosis, an epidemiologic risk factor for ovarian cancer. Interleukin-1? (IL1A) is both regulated by and able to activate NF-?B, a transcription factor family that induces transcription of many proinflammatory genes and may be an important mediator in carcinogenesis. We therefore tagged SNPs in more than 200 genes in the NF-?B pathway for a total of 2,282 SNPs (including rs17561) for genotype analysis of 15,604 cases of ovarian cancer in patients of European descent, including 6,179 of high-grade serous (HGS), 2,100 endometrioid, 1,591 mucinous, 1,034 clear cell, and 1,016 low-grade serous, including 23,235 control cases spanning 40 studies in the Ovarian Cancer Association Consortium. In this large population, we confirmed the association between rs17561 and clear cell ovarian cancer [OR, 0.84; 95% confidence interval (CI), 0.76-0.93; P = 0.00075], which remained intact even after excluding participants in the prior study (OR, 0.85; 95% CI, 0.75-0.95; P = 0.006). Considering a multiple-testing-corrected significance threshold of P < 2.5 × 10(-5), only one other variant, the TNFSF10 SNP rs6785617, was associated significantly with a risk of ovarian cancer (low malignant potential tumors OR, 0.85; 95% CI, 0.79-0.91; P = 0.00002). Our results extend the evidence that borderline tumors may have a distinct genetic etiology. Further investigation of how these SNPs might modify ovarian cancer associations with other inflammation-related risk factors is warranted. Cancer Res; 74(3); 852-61. ©2013 AACR.
EVALuna2:9204

Risk, Prediction and Prevention of Hereditary Breast Cancer - Large-Scale Genomic Studies in Times of Big and Smart Data - Wunderle, Marius; Olmes, Gregor; Nabieva, Naiba; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Hack, Carolin; Erber, Ramona; Ekici, Arif Bülent; Hoyer, Juliane; Vasileiou, Georgia; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Over the last two decades genetic testing for mutations in BRCA1 and BRCA2 has become standard of care for women and men who are at familial risk for breast or ovarian cancer. Currently, genetic testing more often also includes so-called panel genes, which are assumed to be moderate-risk genes for breast cancer. Recently, new large-scale studies provided more information about the risk estimation of those genes. The utilization of information on panel genes with regard to their association with the individual breast cancer risk might become part of future clinical practice. Furthermore, large efforts have been made to understand the influence of common genetic variants with a low impact on breast cancer risk. For this purpose, almost 450 000 individuals have been genotyped for almost 500 000 genetic variants in the OncoArray project. Based on first results it can be assumed that - together with previously identified common variants - more than 170 breast cancer risk single nucleotide polymorphisms can explain up to 18% of familial breast cancer risk. The knowledge about genetic and non-genetic risk factors and its implementation in clinical practice could especially be of use for individualized prevention. This includes an individualized risk prediction as well as the individualized selection of screening methods regarding imaging and possible lifestyle interventions. The aim of this review is to summarize the most recent developments in this area and to provide an overview on breast cancer risk genes, risk prediction models and their utilization for the individual patient.
EVALuna2:34612

RNA-seq and pathway analysis of ocular tissues in PEX patients and healthy subjects - Pasutto, Francesca; Zenkel, Matthias; Berner, Daniel; Uebe, Steffen; Ekici, Arif Bülent; Kruse, Friedrich; Reis, André; Schlötzer-Schrehardt, Ursula (2018)
EVALuna2:34745

RNA sequencing reveals induction of specific renal inflammatory pathways in a rat model of malignant hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Fahlbusch, Fabian; Ekici, Arif Bülent; Kirchner, Philipp; Daniel, Christoph; Amann, Kerstin Ute; Velkeen, Roland; Wölfle, Joachim; Schiffer, Mario; Hartner, Andrea; Hilgers, Karl Friedrich (Journal of Molecular Medicine, 2021)
Abstract: In malignant hypertension, far more severe kidney injury occurs than in the “benign” form of the disease. The role of high blood pressure and the renin–angiotensin–aldosterone system is well recognized, but the pathogenesis of the renal injury of malignant hypertension (MH) remains incompletely understood. Using the rat model of two-kidney, one-clip renovascular hypertension in which some but not all animals develop MH, we performed a transcriptomic analysis of gene expression by RNA sequencing to identify transcriptional changes in the kidney cortex specific for MH. Differential gene expression was assessed in three groups: MH, non-malignant hypertension (NMH), and normotensive, sham-operated controls. To distinguish MH from NMH, we considered two factors: weight loss and typical renovascular lesions. Mean blood pressure measured intraarterially was elevated in MH (220 ± 6.5 mmHg) as well as in NMH (192 ± 6.4 mmHg), compared to controls (119 ± 1.7 mmHg, p < 0.05). Eight hundred eighty-six genes were exclusively regulated in MH only. Principal component analysis revealed a separated clustering of the three groups. The data pointed to an upregulation of many inflammatory mechanisms in MH including pathways which previously attracted relatively little attention in the setting of hypertensive kidney injury: Transcripts from all three complement activation pathways were upregulated in MH compared to NMH but not in NMH compared with controls; immunohistochemistry confirmed complement deposition in MH exclusively. The expression of chemokines attracting neutrophil granulocytes (CXCL6) and infiltration of myeloperoxidase-positive cells were increased only in MH rats. The data suggest that these pathways, especially complement deposition, may contribute to kidney injury under MH. Key messages: The most severe hypertension-induced kidney injury occurs in malignant hypertension.In a rat model of malignant hypertension, we assessed transcriptional responses in the kidney exposed to high blood pressure. A broad stimulation of inflammatory mechanisms was observed, but a few specific pathways were activated only in the malignant form of the disease, notably activation of the complement cascades.Complement inhibitors may alleviate the thrombotic microangiopathy of malignant hypertension even in the absence of primary complement abnormalities.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Complement activation; Inflammation; Kidney injury; Malignant hypertension; RNA-Seq; Two-kidney one-clip renovascular hypertension (2K1C)

RNA splicing modulator for Huntington's disease treatment induces peripheral neuropathy - Krach, Florian; Börstler, Tom; Neubert, Sebastian; Krumm, Laura; Regensburger, Martin; Winkler, Jürgen; Winner, Beate (iScience, 2025)
RNA splicing modulators, a new class of small molecules with the potential to modify the protein expression levels, have quickly been translated into clinical trials. These compounds hold promise for treating neurodegenerative disorders, including branaplam for lowering huntingtin levels in Huntington's disease. However, the VIBRANT-HD trial was terminated due to the emergence of peripheral neuropathy. Here, we describe the complex mechanism whereby branaplam activates p53, induces nucleolar stress in human induced pluripotent stem cell (iPSC)-derived motor neurons (iPSC-MN), and thereby enhanced expression of the neurotoxic p53-target gene BBC3. On the cellular level, branaplam disrupts neurite integrity, reflected by elevated neurofilament light chain levels. These findings illustrate the complex pharmacology of RNA splicing modulators with a small therapeutic window between lowering huntingtin levels and the clinically relevant off-target effect of neuropathy. Comprehensive toxicological screening in human stem cell models can complement pre-clinical testing before advancing RNA-targeting drugs to clinical trials.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Biological sciences; Cell biology; Cellular neuroscience; Natural sciences; Neuroscience; Pharmacology

Roflumilast inhibits tumor growth and migration in STK11/LKB1 deficient pancreatic cancer - Zhang, Shuman; Yun, Duo; Yang, Hao; Eckstein, Markus; Elbait, Gihan Daw; Zhou, Yaxing; Lu, Yanxi; Yang, Hai; Zhang, Jinping; Dörflein, Isabella; Britzen-Laurent, Nathalie; Pfeffer, Susanne; et al. (Cell Death Discovery, 2024)
Pancreatic cancer is a malignant tumor of the digestive system. It is highly aggressive, easily metastasizes, and extremely difficult to treat. This study aimed to analyze the genes that might regulate pancreatic cancer migration to provide an essential basis for the prognostic assessment of pancreatic cancer and individualized treatment. A CRISPR knockout library directed against 915 murine genes was transfected into TB 32047 cell line to screen which gene loss promoted cell migration. Next-generation sequencing and PinAPL.py- analysis was performed to identify candidate genes. We then assessed the effect of serine/threonine kinase 11 (STK11) knockout on pancreatic cancer by wound-healing assay, chick agnosia (CAM) assay, and orthotopic mouse pancreatic cancer model. We performed RNA sequence and Western blotting for mechanistic studies to identify and verify the pathways. After accelerated Transwell migration screening, STK11 was identified as one of the top candidate genes. Further experiments showed that targeted knockout of STK11 promoted the cell migration and increased liver metastasis in mice. Mechanistic analyses revealed that STK11 knockout influences blood vessel morphogenesis and is closely associated with the enhanced expression of phosphodiesterases (PDEs), especially PDE4D, PDE4B, and PDE10A. PDE4 inhibitor Roflumilast inhibited STK11-KO cell migration and tumor size, further demonstrating that PDEs are essential for STK11-deficient cell migration. Our findings support the adoption of therapeutic strategies, including Roflumilast, for patients with STK11-mutated pancreatic cancer in order to improve treatment efficacy and ultimately prolong survival.
CRIS-Team Scopus Importer:2024-04-12

Role of Endogenous Regulators of Hem- And Lymphangiogenesis in Corneal Transplantation - Clahsen, Thomas; Büttner, Christian; Hatami, Niloofar; Reis, André; Cursiefen, Claus (Journal of Clinical Medicine, 2020)
Under normal conditions, the cornea, being the transparent "windscreen" of the eye, is free of both blood and lymphatic vessels. However, various diseases of the eye, like infections, can interfere with the balance between promoting and inhibiting factors, which leads to ingrowth of blood and lymphatic vessels. The newly formed lymphatic vessels increase the risk of graft rejection after subsequent corneal transplantation. Corneal transplantation is one of the most commonly performed transplantations worldwide, with more than 40,000 surgeries per year in Europe. To date, various anti-hem- and anti-lymphangiogenic treatment strategies have been developed specifically for the corneal vascular endothelial growth factor (VEGF) pathway. Currently, however, no treatment strategies are clinically available to specifically modulate lymphangiogenesis. In this review, we will give an overview about endogenous regulators of hem- and lymphangiogenesis and discuss potential new strategies for targeting pathological lymphangiogenesis. Furthermore, we will review recently identified modulators and demonstrate that the cornea is a suitable model for the identification of novel endogenous modulators of lymphangiogenesis. The identification of novel modulators of lymphangiogenesis and a better understanding of the signaling pathways involved will contribute to the development of new therapeutic targets for the treatment of pathological lymphangiogenesis. This, in turn, will improve graft rejection, not only for the cornea.
CRIS-Team WoS Importer:2020-03-24

Role of α-synuclein in adult neurogenesis and neuronal maturation in the dentate gyrus. - Winner, Beate; Regensburger, Martin; Prots, Iryna; Winkler, Jürgen; et al. (Journal of Neuroscience, 2012)
α-Synuclein has been reported to be important in modulating brain plasticity and to be a key protein in neurodegenerative diseases, including Lewy body dementia (LBD). We investigated how α-synuclein levels modulate adult neurogenesis and the development of dendritic arborization and spines in the dentate gyrus, in which new neurons are constantly added. In the human hippocampus, levels of endogenous α-synuclein were increased in LBD, and the numbers of SOX2-positive cells were decreased. We investigated whether newly generated neurons were modulated by endogenous α-synuclein, and we found increased adult neurogenesis in α/β-synuclein knock-out mice. In contrast, overexpression of human wild-type α-synuclein (WTS) decreased the survival and dendritic development of newborn neurons. Endogenous α-synuclein expression levels increased the negative impact of WTS on dendrite development, suggesting a toxic effect of increasing amounts of α-synuclein. To attempt a rescue of the dendritic phenotype, we administered rolipram to activate the cAMP response element-binding protein pathway, which led to a partial rescue of neurite development. The current work provides novel insights into the role of α-synuclein in adult hippocampal neurogenesis.

rs495139 in the TYMS-ENOSF1 Region and Risk of Ovarian Carcinoma of Mucinous Histology - Kelemen, Linda E.; Earp, Madalene; Fridley, Brooke L.; Chenevix-Trench, Georgia; Fasching, Peter; Beckmann, Matthias; Ekici, Arif Bülent; Hein, Alexander; Lambrechts, Diether; Lambrechts, Sandrina; Van Nieuwenhuysen, Els; Vergote, Ignace; et al. (International Journal of Molecular Sciences, 2018)
Thymidylate synthase (TYMS) is a crucial enzyme for DNA synthesis. TYMS expression is regulated by its antisense mRNA, ENOSF1. Disrupted regulation may promote uncontrolled DNA synthesis and tumor growth. We sought to replicate our previously reported association between rs495139 in the TYMS-ENOSF1 3' gene region and increased risk of mucinous ovarian carcinoma (MOC) in an independent sample. Genotypes from 24,351 controls to 15,000 women with invasive OC, including 665 MOC, were available. We estimated per-allele odds ratios (OR) and 95% confidence intervals (CI) using unconditional logistic regression, and meta-analysis when combining these data with our previous report. The association between rs495139 and MOC was not significant in the independent sample (OR = 1.09; 95% CI = 0.97⁻1.22; p = 0.15; N = 665 cases). Meta-analysis suggested a weak association (OR = 1.13; 95% CI = 1.03⁻1.24; p = 0.01; N = 1019 cases). No significant association with risk of other OC histologic types was observed (p = 0.05 for tumor heterogeneity). In expression quantitative trait locus (eQTL) analysis, the rs495139 allele was positively associated with ENOSF1 mRNA expression in normal tissues of the gastrointestinal system, particularly esophageal mucosa (r = 0.51, p = 1.7 × 10-28), and nonsignificantly in five MOC tumors. The association results, along with inconclusive tumor eQTL findings, suggest that a true effect of rs495139 might be small.
EVALuna2:35118

Saliva samples as a source of DNA for high throughput genotyping: an acceptable and sufficient means in improvement of risk estimation throughout mammographic diagnostics - Poehls, U. G.; Hack, Caroline; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Hübner, Hanna (European Journal of Medical Research, 2018)
BACKGROUND: Breast cancer screening programs seem to be an insufficient tool for women at high genetic risk for breast cancer. These women are not adequately monitored yet. Genetic testing may improve clearly the quality of breast cancer prevention programs. At present, blood samples are favored for obtaining high-quality DNA; however, DNA can also be obtained by collecting saliva. The aim of this study was, on the one hand, to determine whether saliva sampling is a practicable means to obtain sufficient quantity and quality of DNA and, on the other hand, whether it is accepted by patients throughout mammographic diagnostics. METHODS: 67 consecutive women with diagnostic need for mammography with or without a family history for breast cancer were asked for their basic willingness to undergo a genetic testing by saliva sample in addition to standard diagnostics. Saliva samples were analyzed in terms of DNA quantity and quality. RESULTS: 64 (95.6%) women agreed to provide a saliva sample; 3 of them denied participation. And even 63 out of 64 (98.4%) were interested in their specific results. 45 out of 64 samples contained a DNA concentration above 50 ng/µl, 12 samples were between 25 and 50 ng/µl and only 7 of them were under 25 ng/µl with the standard extraction procedure. CONCLUSION: A high number of patients seem to accept salvia samples as a risk assessment tool in breast diagnostics and are interested in their specific risk situation. At the same time, it could be demonstrated that it is an effective way to provide high-quality DNA for breast cancer gene analysis. However, it remains to be shown whether it would be possible to integrate it with the same acceptance in a nationwide breast cancer screening program.
EVALuna2:34632

SARS-CoV-2 Spike Protein Induces Time-Dependent CTSL Upregulation in HeLa Cells and Alveolarspheres - Bolsinger, Magdalena; Drobny, Alice; Wilfling, Sibylle; Reischl, Stephanie; Krach, Florian; Moritz, Raul; Balta, Denise; Hehr, Ute; Sock, Elisabeth; Bleibaum, Florian; Hanses, Frank; Winner, Beate; et al. (Journal of Cellular Biochemistry, 2024)
Autophagy and lysosomal pathways are involved in the cell entry of SARS-CoV-2 virus. To infect the host cell, the spike protein of SARS-CoV-2 binds to the cell surface receptor angiotensin-converting enzyme 2 (ACE2). To allow the fusion of the viral envelope with the host cell membrane, the spike protein has to be cleaved. One possible mechanism is the endocytosis of the SARS-CoV-2–ACE2 complex and subsequent cleavage of the spike protein, mainly by the lysosomal protease cathepsin L. However, detailed molecular and dynamic insights into the role of cathepsin L in viral cell entry remain elusive. To address this, HeLa cells and iPSC-derived alveolarspheres were treated with recombinant SARS-CoV-2 spike protein, and the changes in mRNA and protein levels of cathepsins L, B, and D were monitored. Additionally, we studied the effect of cathepsin L deficiency on spike protein internalization and investigated the influence of the spike protein on cathepsin L promoters in vitro. Furthermore, we analyzed variants in the genes coding for cathepsin L, B, D, and ACE2 possibly associated with disease progression using data from Regeneron's COVID Results Browser and our own cohort of 173 patients with COVID-19, exhibiting a variant of ACE2 showing significant association with COVID-19 disease progression. Our in vitro studies revealed a significant increase in cathepsin L mRNA and protein levels following exposure to the SARS-CoV-2 spike protein in HeLa cells, accompanied by elevated mRNA levels of cathepsin B and D in alveolarspheres. Moreover, an increase in cathepsin L promoter activity was detected in vitro upon spike protein treatment. Notably, the knockout of cathepsin L resulted in reduced internalization of the spike protein. The study highlights the importance of cathepsin L and lysosomal proteases in the SARS-CoV-2 spike protein internalization and suggests the potential of lysosomal proteases as possible therapeutic targets against COVID-19 and other viral infections.
CRIS-Team Scopus Importer:2024-07-19
Keywords: cathepsin L; cathepsins; lysosomes; SARS-CoV-2; spike protein

SCAF4 loss of function in humans and Drosophila implicates mRNA transcriptional termination in neuro-developmental disorders - Fliedner, Anna; Kirchner, P.; Agre, K. E.; De Graaf-Van De Laar, I.; Clarke, M. Dutra; Davis-Keppen, L.; Ekici, Arif Bülent; Gregor, Anne; Lippa, N.; Mcwalter, K.; Mirzaa, G.; Noh, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Scaffold-Based (Matrigel™) 3D Culture Technique of Glioblastoma Recovers a Patient-like Immunosuppressive Phenotype - Braun, Frank K.; Rothhammer-Hampl, Tanja; Lorenz, Julia; Pohl, Sandra; Menevse, Ayse Nur; Vollmann-Zwerenz, Arabel; Bumes, Elisabeth; Büttner, Maren; Zoubaa, Saida; Proescholdt, Martin; Schmidt, Nils O.; Hau, Peter; et al. (Cells, 2023)
Conventional 2D cultures are commonly used in cancer research though they come with limitations such as the lack of microenvironment or reduced cell heterogeneity. In this study, we investigated in what respect a scaffold-based (Matrigel™) 3D culture technique can ameliorate the limitations of 2D cultures. NGS-based bulk and single-cell sequencing of matched pairs of 2D and 3D models showed an altered transcription of key immune regulatory genes in around 36% of 3D models, indicating the reoccurrence of an immune suppressive phenotype. Changes included the presentation of different HLA surface molecules as well as cellular stressors. We also investigated the 3D tumor organoids in a co-culture setting with tumor-infiltrating lymphocytes (TILs). Of note, lymphocyte-mediated cell killing appeared less effective in clearing 3D models than their 2D counterparts. IFN-γ release, as well as live cell staining and proliferation analysis, pointed toward an elevated resistance of 3D models. In conclusion, we found that the scaffold-based (Matrigel™) 3D culture technique affects the transcriptional profile in a subset of GBM models. Thus, these models allow for depicting clinically relevant aspects of tumor-immune interaction, with the potential to explore immunotherapeutic approaches in an easily accessible in vitro system.
CRIS-Team Scopus Importer:2023-08-11
Keywords: brain cancer; GBM; next-generation sequencing; single-cell RNA sequencing; tumor organoids

scRNA sequencing uncovers a TCF4-dependent transcription factor network regulating commissure development in mouse - Wittmann, Marie-Theres; Katada, Sayako; Sock, Elisabeth; Kirchner, Philipp; Ekici, Arif Bülent; Wegner, Michael; Nakashima, Kinichi; Lie, Dieter Chichung; Reis, André (Development, 2021)
Transcription factor 4 (TCF4) is a crucial regulator of neurodevelopment and has been linked to the pathogenesis of autism, intellectual disability and schizophrenia. As a class I bHLH transcription factor (TF), it is assumed that TCF4 exerts its neurodevelopmental functions through dimerization with proneural class II bHLH TFs. Here, we aim to identify TF partners of TCF4 in the control of interhemispheric connectivity formation. Using a new bioinformatic strategy integrating TF expression levels and regulon activities from single cell RNA-sequencing data, we find evidence that TCF4 interacts with non-bHLH TFs and modulates their transcriptional activity in Satb2+ intercortical projection neurons. Notably, this network comprises regulators linked to the pathogenesis of neurodevelopmental disorders, e.g. FOXG1, SOX11 and BRG1. In support of the functional interaction of TCF4 with non-bHLH TFs, we find that TCF4 and SOX11 biochemically interact and cooperatively control commissure formation in vivo, and regulate the transcription of genes implicated in this process. In addition to identifying new candidate interactors of TCF4 in neurodevelopment, this study illustrates how scRNA-Seq data can be leveraged to predict TF networks in neurodevelopmental processes.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Commissure development; Gene regulatory networks; Mouse; Protein-protein interaction; Single-cell RNA sequencing; SOX11; TCF4

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Serum levels of miR-320 family members are associated with clinical parameters and diagnosis in prostate cancer patients - Lieb, Verena; Weigelt, Katrin; Scheinost, Lena; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Klocker, Helmut; Holzhausen, Hans Juergen; Lai, Xin; Vera, Julio; Ekici, Arif Bülent; et al. (Oncotarget, 2018)
We studied the association of the serum levels of the microRNA family members miR-320a/-b/-c with clinico-pathological data to assess their applicability as diagnostic biomarker in prostate cancer (PCa) patients. The levels of miR-320a/-b/-c in 3 groups were evaluated by qRT-PCR (145 patients with PCa, 31 patients with benign prostatic hyperplasia (BPH) and 19 healthy controls). The levels of the three family members of miR-320 were directly correlated within each group (P < 0.001), but they differed significantly among the three groups (P < 0.001). The serum levels of the miR-320 family members were significantly increased in older patients compared to younger patients (≤ 66 years vs. > 66 years, P ≤ 0.001). In addition, the levels of all three miR-320 family members were significantly different in patients with low tumor stage compared with those with high tumor stage (miR-320a: P = 0.034; miR-320b: P = 0.006; miR-320c: P = 0.007) and in patients with low serum PSA compared with those with high serum PSA (≤ 4 ng vs. > 4 ng; miR-320a: P = 0.003; miR-320b: P = 0.003; miR-320c: P = 0.006). The levels of these miRNAs were inversely correlated with serum PSA levels. Detection in the serum samples of PCa patients with or without PSA relapse revealed higher levels of miR-320a/-b/-c in the group without PSA relapse before/after radical prostatectomy than in that with PCa relapse. In summary, the differences among the PCa/BPH/healthy control groups with respect to miR-320a/-b/-c levels in conjunction with higher levels in patients without a PSA relapse than in those with a relapse suggest the diagnostic potential of these miRNA-320 family members in PCa patients.
EVALuna2:35121

Severe manifestation of Rauch-Azzarello syndrome associated with biallelic deletion of CTNND2 - Pauly, Melissa; Krumbiegel, Mandy; Trumpp, Sandra; Braig, Sonja; Rupprecht, Thomas; Kraus, Cornelia; Uebe, Steffen; Reis, André; Vasileiou, Georgia (Clinical Genetics, 2024)
CTNND2 encodes δ-catenin, a component of an adherens junction complex, and plays an important role in neuronal structure and function. To date, only heterozygous loss-of-function CTNND2 variants have been associated with mild neurodevelopmental delay and behavioral anomalies, a condition, which we named Rauch-Azzarello syndrome. Here, we report three siblings of a consanguineous family of Syrian descent with a homozygous deletion encompassing the last 19 exons of CTNND2 predicted to disrupt the transcript. All presented with severe neurodevelopmental delay with absent speech, profound motor delay, stereotypic behavior, microcephaly, short stature, muscular hypotonia with lower limb hypertonia, and variable eye anomalies. The parents and the fourth sibling were heterozygous carriers of the deletion and exhibited mild neurodevelopmental impairment resembling that of the previously described heterozygous individuals. The present study unveils a severe manifestation of CTNND2-associated Rauch-Azzarello syndrome attributed to biallelic loss-of-function aberrations, clinically distinct from the already described mild presentation of heterozygous individuals. Furthermore, we demonstrate novel clinical features in homozygous individuals that have not been reported in heterozygous cases to date.
CRIS-Team Scopus Importer:2024-04-19
Keywords: biallelic; CTNND2; LoF; NDD; neurodevelopmental delay; δ-catenin

Single-cell RNA sequencing of adult mouse testes - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Data, 2018)
Spermatogenesis is an efficient and complex system of continuous cell differentiation. Previous studies investigating the transcriptomes of different cell populations in the testis relied either on sorting cells, cell depletion, or juvenile animals where not all stages of spermatogenesis have been completed. We present single-cell RNA sequencing (scRNA-Seq) data of 2,500 cells from the testes of two 8-week-old C57Bl/6J mice. Our dataset includes all spermatogenic stages from preleptotene to condensing spermatids as well as individual spermatogonia, Sertoli and Leydig cells. The data capture the full continuity of the meiotic and postmeiotic stages of spermatogenesis, and is thus ideally suited for marker discovery, network inference and similar analyses for which temporal ordering of differentiation processes can be exploited. Furthermore, it can serve as a reference for future studies involving single-cell RNA-Seq in mice where spermatogenesis is perturbed.
EVALuna2:34826

Single molecule real time sequencing in ADTKD-MUC1 allows complete assembly of the VNTR and exact positioning of causative mutations - Wenzel, Andrea; Altmueller, Janine; Ekici, Arif Bülent; Popp, Bernt; Stueber, Kurt; Thiele, Holger; Pannes, Alois; Staubach, Simon; Salido, Eduardo; Nuernberg, Peter; Reinhardt, Richard; Reis, André; et al. (Scientific Reports, 2018)
Recently, the Mucin-1 (MUC1) gene has been identified as a causal gene of autosomal dominant tubulointerstitial kidney disease (ADTKD). Most causative mutations are buried within a GC-rich 60 basepair variable number of tandem repeat (VNTR), which escapes identification by massive parallel sequencing methods due to the complexity of the VNTR. We established long read single molecule real time sequencing (SMRT) targeted to the MUC1-VNTR as an alternative strategy to the snapshot assay. Our approach allows complete VNTR assembly, thereby enabling the detection of all variants residing within the VNTR and simultaneous determination of VNTR length. We present high resolution data on the VNTR architecture for a cohort of snapshot positive (n = 9) and negative (n = 7) ADTKD families. By SMRT sequencing we could confirm the diagnosis in all previously tested cases, reconstruct both VNTR alleles and determine the exact position of the causative variant in eight of nine families. This study demonstrates that precise positioning of the causative mutation(s) and identification of other coding and noncoding sequence variants in ADTKD-MUC1 is feasible. SMRT sequencing could provide a powerful tool to uncover potential factors encoded within the VNTR that associate with intra- and interfamilial phenotype variability of MUC1 related kidney disease.
EVALuna2:34138

Skeletal abnormalities are common features in Ayme-Gripp syndrome - Niceta, Marcello; Barbuti, Domenico; Gupta, Neerja; Ruggiero, Carlos; Tizzano, Eduardo F.; Graul-Neumann, Luitgard; Barresi, Sabina; Nishimura, Gen; Valenzuela, Irene; Lopez-Grondona, Fermina; Fernandez-Alvarez, Paula; Leoni, Chiara; et al. (Clinical Genetics, 2019)
Ayme-Gripp syndrome (AYGRPS) is a recognizable condition caused by a restricted spectrum of dominantly acting missense mutations affecting the transcription factor MAF. Major clinical features of AYGRPS include congenital cataracts, sensorineural hearing loss, intellectual disability, and a distinctive flat facial appearance. Skeletal abnormalities have also been observed in affected individuals, even though these features have not been assessed systematically. Expanding the series with four additional patients, here we provide a more accurate delineation of the molecular aspects and clinical phenotype, particularly focusing on the skeletal features characterizing this disorder. Apart from previously reported malar flattening and joint limitations, we document that carpal/tarsal and long bone defects, and hip dysplasia occur in affected subjects more frequently than formerly appreciated.
CRIS-Team WoS Importer:2019-11-15

Skeletal defects and defective osteoclast and osteoblast function in Ayme-Gripp syndrome - Niceta, M.; Del Fattore, A.; Barbuti, D.; Rossi, M.; Stellacci, E.; Gupta, N.; Ruggiero, C.; Tizzano, E.; Graul-Neumann, L.; Leoni, C.; Zweier, Christiane; Fernandez Alvarez, P.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Skeletal muscle vulnerability in a child with Pitt-Hopkins syndrome - Chiu, Celine; Küchler, Alma; Depienne, Christel; Preuße, Corinna; Marina, Adela Della; Reis, André; Kaiser, Frank J.; Nolte, Kay; Hentschel, Andreas; Schara-Schmidt, Ulrike; Kölbel, Heike; Roos, Andreas (Skeletal Muscle, 2024)
Background: TCF4 acts as a transcription factor that binds to the immunoglobulin enhancer Mu-E5/KE5 motif. Dominant variants in TCF4 are associated with the manifestation of Pitt-Hopkins syndrome, a rare disease characterized by severe mental retardation, certain features of facial dysmorphism and, in many cases, with abnormalities in respiratory rhythm (episodes of paroxysmal tachypnea and hyperventilation, followed by apnea and cyanosis). Frequently, patients also develop epilepsy, microcephaly, and postnatal short stature. Although TCF4 is expressed in skeletal muscle and TCF4 seems to play a role in myogenesis as demonstrated in mice, potential myopathological findings taking place upon the presence of dominant TCF4 variants are thus far not described in human skeletal muscle. Method: To address the pathological effect of a novel deletion affecting exons 15 and 16 of TCF4 on skeletal muscle, histological and immunofluorescence studies were carried out on a quadriceps biopsy in addition to targeted transcript studies and global proteomic profiling. Results: We report on muscle biopsy findings from a Pitt-Hopkins patient with a novel heterozygous deletion spanning exon 15 and 16 presenting with neuromuscular symptoms. Microscopic characterization of the muscle biopsy revealed moderate fiber type I predominance, imbalance in the proportion of fibroblasts co-expressing Vimentin and CD90, and indicate activation of the complement cascade in TCF4-mutant muscle. Protein dysregulations were unraveled by proteomic profiling. Transcript studies confirmed a mitochondrial vulnerability in muscle and confirmed reduced TCF4 expression. Conclusion: Our combined findings, for the first time, unveil myopathological changes as phenotypical association of Pitt-Hopkins syndrome and thus expand the current clinical knowledge of the disease as well as support data obtained on skeletal muscle of a mouse model.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Muscle; Muscle proteomics; Myogenesis; Pitt Hopkins syndrome; TCF4

Sox11 is an Activity-Regulated Gene with Dentate-Gyrus-Specific Expression Upon General Neural Activation - von Wittgenstein, Julia; Zheng, Fang; Wittmann, Marie-Theres; Balta, Elli-Anna; Ferrazzi, Fulvia; Schäffner, Iris; Häberle, Benjamin; Valero Aracama, Maria Jesus; Koehl, Muriel; Miranda, Carlos J.; Kaspar, Brian K.; Ekici, Arif Bülent; et al. (Cerebral Cortex, 2020)
Neuronal activity initiates transcriptional programs that shape long-term changes in plasticity. Although neuron subtypes differ in their plasticity response, most activity-dependent transcription factors (TFs) are broadly expressed across neuron subtypes and brain regions. Thus, how region- and neuronal subtype-specific plasticity are established on the transcriptional level remains poorly understood. We report that in young adult (i.e., 6-8 weeks old) mice, the developmental TF SOX11 is induced in neurons within 6 h either by electroconvulsive stimulation or by exploration of a novel environment. Strikingly, SOX11 induction was restricted to the dentate gyrus (DG) of the hippocampus. In the novel environment paradigm, SOX11 was observed in a subset of c-FOS expressing neurons (ca. 15%); whereas around 75% of SOX11+ DG granule neurons were c-FOS+, indicating that SOX11 was induced in an activity-dependent fashion in a subset of neurons. Environmental enrichment or virus-mediated overexpression of SOX11 enhanced the excitability of DG granule cells and downregulated the expression of different potassium channel subunits, whereas conditional Sox11/4 knock-out mice presented the opposite phenotype. We propose that Sox11 is regulated in an activity-dependent fashion, which is specific to the DG, and speculate that activity-dependent Sox11 expression may participate in the modulation of DG neuron plasticity.
CRIS-Team Scopus Importer:2020-05-29
Keywords: dentate gyrus; hippocampus; immediate early gene; plasticity; Sox11

SOX11 variants cause a neurodevelopmental disorder with infrequent ocular malformations and hypogonadotropic hypogonadism and with distinct DNA methylation profile - Al-Jawahiri, Reem; Foroutan, Aidin; Kerkhof, Jennifer; McConkey, Haley; Levy, Michael; Haghshenas, Sadegheh; Rooney, Kathleen; Turner, Jasmin; Shears, Debbie; Holder, Muriel; Lefroy, Henrietta; Castle, Bruce; et al. (Genetics in Medicine, 2022)
Purpose: This study aimed to undertake a multidisciplinary characterization of the phenotype associated with SOX11 variants. Methods: Individuals with protein altering variants in SOX11 were identified through exome and genome sequencing and international data sharing. Deep clinical phenotyping was undertaken by referring clinicians. Blood DNA methylation was assessed using Infinium MethylationEPIC array. The expression pattern of SOX11 in developing human brain was defined using RNAscope. Results: We reported 38 new patients with SOX11 variants. Idiopathic hypogonadotropic hypogonadism was confirmed as a feature of SOX11 syndrome. A distinctive pattern of blood DNA methylation was identified in SOX11 syndrome, separating SOX11 syndrome from other BAFopathies. Conclusion: SOX11 syndrome is a distinct clinical entity with characteristic clinical features and episignature differentiating it from BAFopathies.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Exome; Genome sequencing; Hypogonadism; Methylation; Neurodevelopmental disorder; SOX11

SPATA5 mutations cause a distinct autosomal recessive phenotype of intellectual disability, hypotonia and hearing loss - Buchert, Rebecca; Nesbitt, Addie I.; Tawamie, Hasan; Krantz, Ian D.; Medne, Livija; Helbig, Ingo; Matalon, Dena R.; Reis, André; Santani, Avni; Sticht, Heinrich; Abou Jamra, Rami (Orphanet Journal of Rare Diseases, 2016)
We examined an extended, consanguineous family with seven individuals with severe intellectual disability and microcephaly. Further symptoms were hearing loss, vision impairment, gastrointestinal disturbances, and slow and asymmetric waves in the EEG. Linkage analysis followed by exome sequencing revealed a homozygous variant in SPATA5 (c.1822_1824del; p.Asp608del), which segregates with the phenotype in the family. Molecular modelling suggested a deleterious effect of the identified alterations on the protein function. In an unrelated family, we identified compound heterozygous variants in SPATA5 (c.[2081G > A];[989_991delCAA]; p.[Gly694Glu];[.Thr330del]) in a further individual with global developmental delay, infantile spasms, profound dystonia, and sensorineural hearing loss. Molecular modelling suggested an impairment of protein function in the presence of both variants.SPATA5 is a member of the ATPase associated with diverse activities (AAA) protein family and was very recently reported in one publication to be mutated in individuals with intellectual disability, epilepsy and hearing loss. Our results describe new, probably pathogenic variants in SPATA5 that were identified in individuals with a comparable phenotype. We thus independently confirm that bi-allelic pathogenic variants in SPATA5 cause a syndromic form of intellectual disability, and we delineate its clinical presentation.
EVALuna2:9313

Spatially clustering de novo variants in CYFIP2, encoding the cytoplasmic FMRP interacting protein 2, cause intellectual disability and seizures - Zweier, M.; Begemann, A.; Mcwalter, K.; Cho, M. T.; Abela, L.; Banka, S.; Behring, B.; Berger, A.; Brown, C. W.; Carneiro, M.; Chen, J.; Cooper, G. M.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Spatially clustering de novo variants in CYFIP2, encoding the cytoplasmic FMRP interacting protein 2, cause intellectual disability and seizures - Zweier, Markus; Begemann, Anais; Mcwalter, Kirsty; Cho, Megan T.; Abela, Lucia; Banka, Siddharth; Behring, Bettina; Berger, Andrea; Brown, Chester W.; Carneiro, Maryline; Chen, Jiani; Cooper, Gregory M.; et al. (European journal of human genetics, 2019)
CYFIP2, encoding the evolutionary highly conserved cytoplasmic FMRP interacting protein 2, has previously been proposed as a candidate gene for intellectual disability and autism because of its important role linking FMRP-dependent transcription regulation and actin polymerization via the WAVE regulatory complex (WRC). Recently, de novo variants affecting the amino acid p.Arg87 of CYFIP2 were reported in four individuals with epileptic encephalopathy. We here report 12 independent patients harboring a variety of de novo variants in CYFIP2 broadening the molecular and clinical spectrum of a novel CYFIP2-related neurodevelopmental disorder. Using trio whole-exome or -genome sequencing, we identified 12 independent patients carrying a total of eight distinct de novo variants in CYFIP2 with a shared phenotype of intellectual disability, seizures, and muscular hypotonia. We detected seven different missense variants, of which two occurred recurrently (p.(Arg87Cys) and p.(Ile664Met)), and a splice donor variant in the last intron for which we showed exon skipping in the transcript. The latter is expected to escape nonsense-mediated mRNA decay resulting in a truncated protein. Despite the large spacing in the primary structure, the variants spatially cluster in the tertiary structure and are all predicted to weaken the interaction with WAVE1 or NCKAP1 of the actin polymerization regulating WRC-complex. Preliminary genotype-phenotype correlation indicates a profound phenotype in p.Arg87 substitutions and a more variable phenotype in other alterations. This study evidenced a variety of de novo variants in CYFIP2 as a novel cause of mostly severe intellectual disability with seizures and muscular hypotonia.
CRIS-Team WoS Importer:2019-04-23

Specifications of the ACMG/AMP variant curation guidelines for myocilin: Recommendations from the clingen glaucoma expert panel - Burdon, Kathryn P.; Graham, Patricia; Hadler, Johanna; Hulleman, John D.; Pasutto, Francesca; Boese, Erin A.; Craig, Jamie E.; Fingert, John H.; Hewitt, Alex W.; Siggs, Owen M.; Whisenhunt, Kristina; Young, Terri L.; et al. (Human Mutation, 2022)
The standardization of variant curation criteria is essential for accurate interpretation of genetic results and clinical care of patients. The variant curation guidelines developed by the American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) in 2015 are widely used but are not gene specific. To address this issue, the Clinical Genome Resource (ClinGen) Variant Curation Expert Panels (VCEP) have been tasked with developing gene-specific variant curation guidelines. The Glaucoma VCEP was created to develop rule specifications for genes associated with primary glaucoma, including myocilin (MYOC), the most common cause of Mendelian glaucoma. Of the 28 ACMG/AMP criteria, the Glaucoma VCEP adapted 15 rules to MYOC and determined 13 rules not applicable. Key specifications included determining minor allele frequency thresholds, developing an approach to counting probands and segregations, and reviewing functional assays. The rules were piloted on 81 variants and led to a change in classification in 40% of those that were classified in ClinVar, with functional evidence influencing the classification of 18 variants. The standardized variant curation guidelines for MYOC provide a framework for the consistent application of the rules between laboratories, to improve MYOC genetic testing in the management of glaucoma.
CRIS-Team WoS Importer:2022-11-04

Specific phenotype and function of CD56-expressing innate immune cell subsets in human thymus - Gerstner, Stephanie; Köhler, Wolfgang; Heidkamp, Gordon Frederik; Purbojo, Ariawan; Uchida, Shizuka; Ekici, Arif Bülent; Heger, Lukas; Luetke-Eversloh, Merlin; Schubert, Ralf; Bader, Peter; Klingebiel, Thomas; Koehl, Ulrike; et al. (Journal of Leukocyte Biology, 2016)
Whereas innate immune cells, such as NK and innate lymphoid cells (ILCs), have been characterized in different human tissues, knowledge on the thymic CD56-expressing cell subsets is limited. In this study, the rare subpopulations of thymic CD56(+)CD3(-) cells from samples of >100 patients have been successfully analyzed. The results revealed fundamental differences between thymic and peripheral blood (PB) CD56(+)CD3(-) cells. Thymic tissues lacked immunoregulatory CD56(high)CD16(dim) NK cells but showed two Eomes(+)CD56(dim) subsets on which common NK cell markers were significantly altered. CD56(dim)CD16(high) cells expressed high amounts of NKG2A, NKG2D, and CD27 with low CD57. Conversely, CD56(dim)CD16(dim) cells displayed high CD127 but low expression of KIR, NKG2D, and natural cytotoxicity receptors (NCRs). Thymic CD56(+)CD3(-) cells were able to gain cytotoxicity but were especially immunoregulatory cells, producing a broad range of cytokines. Finally, one population of thymic CD56(+) cells resembled conventional NK cells, whereas the other represented a novel, noncanonical NK subset.
EVALuna2:9311

Spliceosome malfunction causes neurodevelopmental disorders with overlapping features - Li, Dong; Wang, Qin; Bayat, Allan; Battig, Mark R.; Zhou, Yijing; Bosch, Daniëlle G.M.; van Haaften, Gijs; Granger, Leslie; Petersen, Andrea K.; Pérez-Jurado, Luis A.; Aznar-Laín, Gemma; Aneja, Anushree; et al. (Journal of Clinical Investigation, 2024)
Pre-mRNA splicing is a highly coordinated process. While its dysregulation has been linked to neurological deficits, our understanding of the underlying molecular and cellular mechanisms remains limited. We implicated pathogenic variants in U2AF2 and PRPF19, encoding spliceosome subunits in neurodevelopmental disorders (NDDs), by identifying 46 unrelated individuals with 23 de novo U2AF2 missense variants (including 7 recurrent variants in 30 individuals) and 6 individuals with de novo PRPF19 variants. Eight U2AF2 variants dysregulated splicing of a model substrate. Neuritogenesis was reduced in human neurons differentiated from human pluripotent stem cells carrying two U2AF2 hyper-recurrent variants. Neural loss of function (LoF) of the Drosophila orthologs U2af50 and Prp19 led to lethality, abnormal mushroom body (MB) patterning, and social deficits, which were differentially rescued by wild-type and mutant U2AF2 or PRPF19. Transcriptome profiling revealed splicing substrates or effectors (including Rbfox1, a third splicing factor), which rescued MB defects in U2af50deficient flies. Upon reanalysis of negative clinical exomes followed by data sharing, we further identified 6 patients with NDD who carried RBFOX1 missense variants which, by in vitro testing, showed LoF. Our study implicates 3 splicing factors as NDD-causative genes and establishes a genetic network with hierarchy underlying human brain development and function.
CRIS-Team Scopus Importer:2024-01-19

Sporadic Parkinson's disease derived neuronal cells show disease-specific mRNA and small RNA signatures with abundant deregulation of piRNAs - Schulze, Markus; Sommer, Annika; Plotz, Sonja; Farrell, Michaela; Winner, Beate; Grosch, Janina; Winkler, Jürgen; Riemenschneider, Markus J. (Acta Neuropathologica Communications, 2018)
Differentiated neurons established via iPSCs from patients that suffer from familial Parkinson's disease (PD) have allowed insights into the mechanisms of neurodegeneration. In the larger cohort of patients with sporadic PD, iPSC based information on disease specific cellular phenotypes is rare. We asked whether differences may be present on genomic and epigenomic levels and performed a comprehensive transcriptomic and epigenomic analysis of fibroblasts, iPSCs and differentiated neuronal cells of sporadic PD-patients and controls. We found that on mRNA level, although fibroblasts and iPSCs are largely indistinguishable, differentiated neuronal cells of sporadic PD patients show significant alterations enriched in pathways known to be involved in disease aetiology, like the CREB-pathway and the pathway regulating PGC1a. Moreover, miRNAs and piRNAs/piRNA-like molecules are largely differentially regulated in cells and post-mortem tissue samples between control-and PD-patients. The most striking differences can be found in piRNAs/piRNA-like molecules, with SINE-and LINE-derived piRNAs highly downregulated in a disease specific manner. We conclude that neuronal cells derived from sporadic PD-patients help to elucidate novel disease mechanisms and provide relevant insight into the epigenetic landscape of sporadic Parkinson's disease as particularly regulated by small RNAs.
EVALuna2:35781

SRD5A3-CDG: Twins with an intragenic tandem duplication - Rieger, Melissa; Türk, Matthias; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Huchzermeyer, Cord; Wiesmann da Silva Reis, André; Thiel, Christian (European Journal of Medical Genetics, 2022)
Steroid 5α-reductase type 3 congenital disorder of glycosylation (SRD5A3-CDG) is a rare metabolic disease mainly characterized by psychomotor disability, visual impairment, and variable eye malformations caused by bi-allelic pathogenic variants in SRD5A3. So far, only 23 distinct mutations were described. Exome sequencing in 32-year old monozygotic male twins revealed only the heterozygous splice variant c.562+3delG in SRD5A3, but no second variant. The twins presented with psychomotor deficit and a complex eye disease including retinal dystrophy, pallor of the papilla, nystagmus, and strabismus suggestive of SRD5A3-CDG. Only when applying exome-based copy number analysis, we identified as a second compound heterozygous variant a previously not reported tandem duplication of exons 2–4 in SRD5A3. Next to the typical skeletal anomalies of SRD5A3-CDG such as kyphosis and scoliosis, extension deficits of the proximal interphalangeal (PIP) joints IV were observed. Since similar contractures were described once in a patient with SRD5A3-CDG, we suggest that this rare symptom is possibly associated with SRD5A3-CDG. Our findings further expand the mutational and clinical spectrum of SRD5A3-CDG and emphasize the importance of an intragenic copy number analysis in patients with strong clinical suspicion of SRD5A3-CDG and only one detectable sequence variant.
CRIS-Team Scopus Importer:2022-04-15
Keywords: CDG; Exon duplication; SRD5A3

Stable DNA methylation boundaries and expanded trinucleotide repeats: role of DNA insertions - Naumann, Anja; Kraus, Cornelia; Hoogeveen, Andre; Ramirez, Christina M.; Dörfler, Walter (Journal of Molecular Biology, 2014)
The human genome segment upstream of the FMR1 (fragile X mental retardation 1) gene (Xq27.3) contains several genetic signals, among them is a DNA methylation boundary that is located 65-70 CpGs upstream of the CGG repeat. In fragile X syndrome (FXS), the boundary is lost, and the promoter is inactivated by methylation spreading. Here we document boundary stability in spite of critical expansions of the CGG trinucleotide repeat in male or female premutation carriers and in high functioning males (HFMs). HFMs carry a full CGG repeat expansion but exhibit an unmethylated promoter and lack the FXS phenotype. The boundary is also stable in Turner (45, X) females. A CTCF-binding site is located slightly upstream of the methylation boundary and carries a unique G-to-A polymorphism (single nucleotide polymorphism), which occurs 3.6 times more frequently in genomes with CGG expansions. The increased frequency of this single nucleotide polymorphism might have functional significance. In CGG expansions, the CTCF region does not harbor additional mutations. In FXS individuals and often in cells transgenomic for EBV (Epstein Barr Virus) DNA or for the telomerase gene, the large number of normally methylated CpGs in the far-upstream region of the boundary is decreased about 4-fold. A methylation boundary is also present in the human genome segment upstream of the HTT (huntingtin) promoter (4p16.3) and is stable both in normal and Huntington disease chromosomes. Hence, the vicinity of an expanded repeat does not per se compromise methylation boundaries. Methylation boundaries exert an important function as promoter safeguards.
EVALuna2:8223

STAG1 mutations cause a novel cohesinopathy characterised by unspecific syndromic intellectual disability - Lehalle, Daphne; Mosca-Boidron, Anne-Laure; Begtrup, Amber; Boute-Benejean, Odile; Charles, Perrine; Cho, Megan T.; Clarkson, Amanda; Devinsky, Orrin; Duffourd, Yannis; Duplomb-Jego, Laurence; Gerard, Benedicte; Jacquette, Aurelia; et al. (Journal of Medical Genetics, 2017)
Cohesinopathies are rare neurodevelopmental disorders arising from a dysfunction in the cohesin pathway, which enables chromosome segregation and regulates gene transcription. So far, eight genes from this pathway have been reported in human disease. STAG1 belongs to the STAG subunit of the core cohesin complex, along with five other subunits. This work aimed to identify the phenotype ascribed to STAG1 mutations.Among patients referred for intellectual disability (ID) in genetics departments worldwide, array-comparative genomic hybridisation (CGH), gene panel, whole-exome sequencing or whole-genome sequencing were performed following the local diagnostic standards.A mutation in STAG1 was identified in 17 individuals from 16 families, 9 males and 8 females aged 2-33 years. Four individuals harboured a small microdeletion encompassing STAG1; three individuals from two families had an intragenic STAG1 deletion. Six deletions were identified by array-CGH, one by whole-exome sequencing. Whole-exome sequencing found de novo heterozygous missense or frameshift STAG1 variants in eight patients, a panel of genes involved in ID identified a missense and a frameshift variant in two individuals. The 17 patients shared common facial features, with wide mouth and deep-set eyes. Four individuals had mild microcephaly, seven had epilepsy.We report an international series of 17 individuals from 16 families presenting with syndromic unspecific ID that could be attributed to a STAG1 deletion or point mutation. This first series reporting the phenotype ascribed to mutation in STAG1 highlights the importance of data sharing in the field of rare disorders.
EVALuna2:9353

STAT1 coordinates intestinal epithelial cell death during gastrointestinal infection upstream of Caspase-8 - Stolzer, Iris; Schickedanz, Laura; Chiriac, Mircea T.; López-Posadas, Rocío; Grassl, Guntram A.; Mattner, Jochen; Wirtz, Stefan; Neurath, Markus; Günther, Claudia; Winner, Beate (Mucosal Immunology, 2021)
Intestinal homeostasis and the maintenance of the intestinal epithelial barrier are essential components of host defense during gastrointestinal Salmonella Typhimurium infection. Both require a strict regulation of cell death. However, the molecular pathways regulating epithelial cell death have not been completely understood. Here, we elucidated the contribution of central mechanisms of regulated cell death and upstream regulatory components during gastrointestinal infection. Mice lacking Caspase-8 in the intestinal epithelium are highly sensitive towards bacterial induced enteritis and intestinal inflammation, resulting in an enhanced lethality of these mice. This phenotype was associated with an increased STAT1 activation during Salmonella infection. Cell death, barrier breakdown and systemic infection were abrogated by an additional deletion of STAT1 in Casp8ΔIEC mice. In the absence of epithelial STAT1, loss of epithelial cells was abolished which was accompanied by a reduced Caspase-8 activation. Mechanistically, we demonstrate that epithelial STAT1 acts upstream of Caspase-8-dependent as well as -independent cell death and thus might play a major role at the crossroad of several central cell death pathways in the intestinal epithelium. In summary, we uncovered that transcriptional control of STAT1 is an essential host response mechanism that is required for the maintenance of intestinal barrier function and host survival.
CRIS-Team Scopus Importer:2021-09-17

STAT3 activation through IL-6/IL-11 in cancer-associated fibroblasts promotes colorectal tumour development and correlates with poor prognosis - Heichler, Christina; Scheibe, Kristina; Schmied, Anabel; Geppert, Carol-Immanuel; Schmid, Benjamin; Wirtz, Stefan; Thoma, Oana Maria; Kramer, Viktoria; Waldner, Maximilian; Büttner, Christian; Farin, Henner; Pešić, Marina; et al. (Gut, 2019)
Objective: Cancer-associated fibroblasts (CAFs) influence the tumour microenvironment and tumour growth. However, the role of CAFs in colorectal cancer (CRC) development is incompletely understood. Design: We quantified phosphorylation of STAT3 (pSTAT3) expression in CAFs of human colon cancer tissue using a tissue microarray (TMA) of 375 patients, immunofluorescence staining and digital pathology. To investigate the functional role of CAFs in CRC, we took advantage of two murine models of colorectal neoplasia and advanced imaging technologies. In loss-of-function and gain-of-function experiments, using genetically modified mice with collagen type VI (COLVI)-specific signal transducer and activator of transcription 3 (STAT3) targeting, we evaluated STAT3 signalling in fibroblasts during colorectal tumour development. We performed a comparative gene expression profiling by whole genome RNA-sequencing of fibroblast subpopulations (COLVI+ vs COLVI-) on STAT3 activation (IL-6 vs IL-11). Results: The analysis of pSTAT3 expression in CAFs of human TMAs revealed a negative correlation of increased stromal pSTAT3 expression with the survival of colon cancer patients. In the loss-of-function and gain-of-function approach, we found a critical role of STAT3 activation in fibroblasts in driving colorectal tumourigenesis in vivo. With different imaging technologies, we detected an expansion of activated fibroblasts in colorectal neoplasias. Comparative gene expression profiling of fibroblast subpopulations on STAT3 activation revealed the regulation of transcriptional patterns associated with angiogenesis. Finally, the blockade of proangiogenic signalling significantly reduced colorectal tumour growth in mice with constitutive STAT3 activation in COLVI+ fibroblasts. Conclusion: Altogether our work demonstrates a critical role of STAT3 activation in CAFs in CRC development.
CRIS-Team Scopus Importer:2019-11-19
Keywords: colorectal cancer

Store-operated calcium entry is reduced in spastin-linked hereditary spastic paraplegia - Winner, Beate; Rizo Garza, Tania; Gebhardt, Lisa; Riedlberger, Julia; Eberhardt, Esther; Fester, Lars; Alansary, Dalia; Winkler, Jürgen; Turan, Sören; Arnold, Philipp; Niemeyer, Barbara; Fischer, Michael (2022)
Pathogenic variants in SPAST, the gene coding for spastin, are the single most common cause of hereditary spastic paraplegia, a progressive motor neuron disease. Spastin regulates key cellular functions, including microtubule-severing and endoplasmic reticulum-morphogenesis. However, it remains unclear how alterations in these cellular functions due to SPAST pathogenic variants result in motor neuron dysfunction. Since spastin influences both microtubule network and endoplasmic reticulum structure, we hypothesized that spastin is necessary for the regulation of Ca2+ homeostasis via store-operated calcium entry. Here, we show that the lack of spastin enlarges the endoplasmic reticulum and reduces store-operated calcium entry. In addition, elevated levels of different spastin variants induced clustering of STIM1 within the endoplasmic reticulum, altered the transport of STIM1 to the plasma membrane and reduced store-operated calcium entry, which could be rescued by exogenous expression of STIM1. Importantly, store-operated calcium entry was strongly reduced in induced pluripotent stem cell-derived neurons from hereditary spastic paraplegia patients with pathogenic variants in SPAST resulting in spastin haploinsufficiency. These neurons developed axonal swellings in response to lack of spastin. We were able to rescue both store-operated calcium entry and axonal swellings in SPAST patient neurons by restoring spastin levels, using CRISPR/Cas9 to correct the pathogenic variants in SPAST. These findings demonstrate that proper amounts of spastin are a key regulatory component for store-operated calcium entry mediated Ca2+ homeostasis and suggest store-operated calcium entry as a disease relevant mechanism of spastin-linked motor neuron disease.Rizo et al. use iPSC-derived neurons from patients to investigate how pathogenic variants in SPAST give rise to hereditary spastic paraplegia. They show that dysregulation of spastin, a microtubule- and ER-remodelling protein encoded by SPAST, alters the dynamics of the ER, resulting in aberrant Ca2+ regulation.
Keywords: spastin; STIM1; microtubules; endoplasmic reticulum; store-operated calcium entry

Successful treatment with interleukin-17A antagonists of generalized pustular psoriasis in patients without IL36RN mutations - Wilsmann-Theis, Dagmar; Schnell, Lisa Marie; Ralser-Isselstein, Veronika; Bieber, Thomas; Schoen, Michael P.; Hüffmeier, Ulrike; Moessner, Rotraut (Journal of Dermatology, 2018)
Generalized pustular psoriasis (GPP) is a potentially life-threatening disease that can be attributed to mutations in IL36RN in a subgroup of patients. In small trials, interleukin (IL)-17A and IL-17RA antagonists have been shown to be effective in patients with generalized pustular psoriasis in Japan. We identified seven patients who received the IL-17A antagonists secukinumab (six cases) or ixekizumab (one case) in two dermatological centers. All patients showed a good or excellent clinical response. Anti-IL-17A therapy was well tolerated and ongoing in all patients after an average therapy duration of 12.9 months. Analysis of IL36RN mutation status was performed in six patients, one patient carried a heterozygous mutation, while the other five patients did not show a mutation in IL36RN. This is the first report of a successful treatment of GPP patients without IL36RN mutations responding to anti-IL-17A therapy.
EVALuna2:34625

Surveillance recommendations for DICER1 pathogenic variant carriers: a report from the SIOPE Host Genome Working Group and CanGene-CanVar Clinical Guideline Working Group - Bakhuizen, Jette J.; Hanson, Helen; Van De Tuin, Karin; Lalloo, Fiona; Tischkowitz, Marc; Wadt, Karin; Doergeloh, Beate B.; Farah, Roula A.; Glentis, Stavros; Golmard, Lisa; Hoyer, Juliane; Jahnukainen, Kirsi; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter; Hu, Chunling; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Hübner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast Cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17–0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of 5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.
CRIS-Team Scopus Importer:2024-07-19

Sweating ability of patients with p63-associated syndromes - Ferstl, Paul; Wohlfart, Sigrun; Schneider, Holm (European Journal of Pediatrics, 2018)
Sweating deficiency has been reported to represent a cardinal symptom of ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome and ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome, two rare p63-associated disorders. According to online resources, hypohidrosis may lead to most life-threatening complications in affected patients. Thus, counseling on the prevention of hyperthermia would be indispensable in case of such syndromes, although detailed information on this issue is missing in the literature. We investigated 14 individuals with ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome (age range 2-48 years) and 9 individuals with ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome (0.5-60 years of age) by confocal laser scanning microscopy to determine their palmar sweat duct density and by quantification of pilocarpine-induced sweating. Genotype-phenotype correlations were assessed. In 12 of 23 patients (52%), a normal amount of sweat ducts was detected. These individuals (9 with ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome, 3 with ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome) produced sufficient sweat volumes (≥ 20 μl) in response to pilocarpine. All other patients had clearly reduced sweating ability and fewer sweat glands, but no anhidrosis. Alteration of a specific proline residue (Pro590) of p63 was consistently linked to impaired perspiration.Conclusion: Hypohidrosis in p63-associated syndromes is less common and potentially less severe than previously thought and may be attributable to certain genotypes. What is Known: • Hypohidrosis which has been listed as a cardinal symptom of AEC and EEC syndromes may lead to life-threatening hyperthermia. What is New: • Patients with EEC and AEC syndromes often can sweat normally. • Hypohidrosis seems to be attributed to certain TP63 genotypes.
EVALuna2:35484

Swiprosin-1/EFhd2-another piece in the puzzle of tauopathy? - Regensburger, Martin; Mielenz, Dirk; Winner, Beate (Aging-Us, 2018)
EVALuna2:35785
Keywords: Neurodegeneration; Swiprosin-1; EFhd2; Adult neurogenesis

SWI/SNF protein expression status in fumarate hydratase-deficient renal cell carcinoma: immunohistochemical analysis of 32 tumors from 28 patients - Agaimy, Abbas; Amin, Mahul B.; Gill, Anthony; Popp, Bernt; Reis, André; Berney, Daniel M.; Magi-Galluzzi, Cristina; Sibony, Mathilde; Smith, Steven C.; Suster, Saul; Trpkov, Kiril; Hes, Ondrej; et al. (Human Pathology, 2018)
Fumarate hydratase-deficient renal cell carcinoma (FH-RCC) is a rare, aggressive RCC type, originally described in the setting of hereditary leiomyomatosis and RCC syndrome, which is defined by germline FH gene inactivation. Inactivation of components of the switch/sucrose nonfermentable (SWI/SNF) chromatin remodeling complex is involved in renal medullary carcinoma (SMARCB1/INI1 loss), clear cell RCC (PBRM1 loss), and subsets of dedifferentiated RCC of clear cell, chromophobe, and papillary types (loss of different SWI/SNF components). FH-RCC and SWI/SNF-deficient RCC share anaplastic nuclear features and highly aggressive course. We analyzed 32 FH-RCCs from 28 patients using 7 commercially available SWI/SNF antibodies (SMARCB1/INI1, SMARCA2, SMARCA4, SMARCC1, SMARCC2, PBRM1, and ARID1A). Variable loss of SMARCB1, ARID1A, and SMARCC1 was observed in 1 of 31, 2 of 31, and 1 of 29 evaluable cases, respectively; 3 of these 4 SWI/SNF-deficient tumors had confirmed FH mutations. No correlation of SWI/SNF loss with solid or sarcomatoid features was observed. Two tumors with SMARCB1 and ARID1A deficiency had available SWI/SNF molecular data; both lacked SMARCB1 and ARID1A mutations. The remaining 5 SWI/SNF components were intact in all cases. Especially PBRM1 seems not to be involved in the pathogenesis or progression of FH-RCC. Our data showed that a subset of FH-RCC (12%) have a variable loss of SWI/SNF complex subunits, likely as secondary genetic events. This should not be confused with SWI/SNF-deficient RCC of other types. Evaluation of FH and SWI/SNF together with comprehensive molecular genetic profiling is needed to explore possible prognostic implications of FH/SWI-SNF double deficiency and to better understand the somatic mutation landscape in high-grade RCC.
EVALuna2:34610

?-Synuclein impairs oligodendrocyte progenitor maturation in multiple system atrophy - May, Verena Elisabeth Luise; Ettle, Benjamin; Pöhler, Anne-Maria; Nuber, Silke; Ubhi, Kiren; Rockenstein, Edward; Winner, Beate; Wegner, Michael; Masliah, Eliezer; Winkler, Jürgen (Neurobiology of Aging, 2014)
Multiple system atrophy (MSA), an atypical parkinsonian disorder, is characterized by ?-synuclein (?-syn(+)) cytoplasmatic inclusions in mature oligodendrocytes. Oligodendrocyte progenitor cells (OPCs) represent a distinct cell population with the potential to replace dysfunctional oligodendrocytes. However, the role of OPCs in MSA and their potential to replace mature oligodendrocytes is still unclear. A postmortem analysis in MSA patients revealed ?-syn within OPCs and an increased number of striatal OPCs. In an MSA mouse model, an age-dependent increase of dividing OPCs within the striatum and the cortex was detected. Despite of myelin loss, there was no reduction of mature oligodendrocytes in the corpus callosum or the striatum. Dissecting the underlying molecular mechanisms an oligodendroglial cell line expressing human ?-syn revealed that ?-syn delays OPC maturation by severely downregulating myelin-gene regulatory factor and myelin basic protein. Brain-derived neurotrophic factor was reduced in MSA models and its in vitro supplementation partially restored the phenotype. Taken together, efficacious induction of OPC maturation may open the window to restore glial and neuronal function in MSA.
EVALuna2:4963

?-Synuclein-induced myelination deficit defines a novel interventional target for multiple system atrophy - Ettle, Benjamin; Kerman, Bilal E.; Valera, Elvira; Gillmann, Clarissa; Schlachetzki, Johannes; Reiprich, Simone; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Wegner, Michael; Bäuerle, Tobias; Riemenschneider, Markus J.; et al. (Acta Neuropathologica, 2016)
Multiple system atrophy (MSA) is a rare atypical parkinsonian disorder characterized by a rapidly progressing clinical course and at present without any efficient therapy. Neuropathologically, myelin loss and neurodegeneration are associated with ?-synuclein accumulation in oligodendrocytes, but underlying pathomechanisms are poorly understood. Here, we analyzed the impact of oligodendrocytic ?-synuclein on the formation of myelin sheaths to define a potential interventional target for MSA. Post-mortem analyses of MSA patients and controls were performed to quantify myelin and oligodendrocyte numbers. As pre-clinical models, we used transgenic MSA mice, a myelinating stem cell-derived oligodendrocyte-neuron co-culture, and primary oligodendrocytes to determine functional consequences of oligodendrocytic ?-synuclein overexpression on myelination. We detected myelin loss accompanied by preserved or even increased numbers of oligodendrocytes in post-mortem MSA brains or transgenic mouse forebrains, respectively, indicating an oligodendrocytic dysfunction in myelin formation. Corroborating this observation, overexpression of ?-synuclein in primary and stem cell-derived oligodendrocytes severely impaired myelin formation, defining a novel ?-synuclein-linked pathomechanism in MSA. We used the pro-myelinating activity of the muscarinic acetylcholine receptor antagonist benztropine to analyze the reversibility of the myelination deficit. Transcriptome profiling of primary pre-myelinating oligodendrocytes demonstrated that benztropine readjusts myelination-related processes such as cholesterol and membrane biogenesis, being compromised by oligodendrocytic ?-synuclein. Additionally, benztropine restored the ?-synuclein-induced myelination deficit of stem cell-derived oligodendrocytes. Strikingly, benztropine also ameliorated the myelin deficit in transgenic MSA mice, resulting in a prevention of neuronal cell loss. In conclusion, this study defines the ?-synuclein-induced myelination deficit as a novel and crucial pathomechanism in MSA. Importantly, the reversible nature of this oligodendrocytic dysfunction opens a novel avenue for an intervention in MSA.
EVALuna2:4991

Systematic approach demonstrates enrichment of multiple interactions between non-HLA risk variants and HLA-DRB1 risk alleles in rheumatoid arthritis - Diaz-Gallo, Lina-Marcela; Ramskold, Daniel; Shchetynsky, Klementy; Folkersen, Lasse; Chemin, Karine; Brynedal, Boel; Uebe, Steffen; Okada, Yukinori; Alfredsson, Lars; Klareskog, Lars; Padyukov, Leonid (Annals of the Rheumatic Diseases, 2018)
OBJECTIVE: In anti-citrullinated protein antibody positive rheumatoid arthritis (ACPA-positive RA), a particular subset of HLA-DRB1 alleles, called shared epitope (SE) alleles, is a highly influential genetic risk factor. Here, we investigated whether non-HLA single nucleotide polymorphisms (SNP), conferring low disease risk on their own, interact with SE alleles more frequently than expected by chance and if such genetic interactions influence the HLA-DRB1 SE effect concerning risk to ACPA-positive RA. METHODS: We computed the attributable proportion (AP) due to additive interaction at genome-wide level for two independent ACPA-positive RA cohorts: the Swedish epidemiological investigation of rheumatoid arthritis (EIRA) and the North American rheumatoid arthritis consortium (NARAC). Then, we tested for differences in the AP p value distributions observed for two groups of SNPs, non-associated and associated with disease. We also evaluated whether the SNPs in interaction with HLA-DRB1 were cis-eQTLs in the SE alleles context in peripheral blood mononuclear cells from patients with ACPA-positive RA (SE-eQTLs). RESULTS: We found a strong enrichment of significant interactions (AP p<0.05) between the HLA-DRB1 SE alleles and the group of SNPs associated with ACPA-positive RA in both cohorts (Kolmogorov-Smirnov test D=0.35 for EIRA and D=0.25 for NARAC, p<2.2e-16 for both). Interestingly, 564 out of 1492 SNPs in consistent interaction for both cohorts were significant SE-eQTLs. Finally, we observed that the effect size of HLA-DRB1 SE alleles for disease decreases from 5.2 to 2.5 after removal of the risk alleles of the two top interacting SNPs (rs2476601 and rs10739581). CONCLUSION: Our data demonstrate that there are massive genetic interactions between the HLA-DRB1 SE alleles and non-HLA genetic variants in ACPA-positive RA.
EVALuna2:215757

Systematic Phenomics Analysis Deconvolutes Genes Mutated in Intellectual Disability into Biologically Coherent Modules - Kochinke, Korinna; Zweier, Christiane; Nijhof, Bonnie; Fenckova, Michaela; Cizek, Pavel; Honti, Frank; Keerthikumar, Shivakumar; Oortveld, Merel A. W.; Kleefstra, Tjitske; Kramer, Jamie M.; Webber, Caleb; Huynen, Martijn A.; et al. (American Journal of Human Genetics, 2016)
Intellectual disability (ID) disorders are genetically and phenotypically extremely heterogeneous. Can this complexity be depicted in a comprehensive way as a means of facilitating the understanding of ID disorders and their underlying biology? We provide a curated database of 746 currently known genes, mutations in which cause ID (ID-associated genes [ID-AGs]), classified according to ID manifestation and associated clinical features. Using this integrated resource, we show that ID-AGs are substantially enriched with co-expression, protein-protein interactions, and specific biological functions. Systematic identification of highly enriched functional themes and phenotypes revealed typical phenotype combinations characterizing process-defined groups of ID disorders, such as chromatin-related disorders and deficiencies in DNA repair. Strikingly, phenotype classification efficiently breaks down ID-AGs into subsets with significantly elevated biological coherence and predictive power. Custom-made functional Drosophila datasets revealed further characteristic phenotypes among ID-AGs and specific clinical classes. Our study and resource provide systematic insights into the molecular and clinical landscape of ID disorders, represent a significant step toward overcoming current limitations in ID research, and prove the utility of systematic human and cross-species phenomics analyses in highly heterogeneous genetic disorders.
EVALuna2:9318

Targeted sequencing of FH-deficient uterine leiomyomas reveals biallelic inactivating somatic fumarase variants and allows characterization of missense variants - Popp, Bernt; Erber, Ramona; Kraus, Cornelia; Vasileiou, Georgia; Hoyer, Juliane; Burghaus, Stefanie; Hartmann, Arndt; Beckmann, Matthias; Reis, André; Agaimy, Abbas (Modern Pathology, 2020)
Uterine leiomyomas (ULs) constitute a considerable health burden in the general female population. The fumarate hydratase (FH) deficient subtype is found in up to 1.6% and can occur in hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome. We sequenced 13 FH deficient ULs from a previous immunohistochemical screen using a targeted panel and identified biallelic FH variants in all. In eight, we found an FH point mutation (two truncating, six missense) with evidence for loss of the second allele. Variant allele-frequencies in all cases with a point mutation pointed to somatic variants. Spatial clustering of the identified missense variants in the lyase domain indicated altered fumarase oligomerization with subsequent degradation as explanation for the observed FH deficiency. Biallelic FH deletions in five tumors confirm the importance of copy number loss as mutational mechanism. By curating all pathogenic FH variants and calculating their population frequency, we estimate a carrier frequency of up to 1/2,563. Comparing with the prevalence of FH deficient ULs, we conclude that most are sporadic and estimate 2.7–13.9% of females with an FH deficient UL to carry a germline FH variant. Further prospective tumor/normal sequencing studies are needed to develop a reliable screening strategy for HLRCC in women with ULs.
CRIS-Team Scopus Importer:2020-07-10

Targeted transgene expression in neuronal precursors: watching young neurons in the old brain. - Winner, Beate; Bogdahn, Ulrich; Winkler, Jürgen; et al. (European Journal of Neuroscience, 2006)
Progress in the field of neurogenesis is limited by the lack of animal models allowing direct detection and analysis of living cells participating in neurogenesis. We engineered a transgenic mouse model that expresses the fluorescent reporter proteins enhanced green fluorescent protein or Discoma sp. reef coral red fluorescent protein under the control of the doublecortin (DCX) promoter, a gene specifically and transiently active in neuronal precursors and young neurons. The expression of the reporter proteins correlated with expression of the endogenous DCX protein, and with developmental and adult neurogenesis. Neurogenesis was unaffected by the presence of the fluorescent proteins. The transgenic mice allowed direct identification of the very few newly generated neurons present in the aged brain. We performed electrophysiological analysis and established that newly generated hippocampal granule cells in aged and young mice shared identical physiological properties. Hence, although the rate of neurogenesis tapers with ageing, a population of highly excitable young neurons indistinguishable to those found in younger animals is continuously generated. Therefore, maintenance of the fundamental properties of neuronal precursors even at advanced age suggests that stimulation of neurogenesis may constitute a valid strategy to counteract age-related neuronal loss and cognitive declines.

T cells are influenced by a long non-coding RNA in the autoimmune associated PTPN2 locus - Houtman, Miranda; Shchetynsky, Klementy; Chemin, Karine; Hensvold, Aase Haj; Ramskold, Daniel; Tandre, Karolina; Eloranta, Maija-Leena; Ronnblom, Lars; Uebe, Steffen; Catrina, Anca Irinel; Malmstrom, Vivianne; Padyukov, Leonid (Journal of Autoimmunity, 2018)
Non-coding SNPs in the protein tyrosine phosphatase non-receptor type 2 (PTPN2) locus have been linked with several autoimmune diseases, including rheumatoid arthritis, type I diabetes, and inflammatory bowel disease. However, the functional consequences of these SNPs are poorly characterized. Herein, we show in blood cells that SNPs in the PTPN2 locus are highly correlated with DNA methylation levels at four CpG sites downstream of PTPN2 and expression levels of the long non-coding RNA (lncRNA) LINC01882 downstream of these CpG sites. We observed that LINC01882 is mainly expressed in T cells and that anti-CD3/CD28 activated naïve CD4+ T cells downregulate the expression of LINC01882. RNA sequencing analysis of LINC01882 knockdown in Jurkat T cells, using a combination of antisense oligonucleotides and RNA interference, revealed the upregulation of the transcription factor ZEB1 and kinase MAP2K4, both involved in IL-2 regulation. Overall, our data suggests the involvement of LINC01882 in T cell activation and hints towards an auxiliary role of these non-coding SNPs in autoimmunity associated with the PTPN2 locus.
EVALuna2:34629

TCF4 (E2-2) harbors tumor suppressive functions in SHH medulloblastoma - Hellwig, Malte; Lauffer, Marlen C.; Bockmayr, Michael; Spohn, Michael; Merk, Daniel J.; Harrison, Luke; Ahlfeld, Julia; Kitowski, Annabel; Neumann, Julia E.; Ohli, Jasmin; Holdhof, Doerthe; Niesen, Judith; et al. (Acta Neuropathologica, 2019)
The TCF4 gene encodes for the basic helix-loop-helix transcription factor 4 (TCF4), which plays an important role in the development of the central nervous system (CNS). Haploinsufficiency of TCF4 was found to cause Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder. Recently, the screening of a large cohort of medulloblastoma (MB), a highly aggressive embryonal brain tumor, revealed almost 20% of adult patients with MB of the Sonic hedgehog (SHH) subtype carrying somatic TCF4 mutations. Interestingly, many of these mutations have previously been detected as germline mutations in patients with PTHS. We show here that overexpression of wild-type TCF4 in vitro significantly suppresses cell proliferation in MB cells, whereas mutant TCF4 proteins do not to the same extent. Furthermore, RNA sequencing revealed significant upregulation of multiple well-known tumor suppressors upon expression of wild-type TCF4. In vivo, a prenatal knockout of Tcf4 in mice caused a significant increase in apoptosis accompanied by a decreased proliferation and failed migration of cerebellar granule neuron precursor cells (CGNP), which are thought to be the cells of origin for SHH MB. In contrast, postnatal in vitro and in vivo knockouts of Tcf4 with and without an additional constitutive activation of the SHH pathway led to significantly increased proliferation of CGNP or MB cells. Finally, publicly available data from human MB show that relatively low expression levels of TCF4 significantly correlate with a worse clinical outcome. These results not only point to time-specific roles of Tcf4 during cerebellar development but also suggest a functional linkage between TCF4 mutations and the formation of SHH MB, proposing that TCF4 acts as a tumor suppressor during postnatal stages of cerebellar development.
CRIS-Team WoS Importer:2019-04-04

Tetrasomy of SCN2A associated with refractory neonatal epileptic encephalopathy - Krumbiegel, Mandy; Trollmann, Regina; Mammadova, Dilbar; Schnell, Alexander; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Th17 cells: a promising therapeutic target for Parkinson's disease? - Prots, Iryna; Winner, Beate (Expert Opinion on Therapeutic Targets, 2019)
Introduction: Parkinson's disease (PD) is the most common neurodegenerative movement disorder caused by the progressive loss of neurons in the midbrain and other brain regions. Only symptomatic treatment is currently available. Mounting evidence suggests that T cells are a key contributor to PD pathogenesis and neurodegeneration by a mechanism that requires further elucidation. Areas covered: We discuss the evidence of imbalanced activation of effector T cell populations in PD and summarize the data of Th17 involvement and Th17-regulated mechanisms in PD pathology. Moreover, possible Th17-related molecular targets as possible neuroprotective immunomodulatory therapeutic targets for PD are examined. Expert Opinion: Existing data show that Th17 cells, their effector molecules, and signaling pathways are potentially effective therapeutic targets for neuroprotective immunomodulation in PD treatment. However, specificity of action within Th17-mediated signaling pathways for PD requires careful consideration.
CRIS-Team WoS Importer:2019-04-09
Keywords: T cells; Th17 cells; neurodegeneration; Parkinson’s disease; IL-6; IL-1β

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

Th2 single-cell heterogeneity and clonal distribution at distant sites in helminth-infected mice - Radtke, Daniel; Thuma, Natalie; Schülein, Christine; Kirchner, Philipp; Ekici, Arif Bülent; Schober, Kilian; Vöhringer, David (eLife, 2022)
Th2 cells provide effector functions in type 2 immune responses to helminths and allergens. Despite knowledge about molecular mechanisms of Th2 cell differentiation, there is little information on Th2 cell heterogeneity and clonal distribution between organs. To address this, we performed combined single-cell transcriptome and T-cell receptor (TCR) clonotype analysis on murine Th2 cells in mesenteric lymph nodes (MLNs) and lung after infection with Nippostrongylus brasiliensis (Nb) as a human hookworm infection model. We find organ-specific expression profiles, but also populations with conserved migration or effector/resident memory signatures that unexpectedly cluster with potentially regulatory Il10(pos)Foxp3(neg) cells. A substantial MLN subpopulation with an interferon response signature suggests a role for interferon signaling in Th2 differentiation or diversification. Further RNA-inferred developmental directions indicate proliferation as a hub for differentiation decisions. Although the TCR repertoire is highly heterogeneous, we identified expanded clones and CDR3 motifs. Clonal relatedness between distant organs confirmed effective exchange of Th2 effector cells, although locally expanded clones dominated the response. We further cloned an Nb-specific TCR from an expanded clone in the lung effector cluster and describe surface markers that distinguish transcriptionally defined clusters. These results provide insights in Th2 cell subset diversity and clonal relatedness in distant organs.
CRIS-Team WoS Importer:2022-09-02

The anti-viral properties of IL-17A in allergic asthma - Graser, Anna; Ekici, Arif Bülent; Melichar, Volker O.; Zimmermann, Theodor; Papadopoulos, Nikolaos G.; Taka, Stella; Ferrazzi, Fulvia; Vuorinen, Tytti; Finotto, Susetta (2015)
EVALuna2:25975

The Bavarian Ethics Committee for Pre-Implantation Diagnosis-811 Decisions Over 5 Years - Genzel-Boroviczeny, Orsolya; Bannasch, Thomas; Baeuml, Josef; Friedrich, Orsolya; Hellemann, Joachim; Kress, Wolfram; Magdefrau, Carola; Manzeschke, Arne; Pettinger, Joseph; Pogarell, Oliver; Rieger-Fackeldey, Esther; Robin, Dunja; et al. (Deutsches Ärzteblatt international, 2021)
CRIS-Team WoS Importer:2021-04-23

The Brief Case: Cutaneous Sporotrichosis in an Immunocompetent Patient after Travel to Peru - Wolff, Dorit; Feldt, Torsten; Reifenberger, Julia; Sebald, Heidi; Bogdan, Christian (Journal of Clinical Microbiology, 2018)
EVALuna2:36422

The Ca2+ sensor protein swiprosin-1/EFhd2 is present in neurites and involved in kinesin-mediated transport in neurons - Purohit, Pavitra; Perez-Branguli, Francesc; Prots, Iryna; Borger, Eva; Gunn-Moore, Frank; Welzel, Oliver; Loy, Kristina; Wenzel, Eva Maria; Groemer, Teja W.; Brachs, Sebastian; Holzer, Max; Buslei, Rolf; et al. (PLoS ONE, 2014)
Swiprosin-1/EFhd2 (EFhd2) is a cytoskeletal Ca2+ sensor protein strongly expressed in the brain. It has been shown to interact with mutant tau, which can promote neurodegeneration, but nothing is known about the physiological function of EFhd2 in the nervous system. To elucidate this question, we analyzed EFhd2-/-/lacZ reporter mice and showed that lacZ was strongly expressed in the cortex, the dentate gyrus, the CA1 and CA2 regions of the hippocampus, the thalamus, and the olfactory bulb. Immunohistochemistry and western blotting confirmed this pattern and revealed expression of EFhd2 during neuronal maturation. In cortical neurons, EFhd2 was detected in neurites marked by MAP2 and co-localized with pre- and post-synaptic markers. Approximately one third of EFhd2 associated with a biochemically isolated synaptosome preparation. There, EFhd2 was mostly confined to the cytosolic and plasma membrane fractions. Both synaptic endocytosis and exocytosis in primary hippocampal EFhd2-/- neurons were unaltered but transport of synaptophysin-GFP containing vesicles was enhanced in EFhd2-/- primary hippocampal neurons, and notably, EFhd2 inhibited kinesin mediated microtubule gliding. Therefore, we found that EFhd2 is a neuronal protein that interferes with kinesin-mediated transport.
EVALuna2:7246

The clinical data intelligence project - Sonntag, Daniel; Tresp, Volker; Zillner, Sonja; Hammon, Matthias; Reis, André; Fasching, Peter; Sedlmayr, Martin; Ganslandt, Thomas; Prokosch, Hans-Ulrich; Budde, Clemens; Schmidt, Danilo; Hinrichs, Carl; et al. (Informatik-Spektrum, 2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.IMMD.infome.thecli

The clinical significance of small copy number variants in neurodevelopmental disorders - Asadollahi, Reza; Oneda, Beatrice; Joset, Pascal; Azzarello-Burri, Silvia; Bartholdi, Deborah; Steindl, Katharina; Vincent, Marie; Cobilanschi, Joana; Sticht, Heinrich; Baldinger, Rosa; Reissmann, Regina; Sudholt, Irene; et al. (Journal of Medical Genetics, 2014)
Despite abundant evidence for pathogenicity of large copy number variants (CNVs) in neurodevelopmental disorders (NDDs), the individual significance of genome-wide rare CNVs <500 kb has not been well elucidated in a clinical context.By high-resolution chromosomal microarray analysis, we investigated the clinical significance of all rare non-polymorphic exonic CNVs sizing 1-500 kb in a cohort of 714 patients with undiagnosed NDDs.We detected 96 rare CNVs <500 kb affecting coding regions, of which 58 (60.4%) were confirmed. 6 of 14 confirmed de novo, one of two homozygous and four heterozygous inherited CNVs affected the known microdeletion regions 17q21.31, 16p11.2 and 2p21 or OMIM morbid genes (CASK, CREBBP, PAFAH1B1, SATB2; AUTS2, NRXN3, GRM8). Two further de novo CNVs affecting single genes (MED13L, CTNND2) were instrumental in delineating novel recurrent conditions. For the first time, we here report exonic deletions of CTNND2 causing low normal IQ with learning difficulties with or without autism spectrum disorder. Additionally, we discovered a homozygous out-of-frame deletion of ACOT7 associated with features comparable to the published mouse model. In total, 24.1% of the confirmed small CNVs were categorised as pathogenic or likely pathogenic (median size 130 kb), 17.2% as likely benign, 3.4% represented incidental findings and 55.2% remained unclear.These results verify the diagnostic relevance of genome-wide rare CNVs <500 kb, which were found pathogenic in 2% (14/714) of cases (1.1% de novo, 0.3% homozygous, 0.6% inherited) and highlight their inherent potential for discovery of new conditions.
EVALuna2:9237

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The FANCM:p.Arg658* truncating variant is associated with risk of triple-negative breast cancer - Figlioli, Gisella; Bogliolo, Massimo; Catucci, Irene; Caleca, Laura; Lasheras, Sandra Viz; Pujol, Roser; Kiiski, Johanna I.; Muranen, Taru A.; Barnes, Daniel R.; Dennis, Joe; Michailidou, Kyriaki; Bolla, Manjeet K.; et al. (npj Breast Cancer, 2019)
Breast cancer is a common disease partially caused by genetic risk factors. Germline pathogenic variants in DNA repair genes BRCA1, BRCA2, PALB2, ATM, and CHEK2 are associated with breast cancer risk. FANCM, which encodes for a DNA translocase, has been proposed as a breast cancer predisposition gene, with greater effects for the ER-negative and triple-negative breast cancer (TNBC) subtypes. We tested the three recurrent protein-truncating variants FANCM:p.Arg658*, p.Gln1701*, and p.Arg1931* for association with breast cancer risk in 67,112 cases, 53,766 controls, and 26,662 carriers of pathogenic variants of BRCA1 or BRCA2. These three variants were also studied functionally by measuring survival and chromosome fragility in FANCM−/− patient-derived immortalized fibroblasts treated with diepoxybutane or olaparib. We observed that FANCM:p.Arg658* was associated with increased risk of ER-negative disease and TNBC (OR = 2.44, P = 0.034 and OR = 3.79; P = 0.009, respectively). In a country-restricted analysis, we confirmed the associations detected for FANCM:p.Arg658* and found that also FANCM:p.Arg1931* was associated with ER-negative breast cancer risk (OR = 1.96; P = 0.006). The functional results indicated that all three variants were deleterious affecting cell survival and chromosome stability with FANCM:p.Arg658* causing more severe phenotypes. In conclusion, we confirmed that the two rare FANCM deleterious variants p.Arg658* and p.Arg1931* are risk factors for ER-negative and TNBC subtypes. Overall our data suggest that the effect of truncating variants on breast cancer risk may depend on their position in the gene. Cell sensitivity to olaparib exposure, identifies a possible therapeutic option to treat FANCM-associated tumors.
CRIS-Team Scopus Importer:2019-11-12

The genetic basis for most patients with pustular skin disease remains elusive - Mössner, R.; Wilsmann-Theis, D.; Oji, V.; Gkogkolou, P.; Löhr, S.; Schulz, P.; Körber, A.; Prinz, J. C.; Renner, R.; Schäkel, K.; Vogelsang, L.; Peters, K. P.; et al. (British Journal of Dermatology, 2017)
Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause/ contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP).To better understand the disease-relevance of these genes, we screened our cohorts of patients with pustular skin diseases (primarily GPP and palmoplantar pustular psoriasis [PPP]) for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36RN.Coding exons of IL36RN, CARD14 and AP1S3 were sequenced in 67 patients - 61 with GPP, 2 with acute generalized exanthematous pustulosis and 4 with acrodermatitis continua suppurativa Hallopeau. We screened IL36RN and AP1S3 for intragenic copy-number-variants, 258 PPP patients for coding changes in AP1S3. 11 heterozygous IL36RN mutations carriers were analyzed for a 2(nd) non-coding IL36RN mutation. Genotype-phenotype-correlations in carriers/ non-carriers of IL36RN mutations were assessed within the GPP cohort.The majority of patients (GPP:64%) did not carry rare variants in any of the three genes. Bi-allelic and mono-allelic IL36RN mutations were identified in 15 and 5 GPP patients, respectively. Non-coding rare IL36RN variants were not identified in heterozygous carriers. The only significant genotype-phenotype-correlation observed for IL36RN mutation carriers was early age of disease onset. Additional rare CARD14 or AP1S3 variants were identified in 15% of IL36RN mutations carriers.The identification of IL36RN mutation carriers harboring additional rare variants in CARD14 or AP1S3, indicates a more complex mode of inheritance of pustular psoriasis. Our results suggest additional disease-causing genetic factors in heterozygous IL36RN mutation carriers outside IL36RN. This article is protected by copyright. All rights reserved.
EVALuna2:9330

The Genetics of Intelligence - Reis, André; Spinath, Frank M. (Deutsches Ärzteblatt international, 2025)
Background: Intelligence is defined as general mental capacity, which includes the abilities to reason, solve new problems, think abstractly, and learn quickly. Genetic factors explain a considerable fraction of inter-individual differences in intelligence. For many years, research on intelligence was limited to estimating the relative importance of genetic and environmental factors, without identifying any individual causal factors. Methods: This review of the literature is based on pertinent original publications and reviews. Results: Genome-wide association studies (GWAS) have shown that certain gene loci are associated with intelligence, as well as with educational attainment, which is known to be correlated with intelligence. As each individual gene locus accounts for only a very small part of the variance in intelligence (< 0.02%), so-called “polygenic scores” (PGS) have been calculated in which thousands of genetic variants are summarized together. On the basis of the largest GWAS performed to date, it is estimated that 7–15% of inter-individual differences in educational attainment and 7–10% in intelligence among persons of European descent can be explained by genetic factors. These genetic effects are partly indirect. At the same time, the relative importance of genetic factors in determining complex features such as intelligence and educational attainment must always be seen against the background of individual environmental conditions. In the presence of difficult social conditions, for example, the influence of genetic factors is typically lower. Conclusion: At present, the polygenic scores generated from genome-wide association studies are primarily of scientific interest, yet they are becoming increasingly informative and valid for individual prediction. There is, therefore, a need for broad social discussion about their future use.
CRIS-Team Scopus Importer:2025-04-04

The gut-brain axis in inflammatory bowel disease—current and future perspectives - Günther, Claudia; Rothhammer, Veit; Karow, Marisa; Neurath, Markus; Winner, Beate (International Journal of Molecular Sciences, 2021)
The gut–brain axis is a bidirectional communication system driven by neural, hormonal, metabolic, immunological, and microbial signals. Signaling events from the gut can modulate brain function and recent evidence suggests that the gut–brain axis may play a pivotal role in linking gastrointestinal and neurological diseases. Accordingly, accumulating evidence has suggested a link between inflammatory bowel diseases (IBDs) and neurodegenerative, as well as neuroinflammatory diseases. In this context, clinical, epidemiological and experimental data have demonstrated that IBD predisposes a person to pathologies of the central nervous system (CNS). Likewise, a number of neurological disorders are associated with changes in the intestinal environment, which are indicative for disease-mediated gut–brain inter-organ communication. Although this axis was identified more than 20 years ago, the sequence of events and underlying molecular mechanisms are poorly defined. The emergence of precision medicine has uncovered the need to take into account non-intestinal symptoms in the context of IBD that could offer the opportunity to tailor therapies to individual patients. The aim of this review is to highlight recent findings supporting the clinical and biological link between the gut and brain, as well as its clinical significance for IBD as well as neurodegeneration and neuroinflammation. Finally, we focus on novel human-specific preclinical models that will help uncover disease mechanisms to better understand and modulate the function of this complex system.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Ex vivo organ models; Gut-brain axis; IBD; MS; PD

The Gut–Immune–Brain Axis: An Important Route for Neuropsychiatric Morbidity in Inflammatory Bowel Disease - Masanetz, Rebecca Katharina; Winkler, Jürgen; Winner, Beate; Günther, Claudia; Süß, Patrick (International Journal of Molecular Sciences, 2022)
Inflammatory bowel disease (IBD) comprises Crohn’s disease (CD) and ulcerative colitis (UC) and is associated with neuropsychiatric symptoms like anxiety and depression. Both conditions strongly worsen IBD disease burden. In the present review, we summarize the current understanding of the pathogenesis of depression and anxiety in IBD. We present a stepwise cascade along a gut–immune–brain axis initiated by evasion of chronic intestinal inflammation to pass the epithelial and vascular barrier in the gut and cause systemic inflammation. We then summarize different anatomical transmission routes of gut-derived peripheral inflammation into the central nervous system (CNS) and highlight the current knowledge on neuroinflammatory changes in the CNS of preclinical IBD mouse models with a focus on microglia, the brain-resident macrophages. Subsequently, we discuss how neuroinflammation in IBD can alter neuronal circuitry to trigger symptoms like depression and anxiety. Finally, the role of intestinal microbiota in the gut–immune–brain axis in IBD will be reviewed. A more comprehensive understanding of the interaction between the gastrointestinal tract, the immune system and the CNS accounting for the similarities and differences between UC and CD will pave the path for improved prediction and treatment of neuropsychiatric comorbidities in IBD and other inflammatory diseases.
Created from Fastlane, Scopus look-up
Keywords: Crohn’s disease; depression; gut microbiota; gut-brain axis; inflammatory bowel disease; neuroinflammation; systemic inflammation; ulcerative colitis

The interaction of ENL with PAF1 mitigates polycomb silencing and facilitates murine leukemogenesis - Hetzner, Katrin; Garcia-Cuellar, Maria-Paz; Büttner, Christian; Slany, Robert (Blood, 2018)
Eleven-nineteen leukemia (ENL) is a chromatin reader present in complexes stimulating transcriptional elongation. It is fused to mixed-lineage leukemia (MLL) in leukemia, and missense mutations have been identified in Wilms tumor and acute myeloid leukemia. Here we demonstrate that ENL overcomes polycomb silencing through recruitment of PAF1 via the conserved YEATS domain, which recognizes acetylated histone H3. PAF1 was responsible for antirepressive activities of ENL in vitro, and it determined the transforming potential of MLL-ENL. MLL-ENL target loci showed supraphysiological PAF1 binding, hyperubiquitination of histone H2B and hypomodification with H2AUb, resulting in accelerated transcription rates. YEATS mutations induced a gain of function, transforming primary hematopoietic cells in vitro and in transplantation assays through aberrant transcription and H2B ubiquitination of Hoxa9 and Meis1 Mechanistically, H3 and PAF1 competed for ENL interaction, with activating mutations favoring PAF1 binding, whereas the MLL moiety provided a constitutive PAF1 tether allowing MLL fusions to circumvent H3 competition.
EVALuna2:34633

The missing link: ARID1B non-truncating variants causing Coffin-Siris syndrome due to protein aggregation - Bosch, Elisabeth; Güse, Esther; Kirchner, Philipp; Winterpacht, Andreas; Walther, Mona; Alders, Marielle; Kerkhof, Jennifer; Ekici, Arif Bülent; Sticht, Heinrich; Sadikovic, Bekim; Reis, André; Vasileiou, Georgia (Human genetics, 2024)
ARID1B is the most frequently mutated gene in Coffin-Siris syndrome (CSS). To date, the vast majority of causative variants reported in ARID1B are truncating, leading to nonsense-mediated mRNA decay. In the absence of experimental data, only few ARID1B amino acid substitutions have been classified as pathogenic, mainly based on clinical data and their de novo occurrence, while most others are currently interpreted as variants of unknown significance. The present study substantiates the pathogenesis of ARID1B non-truncating/NMD-escaping variants located in the SMARCA4-interacting EHD2 and DNA-binding ARID domains. Overexpression assays in cell lines revealed that the majority of EHD2 variants lead to protein misfolding and formation of cytoplasmic aggresomes surrounded by vimentin cage-like structures and co-localizing with the microtubule organisation center. ARID domain variants exhibited not only aggresomes, but also nuclear aggregates, demonstrating robust pathological effects. Protein levels were not compromised, as shown by quantitative western blot analysis. In silico structural analysis predicted the exposure of amylogenic segments in both domains due to the nearby variants, likely causing this aggregation. Genome-wide transcriptome and methylation analysis in affected individuals revealed expression and methylome patterns consistent with those of the pathogenic haploinsufficiency ARID1B alterations in CSS cases. These results further support pathogenicity and indicate two approaches for disambiguation of such variants in everyday practice. The few affected individuals harbouring EHD2 non-truncating variants described to date exhibit mild CSS clinical traits. In summary, this study paves the way for the re-evaluation of previously unclear ARID1B non-truncating variants and opens a new era in CSS genetic diagnosis.
CRIS-Team Scopus Importer:2024-07-26

The mutational and phenotypic spectrum of TUBA1A-associated tubulinopathy - Hebebrand, Moritz; Hüffmeier, Ulrike; Trollmann, Regina; Hehr, Ute; Uebe, Steffen; Ekici, Arif Bülent; Kraus, Cornelia; Krumbiegel, Mandy; Reis, André; Thiel, Christian; Popp, Bernt (Orphanet Journal of Rare Diseases, 2019)
BackgroundThe TUBA1A-associated tubulinopathy is clinically heterogeneous with brain malformations, microcephaly, developmental delay and epilepsy being the main clinical features. It is an autosomal dominant disorder mostly caused by de novo variants in TUBA1A.ResultsIn three individuals with developmental delay we identified heterozygous de novo missense variants in TUBA1A using exome sequencing. While the c.1307G>A, p.(Gly436Asp) variant was novel, the two variants c.518C>T, p.(Pro173Leu) and c.641G>A, p.(Arg214His) were previously described. We compared the variable phenotype observed in these individuals with a carefully conducted review of the current literature and identified 166 individuals, 146 born and 20 fetuses with a TUBA1A variant. In 107 cases with available clinical information we standardized the reported phenotypes according to the Human Phenotype Ontology. The most commonly reported features were developmental delay (98%), anomalies of the corpus callosum (96%), microcephaly (76%) and lissencephaly (agyria-pachygyria) (70%), although reporting was incomplete in the different studies. We identified a total of 121 specific variants, including 15 recurrent ones. Missense variants cluster in the C-terminal region around the most commonly affected amino acid position Arg402 (13.3%). In a three-dimensional protein model, 38.6% of all disease-causing variants including those in the C-terminal region are predicted to affect the binding of microtubule-associated proteins or motor proteins. Genotype-phenotype analysis for recurrent variants showed an overrepresentation of certain clinical features. However, individuals with these variants are often reported in the same publication.ConclusionsWith 166 individuals, we present the most comprehensive phenotypic and genotypic standardized synopsis for clinical interpretation of TUBA1A variants. Despite this considerable number, a detailed genotype-phenotype characterization is limited by large inter-study variability in reporting.
CRIS-Team WoS Importer:2019-02-27

The Nuclear Receptor Nr4a1 Acts as a Microglia Rheostat and Serves as a Therapeutic Target in Autoimmune-Driven Central Nervous System Inflammation - Rothe, Tobias; Ipseiz, Natacha; Faas, Maria; Lang, Stefanie; Perez-Branguli, Francesc; Metzger, Daniel; Ichinose, Hiroshi; Winner, Beate; Schett, Georg; Krönke, Gerhard (Journal of Immunology, 2017)
Microglia cells fulfill key homeostatic functions and essentially contribute to host defense within the CNS. Altered activation of microglia, in turn, has been implicated in neuroinflammatory and neurodegenerative diseases. In this study, we identify the nuclear receptor (NR) Nr4a1 as key rheostat controlling the activation threshold and polarization of microglia. In steady-state microglia, ubiquitous neuronal-derived stress signals such as ATP induced expression of this NR, which contributed to the maintenance of a resting and noninflammatory microglia phenotype. Global and microglia-specific deletion of Nr4a1 triggered the spontaneous and overwhelming activation of microglia and resulted in increased cytokine and NO production as well as in an accelerated and exacerbated form of experimental autoimmune encephalomyelitis. Ligand-induced activation of Nr4a1 accordingly ameliorated the course of this disease. Our current data thus identify Nr4a1 as regulator of microglia activation and potentially new target for the treatment of inflammatory CNS diseases such as multiple sclerosis.
EVALuna2:13374

The phenotypic and genotypic spectrum of individuals with mono- or biallelic ANK3 variants - Furia, Francesca; Levy, Amanda M.; Theunis, Miel; Bamshad, Michael J.; Bartos, Meghan N.; Bijlsma, Emilia K.; Brancati, Francesco; Cejudo, Lucile; Chong, Jessica X.; De Luca, Chiara; Dean, Sarah Joy; Egense, Alena; et al. (Clinical Genetics, 2024)
ANK3 encodes ankyrin-G, a protein involved in neuronal development and signaling. Alternative splicing gives rise to three ankyrin-G isoforms comprising different domains with distinct expression patterns. Mono- or biallelic ANK3 variants are associated with non-specific syndromic intellectual disability in 14 individuals (seven with monoallelic and seven with biallelic variants). In this study, we describe the clinical features of 13 additional individuals and review the data on a total of 27 individuals (16 individuals with monoallelic and 11 with biallelic ANK3 variants) and demonstrate that the phenotype for biallelic variants is more severe. The phenotypic features include language delay (92%), autism spectrum disorder (76%), intellectual disability (78%), hypotonia (65%), motor delay (68%), attention deficit disorder (ADD) or attention deficit hyperactivity disorder (ADHD) (57%), sleep disturbances (50%), aggressivity/self-injury (37.5%), and epilepsy (35%). A notable phenotypic difference was presence of ataxia in three individuals with biallelic variants, but in none of the individuals with monoallelic variants. While the majority of the monoallelic variants are predicted to result in a truncated protein, biallelic variants are almost exclusively missense. Moreover, mono- and biallelic variants appear to be localized differently across the three different ankyrin-G isoforms, suggesting isoform-specific pathological mechanisms.
CRIS-Team Scopus Importer:2024-07-19
Keywords: aggressivity; ankyrin-G; autism spectrum disorder; epilepsy; hypotonia; intellectual disability; language delay; neurodevelopmental disorder; sleep disturbances

The polynucleotide kinase 3'-phosphatase gene (PNKP) is involved in Charcot-Marie-Tooth disease (CMT2B2) previously related to MED25 - Leal, Alejandro; Bogantes-Ledezma, Sixto; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; Sticht, Heinrich; Berghoff, Martin; Berghoff, Corinna; Morera, Bernal; Meisterernst, Michael; Reis, André (Neurogenetics, 2018)
Charcot-Marie-Tooth disease (CMT) represents a heterogeneous group of hereditary peripheral neuropathies. We previously reported a CMT locus on chromosome 19q13.3 segregating with the disease in a large Costa Rican family with axonal neuropathy and autosomal recessive pattern of inheritance (CMT2B2). We proposed a homozygous missense variant in the Mediator complex 25 (MED25) gene as causative of the disease. Nevertheless, the fact that no other CMT individuals with MED25 variants were reported to date led us to reevaluate the original family. Using exome sequencing, we now identified a homozygous nonsense variant (p.Gln517ter) in the last exon of an adjacent gene, the polynucleotide kinase 3'-phosphatase (PNKP) gene. It encodes a DNA repair protein recently associated with recessive ataxia with oculomotor apraxia type 4 (AOA4) and microcephaly, seizures, and developmental delay (MCSZ). Subsequently, five unrelated Costa Rican CMT2 subjects initially identified as being heterozygous for the same MED25 variant were found to be also compound heterozygote for PNKP. All were heterozygous for the same variant found homozygous in the large family and a second one previously associated with ataxia (p.Thr408del). Detailed clinical reassessment of the initial family and the new individuals revealed in all an adult-onset slowly progressive CMT2 associated with signs of cerebellar dysfunction such as slurred speech and oculomotor involvement, but neither microcephaly, seizures, nor developmental delay. We propose that PKNP variants are the major causative variant for the CMT2 phenotype in these individuals and that the milder clinical manifestation is due to an allelic effect.
EVALuna2:35117

The proinflammatory effect of C-reactive protein on human endothelial cells depends on the Fc?RIIa genotype - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Klinghammer, Lutz; Stumpf, Christian; Achenbach, Stephan; Herrmann, Martin; Reis, André; Garlichs, Christoph (Thrombosis Research, 2014)
The stimulatory effects of CRP (C-reactive protein) on endothelial cells are mainly mediated via Fc?RIIa. This receptor exists in two different allotypes bearing either arginine (R131) or histidine (H131) at the extracellular amino acid position 131 of the mature protein, but only Fc?RIIa-R131 displays high avidity for CRP. This study investigated the role of the Fc?RIIa genotype in CRP-stimulated endothelial cells.We tested the effects of CRP on expression of the adhesion molecules ICAM-1, VCAM-1, and E-selectin, as well as the endothelial release of pro-inflammatory molecules as a function of the Fc?RIIa-genotype (Fc?RIIa-H/H131, Fc?RIIa-H/R131, Fc?RIIa-R/R131) in HUVEC (Human Umbilical Vein Endothelial Cells). HUVEC were grouped according to their Fc?RIIa status by genotyping with an allele specific nested-PCR. The expression of ICAM-1, VCAM-1, and E-selectin on HUVEC was detected by flow cytometry. The release of soluble markers (sCD40L, IL-6, IL-8, MCP-1, tPA, sP-selectin, and sVCAM-1) was measured using a multiplex assay for flow cytometry.CRP-stimulated expression of ICAM-1 and E-selectin was dependent on the specific Fc?RIIa-genotype, with most pronounced induction in HUVEC with the Fc?RIIa-R/R genotype, followed by H/R and H/H. In accordance with this finding, the supernatants of stimulated HUVEC with the R/R genotype showed significantly higher levels of tPA, MCP-1, and IL-6. Our data show that CRP stimulates the expression of adhesion molecules and the release of soluble markers by HUVEC as a function of the Fc?RIIa-genotype. These findings could be relevant in the context of risk stratification in patients with cardiovascular disease.
EVALuna2:9209

The protective variant rs7173049 at LOXL1 locus impacts on retinoic acid signaling pathway in pseudoexfoliation syndrome - Berner, Daniel; Hoja, Ursula; Zenkel, Matthias; Ross, James Julian; Uebe, Steffen; Paoli, Daniela; Frezzotti, Paolo; Rautenbach, Robyn M.; Ziskind, Ari; Williams, Susan E.; Carmichael, Trevor R.; Ramsay, Michele; et al. (Human Molecular Genetics, 2019)
LOXL1 (lysyl oxidase-like 1) has been identified as the major effect locus in pseudoexfoliation (PEX) syndrome, a fibrotic disorder of the extracellular matrix and frequent cause of chronic open-angle glaucoma. However, all known PEX-associated common variants show allele effect reversal in populations of different ancestry, casting doubt on their biological significance. Based on extensive LOXL1 deep sequencing, we report here the identification of a common non-coding sequence variant, rs7173049A>G, located downstream of LOXL1, consistently associated with a decrease in PEX risk (odds ratio, OR=0.63; P=6.33x10(-31)) in nine different ethnic populations. We provide experimental evidence for a functional enhancer-like regulatory activity of the genomic region surrounding rs7173049 influencing expression levels of ISLR2 (immunoglobulin superfamily containing leucine-rich repeat protein 2) and STRA6 [stimulated by retinoic acid (RA) receptor 6], apparently mediated by allele-specific binding of the transcription factor thyroid hormone receptor beta. We further show that the protective rs7173049-G allele correlates with increased tissue expression levels of ISLR2 and STRA6 and that both genes are significantly downregulated in tissues of PEX patients together with other key components of the STRA6 receptor-driven RA signaling pathway. siRNA-mediated downregulation of RA signaling induces upregulation of LOXL1 and PEX-associated matrix genes in PEX-relevant cell types. These data indicate that dysregulation of STRA6 and impaired retinoid metabolism are involved in the pathophysiology of PEX syndrome and that the variant rs7173049-G, which represents the first common variant at the broad LOXL1 locus without allele effect reversal, mediates a protective effect through upregulation of STRA6 in ocular tissues.
CRIS-Team WoS Importer:2019-11-12

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The Quest for Anti-α-Synuclein Antibody Specificity—Lessons Learnt From Flow Cytometry Analysis - Leupold, Lukas; Sigutova, Veronika; Gerasimova, Elizaveta; Regensburger, Martin; Zundler, Sebastian; Zunke, Friederike; Xiang, Wei; Winner, Beate; Prots, Iryna (Frontiers in Neurology, 2022)
The accumulation of alpha-synuclein (aSyn) is the hallmark of a group of neurodegenerative conditions termed synucleopathies. Physiological functions of aSyn, including those outside of the CNS, remain elusive. However, a reliable and reproducible evaluation of aSyn protein expression in different cell types and especially in low-expressing cells is impeded by the existence of a huge variety of poorly characterized anti-aSyn antibodies and a lack of a routinely used sensitive detection methods. Here, we developed a robust flow cytometry-based workflow for aSyn detection and antibody validation. We test our workflow using three commercially available antibodies (MJFR1, LB509, and 2A7) in a variety of human cell types, including induced pluripotent stem cells, T lymphocytes, and fibroblasts, and provide a cell- and antibody-specific map for aSyn expression. Strikingly, we demonstrate a previously unobserved unspecificity of the LB509 antibody, while the MJFR1 clone revealed specific aSyn binding however with low sensitivity. On the other hand, we identified an aSyn-specific antibody clone 2A7 with an optimal sensitivity for detecting aSyn in a range of cell types, including those with low aSyn expression. We further utilize our workflow to demonstrate the ability of the 2A7 antibody to distinguish between physiological differences in aSyn expression in neuronal and non-neuronal cells from the cortical organoids, and in neural progenitors and midbrain dopaminergic neurons from healthy controls and in patients with Parkinson's disease who have aSyn gene locus duplication. Our results provide a proof of principle for the use of high-throughput flow cytometry-based analysis of aSyn and highlight the necessity of rigorous aSyn antibody validation to facilitate the research of aSyn physiology and patholog
Keywords: alpha-synuclein; antibodies; synuclein antibodies; T cell; antibody specificity; flow cytometry; α-synuclein expression

The recurrent missense mutation p.(Arg367Trp) in YARS1 causes a distinct neurodevelopmental phenotype - Averdunk, Luisa; Sticht, Heinrich; Surowy, Harald; Luedecke, Hermann-Josef; Koch-Hogrebe, Margarete; Alsaif, Hessa S.; Kahrizi, Kimia; Alzaidan, Hamad; Alawam, Bashayer S.; Tohary, Mohamed; Kraus, Cornelia; Endele, Sabine; et al. (Journal of Molecular Medicine, 2021)
Pathogenic variants in aminoacyl-tRNA synthetases (ARS1) cause a diverse spectrum of autosomal recessive disorders. Tyrosyl tRNA synthetase (TyrRS) is encoded by YARS1 (cytosolic, OMIM*603,623) and is responsible of coupling tyrosine to its specific tRNA. Next to the enzymatic domain, TyrRS has two additional functional domains (N-Terminal TyrRS(Mini) and C-terminal EMAP-II-like domain) which confer cytokine-like functions. Mutations in YARS1 have been associated with autosomal-dominant Charcot-Marie-Tooth (CMT) neuropathy type C and a heterogenous group of autosomal recessive, multisystem diseases. We identified 12 individuals from 6 families with the recurrent homozygous missense variant c.1099C > T;p.(Arg367Trp) (NM_003680.3) in YARS1. This variant causes a multisystem disorder with developmental delay, microcephaly, failure to thrive, short stature, muscular hypotonia, ataxia, brain anomalies, microcytic anemia, hepatomegaly, and hypothyroidism. In silico analyses show that the p.(Arg367Trp) does not affect the catalytic domain responsible of enzymatic coupling, but destabilizes the cytokine-like C-terminal domain. The phenotype associated with p.(Arg367Trp) is distinct from the other biallelic pathogenic variants that reside in different functional domains of TyrRS which all show some common, but also divergent clinical signs [(e.g., p.(Phe269Ser)-retinal anomalies, p.(Pro213Leu)/p.(Gly525Arg)-mild ID, p.(Pro167Thr)-high fatality)]. The diverse clinical spectrum of ARS1-associated disorders is related to mutations affecting the various non-canonical domains of ARS1, and impaired protein translation is likely not the exclusive disease-causing mechanism of YARS1- and ARS1-associated neurodevelopmental disorders. Key messages The missense variant p.(Arg367Trp) in YARS1 causes a distinct multisystem disorder. p.(Arg367Trp) affects a non-canonical domain with cytokine-like functions. Phenotypic heterogeneity associates with the different affected YARS1 domains. Impaired protein translation is likely not the exclusive mechanism of ARS1-associated disorders.
CRIS-Team WoS Importer:2021-10-01

The recurrent TCF4 missense variant p.(Arg389Cys) causes a neurodevelopmental disorder overlapping with but not typical for Pitt-Hopkins syndrome - Popp, Bernt; Bienvenu, Thierry; Giurgea, Irina; Metreau, Julia; Kraus, Cornelia; Reis, André; Fischer, Jan; Bralo, Maria Palomares; Tenorio-Castano, Jair; Lapunzina, Pablo; Almoguera, Berta; Lopez-Grondona, Fermina; et al. (Clinical Genetics, 2022)
TCF4 haploinsufficiency by deletions, truncating variants or loss-of-function missense variants within the DNA-binding and protein interacting bHLH domain causes Pitt-Hopkins syndrome (PTHS). This neurodevelopmental disorder (NDD) is characterized by severe intellectual disability (ID), epilepsy, hyperbreathing and a typical facial gestalt. Only few aberrations of the N-terminus of TCF4 were associated with milder or atypical phenotypes. By personal communication and searching databases we assembled six cases with the novel, recurrent, de novo missense variant c.1165C > T, p.(Arg389Cys) in TCF4. This variant was identified by diagnostic exome or panel sequencing and is located upstream of the bHLH domain. All six individuals presented with moderate to severe ID with language impairment. Microcephaly occurred in two individuals, epilepsy only in one, and no breathing anomalies or myopia were reported. Facial gestalt showed some aspects of PTHS but was rather non-specific in most individuals. Interestingly, the variant is located within the AD2 activation domain next to a highly conserved coactivator-recruitment motif and might alter interaction with coactivator proteins independently from the bHLH domain. Our findings of a recurrent missense variant outside the bHLH domain in six individuals with an ID phenotype overlapping with but not typical for PTHS delineate a novel genotype-phenotype correlation for TCF4-related NDDs.
CRIS-Team WoS Importer:2022-09-02

The role of Nav1.7 in human nociceptors: Insights from human induced pluripotent stem cell-derived sensory neurons of erythromelalgia patients - Meents, Jannis E.; Bressan, Elisangela; Sontag, Stephanie; Foerster, Alec; Hautvast, Petra; Rösseler, Corinna; Hampl, Martin; Schüler, Herdit; Goetzke, Roman; Le, Thi Kim Chi; Kleggetveit, Inge Petter; Le Cann, Kim; et al. (Pain, 2019)
The chronic pain syndrome inherited erythromelalgia (IEM) is attributed to mutations in the voltage-gated sodium channel (NaV) 1.7. Still, recent studies targeting NaV1.7 in clinical trials have provided conflicting results. Here, we differentiated induced pluripotent stem cells from IEM patients with the NaV1.7/I848T mutation into sensory nociceptors. Action potentials in these IEM nociceptors displayed a decreased firing threshold, an enhanced upstroke, and afterhyperpolarization, all of which may explain the increased pain experienced by patients. Subsequently, we investigated the voltage dependence of the tetrodotoxin-sensitive NaV activation in these human sensory neurons using a specific prepulse voltage protocol. The IEM mutation induced a hyperpolarizing shift of NaV activation, which leads to activation of NaV1.7 at more negative potentials. Our results indicate that NaV1.7 is not active during subthreshold depolarizations, but that its activity defines the action potential threshold and contributes significantly to the action potential upstroke. Thus, our model system with induced pluripotent stem cell-derived sensory neurons provides a new rationale for NaV1.7 function and promises to be valuable as a translational tool to profile and develop more efficacious clinical analgesics.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Action potential firing; Erythromelalgia; Induced pluripotent stem cells; Inherited pain syndrome; iPS cells; Nociceptor; Pain; Patch-clamp; Voltage-gated sodium channel

The Slavic NBN Founder Mutation: A Role for Reproductive Fitness? - Seemanova, Eva; Varon, Raymonda; Vejvalka, Jan; Jarolim, Petr; Seeman, Pavel; Chrzanowska, Krystyna H.; Digweed, Martin; Resnick, Igor; Kremensky, Ivo; Saar, Kathrin; Hoffmann, Katrin; Dutrannoy, Veronique; et al. (PLoS ONE, 2016)
The vast majority of patients with Nijmegen Breakage Syndrome (NBS) are of Slavic origin and carry a deleterious deletion (c.657del5; rs587776650) in the NBN gene on chromosome 8q21. This mutation is essentially confined to Slavic populations and may thus be considered a Slavic founder mutation. Notably, not a single parenthood of a homozygous c.657del5 carrier has been reported to date, while heterozygous carriers do reproduce but have an increased cancer risk. These observations seem to conflict with the considerable carrier frequency of c.657del5 of 0.5% to 1% as observed in different Slavic populations because deleterious mutations would be eliminated quite rapidly by purifying selection. Therefore, we propose that heterozygous c.657del5 carriers have increased reproductive success, i.e., that the mutation confers heterozygote advantage. In fact, in our cohort study of the reproductive history of 24 NBS pedigrees from the Czech Republic, we observed that female carriers gave birth to more children on average than female non-carriers, while no such reproductive differences were observed for males. We also estimate that c.657del5 likely occurred less than 300 generations ago, thus supporting the view that the original mutation predated the historic split and subsequent spread of the 'Slavic people'. We surmise that the higher fertility of female c.657del5 carriers reflects a lower miscarriage rate in these women, thereby reflecting the role of the NBN gene product, nibrin, in the repair of DNA double strand breaks and their processing in immune gene rearrangements, telomere maintenance, and meiotic recombination, akin to the previously described role of the DNA repair genes BRCA1 and BRCA2.
EVALuna2:9351

The Status Quo of Rare Diseases Centres for the Development of a Clinical Decision Support System - A Cross-Sectional Study - Schaaf, Jannik; Sedlmayr, Martin; Prokosch, Hans-Ulrich; Ganslandt, Thomas; Schade-Brittinger, Carmen; von Wagner, Michael; Kadioglu, Dennis; Schubert, Katharina; Lee-Kirsch, Min Ae; Kraemer, Bernhard K.; Winner, Beate; Mueller, Tobias; et al. (dHealth 2020 – Biomedical Informatics for Health and Care, 2020)
Clinical decision support systems (CDSS) help to improve the diagnostics and treatment of rare diseases (RD). As one of four funded consortia of the Medical Informatics Initiative supported by the Federal Ministry of Education and Research (BMBF, Germany), MIRACUM develops a clinical decision support system (CDSS) for RD based on distributed data of ten university hospitals. The CDSS will be developed at the Rare Diseases Centres (RDC) of the MIRACUM consortium. Since it is essential to deliver decision support at the right time and place in the clinician's workflow, this study aimed to capture relevant information of the RDCs regarding patient admission and diagnostic process. Additionally, we investigated how patient documentation and digitalisation is performed at the centres. Therefore, we conducted a cross-sectional survey involving experts in the RDs domain to capture relevant information for the further development of a CDSS in RD. For each centre, one expert on RDs participated in the study (n=8). The survey identified several challenges regarding the reuse of patient data, e.g. the paper-based documentation of a patientâĂŹs medical history and coding of diagnoses using ICD-10. However, we noticed a relevant use of current software diagnosis support and a similarly performed diagnostic process in all RDC. Further studies are needed to get more detailed insights and to define specific requirements.
CRIS-Team Scopus Importer:2020-07-10
Keywords: clinical decision support; quantitative analysis; rare diseases

The temporal expression pattern of alpha-synuclein modulates olfactory neurogenesis in transgenic mice - Schreglmann, Sebastian R.; Regensburger, Martin; Rockenstein, Edward; Masliah, Eliezer; Xiang, Wei; Winkler, Jürgen; Winner, Beate (PLoS ONE, 2015)
Adult neurogenesis mirrors the brain´s endogenous capacity to generate new neurons throughout life. In the subventricular zone/ olfactory bulb system adult neurogenesis is linked to physiological olfactory function and has been shown to be impaired in murine models of neuronal alpha-Synuclein overexpression. We analyzed the degree and temporo-spatial dynamics of adult olfactory bulb neurogenesis in transgenic mice expressing human wild-type alpha-Synuclein (WTS) under the murine Thy1 (mThy1) promoter, a model known to have a particularly high tg expression associated with impaired olfaction.Survival of newly generated neurons (NeuN-positive) in the olfactory bulb was unchanged in mThy1 transgenic animals. Due to decreased dopaminergic differentiation a reduction in new dopaminergic neurons within the olfactory bulb glomerular layer was present. This is in contrast to our previously published data on transgenic animals that express WTS under the control of the human platelet-derived growth factor ? (PDGF) promoter, that display a widespread decrease in survival of newly generated neurons in regions of adult neurogenesis, resulting in a much more pronounced neurogenesis deficit. Temporal and quantitative expression analysis using immunofluorescence co-localization analysis and Western blots revealed that in comparison to PDGF transgenic animals, in mThy1 transgenic animals WTS is expressed from later stages of neuronal maturation only but at significantly higher levels both in the olfactory bulb and cortex.The dissociation between higher absolute expression levels of alpha-Synuclein but less severe impact on adult olfactory neurogenesis in mThy1 transgenic mice highlights the importance of temporal expression characteristics of alpha-Synuclein on the maturation of newborn neurons.
EVALuna2:4712

The Trojan horse - neuroinflammatory impact of T cells in neurodegenerative diseases - Sommer, Annika; Winner, Beate; Prots, Iryna (Molecular Neurodegeneration, 2017)
Neuronal degeneration is a common mechanism of many neurological diseases including Parkinson's disease (PD), Alzheimer's disease (AD), and Multiple Sclerosis (MS). While AD and PD are classical neurodegenerative diseases, the primary pathology in MS is driven by autoimmune inflammation, attacking oligodendrocytes and thereby inducing neurodegeneration. In AD and PD, immune cells are also considered to play an important role in the disease progression. While the role of local central nervous system (CNS) innate immune cells is well described, a potential influence of adaptive immune cells in PD and AD is not yet fully understood.Here, we aim to summarize findings concerning adaptive immune cells in PD pathogenesis and compare them to AD and MS. In the first part, we focus on disease-specific alterations of lymphocytes in the circulating blood. Subsequently, we describe what is known about CNS-infiltrated lymphocytes and mechanisms of their infiltration. Finally, we summarize published data and try to understand the mechanisms of how lymphocytes contribute to neurodegeneration in PD, AD, and MS.Lymphocytes are critically involved in the pathogenesis of MS, and clarifying the role of lymphocytes in PD and AD pathogenesis might lead to an identification of a common signature of lymphocytes in neurodegeneration and thus pave the road towards novel treatment options.
EVALuna2:34020

Thin corpus callosum and amyotrophy in spastic paraplegia–case report and review of literature. - Winner, Beate; Winkler, Jürgen; Bogdahn, Ulrich; Hehr, Ute; et al. (Clinical Neurology and Neurosurgery, 2006)
We report the clinical, structural, functional and genetic characterization of a 37-year-old Caucasian female, presenting as a sporadic case of complicated spastic paraplegia with thin corpus callosum (CC), cognitive impairment, amyotrophy of the hand muscles and a sensorimotor neuropathy and review the literature for spastic paraplegia with thin CC. Magnetic resonance imaging (MRI) examination revealed a thin CC with fronto-parietal cortical atrophy. 18Fluordesoxyglucose positron emission tomography (FDG-PET) showed reduced cortical and thalamic metabolism. By transcranial magnetic stimulation, we delineated a severe impairment of transcallosal inhibition. Sequence analysis did not reveal disease causing mutations in the genes SLC12A6 (Andermann), Spastin (SPG 4), BSCL2 (SPG 17) and Spartin (SPG 20). We reviewed the literature for HSP with thin CC and found 113 HSP patients with thin CC previously described (35 with linkage to chromosome 15q13-15). Thin CC and peripheral neuropathy often appear together in spastic paraplegia and might be indicative for combined degeneration mechanism of central and peripheral axons.

Thoracic rat spinal cord contusion injury induces remote spinal gliogenesis but not neurogenesis or gliogenesis in the brain - Franz, Steffen; Ciatipis, Mareva; Pfeifer, Kathrin; Kierdorf, Birthe; Sandner, Beatrice; Bogdahn, Ulrich; Blesch, Armin; Winner, Beate; Weidner, Norbert (PLoS ONE, 2014)
After spinal cord injury, transected axons fail to regenerate, yet significant, spontaneous functional improvement can be observed over time. Distinct central nervous system regions retain the capacity to generate new neurons and glia from an endogenous pool of progenitor cells and to compensate neural cell loss following certain lesions. The aim of the present study was to investigate whether endogenous cell replacement (neurogenesis or gliogenesis) in the brain (subventricular zone, SVZ; corpus callosum, CC; hippocampus, HC; and motor cortex, MC) or cervical spinal cord might represent a structural correlate for spontaneous locomotor recovery after a thoracic spinal cord injury. Adult Fischer 344 rats received severe contusion injuries (200 kDyn) of the mid-thoracic spinal cord using an Infinite Horizon Impactor. Uninjured rats served as controls. From 4 to 14 days post-injury, both groups received injections of bromodeoxyuridine (BrdU) to label dividing cells. Over the course of six weeks post-injury, spontaneous recovery of locomotor function occurred. Survival of newly generated cells was unaltered in the SVZ, HC, CC, and the MC. Neurogenesis, as determined by identification and quantification of doublecortin immunoreactive neuroblasts or BrdU/neuronal nuclear antigen double positive newly generated neurons, was not present in non-neurogenic regions (MC, CC, and cervical spinal cord) and unaltered in neurogenic regions (dentate gyrus and SVZ) of the brain. The lack of neuronal replacement in the brain and spinal cord after spinal cord injury precludes any relevance for spontaneous recovery of locomotor function. Gliogenesis was increased in the cervical spinal cord remote from the injury site, however, is unlikely to contribute to functional improvement.
EVALuna2:26226

Tideglusib Rescues Neurite Pathology of SPG11 iPSC Derived Cortical Neurons. - Pozner, Tatyana; Schray, Annika; Regensburger, Martin; Lie, Dieter Chichung; Schlötzer-Schrehardt, Ursula; Winkler, Jürgen; Turan, Sören; Winner, Beate (Frontiers in Neuroscience, 2018)
Mutations in SPG11 cause a complicated autosomal recessive form of hereditary spastic paraplegia (HSP). Mechanistically, there are indications for the dysregulation of the GSK3 beta/beta Cat signaling pathway in SPG11. In this study, we tested the therapeutic potential of the GSK3 beta inhibitor, tideglusib, to rescue neurodegeneration associated characteristics in an induced pluripotent stem cells (iPSCs) derived neuronal model from SPG11 patients and matched healthy controls as well as a CRISPR-Cas9 mediated SPG11 knock-out line and respective control. SPG11-iPSC derived cortical neurons, as well as the genome edited neurons exhibited shorter and less complex neurites than controls. Administration of tideglusib to these lines led to the rescue of neuritic impairments. Moreover, the treatment restored increased cell death and ameliorated the membranous inclusions in iPSC derived SPG11 neurons. Our results provide a first evidence for the rescue of neurite pathology in SPG11-HSP by tideglusib. The current lack of disease-modifying treatments for SPG11 and related types of complicated HSP renders tideglusib a candidate compound for future clinical application.
EVALuna2:35778
Keywords: CRISPR knock-out; GSK3β inhibitor; SPG11; hereditary spastic paraplegia; induced pluripotent stem cell; neuronal culture; tideglusib

Transcriptional repressor ZEB2 promotes terminal differentiation of CD8+ effector and memory T cell populations during infection - Omilusik, Kyla D.; Best, J. Adam; Yu, Bingfei; Goossens, Steven; Weidemann, Alexander; Nguyen, Jessica V.; Seuntjens, Eve; Stryjewska, Agata; Zweier, Christiane; Roychoudhuri, Rahul; Gattinoni, Luca; Bird, Lynne M.; et al. (Journal of Experimental Medicine, 2015)
ZEB2 is a multi-zinc-finger transcription factor known to play a significant role in early neurogenesis and in epithelial-mesenchymal transition-dependent tumor metastasis. Although the function of ZEB2 in T lymphocytes is unknown, activity of the closely related family member ZEB1 has been implicated in lymphocyte development. Here, we find that ZEB2 expression is up-regulated by activated T cells, specifically in the KLRG1(hi) effector CD8(+) T cell subset. Loss of ZEB2 expression results in a significant loss of antigen-specific CD8(+) T cells after primary and secondary infection with a severe impairment in the generation of the KLRG1(hi) effector memory cell population. We show that ZEB2, which can bind DNA at tandem, consensus E-box sites, regulates gene expression of several E-protein targets and may directly repress Il7r and Il2 in CD8(+) T cells responding to infection. Furthermore, we find that T-bet binds to highly conserved T-box sites in the Zeb2 gene and that T-bet and ZEB2 regulate similar gene expression programs in effector T cells, suggesting that T-bet acts upstream and through regulation of ZEB2. Collectively, we place ZEB2 in a larger transcriptional network that is responsible for the balance between terminal differentiation and formation of memory CD8(+) T cells.
EVALuna2:3800

Transcription factor Fra-1 targets arginase-1 to enhance macrophage-mediated inflammation in arthritis - Hannemann, Nicole; Cao, Shan; Eriksson, Daniel; Schnelzer, Anne; Jordan, Jutta; Eberhardt, Martin; Schleicher, Ulrike; Rech, Jürgen; Uebe, Steffen; Ekici, Arif Bülent; Canete, Juan D.; Chen, Xiaoxiang; et al. (Journal of Clinical Investigation, 2019)
The polarization of macrophages is regulated by transcription factors, such as NF-κB and activator protein 1 (AP-1). In this manuscript, we delineated the role of the transcription factor Fos-related antigen 1 (Fra-1) during macrophage activation and development of arthritis. Network level interaction analysis of microarray data derived from Fra-1- or Fra-2-deficient macrophages revealed a central role of Fra-1, but not of Fra-2, in orchestrating the expression of genes related to wound response, Toll-like receptor activation, and interleukin signaling. ChIP sequencing and standard ChIP analyses of macrophages identified arginase 1 (Arg1) as a target of Fra-1. Luciferase reporter assays revealed that Fra-1 downregulated Arg1 expression by direct binding to the promoter region. Using macrophage-specific Fra-1- or Fra-2-deficient mice, we observed enhanced expression and activity of Arg1 and a reduction of arthritis in the absence of Fra-1, but not of Fra-2. This phenotype was reversed by treatment with the arginase inhibitor Nω-hydroxy-nor-arginine, while -arginine supplementation increased arginase activity and alleviated arthritis, supporting the notion that reduced arthritis in macrophage-specific Fra-1-deficient mice resulted from enhanced Arg1 expression and activity. Moreover, patients with active rheumatoid arthritis (RA) showed increased Fra-1 expression in the peripheral blood and elevated Fra-1 protein in synovial macrophages compared with RA patients in remission. In addition, the Fra-1/ARG1 ratio in synovial macrophages was related to RA disease activity. In conclusion, these data suggest that Fra-1 orchestrates the inflammatory state of macrophages by inhibition of Arg1 expression and thereby impedes the resolution of inflammation.
CRIS-Team Scopus Importer:2019-07-16

Transcription factor Tcf4 is the preferred heterodimerization partner for Olig2 in oligodendrocytes and required for differentiation - Wedel, Miriam; Fröb, Franziska; Elsesser, Olga; Wittmann, Marie-Theres; Lie, Dieter Chichung; Reis, André; Wegner, Michael (Nucleic Acids Research, 2020)
Development of oligodendrocytes and myelin formation in the vertebrate central nervous system is under control of several basic helix-loop-helix transcription factors such as Olig2, Ascl1, Hes5 and the Id proteins. The class I basic helix-loop-helix proteins Tcf3, Tcf4 and Tcf12 represent potential heterodimerization partners and functional modulators for all, but have not been investigated in oligodendrocytes so far. Using mouse mutants, organotypic slice and primary cell cultures we here show that Tcf4 is required in a cell-autonomous manner for proper terminal differentiation and myelination in vivo and ex vivo. Partial compensation is provided by the paralogous Tcf3, but not Tcf12. On the mechanistic level Tcf4 was identified as the preferred heterodimerization partner of the central regulator of oligodendrocyte development Olig2. Both genetic studies in the mouse as well as functional studies on enhancer regions of myelin genes confirmed the relevance of this physical interaction for oligodendrocyte differentiation. Considering that alterations in TCF4 are associated with syndromic and non-syndromic forms of intellectual disability, schizophrenia and autism in humans, our findings point to the possibility of an oligodendroglial contribution to these disorders.
CRIS-Team Scopus Importer:2020-05-29

Transcriptome-pathology correlation identifies interplay between TDP-43 and the expression of its kinase CK1E in sporadic ALS - Krach, Florian; Batra, Ranjan; Wheeler, Emily C.; Vu, Anthony Q.; Wang, Ruth; Hutt, Kasey; Rabin, Stuart J.; Baughn, Michael W.; Libby, Ryan T.; Diaz-Garcia, Sandra; Stauffer, Jennifer; Pirie, Elaine; et al. (Acta Neuropathologica, 2018)
Sporadic amyotrophic lateral sclerosis (sALS) is the most common form of ALS, however, the molecular mechanisms underlying cellular damage and motor neuron degeneration remain elusive. To identify molecular signatures of sALS we performed genome-wide expression profiling in laser capture microdissection-enriched surviving motor neurons (MNs) from lumbar spinal cords of sALS patients with rostral onset and caudal progression. After correcting for immunological background, we discover a highly specific gene expression signature for sALS that is associated with phosphorylated TDP-43 (pTDP-43) pathology. Transcriptome-pathology correlation identified casein kinase 1 epsilon (CSNK1E) mRNA as tightly correlated to levels of pTDP-43 in sALS patients. Enhanced crosslinking and immunoprecipitation in human sALS patient- and healthy control-derived frontal cortex, revealed that TDP-43 binds directly to and regulates the expression of CSNK1E mRNA. Additionally, we were able to show that pTDP-43 itself binds RNA. CK1E, the protein product of CSNK1E, in turn interacts with TDP-43 and promotes cytoplasmic accumulation of pTDP-43 in human stem-cell-derived MNs. Pathological TDP-43 phosphorylation is therefore, reciprocally regulated by CK1E activity and TDP-43 RNA binding. Our framework of transcriptome-pathology correlations identifies candidate genes with relevance to novel mechanisms of neurodegeneration.
EVALuna2:35779

Transcriptome sequencing reveals maelstrom as a novel target gene of the terminal system in the red flour beetle Tribolium castaneum - Pridöhl, Fabian; Weißkopf, Matthias; Koniszewski, Nikolaus; Sulzmaier, Andreas; Uebe, Steffen; Ekici, Arif Bülent; Schoppmeier, Michael (Development, 2017)
Terminal regions of the Drosophila embryo are patterned by the localized activation of the Torso-RTK pathway, which promotes the downregulation of Capicua. In the short-germ beetle Tribolium, the function of the terminal system appears to be rather different, as the pathway promotes axis elongation and, in addition, is required for patterning the extra-embryonic serosa at the anterior. Here, we show that Torso signalling also induces gene expression by relieving Capicua-mediated repression in Tribolium Given that the majority of Torso target genes remain to be identified, we established a differential gene-expression screen. A subset of 50 putative terminal target genes was screened for functions in early embryonic patterning. Of those, 13 genes show early terminal expression domains and also phenotypes were related to terminal patterning. Among others, we found the PIWI-interacting RNA factor Maelstrom to be crucial for early embryonic polarization. Tc-mael is required for proper serosal size regulation and head morphogenesis. Moreover, Tc-mael promotes growth-zone formation and axis elongation. Our results suggest that posterior patterning by Torso may be realized through Maelstrom-dependent activation of posterior Wnt domains.
EVALuna2:9357

Transcriptomes of MPO-deficient patients with generalized pustular psoriasis reveals expansion of CD4+cytotoxic T cells and an involvement of complement system and interferon pathways - Hüffmeier, Ulrike; Frey, Benjamin; Becker, Ina; Atreya, Imke; Berking, Carola; Moessner, R.; Wilsmann-Theis, D.; Uebe, Steffen; Kirchner, P.; Haskamp, Stefan (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-05

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

Transient receptor potential ankyrin 1 promoter methylation and peripheral pain sensitivity in Crohn's disease - Gombert, Sara; Rhein, Mathias; Winterpacht, Andreas; Münster, Tino; Hillemacher, Thomas; Leffler, Andreas; Frieling, Helge (Clinical Epigenetics, 2019)
Background Crohn's disease is a chronic inflammatory disorder of the gastrointestinal tract associated with abdominal pain and diarrhea. Pain caused by Crohn's disease likely involves neurogenic inflammation which seems to involve the ion channel transient receptor potential ankyrin 1 (TRPA1). Since the promoter methylation of TRPA1 was shown to influence pain sensitivity, we asked if the expression of TRPA1 is dysregulated in patients suffering from Crohn's disease. The methylation rates of CpG dinucleotides in the TRPA1 promoter region were determined from DNA derived from whole blood samples of Crohn patients and healthy participants. Quantitative sensory testing was used to examine pain sensitivities. Results Pressure pain thresholds were lower in Crohn patients as compared to healthy participants, and they were also lower in females than in males. They correlated inversely with the methylation rate at the CpG - 628 site of the TRPA1 promoter. This effect was more pronounced in female compared to male Crohn patients. Similar results were found for mechanical pain thresholds. Furthermore, age-dependent effects were detected. Whereas the CpG - 628 methylation rate declined with age in healthy participants, the methylation rate in Crohn patients increased. Pressure pain thresholds increased with age in both cohorts. Conclusions The TRPA1 promoter methylation appears to be dysregulated in patients suffering from Crohn's disease, and this effect is most obvious when taking gender and age into account. As TRPA1 is regarded to be involved in pain caused by neurogenic inflammation, its aberrant expression may contribute to typical symptoms of Crohn's disease.
CRIS-Team WoS Importer:2020-01-10

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation - Pieger, Katharina; Schmitt, Verena; Gauer, Carina; Gießl, Nadja; Prots, Iryna; Winner, Beate; Winkler, Jürgen; Brandstätter, Johann Helmut; Xiang, Wei (Biomolecules, 2022)
Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson's disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffinity towards aSyn in the nucleus. Comparing the Nu-aSyn-C antibody to aSyn antibodies developed against phosphorylated or aggregated forms, we observed that nuclear aSyn differs from cytosolic aSyn by an increased phosphorylation and assembly level in proliferating cells. Employing Nu-aSyn-C, we characterized aSyn distribution during neuronal differentiation in midbrain dopaminergic neurons (mDANs) derived from human-induced pluripotent stem cells (hiPSCs) and Lund human mesencephalic cells, and in primary rat hippocampal neurons. We detected a specific translocation pattern of aSyn during neuronal differentiation from the nucleus to the soma and finally to neuronal processes. Interestingly, a remarkable shift of Nu-aSyn-C-positive species towards neurites was detected in hiPSC mDANs from a PD patient carrying aSyn gene duplication. Together, our results reveal distinct nuclear and cytosolic aSyn species that redistribute during neuronal differentiation-a process that is altered in PD-derived neurons.
CRIS-Team WoS Importer:2022-09-09

TRIM28 haploinsufficiency predisposes to Wilms tumor - Diets, Illja J.; Hoyer, Juliane; Ekici, Arif Bülent; Popp, Bernt; Hoogerbrugge, Nicoline; van Reijmersdal, Simon V.; Bhaskaran, Rajith; Hadjihannas, Michel; Vasileiou, Georgia; Thiel, Christian; Seven, Didem; Uebe, Steffen; et al. (International Journal of Cancer, 2019)
Two percent of patients with Wilms tumors have a positive family history. In many of these cases the genetic cause remains unresolved. By applying germline exome sequencing in two families with two affected individuals with Wilms tumors, we identified truncating mutations in TRIM28. Subsequent mutational screening of germline and tumor DNA of 269 children affected by Wilms tumor was performed, and revealed seven additional individuals with germline truncating mutations, and one individual with a somatic truncating mutation in TRIM28. TRIM28 encodes a complex scaffold protein involved in many different processes, including gene silencing, DNA repair and maintenance of genomic integrity. Expression studies on mRNA and protein level showed reduction of TRIM28, confirming a loss-of-function effect of the mutations identified. The tumors showed an epithelial-type histology that stained negative for TRIM28 by immunohistochemistry. The tumors were bilateral in six patients, and 10/11 tumors are accompanied by perilobar nephrogenic rests. Exome sequencing on eight tumor DNA samples from six individuals showed loss-of-heterozygosity (LOH) of the TRIM28-locus by mitotic recombination in seven tumors, suggesting that TRIM28 functions as a tumor suppressor gene in Wilms tumor development. Additionally, the tumors showed very few mutations in known Wilms tumor driver genes, suggesting that loss of TRIM28 is the main driver of tumorigenesis. In conclusion, we identified heterozygous germline truncating mutations in TRIM28 in 11 children with mainly epithelial-type Wilms tumors, which become homozygous in tumor tissue. These data establish TRIM28 as a novel Wilms tumor predisposition gene, acting as a tumor suppressor gene by LOH.
CRIS-Team Scopus Importer:2019-05-02
Keywords: genetic predisposition; haploinsufficiency; TRIM28; Wilms tumor

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Two truncating variants in FANCC and breast cancer risk - Dork, Thilo; Peterlongo, Paolo; Mannermaa, Arto; Bolla, Manjeet K.; Wang, Qin; Dennis, Joe; Ahearn, Thomas; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Aronson, Kristan J.; Augustinsson, Annelie; et al. (Scientific Reports, 2019)
Fanconi anemia (FA) is a genetically heterogeneous disorder with 22 disease-causing genes reported to date. In some FA genes, monoallelic mutations have been found to be associated with breast cancer risk, while the risk associations of others remain unknown. The gene for FA type C, FANCC, has been proposed as a breast cancer susceptibility gene based on epidemiological and sequencing studies. We used the Oncoarray project to genotype two truncating FANCC variants (p.R185X and p.R548X) in 64,760 breast cancer cases and 49,793 controls of European descent. FANCC mutations were observed in 25 cases (14 with p.R185X, 11 with p.R548X) and 26 controls (18 with p.R185X, 8 with p.R548X). There was no evidence of an association with the risk of breast cancer, neither overall (odds ratio 0.77, 95%CI 0.44–1.33, p = 0.4) nor by histology, hormone receptor status, age or family history. We conclude that the breast cancer risk association of these two FANCC variants, if any, is much smaller than for BRCA1, BRCA2 or PALB2 mutations. If this applies to all truncating variants in FANCC it would suggest there are differences between FA genes in their roles on breast cancer risk and demonstrates the merit of large consortia for clarifying risk associations of rare variants.
CRIS-Team Scopus Importer:2019-09-17

Tyrosinase downregulates Fibromodulin- induced lymphangiogenesis - Clahsen, Thomas; Regenfuss, Birgit; Büttner, Christian; Gabriel, Tim; Bock, Felix; Reis, André; Cursiefen, Claus (2018)
EVALuna2:34828

Tyrosinase is a novel endogenous inhibitor of lymphangiogenesis - Clahsen, Thomas; Büttner, Christian; Regenfuss, Birgit; Gabriel, Tim; Bock, Felix; Reis, André; Cursiefen, Claus (2019)
EVALuna2:206970

Tyrosinase is a novel endogenous regulator of developmental and inflammatory lymphangiogenesis - Büttner, Christian; Clahsen, Thomas; Regenfuss, Birgit; Dreisow, Marie Luise; Steiber, Zita; Bock, Felix; Reis, André; Cursiefen, Claus (American Journal of Pathology, 2018)
Lymphangiogenesis is critically involved in tissue fluid balance, graft rejection, and tumor metastasis. Endogenous regulation of lymphangiogenesis is poorly understood. Here we use the lymphatic vessel architecture at the limbal border of the normally avascular cornea, a quantitative trait under strong genetic influence, as a model system to identify new candidate genes regulating lymphangiogenesis. Comparing low-lymphangiogenic BALB/cN versus high-lymphangiogenic C57BL/6N mice, we performed quantitative trait loci analysis of five phenotypes in a large BALB/cN x C57BL/6N intercross (n=795) and identified three to eight genome-wide significant loci, the strongest on chromosome 7 containing Tyrosinase (Tyr). Tyrosinase-negative mice showed significantly increased limbal lymphvascularized areas, a higher number of lymphatic vessel endpoints, and branching points and increased inflammation-induced lymphangiogenesis. These findings confirm that tyrosinase is a novel lymphangiogenesis regulator in developmental and inflammatory lymphangiogenesis. Our findings link melanin synthesis with lymphangiogenesis and open new treatment options in lymphangiogenesis-related diseases.
EVALuna2:34844

Tyrosinase reduces expression of vascular endothelial growth factors and improves corneal graft survival - Clahsen, Thomas; Hatami, Niloofar; Büttner, Christian; Reis, André; Cursiefen, Claus (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Unexpected phenotypic variability in a family with epilepsy explained by independent segregation of biparental CACNA1A loss-of-function variants - Kraus, Cornelia; Mammadova, Dilbar; Leis, T.; Ekici, Arif Bülent; Thiel, C.; Reis, André; Trollmann, Regina (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Unique signatures of stress-induced senescent human astrocytes - Simmnacher, Katrin; Krach, Florian; Schneider, Yanni; Alecu, Julian E.; Mautner, Lena; Klein, Paulina; Roybon, Laurent; Prots, Iryna; Xiang, Wei; Winner, Beate (Experimental Neurology, 2020)
Senescence was recently linked to neurodegeneration and astrocytes are one of the major cell types to turn senescent under neurodegenerative conditions. Senescent astrocytes were detected in Parkinson's disease (PD) patients' brains besides reactive astrocytes, yet the difference between senescent and reactive astrocytes is unclear. We aimed to characterize senescent astrocytes in comparison to reactive astrocytes and investigate differences and similarities. In a cell culture model of human fetal astrocytes, we determined a unique senescent transcriptome distinct from reactive astrocytes, which comprises dysregulated pathways. Both, senescent and reactive human astrocytes activated a proinflammatory pattern. Astrocyte senescence was at least partially depending on active mechanistic-target-of-rapamycin (mTOR) and DNA-damage response signaling, both drivers of senescence. To further investigate how PD and senescence connect to each other, we asked if a PD-linked environmental factor induces senescence and if senescence impairs midbrain neurons. We could show that the PD-linked pesticide rotenone causes astrocyte senescence. We further delineate, that the senescent secretome exaggerates rotenone-induced neurodegeneration in midbrain neurons differentiated from human induced pluripotent stem cells (hiPSC) of PD patients with alpha-synuclein gene (SNCA) locus duplication.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Alpha synuclein; Astrocyte neuron interplay; iPSC derived neurons; Parkinson's disease; Reactive astrocyte; Rotenone; Senescence

Updated insight into the mutational and phenotypic spectrum of MED13L-related intellectual disability - Asadollahi, R.; Boonsawat, P.; Popp, B.; Torti, E.; Bader, I.; Vitobello, A.; Moutton, S.; Pinson, L.; Lambert, L.; Thuresson, A. C.; Sobol, M.; Zander, C. Soussi; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Variants in ASB10 are associated with open-angle glaucoma - Pasutto, Francesca; Keller, Kate E.; Weisschuh, Nicole; Sticht, Heinrich; Samples, John R.; Yang, Yong-Feng; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Mardin, Christian Y.; Frezzotti, Paolo; Edmunds, Beth; Kramer, Patricia L.; et al. (Human Molecular Genetics, 2012)
The molecular events responsible for obstruction of aqueous humor outflow and the loss of retinal ganglion cells in glaucoma, one of the main causes of blindness worldwide, remain poorly understood. We identified a synonymous variant, c.765C>T (Thr255Thr), in ankyrin repeats and suppressor of cytokine signaling box-containing protein 10 (ASB10) in a large family with primary open angle glaucoma (POAG) mapping to the GLC1F locus. This variant affects an exon splice enhancer site and alters mRNA splicing in lymphoblasts of affected family members. Systematic sequence analysis in two POAG patient groups (195 US and 977 German) and their respective controls (85 and 376) lead to the identification of 26 amino acid changes in 70 patients (70 of 1172; 6.0%) compared with 9 in 13 controls (13 of 461; 2.8%; P = 0.008). Molecular modeling suggests that these missense variants change ASB10 net charge or destabilize ankyrin repeats. ASB10 mRNA and protein were found to be strongly expressed in trabecular meshwork, retinal ganglion cells and ciliary body. Silencing of ASB10 transcripts in perfused anterior segment organ culture reduced outflow facility by 50% compared with control-infected anterior segments (P = 0.02). In conclusion, genetic and molecular analyses provide evidence for ASB10 as a glaucoma-causing gene.
EVALuna2:9125

Variants in genes encoding small GTPases and association with epithelial ovarian cancer susceptibility - Earp, Madalene; Tyrer, Jonathan P.; Winham, Stacey J.; Lin, Hui-Yi; Chornokur, Ganna; Dennis, Joe; Aben, Katja K. H.; Anton-Culver, Hoda; Antonenkova, Natalia; Bandera, Elisa V.; Bean, Yukie T.; Beckmann, Matthias; et al. (PLoS ONE, 2018)
Epithelial ovarian cancer (EOC) is the fifth leading cause of cancer mortality in American women. Normal ovarian physiology is intricately connected to small GTP binding proteins of the Ras superfamily (Ras, Rho, Rab, Arf, and Ran) which govern processes such as signal transduction, cell proliferation, cell motility, and vesicle transport. We hypothesized that common germline variation in genes encoding small GTPases is associated with EOC risk. We investigated 322 variants in 88 small GTPase genes in germline DNA of 18,736 EOC patients and 26,138 controls of European ancestry using a custom genotype array and logistic regression fitting log-additive models. Functional annotation was used to identify biofeatures and expression quantitative trait loci that intersect with risk variants. One variant, ARHGEF10L (Rho guanine nucleotide exchange factor 10 like) rs2256787, was associated with increased endometrioid EOC risk (OR = 1.33, p = 4.46 x 10-6). Other variants of interest included another in ARHGEF10L, rs10788679, which was associated with invasive serous EOC risk (OR = 1.07, p = 0.00026) and two variants in AKAP6 (A-kinase anchoring protein 6) which were associated with risk of invasive EOC (rs1955513, OR = 0.90, p = 0.00033; rs927062, OR = 0.94, p = 0.00059). Functional annotation revealed that the two ARHGEF10L variants were located in super-enhancer regions and that AKAP6 rs927062 was associated with expression of GTPase gene ARHGAP5 (Rho GTPase activating protein 5). Inherited variants in ARHGEF10L and AKAP6, with potential transcriptional regulatory function and association with EOC risk, warrant investigation in independent EOC study populations.
EVALuna2:34624

Variants in LRRC7 lead to intellectual disability, autism, aggression and abnormal eating behaviors - Willim, Jana; Woike, Daniel; Greene, Daniel; Das, Sarada; Pfeifer, Kevin; Yuan, Weimin; Lindsey, Anika; Itani, Omar; Böhme, Amber L.; Tibbe, Debora; Hönck, Hans Hinrich; Hassani Nia, Fatemeh; et al. (Nature Communications, 2024)
Members of the leucine rich repeat (LRR) and PDZ domain (LAP) protein family are essential for animal development and histogenesis. Densin-180, encoded by LRRC7, is the only LAP protein selectively expressed in neurons. Densin-180 is a postsynaptic scaffold at glutamatergic synapses, linking cytoskeletal elements with signalling proteins such as the α-subunit of Ca2+/calmodulin-dependent protein kinase II. We have previously observed an association between high impact variants in LRRC7 and Intellectual Disability; also three individual cases with variants in LRRC7 had been described. We identify here 33 individuals (one of them previously described) with a dominant neurodevelopmental disorder due to heterozygous missense or loss-of-function variants in LRRC7. The clinical spectrum involves intellectual disability, autism, ADHD, aggression and, in several cases, hyperphagia-associated obesity. A PDZ domain variant interferes with synaptic targeting of Densin-180 in primary cultured neurons. Using in vitro systems (two hybrid, BioID, coimmunoprecipitation of tagged proteins from 293T cells) we identified new candidate interaction partners for the LRR domain, including protein phosphatase 1 (PP1), and observed that variants in the LRR reduced binding to these proteins. We conclude that LRRC7 encodes a major determinant of intellectual development and behaviour.
CRIS-Team Scopus Importer:2024-11-22

Variants in PUS7 Cause Intellectual Disability with Speech Delay, Microcephaly, Short Stature, and Aggressive Behavior - De Brouwer, Arjan P. M.; Abou Jamra, Rami; Koertel, Nadine; Soyris, Clara; Polla, Daniel L.; Safra, Modi; Zisso, Avia; Powell, Christopher A.; Rebelo-Guiomar, Pedro; Dinges, Nadja; Morin, Violeta; Stock, Michael; et al. (American Journal of Human Genetics, 2018)
We describe six persons from three families with three homozygous protein truncating variants in PUS7: c.89_90del (p.Thr30Lysfs∗20), c.1348C>T (p.Arg450∗), and a deletion of the penultimate exon 15. All these individuals have intellectual disability with speech delay, short stature, microcephaly, and aggressive behavior. PUS7 encodes the RNA-independent pseudouridylate synthase 7. Pseudouridylation is the most abundant post-transcriptional modification in RNA, which is primarily thought to stabilize secondary structures of RNA. We show that the disease-related variants lead to abolishment of PUS7 activity on both tRNA and mRNA substrates. Moreover, pus7 knockout in Drosophila melanogaster results in a number of behavioral defects, including increased activity, disorientation, and aggressiveness supporting that neurological defects are caused by PUS7 variants. Our findings demonstrate that RNA pseudouridylation by PUS7 is essential for proper neuronal development and function.
EVALuna2:215758

Variants in SCAF4 Cause a Neurodevelopmental Disorder and Are Associated with Impaired mRNA Processing - Fliedner, Anna; Kirchner, Philipp; Wiesener, Antje; van de Beek, Irma; Waisfisz, Quinten; van Haelst, Mieke; Scott, Daryl A.; Lalani, Seema R.; Rosenfeld, Jill A.; Azamian, Mahshid S.; Xia, Fan; Dutra-Clarke, Marina; et al. (American Journal of Human Genetics, 2020)
RNA polymerase II interacts with various other complexes and factors to ensure correct initiation, elongation, and termination of mRNA transcription. One of these proteins is SR-related CTD-associated factor 4 (SCAF4), which is important for correct usage of polyA sites for mRNA termination. Using exome sequencing and international matchmaking, we identified nine likely pathogenic germline variants in SCAF4 including two splice-site and seven truncating variants, all residing in the N-terminal two thirds of the protein. Eight of these variants occurred de novo, and one was inherited. Affected individuals demonstrated a variable neurodevelopmental disorder characterized by mild intellectual disability, seizures, behavioral abnormalities, and various skeletal and structural anomalies. Paired-end RNA sequencing on blood lymphocytes of SCAF4-deficient individuals revealed a broad deregulation of more than 9,000 genes and significant differential splicing of more than 2,900 genes, indicating an important role of SCAF4 in mRNA processing. Knockdown of the SCAF4 ortholog CG4266 in the model organism Drosophila melanogaster resulted in impaired locomotor function, learning, and short-term memory. Furthermore, we observed an increased number of active zones in larval neuromuscular junctions, representing large glutamatergic synapses. These observations indicate a role of CG4266 in nervous system development and function and support the implication of SCAF4 in neurodevelopmental phenotypes. In summary, our data show that heterozygous, likely gene-disrupting variants in SCAF4 are causative for a variable neurodevelopmental disorder associated with impaired mRNA processing.
CRIS-Team Scopus Importer:2020-08-21
Keywords: epilepsy; intellectual disability; mRNA processing; neurodevelopmental disorder; SCAF4; seizures

Variation in NF-?B signaling pathways and survival in invasive epithelial ovarian cancer - Block, Matthew S.; Charbonneau, Bridget; Vierkant, Robert A.; Fogarty, Zachary; Bamlet, William R.; Pharoah, Paul D. P.; Chenevix-Trench, Georgia; Rossing, Mary Anne; Cramer, Daniel; Pearce, Celeste Leigh; Schildkraut, Joellen; Menon, Usha; et al. (Cancer Epidemiology Biomarkers & Prevention, 2014)
Survival in epithelial ovarian cancer (EOC) is influenced by the host immune response, yet the key genetic determinants of inflammation and immunity that affect prognosis are not known. The nuclear factor-?B (NF-?B) transcription factor family plays an important role in many immune and inflammatory responses, including the response to cancer. We studied common inherited variation in 210 genes in the NF-?B family in 10,084 patients with invasive EOC (5,248 high-grade serous, 1,452 endometrioid, 795 clear cell, and 661 mucinous) from the Ovarian Cancer Association Consortium. Associations between genotype and overall survival were assessed using Cox regression for all patients and by major histology, adjusting for known prognostic factors and correcting for multiple testing (threshold for statistical significance, P < 2.5 × 10(-5)). Results were statistically significant when assessed for patients of a single histology. Key associations were with caspase recruitment domain family, member 11 (CARD11) rs41324349 in patients with mucinous EOC [HR, 1.82; 95% confidence interval (CI), 1.41-2.35; P = 4.13 × 10(-6)] and tumor necrosis factor receptor superfamily, member 13B (TNFRSF13B) rs7501462 in patients with endometrioid EOC (HR, 0.68; 95% CI, 0.56-0.82; P = 2.33 × 10(-5)). Other associations of note included TNF receptor-associated factor 2 (TRAF2) rs17250239 in patients with high-grade serous EOC (HR, 0.84; 95% CI, 0.77-0.92; P = 6.49 × 10(-5)) and phospholipase C, gamma 1 (PLCG1) rs11696662 in patients with clear cell EOC (HR, 0.43; 95% CI, 0.26-0.73; P = 4.56 × 10(-4)). These associations highlight the potential importance of genes associated with host inflammation and immunity in modulating clinical outcomes in distinct EOC histologies.
EVALuna2:9241

VEXAS-Syndrome, a newly described autoinflammatory systemic disease with dermatologic manifestations - Baur, Vera; Stoevesandt, Johanna; Hueber, Axel; Hüffmeier, Ulrike; Kneitz, Hermann; Morbach, Henner; Schultz, Erwin; Goebeler, Matthias (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
VEXAS syndrome is a recently identified autoinflammatory systemic disease caused by an acquired somatic mutation of the X-linked UBA1 gene, the key enzyme of the first step of ubiquitylation. The acronym VEXAS stands for the characteristics Vacuoles, E1 enzyme, X-linked, autoinflammatory and somatic. The disease occurs in advanced adulthood preferentially in men and is characterized by hematological, rheumatological and dermatological symptoms. The latter include neutrophil-rich lesions reminiscent of Sweet's syndrome, erythema nodosum- and panniculitis-like skin manifestations and recurrent polychondritis of the nose and auricles. The presence of cytoplasmic vacuoles in myeloid and erythroid precursors in the bone marrow is characteristic. In up to half of the cases, VEXAS syndrome is associated with myelodysplastic syndrome. Dermatologists should be familiar with the clinical picture, as skin symptoms are often the first indicator of the disease. Molecular diagnostics are essential for confirming the diagnosis and risk stratification of affected patients. In this minireview we provide an overview of the pathophysiology, diagnosis and therapy of VEXAS syndrome and illustrate its clinical picture with two own cases.
CRIS-Team Scopus Importer:2023-11-24

Whole exome sequencing reveals a novel de novo FOXC1 mutation in a patient with unrecognized Axenfeld-Rieger syndrome and glaucoma - Pasutto, F.; Mauri, L.; Popp, Bernt; Sticht, Heinrich; Ekici, Arif Bülent; Piozzi, E.; Bonfante, A.; Penco, Silvana; Schlötzer-Schrehardt, Ursula; Reis, André (Gene, 2015)
We report the identification of a novel mutation in the fork-head box C1 (FOXC1) gene which occurred de novo in an Italian patient with unrecognized Axenfeld-Rieger syndrome. He was previously diagnosed as having late recognized primary congenital glaucoma at the age of 14 years and was subsequently subjected to multiple surgical interventions due to uncontrolled intraocular pressure and progressive visual field loss. After exclusion of mutations in CYP1B1 and MYOC, trio-whole-exome sequencing revealed de novo in frame deletion in the coding region of the FOXC1 gene (c.407_409delGTC, p.V137del) leading to a deletion of the evolutionary conserved amino acid Valine at position 137 of the protein. Molecular modeling predicted that Val137 deletion impairs FOXC1 DNA-binding capacity and transcriptional activation. Since loss-of-function mutations in FOXC1 are associated with Axenfeld-Rieger syndrome, the genetic findings in combination with re-evaluation of the patient's clinical data resulted in a corrected diagnosis of Axenfeld-Rieger syndrome with developmental glaucoma. We therefore suggest that in addition to CYP1B1 and MYOC, FOXC1 should be included in the genetic analysis of cases with unclear glaucomatous phenotypes to ensure proper diagnosis, adequate treatment and appropriate genetic counseling.
EVALuna2:9257

Zeb2 recruits HDAC-NuRD to inhibit Notch and controls Schwann cell differentiation and remyelination - Wu, Lai Man Natalie; Wang, Jincheng; Conidi, Andrea; Zhao, Chuntao; Wang, Haibo; Ford, Zachary; Zhang, Liguo; Zweier, Christiane; Ayee, Brian G.; Maurel, Patrice; Zwijsen, An; Chan, Jonah R.; et al. (Nature Neuroscience, 2016)
The mechanisms that coordinate and balance a complex network of opposing regulators to control Schwann cell (SC) differentiation remain elusive. Here we demonstrate that zinc-finger E-box-binding homeobox 2 (Zeb2, also called Sip1) transcription factor is a critical intrinsic timer that controls the onset of SC differentiation by recruiting histone deacetylases HDAC 1 and 2 (HDAC1/2) and nucleosome remodeling and deacetylase complex (NuRD) co-repressor complexes in mice. Zeb2 deletion arrests SCs at an undifferentiated state during peripheral nerve development and inhibits remyelination after injury. Zeb2 antagonizes inhibitory effectors including Notch and Sox2. Importantly, genome-wide transcriptome analysis reveals a Zeb2 target gene encoding the Notch effector Hey2 as a potent inhibitor for Schwann cell differentiation. Strikingly, a genetic Zeb2 variant associated with Mowat-Wilson syndrome disrupts the interaction with HDAC1/2-NuRD and abolishes Zeb2 activity for SC differentiation. Therefore, Zeb2 controls SC maturation by recruiting HDAC1/2-NuRD complexes and inhibiting a Notch-Hey2 signaling axis, pointing to the critical role of HDAC1/2-NuRD activity in peripheral neuropathies caused by ZEB2 mutations.
EVALuna2:9316

ZMYND11 variants are a novel cause of centrotemporal and generalised epilepsies with neurodevelopmental disorder - Oates, Stephanie; Absoud, Michael; Goyal, Sushma; Bayley, Sophie; Baulcomb, Jennifer; Sims, Annemarie; Riddett, Amy; Allis, Katrina; Brasch-Andersen, Charlotte; Balasubramanian, Meena; Bai, Renkui; Callewaert, Bert; et al. (Clinical Genetics, 2021)
ZMYND11 is the critical gene in chromosome 10p15.3 microdeletion syndrome, a syndromic cause of intellectual disability. The phenotype of ZMYND11 variants has recently been extended to autism and seizures. We expand on the epilepsy phenotype of 20 individuals with pathogenic variants in ZMYND11. We obtained clinical descriptions of 16 new and nine published individuals, plus detailed case history of two children. New individuals were identified through GeneMatcher, ClinVar and the European Network for Therapies in Rare Epilepsy (NETRE). Genetic evaluation was performed using gene panels or exome sequencing; variants were classified using American College of Medical Genetics (ACMG) criteria. Individuals with ZMYND11 associated epilepsy fell into three groups: (i) atypical benign partial epilepsy or idiopathic focal epilepsy (n = 8); (ii) generalised epilepsies/infantile epileptic encephalopathy (n = 4); (iii) unclassified (n = 8). Seizure prognosis ranged from spontaneous remission to drug resistant. Neurodevelopmental deficits were invariable. Dysmorphic features were variable. Variants were distributed across the gene and mostly de novo with no precise genotype–phenotype correlation. ZMYND11 is one of a small group of chromatin reader genes associated in the pathogenesis of epilepsy, and specifically ABPE. More detailed epilepsy descriptions of larger cohorts and functional studies might reveal genotype–phenotype correlation. The epileptogenic mechanism may be linked to interaction with histone H3.3.
CRIS-Team Scopus Importer:2021-07-30
Keywords: antiepileptic drug; autism; bromodomain; comorbidity; EEG; epigenetic; histone H3.3; seizure

Zooming in on Cryopreservation of hiPSCs and Neural Derivatives: A Dual-Center Study Using Adherent Vitrification - Kaindl, Johanna; Meiser, Ina; Majer, Julia; Sommer, Annika; Krach, Florian; Katsen-Globa, Alisa; Winkler, Jürgen; Zimmermann, Heiko; Neubauer, Julia C.; Winner, Beate (Stem Cells Translational Medicine, 2019)
Human induced pluripotent stem cells (hiPSCs) are an important tool for research and regenerative medicine, but their efficient cryopreservation remains a major challenge. The current gold standard is slow-rate freezing of dissociated colonies in suspension, but low recovery rates limit immediate post-thawing applicability. We tested whether ultrafast cooling by adherent vitrification improves post-thawing survival in a selection of hiPSCs and small molecule neural precursor cells (smNPCs) from Parkinson's disease and controls. In a dual-center study, we compared the results by immunocytochemistry (ICC), fluorescence-activated cell sorting analysis, and RNA-sequencing (RNA-seq). Adherent vitrification was achieved in the so-called TWIST substrate, a device combining cultivation, vitrification, storage, and post-thawing cultivation. Adherent vitrification resulted in preserved confluency and significantly higher cell numbers, and viability at day 1 after thawing, while results were not significantly different at day 4 after thawing. RNA-seq and ICC of hiPSCs revealed no change in gene expression and pluripotency markers, indicating that physical damage of slow-rate freezing disrupts cellular membranes. Scanning electron microscopy showed preserved colony integrity by adherent vitrification. Experiments using smNPCs demonstrated that adherent vitrification is also applicable to neural derivatives of hiPSCs. Our data suggest that, compared to the state-of-the-art slow-rate freezing in suspension, adherent vitrification is an improved cryopreservation technique for hiPSCs and derivatives. Stem Cells Translational Medicine 2019;8:247&259.
EVALuna2:36383

α-Synuclein impairs oligodendrocyte progenitor maturation in multiple system atrophy. - Winner, Beate; May, Verena Elisabeth Luise; Ettle, Benjamin; Pöhler, Anne-Maria; Nuber, Silke; Ubhi, Kiren; Rockenstein, Edward; Wegner, Michael; Masliah, Eliezer; Winkler, Jürgen (Neurobiology of Aging, 2014)
Multiple system atrophy (MSA), an atypical parkinsonian disorder, is characterized by α-synuclein (α-syn(+)) cytoplasmatic inclusions in mature oligodendrocytes. Oligodendrocyte progenitor cells (OPCs) represent a distinct cell population with the potential to replace dysfunctional oligodendrocytes. However, the role of OPCs in MSA and their potential to replace mature oligodendrocytes is still unclear. A postmortem analysis in MSA patients revealed α-syn within OPCs and an increased number of striatal OPCs. In an MSA mouse model, an age-dependent increase of dividing OPCs within the striatum and the cortex was detected. Despite of myelin loss, there was no reduction of mature oligodendrocytes in the corpus callosum or the striatum. Dissecting the underlying molecular mechanisms an oligodendroglial cell line expressing human α-syn revealed that α-syn delays OPC maturation by severely downregulating myelin-gene regulatory factor and myelin basic protein. Brain-derived neurotrophic factor was reduced in MSA models and its in vitro supplementation partially restored the phenotype. Taken together, efficacious induction of OPC maturation may open the window to restore glial and neuronal function in MSA.

α-Synuclein induces alterations in adult neurogenesis in Parkinson disease models via p53-mediated repression of Notch1. - Desplats, Paula; Spencer, Brian; Crews, Leslie; Pathel, Pruthul; Morvinski-Friedmann, Dinorah; Kosberg, Kori; Roberts, Scott; Patrick, Christina; Winner, Beate; Winkler, Jürgen; Masliah, Eliezer (Journal of Biological Chemistry, 2012)
Parkinson disease is characterized by the loss of dopaminergic neurons mainly in the substantia nigra. Accumulation of α-synuclein and cell loss has been also reported in many other brain regions including the hippocampus, where it might impair adult neurogenesis, contributing to nonmotor symptoms. However, the molecular mechanisms of these alterations are still unknown. In this report we show that α-synuclein-accumulating adult rat hippocampus neural progenitors present aberrant neuronal differentiation, with reduction of Notch1 expression and downstream signaling targets. We characterized a Notch1 proximal promoter that contains p53 canonical response elements. In vivo binding of p53 represses the transcription of Notch1 in neurons. Moreover, we demonstrated that α-synuclein directly binds to the DNA at Notch1 promoter vicinity and also interacts with p53 protein, facilitating or increasing Notch1 signaling repression, which interferes with maturation and survival of neural progenitors cells. This study provides a molecular basis for α-synuclein-mediated disruption of adult neurogenesis in Parkinson disease.

α-Synuclein oligomers impair neuronal microtubule-kinesin interplay. - Winner, Beate; Prots, Iryna; Brey, Stefanie; et al. (Journal of Biological Chemistry, 2013)
Early α-synuclein (α-Syn)-induced alterations are neurite pathologies resulting in Lewy neurites. α-Syn oligomers are a toxic species in synucleinopathies and are suspected to cause neuritic pathology. To investigate how α-Syn oligomers may be linked to aberrant neurite pathology, we modeled different stages of α-Syn aggregation in vitro and investigated the interplay of α-Syn aggregates with proteins involved in axonal transport. The interaction of wild type α-Syn (WTS) and α-Syn variants (E57K, A30P, and aSyn(30-110)) with kinesin, tubulin, and the microtubule (MT)-associated proteins, MAP2 and Tau, is stronger for multimers than for monomers. WTS seeds but not α-Syn oligomers significantly and dose-dependently reduced Tau-promoted MT assembly in vitro. In contrast, MT gliding velocity across kinesin-coated surfaces was significantly decreased in the presence of α-Syn oligomers but not WTS seeds or fibrils (aSyn(30-110) multimers). In a human dopaminergic neuronal cell line, mild overexpression of the oligomerizing E57K α-Syn variant significantly impaired neurite network morphology without causing profound cell death. In accordance with these findings, MT stability, neuritic kinesin, and neuritic kinesin-dependent cargoes were significantly reduced by the presence of α-Syn oligomers. In summary, different α-Syn species act divergently on the axonal transport machinery. These findings provide new insights into α-Syn oligomer-driven neuritic pathology as one of the earliest events in synucleinopathies.

α-Synuclein oligomers induce early axonal dysfunction in human iPSC-based models of synucleinopathies - Prots, Iryna; Grosch, Janina; Brazdis, Razvan-Marius; Simmnacher, Katrin; Veber, Vanesa; Havlicek, Steven; Hannappel, Christian; Krach, Florian; Krumbiegel, Mandy; Schuetz, Oliver; Reis, André; Wrasidlo, Wolfgang; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
α-Synuclein (α-Syn) aggregation, proceeding from oligomers to fibrils, is one central hallmark of neurodegeneration in synucleinopathies. α-Syn oligomers are toxic by triggering neurodegenerative processes in in vitro and in vivo models. However, the precise contribution of α-Syn oligomers to neurite pathology in human neurons and the underlying mechanisms remain unclear. Here, we demonstrate the formation of oligomeric α-Syn intermediates and reduced axonal mitochondrial transport in human neurons derived from induced pluripotent stem cells (iPSC) from a Parkinson's disease patient carrying an α-Syn gene duplication. We further show that increased levels of α-Syn oligomers disrupt axonal integrity in human neurons. We apply an α-Syn oligomerization model by expressing α-Syn oligomer-forming mutants (E46K and E57K) and wild-type α-Syn in human iPSC-derived neurons. Pronounced α-Syn oligomerization led to impaired anterograde axonal transport of mitochondria, which can be restored by the inhibition of α-Syn oligomer formation. Furthermore, α-Syn oligomers were associated with a subcellular relocation of transport-regulating proteins Miro1, KLC1, and Tau as well as reduced ATP levels, underlying axonal transport deficits. Consequently, reduced axonal density and structural synaptic degeneration were observed in human neurons in the presence of high levels of α-Syn oligomers. Together, increased dosage of α-Syn resulting in α-Syn oligomerization causes axonal transport disruption and energy deficits, leading to synapse loss in human neurons. This study identifies α-Syn oligomers as the critical species triggering early axonal dysfunction in synucleinopathies.
EVALuna2:34623
Keywords: alpha-synuclein; oligomers; axonal transport; synucleinopathies; neurodegeneration

β1 and β3 subunits amplify mechanosensitivity of the cardiac voltage-gated sodium channel Nav1.5 - Maroni, Michele; Körner, Jannis; Schüttler, Jürgen; Winner, Beate; Lampert, Angelika; Eberhardt, Esther (Pflügers Archiv: European Journal of Physiology, 2019)
In cardiomyocytes, electrical activity is coupled to cellular contraction, thus exposing all proteins expressed in the sarcolemma to mechanical stress. The voltage-gated sodium channel Nav1.5 is the main contributor to the rising phase of the action potential in the heart. There is growing evidence that gating and kinetics of Nav1.5 are modulated by mechanical forces and pathogenic variants that affect mechanosensitivity have been linked to arrhythmias. Recently, the sodium channel β1 subunit has been described to stabilise gating against mechanical stress of Nav1.7 expressed in neurons. Here, we tested the effect of β1 and β3 subunits on mechanosensitivity of the cardiac Nav1.5. β1 amplifies stress-induced shifts of V1/2 of steady-state fast inactivation to hyperpolarised potentials (ΔV1/2: 6.2 mV without and 10.7 mV with β1 co-expression). β3, on the other hand, almost doubles stress-induced speeding of time to sodium current transient peak (Δtime to peak at − 30 mV: 0.19 ms without and 0.37 ms with β3 co-expression). Our findings may indicate that in cardiomyocytes, the interdependence of electrical activity and contraction is used as a means of fine tuning cardiac sodium channel function, allowing quicker but more strongly inactivating sodium currents under conditions of increased mechanical stress. This regulation may help to shorten action potential duration during tachycardia, to prevent re-entry phenomena and thus arrhythmias.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Cardiac ion channel; Mechanosensitivity; Patch-clamp; Sodium channel

β2-microglobulin triggers NLRP3 inflammasome activation in tumor-associated macrophages to promote multiple myeloma progression - Hofbauer, Daniel; Mougiakakos, Dimitrios; Broggini, Luca; Zaiss, Mario; Büttner-Herold, Maike; Bach, Christian; Spriewald, Bernd; Neumann, Frank; Bisht, Savita; Nolting, Jens; Zeiser, Robert; Hamarsheh, Shaima'a; et al. (Immunity, 2021)
As substantial constituents of the multiple myeloma (MM) microenvironment, pro-inflammatory macrophages have emerged as key promoters of disease progression, bone destruction, and immune impairment. We identify beta-2-microglobulin (β2m) as a driver in initiating inflammation in myeloma-associated macrophages (MAMs). Lysosomal accumulation of phagocytosed β2m promotes β2m amyloid aggregation in MAMs, resulting in lysosomal rupture and ultimately production of active interleukin-1β (IL-1β) and IL-18. This process depends on activation of the NLRP3 inflammasome after β2m accumulation, as macrophages from NLRP3-deficient mice lack efficient β2m-induced IL-1β production. Moreover, depletion or silencing of β2m in MM cells abrogates inflammasome activation in a murine MM model. Finally, we demonstrate that disruption of NLRP3 or IL-18 diminishes tumor growth and osteolytic bone destruction normally promoted by β2m-induced inflammasome signaling. Our results provide mechanistic evidence for β2m's role as an NLRP3 inflammasome activator during MM pathogenesis. Moreover, inhibition of NLRP3 represents a potential therapeutic approach in MM.
CRIS-Team Scopus Importer:2021-08-13
Keywords: inflammation; macrophages; multiple myeloma; NLRP3; phagocytosis; tumor-associated macrophages

β-catenin signaling modulates the tempo of dendritic growth of adult-born hippocampal neurons - Heppt, Jana; Wittmann, Marie-Theres; Schäffner, Iris; Billmann, Charlotte; Zhang, Jingzhong; Vogt-Weisenhorn, Daniela; Prakash, Nilima; Wurst, Wolfgang; Taketo, Makoto Mark; Lie, Dieter Chichung (EMBO Journal, 2020)
In adult hippocampal neurogenesis, stem/progenitor cells generate dentate granule neurons that contribute to hippocampal plasticity. The establishment of a morphologically defined dendritic arbor is central to the functional integration of adult-born neurons. We investigated the role of canonical Wnt/β-catenin signaling in dendritogenesis of adult-born neurons. We show that canonical Wnt signaling follows a biphasic pattern, with high activity in stem/progenitor cells, attenuation in immature neurons, and reactivation during maturation, and demonstrate that this activity pattern is required for proper dendrite development. Increasing β-catenin signaling in maturing neurons of young adult mice transiently accelerated dendritic growth, but eventually produced dendritic defects and excessive spine numbers. In middle-aged mice, in which protracted dendrite and spine development were paralleled by lower canonical Wnt signaling activity, enhancement of β-catenin signaling restored dendritic growth and spine formation to levels observed in young adult animals. Our data indicate that precise timing and strength of β-catenin signaling are essential for the correct functional integration of adult-born neurons and suggest Wnt/β-catenin signaling as a pathway to ameliorate deficits in adult neurogenesis during aging.
CRIS-Team Scopus Importer:2020-09-25
Keywords: adult neurogenesis; aging; dendrite; hippocampus; Wnt signaling

A de novo microdeletion in NRXN1 in a Dutch patient with mild intellectual disability, microcephaly and gonadal dysgenesis - Agha, Zehra; Iqbal, Zafar; Kleefstra, Tjitske; Zweier, Christiane; Pfundt, Rolph; Qamar, Raheel; Van Bokhoven, Hans; Willemsen, Marjolein H. (Genetics Research, 2015)
This report is regarding a Dutch female with microcephaly, mild intellectual disability (ID), gonadal dysgenesis and dysmorphic facial features with synophrys. Upon genotyping, an 455 kb de novo deletion encompassing the first exon of NRXN1 was found. Bidirectional sequencing of the coding exons of the NRXN1 alpha isoform was subsequently performed to investigate the possibility of a pathogenic mutation on the other allele, but we could not find any other mutation. Previously, many heterozygous mutations as well as microdeletions in NRXN1 were shown to be associated with ID, autism, schizophrenia, and other psychiatric and psychotic disorders. Our results are in agreement with other reports that show that NRXN1 deletions can lead to ID, microcephaly and mild dysmorphic features. However, this is the first report of gonadal dysgenesis being associated with such deletions. It is not clear whether there is a causal relationship between the NRXN1 deletion and gonadal dysgenesis, but it is of interest that the FSHR gene, which encodes the follicle-stimulating hormone receptor causative correlation that is mutated in ovarian dysgenesis, is located proximal to the NRXN1 gene. Given that most of the females carrying NRXN1 deletions have been diagnosed at a prepubertal age, gynecologic screening of female carriers of a NRXN1 deletion is warranted.
EVALuna2:9289

Advanced in early- and adult-onset glaucoma genetics - Pasutto, Francesca (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Choline transporter-like 1 deficiency causes a new type of childhood-onset neurodegeneration - Fagerberg, Christina R.; Taylor, Adrian; Distelmaier, Felix; Schrøder, Henrik D.; Kibæk, Maria; Wieczorek, Dagmar; Tarnopolsky, Mark; Brady, Lauren; Larsen, Martin J.; Jamra, Rami A.; Seibt, Annette; Hejbøl, Eva Kildall; et al. (Brain, 2020)
Cerebral choline metabolism is crucial for normal brain function, and its homoeostasis depends on carrier-mediated transport. Here, we report on four individuals from three families with neurodegenerative disease and homozygous frameshift mutations (Asp517Metfs*19, Ser126Metfs*8, and Lys90Metfs*18) in the SLC44A1 gene encoding choline transporter-like protein 1. Clinical features included progressive ataxia, tremor, cognitive decline, dysphagia, optic atrophy, dysarthria, as well as urinary and bowel incontinence. Brain MRI demonstrated cerebellar atrophy and leukoencephalopathy. Moreover, low signal intensity in globus pallidus with hyperintensive streaking and low signal intensity in substantia nigra were seen in two individuals. The Asp517Metfs*19 and Ser126Metfs*8 fibroblasts were structurally and functionally indistinguishable. The most prominent ultrastructural changes of the mutant fibroblasts were reduced presence of free ribosomes, the appearance of elongated endoplasmic reticulum and strikingly increased number of mitochondria and small vesicles. When chronically treated with choline, those characteristics disappeared and mutant ultrastructure resembled healthy control cells. Functional analysis revealed diminished choline transport yet the membrane phosphatidylcholine content remained unchanged. As part of the mechanism to preserve choline and phosphatidylcholine, choline transporter deficiency was implicated in impaired membrane homeostasis of other phospholipids. Choline treatments could restore the membrane lipids, repair cellular organelles and protect mutant cells from acute iron overload. In conclusion, we describe a novel childhood-onset neurometabolic disease caused by choline transporter deficiency with autosomal recessive inheritance.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Choline transporter; Neurodegeneration; Phospholipids; SLC44A1

Delineating the clinical spectrum due to heterozygous TRAF7 missense mutations: A series of 38 cases - Amiel, J.; Mishra, K.; Castilla, L.; Selmer, K. K.; Barak, T.; Yang, S.; Blanco-Sanchez, B.; Reijnders, M.; Houge, G.; Cox, H.; Kingston, H.; Clayton-Smith, J.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Functional analyses of Pericentrin and Syne-2 interaction in ciliogenesis - Falk, Nathalie; Keßler, Kristin; Schramm, Sinja-Fee; Boldt, Karsten; Becirovic, Elvir; Michalakis, Stylianos; Regus-Leidig, Hanna; Noegel, Angelika A.; Ueffing, Marius; Thiel, Christian; Roepman, Ronald; Brandstätter, Johann Helmut; et al. (Journal of Cell Science, 2018)
Pericentrin (Pcnt) is a multifunctional scaffold protein and mutations in the human PCNT gene are associated with several diseases, including ciliopathies. Pcnt plays a crucial role in ciliary development in olfactory receptor neurons, but its function in the photoreceptor-connecting cilium is unknown. We downregulated Pcnt in the retina ex vivo and in vivo via a virus-based RNA interference approach to study Pcnt function in photoreceptors. ShRNA-mediated knockdown of Pcnt impaired the development of the connecting cilium and the outer segment of photoreceptors, and caused a nuclear migration defect. In protein interaction screens, we found that the outer nuclear membrane protein Syne-2 (also known as Nesprin-2) is an interaction partner of Pcnt in photoreceptors. Syne-2 is important for positioning murine photoreceptor cell nuclei and for centrosomal migration during early ciliogenesis. CRISPR/Cas9-mediated knockout of Syne-2 in cell culture led to an overexpression and mislocalization of Pcnt and to ciliogenesis defects. Our findings suggest that the Pcnt-Syne-2 complex is important for ciliogenesis and outer segment formation during retinal development and plays a role in nuclear migration.
EVALuna2:34620

Loss-of-Function Myeloperoxidase Mutations Are Associated with Increased Neutrophil Counts and Pustular Skin Disease - Vergnano, Marta; Mockenhaupt, Maja; Benzian-Olsson, Natashia; Paulmann, Maren; Grys, Katarzyna; Mahil, Satveer K.; Chaloner, Charlotte; Barbosa, Ines A.; August, Suzannah; Burden, A. David; Choon, Siew Eng; Cooper, Hywel; et al. (American Journal of Human Genetics, 2020)
The identification of disease alleles underlying human autoinflammatory diseases can provide important insights into the mechanisms that maintain neutrophil homeostasis. Here, we focused our attention on generalized pustular psoriasis (GPP), a potentially life-threatening disorder presenting with cutaneous and systemic neutrophilia. Following the whole-exome sequencing of 19 unrelated affected individuals, we identified a subject harboring a homozygous splice-site mutation (c.2031−2A>C) in MPO. This encodes myeloperoxidase, an essential component of neutrophil azurophil granules. MPO screening in conditions phenotypically related to GPP uncovered further disease alleles in one subject with acral pustular psoriasis (c.2031−2A>C;c.2031−2A>C) and in two individuals with acute generalized exanthematous pustulosis (c.1705C>T;c.2031−2A>C and c.1552_1565del;c.1552_1565del). A subsequent analysis of UK Biobank data demonstrated that the c.2031−2A>C and c.1705C>T (p.Arg569Trp) disease alleles were also associated with increased neutrophil abundance in the general population (p = 5.1 × 10−6 and p = 3.6 × 10−5, respectively). The same applied to three further deleterious variants that had been genotyped in the cohort, with two alleles (c.995C>T [p.Ala332Val] and c.752T>C [p.Met251Thr]) yielding p values < 10−10. Finally, treatment of healthy neutrophils with an MPO inhibitor (4-Aminobenzoic acid hydrazide) increased cell viability and delayed apoptosis, highlighting a mechanism whereby MPO mutations affect granulocyte numbers. These findings identify MPO as a genetic determinant of pustular skin disease and neutrophil abundance. Given the recent interest in the development of MPO antagonists for the treatment of neurodegenerative disease, our results also suggest that the pro-inflammatory effects of these agents should be closely monitored.
CRIS-Team Scopus Importer:2020-09-11
Keywords: acute generalized exanthematous pustulosis; AGEP; generalized pustular psoriasis; GPP; MPO; myeloperoxidase; myeloperoxidase deficiency; neutrophils

Loss of Function of GALNT2 Lowers High-Density Lipoproteins in Humans, Nonhuman Primates, and Rodents - Khetarpal, Sumeet A.; Schjoldager, Katrine T.; Christoffersen, Christina; Raghavan, Avanthi; Edmondson, Andrew C.; Reutter, Heiko M.; Ahmed, Bouhouche; Ouazzani, Reda; Peloso, Gina M.; Vitali, Cecilia; Zhao, Wei; Somasundara, Amritha Varshini Hanasoge; et al. (Cell Metabolism, 2016)
Human genetics studies have implicated GALNT2, encoding GalNAc-T2, as a regulator of high-density lipoprotein cholesterol (HDL-C) metabolism, but the mechanisms relating GALNT2 to HDL-C remain unclear. We investigated the impact of homozygous GALNT2 deficiency on HDL-C in humans and mammalian models. We identified two humans homozygous for loss-of-function mutations in GALNT2 who demonstrated low HDL-C. We also found that GALNT2 loss of function in mice, rats, and nonhuman primates decreased HDL-C. O-glycoproteomics studies of a human GALNT2-deficient subject validated ANGPTL3 and ApoC-III as GalNAc-T2 targets. Additional glycoproteomics in rodents identified targets influencing HDL-C, including phospholipid transfer protein (PLTP). GALNT2 deficiency reduced plasma PLTP activity in humans and rodents, and in mice this was rescued by reconstitution of hepatic Galnt2. We also found that GALNT2 GWAS SNPs associated with reduced HDL-C also correlate with lower hepatic GALNT2 expression. These results posit GALNT2 as a direct modulator of HDL metabolism across mammals.
EVALuna2:9336

PEDIA: prioritization of exome data by image analysis - Hsieh, Tzung Chien; Mensah, Martin A.; Pantel, Jean T.; Aguilar, Dione; Bar, Omri; Bayat, Allan; Becerra-Solano, Luis; Bentzen, Heidi B.; Biskup, Saskia; Borisov, Oleg; Braaten, Oivind; Ciaccio, Claudia; et al. (Genetics in Medicine, 2019)
Purpose: Phenotype information is crucial for the interpretation of genomic variants. So far it has only been accessible for bioinformatics workflows after encoding into clinical terms by expert dysmorphologists. Methods: Here, we introduce an approach driven by artificial intelligence that uses portrait photographs for the interpretation of clinical exome data. We measured the value added by computer-assisted image analysis to the diagnostic yield on a cohort consisting of 679 individuals with 105 different monogenic disorders. For each case in the cohort we compiled frontal photos, clinical features, and the disease-causing variants, and simulated multiple exomes of different ethnic backgrounds. Results: The additional use of similarity scores from computer-assisted analysis of frontal photos improved the top 1 accuracy rate by more than 20–89% and the top 10 accuracy rate by more than 5–99% for the disease-causing gene. Conclusion: Image analysis by deep-learning algorithms can be used to quantify the phenotypic similarity (PP4 criterion of the American College of Medical Genetics and Genomics guidelines) and to advance the performance of bioinformatics pipelines for exome analysis.
CRIS-Team Scopus Importer:2019-06-21
Keywords: computer vision; deep learning; dysmorphology; exome diagnostics; variant prioritization

Proteome-wide analysis of chaperone-mediated autophagy targeting motifs - Kirchner, Philipp; Bourdenx, Mathieu; Madrigal-Matute, Julio; Tiano, Simoni; Diaz, Antonio; Bartholdy, Boris A.; Will, Britta; Cuervo, Ana Maria (Plos Biology, 2019)
Chaperone-mediated autophagy (CMA) contributes to the lysosomal degradation of a selective subset of proteins. Selectivity lies in the chaperone heat shock cognate 71 kDa protein (HSC70) recognizing a pentapeptide motif (KFERQ-like motif) in the protein sequence essential for subsequent targeting and degradation of CMA substrates in lysosomes. Interest in CMA is growing due to its recently identified regulatory roles in metabolism, differentiation, cell cycle, and its malfunctioning in aging and conditions such as cancer, neurodegeneration, or diabetes. Identification of the subset of the proteome amenable to CMA degradation could further expand our understanding of the pathophysiological relevance of this form of autophagy. To that effect, we have performed an in silico screen for KFERQ-like motifs across proteomes of several species. We have found that KFERQ-like motifs are more frequently located in solvent-exposed regions of proteins, and that the position of acidic and hydrophobic residues in the motif plays the most important role in motif construction. Cross-species comparison of proteomes revealed higher motif conservation in CMA-proficient species. The tools developed in this work have also allowed us to analyze the enrichment of motif-containing proteins in biological processes on an unprecedented scale and discover a previously unknown association between the type and combination of KFERQ-like motifs in proteins and their participation in specific biological processes. To facilitate further analysis by the scientific community, we have developed a free web-based resource (KFERQ finder) for direct identification of KFERQ-like motifs in any protein sequence. This resource will contribute to accelerating understanding of the physiological relevance of CMA.
CRIS-Team Scopus Importer:2021-04-20

QRICH1 variants in Ververi-Brady syndrome-delineation of the genotypic and phenotypic spectrum - Foehrenbach, Melanie; Jamra, Rami Abou; Borkhardt, Arndt; Brozou, Triantafyllia; Muschke, Petra; Popp, Bernt; Rey, Linda K.; Schaper, Joerg; Surowy, Harald; Zenker, Martin; Zweier, Christiane; Wieczorek, Dagmar; et al. (Clinical Genetics, 2020)
Ververi-Brady syndrome (VBS, # 617982) is a rare developmental disorder, and loss-of-function variants in QRICH1 were implicated in its etiology. Furthermore, a recognizable phenotype was proposed comprising delayed speech, learning difficulties and dysmorphic signs. Here, we present four unrelated individuals with one known nonsense variant (c.1954C > T; p.[Arg652*]) and three novel de novo QRICH1 variants, respectively. These included two frameshift mutations (c.832_833del; p.(Ser278Leufs*25), c.1812_1813delTG; p.(Glu605Glyfs*25)) and interestingly one missense mutation (c.2207G > A; p.[Ser736Asn]), expanding the mutational spectrum. Enlargement of the cohort by these four individuals contributes to the delineation of the VBS phenotype and suggests expressive speech delay, moderate motor delay, learning difficulties/mild ID, mild microcephaly, short stature and notable social behavior deficits as clinical hallmarks. In addition, one patient presented with nephroblastoma. The possible involvement of QRICH1 in pediatric cancer assumes careful surveillance a key priority for outcome of these patients. Further research and enlargement of cohorts are warranted to learn about the genetic architecture and the phenotypic spectrum in more detail.
CRIS-Team WoS Importer:2020-11-27

The role of genetic variation of human metabolism for BMI, mental traits and mental disorders - Hebebrand, Johannes; Peters, Triinu; Schijven, Dick; Hebebrand, Moritz; Grasemann, Corinna; Winkler, Thomas W.; Heid, Iris M.; Antel, Jochen; Foecker, Manuel; Tegeler, Lisa; Brauner, Lena; Adan, Roger A. H.; et al. (Molecular Metabolism, 2018)
OBJECTIVE: The aim was to assess whether loci associated with metabolic traits also have a significant role in BMI and mental traits/disorders METHODS: We first assessed the number of single nucleotide polymorphisms (SNPs) with genome-wide significance for human metabolism (NHGRI-EBI Catalog). These 516 SNPs (216 independent loci) were looked-up in genome-wide association studies for association with body mass index (BMI) and the mental traits/disorders educational attainment, neuroticism, schizophrenia, well-being, anxiety, depressive symptoms, major depressive disorder, autism-spectrum disorder, attention-deficit/hyperactivity disorder, Alzheimer's disease, bipolar disorder, aggressive behavior, and internalizing problems. A strict significance threshold of p < 6.92 × 10-6 was based on the correction for 516 SNPs and all 14 phenotypes, a second less conservative threshold (p < 9.69 × 10-5) on the correction for the 516 SNPs only. RESULTS: 19 SNPs located in nine independent loci revealed p-values < 6.92 × 10-6; the less strict criterion was met by 41 SNPs in 24 independent loci. BMI and schizophrenia showed the most pronounced genetic overlap with human metabolism with three loci each meeting the strict significance threshold. Overall, genetic variation associated with estimated glomerular filtration rate showed up frequently; single metabolite SNPs were associated with more than one phenotype. Replications in independent samples were obtained for BMI and educational attainment. CONCLUSIONS: Approximately 5-10% of the regions involved in the regulation of blood/urine metabolite levels seem to also play a role in BMI and mental traits/disorders and related phenotypes. If validated in metabolomic studies of the respective phenotypes, the associated blood/urine metabolites may enable novel preventive and therapeutic strategies.
EVALuna2:34627